Alzheimer's disease-related cortical proteins modify the association of brain insulin signaling with cognitive decline. - Tong, Han; Petyuk, Vladislav A; Sendtner, Michael; Sood, Ajay; Bennett, David A; Capuano, Ana W; Arvanitakis, Zoe (J Alzheimers Dis, 2025)
BackgroundBrain insulin signaling has been associated with both Alzheimer's disease (AD) pathology and cognitive decline, but the mechanisms remain unclear.ObjectiveTo examine whether AD-related cortically-expressed proteins modify the association of brain insulin signaling and cognitive decline.MethodsParticipants included 116 autopsied members of the Religious Orders Study (58 with diabetes matched to 58 without, by age at death, sex, and education) who had both postmortem brain (prefrontal cortex) insulin signaling (by ELISA and immunohistochemistry, including RAC-alpha serine/threonine-protein kinase or AKT1) and AD-related cortical protein measurements. Levels of five AD-related proteins including insulin-like growth factor-binding protein-5 (IGFBP-5) and inositol-tetrakisphosphate 1-kinase (ITPK1) were measured using quantitative proteomics. We conducted adjusted linear mixed model analyses to examine associations of insulin signaling measures and AD-related proteins with longitudinally assessed cognitive function.ResultsHigher levels of IGFBP-5 and lower levels of ITPK1 were each associated with higher levels of AKT1 phosphorylation (pTAKT1 /total AKT1). Additionally, higher levels of AKT1 phosphorylation were associated with faster decline in global cognition and most cognitive domains. IGFBP-5 partially mediated the association of AKT1 phosphorylation with the decline rate of global cognition and cognitive domains including perceptual speed and visuospatial abilities. Further, ITPK1 had an interaction with AKT1 phosphorylation on decline of global cognition and domains including episodic memory, perceptual speed, and visuospatial abilities.ConclusionsAD-related proteins IGFBP-5 and ITPK1 are each associated with insulin signaling AKT1 phosphorylation in the postmortem human brain. Moreover, IGFBP-5 mediates, while ITPK1 moderates, the association between AKT1 phosphorylation and late-life cognitive decline.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Brain; Cognitive Dysfunction; Female; Humans; Insulin; Insulin-Like Growth Factor Binding Protein 5; Male; Phosphorylation; Proto-Oncogene Proteins c-akt; Signal Transduction

Acute Hyperglycemia Induced by Hyperglycemic Clamp Affects Plasma Amyloid-β in Type 2 Diabetes. - Rolandsson, Olov; Tornevi, Andreas; Steneberg, Pär; Edlund, Helena; Olsson, Tommy; Andreasson, Ulf; Zetterberg, Henrik; Blennow, Kaj (J Alzheimers Dis, 2024)
BACKGROUND: Individuals with type 2 diabetes (T2D) have an increased risk of cognitive symptoms and Alzheimer's disease (AD). Mis-metabolism with aggregation of amyloid-β peptides (Aβ) play a key role in AD pathophysiology. Therefore, human studies on Aβ metabolism and T2D are warranted. OBJECTIVE: The objective of this study was to examine whether acute hyperglycemia affects plasma Aβ1-40 and Aβ1-42 concentrations in individuals with T2D and matched controls. METHODS: Ten participants with T2D and 11 controls (median age, 69 years; range, 66-72 years) underwent hyperglycemic clamp and placebo clamp (saline infusion) in a randomized order, each lasting 4 hours. Aβ1-40, Aβ1-42, and insulin-degrading enzyme (IDE) plasma concentrations were measured in blood samples taken at 0 and 4 hours of each clamp. Linear mixed-effect regression models were used to evaluate the 4-hour changes in Aβ1-40 and Aβ1-42 concentrations, adjusting for body mass index, estimated glomerular filtration rate, and 4-hour change in insulin concentration. RESULTS: At baseline, Aβ1-40 and Aβ1-42 concentrations did not differ between the two groups. During the hyperglycemic clamp, Aβ decreased in the control group, compared to the placebo clamp (Aβ1-40: p = 0.034, Aβ1-42: p = 0.020), IDE increased (p = 0.016) during the hyperglycemic clamp, whereas no significant changes in either Aβ or IDE was noted in the T2D group. CONCLUSIONS: Clamp-induced hyperglycemia was associated with increased IDE levels and enhanced Aβ40 and Aβ42 clearance in controls, but not in individuals with T2D. We hypothesize that insulin-degrading enzyme was inhibited during hyperglycemic conditions in people with T2D.
Keywords: Aged; Amyloid beta-Peptides; Blood Glucose; Diabetes Mellitus, Type 2; Female; Glucose Clamp Technique; Humans; Hyperglycemia; Insulysin; Male; Peptide Fragments

Amyloid-β Pathology Is the Common Nominator Proteinopathy of the Primate Brain Aging. - Ferrer, Isidro (J Alzheimers Dis, 2024)
Senile plaques, mainly diffuse, and cerebral amyloid-β (Aβ) angiopathy are prevalent in the aging brain of non-human primates, from lemurs to non-human Hominidae. Aβ but not hyper-phosphorylated tau (HPtau) pathology is the common nominator proteinopathy of non-human primate brain aging. The abundance of Aβ in the aging primate brain is well tolerated, and the impact on cognitive functions is usually limited to particular tasks. In contrast, human brain aging is characterized by the early appearance of HPtau pathology, mainly forming neurofibrillary tangles, dystrophic neurites of neuritic plaques, and neuropil threads, preceding Aβ deposits by several decades and by its severity progressing from selected nuclei of the brain stem, entorhinal cortex, and hippocampus to the limbic system, neocortex, and other brain regions. Neurofibrillary tangles correlate with cognitive impairment and dementia in advanced cases. Aβ pathology is linked in humans to altered membrane protein and lipid composition, particularly involving lipid rafts. Although similar membrane alterations are unknown in non-human primates, membrane senescence is postulated to cause the activated β-amyloidogenic pathway, and Aβ pathology is the prevailing signature of non-human and human primate brain aging.
Keywords: Aging; Amyloid beta-Peptides; Animals; Brain; Humans; Neurofibrillary Tangles; Plaque, Amyloid; Primates; tau Proteins

Aniracetam: An Evidence-Based Model for Preventing the Accumulation of Amyloid-β Plaques in Alzheimer's Disease. - Love, Robert W B (J Alzheimers Dis, 2024)
Alzheimer's disease is the leading cause of dementia in the world. It affects 6 million people in the United States and 50 million people worldwide. Alzheimer's disease is characterized by the accumulation of amyloid-β plaques (Aβ), an increase in tau protein neurofibrillary tangles, and a loss of synapses. Since the 1990s, removing and reducing Aβ has been the focus of Alzheimer's treatment and prevention research. The accumulation of Aβ can lead to oxidative stress, inflammation, neurotoxicity, and eventually apoptosis. These insults impair signaling systems in the brain, potentially leading to memory loss and cognitive decline. Aniracetam is a safe, effective, cognitive-enhancing drug that improves memory in both human and animal studies. Aniracetam may prevent the production and accumulation of Aβ by increasing α-secretase activity through two distinct pathways: 1) increasing brain derived neurotrophic factor expression and 2) positively modulating metabotropic glutamate receptors. This is the first paper to propose an evidence-based model for aniracetam reducing the accumulation and production of Aβ.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; Humans; Neurofibrillary Tangles; Plaque, Amyloid; Pyrrolidinones; tau Proteins

Association of Plastic Exposure with Cognitive Function Among Chinese Older Adults. - Zhu, Yongbin; Wu, Yueping; Shi, Liping; Yang, Yue; Wang, Yanrong; Pan, Degong; He, Shulan; Wang, Liqun; Li, Jiangping (J Alzheimers Dis, 2024)
BACKGROUND: The widespread exposure to plastic products and the increasing number of individuals with cognitive impairments have imposed a heavy burden on society. OBJECTIVE: This study aims to investigate the relationship between plastic product exposure in daily life and cognitive function in older Chinese individuals. METHODS: Data were obtained from the 2023 Ningxia Older Psychological Health Cohort, comprising 4045 participants aged 60 and above. Cognitive function was assessed using the Mini-Mental State Examination scale. A population-based plastic exposure questionnaire was used to calculate plastic exposure scores (PES). Binary logistic regression was employed to analyze the relationship between PES and cognitive function, while restricted cubic splines were used to examine the dose-response relationship between PES and cognitive function. Latent profile analysis (LPA) was employed to explore the potential patterns of plastic exposure, and logistic regression was used to investigate the relationship between different exposure patterns and cognitive function. A linear regression model was utilized to investigate the relationship between PES and different dimensions of cognitive function. RESULTS: Among the 4045 participants, 1915 individuals were assessed with mild cognitive impairment (MCI). After adjusting for all covariates, PES (OR = 1.04, 95% CI 1.02-1.06) was significantly associated with the risk of MCI and exhibited a dose-response relationship. LPA identified two potential categories of plastic exposure, with a higher risk of MCI observed in the group using plastic utensils. CONCLUSIONS: This study indicates a positive correlation between plastic exposure levels and MCI risk, particularly among individuals who frequently use plastic tableware.
Keywords: Aged; Aged, 80 and over; China; Cognition; Cognitive Dysfunction; Cohort Studies; East Asian People; Environmental Exposure; Female; Humans; Male; Mental Status and Dementia Tests; Middle Aged; Plastics; Surveys and Questionnaires

Association of Vitamin D Levels with Risk of Cognitive Impairment and Dementia: A Systematic Review and Meta-Analysis of Prospective Studies. - Zhang, Xiao-Xue; Wang, He-Ran; Hu, Ya-Zhuo; Sun, Hong-Mei; Feng, Yu-Xin; Jia, Jian-Jun (J Alzheimers Dis, 2024)
BACKGROUND: Emerging evidence suggests the potential relationship between vitamin D deficiency and risk of cognitive impairment or dementia. To what extent the excess risk of dementia conferred by vitamin D deficiency is less clear. OBJECTIVE: We summarized the current evidence from several aspects and further quantified these associations. METHODS: We collected relevant prospective cohort studies by searching PubMed, Embase and Cochrane up to July 2023. The pooled relative risks (RR) were evaluated by random-effects models. Dose-response analyses were conducted by the method of two-stage generalized least squares regression. RESULTS: Of 9,267 identified literatures, 23 were eligible for inclusion in the meta-analyses, among which 9 and 4 literatures were included in the dose-response analyses for the risk of dementia and Alzheimer's disease (AD). Vitamin D deficiency exhibited a 1.42 times risk for dementia (95% confidence interval (CI) = 1.21-1.65) and a 1.57-fold excess risk for AD (95% CI = 1.15-2.14). And vitamin D deficiency was associated with 34% elevated risk with cognitive impairment (95% CI = 1.19-1.52). Additionally, vitamin D was non-linearly related to the risk of dementia (pnonlinearity = 0.0000) and AD (pnonlinearity = 0.0042). The approximate 77.5-100 nmol/L 25-hydroxyvitamin D [25(OH)D] was optimal for reducing dementia risk. And the AD risk seemed to be decreased when the 25(OH)D level >40.1 nmol/L. CONCLUSIONS: Vitamin D deficiency was a risk factor for dementia, AD, and cognitive impairment. The nonlinear relationships may further provide the optimum dose of 25(OH)D for dementia prevention.
Keywords: Alzheimer Disease; Cognitive Dysfunction; Dementia; Humans; Prospective Studies; Risk Factors; Vitamin D; Vitamin D Deficiency

Comparative accuracy of Mini-Linguistic State Examination, Addenbrooke's Cognitive Examination, and Depistage Cognitif de Quebec for the diagnosis of primary progressive aphasia. - Fernández-Romero, Lucía; Morello-García, Florentina; Laforce, Robert; Delgado-Alonso, Cristina; Delgado-Álvarez, Alfonso; Gil-Moreno, María José; Lavoie, Monica; Matías-Guiu, Jorge; Cuetos, Fernando; Matías-Guiu, Jordi A (J Alzheimers Dis, 2024)
BACKGROUND: Clinical diagnosis in primary progressive aphasia (PPA) is challenging. Recently, emphasis has been placed on the importance of screening evaluation. Three different screening tests that use different strategies based on the assessment of language (Mini-Linguistic State Examination, MLSE) or different cognitive domains (Addenbrooke's Cognitive Examination, ACE-III and Dépistage Cognitif de Québec, DCQ) have been proposed and independently validated. These tests aim to detect PPA and classify into the three main variants (non-fluent (nfvPPA), semantic (svPPA) and logopenic (lvPPA)). OBJECTIVE: This study aims to evaluate and compare the diagnostic capacity of these three instruments in PPA. METHODS: A cross-sectional study including 43 patients with PPA (nfvPPA ( = 19), svPPA ( = 8), and lvPPA ( = 16)) and 21 cognitively unimpaired controls was conducted. Clinical diagnoses were established based on an extensive multidisciplinary assessment including neuropsychological assessment, fluorodeoxyglucose-positron emission tomography, MRI, and cerebrospinal fluid biomarkers. Both PPA patients and controls completed the three tests (MLSE, ACE-III, and DCQ). RESULTS: Internal consistency was excellent for the three tests. The area under the curve for the diagnosis of PPA was 0.950 for MLSE, 0.953 for ACE-III, and 0.933 for DCQ. Correlations between the three tests were high. The MLSE, ACE-III, and DCQ tests obtained adequate levels of discrimination between the variants of PPA, with accuracies between 76-79%. CONCLUSIONS: This study confirms the validity of ACE-III, MLSE, and DCQ for the diagnosis of PPA and its variants. This suggests that detailed assessment of linguistic characteristics (MLSE) and non-linguistic features (DCQ, ACE-III) are relevant for the diagnosis and classification of PPA.
Keywords: Aged; Aphasia, Primary Progressive; Cross-Sectional Studies; Female; Humans; Magnetic Resonance Imaging; Male; Middle Aged; Neuropsychological Tests; Positron-Emission Tomography; Reproducibility of Results

Current Status and Challenges in Dementia Care in the Philippines: A Scoping Review. - Anlacan, Veeda Michelle M; Lanuza, Pamela Danielle T; Sanchez, Anna Anjelica R; Jamora, Roland Dominic G (J Alzheimers Dis, 2024)
BACKGROUND: Dementia prevalence is increasing in low- and middle-income countries such as the Philippines. OBJECTIVE: This study aimed to give an overview of dementia care in the Philippines and to identify gaps in terms of local epidemiology, research, financial coverage, diagnostics, pharmacotherapy, manpower, and caregiver support. METHODS: This scoping review was conducted using the Preferred Reporting Items for Systematic reviews and Meta-analysis guidelines extension for scoping reviews. Six international and two local databases, and government and non-government websites were searched. Data published in the English or Filipino language on dementia epidemiology, research, diagnostics, management, manpower, and training were extracted from the earliest indexed record until June 2022. RESULTS: The prevalence of dementia in the Philippines is high and research output on all aspects of dementia is low. Cost is a major barrier as health care coverage is limited, with reliance mainly on out-of-pocket payments, leading to challenges in the proper diagnosis and treatment of dementia. There is a low specialist-to-population ratio, with shortages beyond manpower and training. CONCLUSIONS: Gaps in dementia care include limited published local data, high healthcare costs, inadequate health financing, and limited manpower.
Keywords: Dementia; Health Care Costs; Health Services; Humans; Philippines; Prevalence

Dementia Ideal Care: Ecosystem Map of Best Practices and Care Pathways Enhanced by Technology and Community. - Dombrowski, Wen; Mims, Adrienne; Kremer, Ian; Cano Desandes, Pedro; Rodrigo-Herrero, Silvia; Epps, Fayron; Snow, Teepa; Gutierrez, Myrna; Nasta, Anil; Epperly, Mikele Bunce; Manaloto, Katrina; Hansen, Jennie Chin (J Alzheimers Dis, 2024)
BACKGROUND: Globally, much work has been done by nonprofit, private, and academic groups to develop best practices for the care of people living with dementia (PLWD), including Alzheimer's disease. However, these best practices reside in disparate repositories and tend to focus on one phase of the patient journey or one relevant group. OBJECTIVE: To fill this gap, we developed a Dementia Ideal Care Map that everyone in the dementia ecosystem can use as an actionable tool for awareness, policy development, funding, research, training, service delivery, and technology design. The intended audience includes (and not limited to) policymakers, academia, industry, technology developers, health system leaders, clinicians, social service providers, patient advocates, PLWD, their families, and communities at large. METHODS: A search was conducted for published dementia care best practices and quality measures, which were then summarized in a visual diagram. The draft diagram was analyzed to identify barriers to ideal care. Then, additional processes, services, technologies, and quality measures to overcome those challenges were brainstormed. Feedback was then obtained from experts. RESULTS: The Dementia Ideal Care Map summarizes the ecosystem of over 200 best practices, nearly 100 technology enablers, other infrastructure, and enhanced care pathways in one comprehensive diagram. It includes psychosocial interventions, care partner support, community-based organizations; awareness, risk reduction; initial detection, diagnosis, ongoing medical care; governments, payers, health systems, businesses, data, research, and training. CONCLUSIONS: Dementia Ideal Care Map is a practical tool for planning and coordinating dementia care. This visualized ecosystem approach can be applied to other conditions.
Keywords: Delivery of Health Care; Dementia; Humans; Practice Guidelines as Topic

Effect of Metformin on Plasma and Cerebrospinal Fluid Biomarkers in Non-Diabetic Older Adults with Mild Cognitive Impairment Related to Alzheimer's Disease. - Weinberg, Marc S; He, Yingnan; Kivisäkk, Pia; Arnold, Steven E; Das, Sudeshna (J Alzheimers Dis, 2024)
BACKGROUND: Alzheimer's disease (AD) is a complicated condition involving multiple metabolic and immunologic pathophysiological processes that can occur with the hallmark pathologies of amyloid-β, tau, and neurodegeneration. Metformin, an anti-diabetes drug, targets several of these disease processes in in vitro and animal studies. However, the effects of metformin on human cerebrospinal fluid (CSF) and plasma proteins as potential biomarkers of treatment remain unexplored. OBJECTIVE: Using proteomics data from a metformin clinical trial, identify the impact of metformin on plasma and CSF proteins. METHODS: We analyzed plasma and CSF proteomics data collected previously (ClinicalTrials.gov identifier: NCT01965756, conducted between 2013 and 2015), and conduced bioinformatics analyses to compare the plasma and CSF protein levels after 8 weeks of metformin or placebo use to their baseline levels in 20 non-diabetic patients with mild cognitive impairment (MCI) and positive AD biomarkers participants. RESULTS: 50 proteins were significantly (unadjusted p < 0.05) altered in plasma and 26 in CSF after 8 weeks of metformin use, with 7 proteins in common (AZU1, CASP-3, CCL11, CCL20, IL32, PRTN3, and REG1A). The correlation between changes in plasma and CSF levels of these 7 proteins after metformin use relative to baseline levels was high (r = 0.98). The proteins also demonstrated temporal stability. CONCLUSIONS: Our pilot study is the first to investigate the effect of metformin on plasma and CSF proteins in non-diabetic patients with MCI and positive AD biomarkers and identifies several candidate plasma biomarkers for future clinical trials after confirmatory studies.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Biomarkers; Cognitive Dysfunction; Double-Blind Method; Female; Humans; Hypoglycemic Agents; Male; Metformin; Middle Aged; Proteomics

The Effects of Pomegranate Seed Oil on Mild Cognitive Impairment. - Chatzikostopoulos, Thanos; Gialaouzidis, Moses; Koutoupa, Anna; Tsolaki, Magda (J Alzheimers Dis, 2024)
BACKGROUND: In recent years, there has been a growing interest, supported by many experimental and clinical studies, about the benefits of pomegranate in preventing various pathologic conditions, including brain neurodegeneration. The pomegranate seed oil (PSO) contains high levels of fatty acids that have antioxidant and anti-inflammatory properties. OBJECTIVE: Due to the lack of clinical trials, the aim of the present study was to investigate the effects of PSO on cognition of people with mild cognitive impairment (MCI). METHODS: Eighty people with the diagnosis of MCI were randomized forty to take 5 drops of PSO and follow the Mediterranean Diet (MeDi) and forty just followed MeDi. All were examined with an extensive neuropsychological assessment before and after one year of treatment. RESULTS: The results showed that the participants who took the PSO had statistically significantly better global cognition (p = 0.004), verbal episodic memory (p = 0.009), and processing and executive functions (p < 0.001) in contrast with the participants who did not take it. CONCLUSIONS: In conclusion, the PSO can be beneficial for people with MCI as it is helpful for some important cognitive domains. As PSO is a natural product that does not burden the human body, it can be used by people with MCI and be a significant and promising part of holistic approaches for the prevention of dementia.
Keywords: Biological Products; Cognition; Cognitive Dysfunction; Humans; Neuropsychological Tests; Plant Oils; Pomegranate

Elevated Risk of Dementia Diagnosis in Older Adults with Low Frequencies and Durations of Social Conversation. - Shimada, Hiroyuki; Doi, Takehiko; Tsutsumimoto, Kota; Makino, Keitaro; Harada, Kenji; Tomida, Kouki; Arai, Hidenori (J Alzheimers Dis, 2024)
BACKGROUND: Social networks and social participation have protective effects on cognitive function maintenance and Alzheimer's disease and general dementia development. OBJECTIVE: We aimed to investigate the association between conversations and dementia incidence in older adults. METHODS: This longitudinal prospective cohort study used population data from the National Center for Geriatric and Gerontology-Study of Geriatric Syndromes (NCGG-SGS) from September 2015 to February 2017. The database included 4,167 individuals in Japan aged ≥60 years who were generally healthy and without major cognitive impairment. Participants were classified into two groups according to six daily conversation measures at baseline. The conversation index was calculated as a composite score for these measures. Participants were tracked monthly over 60 months for new-onset dementia. RESULTS: Data from 2,531 participants were analyzed (72.7±6.7 years; range: 60-96 years). Dementia incidence per 1,000 person-years was 15.7 (95% confidence interval, 13.6-18.1). The Youden index determined the cut-off point for dementia incidence, with a conversation index of 16/17 points. The low conversation group included more participants with new-onset dementia. Cox proportional hazards regression crude models showed remarkable relationships between dementia onset and specific conversation measurements, including conversation index. According to the Cox regression adjusted model, the cut-off point of the conversation index showed only a remarkable relationship with dementia onset. CONCLUSIONS: Dementia risk was extensively associated with low daily conversation statuses. The assessment of conversational factors may be useful as a risk indicator for the development of Alzheimer's disease and general dementia.
Keywords: Aged; Alzheimer Disease; Cognitive Dysfunction; Dementia; Geriatrics; Humans; Prospective Studies

Epistatic Features and Machine Learning Improve Alzheimer's Disease Risk Prediction Over Polygenic Risk Scores. - Hermes, Stephen; Cady, Janet; Armentrout, Steven; O'Connor, James; Holdaway, Sarah Carlson; Cruchaga, Carlos; Wingo, Thomas; Greytak, Ellen McRae (J Alzheimers Dis, 2024)
BACKGROUND: Polygenic risk scores (PRS) are linear combinations of genetic markers weighted by effect size that are commonly used to predict disease risk. For complex heritable diseases such as late-onset Alzheimer's disease (LOAD), PRS models fail to capture much of the heritability. Additionally, PRS models are highly dependent on the population structure of the data on which effect sizes are assessed and have poor generalizability to new data. OBJECTIVE: The goal of this study is to construct a paragenic risk score that, in addition to single genetic marker data used in PRS, incorporates epistatic interaction features and machine learning methods to predict risk for LOAD. METHODS: We construct a new state-of-the-art genetic model for risk of Alzheimer's disease. Our approach innovates over PRS models in two ways: First, by directly incorporating epistatic interactions between SNP loci using an evolutionary algorithm guided by shared pathway information; and second, by estimating risk via an ensemble of non-linear machine learning models rather than a single linear model. We compare the paragenic model to several PRS models from the literature trained on the same dataset. RESULTS: The paragenic model is significantly more accurate than the PRS models under 10-fold cross-validation, obtaining an AUC of 83% and near-clinically significant matched sensitivity/specificity of 75%. It remains significantly more accurate when evaluated on an independent holdout dataset and maintains accuracy within APOE genotype strata. CONCLUSIONS: Paragenic models show potential for improving disease risk prediction for complex heritable diseases such as LOAD over PRS models.
Keywords: Aged; Alzheimer Disease; Apolipoproteins E; Epistasis, Genetic; Female; Genetic Predisposition to Disease; Genetic Risk Score; Genome-Wide Association Study; Humans; Machine Learning; Male; Models, Genetic; Multifactorial Inheritance; Polymorphism, Single Nucleotide

First Biodistribution Study of [68Ga]Ga-NOTA-Insulin Following Intranasal Administration in Adult Vervet Monkeys. - Solingapuram Sai, Kiran Kumar; Erichsen, Jennifer M; Gollapelli, Krishna K; Krizan, Ivan; Miller, Mack; Bansode, Avinash; Jorgensen, Mathew J; Register, Thomas; Cazzola, Charles; Gandhi, Reenal; Suman, Julie; Craft, Suzanne (J Alzheimers Dis, 2024)
BACKGROUND: Intranasal insulin (INI) is being explored as a treatment for Alzheimer's disease (AD). Improved memory, functional ability, and cerebrospinal fluid (CSF) AD biomarker profiles have been observed following INI administration. However, the method of intranasal delivery may significantly affect outcomes. OBJECTIVE: To show reliable delivery of insulin to the brain using the Aptar Cartridge Pump System (CPS) intranasal delivery system. METHODS: To visualize INI biodistribution, we developed a novel PET radiotracer, Gallium 68-radiolabeled (NOTA-conjugated) insulin, [68Ga]Ga-NOTA-insulin. We used the Aptar CPS to administer [68Ga]Ga-NOTA-insulin to anesthetized healthy adult vervet monkeys and measured brain regional activity and whole-body dosimetry following PET/CT scans. RESULTS: We observed brain penetration of [68Ga]Ga-NOTA-insulin following intranasal administration with the Aptar CPS. Radioactive uptake was seen in multiple regions, including the amygdala, putamen, hypothalamus, hippocampus, and choroid plexus. A safety profile and whole-body dosimetry were also established in a second cohort of vervets. Safety was confirmed: vitals remained stable, blood glucose levels were unchanged, and no organ was exposed to more than 2.5 mSv of radioactivity. Extrapolations from vervet organ distribution allowed for estimation of the [68Ga]Ga-NOTA-insulin absorbed dose in humans, and the maximum dose of [68Ga]Ga-NOTA-insulin that can be safely administered to humans was determined to be 185 MBq. CONCLUSIONS: The use of [68Ga]Ga-NOTA-insulin as a PET radiotracer is safe and effective for observing brain uptake in vervet monkeys. Further, the Aptar CPS successfully targets [68Ga]Ga-NOTA-insulin to the brain. The data will be essential in guiding future studies of intranasal [68Ga]Ga-NOTA-insulin administration in humans.
Keywords: Administration, Intranasal; Animals; Brain; Chlorocebus aethiops; Female; Gallium Radioisotopes; Heterocyclic Compounds; Heterocyclic Compounds, 1-Ring; Insulin; Male; Positron Emission Tomography Computed Tomography; Positron-Emission Tomography; Radiopharmaceuticals; Tissue Distribution

Functional Connectivity Favors Aberrant Visual Network c-Fos Expression Accompanied by Cortical Synapse Loss in a Mouse Model of Alzheimer's Disease. - L'Esperance, Oliver J; McGhee, Joshua; Davidson, Garett; Niraula, Suraj; Smith, Adam S; Sosunov, Alexandre A; Yan, Shirley ShiDu; Subramanian, Jaichandar (J Alzheimers Dis, 2024)
BACKGROUND: While Alzheimer's disease (AD) has been extensively studied with a focus on cognitive networks, visual network dysfunction has received less attention despite compelling evidence of its significance in AD patients and mouse models. We recently reported c-Fos and synaptic dysregulation in the primary visual cortex of a pre-amyloid plaque AD-model. OBJECTIVE: We test whether c-Fos expression and presynaptic density/dynamics differ in cortical and subcortical visual areas in an AD-model. We also examine whether aberrant c-Fos expression is inherited through functional connectivity and shaped by light experience. METHODS: c-Fos+ cell density, functional connectivity, and their experience-dependent modulation were assessed for visual and whole-brain networks in both sexes of 4-6-month-old J20 (AD-model) and wildtype (WT) mice. Cortical and subcortical differences in presynaptic vulnerability in the AD-model were compared using ex vivo and in vivo imaging. RESULTS: Visual cortical, but not subcortical, networks show aberrant c-Fos expression and impaired experience-dependent modulation. The average functional connectivity of a brain region in WT mice significantly predicts aberrant c-Fos expression, which correlates with impaired experience-dependent modulation in the AD-model. We observed a subtle yet selective weakening of excitatory visual cortical synapses. The size distribution of cortical boutons in the AD-model is downscaled relative to those in WT mice, suggesting a synaptic scaling-like adaptation of bouton size. CONCLUSIONS: Visual network structural and functional disruptions are biased toward cortical regions in pre-plaque J20 mice, and the cellular and synaptic dysregulation in the AD-model represents a maladaptive modification of the baseline physiology seen in WT conditions.
Keywords: Alzheimer Disease; Animals; Disease Models, Animal; Female; Male; Mice; Mice, Inbred C57BL; Mice, Transgenic; Proto-Oncogene Proteins c-fos; Synapses; Visual Cortex

Influence of genotype on PCSK9-lipids association in cerebrospinal fluid and serum of patients in the Alzheimer's disease continuum. - Papotti, Bianca; Palumbo, Marcella; Adorni, Maria Pia; Elviri, Lisa; Chiari, Annalisa; Tondelli, Manuela; Bedin, Roberta; Baldelli, Enrica; Lancellotti, Giulia; Lupo, Maria Giovanna; Ferri, Nicola; Bertolotti, Marco; et al. (J Alzheimers Dis, 2024)
BACKGROUND: Alterations in factors involved in cholesterol homeostasis are critical in Alzheimer's disease (AD), but the stage of occurrence, their specific association, and a possible relationship with the genotype are not clarified. OBJECTIVE: We aimed to quantify and correlate specific lipid factors in patients with different degrees of cognitive decline, namely patients with AD and patients with mild cognitive impairment due to AD (MCI-AD), carriers or non-carriers of the genotype. METHODS: We evaluated Proprotein Convertase Subtilisin/Kexin type 9 (PCSK9), cholesterol and the oxidative metabolites 24-, 25-, 27-hydroxycholesterol (HC) in the cerebrospinal fluid (CSF) and serum of AD (n = 28) and MCI-AD (n = 27) patients. RESULTS: CSF and serum PCSK9 and lipids were similar, except for higher serum PCSK9 and triglycerides in MCI-AD compared to AD. In CSF, AD carriers showed higher PCSK9 and 24-HC (+61.3%,  = 0.027 and +32.7%,  = 0.037), compared to non-carriers. There was a negative association between CSF PCSK9 and 27-HC in AD (r = -0.444,  = 0.049) and, exclusively among AD carriers, a negative association between CSF PCSK9 and 24-HC (r = -0.786,  = 0.028). A positive correlation was observed between CSF and serum PCSK9 in AD (r = 0.520,  = 0.004), driven by carriers (r = 0.544,  = 0.038), suggesting PCSK9 exchange between brain and periphery. A positive correlation was detected between serum and CSF 27-HC (r = 0.465,  = 0.039) in AD. None of these results were found in MCI-AD patients. CONCLUSIONS: PCSK9 and 24-HC might be specific markers of ApoE4-associated lipid alterations in AD, possibly contributing to clinical progression in the AD continuum.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Apolipoprotein E4; Biomarkers; Cholesterol; Cognitive Dysfunction; Female; Genotype; Humans; Lipids; Male; Middle Aged; Proprotein Convertase 9

An Insertion Within SIRPβ1 Shows a Dual Effect Over Alzheimer's Disease Cognitive Decline Altering the Microglial Response. - García-Alberca, José María; de Rojas, Itziar; Sanchez-Mejias, Elisabeth; Garrido-Martín, Diego; Gonzalez-Palma, Laura; Jimenez, Sebastian; Pino-Angeles, Almudena; Cruz-Gamero, Jose Manuel; Mendoza, Silvia; Alarcón-Martín, Emilio; Muñoz-Castro, Clara; Real, Luis Miguel; et al. (J Alzheimers Dis, 2024)
BACKGROUND: Microglial dysfunction plays a causative role in Alzheimer's disease (AD) pathogenesis. Here we focus on a germline insertion/deletion variant mapping SIRPβ1, a surface receptor that triggers amyloid-β(Aβ) phagocytosis via TYROBP. OBJECTIVE: To analyze the impact of this copy-number variant in SIRPβ1 expression and how it affects AD molecular etiology. METHODS: Copy-number variant proxy rs2209313 was evaluated in GERALD and GR@ACE longitudinal series. Hippocampal specimens of genotyped AD patients were also examined. SIRPβ1 isoform-specific phagocytosis assays were performed in HEK393T cells. RESULTS: The insertion alters the SIRPβ1 protein isoform landscape compromising its ability to bind oligomeric Aβ and its affinity for TYROBP. SIRPβ1 Dup/Dup patients with mild cognitive impairment show an increased cerebrospinal fluid t-Tau/Aβ ratio (p = 0.018) and a higher risk to develop AD (OR = 1.678, p = 0.018). MRIs showed that Dup/Dup patients exhibited a worse initial response to AD. At the moment of diagnosis, all patients showed equivalent Mini-Mental State Examination scores. However, AD patients with the duplication had less hippocampal degeneration (p < 0.001) and fewer white matter hyperintensities. In contrast, longitudinal studies indicate that patients bearing the duplication allele show a slower cognitive decline (p = 0.013). Transcriptional analysis also shows that the SIRPβ1 duplication allele correlates with higher TREM2 expression and an increased microglial activation. CONCLUSIONS: The SIRPβ1 internal duplication has opposite effects over MCI-to-Dementia conversion risk and AD progression, affecting microglial response to Aβ. Given the pharmacological approaches focused on the TREM2-TYROBP axis, we believe that SIRPβ1 structural variant might be considered as a potential modulator of this causative pathway.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Cognitive Dysfunction; Humans; Microglia; Phagocytosis; Receptors, Cell Surface

Memory consolidation, temporal and parietal atrophy, and metabolism in amyloid-β positive and negative mild cognitive impairment. - Keith, Cierra M; Haut, Marc W; Vieira Ligo Teixeira, Camila; Mehta, Rashi I; Phelps, Holly; Ward, Melanie; Miller, Mark; Navia, R Osvaldo; Coleman, Michelle M; Marano, Gary; Wang, Xiaofei; Pockl, Stephanie; et al. (J Alzheimers Dis, 2024)
BACKGROUND: Alzheimer's disease (AD) is classically characterized by alterations in memory consolidation. With the advent of diagnostic biomarkers, some patients clinically diagnosed with AD display biomarkers inconsistent with the diagnosis. OBJECTIVE: We aimed to explore differences in memory consolidation and neurodegeneration of the temporal and parietal lobes as a function of amyloid-β status in amnestic mild cognitive impairment (aMCI). METHODS: We examined differences in memory consolidation and neurodegeneration between patients diagnosed with amyloid-β positive aMCI (Aβ+ N = 78), amyloid-β negative aMCI (Aβ- N = 48), and healthy participants (HP; N = 41), within a well-characterized clinical cohort. RESULTS: Aβ+ exhibited more pronounced consolidation impairments compared to Aβ-, while Aβ- faced more consolidation challenges than HP. Both Aβ+ and Aβ- were similar in hippocampal volume and entorhinal thickness, but Aβ+ had thinner inferior parietal cortex than Aβ-. Using F-fluoro-deoxyglucose-positron emission tomography, metabolism in both temporal and parietal regions was lower in Aβ+ relative to Aβ-. CONCLUSIONS: These findings suggest pathologies other than AD likely contribute to memory consolidation difficulties in aMCI, and neurodegeneration of the parietal cortex in combination with hypometabolism may contribute to more pronounced consolidation problems in Aβ+.
Keywords: Aged; Aged, 80 and over; Amyloid beta-Peptides; Atrophy; Cognitive Dysfunction; Female; Fluorodeoxyglucose F18; Humans; Magnetic Resonance Imaging; Male; Memory Consolidation; Middle Aged; Neuropsychological Tests; Parietal Lobe; Positron-Emission Tomography; Temporal Lobe

A Metabolomics Analysis of a Novel Phenotype of Older Adults at Higher Risk of Dementia. - Sultana, Munira; Camicioli, Richard; Dixon, Roger A; Whitehead, Shawn; Pieruccini-Faria, Frederico; Petrotchenko, Evgeniy; Speechley, Mark; Borchers, Christoph H; Montero-Odasso, Manuel (J Alzheimers Dis, 2024)
BACKGROUND: Older adults presenting with dual-decline in cognition and walking speed face a 6-fold higher risk for dementia compared with those showing no decline. We hypothesized that the metabolomics profile of dual-decliners would be unique even before they show signs of decline in cognition and gait speed. OBJECTIVE: The objective of this study was to determine if plasma metabolomics signatures can discriminate dual-decliners from no decliners, purely cognitive decliners, and purely motor decliners prior to decline. METHODS: A retrospective cross-sectional study using baseline plasma for untargeted metabolomics analyses to investigate early signals of later dual-decline status in study participants (n = 76) with convenient sampling. Dual-decline was operationalized as decline in gait speed (>10 cm/s) and cognition (>2 points decline in Montreal Cognitive Assessment score) on at least two consecutive 6-monthly assessments. The participants' decliner status was evaluated 3 years after the blood sample was collected. Pair-wise comparison of detected compounds was completed using principal components and hierarchical clustering analyses. RESULTS: Analyses did not detect any cluster separation in untargeted metabolomes across baseline groups. However, follow-up analyses of specific molecules detected 4 compounds (17-Hydroxy-12-(hydroxymethyl)-10-oxo-8 oxapentacyclomethyl hexopyranoside, Fleroxacin, Oleic acid, and 5xi-11,12-Dihydroxyabieta-8(14),9(11),12-trien-20-oic acid) were at significantly higher concentration among the dual-decliners compared to non-decliners. The pure cognitive decliner group had significantly lower concentration of six compounds (1,3-nonanediol acetate, 4-(2-carboxyethyl)-2-methoxyphenyl beta-D-glucopyranosiduronic acid, oleic acid, 2E-3-[4-(sulfo-oxy)phenyl] acrylic acid, palmitelaidic acid, and myristoleic acid) compared to the non-decliner group. CONCLUSIONS: The unique metabolomics profile of dual-decliners warrants follow-up metabolomics analysis. Results may point to modifiable pathways.
Keywords: Aged; Aged, 80 and over; Cognitive Dysfunction; Cross-Sectional Studies; Dementia; Female; Humans; Male; Metabolomics; Phenotype; Retrospective Studies

Neural Computation-Based Methods for the Early Diagnosis and Prognosis of Alzheimer's Disease Not Using Neuroimaging Biomarkers: A Systematic Review. - Cabrera-León, Ylermi; Báez, Patricio García; Fernández-López, Pablo; Suárez-Araujo, Carmen Paz (J Alzheimers Dis, 2024)
BACKGROUND: The growing number of older adults in recent decades has led to more prevalent geriatric diseases, such as strokes and dementia. Therefore, Alzheimer's disease (AD), as the most common type of dementia, has become more frequent too. BACKGROUND: Objective: The goals of this work are to present state-of-the-art studies focused on the automatic diagnosis and prognosis of AD and its early stages, mainly mild cognitive impairment, and predicting how the research on this topic may change in the future. METHODS: Articles found in the existing literature needed to fulfill several selection criteria. Among others, their classification methods were based on artificial neural networks (ANNs), including deep learning, and data not from brain signals or neuroimaging techniques were used. Considering our selection criteria, 42 articles published in the last decade were finally selected. RESULTS: The most medically significant results are shown. Similar quantities of articles based on shallow and deep ANNs were found. Recurrent neural networks and transformers were common with speech or in longitudinal studies. Convolutional neural networks (CNNs) were popular with gait or combined with others in modular approaches. Above one third of the cross-sectional studies utilized multimodal data. Non-public datasets were frequently used in cross-sectional studies, whereas the opposite in longitudinal ones. The most popular databases were indicated, which will be helpful for future researchers in this field. CONCLUSIONS: The introduction of CNNs in the last decade and their superb results with neuroimaging data did not negatively affect the usage of other modalities. In fact, new ones emerged.
Keywords: Alzheimer Disease; Biomarkers; Cognitive Dysfunction; Deep Learning; Early Diagnosis; Humans; Neural Networks, Computer; Neuroimaging; Prognosis

Odor Identification Across Time in Mutation Carriers and Non-Carriers in Autosomal-Dominant Alzheimer's Disease. - Almkvist, Ove; Larsson, Maria; Graff, Caroline (J Alzheimers Dis, 2024)
BACKGROUND: Impaired odor identification is a characteristic of sporadic Alzheimer'sdisease(AD), but its presence in autosomal-dominantAD (adAD) remains uncertain. OBJECTIVE: To investigate odor identification ability in mutation carriers (MC) and non-carriers (NC) of adAD in relation to years to estimated clinical onset clinical onset (YECO) of disease. METHODS: Participants from six families with autosomal-dominant mutations (APP Swedish, APP Arctic, and PSEN1 mutations) included 20 MC and 20 NC. The groups were comparable in age, gender, education, number of APOE ɛ4 alleles, and YECO, but differed in global cognition (Mini-Mental State Examination). The MC group included individuals in asymptomatic, symptomatic cognitively unimpaired, mild cognitive impairment, and dementia stages of disease, spanning approximately 40 years of the AD continuum. All NC were asymptomatic. Olfactory function was assessed by means of free and cued identification of common odors summarized as total identification. RESULTS: MC performed poorer than NC in free and total identification. Four MC and none of the NC were anosmic. Olfactory functions in MC and NC were significantly and inversely related to time course (YECO) for both free and total identification. The decline in free identification began approximately 10 years prior to the estimated clinical onset of AD in MC. Odor identification proficiency was associated with episodic memory and executive function in MC and NC. CONCLUSIONS: Impaired odor identification is present well before the clinical diagnosis of AD in MC and is associated with disease progression. Odor identification ability may be a useful early biomarker for adAD.
Keywords: Alzheimer Disease; Cognition; Cognitive Dysfunction; Humans; Mutation; Odorants; Presenilin-1

O-GlcNAcylation and Its Roles in Neurodegenerative Diseases. - Du, Pengyang; Zhang, Xiaomin; Lian, Xia; Holscher, Christian; Xue, Guofang (J Alzheimers Dis, 2024)
As a non-classical post-translational modification, O-linked β-N-acetylglucosamine (O-GlcNAc) modification (O-GlcNAcylation) is widely found in human organ systems, particularly in our brains, and is indispensable for healthy cell biology. With the increasing age of the global population, the incidence of neurodegenerative diseases is increasing, too. The common characteristic of these disorders is the aggregation of abnormal proteins in the brain. Current research has found that O-GlcNAcylation dysregulation is involved in misfolding or aggregation of these abnormal proteins to mediate disease progression, but the specific mechanism has not been defined. This paper reviews recent studies on O-GlcNAcylation's roles in several neurodegenerative disorders such as Alzheimer's disease, Parkinson's disease, amyotrophic lateral sclerosis, Huntington's disease, Machado-Joseph's disease, and giant axonal neuropathy, and shows that O-GlcNAcylation, as glucose metabolism sensor, mediating synaptic function, participating in oxidative stress response and signaling pathway conduction, directly or indirectly regulates characteristic pathological protein toxicity and affects disease progression. The existing results suggest that targeting O-GlcNAcylation will provide new ideas for clinical diagnosis, prevention, and treatment of neurodegenerative diseases.
Keywords: Acetylglucosamine; Alzheimer Disease; Disease Progression; Humans; N-Acetylglucosaminyltransferases; Neurodegenerative Diseases; Protein Processing, Post-Translational; Proteins

Olfactory Dysfunction and Alzheimer's Disease: A Review. - McLaren, Alexandra M R; Kawaja, Michael D (J Alzheimers Dis, 2024)
Alzheimer's disease is the most common cause of dementia, and it is one of the leading causes of death globally. Identification and validation of biomarkers that herald the onset and progression of Alzheimer's disease is of paramount importance for early reliable diagnosis and effective pharmacological therapy commencement. A substantial body of evidence has emerged demonstrating that olfactory dysfunction is a preclinical symptom of neurodegenerative diseases including Alzheimer's disease. While a correlation between olfactory dysfunction and Alzheimer's disease onset and progression in humans exists, the mechanism underlying this relationship remains unknown. The aim of this article is to review the current state of knowledge regarding the range of potential factors that may contribute to the development of Alzheimer's disease-related olfactory dysfunction. This review predominantly focuses on genetic mutations associated with Alzheimer's disease including amyloid-β protein precursor, presenilin 1 and 2, and apolipoprotein E mutations, that may (in varying ways) drive the cellular events that lead to and sustain olfactory dysfunction.
Keywords: Alzheimer Disease; Amyloid beta-Protein Precursor; Animals; Apolipoproteins E; Humans; Mutation; Olfaction Disorders; Presenilin-1

Palliative Care in Nursing Home Residents with Young-Onset Dementia: Professional and Family Caregiver Perspectives. - Maters, Jasper; van der Steen, Jenny T; de Vugt, Marjolein E; Bakker, Christian; Koopmans, Raymond T C M (J Alzheimers Dis, 2024)
BACKGROUND: The evidence underpinning palliative care in dementia is mostly based on research in older populations. Little is known about the palliative care needs of people with young-onset dementia (YOD). OBJECTIVE: To describe palliative care practices including advance care planning (ACP) in people with YOD residing in Dutch nursing homes. METHODS: The study presents baseline questionnaire data from an observational cohort study. Physicians, family caregivers, and nursing staff completed questionnaires about 185 residents with YOD. The questionnaires included items on sociodemographics, quality of life measured with the quality of life in late-stage dementia (QUALID) scale, dementia-related somatic health problems, symptoms, pain medication, psychotropic drugs, and ACP. RESULTS: The mean age was 63.9 (SD 5.8) years. Half (50.3%) of them were female. Alzheimer's disease dementia (42.2%) was the most prevalent subtype. The mean QUALID score was 24.0 (SD 7.9) as assessed by family caregivers, and 25.3 (SD 8.6) as assessed by the nursing staff. Swallowing problems were the most prevalent dementia-related health problem (11.4%). Agitation was often reported by physicians (42.0%) and nursing staff (40.5%). Psychotropics were prescribed frequently (72.3%). A minority had written advance directives (5.4%) or documentation on treatment preferences by the former general practitioner (27.2%). Global care goals most often focused on comfort (73.9%). Proportions of do-not-treat orders were higher than do-treat orders for all interventions except for hospitalization and antibiotics. CONCLUSIONS: ACP must be initiated earlier, before nursing home admission. A palliative approach seems appropriate even though residents are relatively young and experience few dementia-related health problems.
Keywords: Aged; Alzheimer Disease; Caregivers; Dementia; Female; Humans; Male; Nursing Homes; Palliative Care; Quality of Life

Pharmacodynamic and Clinical Effects of Ginkgo Biloba Extract EGb 761 and Its Phytochemical Components in Alzheimer's Disease. - Morató, Xavier; Tartari, Juan Pablo; Pytel, Vanesa; Boada, Merce (J Alzheimers Dis, 2024)
Extracts made from plants are complex mixtures of substances with varying compositions depending on the plant material and method of manufacture. This complexity makes it difficult for scientists and clinicians to interpret findings from pharmacological and clinical research. We performed a narrative review summarizing information on ginkgo biloba leaf extract, its composition, pharmacological data and clinical evidence supporting its administration for the treatment of Alzheimer's disease (AD). Medicinal products containing ginkgo biloba leaf extract which are manufactured in compliance with the requirements of the European Pharmacopoeia are approved as medicinal products for the treatment of dementia and related conditions by drug regulatory agencies in Europe, Asia and South America. As multicomponent mixtures, they may affect various targets in the pathogenesis of AD, the most common form of dementia. Pharmacodynamic studies demonstrate the effects of EGb 761 and individual constituents on various pathophysiological features of experimentally induced cognitive impairment and neurodegeneration that could contribute to its clinical efficacy. The safety and efficacy in the treatment of AD and cognitive decline has been studied in randomized, placebo-controlled clinical trials. Most of the studies that investigate the effects of ginkgo biloba extract (GbE) used the special extract EGb 761, which makes it the best-researched plant preparation worldwide. It is therefore the only herbal alternative to standard-of-care anti-dementia drugs. However, the mechanism of action has not been fully elucidated yet, and the clinical studies in AD show heterogeneity.
Keywords: Alzheimer Disease; Animals; Ginkgo biloba; Ginkgo Extract; Humans; Phytotherapy; Plant Extracts

Psychosis in Neurodegenerative Dementias: A Systematic Comparative Review. - Cressot, Coralie; Vrillon, Agathe; Lilamand, Matthieu; Francisque, Hélène; Méauzoone, Aurélie; Hourregue, Claire; Dumurgier, Julien; Marlinge, Emeline; Paquet, Claire; Cognat, Emmanuel (J Alzheimers Dis, 2024)
BACKGROUND: Psychosis, characterized by delusions and/or hallucinations, is frequently observed during the progression of Alzheimer's disease (AD) and other neurodegenerative dementias (ND) (i.e., dementia with Lewy bodies (DLB), and frontotemporal dementia (FTD)) and cause diagnostic and management difficulties. OBJECTIVE: This review aims at presenting a concise and up-to-date overview of psychotic symptoms that occur in patients with ND with a comparative approach. METHODS: A systematic review was conducted following the PRISMA guidelines. 98 original studies investigating psychosis phenotypes in neurodegenerative dementias were identified (40 cohort studies, 57 case reports). RESULTS: Psychosis is a frequently observed phenomenon during the course of ND, with reported prevalence ranging from 22.5% to 54.1% in AD, 55.9% to 73.9% in DLB, and 18% to 42% in FTD. Throughout all stages of these diseases, noticeable patterns emerge depending on their underlying causes. Misidentification delusions (16.6-78.3%) and visual hallucinations (50-69.6%) are frequently observed in DLB, while paranoid ideas and somatic preoccupations seem to be particularly common in AD and FTD, (respectively 9.1-60.3% and 3.10-41.5%). Limited data were found regarding psychosis in the early stages of these disorders. CONCLUSIONS: Literature data suggest that different ND are associated with noticeable variations in psychotic phenotypes, reflecting disease-specific tendencies. Further studies focusing on the early stages of these disorders are necessary to enhance our understanding of early psychotic manifestations associated with ND and help in differential diagnosis issues.
Keywords: Alzheimer Disease; Delusions; Dementia; Frontotemporal Dementia; Humans; Lewy Body Disease; Neurodegenerative Diseases; Psychotic Disorders

Quantitative Metabolomic Analysis of the Rat Hippocampus: Effects of Age and of the Development of Alzheimer's Disease-Like Pathology. - Snytnikova, Olga; Telegina, Darya; Savina, Ekaterina; Tsentalovich, Yuri; Kolosova, Nataliya (J Alzheimers Dis, 2024)
BACKGROUND: Alzheimer's disease (AD) is the most common type of dementia in the elderly. Incomplete knowledge about the pathogenesis of this disease determines the absence of medications for the treatment of AD today. Animal models can provide the necessary knowledge to understand the mechanisms of biochemical processes occurring in the body in health and disease. OBJECTIVE: To identify the most promising metabolomic predictors and biomarkers reflecting metabolic disorders in the development of AD signs. METHODS: High resolution 1H NMR spectroscopy was used for quantitative metabolomic profiling of the hippocampus of OXYS rats, an animal model of sporadic AD, which demonstrates key characteristics of this disease. Animals were examined during several key periods: 20 days group corresponds to the "preclinical" period preceding the development of AD signs, during their manifestation (3 months), and active progression (18 months). Wistar rats of the same age were used as control. RESULTS: Ranges of variation and mean concentrations were established for 59 brain metabolites. The main metabolic patterns during aging, which are involved in energy metabolism pathways and metabolic shifts of neurotransmitters, have been established. Of particular note is the significant increase of scyllo-inositol and decrease of hypotaurine in the hippocampus of OXYS rats as compared to Wistars for all studied age groups. CONCLUSIONS: We suggest that the accumulation of scyllo-inositol and the reduction of hypotaurine in the brain, even at an early age, can be considered as predictors and potential biomarkers of the development of AD signs in OXYS rats and, probably, in humans.
Keywords: Aging; Alzheimer Disease; Animals; Disease Models, Animal; Hippocampus; Inositol; Magnetic Resonance Spectroscopy; Male; Metabolomics; Proton Magnetic Resonance Spectroscopy; Rats; Rats, Wistar

Recalibrating the Risk-Benefit Profiles of Lecanemab and Donanemab: Scales, Immunoreactivity, and Changes in Amyloid-β42. - Espay, Alberto J; Herrup, Karl; Imbimbo, Bruno P; Kepp, Kasper P; Daly, Timothy (J Alzheimers Dis, 2024)
Three recent anti-amyloid-β antibody trials for Alzheimer's disease reported similar effect sizes, used non-reactive saline as placebo, and showed large numbers of adverse events including imaging anomalies (ARIA) that correlate with cognitive changes. Conversely, all previous antibody trials were less reactive and pronounced ineffective. We argue that these observations point to unblinding bias, inflating apparent efficacy and thus altering the risk-benefit balance. Further, we highlight data demonstrating that beyond reducing amyloid, monoclonal antibodies increase monomeric amyloid-β42 in cerebrospinal fluid, which may explain potential benefits. We should recalibrate the efficacy of these antibodies and devote more resources into strategies beyond removing amyloid.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Antibodies, Monoclonal; Antibodies, Monoclonal, Humanized; Humans; Peptide Fragments; Risk Assessment

Regional differences in glucose metabolic decline and tau deposition in the Alzheimer's continuum brain. - Ishii, Kazunari; Yamada, Takahiro; Hanaoka, Kohei; Kaida, Hayato; Kojita, Yasuyuki; Kono, Atsushi; Hanada, Kazushi; Saigoh, Kazumasa; Sakuta, Shizuka; Hashimoto, Mamoru; Kato, Takashi; Nakamura, Akinori (J Alzheimers Dis, 2024)
BACKGROUND: Alzheimer's disease (AD) is characterized by the accumulation of amyloid-β and tau proteins, leading to neurofibrillary tangles. A biomarker-based diagnostic method called the ATN system categorizes AD pathology into amyloid-β (A), tau (T), and neurodegeneration (N). The relationship between regional tau deposition and reduced glucose metabolism in the preclinical AD stage is not well understood. OBJECTIVE: We presented voxel-by-voxel metabolic/tau deposition ratio (MTR) images to investigate the effects of tau deposition on metabolism in AD brains on a stage-by-stage basis. METHODS: We selected 174 subjects who underwent 3D-MRI, FDG-PET, amyloid PET, and tau PET scans. MTR images were created by normalizing FDG-PET toMK6240 PET images. Voxel-wise comparisons among 63 cognitively normal amyloid-negative (CNA) subjects, 49 subjects with AD dementia (ADD), 23 subjects with mild cognitive impairment due to AD (MCA), and 39 preclinical AD (PRC) subjects were conducted. RESULTS: There was reduced glucose metabolism in ADD and MCA groups compared to CNA, predominantly in parietotemporal areas. Tau deposition was observed in wider areas in ADD and restricted to the medial temporal lobes in MCA. MTR exhibited significant reductions in broader regions in ADD and MCA, indicating simultaneous glucose metabolism decrease and tau deposition. At the MCA and PRC stages, glucose metabolism impairment and tau deposition were shown in separate regions by FDG PET and tau PET, respectively, while MTR images showed impairment in both regions. CONCLUSIONS: Our findings suggest that MTR imaging provides insights into AD pathophysiology by simultaneously assessing glucose metabolism and tau deposition. In the early stage of the AD continuum (MCA and PRC), metabolic decline and tau deposition occur independently in different brain regions.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Brain; Cognitive Dysfunction; Female; Fluorodeoxyglucose F18; Glucose; Humans; Magnetic Resonance Imaging; Male; Middle Aged; Positron-Emission Tomography; tau Proteins

Research Participants' Perspectives on Precision Diagnostics for Alzheimer's Disease. - Smith, Hadley Stevens; Robinson, Jill O; Levchenko, Ariel; Pereira, Stacey; Pascual, Belen; Bradbury, Kathleen; Arbones, Victoria; Fong, Jamie; Shulman, Joshua M; McGuire, Amy L; Masdeu, Joseph (J Alzheimers Dis, 2024)
BACKGROUND: Understanding research participants' responses to learning Alzheimer's disease (AD) risk information is important to inform clinical implementation of precision diagnostics given rapid advances in disease modifying therapies. OBJECTIVE: We assessed participants' perspectives on the meaning of their amyloid positron emission tomography (PET) imaging results for their health, self-efficacy to understand their results, psychological impact of learning their results, experience receiving their results from the clinical team, and interest in genetic testing for AD risk. METHODS: We surveyed individuals who were being clinically evaluated for AD and received PET imaging six weeks after the return of results. We analyzed responses to close-ended survey items by PET result using Fisher's exact test and qualitatively coded open-ended responses. RESULTS: A total of 88 participants completed surveys, most of whom had mild cognitive impairment due to AD (38.6%), AD (28.4%), or were cognitively unimpaired (21.6%). Participants subjectively understood their results (25.3% strongly agreed, 41.8% agreed), which could help them plan (16.5% strongly agreed, 49.4% agreed). Participants with a negative PET result (n = 25) reported feelings of relief (Fisher's exact p < 0.001) and happiness (p < 0.001) more frequently than those with a positive result. Most participants felt that they were treated respectfully and were comfortable voicing concerns during the disclosure process. Genetic testing was anticipated to be useful for medical care decisions (48.2%) and to inform family members about AD risk (42.9%). CONCLUSIONS: Participants had high subjective understanding and self-efficacy around their PET results and did not experience negative psychological effects. Interest in genetic testing was high.
Keywords: Alzheimer Disease; Amyloid; Amyloid beta-Peptides; Cognitive Dysfunction; Emotions; Humans; Positron-Emission Tomography

Safety Profile of Pimavanserin Therapy in Elderly Patients with Neurodegenerative Disease-Related Neuropsychiatric Symptoms: A Phase 3B Study. - Alva, Gus; Cubała, Wiesław J; Berrio, Ana; Coate, Bruce; Abler, Victor; Pathak, Sanjeev (J Alzheimers Dis, 2024)
BACKGROUND: Pimavanserin, a 5-HT2A receptor inverse agonist/antagonist, is the only medication approved by the FDA for the treatment of hallucinations and delusions associated with Parkinson's disease psychosis (PDP). Further expanding knowledge of the safety profile of pimavanserin in PDP and neurodegenerative diseases (NDD) such as Alzheimer's disease is of great interest for informing its use in patients with PDP (with or without dementia), given this population is highly sensitive to adverse effects following antipsychotic use. OBJECTIVE: This trial evaluated the effects of pimavanserin compared to placebo in frail older adults and elderly patients with neuropsychiatric symptoms related to NDD, such as hallucinations and delusions, to better understand the safety of pimavanserin in this population. METHODS: This was a phase 3b, 8-week treatment (study duration of up to 16 weeks), multicenter, randomized, double-blind, placebo-controlled, two-arm parallel-group trial (NCT03575052). The primary endpoint was safety and tolerability, measured by treatment-emergent adverse events (TEAEs). Secondary safety endpoints were change from baseline in motor and cognitive function; exploratory endpoints included suicidality, sleep quality, and neuropsychiatric symptoms. RESULTS: Incidences of TEAEs were similar between treatment groups; 29.8% reported ≥1 TEAE (pimavanserin: 30.4%; placebo: 29.3%), and 1.8% reported serious TEAEs (pimavanserin: 2.0%; placebo: 1.5%). Pimavanserin did not impact motor- or cognitive-related function. CONCLUSIONS: Pimavanserin was well tolerated and not associated with motor or cognitive impairment. Together, these findings highlight the manageable and generally favorable safety profile of pimavanserin in patients with NDD, contributing to our knowledge on the safety of pimavanserin as it generalizes to patients with PDP.
Keywords: Aged; Antipsychotic Agents; Drug Inverse Agonism; Hallucinations; Humans; Neurodegenerative Diseases; Piperidines; Psychotic Disorders; Urea

Short-Term Practice Effects on Cognitive Tests Across the Late Life Cognitive Spectrum and How They Compare to Biomarkers of Alzheimer's Disease. - Duff, Kevin; Hammers, Dustin B; Koppelmans, Vincent; King, Jace B; Hoffman, John M (J Alzheimers Dis, 2024)
BACKGROUND: Practice effects on cognitive testing in mild cognitive impairment (MCI) and Alzheimer's disease (AD) remain understudied, especially with how they compare to biomarkers of AD. OBJECTIVE: The current study sought to add to this growing literature. METHODS: Cognitively intact older adults (n = 68), those with amnestic MCI (n = 52), and those with mild AD (n = 45) completed a brief battery of cognitive tests at baseline and again after one week, and they also completed a baseline amyloid PET scan, a baseline MRI, and a baseline blood draw to obtain APOE ɛ4 status. RESULTS: The intact participants showed significantly larger baseline cognitive scores and practice effects than the other two groups on overall composite measures. Those with MCI showed significantly larger baseline scores and practice effects than AD participants on the composite. For amyloid deposition, the intact participants had significantly less tracer uptake, whereas MCI and AD participants were comparable. For total hippocampal volumes, all three groups were significantly different in the expected direction (intact > MCI > AD). For APOE ɛ4, the intact had significantly fewer copies of ɛ4 than MCI and AD. The effect sizes of the baseline cognitive scores and practice effects were comparable, and they were significantly larger than effect sizes of biomarkers in 7 of the 9 comparisons. CONCLUSION: Baseline cognition and short-term practice effects appear to be sensitive markers in late life cognitive disorders, as they separated groups better than commonly-used biomarkers in AD. Further development of baseline cognition and short-term practice effects as tools for clinical diagnosis, prognostic indication, and enrichment of clinical trials seems warranted.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Apolipoprotein E4; Biomarkers; Cognition; Cognitive Dysfunction; Female; Hippocampus; Humans; Magnetic Resonance Imaging; Male; Neuropsychological Tests; Positron-Emission Tomography; Practice, Psychological

The Standardized Extract of Centella asiatica and Its Fractions Exert Antioxidative and Anti-Neuroinflammatory Effects on Microglial Cells and Regulate the Nrf2/HO-1 Signaling Pathway. - Hambali, Aqilah; Jusril, Nor Atiqah; Md Hashim, Nur Fariesha; Abd Manan, Nizar; Adam, Siti Khadijah; Mehat, Muhammad Zulfadli; Adenan, Mohd Ilham; Stanslas, Johnson; Abdul Hamid, Hafizah (J Alzheimers Dis, 2024)
BACKGROUND: Neuroinflammation and oxidative stress can aggravate the progression of Alzheimer's disease (AD). Centella asiatica has been traditionally consumed for memory and cognition. The triterpenes (asiaticoside, madecassoside, asiatic acid, madecassic acid) have been standardized in the ethanolic extract of Centella asiatica (SECA). The bioactivity of the triterpenes in different solvent polarities of SECA is still unknown. OBJECTIVE: In this study, the antioxidative and anti-neuroinflammatory effects of SECA and its fractions were explored on lipopolysaccharides (LPS)-induced microglial cells. METHODS: HPLC measured the four triterpenes in SECA and its fractions. SECA and its fractions were tested for cytotoxicity on microglial cells using MTT assay. NO, pro-inflammatory cytokines (TNF-α, IL-6, IL-1β), ROS, and MDA (lipid peroxidation) produced by LPS-induced microglial cells were measured by colorimetric assays and ELISA. Nrf2 and HO-1 protein expressions were measured using western blotting. RESULTS: The SECA and its fractions were non-toxic to BV2 microglial cells at tested concentrations. The levels of NO, TNF-α, IL-6, ROS, and lipid peroxidation in LPS-induced BV2 microglial cells were significantly reduced (p < 0.001) by SECA and its fractions. SECA and some of its fractions can activate the Nrf2/HO-1 signaling pathway by significantly enhancing (p < 0.05) the Nrf2 and HO-1 protein expressions. CONCLUSIONS: This study suggests that the inhibitory activity of SECA and its fractions on pro-inflammatory and oxidative stress events may be the result of the activation of antioxidant defense systems. The potential of SECA and its fractions in reducing neuroinflammation and oxidative stress can be further studied as a potential therapeutic strategy for AD.
Keywords: Animals; Anti-Inflammatory Agents; Antioxidants; Cell Line; Centella; Heme Oxygenase-1; Lipopolysaccharides; Membrane Proteins; Mice; Microglia; Neuroinflammatory Diseases; NF-E2-Related Factor 2; Oxidative Stress; Plant Extracts; Signal Transduction; Triterpenes

Unveiling New Strategies Facilitating the Implementation of Artificial Intelligence in Neuroimaging for the Early Detection of Alzheimer's Disease. - Etekochay, Maudlyn O; Amaravadhi, Amoolya Rao; González, Gabriel Villarrubia; Atanasov, Atanas G; Matin, Maima; Mofatteh, Mohammad; Steinbusch, Harry Wilhelm; Tesfaye, Tadele; Praticò, Domenico (J Alzheimers Dis, 2024)
Alzheimer's disease (AD) is a chronic neurodegenerative disorder with a global impact. The past few decades have witnessed significant strides in comprehending the underlying pathophysiological mechanisms and developing diagnostic methodologies for AD, such as neuroimaging approaches. Neuroimaging techniques, including positron emission tomography and magnetic resonance imaging, have revolutionized the field by providing valuable insights into the structural and functional alterations in the brains of individuals with AD. These imaging modalities enable the detection of early biomarkers such as amyloid-β plaques and tau protein tangles, facilitating early and precise diagnosis. Furthermore, the emerging technologies encompassing blood-based biomarkers and neurochemical profiling exhibit promising results in the identification of specific molecular signatures for AD. The integration of machine learning algorithms and artificial intelligence has enhanced the predictive capacity of these diagnostic tools when analyzing complex datasets. In this review article, we will highlight not only some of the most used diagnostic imaging approaches in neurodegeneration research but focus much more on new tools like artificial intelligence, emphasizing their application in the realm of AD. These advancements hold immense potential for early detection and intervention, thereby paving the way for personalized therapeutic strategies and ultimately augmenting the quality of life for individuals affected by AD.
Keywords: Alzheimer Disease; Artificial Intelligence; Biomarkers; Brain; Early Diagnosis; Humans; Neuroimaging; Positron-Emission Tomography

Voluntary wheel running decreases amyloidogenic pathway and rescues cognition and mitochondrial energy metabolism in middle-aged female 3xTg-AD mouse model of Alzheimer's disease. - Dos Santos, Jonathas Rodrigo; Catalão, Carlos Henrique Rocha; Vulczak, Anderson; Azzolini, Ana Elisa Caleiro Seixas; Alberici, Luciane Carla (J Alzheimers Dis, 2024)
BACKGROUND: Evidence supports the neuroprotective effects of physical activity, either in experimental animal models or humans. However, the biological mechanisms by which physical exercise modulates dementia and Alzheimer's disease (AD) progression are still unclear. OBJECTIVE: This study investigated whether long-term (6 months) of voluntary wheel running induces neuroprotective effects in the pathogenesis of AD in middle-aged (8 months) female mice, focusing on energy metabolism. METHODS: A genetic mice model of AD (3xTg-AD) that performed wheel running presented changes in body metabolism and muscle oxidative profile, as well as restored discriminative and non-associative retention memories, evaluated by novel object recognition and open field tasks, respectively. RESULTS: In the hippocampus, these mice exhibited reduced levels of amyloidogenic AβPPβ fragment, phospho-Tau protein and phospho-Akt (activated form), without changes in phospho-AMPK (activated form). In addition, hippocampal mitochondria presented a restored respiratory function, characterized by lower coupling degree and weak contribution from complex I found in 3xTg-AD mice. CONCLUSIONS: The results demonstrated that voluntary exercise improves cognitive parameters and biochemical hallmarks of AD, modulates Akt activation and enhances mitochondrial energy metabolism in hippocampus of middle-aged 3xTg-AD female mice, thereby reinforcing the neuroprotective role of physical exercise and the involvement of mitochondria in the etiology of the AD.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Amyloid beta-Protein Precursor; Animals; Cognition; Disease Models, Animal; Energy Metabolism; Female; Hippocampus; Mice; Mice, Transgenic; Mitochondria; Physical Conditioning, Animal; tau Proteins

A 19-Year-Old Adolescent with Probable Alzheimer's Disease. - Jia, Jianping; Zhang, Yue; Shi, Yuqing; Yin, Xuping; Wang, Shiyuan; Li, Yan; Zhao, Tan; Liu, Wenying; Zhou, Aihong; Jia, Longfei (J Alzheimers Dis, 2023)
Alzheimer's disease (AD) primarily affects older adults. In this report, we present the case of a 19-year-old male with gradual memory decline for 2 years and World Health Organization-University of California Los Angeles Auditory Verbal Learning Test (WHO-UCLA AVLT) results also showing memory impairment. Positron emission tomography-magnetic resonance imaging with 18F fluorodeoxyglucose revealed atrophy of the bilateral hippocampus and hypometabolism in the bilateral temporal lobe. Examination of the patient's cerebrospinal fluid showed an increased concentration of p-tau181 and a decreased amyloid-β 42/40 ratio. However, through whole-genome sequencing, no known gene mutations were identified. Considering the above, the patient was diagnosed with probable AD.
Keywords: Adolescent; Aged; Alzheimer Disease; Amyloid beta-Peptides; Fluorodeoxyglucose F18; Humans; Magnetic Resonance Imaging; Male; Positron-Emission Tomography

Age-Related Association Between APOE ɛ4 and Cognitive Progression in de novo Parkinson's Disease. - Liu, Jia-Yao; Ma, Ling-Zhi; Wang, Jun; Cui, Xin-Jing; Sheng, Ze-Hu; Fu, Yan; Li, Meng; Ou, Ya-Nan; Yu, Jin-Tai; Tan, Lan; Lian, Yan (J Alzheimers Dis, 2023)
BACKGROUND: APOE ɛ4 genotype was correlated with exacerbation of pathology and higher risk of dementia in Parkinson's disease (PD). Meanwhile, the differential influence of APOE ɛ4 on cognition in young and old individuals interpreted as antagonistic pleiotropy. OBJECTIVE: To examine whether the effect of APOE ɛ4 on cognitive progression in de novo PD is age dependent. METHODS: In this study, 613 de novo PD patients were recruited from Parkinson's Progression Markers Initiative (PPMI). To examine the age-dependent relationship between APOE ɛ4 and cognitive changes, we added 3-way interaction of APOE ɛ4*baseline age*time to the linear mixed-effect (LME) models and evaluated the specific roles of APOE ɛ4 in the middle age group and elderly group separately. Cox regression was utilized to examine the progression of cognition in age-stratified PD participants. RESULTS: Age significantly modified relationship between APOE ɛ4 and cognitive changes in most cognitive domains (pinteraction <0.05). In the elderly group, APOE ɛ4 carriers showed steeper decline in global cognition (p = 0.001) as well as in most cognitive domains, and they had a greater risk of cognitive progression (adjusted HR 1.625, 95% CI 1.143-2.310, p = 0.007), compared with non-carriers. However, in the middle age group, no significant relationships between APOE ɛ4 and cognitive decline can be detected. CONCLUSION: Our results indicated that the APOE ɛ4 allele has an age-dependent effect on cognitive decline in PD patients. The underlying mechanisms need to be investigated in the future.
Keywords: Aged; Apolipoprotein E4; Cognition; Cognitive Dysfunction; Disease Progression; Genotype; Heterozygote; Humans; Parkinson Disease

An Alternative View of Familial Alzheimer's Disease Genetics. - Lardelli, Michael (J Alzheimers Dis, 2023)
Probabilistic and parsimony-based arguments regarding available genetics data are used to propose that Hardy and Higgin's amyloid cascade hypothesis is valid but is commonly interpreted too narrowly to support, incorrectly, the primacy of the amyloid-β peptide (Aβ) in driving Alzheimer's disease pathogenesis. Instead, increased activity of the βCTF (C99) fragment of AβPP is the critical pathogenic determinant altered by mutations in the APP gene. This model is consistent with the regulation of APP mRNA translation via its 5' iron responsive element. Similar arguments support that the pathological effects of familial Alzheimer's disease mutations in the genes PSEN1 and PSEN2 are not exerted directly via changes in AβPP cleavage to produce different ratios of Aβ length. Rather, these mutations likely act through effects on presenilin holoprotein conformation and function, and possibly the formation and stability of multimers of presenilin holoprotein and/or of the γ-secretase complex. All fAD mutations in APP, PSEN1, and PSEN2 likely find unity of pathological mechanism in their actions on endolysosomal acidification and mitochondrial function, with detrimental effects on iron homeostasis and promotion of "pseudo-hypoxia" being of central importance. Aβ production is enhanced and distorted by oxidative stress and accumulates due to decreased lysosomal function. It may act as a disease-associated molecular pattern enhancing oxidative stress-driven neuroinflammation during the cognitive phase of the disease.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Amyloid beta-Protein Precursor; Amyloid Precursor Protein Secretases; Humans; Iron; Mutation; Presenilin-1

Alzheimer's Disease: A Systems View Provides a Unifying Explanation of Its Development. - Grobler, Corlia; van Tongeren, Marvi; Gettemans, Jan; Kell, Douglas B; Pretorius, Etheresia (J Alzheimers Dis, 2023)
Alzheimer's disease (AD) is a debilitating neurodegenerative disorder affecting 50 million people globally. It is characterized by the presence of extracellular senile plaques and intracellular neurofibrillary tangles, consisting of amyloid-β and hyperphosphorylated tau proteins, respectively. Despite global research efforts, there is currently no cure available, due in part to an incomplete understanding of the disease pathogenesis. Numerous possible mechanisms, or hypotheses, explaining the origins of sporadic or late-onset AD have been proposed, including the amyloid-β, inflammatory, vascular, and infectious hypotheses. However, despite ample evidence, the failure of multiple trial drugs at the clinical stage illuminates the possible pitfalls of these hypotheses. Systems biology is a strategy which aims to elucidate the interactions between parts of a whole. Using this approach, the current paper shows how the four previously mentioned hypotheses of AD pathogenesis can be intricately connected. This approach allows for seemingly contradictory evidence to be unified in a system-focused explanation of sporadic AD development. Within this view, it is seen that infectious agents, such as P. gingivalis, may play a central role. The data presented here shows that when present, P. gingivalis or its virulence factors, such as gingipains, may induce or exacerbate pathologies underlying sporadic AD. This evidence supports the view that infectious agents, and specifically P. gingivalis, may be suitable treatment targets in AD.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Humans; Neurofibrillary Tangles; Plaque, Amyloid; tau Proteins

Association Between Oral Bacteria and Alzheimer's Disease: A Systematic Review and Meta-Analysis. - Liu, Sixin; Dashper, Stuart G; Zhao, Rui (J Alzheimers Dis, 2023)
BACKGROUND: Pre-clinical evidence implicates oral bacteria in the pathogenesis of Alzheimer's disease (AD), while clinical studies show diverse results. OBJECTIVE: To comprehensively assess the association between oral bacteria and AD with clinical evidence. METHODS: Studies investigating the association between oral bacteria and AD were identified through a systematic search of six databases PubMed, Embase, Cochrane Central Library, Scopus, ScienceDirect, and Web of Science. Methodological quality ratings of the included studies were performed. A best evidence synthesis was employed to integrate the results. When applicable, a meta-analysis was conducted using a random-effect model. RESULTS: Of the 16 studies included, ten investigated periodontal pathobionts and six were microbiome-wide association studies. Samples from the brain, serum, and oral cavity were tested. We found over a ten-fold and six-fold increased risk of AD when there were oral bacteria (OR = 10.68 95% CI: 4.48-25.43; p < 0.00001, I2 = 0%) and Porphyromonas gingivalis (OR = 6.84 95% CI: 2.70-17.31; p < 0.0001, I2 = 0%) respectively in the brain. While AD patients exhibited lower alpha diversity of oral microbiota than healthy controls, the findings of bacterial communities were inconsistent among studies. The best evidence synthesis suggested a moderate level of evidence for an overall association between oral bacteria and AD and for oral bacteria being a risk factor for AD. CONCLUSION: Current evidence moderately supports the association between oral bacteria and AD, while the association was strong when oral bacteria were detectable in the brain. Further evidence is needed to clarify the interrelationship between both individual species and bacterial communities and the development of AD.
Keywords: Alzheimer Disease; Cognitive Dysfunction; Humans; Microbiota; Porphyromonas gingivalis; Risk Factors

Associations of the Harvard Automated Phone Task and Alzheimer's Disease Pathology in Cognitively Normal Older Adults: Preliminary Findings. - Gonzalez, Christopher; Mimmack, Kayden J; Amariglio, Rebecca E; Becker, J Alex; Chhatwal, Jasmeer P; Fitzpatrick, Colleen D; Gatchel, Jennifer R; Johnson, Keith A; Katz, Zoe S; Kuppe, Madeline K; Locascio, Joseph J; Udeogu, Onyinye J; et al. (J Alzheimers Dis, 2023)
BACKGROUND: Detecting clinically meaningful changes in instrumental activities of daily living (IADL) at the earliest stages of Alzheimer's disease (AD) is critical. OBJECTIVE: The objective of this exploratory study was to examine the cross-sectional relationship between a performance-based IADL test, the Harvard Automated Phone Task (APT), and cerebral tau and amyloid burden in cognitively normal (CN) older adults. METHODS: Seventy-seven CN participants underwent flortaucipir tau and Pittsburgh Compound B amyloid PET. IADL were assessed using the three Harvard APT tasks: prescription refill (APT-Script), health insurance company call (APT-PCP), and bank transaction (APT-Bank). Linear regression models were used to determine associations between each APT task and entorhinal cortex, inferior temporal, or precuneus tau with or without an interaction with amyloid. RESULTS: Significant associations were found between APT-Bank task rate and interaction between amyloid and entorhinal cortex tau, and APT-PCP task and interactions between amyloid and inferior temporal and precuneus tau. No significant associations were found between the APT tasks and tau or amyloid alone. CONCLUSION: Our preliminary findings suggest an association between a simulated real-life IADL test and interactions of amyloid and several regions of early tau accumulation in CN older adults. However, some analyses were underpowered due to the small number of participants with elevated amyloid, and findings should be interpreted with caution. Future studies will further explore these associations cross-sectionally and longitudinally in order to determine whether the Harvard APT can serve as a reliable IADL outcome measure for preclinical AD prevention trials and ultimately in the clinic setting.
Keywords: Activities of Daily Living; Aged; Alzheimer Disease; Amyloid; Amyloid beta-Peptides; Amyloidogenic Proteins; Cognitive Dysfunction; Entorhinal Cortex; Humans; Positron-Emission Tomography; tau Proteins

CERAD (Consortium to Establish a Registry for Alzheimer's Disease) Neuropsychology Assessment Battery: 35 Years and Counting. - Fillenbaum, Gerda G; Mohs, Richard (J Alzheimers Dis, 2023)
BACKGROUND: In 1986, the Consortium to Establish a Registry for Alzheimer's Disease (CERAD) was mandated to develop a brief neuropsychological assessment battery (CERAD-NAB) for AD, for uniform neuropsychological assessment, and information aggregation. Initially used across the National Institutes of Aging-funded Alzheimer's Disease Research Centers, it has become widely adopted wherever information is desired on cognitive status and change therein, particularly in older populations. OBJECTIVE: Our purpose is to provide information on the multiple uses of the CERAD-NAB since its inception, and possible further developments. METHODS: Since searching on "CERAD neuropsychological assessment battery" or similar terms missed important information, "CERAD" alone was entered into PubMed and SCOPUS, and CERAD-NAB use identified from the resulting studies. Use was sorted into major categories, e.g., psychometric information, norms, dementia/differential dementia diagnosis, epidemiology, intervention evaluation, genetics, etc., also translations, country of use, and alternative data gathering approaches. RESULTS: CERAD-NAB is available in ∼20 languages. In addition to its initial purpose assessing AD severity, CERAD-NAB can identify mild cognitive impairment, facilitate differential dementia diagnosis, determine cognitive effects of naturally occurring and experimental interventions (e.g., air pollution, selenium in soil, exercise), has helped to clarify cognition/brain physiology-neuroanatomy, and assess cognitive status in dementia-risk conditions. Surveys of primary and tertiary care patients, and of population-based samples in multiple countries have provided information on prevalent and incident dementia, and cross-sectional and longitudinal norms for ages 35-100 years. CONCLUSION: CERAD-NAB has fulfilled its original mandate, while its uses have expanded, keeping up with advances in the area of dementia.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cross-Sectional Studies; Humans; Neuropsychological Tests; Neuropsychology; Psychometrics; Registries

Cerebrospinal Fluid sTREM-2, GFAP, and β-S100 in Symptomatic Sporadic Alzheimer's Disease: Microglial, Astrocytic, and APOE Contributions Along the Alzheimer's Disease Continuum. - Bonomi, Chiara Giuseppina; Assogna, Martina; Di Donna, Martina Gaia; Bernocchi, Francesca; De Lucia, Vincenzo; Nuccetelli, Marzia; Fiorelli, Denise; Loizzo, Stefano; Mercuri, Nicola Biagio; Koch, Giacomo; Martorana, Alessandro; Motta, Caterina (J Alzheimers Dis, 2023)
BACKGROUND: Many transversal mechanisms act synergistically at different time-points in the cascade of Alzheimer's disease (AD), since amyloid-β (Aβ) deposition, tau pathology, and neuroinflammation influence each other. OBJECTIVE: We explored the contributions of microglia and astrocytes in patients with symptomatic sporadic AD stratified according to AT(N) system and APOE genotype. METHODS: We compared the cerebrospinal fluid (CSF) levels of sTREM-2 and markers of astrocytic activation (GFAP; β-S100) from 71 patients with AD (23 A+T-,48 A+T+; 38 APOEɛ3, 33 APOEɛ4) and 30 healthy controls (HC). With multivariate analyses we investigated associations between glial biomarkers, Aβ42, and p-tau in all subgroups. RESULTS: CSF sTREM-2 was higher in A+T+ [1.437 (0.264)] and A+T- [1.355 (0.213)] than in HC [1.042 (0.198); both p < 0.001]; GFAP and β-S100 were comparable across groups. Considering all patients, sTREM-2 positively associated with Aβ42 (p = 0.04) and p-tau (=0.016), with the first being present only in the A+T- subgroup (p = 0.023). GFAP positively associated with Aβ42 in all patients (p = 0.020) and in the A+T+ subgroup (p = 0.04). Stratifying by APOE, a positive association of sTREM-2 and p-tau was confirmed selectively in carriers of ɛ4 (p = 0.018). Finally, sTREM-2 positively correlated with β-S100 in all subgroups, and with GFAP in A+T+ (p = 0.042). CONCLUSION: Our results confirm the increase of CSF sTREM-2 in AD, which associates with reduced amyloidopathy in A+T- patients. Moreover, microglial activation seems to increase CSF tau levels in carriers of APOEɛ4, is associated with astrocytic reactivity (GFAP) in A+T+, and likely leads the acquisition of a more neurotoxic astrocytic phenotype (β-S100).
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Apolipoproteins E; Astrocytes; Biomarkers; Humans; Microglia; Peptide Fragments; tau Proteins

Chiral Amino Acid Profiling in Serum Reveals Potential Biomarkers for Alzheimer's Disease. - Liu, Mingxia; Li, Mo; He, Jing; He, Yi; Yang, Jian; Sun, Zuoli (J Alzheimers Dis, 2023)
BACKGROUND: Alzheimer's disease (AD) is a complex neurodegenerative disease, and increasing evidence has linked dysregulation of amino acids to AD pathogenesis. However, the existing studies often ignore the chirality of amino acids, and some results are inconsistent and controversial. The changes of amino acid profiles in AD from the perspective of enantiomers remain elusive. OBJECTIVE: The purpose of this study is to investigate whether the levels of amino acids, especially D-amino acids, are deregulated in the peripheral serum of AD patients, with the ultimate goal of discovering novel biomarkers for AD. METHODS: The chiral amino acid profiles were determined by HPLC-MS/MS with a pre-column derivatization method. Experimental data obtained from 37 AD patients and 34 healthy controls (HC) were statistically analyzed. RESULTS: Among the 35 amino acids detected, D-proline, D/total-proline ratio, D-aspartate, and D/total-aspartate ratio were decreased, while D-phenylalanine was elevated in AD compared to HC. Significant age-dependent increases in D-proline, D/total-proline ratio, and D-phenylalanine were observed in HC, but not in AD. Receiver operator characteristic analyses of the combination of D-proline, D-aspartate, D-phenylalanine, and age for discriminating AD from HC provided satisfactory area under the curve (0.87), specificity (97.0%), and sensitivity (83.8%). Furthermore, the D-aspartate level was significantly decreased with the progression of AD, as assessed by the Clinical Dementia Rating Scale and Mini-Mental State Examination. CONCLUSION: The panels of D-proline, D-phenylalanine, and D-aspartate in peripheral serum may serve as novel biomarker candidates for AD. The latter parameter is further associated with the severity of AD.
Keywords: Alzheimer Disease; Amino Acids; Aspartic Acid; Biomarkers; D-Aspartic Acid; Humans; Neurodegenerative Diseases; Phenylalanine; Proline; Tandem Mass Spectrometry

Cleveland Clinic Cognitive Battery (C3B): Normative, Reliability, and Validation Studies of a Self-Administered Computerized Tool for Screening Cognitive Dysfunction in Primary Care. - Rao, Stephen M; Galioto, Rachel; Sokolowski, Megan; Pierce, Madelyn; Penn, Lisa; Sturtevant, Anna; Skugor, Blazenka; Anstead, Brent; Leverenz, James B; Schindler, David; Blum, David; Alberts, Jay L; et al. (J Alzheimers Dis, 2023)
BACKGROUND: The self-administered iPad-based Cleveland Clinic Cognitive Battery (C3B) was designed specifically for the efficient screening of cognitive functioning of older adults in a primary care setting. OBJECTIVE: 1) Generate regression-based norms from healthy participants to enable demographic corrections to facilitate clinical interpretation; 2) estimate test-retest reliability and practice effects; 3) examine ability to discriminate mild cognitive impairment (MCI) from healthy aging; 4) d etermine validity of screening in a distracting clinical environment; and 5) determine completion rates and patient satisfaction in a primary care setting. METHODS: Study 1 (S1) recruited a stratified sample of 428 healthy adults, ages 18-89, to generate regression-based equations. S2 assessed 2-week test-retest reliability and practice effects in 30 healthy elders. S3 recruited 30 MCI patients and 30 demographically-matched healthy controls. In S4, 30 healthy elders self-administered the C3B in a distracting environment and in a quiet private room in counterbalanced order. In a demonstration project, 470 consecutive primary care patients were administered the C3B as part of routine clinical care (S5). RESULTS: C3B performance was primarily influenced by age, education, and race (S1), had acceptably high test-retest reliability and minimal practice effects (S2), discriminated MCI from healthy controls (S3), was not negatively impacted by a distracting clinical environment (S4), had high completion rates (>92%) and positive ratings from primary care patients (S5). CONCLUSION: The C3B is a computerized cognitive screening tool that is reliable, validated, self-administered, and is conducive to integration into a busy primary care clinical workflow for detecting MCI, early Alzheimer's disease, and other related dementias.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Cognition; Cognitive Dysfunction; Humans; Middle Aged; Neuropsychological Tests; Primary Health Care; Reproducibility of Results; Young Adult

Detecting Anosognosia from the Prodromal Stage of Alzheimer's Disease. - Guieysse, Thomas; Lamothe, Roxane; Houot, Marion; Razafimahatratra, Solofo; Medani, Takfarinas; Lejeune, François-Xavier; Dreyfus, Gérard; Klarsfeld, André; Pantazis, Dimitrios; Koechlin, Etienne; Andrade, Katia (J Alzheimers Dis, 2023)
BACKGROUND: Though not originally developed for this purpose, the Healthy Aging Brain Care Monitor (HABC-M) seems a valuable instrument for assessing anosognosia in Alzheimer's disease (AD). OBJECTIVES: Our study aimed at 1) investigating the validity of the HABC-M (31 items), and its cognitive, psychological, and functional subscales, in discriminating AD patients from controls; 2) exploring whether the HABC-M discrepancy scores between the self-reports of patients/controls in these different domains and the respective ratings provided by their caregivers/informants correlate with an online measure of self-awareness; 3) determining whether the caregiver burden level, also derived from the HABC-M, could add additional support for detecting anosognosia. METHODS: The HABC-M was administered to 30 AD patients and 30 healthy controls, and to their caregivers/informants. A measure of online awareness was established from subjects' estimation of their performances in a computerized experiment. RESULTS: The HABC-M discrepancy scores distinguished AD patients from controls. The cognitive subscale discriminated the two groups from the prodromal AD stage, with an AUC of 0.88 [95% CI: 0.78;0.97]. Adding the caregiver burden level raised it to 0.94 [0.86;0.99]. Significant correlations between the HABC-M and online discrepancy scores were observed in the patients group, providing convergent validity of these methods. CONCLUSIONS: The cognitive HABC-M (six items) can detect anosognosia across the AD spectrum. The caregiver burden (four items) may corroborate the suspicion of anosognosia. The short-hybrid scale, built from these 10 items instead of the usual 31, showed the highest sensitivity for detecting anosognosia from the prodromal AD stage, which may further help with timely diagnosis.
Keywords: Agnosia; Alzheimer Disease; Brain; Caregivers; Humans; Neuropsychological Tests; Prodromal Symptoms

Diet's Role in Modifying Risk of Alzheimer's Disease: History and Present Understanding. - Grant, William B; Blake, Steven M (J Alzheimers Dis, 2023)
Diet is an important nonpharmacological risk-modifying factor for Alzheimer's disease (AD). The approaches used here to assess diet's role in the risk of AD include multi-country ecological studies, prospective and cross-sectional observational studies, and laboratory studies. Ecological studies have identified fat, meat, and obesity from high-energy diets as important risk factors for AD and reported that AD rates peak about 15-20 years after national dietary changes. Observational studies have compared the Western dietary pattern with those of the Dietary Approaches to Stop Hypertension (DASH), Mediterranean (MedDi), and Mediterranean-DASH Intervention for Neurodegenerative Delay (MIND) diets. Those studies identified AD risk factors including higher consumption of saturated and total fats, meat, and ultraprocessed foods and a lower risk of AD with higher consumption of fruits, legumes, nuts, omega-3 fatty acids, vegetables, and whole grains. Diet-induced factors associated with a significant risk of AD include inflammation, insulin resistance, oxidative stress, elevated homocysteine, dietary advanced glycation end products, and trimethylamine N-oxide. The molecular mechanisms by which dietary bioactive components and specific foods affect risk of AD are discussed. Given most countries' entrenched food supply systems, the upward trends of AD rates would be hard to reverse. However, for people willing and able, a low-animal product diet with plenty of anti-inflammatory, low-glycemic load foods may be helpful.
Keywords: Alzheimer Disease; Cross-Sectional Studies; Diet; Humans; Prospective Studies; Risk Factors

Early Life Stress Enhances Cognitive Decline and Alters Synapse Function and Interneuron Numbers in Young Male APP/PS1 Mice. - Brosens, Niek; Samouil, Dimitris; Stolker, Sabine; Katsika, Efthymia Vasilina; Weggen, Sascha; Lucassen, Paul J; Krugers, Harm J (J Alzheimers Dis, 2023)
BACKGROUND: Exposure to stress early in life increases the susceptibility to Alzheimer's disease (AD) pathology in aged AD mouse models. So far, the underlying mechanisms have remained elusive. OBJECTIVE: To investigate 1) effects of early life stress (ELS) on early functional signs that precede the advanced neuropathological changes, and 2) correlate synaptosomal protein content with cognition to identify neural correlates of AD. METHODS: APPswe/PS1dE9 mice and littermates were subjected to ELS by housing dams and pups with limited bedding and nesting material from postnatal days 2-9. At 3 months of age, an age where no cognitive loss or amyloid-β (Aβ) pathology is typically reported in this model, we assessed hippocampal Aβ pathology, synaptic strength and synapse composition and interneuron populations. Moreover, cognitive flexibility was assessed and correlated with synaptosomal protein content. RESULTS: While ELS did not affect Aβ pathology, it increased synaptic strength and decreased the number of calretinin+ interneurons in the hippocampal dentate gyrus. Both genotype and condition further affected the level of postsynaptic glutamatergic protein content. Finally, APP/PS1 mice were significantly impaired in cognitive flexibility at 3 months of age, and ELS exacerbated this impairment, but only at relatively high learning criteria. CONCLUSIONS: ELS reduced cognitive flexibility in young APP/PS1 mice and altered markers for synapse and network function. These findings at an early disease stage provide novel insights in AD etiology and in how ELS could increase AD susceptibility.
Keywords: Adverse Childhood Experiences; Alzheimer Disease; Amyloid beta-Peptides; Amyloid beta-Protein Precursor; Animals; Cognitive Dysfunction; Disease Models, Animal; Interneurons; Male; Mice; Mice, Transgenic; Plaque, Amyloid; Presenilin-1; Synapses

Effects of a Physical Activity Program that Incorporates Exercises Targeting Balance, Strength, and Proprioception on Cognitive Functions and Physical Performance in Old Adults with Mild Cognitive Impairment. - Boulares, Ayoub; Fabre, Claudine; Cherni, Ala; Jdidi, Hela; Gaied Chortane, Sabri; Trompetto, Carlo; Puce, Luca; Bragazzi, Nicola Luigi (J Alzheimers Dis, 2023)
BACKGROUND: Aging often leads to cognitive function decline, sensory structure deterioration, and musculoskeletal system weakening. This impacts postural control during static and dynamic activities like walking, increasing the fall risk among the elderly. Older adults with mild cognitive impairment (MCI) face an elevated fall risk and cognitive decline, magnifying the public health concern. OBJECTIVE: This study aimed to explore solutions by investigating the effects of a multi-component physical activity program on cognitive and motor functions in MCI patients. METHODS: Twenty-three participants were enrolled in the study and assigned into two groups: an intervention group (n = 13; age = 85.7±5.5 years) and a control group (n = 9; age = 85±6.7 years). The study spanned two months, with participants engaging in three 60-minute weekly physical exercise sessions. The intervention focused on improving proprioception, muscle strength, and balance. RESULTS: Results demonstrated significant enhancements in physical performance, fall risk reduction, and balance (p < 0.05). Various tests, including the timed up and go test, Unipedal Stance test, Tinetti test, Short Physical Performance Battery, and 6-minute walking test, indicated these improvements. Cognitive function was evaluated with the Mini-Mental State Examination, revealing non-significant progress (p > 0.05). Predictive models for outcomes were developed using linear regression analysis during the follow-up stage. CONCLUSIONS: This study underscores the effectiveness of a multi-component physical activity program encompassing balance, proprioception, and muscle-strengthening exercises as a non-pharmaceutical approach in improving balance skills and playing a key role in mitigating the risk of falls among old adults with MCI.
Keywords: Accidental Falls; Aged; Aged, 80 and over; Cognition; Cognitive Dysfunction; Exercise; Exercise Therapy; Humans; Physical Functional Performance; Postural Balance; Proprioception; Time and Motion Studies

Effects of Striatal Amyloidosis on the Dopaminergic System and Behavior: A Comparative Study in Male and Female 5XFAD Mice. - Lansdell, Theresa A; Xu, Hui; Galligan, James J; Dorrance, Anne M (J Alzheimers Dis, 2023)
BACKGROUND: Nearly two-thirds of patients diagnosed with Alzheimer's disease (AD) are female. In addition, female patients with AD have more significant cognitive impairment than males at the same disease stage. This disparity suggests there are sex differences in AD progression. While females appear to be more affected by AD, most published behavioral studies utilize male mice. In humans, there is an association between antecedent attention-deficit/hyperactivity disorder and increased risk of dementia. Functional connectivity studies indicate that dysfunctional cortico-striatal networks contribute to hyperactivity in attention deficit hyperactivity disorder. Higher plaque density in the striatum accurately predicts the presence of clinical AD pathology. In addition, there is a link between AD-related memory dysfunction and dysfunctional dopamine signaling. OBJECTIVE: With the need to consider sex as a biological variable, we investigated the influence of sex on striatal plaque burden, dopaminergic signaling, and behavior in prodromal 5XFAD mice. METHODS: Six-month-old male and female 5XFAD and C57BL/6J mice were evaluated for striatal amyloid plaque burden, locomotive behavior, and changes in dopaminergic machinery in the striatum. RESULTS: 5XFAD female mice had a higher striatal amyloid plaque burden than male 5XFAD mice. 5XFAD females, but not males, were hyperactive. Hyperactivity in female 5XFAD mice was associated with increased striatal plaque burden and changes in dopamine signaling in the dorsal striatum. CONCLUSION: Our results indicate that the progression of amyloidosis involves the striatum in females to a greater extent than in males. These studies have significant implications for using male-only cohorts in the study of AD progression.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Amyloidosis; Animals; Disease Models, Animal; Dopamine; Female; Humans; Male; Mice; Mice, Inbred C57BL; Mice, Transgenic; Plaque, Amyloid

The Efficacy and Safety of Physiotherapy in People with Dementia: A Systematic Review. - Saúde, Alexandra; Bouça-Machado, Raquel; Leitão, Mariana; Benedetti, Andrea; Ferreira, Joaquim J (J Alzheimers Dis, 2023)
BACKGROUND: Physiotherapy has become increasingly relevant as a new therapeutic intervention for dementia. However, it is unclear which interventions are the most suitable. OBJECTIVE: This study sought to summarize and critically appraise the evidence on physiotherapy interventions in dementia. METHODS: A systematic review conducted using CENTRAL, MEDLINE, and PEDro databases, from their inception to July 2022, identified all experimental studies of dementia that included physiotherapy interventions. RESULTS: Of 194 articles included, the most frequently used interventions were aerobic training (n = 82, 42%), strength training (n = 79, 41%), balance training (n = 48, 25%), and stretching (n = 22, 11%). These were associated with a positive effect on several motor and cognitive outcomes. A total number of 1,119 adverse events were reported. CONCLUSION: Physiotherapy has several motor and cognitive benefits in dementia. Future research should focus on establishing a physiotherapy prescription protocol for people with mild cognitive impairment and for each stage of dementia.
Keywords: Cognitive Dysfunction; Dementia; Humans; Physical Therapy Modalities; Resistance Training

Emotional Dysregulation in Mild Behavioral Impairment Is Associated with Reduced Cortical Thickness in the Right Supramarginal Gyrus. - Imai, Ayu; Matsuoka, Teruyuki; Narumoto, Jin (J Alzheimers Dis, 2023)
BACKGROUND: Mild behavioral impairment (MBI) has attracted attention as a possible precursor symptom of dementia, but its neural basis has not been fully investigated. OBJECTIVE: We aimed to investigate the relationship between MBI and surface area, cortical thickness, and volume in the temporal and parietal lobes, which are strongly associated with dementia and emotional disorders. METHODS: This retrospective study evaluated 123 participants: 90 with mild cognitive impairment (MCI), 13 with subjective cognitive decline (SCD), and 20 cognitively healthy (CH). Using analysis of covariance (ANCOVA) with sex, age, and MMSE score as covariates, cortical thickness, surface area, and volume in 10 regions were compared between groups with and without MBI. Groups with MBI emotional dysregulation were also compared with groups without MBI. RESULTS: ANCOVA revealed significantly smaller cortical thickness in the MBI group's right parahippocampal (p = 0.01) and supramarginal gyri (p = 0.002). After multiple comparison correction, only the right supramarginal gyrus was significantly smaller (p = 0.02). When considering only MBI emotional dysregulation, the right parahippocampal and supramarginal gyrus' cortical thicknesses were significantly smaller in this MBI group (p = 0.03, 0.01). However, multiple comparison correction identified no significant differences (p = 0.14, 0.11). CONCLUSION: Overall MBI and the emotional dysregulation domains were associated with reduced cortical thickness in the right parahippocampal and supramarginal gyri. Since neurodegeneration in the medial temporal and parietal lobe precedes early Alzheimer's disease (AD), MBI, particularly emotion dysregulation, may predict early AD below the diagnostic threshold.
Keywords: Alzheimer Disease; Attention; Cognitive Dysfunction; Dementia; Humans; Neuropsychological Tests; Parietal Lobe; Retrospective Studies

Evaluation of Blood-Based Plasma Biomarkers as Potential Markers of Amyloid Burden in Preclinical Alzheimer's Disease. - Winston, Charisse N; Langford, Oliver; Levin, Natalie; Raman, Rema; Yarasheski, Kevin; West, Tim; Abdel-Latif, Sara; Donohue, Michael; Nakamura, Akinori; Toba, Kenji; Masters, Colin L; Doecke, James; et al. (J Alzheimers Dis, 2023)
BACKGROUND: Participant eligibility for the A4 Study was determined by amyloid PET imaging. Given the disadvantages of amyloid PET imaging in accessibility and cost, blood-based biomarkers may serve as a sufficient biomarker and more cost-effective screening tool for patient enrollment into preclinical AD trials. OBJECTIVE: To determine if a blood-based screening test can adequately identify amyloid burden in participants screened into a preclinical AD trial. METHODS: In this cross-sectional study, 224 participants from the A4 Study received an amyloid PET scan (18Florbetapir) within 90 days of blood sample collection. Blood samples from all study participants were processed within 2 h after phlebotomy. Plasma amyloid measures were quantified by Shimazdu and C2 N Diagnostics using mass spectrometry-based platforms. A corresponding subset of blood samples (n = 100) was processed within 24 h after phlebotomy and analyzed by C2 N. RESULTS: Plasma Aβ42/Aβ40 demonstrated the highest association for Aβ accumulation in the brain with an AUC 0.76 (95%CI = 0.69, 0.82) at C2 N and 0.80 (95%CI = 0.75, 0.86) at Shimadzu. Blood samples processed to plasma within 2 h after phlebotomy provided a better prediction of amyloid PET status than blood samples processed within 24 h (AUC 0.80 versus 0.64; p < 0.001). Age, sex, and APOE ɛ4 carrier status did not the diagnostic performance of plasma Aβ42/Aβ40 to predict amyloid PET positivity in A4 Study participants. CONCLUSION: Plasma Aβ42/Aβ40 may serve as a potential biomarker for predicting elevated amyloid in the brain. Utilizing blood testing over PET imaging may improve screening efficiency into clinical trials.
Keywords: Alzheimer Disease; Amyloid; Amyloid beta-Peptides; Amyloidogenic Proteins; Biomarkers; Cross-Sectional Studies; Humans; Peptide Fragments; Positron-Emission Tomography

Impact of Hearing Aids on Progression of Cognitive Decline, Depression, and Quality of Life Among People with Cognitive Impairment and Dementia. - Atef, Roaa Zayed; Michalowsky, Bernhard; Raedke, Anika; Platen, Moritz; Mohr, Wiebke; Mühlichen, Franka; Thyrian, Jochen René; Hoffmann, Wolfgang (J Alzheimers Dis, 2023)
BACKGROUND: Hearing loss is common in people with dementia (PwD) and a modifiable risk factor for cognitive decline. Recent studies revealed that hearing loss could cause social isolation and depression, which is associated with health-related quality of life (HRQoL). However, there is a lack of knowledge about the impact of the utilization of hearing aids on these outcomes. OBJECTIVE: To assess whether hearing aids use might be positively associated with the progression of cognitive function, depression, and HRQoL among PwD. METHODS: We analyzed two-year follow-up data from 258 PwD (≥70 years, living at home). Cognitive decline was measured with Mini-Mental Status Examination (MMSE), depression using Geriatric Depression Scale (GDS), and HRQoL with Quality of Life in Alzheimer's Disease Scale (QoL-AD). The impact of hearing aid utilization on the progression of outcomes was assessed using multivariate regression models. RESULTS: 123 patients had hearing loss (47.7%), from which n = 54 (43.9%) used hearing aids. Patients with hearing loss were older and had a lower HRQoL than those without hearing loss. Use of hearing aids in patients with hearing loss was associated with a lower increase in depressive symptoms (b = -0.74, CI95 -1.48 --0.01, p = 0.047) over time as compared to those not using hearing aids. There was no effect on PwD's cognition, and the association with higher HRQoL was significant after one, but not consistently over two years. CONCLUSION: Early detection and intervention of presbycusis using hearing aids might improve mental health and HRQoL in dementia.
Keywords: Aged; Cognitive Dysfunction; Deafness; Dementia; Depression; Hearing Aids; Humans; Presbycusis; Quality of Life

Insights into the Pathophysiology of Alzheimer's Disease and Potential Therapeutic Targets: A Current Perspective. - Rajah Kumaran, Kesevan; Yunusa, Suleiman; Perimal, Enoch; Wahab, Habibah; Müller, Christian P; Hassan, Zurina (J Alzheimers Dis, 2023)
The aging population increases steadily because of a healthy lifestyle and medical advancements in healthcare. However, Alzheimer's disease (AD) is becoming more common and problematic among older adults. AD-related cases show an increasing trend annually, and the younger age population may also be at risk of developing this disorder. AD constitutes a primary form of dementia, an irreversible and progressive brain disorder that steadily damages cognitive functions and the ability to perform daily tasks. Later in life, AD leads to death as a result of the degeneration of specific brain areas. Currently, the cause of AD is poorly understood, and there is no safe and effective therapeutic agent to cure or slow down its progression. The condition is entirely preventable, and no study has yet demonstrated encouraging findings in terms of treatment. Identifying this disease's pathophysiology can help researchers develop safe and efficient therapeutic strategies to treat this ailment. This review outlines and discusses the pathophysiology that resulted in the development of AD including amyloid-β plaques, tau neurofibrillary tangles, neuroinflammation, oxidative stress, cholinergic dysfunction, glutamate excitotoxicity, and changes in neurotrophins level may sound better based on the literature search from Scopus, PubMed, ScienceDirect, and Google Scholar. Potential therapeutic strategies are discussed to provide more insights into AD mechanisms by developing some possible pharmacological agents for its treatment.
Keywords: Aged; Aging; Alzheimer Disease; Amyloid beta-Peptides; Humans; Neurofibrillary Tangles; Oxidative Stress; Plaque, Amyloid; tau Proteins

JAD: A Forum for Philosophy in Science. - Daly, Timothy (J Alzheimers Dis, 2023)
The Journal of Alzheimer's Disease (JAD) is already an established forum for cutting-edge science as well as ethical reflection. But I argue that beyond science and ethics, JAD is also a forum for philosophy in science, and that interdisciplinary researchers asking innovative questions about AD should publish their reflections and findings in JAD.
Keywords: Alzheimer Disease; Humans; Philosophy

Linking Air Pollution Exposure to Blood-Based Metabolic Features in a Community-Based Aging Cohort with and without Dementia. - Kalia, Vrinda; Kulick, Erin R; Vardarajan, Badri; Gu, Yian; Manly, Jennifer J; Elkind, Mitchell S V; Kaufman, Joel D; Jones, Dean P; Baccarelli, Andrea A; Mayeux, Richard; Kioumourtzoglou, Marianthi-Anna; Miller, Gary W (J Alzheimers Dis, 2023)
BACKGROUND: Long-term exposure to air pollution has been associated with changes in levels of metabolites measured in the peripheral blood. However, most research has been conducted in ethnically homogenous, young or middle-aged populations. OBJECTIVE: To study the relationship between the plasma metabolome and long-term exposure to three air pollutants: particulate matter (PM) less than 2.5μm in aerodynamic diameter (PM2.5), PM less than 10μm in aerodynamic diameter (PM10), and nitrogen dioxide (NO2) in an ethnically diverse, older population. METHODS: Plasma metabolomic profiles of 107 participants of the Washington Heights and Inwood Community Aging Project in New York City, collected from 1995-2015, including non-Hispanic white, Caribbean Hispanic, and non-Hispanic Black older adults were used. We estimated the association between each metabolic feature and predicted annual mean exposure to the air pollutants using three approaches: 1) A metabolome wide association study framework; 2) Feature selection using elastic net regression; and 3) A multivariate approach using partial-least squares discriminant analysis. RESULTS: 79 features associated with exposure to PM2.5 but none associated with PM10 or NO2. PM2.5 exposure was associated with altered amino acid metabolism, energy production, and oxidative stress response, pathways also associated with Alzheimer's disease. Three metabolites were associated with PM2.5 exposure through all three approaches: cysteinylglycine disulfide, a diglyceride, and a dicarboxylic acid. The relationship between several features and PM2.5 exposure was modified by diet and metabolic diseases. CONCLUSIONS: These relationships uncover the mechanisms through which PM2.5 exposure can lead to altered metabolic outcomes in an older population.
Keywords: Aged; Aging; Air Pollutants; Air Pollution; Dementia; Environmental Exposure; Humans; Nitrogen Dioxide; Particulate Matter

Longitudinal White and Gray Matter Response to Precision Medicine-Guided Intervention for Alzheimer's Disease. - Chwa, Won Jong; Raji, Cyrus A; Toups, Kat; Hathaway, Ann; Gordon, Deborah; Chung, Henrianna; Boyd, Alan; Hill, Benjamin D; Hausman-Cohen, Sharon; Attarha, Mouna; Jarrett, Michael; Bredesen, Dale E (J Alzheimers Dis, 2023)
BACKGROUND: Alzheimer's disease (AD) is a debilitating condition that is widely known to adversely affect gray matter (GM) and white matter (WM) tracts within the brain. Recently, precision medicine has shown promise in alleviating the clinical and gross morphological trajectories of patients with AD. However, regional morphological changes have not yet been adequately characterized. OBJECTIVE: Investigate regional morphological responses to a precision medicine-guided intervention with regards to white and gray matter in AD and mild cognitive impairment (MCI). METHODS: Clinical and neuroimaging data were compiled over a 9-month period from 25 individuals who were diagnosed with AD or MCI receiving individualized treatment plans. Structural T1-weighted MRI scans underwent segmentation and volumetric quantifications via Neuroreader. Longitudinal changes were calculated via annualized percent change of WM or GM ratios. RESULTS: Montreal Cognitive Assessment scores (p < 0.001) and various domains of the Computerized Neurocognitive Screening Vital Signs significantly improved from baseline to 9-month follow-up. There was regional variability in WM and GM atrophy or hypertrophy, but none of these observed changes were statistically significant after correction for multiple comparisons.
Keywords: Alzheimer Disease; Atrophy; Brain; Cognitive Dysfunction; Gray Matter; Humans; Magnetic Resonance Imaging; Precision Medicine; White Matter

Neuroprotective Effect of Phloretin in Rotenone-Induced Mice Model of Parkinson's Disease: Modulating mTOR-NRF2-p62 Mediated Autophagy-Oxidative Stress Crosstalk. - Shirgadwar, Shubhendu M; Kumar, Rahul; Preeti, Kumari; Khatri, Dharmendra Kumar; Singh, Shashi Bala (J Alzheimers Dis, 2023)
BACKGROUND: Parkinson's disease (PD) is an age-related progressive multifactorial, neurodegenerative disease. The autophagy and Keap1-Nrf2 axis system are both implicated in the oxidative-stress response, metabolic stress, and innate immunity, and their dysregulation is associated with pathogenic processes in PD. Phloretin (PLT) is a phenolic compound reported possessing anti-inflammatory and antioxidant activities. OBJECTIVE: To evaluate the neuroprotective potential of PLT in PD via modulating the autophagy-antioxidant axisMethods:The neuroprotective effect of PLT was evaluated in vitro using rotenone (ROT) exposed SH-SY5Y cell line and in vivo using ROT administered C57BL/6 mice. Mice were administered with PLT (50 and 100 mg/kg, p.o.) concomitantly with ROT (1 mg/kg, i.p) for 3 weeks. Locomotive activity and anxiety behaviors were assessed using rotarod and open field tests respectively. Further apoptosis (Cytochrome-C, Bax), α-Synuclein (α-SYN), tyrosine hydroxylase (TH), antioxidant proteins (nuclear factor erythroid 2-related factor 2 (NRF2), heme oxygenase-1 (HO-1) and autophagic (mTOR, Atg5,7, p62, Beclin,LC3B-I/II) protein activity were evaluated both in in vitro and in vivo. RESULTS: PLT improved locomotive activity and anxiety-like behavior in mice. Further PLT diminished apoptotic cell death, α-SYN expression and improved the expression of TH, antioxidant, and autophagic regulating protein. CONCLUSION: Taken together, present data deciphers that the PLT effectively improves motor and non-motor symptoms via modulating the mTOR/NRF2/p62 pathway-mediated feedback loop. Hence, PLT could emerge as a prospective disease-modifying drug for PD management.
Keywords: Animals; Antioxidants; Autophagy; Humans; Kelch-Like ECH-Associated Protein 1; Mice; Mice, Inbred C57BL; Neuroblastoma; Neurodegenerative Diseases; Neuroprotective Agents; NF-E2-Related Factor 2; Oxidative Stress; Parkinson Disease; Phloretin; Prospective Studies; Rotenone; TOR Serine-Threonine Kinases

Neuroprotective Properties of Eudesmin on a Cellular Model of Amyloid-β Peptide Toxicity. - Castillo, Carolina; Bravo-Arrepol, Gastón; Wendt, Aline; Saez-Orellana, Francisco; Millar, Camila; Burgos, Carlos F; Gavilán, Javiera; Pacheco, Carla; Ahumada-Rudolph, Ramón; Napiórkowska, Mariola; Pérez, Claudia; Becerra, José; et al. (J Alzheimers Dis, 2023)
BACKGROUND: Alzheimer's disease (AD) is a neurodegenerative disorder characterized by progressive cognitive impairment and memory loss. One of the hallmarks in AD is amyloid-β peptide (Aβ) accumulation, where the soluble oligomers of Aβ (AβOs) are the most toxic species, deteriorating the synaptic function, membrane integrity, and neuronal structures, which ultimately lead to apoptosis. Currently, there are no drugs to arrest AD progression, and current scientific efforts are focused on searching for novel leads to control this disease. Lignans are compounds extracted from conifers and have several medicinal properties. Eudesmin (Eu) is an extractable lignan from the wood of Araucaria araucana, a native tree from Chile. This metabolite has shown a range of biological properties, including the ability to control inflammation and antibacterial effects. OBJECTIVE: In this study, the neuroprotective abilities of Eu on synaptic failure induced by AβOs were analyzed. METHODS: Using neuronal models, PC12 cells, and in silico simulations we evaluated the neuroprotective effect of Eu (30 nM) against the toxicity induced by AβOs. RESULTS: In primary cultures from mouse hippocampus, Eu preserved the synaptic structure against AβOs toxicity, maintaining stable levels of the presynaptic protein SV2 at the same concentration. Eu also averted synapsis failure from the AβOs toxicity by sustaining the frequencies of cytosolic Ca2+ transients. Finally, we found that Eu (30 nM) interacts with the Aβ aggregation process inducing a decrease in AβOs toxicity, suggesting an alternative mechanism to explain the neuroprotective activity of Eu. CONCLUSION: We believe that Eu represents a novel lead that reduces the Aβ toxicity, opening new research venues for lignans as neuroprotective agents.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; Lignans; Mice; Neuroprotective Agents; PC12 Cells; Rats

Observed Improvement in Cognition During a Personalized Lifestyle Intervention in People with Cognitive Decline. - Sandison, Heather; Callan, Nini G L; Rao, Rammohan V; Phipps, John; Bradley, Ryan (J Alzheimers Dis, 2023)
BACKGROUND: Alzheimer's disease (AD) is a chronic condition marked by progressive objective cognitive impairment (OCI). No monotherapy has substantially altered disease progression, suggesting the disease is multifactorial and may require a multimodal therapeutic approach. OBJECTIVE: We sought to determine if cognitive function in a sample with OCI would change in response to a multimodal, individualized care plan based on potential contributors to cognitive decline (e.g., nutritional status, infection, etc.). METHODS: Participants (n = 34) were recruited from the San Diego, CA area. The multimodal intervention included lifestyle changes (i.e., movement, diet, and stress management), nutraceutical support, and medications. It was delivered pragmatically over four clinical visits, and outcome measures were gathered at four study visits, occurring at baseline, one, three, and six months (primary endpoint). Study participants received weekly phone calls for nutrition support throughout study participation. Outcome measures included the Cambridge Brain Sciences (CBS) battery, and the Montreal Cognitive Assessment (MoCA). RESULTS: At 6 months, mean MoCA scores improved from 19.6±3.1 to 21.7±6.2 (p = 0.013). Significant improvement was observed in mean scores of the CBS memory domain [25.2 (SD 23.3) to 35.8 (SD 26.9); p < 0.01] and CBS overall composite cognition score [24.5 (SD 16.1) to 29.7 (SD 20.5); p = 0.02]. All CBS domains improved. CONCLUSION: Multiple measures of cognitive function improved after six months of intervention. Our results support the feasibility and impact of a multimodal, individualized treatment approach to OCI, warranting further research.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; California; Cognition; Cognitive Dysfunction; Diet, Healthy; Dietary Supplements; Disease Progression; Exercise; Feasibility Studies; Female; Healthy Lifestyle; Humans; Infections; Male; Memory; Middle Aged; Nutritional Status; Pragmatic Clinical Trials as Topic; Reproducibility of Results; Stress, Psychological; Time Factors; Treatment Outcome; Verbal Behavior

Pathological and Therapeutic Advances in Parkinson's Disease: Mitochondria in the Interplay. - Naren, Padmashri; Cholkar, Anjali; Kamble, Suchita; Khan, Sabiya Samim; Srivastava, Saurabh; Madan, Jitender; Mehra, Neelesh; Tiwari, Vinod; Singh, Shashi Bala; Khatri, Dharmendra Kumar (J Alzheimers Dis, 2023)
Parkinson's disease (PD) is the second most common neurodegenerative illness majorly affecting the population between the ages of 55 to 65 years. Progressive dopaminergic neuronal loss and the collective assemblage of misfolded alpha-synuclein in the substantia nigra, remain notable neuro-pathological hallmarks of the disease. Multitudes of mechanistic pathways have been proposed in attempts to unravel the pathogenesis of PD but still, it remains elusive. The convergence of PD pathology is found in organelle dysfunction where mitochondria remain a major contributor. Mitochondrial processes like bioenergetics, mitochondrial dynamics, and mitophagy are under strict regulation by the mitochondrial genome and nuclear genome. These processes aggravate neurodegenerative activities upon alteration through neuroinflammation, oxidative damage, apoptosis, and proteostatic stress. Therefore, the mitochondria have grabbed a central position in the patho-mechanistic exploration of neurodegenerative diseases like PD. The management of PD remains a challenge to physicians to date, due to the variable therapeutic response of patients and the limitation of conventional chemical agents which only offer symptomatic relief with minimal to no disease-modifying effect. This review describes the patho-mechanistic pathways involved in PD not only limited to protein dyshomeostasis and oxidative stress, but explicit attention has been drawn to exploring mechanisms like organelle dysfunction, primarily mitochondria and mitochondrial genome influence, while delineating the newer exploratory targets such as GBA1, GLP, LRRK2, and miRNAs and therapeutic agents targeting them.
Keywords: Aged; alpha-Synuclein; Humans; Mitochondria; Oxidative Stress; Parkinson Disease

The PI3K/AKT Signaling Pathway and Caspase-3 in Alzheimer's Disease: Which One Is the Beginner? - Khezri, Mohammad Rafi; Ghasemnejad-Berenji, Morteza; Moloodsouri, Donya (J Alzheimers Dis, 2023)
One of the main players in apoptosis during Alzheimer's disease progression are different members of caspase family of proteases. The most well-known member of this family is caspase-3, in which alterations of its levels have been detected in samples from Alzheimer's disease patients. There are numerous intracellular factors involved in regulation of cellular apoptosis through regulation of caspase-3 activity, the most important of which is the PI3K/AKT signaling pathway. This commentary tries to highlight the probable relations between PI3K/AKT signaling pathway and caspase-3 in Alzheimer's disease.
Keywords: Alzheimer Disease; Apoptosis; Caspase 3; Humans; Phosphatidylinositol 3-Kinases; Proto-Oncogene Proteins c-akt; Signal Transduction

Plasma Glial Fibrillary Acidic Protein Is Associated with 18F-SMBT-1 PET: Two Putative Astrocyte Reactivity Biomarkers for Alzheimer's Disease. - Chatterjee, Pratishtha; Doré, Vincent; Pedrini, Steve; Krishnadas, Natasha; Thota, Rohith; Bourgeat, Pierrick; Ikonomovic, Milos D; Rainey-Smith, Stephanie R; Burnham, Samantha C; Fowler, Christopher; Taddei, Kevin; Mulligan, Rachel; et al. (J Alzheimers Dis, 2023)
BACKGROUND: Astrocyte reactivity is an early event along the Alzheimer's disease (AD) continuum. Plasma glial fibrillary acidic protein (GFAP), posited to reflect astrocyte reactivity, is elevated across the AD continuum from preclinical to dementia stages. Monoamine oxidase-B (MAO-B) is also elevated in reactive astrocytes observed using 18F-SMBT-1 PET in AD. OBJECTIVE: The objective of this study was to evaluate the association between the abovementioned astrocyte reactivity biomarkers. METHODS: Plasma GFAP and Aβ were measured using the Simoa® platform in participants who underwent brain 18F-SMBT-1 and Aβ-PET imaging, comprising 54 healthy control (13 Aβ-PET+ and 41 Aβ-PET-), 11 mild cognitively impaired (3 Aβ-PET+ and 8 Aβ-PET-) and 6 probable AD (5 Aβ-PET+ and 1 Aβ-PET-) individuals. Linear regressions were used to assess associations of interest. RESULTS: Plasma GFAP was associated with 18F-SMBT-1 signal in brain regions prone to early Aβ deposition in AD, such as the supramarginal gyrus (SG), posterior cingulate (PC), lateral temporal (LT) and lateral occipital cortex (LO). After adjusting for age, sex, APOE ɛ4 genotype, and soluble Aβ (plasma Aβ42/40 ratio), plasma GFAP was associated with 18F-SMBT-1 signal in the SG, PC, LT, LO, and superior parietal cortex (SP). On adjusting for age, sex, APOE ɛ4 genotype and insoluble Aβ (Aβ-PET), plasma GFAP was associated with 18F-SMBT-1 signal in the SG. CONCLUSION: There is an association between plasma GFAP and regional 18F-SMBT-1 PET, and this association appears to be dependent on brain Aβ load.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Apolipoproteins E; Astrocytes; Biomarkers; Brain; Cognitive Dysfunction; Glial Fibrillary Acidic Protein; Humans; Positron-Emission Tomography; tau Proteins

Plasma Soluble ST2 Levels Are Higher in Neurodegenerative Disorders and Associated with Poorer Cognition. - Tan, Yi Jayne; Siow, Isabel; Saffari, Seyed Ehsan; Ting, Simon K S; Li, Zeng; Kandiah, Nagaendran; Tan, Louis C S; Tan, Eng King; Ng, Adeline S L (J Alzheimers Dis, 2023)
BACKGROUND: Suppressor of tumorgenicity 2 (ST2) is highly expressed in brain tissue and is a receptor for interleukin 33 (IL-33). ST2 exists in two forms, a transmembrane receptor (ST2L) and a soluble decoy receptor (sST2). IL-33 binds to ST2L, triggering downstream signaling pathways involved in amyloid plaque clearance. Conversely, sST2 binds competitively to IL-33, attenuating its neuroprotective effects. High sST2 levels have been reported in mild cognitive impairment (MCI) and Alzheimer's disease (AD), suggesting that the IL-33/ST2 signaling pathway may be implicated in neurodegenerative diseases. OBJECTIVE: To investigate plasma sST2 levels in controls and patients with MCI, AD, frontotemporal dementia (FTD), and Parkinson's disease (PD). METHODS: Plasma sST2 levels were measured using ELISA in 397 subjects (91 HC, 46 MCI, 38 AD, 28 FTD, and 194 PD). Cerebrospinal fluid (CSF) levels of sST2 were measured in 22 subjects. Relationship between sST2 and clinical outcomes were analyzed. RESULTS: Plasma sST2 levels were increased across all disease groups compared to controls, with highest levels seen in FTD followed by AD and PD. Dementia patients with higher sST2 had lower cross-sectional cognitive scores in Frontal Assessment Battery and Digit Span Backward. At baseline, PD-MCI patients had higher sST2, associated with worse attention. In the longitudinal PD cohort, higher sST2 significantly associated with decline in global cognition and visuospatial domains. Plasma sST2 levels correlated with CSF sST2 levels. CONCLUSION: Plasma sST2 is raised across neurodegenerative diseases and is associated with poorer cognition. Higher baseline sST2 is a potential biomarker of disease severity in neurodegeneration.
Keywords: Alzheimer Disease; Biomarkers; Cognition; Cross-Sectional Studies; Frontotemporal Dementia; Humans; Interleukin-1 Receptor-Like 1 Protein; Interleukin-33; Parkinson Disease

PM2.5 and Dementia in a Low Exposure Setting: The Influence of Odor Identification Ability and APOE. - Andersson, John; Sundström, Anna; Nordin, Maria; Segersson, David; Forsberg, Bertil; Adolfsson, Rolf; Oudin, Anna (J Alzheimers Dis, 2023)
BACKGROUND: Growing evidence show that long term exposure to air pollution increases the risk of dementia. OBJECTIVE: The aim of this study was to investigate associations between PM2.5 exposure and dementia in a low exposure area, and to investigate the role of olfaction and the APOE ɛ4 allele in these associations. METHODS: Data were drawn from the Betula project, a longitudinal study on aging, memory, and dementia in Sweden. Odor identification ability was assessed using the Scandinavian Odor Identification Test (SOIT). Annual mean PM2.5 concentrations were obtained from a dispersion-model and matched at the participants' residential address. Proportional hazard regression was used to calculate hazard ratios. RESULTS: Of 1,846 participants, 348 developed dementia during the 21-year follow-up period. The average annual mean PM2.5 exposure at baseline was 6.77μg/m3, which is 1.77μg/m3 above the WHO definition of clean air. In a fully adjusted model (adjusted for age, sex, APOE, SOIT, cardiovascular diseases and risk factors, and education) each 1μg/m3 difference in annual mean PM2.5-concentration was associated with a hazard ratio of 1.23 for dementia (95% CI: 1.01-1.50). Analyses stratified by APOE status (ɛ4 carriers versus non-carriers), and odor identification ability (high versus low), showed associations only for ɛ4 carriers, and for low performance on odor identification ability. CONCLUSION: PM2.5 was associated with an increased risk of dementia in this low pollution setting. The associations between PM2.5 and dementia seemed stronger in APOE carriers and those with below average odor identification ability.
Keywords: Air Pollutants; Air Pollution; Apolipoproteins E; Cohort Studies; Dementia; Environmental Exposure; Humans; Longitudinal Studies; Odorants; Particulate Matter

Precision Medicine Approach to Alzheimer's Disease: Rationale and Implications. - Bredesen, Dale E; Toups, Kat; Hathaway, Ann; Gordon, Deborah; Chung, Henrianna; Raji, Cyrus; Boyd, Alan; Hill, Benjamin D; Hausman-Cohen, Sharon; Attarha, Mouna; Chwa, Won Jong; Kurakin, Alexei; et al. (J Alzheimers Dis, 2023)
The neurodegenerative disease field has enjoyed extremely limited success in the development of effective therapeutics. One potential reason is the lack of disease models that yield accurate predictions and optimal therapeutic targets. Standard clinical trials have pre-determined a single treatment modality, which may be unrelated to the primary drivers of neurodegeneration. Recent proof-of-concept clinical trials using a precision medicine approach suggest a new model of Alzheimer's disease (AD) as a chronic innate encephalitis that creates a network insufficiency. Identifying and addressing the multiple potential contributors to cognitive decline for each patient may represent a more effective strategy. Here we review the rationale for a precision medicine approach in prevention and treatment of cognitive decline associated with AD. Results and implications from recent proof-of-concept clinical trials are presented. Randomized controlled trials, with much larger patient numbers, are likely to be significant to establishing precision medicine protocols as a standard of care for prevention and treatment of cognitive decline. Furthermore, combining this approach with the pharmaceutical approach offers the potential for enhanced outcomes. However, incorporating precision medicine approaches into everyday evaluation and care, as well as future clinical trials, would require fundamental changes in trial design, IRB considerations, funding considerations, laboratory evaluation, personalized treatment plans, treatment teams, and ultimately in reimbursement guidelines. Nonetheless, precision medicine approaches to AD, based on a novel model of AD pathophysiology, offer promise that has not been realized to date with monotherapeutic approaches.
Keywords: Alzheimer Disease; Cognitive Dysfunction; Humans; Neurodegenerative Diseases; Precision Medicine

Safety, Feasibility, and Potential Clinical Efficacy of 40 Hz Invisible Spectral Flicker versus Placebo in Patients with Mild-to-Moderate Alzheimer's Disease: A Randomized, Placebo-Controlled, Double-Blinded, Pilot Study. - Agger, Mikkel Pejstrup; Danielsen, Else Rubæk; Carstensen, Marcus Schultz; Nguyen, N Mai; Horning, Maibritt; Henney, Mark Alexander; Jensen, Christopher Boe Ravn; Baandrup, Anders Ohlhues; Kjær, Troels Wesenberg; Madsen, Kristoffer Hougaard; Miskowiak, Kamilla; Petersen, Paul Michael; et al. (J Alzheimers Dis, 2023)
BACKGROUND: Recent studies suggested induction of 40 Hz neural activity as a potential treatment for Alzheimer's disease (AD). However, prolonged exposure to flickering light raises adherence and safety concerns, encouraging investigation of tolerable light stimulation protocols. OBJECTIVE: To investigate the safety, feasibility, and exploratory measures of efficacy. METHODS: This two-stage randomized placebo-controlled double-blinded clinical trial, recruited first cognitive healthy participants (n = 3/2 active/placebo), and subsequently patients with mild-to-moderate AD (n = 5/6, active/placebo). Participants were randomized 1:1 to receive either active intervention with 40 Hz Invisible Spectral Flicker (ISF) or placebo intervention with color and intensity matched non-flickering white light. RESULTS: Few and mild adverse events were observed. Adherence was above 86.1% of intended treatment days, with participants remaining in front of the device for >51.3 min (60 max) and directed gaze >34.9 min. Secondary outcomes of cognition indicate a tendency towards improvement in the active group compared to placebo (mean: -2.6/1.5, SD: 6.58/6.53, active/placebo) at week 6. Changes in hippocampal and ventricular volume also showed no tendency of improvement in the active group at week 6 compared to placebo. At week 12, a potential delayed effect of the intervention was seen on the volume of the hippocampus in the active group compared to placebo (mean: 0.34/-2.03, SD: 3.26/1.18, active/placebo), and the ventricular volume active group (mean: -0.36/2.50, SD: 1.89/2.05, active/placebo), compared to placebo. CONCLUSION: Treatment with 40 Hz ISF offers no significant safety or adherence concerns. Potential impact on secondary outcomes must be tested in larger scale clinical trials.
Keywords: Alzheimer Disease; Cognition; Double-Blind Method; Feasibility Studies; Humans; Pilot Projects; Treatment Outcome

Serotonin Degeneration and Amyloid-β Deposition in Mild Cognitive Impairment: Relationship to Cognitive Deficits. - Smith, Gwenn S; Kuwabara, Hiroto; Yan, Haijuan; Nassery, Najlla; Yoon, Mark; Kamath, Vidya; Kraut, Michael; Gould, Neda F; Savonenko, Alena; Coughlin, Jennifer M; Lodge, Martin; Pomper, Martin G; et al. (J Alzheimers Dis, 2023)
BACKGROUND: Neuropathological and neuroimaging studies have demonstrated degeneration of the serotonin system in Alzheimer's disease (AD). Neuroimaging studies have extended these observations to the preclinical stages of AD, mild cognitive impairment (MCI). Serotonin degeneration has been observed also in transgenic amyloid mouse models, prior to widespread cortical distribution of amyloid-β (Aβ). OBJECTIVE: The present study evaluated the regional distribution of the serotonin transporter (5-HTT) and of Aβ in individuals with MCI and healthy older controls, as well as the contribution of 5-HTT and Aβ to cognitive deficits. METHODS: Forty-nine MCI participants and 45 healthy older controls underwent positron emission tomography (PET) imaging of 5-HTT and Aβ, structural magnetic resonance imaging and neuropsychological assessments. RESULTS: Lower cortical, striatal, and limbic 5-HTT and higher cortical Aβ was observed in MCIs relative to healthy controls. Lower 5-HTT, mainly in limbic regions, was correlated with greater deficits in auditory-verbal and visual-spatial memory and semantic, not phonemic fluency. Higher cortical A β was associated with greater deficits in auditory-verbal and visual-spatial memory and in semantic, not phonemic fluency. When modeling the association between cognition, gray matter volumes and Aβ, inclusion of 5-HTT in limbic and in select cortical regions significantly improved model fit for auditory-verbal and visual-spatial memory and semantic, but not phonemic fluency. CONCLUSIONS: These results support the role of serotonin degeneration in the memory and semantic fluency deficits observed in MCI.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; Cognition; Cognition Disorders; Cognitive Dysfunction; Humans; Mice; Positron-Emission Tomography; Serotonin

Understanding the Involvement of microRNAs in Mitochondrial Dysfunction and Their Role as Potential Biomarkers and Therapeutic Targets in Parkinson's Disease. - Tryphena, Kamatham Pushpa; Anuradha, Urati; Kumar, Rohith; Rajan, Shruti; Srivastava, Saurabh; Singh, Shashi Bala; Khatri, Dharmendra Kumar (J Alzheimers Dis, 2023)
Parkinson's disease (PD) is the second most common neurodegenerative disease, affecting the elderly worldwide and causing significant movement impairments. The goal of PD treatment is to restore dopamine levels in the striatum and regulate movement symptoms. The lack of specific biomarkers for early diagnosis, as well as medication aimed at addressing the pathogenic mechanisms to decelerate the progression of dopaminergic neurodegeneration, are key roadblocks in the management of PD. Various pathogenic processes have been identified to be involved in the progression of PD, with mitochondrial dysfunction being a major contributor to the disease's pathogenesis. The regulation of mitochondrial functions is influenced by a variety of factors, including epigenetics. microRNAs (miRNAs) are epigenetic modulators involved in the regulation of gene expression and regulate a variety of proteins that essential for proper mitochondrial functioning. They are found to be dysregulated in PD, as evidenced by biological samples from PD patients and in vitro and in vivo research. In this article, we attempt to provide an overview of several miRNAs linked to mitochondrial dysfunction and their potential as diagnostic biomarkers and therapeutic targets in PD.
Keywords: Aged; Biomarkers; Humans; MicroRNAs; Mitochondria; Neurodegenerative Diseases; Parkinson Disease

Vacuolar Protein-Sorting Proteins Are Reduced Even Before Cognitive Decline in a Mouse Model of Alzheimer's Disease. - Shinagawa, Hijiri; Ohuchi, Kazuki; Goto, Yuya; Hashimoto, Kohei; Kijima, Hideki; Maekawa, Shogo; Kurita, Hisaka; Inden, Masatoshi (J Alzheimers Dis, 2023)
Currently, interventions from the preclinical stage are considered necessary for the treatment of Alzheimer's disease (AD). Previous studies have reported that vacuolar protein-sorting protein (VPS), a retromer construct, is involved in the pathogenic mechanisms of AD and Parkinson's disease. This study evaluated VPS26, VPS29, and VPS35 before and after the onset of cognitive decline in an App knock-in mouse model of AD that more closely resembles the human pathology than previous AD models. The results showed that the expression of VPS26 and VPS35 decreased before the onset of cognitive decline, suggesting the possibility of anti-amyloid-β disease-modifying treatment targeting these proteins.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; Cognitive Dysfunction; Humans; Mice; Protein Transport; Vesicular Transport Proteins

Analysis and Identification Genetic Effect of SARS-CoV-2 Infections to Alzheimer's Disease Patients by Integrated Bioinformatics. - Wang, Fang; Xu, Jia; Xu, Shu-Jun; Guo, Jie-Jie; Wang, Feiming; Wang, Qin-Wen (J Alzheimers Dis, 2022)
BACKGROUND: COVID-19 pandemic is a global crisis which results in millions of deaths and causes long-term neurological sequelae, such as Alzheimer's disease (AD). OBJECTIVE: We aimed to explore the interaction between COVID-19 and AD by integrating bioinformatics to find the biomarkers which lead to AD occurrence and development with COVID-19 and provide early intervention. METHODS: The differential expressed genes (DEGs) were found by GSE147507 and GSE132903, respectively. The common genes between COVID-19 and AD were identified. Gene Ontology (GO), Kyoto Encyclopedia of Genes and Genomes (KEGG), and protein-protein interactions (PPI) network analysis were carried out. Hub genes were found by cytoscape. A multivariate logistic regression model was constructed. NetworkAnalyst was used for the analysis of TF-gene interactions, TF-miRNA coregulatory network, and Protein-chemical Interactions. RESULTS: Forty common DEGs for AD and COVID-19 were found. GO and KEGG analysis indicated that the DEGs were enriched in the calcium signal pathway and other pathways. A PPI network was constructed, and 5 hub genes were identified (ITPR1, ITPR3, ITPKB, RAPGEF3, MFGE8). Four hub genes (ITPR1, ITPR3, ITPKB, RAPGEF3) which were considered as important factors in the development of AD that were affected by COVID-19 were shown by nomogram. Utilizing NetworkAnalyst, the interaction network of 4 hub genes and TF, miRNA, common AD risk genes, and known compounds is displayed, respectively. CONCLUSION: COVID-19 patients are at high risk of developing AD. Vaccination is required. Four hub genes can be considered as biomarkers for prediction and treatment of AD development caused by COVID-19. Compounds with neuroprotective effects can be used as adjuvant therapy for COVID-19 patients.
Keywords: Alzheimer Disease; Computational Biology; COVID-19; Databases, Genetic; Gene Expression Profiling; Humans; Protein Interaction Maps; SARS-CoV-2

Antihypertensive Medication Class and the Risk of Dementia and Cognitive Decline in Older Adults: A Secondary Analysis of the Prospective HELIAD Cohort. - Liampas, Ioannis; Hatzimanolis, Alex; Siokas, Vasileios; Yannakoulia, Mary; Kosmidis, Mary H; Sakka, Paraskevi; Hadjigeorgiou, Georgios M; Scarmeas, Nikolaos; Dardiotis, Efthimios (J Alzheimers Dis, 2022)
BACKGROUND: It is unclear whether the main antihypertensive medication classes (diuretics, calcium channel blockers, beta-blockers, angiotensin converting enzyme inhibitors, and angiotensin receptor blockers (ARBs)) are associated with different risks of cognitive decline. Published evidence is conflicting and stems mainly from observational studies. OBJECTIVE: To investigate the differential effects of antihypertensives on the risks of developing dementia and cognitive decline, with a specific focus on the vascular component of the mechanisms underlying these interactions. METHODS: Older adults with a history of hypertension and without dementia were drawn from the population-based HELIAD cohort. Age-, gender-, education-, and antihypertensive medication- (five dichotomous exposures) adjusted Cox proportional-hazards models and generalized estimating equations were performed to appraise the associations of baseline antihypertensive therapy with dementia incidence and cognitive decline (quantified using a comprehensive neuropsychological battery). Analyses were subsequently adjusted for clinical vascular risk (dyslipidemia, diabetes mellitus, smoking, cardiovascular, and cerebrovascular history) and genetic susceptibility to stroke (using polygenic risk scores generated according to the MEGASTROKE consortium GWAS findings). RESULTS: A total of 776 predominantly female participants (73.61±4.94 years) with hypertension and a mean follow-up of 3.02±0.82 years were analyzed. Baseline treatment was not associated with the risk of incident dementia. ARB users experienced a slower yearly global cognitive [2.5% of a SD, 95% CI = (0.1, 4.9)] and language [4.4% of a SD, 95% CI = (1.4, 7.4)] decline compared to non-users. The fully adjusted model reproduced similar associations for both global cognitive [β= 0.027, 95% CI =  (-0.003, 0.057)], and language decline [β= 0.063, 95% CI = (0.023, 0.104)]. CONCLUSION: ARBs may be superior to other antihypertensive agents in the preservation of cognition, an association probably mediated by vascular-independent mechanisms.
Keywords: Aged; Angiotensin Receptor Antagonists; Angiotensin-Converting Enzyme Inhibitors; Antihypertensive Agents; Calcium Channel Blockers; Cognitive Dysfunction; Dementia; Diuretics; Female; Humans; Hypertension; Male; Prospective Studies

Association of Alzheimer's Disease with COVID-19 Susceptibility and Severe Complications: A Nationwide Cohort Study. - Chung, Seok Jong; Chang, Yoonkyung; Jeon, Jimin; Shin, Jae Il; Song, Tae-Jin; Kim, Jinkwon (J Alzheimers Dis, 2022)
BACKGROUND: Identification of patients at high susceptibility and high risk of developing serious complications related to coronavirus disease 2019 (COVID-19) infection is clinically important in the face of the COVID-19 pandemic. OBJECTIVE: To investigate whether patients with Alzheimer's disease (AD) are more susceptible to COVID-19 infection and whether they have a higher risk of developing serious complications. METHODS: We retrospectively reviewed the Korean nationwide population-based COVID-19 dataset for participants who underwent real-time reverse transcription polymerase chain reaction assays for COVID-19 between January 1 and June 4, 2020. A 1 : 3 ratio propensity score matching and binary logistic regression analysis were performed to investigate the association between AD and the susceptibility or severe complications (i.e., mechanical ventilation, intensive care unit admission, or death) of COVID-19. RESULTS: Among 195,643 study participants, 5,725 participants had AD and 7,334 participants were diagnosed with COVID-19. The prevalence of participants testing positive for COVID-19 did not differ according to the presence of AD (p = 0.234). Meanwhile, AD was associated with an increased risk of severe COVID-19 complications (OR 2.25 [95% CI 1.54-3.28]). Secondary outcome analyses showed that AD patients had an increased risk for mortality (OR 3.09 [95% CI 2.00-4.78]) but were less likely to receive mechanical ventilation (OR 0.42 [95% CI 0.20-0.87]). CONCLUSION: AD was not associated with increased susceptibility to COVID-19 infection, but was associated with severe COVID-19 complications, especially with mortality. Early diagnosis and active intervention are necessary for patients with AD suspected COVID-19 infection.
Keywords: Alzheimer Disease; Cohort Studies; COVID-19; Humans; Pandemics; Retrospective Studies; SARS-CoV-2

Behavioral and Psychological Symptoms of Dementia in Different Dementia Disorders: A Large-Scale Study of 10,000 Individuals. - Schwertner, Emilia; Pereira, Joana B; Xu, Hong; Secnik, Juraj; Winblad, Bengt; Eriksdotter, Maria; Nägga, Katarina; Religa, Dorota (J Alzheimers Dis, 2022)
BACKGROUND: The majority of individuals with dementia will suffer from behavioral and psychological symptoms of dementia (BPSD). These symptoms contribute to functional impairment and caregiver burden. OBJECTIVE: To characterize BPSD in Alzheimer's disease (AD), vascular dementia (VaD), mixed (Mixed) dementia, Parkinson's disease dementia (PDD), dementia with Lewy bodies (DLB), frontotemporal dementia (FTD), and unspecified dementia in individuals residing in long-term care facilities. METHODS: We included 10,405 individuals with dementia living in long-term care facilities from the Swedish registry for cognitive/dementia disorders (SveDem) and the Swedish BPSD registry. BPSD was assessed with the Neuropsychiatric Inventory - Nursing Home Version (NPI-NH). Multivariate logistic regression models were used to evaluate the associations between dementia diagnoses and different BPSDs. RESULTS: The most common symptoms were aberrant motor behavior, agitation, and irritability. Compared to AD, we found a lower risk of delusions (in FTD, unspecified dementia), hallucinations (FTD), agitation (VaD, PDD, unspecified dementia), elation/euphoria (DLB), anxiety (Mixed, VaD, unspecified dementia), disinhibition (in PDD), irritability (in DLB, FTD, unspecified dementia), aberrant motor behavior (Mixed, VaD, unspecified dementia), and sleep and night-time behavior changes (unspecified dementia). Higher risk of delusions (DLB), hallucinations (DLB, PDD), apathy (VaD, FTD), disinhibition (FTD), and appetite and eating abnormalities (FTD) were also found in comparison to AD. CONCLUSION: Although individuals in our sample were diagnosed with different dementia disorders, they all exhibited aberrant motor behavior, agitation, and irritability. This suggests common underlying psychosocial or biological mechanisms. We recommend prioritizing these symptoms while planning interventions in long-term care facilities.
Keywords: Alzheimer Disease; Behavioral Symptoms; Dementia, Vascular; Frontotemporal Dementia; Hallucinations; Humans; Parkinson Disease

Burden of Insomnia and Sleep Disturbances and the Impact of Sleep Treatments in Patients with Probable or Possible Alzheimer's Disease: A Structured Literature Review. - Benca, Ruth; Herring, W Joseph; Khandker, Rezaul; Qureshi, Zaina P (J Alzheimers Dis, 2022)
BACKGROUND: Sleep disturbances are frequent in Alzheimer's disease (AD). OBJECTIVE: To summarize the impact of sleep disturbances on AD patients and their caregivers and the effects of currently available sleep therapies. METHODS: Published studies (January 1985-March 2020) assessing the burden associated with insomnia/sleep disturbances in the AD population and insomnia treatment effects were identified by searching PubMed, Embase, and Cochrane Library and screened against inclusion criteria. RESULTS: 58 studies assessing patient and caregiver burden, institutionalization, and insomnia treatments in AD patients with sleep disturbances were identified. Sleep disturbances were associated with worse cognition, functional ability, and behavioral and neuropsychological functioning. Health status and quality of life of both patients and caregivers were reduced in the presence of sleep disturbances. Sleep disturbances were also associated with institutionalization. Although significant associations between sleep problems and clinical outcomes were apparent, there was generally no control for other influencing factors (e.g., cognitive status). Bright light and behavioral therapies as well as drugs showed some promise in AD patients, but studies were primarily small and limited data were available, particularly in regard to the effect on associated clinical burden. CONCLUSION: Sleep disturbances are a significant problem for AD patients and caregivers, associated with behavioral and psychological problems and cognitive decline. However, they remain poorly characterized and under-researched. As the global population is aging and AD is on thes rise, data from larger, prospective trials are required to fully understand the clinical correlates of sleep disturbances and the impact insomnia treatments can have.
Keywords: Alzheimer Disease; Caregivers; Humans; Prospective Studies; Quality of Life; Sleep; Sleep Initiation and Maintenance Disorders; Sleep Wake Disorders

Caregiver Tele-Assistance for Reduction of Emotional Distress During the COVID-19 Pandemic. Psychological Support to Caregivers of People with Dementia: The Italian Experience. - Rotondo, Emanuela; Galimberti, Daniela; Mercurio, Matteo; Giardinieri, Giulia; Forti, Sara; Vimercati, Roberto; Borracci, Vittoria; Fumagalli, Giorgio G; Pietroboni, Anna M; Carandini, Tiziana; Nobili, Alessandro; Scarpini, Elio; et al. (J Alzheimers Dis, 2022)
BACKGROUND: COVID-19 pandemic worsened vulnerability of patients with dementia (PWD). This new reality associated with government restriction and isolation worsened stress burden and psychological frailties in PWD caregivers. OBJECTIVE: To give tele-psychological support to caregivers and evaluate the effect of this intervention by quantifying stress burden and quality of life during the first COVID-19 lockdown. METHODS: 50 caregivers were divided into two groups: "Caregiver-focused group" (Cg) and "Patient-focused group" (Pg). Both groups received telephone contact every 2 weeks over a 28-week period, but the content of the call was different: in Cg, caregivers answered questions about the state of the PWD but also explored their own emotional state, stress burden, and quality of life. In Pg instead, telephone contacts were focused only on the PWD, and no evaluation regarding the caregiver mood or state of stress was made. Psychometric scales were administered to evaluate COVID-19 impact, stress burden, and quality of life. RESULTS: Considering the time of intervention, from baseline (W0) to W28, Zarit Burden Interview and Quality of Life-caregiver questionnaires remained unchanged in Cg as compared with baseline (p > 0.05), whereas they worsened significantly in Pg (p < 0.01), showing increased stress over time and decreased quality of life in this group. Moreover, Impact on Event Scale values improved over the weeks in Cg (p = 0.015), while they remained unchanged in Pg (p = 0.483). CONCLUSION: Caregivers who received telephone support about their mood and stress burden did not worsen their psychological state during the time of intervention, as did instead those who did not get such support.
Keywords: Aged; Aged, 80 and over; Caregiver Burden; Caregivers; COVID-19; Dementia; Female; Humans; Italy; Male; Middle Aged; Psychological Distress; Psychosocial Support Systems; Quality of Life; Surveys and Questionnaires; Telephone

Cerebral Volumetric Correlates of Apathy in Alzheimer's Disease and Cognitively Normal Older Adults: Meta-Analysis, Label-Based Review, and Study of an Independent Cohort. - Chaudhary, Shefali; Zhornitsky, Simon; Chao, Herta H; van Dyck, Christopher H; Li, Chiang-Shan R (J Alzheimers Dis, 2022)
BACKGROUND: Affecting nearly half of the patients with Alzheimer's disease (AD), apathy is associated with higher morbidity and reduced quality of life. Basal ganglia and cortical atrophy have been implicated in apathy. However, the findings have varied across studies and left unclear whether subdomains of apathy may involve distinct neuroanatomical correlates. OBJECTIVE: To identify neuroanatomical correlates of AD-associated apathy. METHODS: We performed a meta-analysis and label-based review of the literature. Further, following published routines of voxel-based morphometry, we aimed to confirm the findings in an independent cohort of 19 patients with AD/mild cognitive impairment and 25 healthy controls assessed with the Apathy Evaluation Scale. RESULTS: Meta-analysis of 167 AD and 56 healthy controls showed convergence toward smaller basal ganglia gray matter volume (GMV) in apathy. Label-based review showed anterior cingulate, putamen, insula, inferior frontal gyrus (IFG) and middle temporal gyrus (MTG) atrophy in AD apathy. In the independent cohort, with small-volume-correction, right putamen and MTG showed GMVs in negative correlation with Apathy Evaluation Scale total, behavioral, and emotional scores, and right IFG with emotional score (p < 0.05 family-wise error (FWE)-corrected), controlling for age, education, intracranial volume, and depression. With the Mini-Mental State Examination scores included as an additional covariate, the correlation of right putamen GMV with behavioral and emotional score, right MTG GMV with total and emotional score, and right IFG GMV with emotional score were significant. CONCLUSION: The findings implicate putamen, MTG and IFG atrophy in AD associated apathy, potentially independent of cognitive impairment and depression, and suggest potentially distinct volumetric correlates of apathy.
Keywords: Aged; Alzheimer Disease; Apathy; Atrophy; Basal Ganglia; Brain; Cognitive Dysfunction; Cohort Studies; Gray Matter; Gyrus Cinguli; Humans; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Prefrontal Cortex

Chronic Renin-Angiotensin System Activation Induced Neuroinflammation: Common Mechanisms Underlying Hypertension and Dementia? - Tran, Shirley; Kuruppu, Sanjaya; Rajapakse, Niwanthi W (J Alzheimers Dis, 2022)
Hypertension is a major risk factor for the pathogenesis of vascular dementia and Alzheimer's disease. Chronic activation of the renin-angiotensin system (RAS) contributes substantially to neuroinflammation. We propose that neuroinflammation arising from chronic RAS activation can initiate and potentiate the onset of hypertension and related dementia. Neuroinflammation induced by chronic activation of the RAS plays a key role in the pathogenesis of dementia. Increased levels of pro-inflammatory cytokines tumor necrosis factor (TNF)-α, interleukin (IL)-1β, and transforming growth factor (TGF)-β have been reported in brain tissue of vascular dementia patients and animal models of vascular dementia induced by either angiotensin II infusion or transverse aortic coarctation. It is proposed that neuronal cell death and synaptic dysfunction induced by neuroinflammation lead to cognitive impairment in dementia. The neuroprotective RAS pathway, regulated by angiotensin-converting enzyme 2 (ACE2) which converts angiotensin II into angiotensin-(1-7), can attenuate hypertension and dementia. Furthermore, the use of anti-hypertensive medications in preventing dementia or cognitive decline in hypertensive patients and animal models of dementia have mostly been beneficial. Current evidence suggests a strong link between RAS induced neuroinflammation and the onset of hypertension and dementia, which warrants further investigation. Strategies to counteract an overactive RAS and enhance the neuroprotective arm of the RAS may help prevent or improve cognitive impairment associated with hypertension.
Keywords: Angiotensin I; Angiotensin II; Animals; Antihypertensive Agents; Brain; Cytokines; Dementia, Vascular; Humans; Hypertension; Inflammation; Peptide Fragments; Renin-Angiotensin System

Cognitive Decline Risk Stratification in People with Late-Onset Epilepsy of Unknown Etiology: An Electroencephalographic Connectivity and Graph Theory Pilot Study. - Costa, Cinzia; Vecchio, Fabrizio; Romoli, Michele; Miraglia, Francesca; Nardi Cesarini, Elena; Alù, Francesca; Calabresi, Paolo; Rossini, Paolo Maria (J Alzheimers Dis, 2022)
BACKGROUND: Although people with late onset epilepsy of unknown etiology (LOEU) are at higher risk of cognitive decline compared to the general population, we still lack affordable tools to predict and stratify their risk of dementia. OBJECTIVE: This pilot-study investigates the potential application of electroencephalography (EEG) network small-world (SW) properties in predicting cognitive decline among patients with LOEU. METHODS: People diagnosed with LOEU and normal cognitive examination at the time of epilepsy diagnosis were included. Cerebrospinal fluid biomarkers, brain imaging, and neuropsychological assessment were performed at the time of epilepsy diagnosis. Baseline EEG was analyzed for SW properties. Patients were followed-up over time with neuropsychological testing to define the trajectory of cognitive decline. RESULTS: Over 5.1 years of follow-up, among 24 patients diagnosed with LOEU, 62.5% were female, mean age was 65.3 years, thirteen developed mild cognitive impairment (MCI), and four developed dementia. Patients with LOEU developing MCI had lower values of SW coefficients in the delta (p = 0.03) band and higher SW values in the alpha frequency bands (p = 0.02) compared to patients having normal cognition at last follow-up. The two separate ANOVAs, for low and alpha bands, confirmed an interaction between SW and cognitive decline at follow-up. A similar gradient was confirmed for patients developing dementia compared to those with normal cognitive function as well as to those developing MCI. CONCLUSION: Baseline EEG analysis through SW is worth investigating as an affordable, widely available tool to stratify LOEU patients for their risk of cognitive decline.
Keywords: Aged; Cognitive Dysfunction; Dementia; Electroencephalography; Epilepsy; Female; Humans; Male; Neuropsychological Tests; Pilot Projects; Risk Assessment

Cognitive, Functional, and Emotional Changes During the COVID-19 Pandemic in Greek Patients with Neurocognitive Disorders. - Tsiakiri, Anna; Vlotinou, Pinelopi; Terzoudi, Aikaterini; Heliopoulos, Ioannis; Vadikolias, Konstantinos (J Alzheimers Dis, 2022)
BACKGROUND: Prolonged periods of social deprivation, such as COVID-19-related lockdowns, are associated with deleterious effects on cognitive functions. OBJECTIVE: The aim of this study was to gauge the effect of prolonged social isolation on the cognitive function of older adults with neurocognitive disorders. METHODS: We recruited 125 older adults with minor or major neurocognitive disorders divided into two groups. The control group was tested at the first period of the study (October 2018-May 2019), whereas the experimental group was evaluated at the second chronological period of the study (October 2020-May 2021) during the second wave of COVID-19. Neuropsychological tests were performed at baseline and six months after baseline. RESULTS: In the control group, significant changes in the scores from the Montreal Cognitive Assessment (MoCA; p = 0.049) and the Functional Rating Scale for Symptoms of Dementia (FRSSD; p = 0.005) were found between baseline and follow-up assessments, whereas no changes were identified in Mini-Mental State Examination (MMSE; p = 0.229) and Geriatric Depression Scale (GDS; p = 0.619) scores. In the experimental group, the scores from all neuropsychological tests (MoCA, MMSE, GDS, and FRSSD; p < 0.001 for all) were significantly different at follow-up when compared with those at baseline measurements. Moreover, significant deterioration of specific functions assessed in MMSE and FRSSD was detected, especially in the experimental group. CONCLUSION: This study highlights cognitive functions directly affected by social deprivation of individuals with neurocognitive disorders. The findings can be used in the rehabilitation from confinement and its negative consequences.
Keywords: Aged; Cognition; Cognitive Dysfunction; Communicable Disease Control; COVID-19; Greece; Humans; Neurocognitive Disorders; Neuropsychological Tests; Pandemics

A Comparison of Behavioral and Psychological Symptoms of Dementia (BPSD) and BPSD Sub-Syndromes in Early-Onset and Late-Onset Alzheimer's Disease. - Altomari, Natalia; Bruno, Francesco; Laganà, Valentina; Smirne, Nicoletta; Colao, Rosanna; Curcio, Sabrina; Di Lorenzo, Raffaele; Frangipane, Francesca; Maletta, Raffaele; Puccio, Gianfranco; Bruni, Amalia Cecilia (J Alzheimers Dis, 2022)
BACKGROUND: Behavioral and psychological symptoms of dementia (BPSD) have a large impact on the quality of life of patients with Alzheimer's disease (AD). Few studies have compared BPSD between early-onset (EOAD) and late-onset (LOAD) patients, finding conflicting results. OBJECTIVE: The aims of this study were to: 1) characterize the presence, overall prevalence, and time of occurrence of BPSD in EOAD versus LOAD; 2) estimate the prevalence over time and severity of each BPSD in EOAD versus LOAD in three stages: pre-T0 (before the onset of the disease), T0 (from onset to 5 years), and T1 (from 5 years onwards); 3) track the manifestation of BPSD sub-syndromes (i.e., hyperactivity, psychosis, affective, and apathy) in EOAD versus LOAD at T0 and T1. METHODS: The sample includes 1,538 LOAD and 387 EOAD diagnosed from 1996 to 2018. Comprehensive assessment batteries, including the Neuropsychiatric Inventory (NPI), were administered at the first medical assessment and at different follow-up period. RESULTS: The overall prevalence for the most of BPSD was significantly higher in EOAD compared to LOAD whereas most BPSD appeared significantly later in EOAD patients. Between the two groups, from pre-T0 to T1 we recorded a different pattern of BPSD prevalence over time as well as for BPSD sub-syndromes at T0 and T1. Results on severity of BPSD did not show significant differences. CONCLUSION: EOAD and LOAD represent two different forms of a single entity not only from a neuropathological, cognitive, and functional level but also from a psychiatric point of view.
Keywords: Affective Symptoms; Age of Onset; Aged; Aged, 80 and over; Alzheimer Disease; Apathy; Behavioral Symptoms; Dementia; Female; Humans; Italy; Male; Middle Aged; Neuropsychological Tests; Psychiatric Status Rating Scales; Psychomotor Agitation; Psychotic Disorders; Severity of Illness Index

A Comparison of Well-Being of Carers of People with Dementia and Their Ability to Manage Before and During the COVID-19 Pandemic: Findings from the IDEAL Study. - Gamble, Laura D; Parker, Sophie; Quinn, Catherine; Bennett, Holly Q; Martyr, Anthony; Sabatini, Serena; Pentecost, Claire; Collins, Rachel; Dawson, Eleanor; Hunt, Anna; Allan, Louise; Burns, Alistair; et al. (J Alzheimers Dis, 2022)
BACKGROUND: Social restriction measures imposed to curb the spread of COVID-19 in the United Kingdom impacted on carers of people with dementia, limiting access to support services and increasing perceived burden of caring. Few studies have compared data collected both during and before the pandemic to examine the effect of these changes. OBJECTIVE: To explore whether the COVID-19 pandemic affected the well-being of carers of people with dementia living in the community, and their ability to cope with their caring responsibilities. METHODS: Analysis was conducted on two groups of carers who were enrolled in the IDEAL programme; the 'pre-pandemic group' (n = 312), assessed at two time points prior to the pandemic, and the 'pandemic group', assessed prior to and several months into the pandemic (n = 156). For the pre-pandemic group, carers were matched 2:1 to carers in the pandemic group on certain characteristics. Differences in change over time between the two groups on self-reported well-being, quality of life, coping, perceived competence, and role captivity, were investigated using mixed effect modelling. RESULTS: Compared to the pre-pandemic group, those in the pandemic group appeared to cope better and had more stable self-rated competency and role captivity. They did not differ in terms of well-being or quality of life. CONCLUSIONS: Despite reports of negative impacts on carers early in the pandemic, the findings suggest the pandemic had little negative longer-term impact on carers of people with dementia, and in fact they appeared to have a more positive attitude towards coping several months into the pandemic.
Keywords: Adaptation, Psychological; Caregivers; COVID-19; Dementia; Humans; Pandemics; Quality of Life

COVID-19 and Neurodegenerative Diseases: Prion-Like Spread and Long-Term Consequences. - Baazaoui, Narjes; Iqbal, Khalid (J Alzheimers Dis, 2022)
COVID-19 emerged as a global pandemic starting from Wuhan in China and spread at a lightning speed to the rest of the world. One of the potential long-term outcomes that we speculate is the development of neurodegenerative diseases as a long-term consequence of SARS-CoV-2 especially in people that have developed severe neurological symptoms. Severe inflammatory reactions and aging are two very strong common links between neurodegenerative diseases and COVID-19. Thus, patients that have very high viral load may be at high risk of developing long-term adverse neurological consequences such as dementia. We hypothesize that people with neurodegenerative diseases such as Alzheimer's disease, Parkinson's disease, and aged people are at higher risk of getting the COVID-19 than normal adults. The basis of this hypothesis is the fact that SARS-CoV-2 uses as a receptor angiotensin-converting enzyme 2 to enter the host cell and that this interaction is calcium-dependent. This could then suggest a direct relationship between neurodegenerative diseases, ACE-2 expression, and the susceptibility to COVID-19. The analysis of the available literature showed that COVID-19 virus is neurotropic and was found in the brains of patients infected with this virus. Furthermore, that the risk of having the infection increases with dementia and that infected people with severe symptoms could develop dementia as a long-term consequence. Dementia could be developed following the acceleration of the spread of prion-like proteins. In the present review we discuss current reports concerning the prevalence of COVID-19 in dementia patients, the individuals that are at high risk of suffering from dementia and the potential acceleration of prion-like proteins spread following SARS-CoV-2 infection.
Keywords: Aged; COVID-19; Dementia; Humans; Neurodegenerative Diseases; Prions; SARS-CoV-2

Dimethyl Fumarate is a Potential Therapeutic Option for Alzheimer's Disease. - Sun, Xiaodi; Suo, Xinjun; Xia, Xianyou; Yu, Chunshui; Dou, Yan (J Alzheimers Dis, 2022)
BACKGROUND: Dimethyl fumarate (DMF) has been approved for clinical treatment of multiple sclerosis based on its antioxidant and anti-inflammatory effects by activating the Nrf2 pathway. Since both oxidative stress and inflammation are involved in Alzheimer's disease (AD), DMF is a potential therapeutic option for AD. OBJECTIVE: This study aims to test the therapeutic effects of DMF on AD model mice and to reveal its underlying molecular mechanisms. METHODS: Cell viability assay and in vitro immunofluorescence imaging were used to evaluate the antioxidant effect of DMF on embryonic mouse hippocampal neurons. Behavioral test and brain magnetic resonance imaging were used to assess the therapeutic effects of DMF on spatial learning and memory as well as hippocampal volume in AD model mice with and without Nrf2 knockdown. Western blotting was used to analyze the expression of antioxidant enzymes and molecules associated with AD-related pathological pathways. RESULTS: DMF inhibits reactive oxygen species overproduction and protects neurons without Nrf2 knockdown from death. DMF reduces amyloid-β induced memory impairment and hippocampal atrophy in AD model mice rather than in Nrf2 knockdown AD mice. DMF delays the progression of AD by activating the Nrf2 pathway to enhance the expression of downstream antioxidant enzymes and inhibits lipid peroxidation, apoptosis, inflammation, mitochondrial dysfunction and amyloid-β deposition. CONCLUSION: These results indicate that DMF is a potential therapeutic option for AD through its antioxidant, anti-inflammatory, anti-apoptotic, and other anti-AD effects by activating the Nrf2 pathway.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; Antioxidants; Cell Survival; Dimethyl Fumarate; Disease Models, Animal; Hippocampus; Inflammation; Male; Memory Disorders; Mice; Mice, Inbred C57BL; Neurons; NF-E2-Related Factor 2; NF-kappa B; Oxidative Stress; Protective Agents; Reactive Oxygen Species

Effect of Probiotic Bifidobacterium breve in Improving Cognitive Function and Preventing Brain Atrophy in Older Patients with Suspected Mild Cognitive Impairment: Results of a 24-Week Randomized, Double-Blind, Placebo-Controlled Trial. - Asaoka, Daisuke; Xiao, Jinzhong; Takeda, Tsutomu; Yanagisawa, Naotake; Yamazaki, Takahiro; Matsubara, Yoichiro; Sugiyama, Hideki; Endo, Noemi; Higa, Motoyuki; Kasanuki, Koji; Ichimiya, Yosuke; Koido, Shigeo; et al. (J Alzheimers Dis, 2022)
BACKGROUND: Probiotics have been reported to ameliorate cognitive impairment. OBJECTIVE: We investigated the effect of the probiotic strain Bifidobacterium breve MCC1274 (A1) in enhancing cognition and preventing brain atrophy of older patients with mild cognitive impairment (MCI). METHODS: In this RCT, 130 patients aged from 65 to 88 years old with suspected MCI received once daily either probiotic (B. breve MCC1274, 2×1010 CFU) or placebo for 24 weeks. Cognitive functions were assessed by ADAS-Jcog and MMSE tests. Participants underwent MRI to determine brain atrophy changes using Voxel-based Specific Regional Analysis System for Alzheimer's disease (VSRAD). Fecal samples were collected for the analysis of gut microbiota composition. RESULTS: Analysis was performed on 115 participants as the full analysis set (probiotic 55, placebo 60). ADAS-Jcog subscale "orientation" was significantly improved compared to placebo at 24 weeks. MMSE subscales "orientation in time" and "writing" were significantly improved compared to placebo in the lower baseline MMSE (< 25) subgroup at 24 weeks. VSRAD scores worsened in the placebo group; probiotic supplementation tended to suppress the progression, in particular among those subjects with progressed brain atrophy (VOI Z-score ≥1.0). There were no marked changes in the overall composition of the gut microbiota by the probiotic supplementation. CONCLUSION: Improvement of cognitive function was observed on some subscales scores only likely due to the lower sensitiveness of these tests for MCI subjects. Probiotics consumption for 24 weeks suppressed brain atrophy progression, suggesting that B. breve MCC1274 helps prevent cognitive impairment of MCI subjects.
Keywords: Aged; Aged, 80 and over; Atrophy; Bifidobacterium breve; Brain; Cognition; Cognitive Dysfunction; Double-Blind Method; Humans; Probiotics

The Efficacy and Safety of Alzheimer's Disease Therapies: An Updated Umbrella Review. - Fan, Fangcheng; Liu, Hua; Shi, Xiaojie; Ai, Yangwen; Liu, Qingshan; Cheng, Yong (J Alzheimers Dis, 2022)
BACKGROUND: Evidence summaries for efficacy and safety of frequently employed treatments of Alzheimer's disease (AD) are sparse. OBJECTIVE: We aimed to perform an updated umbrella review to identify an efficacious and safe treatment for AD patients. METHODS: We conducted a search for meta-analyses and systematic reviews on the Embase, PubMed, The Cochrane Library, and Web of Science to address this knowledge gap. We examined the cognitive functions, behavioral symptoms, global clinical assessment, and Activities of Daily Living as efficacy endpoints, and the incidence of adverse events as safety profiles. RESULTS: Sixteen eligible papers including 149 studies were included in the umbrella review. The results showed that AChE inhibitors (donepezil, galantamine, rivastigmine, Huperzine A), Ginkgo biloba, and cerebrolysin appear to be beneficial for cognitive, global performances, and activities of daily living in patients with AD. Furthermore, anti-Aβ agents are unlikely to have an important effect on slowing cognitive or functional impairment in mild to moderate AD. CONCLUSION: Our study demonstrated that AChE inhibitors, Ginkgo biloba, and cerebrolysin are the optimum cognitive and activities of daily living medication for patients with AD.
Keywords: Activities of Daily Living; Alzheimer Disease; Amino Acids; Cholinesterase Inhibitors; Cognition; Donepezil; Galantamine; Ginkgo biloba; Humans; Nootropic Agents; Patient Safety; Plant Extracts; Rivastigmine

Interaction Between Diet and Microbiota in the Pathophysiology of Alzheimer's Disease: Focus on Polyphenols and Dietary Fibers. - Ticinesi, Andrea; Mancabelli, Leonardo; Carnevali, Luca; Nouvenne, Antonio; Meschi, Tiziana; Del Rio, Daniele; Ventura, Marco; Sgoifo, Andrea; Angelino, Donato (J Alzheimers Dis, 2022)
Animal studies increasingly indicate that the gut microbiota composition and function can be involved in the pathophysiology and progression of Alzheimer's disease (AD) at multiple levels. However, few studies have investigated this putative gut-brain axis in human beings, and none of them considered diet as a determinant of intestinal microbiota composition. Epidemiological studies highlight that a high intake of fruit and vegetables, such as that typical of the Mediterranean diet, can modulate AD progression. Thus, nutritional interventions are being increasingly studied as a possible non-pharmacological strategy to slow down the progression of AD. In particular, polyphenols and fibers represent the nutritional compounds with the higher potential of counterbalancing the pathophysiological mechanisms of dementia due to their antioxidant, anti-inflammatory, and anti-apoptotic properties. These actions are mediated by the gut microbiota, that can transform polyphenols and fibers into biologically active compounds including, among others, phenyl-γ-valerolactones, urolithins, butyrate, and other short-chain fatty acids. In this review, the complex mechanisms linking nutrition, gut microbiota composition, and pathophysiology of cognitive decline in AD are discussed, with a particular focus on the role of polyphenols and fibers. The gaps between pre-clinical and clinical studies are particularly emphasized, as well as the urgent need for studies comprehensively evaluating the link between nutrition, microbiome, and clinical aspects of AD.
Keywords: Alzheimer Disease; Animals; Diet; Diet, Mediterranean; Dietary Fiber; Humans; Microbiota; Polyphenols

Investigating Casual Associations Among Gut Microbiota, Metabolites, and Neurodegenerative Diseases: A Mendelian Randomization Study. - Ning, Jing; Huang, Shu-Yi; Chen, Shi-Dong; Zhang, Ya-Ru; Huang, Yu-Yuan; Yu, Jin-Tai (J Alzheimers Dis, 2022)
BACKGROUND: Recent studies had explored that gut microbiota was associated with neurodegenerative diseases (including Alzheimer's disease (AD), Parkinson's disease (PD), and amyotrophic lateral sclerosis (ALS)) through the gut-brain axis, among which metabolic pathways played an important role. However, the underlying causality remained unclear. OBJECTIVE: Our study aimed to evaluate potential causal relationships between gut microbiota, metabolites, and neurodegenerative diseases through Mendelian randomization (MR) approach. METHODS: We selected genetic variants associated with gut microbiota traits (N = 18,340) and gut microbiota-derived metabolites (N = 7,824) from genome-wide association studies. Summary statistics of neurodegenerative diseases were obtained from IGAP (AD, 17,008 cases; 37,154 controls), IPDGC (PD, 37,688 cases; 141,779 controls), and IALSC (ALS, 20,806 cases; 59,804 controls) respectively. RESULTS: Greater abundance of Ruminococcus (OR, 1.245; 95% CI, 1.103-1.405; p = 0.0004) was found significantly related to higher risk of ALS. Besides, our study found suggestive associations of Actinobacteria, Lactobacillaceae, Faecalibacterium, Ruminiclostridium, and Lachnoclostridium with AD, of Lentisphaerae, Lentisphaeria, Oxalobacteraceae, Victivallales, Bacillales, Eubacteriumhalliigroup, Anaerostipes, and Clostridiumsensustricto1 with PD, and of Lachnospira, Fusicatenibacter, Catenibacterium, and Ruminococcusgnavusgroup with ALS. Our study also revealed suggestive associations between 12 gut microbiome-dependent metabolites and neurodegenerative diseases. Glutamine was related to lower risk of AD. For the serotonin pathway, serotonin was found as a protective factor of PD, while kynurenine as a risk factor for ALS. CONCLUSION: Our study firstly applied a two-sample MR approach to detect causal relationships among gut microbiota, gut metabolites, and neurodegenerative diseases. Our findings may provide new targets for treatments and may offer valuable insights for further studies on the underlying mechanisms.
Keywords: Alzheimer Disease; Amyotrophic Lateral Sclerosis; Gastrointestinal Microbiome; Genome-Wide Association Study; Humans; Mendelian Randomization Analysis; Neurodegenerative Diseases; Parkinson Disease; Risk Factors; Serotonin

Investigating Causal Relations Between Circulating Metabolites and Alzheimer's Disease: A Mendelian Randomization Study. - Huang, Shu-Yi; Yang, Yu-Xiang; Zhang, Ya-Ru; Kuo, Kevin; Li, Hong-Qi; Shen, Xue-Ning; Chen, Shi-Dong; Chen, Ke-Liang; Dong, Qiang; Tan, Lan; Yu, Jin-Tai (J Alzheimers Dis, 2022)
BACKGROUND: Metabolomics is a promising approach that can be used to understand pathophysiological pathways of Alzheimer's disease (AD). However, the causal relationships between metabolism and AD are poorly understood. OBJECTIVE: We aimed to investigate the causal association between circulating metabolites and risk of AD through two-sample Mendelian randomization (MR) approach. METHODS: Genetic associations with 123 circulating metabolic traits were utilized as exposures. Summary statistics data from International Genomics of Alzheimer's Project was used in primary analysis, including 21,982 AD cases and 41,944 controls. Validation was performed using family history of AD data from UK Biobank (27,696 cases of maternal AD, 14,338 cases of paternal AD, and 272,244 controls). We utilized inverse-variance weighted method as primary method. RESULTS: We found significantly increased risks of developing AD per standard deviation increase in the levels of circulating ApoB (odd ratio[OR] = 3.18; 95% confidence interval[CI]: 1.52-6.66, p = 0.0022), glycoprotein acetyls (OR = 1.21; 95% CI: 1.05-1.39, p = 0.0093), total cholesterol (OR = 2.73; 95% CI: 1.41-5.30, p = 0.0030), and low-density lipoprotein (LDL) cholesterol (OR = 2.34; 95% CI: 1.53-3.57, p = 0.0001). Whereas glutamine (OR = 0.81; 95% CI: 0.71-0.92, p = 0.0011) were significantly associated with lower risk of AD. We also detected causal effects of several different composition of LDL fractions on increased AD risk, which has been verified in validation. However, we found no association between circulating high-density lipoprotein cholesterol and AD. CONCLUSION: Our findings suggest causal effects of circulating glycoprotein acetyls, ApoB, LDL cholesterol, and serum total cholesterol on higher risk of AD, whereas glutamine showed the protective effect.
Keywords: Alzheimer Disease; Apolipoproteins B; Cholesterol; Genome-Wide Association Study; Glutamine; Humans; Mendelian Randomization Analysis; Polymorphism, Single Nucleotide; Risk Factors

Medial Temporal Atrophy in Posterior Cortical Atrophy and Its Relationship to the Cingulate Island Sign. - Josephs, Kennedy A; Pham, Nha Trang Thu; Graff-Radford, Jonathan; Machulda, Mary M; Lowe, Val J; Whitwell, Jennifer L (J Alzheimers Dis, 2022)
BACKGROUND: It has been hypothesized that medial temporal sparing may be related to preserved posterior cingulate metabolism and the cingulate island sign (CIS) on [18F]fluorodeoxyglucose (FDG) PET in posterior cortical atrophy (PCA). OBJECTIVE: To assess the severity of medial temporal atrophy in PCA and determine whether the presence of a CIS is related to medial temporal sparing. METHODS: Fifty-five PCA patients underwent MRI and FDG-PET. The degree and symmetry of medial temporal atrophy on MRI was visually assessed using a five-point scale for both hemispheres. Visual assessments of FDG-PET coded the presence/absence of a CIS and whether the CIS was symmetric or asymmetric. Hippocampal volumes and a quantitative CIS were also measured. RESULTS: Medial temporal atrophy was most commonly mild or moderate, was symmetric in 55% of patients, and when asymmetric was most commonly worse on the right (76%). Older age and worse memory performance were associated with greater medial temporal atrophy. The CIS was observed in 44% of the PCA patients and was asymmetric in 50% of these. The patients with a CIS showed greater medial temporal asymmetry, but did not show lower medial temporal atrophy scores, compared to those without a CIS. Hippocampal volumes were not associated with quantitative CIS. CONCLUSION: Mild medial temporal atrophy is a common finding in PCA and is associated with memory impairment. However, medial temporal sparing was not related to the presence of a CIS in PCA.
Keywords: Alzheimer Disease; Atrophy; Fluorodeoxyglucose F18; Humans; Lewy Body Disease; Magnetic Resonance Imaging; Positron-Emission Tomography

Peptidylarginine Deiminase and Alzheimer's Disease. - Wang, Lai; Chen, Hongyang; Tang, Jing; Guo, Zhengwei; Wang, Yanming (J Alzheimers Dis, 2022)
Peptidylarginine deiminases (PADs) are indispensable enzymes for post-translational modification of proteins, which can convert Arg residues on the surface of proteins to citrulline residues. The PAD family has five isozymes, PAD1, 2, 3, 4, and 6, which have been found in multiple tissues and organs. PAD2 and PAD4 were detected in cerebral cortex and hippocampus from human and rodent brain. In the central nervous system, abnormal expression and activation of PADs are involved in the pathological changes and pathogenesis of Alzheimer's disease (AD). This article reviews the classification, distribution, and function of PADs, with an emphasis on the relationship between the abnormal activation of PADs and AD pathogenesis, diagnosis, and the therapeutic potential of PADs as drug targets for AD.
Keywords: Alzheimer Disease; Animals; Cerebral Cortex; Citrulline; Hippocampus; Humans; Isoenzymes; Protein Processing, Post-Translational; Protein-Arginine Deiminases

Post-Stroke Cognitive Impairment: Epidemiology, Risk Factors, and Management. - Huang, Yu-Yuan; Chen, Shi-Dong; Leng, Xin-Yi; Kuo, Kevin; Wang, Zuo-Teng; Cui, Mei; Tan, Lan; Wang, Kai; Dong, Qiang; Yu, Jin-Tai (J Alzheimers Dis, 2022)
Stroke, characterized as a neurological deficit of cerebrovascular cause, is very common in older adults. Increasing evidence suggests stroke contributes to the risk and severity of cognitive impairment. People with cognitive impairment following stroke often face with quality-of-life issues and require ongoing support, which have a profound effect on caregivers and society. The high morbidity of post-stroke cognitive impairment (PSCI) demands effective management strategies, in which preventive strategies are more appealing, especially those targeting towards modifiable risk factors. In this review article, we attempt to summarize existing evidence and knowledge gaps on PSCI: elaborating on the heterogeneity in current definitions, reporting the inconsistent findings in PSCI prevalence in the literature, exploring established or less established predictors, outlining prevention and treatment strategies potentially effective or currently being tested, and proposing promising directions for future research.
Keywords: Aged; Cognitive Dysfunction; Humans; Prevalence; Risk Factors; Stroke

Potential Mechanisms Underlying Resistance to Dementia in Non-Demented Individuals with Alzheimer's Disease Neuropathology. - Kok, Frédérique K; van Leerdam, Suzanne L; de Lange, Elizabeth C M (J Alzheimers Dis, 2022)
Alzheimer's disease (AD) is the most common form of dementia and typically characterized by the accumulation of amyloid-β plaques and tau tangles. Intriguingly, there also exists a group of elderly which do not develop dementia during their life, despite the AD neuropathology, the so-called non-demented individuals with AD neuropathology (NDAN). In this review, we provide extensive background on AD pathology and normal aging and discuss potential mechanisms that enable these NDAN individuals to remain cognitively intact. Studies presented in this review show that NDAN subjects are generally higher educated and have a larger cognitive reserve. Furthermore, enhanced neural hypertrophy could compensate for hippocampal and cingulate neural atrophy in NDAN individuals. On a cellular level, these individuals show increased levels of neural stem cells and 'von Economo neurons'. Furthermore, in NDAN brains, binding of Aβ oligomers to synapses is prevented, resulting in decreased glial activation and reduced neuroinflammation. Overall, the evidence stated here strengthens the idea that some individuals are more resistant to AD pathology, or at least show an elongation of the asymptomatic state of the disease compared to others. Insights into the mechanisms underlying this resistance could provide new insight in understanding normal aging and AD itself. Further research should focus on factors and mechanisms that govern the NDAN cognitive resilience in order to find clues on novel biomarkers, targets, and better treatments of AD.
Keywords: Aged; Alzheimer Disease; Amyloid beta-Peptides; Hippocampus; Humans; Plaque, Amyloid; Synapses

Prions and Neurodegenerative Diseases: A Focus on Alzheimer's Disease. - Crestini, Alessio; Santilli, Francesca; Martellucci, Stefano; Carbone, Elena; Sorice, Maurizio; Piscopo, Paola; Mattei, Vincenzo (J Alzheimers Dis, 2022)
Specific protein misfolding and aggregation are mechanisms underlying various neurodegenerative diseases such as prion disease and Alzheimer's disease (AD). The misfolded proteins are involved in prions, amyloid-β (Aβ), tau, and α-synuclein disorders; they share common structural, biological, and biochemical characteristics, as well as similar mechanisms of aggregation and self-propagation. Pathological features of AD include the appearance of plaques consisting of deposition of protein Aβ and neurofibrillary tangles formed by the hyperphosphorylated tau protein. Although it is not clear how protein aggregation leads to AD, we are learning that the cellular prion protein (PrPC) plays an important role in the pathogenesis of AD. Herein, we first examined the pathogenesis of prion and AD with a focus on the contribution of PrPC to the development of AD. We analyzed the mechanisms that lead to the formation of a high affinity bond between Aβ oligomers (AβOs) and PrPC. Also, we studied the role of PrPC as an AβO receptor that initiates an AβO-induced signal cascade involving mGluR5, Fyn, Pyk2, and eEF2K linking Aβ and tau pathologies, resulting in the death of neurons in the central nervous system. Finally, we have described how the PrPC-AβOs interaction can be used as a new potential therapeutic target for the treatment of PrPC-dependent AD.
Keywords: alpha-Synuclein; Alzheimer Disease; Amyloid beta-Peptides; Animals; Humans; Neurofibrillary Tangles; Neurons; Prion Proteins; Protein Aggregation, Pathological; Randomized Controlled Trials as Topic; Receptor, Metabotropic Glutamate 5; tau Proteins

Probiotic Bifidobacterium breve Prevents Memory Impairment Through the Reduction of Both Amyloid-β Production and Microglia Activation in APP Knock-In Mouse. - Abdelhamid, Mona; Zhou, Chunyu; Ohno, Kazuya; Kuhara, Tetsuya; Taslima, Ferdous; Abdullah, Mohammad; Jung, Cha-Gyun; Michikawa, Makoto (J Alzheimers Dis, 2022)
BACKGROUND: Probiotic supplementation reestablishes microbiome diversity and improves brain function in Alzheimer's disease (AD); their molecular mechanisms, however, have not yet been fully illustrated. OBJECTIVE: We investigated the effects of orally supplemented Bifidobacterium breve MCC1274 on cognitive function and AD-like pathologies in AppNL-G-F mice. METHODS: Three-month-old AppNL-G-F mice were orally supplemented with B. breve MCC1274 for four months. The short-term memory function was evaluated using a novel object recognition test. Amyloid plaques, amyloid-β (Aβ) levels, Aβ fibril, amyloid-β protein precursor and its processing enzymes, its metabolic products, glial activity, and cell proliferation in the subgranular zone of the dentate gyrus were evaluated by immunohistochemistry, Aβ ELISA, western blotting, and immunofluorescence staining. The mRNA expression levels of pro- and anti-inflammatory cytokines were determined by qRT-PCR analysis. RESULTS: We found that the oral B. breve MCC1 274 supplementation prevented memory impairment in AppNL-G-F mice and decreased hippocampal Aβ levels through the enhancement of the a-disintegrin and metalloproteinase 10 (ADAM10) level. Moreover, administration of the probiotic activated the ERK/HIF-1α signaling pathway responsible for increasing the ADAM10 level and also attenuated microglial activation, which in turn led to reduction in the mRNA expression levels of pro-inflammatory cytokines in the brain. In addition, B. breve MCC1274 supplementation increased the level of synaptic proteins in the hippocampus. CONCLUSION: Our findings support the possibility that oral B. breve MCC1274 supplementation might be used as a potential preventive therapy for AD progression.
Keywords: Amyloid beta-Peptides; Animals; Bifidobacterium breve; Brain; Disease Models, Animal; Hippocampus; Memory Disorders; Mice; Mice, Transgenic; Microglia; Probiotics

Psychosis as a Treatment Target in Dementia: A Roadmap for Designing Interventions. - Agüera-Ortiz, Luis; Babulal, Ganesh M; Bruneau, Marie-Andrée; Creese, Byron; D'Antonio, Fabrizia; Fischer, Corinne E; Gatchel, Jennifer R; Ismail, Zahinoor; Kumar, Sanjeev; McGeown, William J; Mortby, Moyra E; Nuñez, Nicolas A; et al. (J Alzheimers Dis, 2022)
Psychotic phenomena are among the most severe and disruptive symptoms of dementias and appear in 30% to 50% of patients. They are associated with a worse evolution and great suffering to patients and caregivers. Their current treatments obtain limited results and are not free of adverse effects, which are sometimes serious. It is therefore crucial to develop new treatments that can improve this situation. We review available data that could enlighten the future design of clinical trials with psychosis in dementia as main target. Along with an explanation of its prevalence in the common diseases that cause dementia, we present proposals aimed at improving the definition of symptoms and what should be included and excluded in clinical trials. A review of the available information regarding the neurobiological basis of symptoms, in terms of pathology, neuroimaging, and genomics, is provided as a guide towards new therapeutic targets. The correct evaluation of symptoms is transcendental in any therapeutic trial and these aspects are extensively addressed. Finally, a critical overview of existing pharmacological and non-pharmacological treatments is made, revealing the unmet needs, in terms of efficacy and safety. Our work emphasizes the need for better definition and measurement of psychotic symptoms in dementias in order to highlight their differences with symptoms that appear in non-dementing diseases such as schizophrenia. Advances in neurobiology should illuminate the development of new, more effective and safer molecules for which this review can serve as a roadmap in the design of future clinical trials.
Keywords: Caregivers; Dementia; Hallucinations; Humans; Psychotic Disorders; Schizophrenia

Rheumatoid Arthritis, Cognitive Impairment, and Neuroimaging Biomarkers: Results from the Mayo Clinic Study of Aging. - Vassilaki, Maria; Crowson, Cynthia S; Davis Iii, John M; Duong, Stephanie Q; Jones, David T; Nguyen, Aivi; Mielke, Michelle M; Vemuri, Prashanthi; Myasoedova, Elena (J Alzheimers Dis, 2022)
BACKGROUND: Observational studies suggested that dementia risk in patients with rheumatoid arthritis (RA) is higher than in the general population. OBJECTIVE: To examine the associations of RA with cognitive decline and dementia, and neuroimaging biomarkers of aging, Alzheimer's disease, and vascular pathology in adult participants in the Mayo Clinic Study of Aging (MCSA). METHODS: Participants with RA were matched 1:3 on age, sex, education, and baseline cognitive diagnosis to participants without RA. RA cases with MRI were also matched with non-cases with available MRI. All available imaging studies (i.e., amyloid and FDG PET, sMRI, and FLAIR) were included. The study included 104 participants with RA and 312 without RA (mean age (standard deviation, SD) 75.0 (10.4) years, 33% male and average follow-up (SD) 4.2 (3.8) years). RESULTS: Groups were similar in cognitive decline and risk of incident dementia. Among participants with neuroimaging, participants with RA (n = 33) and without RA (n = 98) had similar amyloid burden and neurodegeneration measures, including regions sensitive to aging and dementia, but greater mean white matter hyperintensity volume relative to the total intracranial volume (mean (SD)% : 1.12 (0.57)% versus 0.76 (0.69)% of TIV, p = 0.01), and had higher mean (SD) number of cortical infarctions (0.24 (0.44) versus 0.05 (0.33), p = 0.02). CONCLUSION: Although cognitive decline and dementia risk were similar in participants with and without RA, participants with RA had more abnormal cerebrovascular pathology on neuroimaging. Future studies should examine the mechanisms underlying these changes and potential implications for prognostication and prevention of cognitive decline in RA.
Keywords: Aged; Aging; Alzheimer Disease; Amyloid; Amyloid beta-Peptides; Amyloidosis; Arthritis, Rheumatoid; Biomarkers; Brain; Cognitive Dysfunction; Female; Fluorodeoxyglucose F18; Humans; Magnetic Resonance Imaging; Male; Neuroimaging; Positron-Emission Tomography

Risk of Alzheimer's Disease Following Influenza Vaccination: A Claims-Based Cohort Study Using Propensity Score Matching. - Bukhbinder, Avram S; Ling, Yaobin; Hasan, Omar; Jiang, Xiaoqian; Kim, Yejin; Phelps, Kamal N; Schmandt, Rosemarie E; Amran, Albert; Coburn, Ryan; Ramesh, Srivathsan; Xiao, Qian; Schulz, Paul E (J Alzheimers Dis, 2022)
BACKGROUND: Prior studies have found a reduced risk of dementia of any etiology following influenza vaccination in selected populations, including veterans and patients with serious chronic health conditions. However, the effect of influenza vaccination on Alzheimer's disease (AD) risk in a general cohort of older US adults has not been characterized. OBJECTIVE: To compare the risk of incident AD between patients with and without prior influenza vaccination in a large US claims database. METHODS: Deidentified claims data spanning September 1, 2009 through August 31, 2019 were used. Eligible patients were free of dementia during the 6-year look-back period and≥65 years old by the start of follow-up. Propensity-score matching (PSM) was used to create flu-vaccinated and flu-unvaccinated cohorts with similar baseline demographics, medication usage, and comorbidities. Relative risk (RR) and absolute risk reduction (ARR) were estimated to assess the effect of influenza vaccination on AD risk during the 4-year follow-up. RESULTS: From the unmatched sample of eligible patients (n = 2,356,479), PSM produced a sample of 935,887 flu-vaccinated-unvaccinated matched pairs. The matched sample was 73.7 (SD, 8.7) years of age and 56.9% female, with median follow-up of 46 (IQR, 29-48) months; 5.1% (n = 47,889) of the flu-vaccinated patients and 8.5% (n = 79,630) of the flu-unvaccinated patients developed AD during follow-up. The RR was 0.60 (95% CI, 0.59-0.61) and ARR was 0.034 (95% CI, 0.033-0.035), corresponding to a number needed to treat of 29.4. CONCLUSION: This study demonstrates that influenza vaccination is associated with reduced AD risk in a nationwide sample of US adults aged 65 and older.
Keywords: Adult; Aged; Alzheimer Disease; Chronic Disease; Cohort Studies; Female; Humans; Influenza, Human; Male; Middle Aged; Propensity Score; Vaccination

Sex Differences in Behavior and Molecular Pathology in the 5XFAD Model. - Sil, Annesha; Erfani, Arina; Lamb, Nicola; Copland, Rachel; Riedel, Gernot; Platt, Bettina (J Alzheimers Dis, 2022)
BACKGROUND: The prevalence of Alzheimer's disease (AD) is greater in women compared to men, but the reasons for this remain unknown. This sex difference has been widely neglected in experimental studies using transgenic mouse models of AD. OBJECTIVE: Here, we studied behavior and molecular pathology of 5-month-old 5XFAD mice, which express mutated human amyloid precursor protein and presenilin-1 on a C57BL/6J background, versus their wild-type littermate controls, to compare both sex- and genotype-dependent differences. METHODS: A novel behavioral paradigm was utilized (OF-NO-SI), comprising activity measures (Open Field, OF) arena, followed by Novel Object exploration (NO) and Social Interaction (SI) of a sex-matched conspecific. Each segment consisted of two repeated trials to assess between-trial habituation. Subsequently, brain pathology (amyloid load, stress response and inflammation markers, synaptic integrity, trophic support) was assessed using qPCR and western blotting. RESULTS: Female 5XFAD mice had higher levels of human APP and amyloid-β and heightened inflammation versus males. These markers correlated with hyperactivity observed in both sexes, yet only female 5XFAD mice presented with subtle deficits in object and social exploration. Male animals had higher expression of stress markers and neurotrophic factors irrespective of genotype, this correlated with cognitive performance. CONCLUSION: The impact of sex on AD-relevant phenotypes is in line with human data and emphasizes the necessity of appropriate study design and reporting. Differential molecular profiles observed in male versus female mice offer insights into possible protective mechanisms, and hence treatment strategies.
Keywords: Alzheimer Disease; Amyloid beta-Protein Precursor; Animals; Disease Models, Animal; Female; Humans; Male; Mice; Mice, Inbred C57BL; Mice, Transgenic; Mutation; Pathology, Molecular; Presenilin-1; Sex Characteristics

ANMerge: A Comprehensive and Accessible Alzheimer's Disease Patient-Level Dataset. - Birkenbihl, Colin; Westwood, Sarah; Shi, Liu; Nevado-Holgado, Alejo; Westman, Eric; Lovestone, Simon; Hofmann-Apitius, Martin (J Alzheimers Dis, 2021)
BACKGROUND: Accessible datasets are of fundamental importance to the advancement of Alzheimer's disease (AD) research. The AddNeuroMed consortium conducted a longitudinal observational cohort study with the aim to discover AD biomarkers. During this study, a broad selection of data modalities was measured including clinical assessments, magnetic resonance imaging, genotyping, transcriptomic profiling, and blood plasma proteomics. Some of the collected data were shared with third-party researchers. However, this data was incomplete, erroneous, and lacking in interoperability. OBJECTIVE: To provide the research community with an accessible, multimodal, patient-level AD cohort dataset. METHODS: We systematically addressed several limitations of the originally shared resources and provided additional unreleased data to enhance the dataset. RESULTS: In this work, we publish and describe ANMerge, a new version of the AddNeuroMed dataset. ANMerge includes multimodal data from 1,702 study participants and is accessible to the research community via a centralized portal. CONCLUSION: ANMerge is an information rich patient-level data resource that can serve as a discovery and validation cohort for data-driven AD research, such as, for example, machine learning and artificial intelligence approaches.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cohort Studies; Datasets as Topic; Female; Gene Expression Profiling; Genotype; Humans; Magnetic Resonance Imaging; Male; Proteomics

Anti-Aβ Antibody Aducanumab Regulates the Proteome of Senile Plaques and Closely Surrounding Tissue in a Transgenic Mouse Model of Alzheimer's Disease. - Bastrup, Joakim; Hansen, Kathrine H; Poulsen, Thomas B G; Kastaniegaard, Kenneth; Asuni, Ayodeji A; Christensen, Søren; Belling, Dorthe; Helboe, Lone; Stensballe, Allan; Volbracht, Christiane (J Alzheimers Dis, 2021)
BACKGROUND: Alzheimer's disease (AD) is characterized by accumulation of amyloid-β (Aβ) species and deposition of senile plaques (SPs). Clinical trials with the anti-Aβ antibody aducanumab have been completed recently. OBJECTIVE: To characterize the proteomic profile of SPs and surrounding tissue in a mouse model of AD in 10-month-old tgAPPPS1-21 mice after chronic treatment with aducanumab for four months with weekly dosing (10 mg/kg). METHODS: After observing significant reduction of SP numbers in hippocampi of aducanumab-treated mice, we applied a localized proteomic analysis by combining laser microdissection and liquid chromatography-tandem mass spectrometry (LC-MS/MS) of the remaining SPs in hippocampi. We microdissected three subregions, containing SPs, SP penumbra level 1, and an additional penumbra level 2 to follow the proteomic profile as gradient. RESULTS: In the aducanumab-treated mice, we identified 17 significantly regulated proteins that were associated with 1) mitochondria and metabolism (ACAT2, ATP5J, ETFA, EXOG, HK1, NDUFA4, NDUFS7, PLCB1, PPP2R4), 2) cytoskeleton and axons (ADD1, CAPZB, DPYSL3, MAG), 3) stress response (HIST1H1C/HIST1H1D, HSPA12A), and 4) AβPP trafficking/processing (CD81, GDI2). These pathways and some of the identified proteins are implicated in AD pathogenesis. Proteins associated with mitochondria and metabolism were mainly upregulated while proteins associated with AβPP trafficking/processing and stress response pathways were mainly downregulated, suggesting that aducanumab could lead to a beneficial proteomic profile around SPs in tgAPPPS1-21 mice. CONCLUSION: We identified novel proteomic patterns of SPs and surrounding tissue indicating that chronic treatment with aducanumab could inhibit Aβ toxicity and increase phagocytosis and cell viability.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Amyloid beta-Protein Precursor; Animals; Antibodies, Monoclonal, Humanized; Brain; Chromatography, Liquid; Cytoskeletal Proteins; Disease Models, Animal; Humans; Mice; Mice, Transgenic; Mitochondrial Proteins; Plaque, Amyloid; Presenilin-1; Protein Transport; Proteome; Proteomics; Stress, Physiological; Tandem Mass Spectrometry

APOE4 Copy Number-Dependent Proteomic Changes in the Cerebrospinal Fluid. - Berger, Miles; Cooter, Mary; Roesler, Alexander S; Chung, Stacey; Park, John; Modliszewski, Jennifer L; VanDusen, Keith W; Thompson, J Will; Moseley, Arthur; Devinney, Michael J; Smani, Shayan; Hall, Ashley; et al. (J Alzheimers Dis, 2021)
BACKGROUND: APOE4 has been hypothesized to increase Alzheimer's disease risk by increasing neuroinflammation, though the specific neuroinflammatory pathways involved are unclear. OBJECTIVE: Characterize cerebrospinal fluid (CSF) proteomic changes related to APOE4 copy number. METHODS: We analyzed targeted proteomic data from ADNI CSF samples using a linear regression model adjusting for age, sex, and APOE4 copy number, and additional linear models also adjusting for AD clinical status or for CSF Aβ, tau, or p-tau levels. False discovery rate was used to correct for multiple comparisons correction. RESULTS: Increasing APOE4 copy number was associated with a significant decrease in a CRP peptide level across all five models (q < 0.05 for each), and with significant increases in ALDOA, CH3L1 (YKL-40), and FABPH peptide levels (q < 0.05 for each) except when controlling for AD clinical status or neurodegeneration biomarkers (i.e., CSF tau or p-tau). In all models except the one controlling for CSF Aβ levels, though not statistically significant, there was a consistent inverse direction of association between APOE4 copy number and the levels of all 24 peptides from all 8 different complement proteins measured. The odds of this happening by chance for 24 unrelated peptides would be less than 1 in 16 million. CONCLUSION: Increasing APOE4 copy number was associated with decreased CSF CRP levels across all models, and increased CSF ALDOA, CH3L1, and FABH levels when controlling for CSF Aβ levels. Increased APOE4 copy number may also be associated with decreased CSF complement pathway protein levels, a hypothesis for investigation in future studies.
Keywords: Aged; Alzheimer Disease; Apolipoprotein E4; Biomarkers; Chitinase-3-Like Protein 1; DNA Copy Number Variations; Female; Fructose-Bisphosphate Aldolase; Humans; Male; Proteomics; Receptors, Immunologic

Automatic Subtyping of Individuals with Primary Progressive Aphasia. - Themistocleous, Charalambos; Ficek, Bronte; Webster, Kimberly; den Ouden, Dirk-Bart; Hillis, Argye E; Tsapkini, Kyrana (J Alzheimers Dis, 2021)
BACKGROUND: The classification of patients with primary progressive aphasia (PPA) into variants is time-consuming, costly, and requires combined expertise by clinical neurologists, neuropsychologists, speech pathologists, and radiologists. OBJECTIVE: The aim of the present study is to determine whether acoustic and linguistic variables provide accurate classification of PPA patients into one of three variants: nonfluent PPA, semantic PPA, and logopenic PPA. METHODS: In this paper, we present a machine learning model based on deep neural networks (DNN) for the subtyping of patients with PPA into three main variants, using combined acoustic and linguistic information elicited automatically via acoustic and linguistic analysis. The performance of the DNN was compared to the classification accuracy of Random Forests, Support Vector Machines, and Decision Trees, as well as to expert clinicians' classifications. RESULTS: The DNN model outperformed the other machine learning models as well as expert clinicians' classifications with 80% classification accuracy. Importantly, 90% of patients with nfvPPA and 95% of patients with lvPPA was identified correctly, providing reliable subtyping of these patients into their corresponding PPA variants. CONCLUSION: We show that the combined speech and language markers from connected speech productions can inform variant subtyping in patients with PPA. The end-to-end automated machine learning approach we present can enable clinicians and researchers to provide an easy, quick, and inexpensive classification of patients with PPA.
Keywords: Acoustics; Aged; Aphasia, Primary Progressive; Decision Trees; Female; Humans; Linguistics; Machine Learning; Male; Models, Theoretical; Neural Networks, Computer; Primary Progressive Nonfluent Aphasia; Reproducibility of Results; Support Vector Machine

Blood-Based ATN Biomarkers of Alzheimer's Disease: A Meta-Analysis. - Koychev, Ivan; Jansen, Katrin; Dette, Alina; Shi, Liu; Holling, Heinz (J Alzheimers Dis, 2021)
BACKGROUND: The Amyloid Tau Neurodegeneration (ATN) framework was proposed to define the biological state underpinning Alzheimer's disease (AD). Blood-based biomarkers offer a scalable alternative to the costly and invasive currently available biomarkers. OBJECTIVE: In this meta-analysis we sought to assess the diagnostic performance of plasma amyloid (Aβ40, Aβ42, Aβ42/40 ratio), tangle (p-tau181), and neurodegeneration (total tau [t-tau], neurofilament light [NfL]) biomarkers. METHODS: Electronic databases were screened for studies reporting biomarker concentrations for AD and control cohorts. Biomarker performance was examined by random-effect meta-analyses based on the ratio between biomarker concentrations in patients and controls. RESULTS: 83 studies published between 1996 and 2020 were included in the analyses. Aβ42/40 ratio as well as Aβ42 discriminated AD patients from controls when using novel platforms such as immunomagnetic reduction (IMR). We found significant differences in ptau-181 concentration for studies based on single molecule array (Simoa), but not for studies based on IMR or ELISA. T-tau was significantly different between AD patients and control in IMR and Simoa but not in ELISA-based studies. In contrast, NfL differentiated between groups across platforms. Exosome studies showed strong separation between patients and controls for Aβ42, t-tau, and p-tau181. CONCLUSION: Currently available assays for sampling plasma ATN biomarkers appear to differentiate between AD patients and controls. Novel assay methodologies have given the field a significant boost for testing these biomarkers, such as IMR for Aβ, Simoa for p-tau181. Enriching samples through extracellular vesicles shows promise but requires further validation.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Humans; Neurodegenerative Diseases; Neurofibrillary Tangles; Neurofilament Proteins; Peptide Fragments; Phosphorylation; Plaque, Amyloid; tau Proteins

Broader Insights into Understanding Tumor Necrosis Factor and Neurodegenerative Disease Pathogenesis Infer New Therapeutic Approaches. - Clark, I A; Vissel, B (J Alzheimers Dis, 2021)
Proinflammatory cytokines such as tumor necrosis factor (TNF), with its now appreciated key roles in neurophysiology as well as neuropathophysiology, are sufficiently well-documented to be useful tools for enquiry into the natural history of neurodegenerative diseases. We review the broader literature on TNF to rationalize why abruptly-acquired neurodegenerative states do not exhibit the remorseless clinical progression seen in those states with gradual onsets. We propose that the three typically non-worsening neurodegenerative syndromes, post-stroke, post-traumatic brain injury (TBI), and post cardiac arrest, usually become and remain static because of excess cerebral TNF induced by the initial dramatic peak keeping microglia chronically activated through an autocrine loop of microglial activation through excess cerebral TNF. The existence of this autocrine loop rationalizes post-damage repair with perispinal etanercept and proposes a treatment for cerebral aspects of COVID-19 chronicity. Another insufficiently considered aspect of cerebral proinflammatory cytokines is the fitness of the endogenous cerebral anti-TNF system provided by norepinephrine (NE), generated and distributed throughout the brain from the locus coeruleus (LC). We propose that an intact LC, and therefore an intact NE-mediated endogenous anti-cerebral TNF system, plus the DAMP (damage or danger-associated molecular pattern) input having diminished, is what allows post-stroke, post-TBI, and post cardiac arrest patients a strong long-term survival advantage over Alzheimer's disease and Parkinson's disease sufferers. In contrast, Alzheimer's disease and Parkinson's disease patients remorselessly worsen, being handicapped by sustained, accumulating, DAMP and PAMP (pathogen-associated molecular patterns) input, as well as loss of the LC-origin, NE-mediated, endogenous anti-cerebral TNF system. Adrenergic receptor agonists may counter this.
Keywords: Alzheimer Disease; Anti-Inflammatory Agents, Non-Steroidal; Brain; Brain Injuries; COVID-19; Disease Progression; Etanercept; Heart Arrest; Humans; Locus Coeruleus; Neurodegenerative Diseases; Norepinephrine; Parkinson Disease; Risk Factors; SARS-CoV-2; Stroke; Survivors; Tumor Necrosis Factor-alpha

Could Altered Evoked Pain Responsiveness Be a Phenotypic Biomarker for Alzheimer's Disease Risk? A Cross-Sectional Analysis of Cognitively Healthy Individuals. - Romano, Raymond R; Carter, Michael A; Dietrich, Mary S; Cowan, Ronald L; Bruehl, Stephen P; Monroe, Todd B (J Alzheimers Dis, 2021)
BACKGROUND: This study evaluated whether the apolipoprotein ɛ4 (APOE4) allele, a genetic marker associated with increased risk of developing late-onset Alzheimer's disease (AD), was associated with differences in evoked pain responsiveness in cognitively healthy subjects. OBJECTIVE: The aim was to determine whether individuals at increased risk of late-onset AD based on APOE allele genotype differ phenotypically in their response to experimentally-induced painful stimuli compared to those who do not have at least one copy of the ɛ4 allele. METHODS: Forty-nine cognitively healthy subjects aged 30-89 years old with the APOE4 allele (n = 12) and without (n = 37) were assessed for group differences in pain thresholds and affective (unpleasantness) responses to experimentally-induced thermal pain stimuli. RESULTS: Statistically significant main effects of APOE4 status were observed for both the temperature at which three different pain intensity percepts were reached (p = 0.040) and the level of unpleasantness associated with each (p = 0.014). APOE4 positive participants displayed lower overall pain sensitivity than those who were APOE4 negative and also greater overall levels of pain unpleasantness regardless of intensity level. CONCLUSION: Cognitively healthy APOE4 carriers at increased risk of late-onset AD demonstrated reduced thermal pain sensitivity but greater unpleasantness to thermal pain stimuli relative to individuals at lower risk of late-onset AD. These results suggest that altered evoked pain perception could potentially be used as a phenotypic biomarker of late-onset AD risk prior to disease onset. Additional studies of this issue may be warranted.
Keywords: Adult; Aged; Aged, 80 and over; Alleles; Alzheimer Disease; Apolipoprotein E4; Biomarkers; Cross-Sectional Studies; Female; Genetic Association Studies; Hot Temperature; Humans; Male; Middle Aged; Pain Perception; Phenotype; Risk Factors

Current and Future Prevalence Estimates of Mild Cognitive Impairment, Dementia, and Its Subtypes in a Population-Based Sample of People 70 Years and Older in Norway: The HUNT Study. - GjØra, Linda; Strand, Bjørn Heine; Bergh, Sverre; Borza, Tom; Brækhus, Anne; Engedal, Knut; Johannessen, Aud; Kvello-Alme, Marte; Krokstad, Steinar; Livingston, Gill; Matthews, Fiona E; Myrstad, Christian; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Having accurate, up-to-date information on the epidemiology of mild cognitive impairment (MCI) and dementia is imperative. OBJECTIVE: To determine the prevalence of MCI and dementia in Norway using data from a large population-based study. METHODS: All people 70 + years of age, n = 19,403, in the fourth wave of the Trøndelag Health Study (HUNT4) were invited to participate in the study HUNT4 70 + . Trained health personnel assessed participants using cognitive tests at a field station, at homes, or at their nursing home. Interviewers also completed a structured carer questionnaire in regard to participants suspected of having dementia. Clinical experts made diagnoses according to DSM-5 criteria. We calculated prevalence weighing the data to ensure population representativeness. RESULTS: A total of 9,930 (51.2%) of the possible 19,403 people participated, and 9,663 of these had sufficient information for analysis. Standardized prevalence of dementia and MCI was 14.6% (95% confidence interval (CI) 13.9-15.4) and 35.3% (95% CI 34.3-36.4), respectively. Dementia was more prevalent in women and MCI more prevalent in men. The most prevalent dementia subtype was Alzheimer's disease (57%). By adding data collected from a study of persons < 70 years in the same region, we estimate that there are 101,118 persons with dementia in Norway in 2020, and this is projected to increase to 236,789 and 380,134 in 2050 and 2100, respectively. CONCLUSION: We found a higher prevalence of dementia and MCI than most previous studies. The present prevalence and future projections are vital for preparing for future challenges to the healthcare system and the entire society.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cognitive Dysfunction; Dementia; Female; Forecasting; Humans; Male; Mental Status and Dementia Tests; Neuropsychological Tests; Norway; Prevalence; Sex Factors; Surveys and Questionnaires

Current Status and Challenges of Stem Cell Treatment for Alzheimer's Disease. - Pacheco-Herrero, Mar; Soto-Rojas, Luis O; Reyes-Sabater, Heidy; Garcés-Ramirez, Linda; de la Cruz López, Fidel; Villanueva-Fierro, Ignacio; Luna-Muñoz, José (J Alzheimers Dis, 2021)
Neurodegenerative diseases called tauopathies, such as Alzheimer's disease (AD), frontotemporal dementia, progressive supranuclear palsy, and Parkinson's disease, among others, are characterized by the pathological processing and accumulation of tau protein. AD is the most prevalent neurodegenerative disease and is characterized by two lesions: neurofibrillary tangles (NFTs) and neuritic plaques. The presence of NFTs in the hippocampus and neocortex in early and advanced stages, respectively, correlates with the patient's cognitive deterioration. So far, no drugs can prevent, decrease, or limit neuronal death due to abnormal pathological tau accumulation. Among potential non-pharmacological treatments, physical exercise has been shown to stimulate the development of stem cells (SCs) and may be useful in early stages. However, this does not prevent neuronal death from the massive accumulation of NFTs. In recent years, SCs therapies have emerged as a promising tool to repopulate areas involved in cognition in neurodegenerative diseases. Unfortunately, protocols for SCs therapy are still being developed and the mechanism of action of such therapy remains unclear. In this review, we show the advances and limitations of SCs therapy. Finally, we provide a critical analysis of its clinical use for AD.
Keywords: Alzheimer Disease; Amyloid; Government Regulation; Hippocampus; Humans; Neocortex; Neurofibrillary Tangles; Plaque, Amyloid; Stem Cells; tau Proteins

Dementia and COVID-19, a Bidirectional Liaison: Risk Factors, Biomarkers, and Optimal Health Care. - Toniolo, Sofia; Scarioni, Marta; Di Lorenzo, Francesco; Hort, Jakub; Georges, Jean; Tomic, Svetlana; Nobili, Flavio; Frederiksen, Kristian Steen (J Alzheimers Dis, 2021)
Cognitive impairment following SARS-CoV-2 infection is being increasingly recognized as an acute and possibly also long-term sequela of the disease. Direct viral entry as well as systemic mechanisms such as cytokine storm are thought to contribute to neuroinflammation in these patients. Biomarkers of COVID-19-induced cognitive impairment are currently lacking, but there is some limited evidence that SARS-CoV-2 could preferentially target the frontal lobes, as suggested by behavioral and dysexecutive symptoms, fronto-temporal hypoperfusion on MRI, EEG slowing in frontal regions, and frontal hypometabolism on 18F-FDG-PET. Possible confounders include cognitive impairment due to hypoxia and mechanical ventilation and post-traumatic stress disorder. Conversely, patients already suffering from dementia, as well as their caregivers, have been greatly impacted by the disruption of their care caused by COVID-19. Patients with dementia have experienced worsening of cognitive, behavioral, and psychological symptoms, and the rate of COVID-19-related deaths is disproportionately high among cognitively impaired people. Multiple factors, such as difficulties in remembering and executing safeguarding procedures, age, comorbidities, residing in care homes, and poorer access to hospital standard of care play a role in the increased morbidity and mortality. Non-pharmacological interventions and new technologies have shown a potential for the management of patients with dementia, and for the support of their caregivers.
Keywords: Alzheimer Disease; Biomarkers; Brain; Cognitive Dysfunction; Comorbidity; COVID-19; Humans; Neuroimaging; Neuroimmunomodulation; Patient Care; SARS-CoV-2

Dementia-Friendly "Design": Impact on COVID-19 Death Rates in Long-Term Care Facilities Around the World. - Olson, Nancy L; Albensi, Benedict C (J Alzheimers Dis, 2021)
Persons with dementia (PWD) make up a large portion of the long-term care (LTC) population the world over. Before a global pandemic swept the world, governments and healthcare providers struggled with how to best care for this unique population. One of the greatest challenges is a PWD's tendency to "walk with purpose" and exhibit unsafe wayfinding and elopement, which places them at risk of falls and injury. Past solutions included increased use of restraints and pharmacological interventions, but these have fallen out of favor over the years and are not optimal. These challenges put enormous strain on staff and caregivers, who are often poorly trained in dementia care, underpaid, overworked, and overstressed. PWD are impacted by these stresses, and unmet needs in LTC places an even greater stress on them and increases their risks of morbidity and mortality. The physical design of their environments contributes to the problem. Old, institutionalized buildings have poor lighting, poor ventilation, long dead-end hallways, poor visual cues, lack of home-like décor, shared bedrooms and bathrooms, and are often dense and overcrowded. These design elements contribute to the four 'A's' of dementia: apathy, anxiety, agitation, and aggression, and they also contributed to the rapid spread of COVID-19 in these facilities the world over. In this review, we present current "dementia friendly" design models in the home, community, and LTC, and argue how they could have saved lives during the pandemic and reduced the stresses on both the dementia resident and the caregiver/staff.
Keywords: COVID-19; Dementia; Environment Design; Health Services Needs and Demand; Humans; Long-Term Care; Pandemics; Quality of Life

Different Inflammatory Signatures in Alzheimer's Disease and Frontotemporal Dementia Cerebrospinal Fluid. - Boström, Gustaf; Freyhult, Eva; Virhammar, Johan; Alcolea, Daniel; Tumani, Hayrettin; Otto, Markus; Brundin, Rose-Marie; Kilander, Lena; Löwenmark, Malin; Giedraitis, Vilmantas; Lleo, Alberto; von Arnim, Christine A F; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Neuroinflammatory processes are common in neurodegenerative diseases such as Alzheimer's disease (AD) and frontotemporal dementia (FTD), but current knowledge is limited as to whether cerebrospinal fluid (CSF) levels of neuroinflammatory proteins are altered in these diseases. OBJECTIVE: To identify and characterize neuroinflammatory signatures in CSF from patients with AD, mild cognitive impairment (MCI), and FTD. METHODS: We used proximity extension assay and ANOVA to measure and compare levels of 92 inflammatory proteins in CSF from 42 patients with AD, 29 with MCI due to AD (MCI/AD), 22 with stable MCI, 42 with FTD, and 49 control subjects, correcting for age, gender, collection unit, and multiple testing. RESULTS: Levels of matrix metalloproteinase-10 (MMP-10) were increased in AD, MCI/AD, and FTD compared with controls (AD: fold change [FC] = 1.32, 95% confidence interval [CI] 1.14-1.53, q = 0.018; MCI/AD: FC = 1.53, 95% CI 1.20-1.94, q = 0.045; and FTD: FC = 1.42, 95% CI 1.10-1.83, q = 0.020). MMP-10 and eleven additional proteins were increased in MCI/AD, compared with MCI (q < 0.05). In FTD, 36 proteins were decreased, while none was decreased in AD or MCI/AD, compared with controls (q < 0.05). CONCLUSION: In this cross-sectional multi-center study, we found distinct patterns of CSF inflammatory marker levels in FTD and in both early and established AD, suggesting differing neuroinflammatory processes in the two disorders.
Keywords: Aged; Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Cognitive Dysfunction; Cross-Sectional Studies; Female; Frontotemporal Dementia; Humans; Inflammation; Male; Middle Aged; Peptide Fragments; tau Proteins

Effects of COVID-19 Home Confinement on Mental Health in Individuals with Increased Risk of Alzheimer's Disease. - Soldevila-Domenech, Natalia; Forcano, Laura; Boronat, Anna; Lorenzo, Thais; Piera, Iris; Puig-Pijoan, Albert; Mateus, Julian; González de Echevarri Gómez, José María; Knezevic, Iva; Soteras, Anna; Fauria, Karine; Pizarro, Nieves; et al. (J Alzheimers Dis, 2021)
We explored the impact of the Spanish COVID-19 strict home confinement on mental health and cognition in non-infected subjects (N = 16, 60-80 years) diagnosed with subjective cognitive decline and APOEɛ3/ɛ4 carriers. Mental health was monitored for 2 months on a daily, weekly, or monthly basis, and compared to pre-confinement values. Emotional distress, anxiety, and depression scores increased to pathological threshold values during and after confinement. Those with lower mood during confinement experienced a decline in their mood after confinement. Cognition did not change. These preliminary results suggest that mental health consequences of corona measures in preclinical stages of Alzheimer's disease should be further evaluated.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Anxiety Disorders; Apolipoprotein E3; Apolipoprotein E4; Cognition Disorders; Cognitive Dysfunction; COVID-19; Depressive Disorder; Female; Humans; Male; Mental Health; Middle Aged; Psychological Distress; Quarantine; Risk; Spain

Elevated Norepinephrine Metabolism Gauges Alzheimer's Disease-Related Pathology and Memory Decline. - Riphagen, Joost M; van Egroo, Maxime; Jacobs, Heidi I L (J Alzheimers Dis, 2021)
The noradrenergic (NE) locus coeruleus (LC) is vulnerable to hyperphosphorylated tau, and dysregulated NE-metabolism is linked to greater tau and disease progression. We investigated whether elevated NE-metabolism alone predicts memory decline or whether concomitant presence of tau and amyloid-β is required. Among 114 memory clinic participants, time trends (max. six years) showed dose-response declines in learning across groups with elevated NE-metabolite 3-methoxy-4-hydroxyphenylethyleneglycol (MHPG) with no, one, or two Alzheimer's disease biomarkers; and no decline in the low MHPG group. Elevated MHPG is required and sufficient to detect learning declines, supporting a pathophysiologic model including the LC-NE system contributing to initial Alzheimer's disease-related processes.
Keywords: Aged; Alzheimer Disease; Amyloid beta-Peptides; Cognitive Dysfunction; Cohort Studies; Disease Progression; Female; Humans; Learning; Locus Coeruleus; Male; Memory Disorders; Methoxyhydroxyphenylglycol; Middle Aged; Neuropsychological Tests; Norepinephrine; Predictive Value of Tests; tau Proteins

Is Engagement in Intellectual and Social Leisure Activities Protective Against Dementia Risk? Evidence from the English Longitudinal Study of Ageing. - Almeida-Meza, Pamela; Steptoe, Andrew; Cadar, Dorina (J Alzheimers Dis, 2021)
BACKGROUND: Studies have suggested that mentally stimulating activities and socially engaged lifestyles may reduce dementia risk; however, it is unclear which activities are more beneficial. OBJECTIVE: We investigated intellectual and social leisure activities in relation to dementia incidence and explored the modifying role of sex and marital status in these associations. METHODS: The sample was comprised of 8,030 participants aged 50+ from the English Longitudinal Study of Ageing, who joined at wave 1 (2002-2003), or waves 3 (2006-2007), or 4 (2008-2009). The end of the study period was wave 8 (2016-2017). Subdistribution hazard models investigated the role of leisure activities grouped into intellectual and social domains in relation to dementia while accounting for the risk of death. Subsequent analyses were conducted with individual leisure activities. RESULTS: During the study period of up to 15 years, 412 participants developed dementia, and 2,192 died. We found that increased engagement in the intellectual activities' domain was associated with a decreased dementia incidence (SHR 0.85, 95% CI 0.76-0.96, p = 0.007), independent of the risk of death in married individuals, but not in those who were single, divorced, or widowed. Individual analyses for each leisure activity showed independent associations for reading newspapers in females (SHR 0.65, 95% CI 0.49-0.84, p = 0.001), mobile phone usage in males (SHR 0.61, 95% CI 0.45-0.84, p = 0.002), and having hobbies for married individuals (SHR 0.70, 95% CI 0.51-0.95, p = 0.02). CONCLUSION: We found that intellectual leisure activities contribute to lower dementia risk in a representative population of English adults, suggesting intervention opportunities.
Keywords: Aged; Aged, 80 and over; Aging; Dementia; Female; Humans; Incidence; Leisure Activities; Life Style; Longitudinal Studies; Male; Marital Status; Middle Aged; Proportional Hazards Models; Sex Factors; Social Behavior; Surveys and Questionnaires; Survival Analysis; United Kingdom

How Do Persons with Young and Late Onset Dementia Die? - Roβmeier, Carola; Hartmann, Julia; Riedl, Lina; Dorn, Bianca; Fischer, Julia; Hartmann, Florentine; Egert-Schwender, Silvia; Kehl, Victoria; Schneider-Schelte, Helga; Jox, Ralf J; Dinkel, Andreas; Diehl-Schmid, Janine (J Alzheimers Dis, 2021)
BACKGROUND: End of life symptoms and symptom management as well as the quality of dying (QoD) of persons with advanced dementia (PWAD) have not yet been systematically studied in Germany. OBJECTIVE: 1) To investigate symptoms, treatment and care at the end of life, advance care planning, and circumstances of death of recently deceased PWAD; 2) To determine whether there are differences between young and late onset dementia (YOD and LOD). METHODS: The study was performed in the context of the project EPYLOGE (IssuEs in Palliative care for persons in advanced and terminal stages of Young-onset and Late-Onset dementia in Germany). Closest relatives of recently deceased patients with advanced YOD (N = 46) and LOD (N = 54) living at home or in long term care were interviewed. RESULTS: Circumstances of death, symptoms, and treatment appeared to be similar between YOD and LOD, except that persons with LOD had significantly more somatic comorbidities and were admitted to hospital in the last three months of life more often than persons with LOD. At end of life, 60% of PWAD appeared to be "at peace". Difficulty swallowing, gurgling, shortness of breath, and discomfort were observed most frequently. Large interindividual differences in suffering and QoD were present. Determinants of QoD were not identified. CONCLUSION: Our findings suggest that low QoD was caused by inadequate recognition and/or insufficient treatment of burdensome physical and emotional symptoms. PWADs' needs should be assessed regularly, and strategies focusing on treatment and implementing support for both the patient and caregiver must be established.
Keywords: Advance Care Planning; Age of Onset; Aged; Aged, 80 and over; Caregivers; Dementia; Female; Humans; Long-Term Care; Male; Palliative Care; Quality of Life

The Impact of a Global Pandemic on People Living with Dementia and Their Care Partners: Analysis of 417 Lived Experience Reports. - Tam, Mallorie T; Dosso, Jill A; Robillard, Julie M (J Alzheimers Dis, 2021)
BACKGROUND: The COVID-19 pandemic is impacting the physical and emotional health of older adults living with dementia and their care partners. OBJECTIVE: Using a patient-centered approach, we explored the experiences and needs of people living with dementia and their care partners during the COVID-19 pandemic as part of an ongoing evaluation of dementia support services in British Columbia, Canada. METHODS: A survey instrument was developed around the priorities identified in the context of the COVID-19 and Dementia Task Force convened by the Alzheimer Society of Canada. RESULTS: A total of 417 surveys were analyzed. Overall, respondents were able to access information that was helpful for maintaining their own health and managing a period of social distancing. Care partners reported a number of serious concerns, including the inability to visit the person that they care for in long-term or palliative care. Participants also reported that the pandemic increased their levels of stress overall and that they felt lonelier and more isolated than they did before the pandemic. The use of technology was reported as a way to connect socially with their loved ones, with the majority of participants connecting with others at least twice per week. CONCLUSION: Looking at the complex effects of a global pandemic through the experiences of people living with dementia and their care partners is vital to inform healthcare priorities to restore their quality of life and health and better prepare for the future.
Keywords: Adaptation, Psychological; Aged; Alzheimer Disease; British Columbia; Caregivers; COVID-19; Disabled Persons; Female; Humans; Loneliness; Male; Needs Assessment; Psychosocial Support Systems; Social Isolation; Social Support; Stress, Psychological; Surveys and Questionnaires

Impact of Social Isolation on People with Dementia and Their Family Caregivers. - Azevedo, Lílian Viana Dos Santos; Calandri, Ismael Luis; Slachevsky, Andrea; Graviotto, Héctor Gastón; Vieira, Maria Carolina Santos; Andrade, Caíssa Bezerra de; Rossetti, Adriana Peredo; Generoso, Alana Barroso; Carmona, Karoline Carvalho; Pinto, Ludmilla Aparecida Cardoso; Sorbara, Marcos; Pinto, Alejandra; et al. (J Alzheimers Dis, 2021)
BACKGROUND: People with dementia and their family caregivers may face a great burden through social isolation due to the COVID-19 pandemic, which can be manifested as various behavioral and clinical symptoms. OBJECTIVE: To investigate the impacts of social isolation due to the COVID-19 pandemic on individuals with dementia and their family caregivers. METHODS: Two semi-structured questionnaires were applied via telephone to family caregivers of people diagnosed with dementia in three cities in Argentina, Brazil, and Chile, in order to assess clinical and behavioral changes in people with dementia and in their caregivers. RESULTS: In general, 321 interviews were conducted. A significant decline in memory function has been reported among 53.0%of people with dementia. In addition, 31.2%of individuals with dementia felt sadder and 37.4%had increased anxiety symptoms. These symptoms of anxiety were greater in individuals with mild to moderate dementia, while symptoms of agitation were greater in individuals with severe dementia. Moreover, compulsive-obsessive behavior, hallucinations, increased forgetfulness, altered appetite, and increased difficulty in activities of daily living were reported more frequently among individuals with moderate to severe dementia. Caregivers reported feeling more tired and overwhelmed during this period and these symptoms were also influenced by the severity of dementia. CONCLUSION: Social isolation during the COVID-19 pandemic triggered a series of negative behavioral repercussions, both for people with dementia and for their family caregivers in these three South American countries.
Keywords: Activities of Daily Living; Adult; Aged; Aged, 80 and over; Argentina; Brazil; Caregivers; Chile; COVID-19; Dementia; Female; Humans; Male; Middle Aged; Pandemics; Physical Distancing; Social Isolation; Surveys and Questionnaires

Incremental Healthcare Utilization and Cost Burden of Comorbid Insomnia in Alzheimer's Disease Patients. - Qureshi, Zaina P; Thiel, Ellen; Nelson, James; Khandker, Rezaul (J Alzheimers Dis, 2021)
BACKGROUND: Insomnia is associated with worsened clinical outcomes among Alzheimer's disease dementia (AD) patients, increased caregiver burden, and healthcare utilization. OBJECTIVE: This study aimed to characterize the incremental healthcare burden of insomnia in AD using real-world data. METHODS: A retrospective observational study was conducted on AD patients selected from the IBM® MarketScan Commercial and Medicare Supplemental Databases. AD patients with claims-based evidence of insomnia were direct matched to a non-insomnia cohort based on demographic factors. Healthcare utilization and associated costs were assessed for a 12-month follow-up period. RESULTS: A total of 3,500 insomnia AD patients and 9,884 non-insomnia AD patients were analyzed. The insomnia cohort had a higher comorbidity burden at baseline (mean score on Charlson Comorbidity Index 2.5 versus 2.2, p < 0.001) and higher proportions of patients with baseline diagnoses for other conditions including depression: 40%, insomnia cohort versus 25%, non-insomnia (p < 0.001). AD patients with insomnia were more likely to have a claim for inpatient hospitalizations (39.8%versus 32.3%), emergency room services (56.4%versus 48.0%), and skilled-nursing services (42.6%versus 31.9%) (all p < 0.05). Mean total annual healthcare costs during the 12-month follow-up period were significantly higher among AD patients with insomnia as compared to those without. (Mean costs: $37,356 versus $27,990, p < 0.001). CONCLUSION: AD patients with comorbid insomnia are more likely to use higher-cost healthcare services such as inpatient hospitalization, and skilled nursing, and have higher total healthcare costs. This real-world analysis provides evidence that AD disease management should consider proper treatment of comorbid insomnia due to the incremental burden and cost implications.
Keywords: Aged, 80 and over; Alzheimer Disease; Comorbidity; Databases, Factual; Female; Health Care Costs; Humans; Male; Medicare; Patient Acceptance of Health Care; Retrospective Studies; Sleep Initiation and Maintenance Disorders; United States

An Introduction to Ultrasensitive Assays for Plasma Tau Detection. - Ding, Xu-Long; Tuo, Qing-Zhang; Lei, Peng (J Alzheimers Dis, 2021)
The detection of plasma tau and its phosphorylation is technically challenging due to the relatively low sensitivity. However, in Alzheimer's disease and other tauopathies, it is hypothesized that tau in the biofluid may serve as a biomarker. In recent years, several ultrasensitive assays have been developed, which can successfully detect tau and its phosphorylation in various biofluids, and collectively demonstrated the prognostic and diagnostic value of plasma tau/phosphorylated tau. Here we have summarized the principle of four ultrasensitive assays newly developed suitable for plasma tau detection, namely single-molecule array, immunomagnetic reduction assay, enhanced immunoassay using multi-arrayed fiber optics, and meso scale discovery assay, with their advantages and applications. We have also compared these assays with traditional enzyme-linked-immunosorbent serologic assay, hoping to facilitate future tau-based biomarker discovery for Alzheimer's disease and other neurodegenerative diseases.
Keywords: Alzheimer Disease; Biological Assay; Biomarkers; Enzyme-Linked Immunosorbent Assay; Humans; Phosphorylation; tau Proteins

Life Course Air Pollution Exposure and Cognitive Decline: Modelled Historical Air Pollution Data and the Lothian Birth Cohort 1936. - Russ, Tom C; Cherrie, Mark P C; Dibben, Chris; Tomlinson, Sam; Reis, Stefan; Dragosits, Ulrike; Vieno, Massimo; Beck, Rachel; Carnell, Ed; Shortt, Niamh K; Muniz-Terrera, Graciela; Redmond, Paul; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Air pollution has been consistently linked with dementia and cognitive decline. However, it is unclear whether risk is accumulated through long-term exposure or whether there are sensitive/critical periods. A key barrier to clarifying this relationship is the dearth of historical air pollution data. OBJECTIVE: To demonstrate the feasibility of modelling historical air pollution data and using them in epidemiologicalmodels. METHODS: Using the EMEP4UK atmospheric chemistry transport model, we modelled historical fine particulate matter (PM2.5) concentrations for the years 1935, 1950, 1970, 1980, and 1990 and combined these with contemporary modelled data from 2001 to estimate life course exposure in 572 participants in the Lothian Birth Cohort 1936 with lifetime residential history recorded. Linear regression and latent growth models were constructed using cognitive ability (IQ) measured by the Moray House Test at the ages of 11, 70, 76, and 79 years to explore the effects of historical air pollution exposure. Covariates included sex, IQ at age 11 years, social class, and smoking. RESULTS: Higher air pollution modelled for 1935 (when participants would have been in utero) was associated with worse change in IQ from age 11-70 years (β = -0.006, SE = 0.002, p = 0.03) but not cognitive trajectories from age 70-79 years (p > 0.05). There was no support for other critical/sensitive periods of exposure or an accumulation of risk (all p > 0.05). CONCLUSION: The life course paradigm is essential in understanding cognitive decline and this is the first study to examine life course air pollution exposure in relation to cognitive health.
Keywords: Adolescent; Adult; Aged; Air Pollution; Child; Cognitive Dysfunction; Environmental Exposure; Female; History, 20th Century; Humans; Linear Models; Male; Middle Aged; Particulate Matter; Scotland; Young Adult

Low Doses of Ionizing Radiation as a Treatment for Alzheimer's Disease: A Pilot Study. - Cuttler, Jerry M; Abdellah, Eslam; Goldberg, Yael; Al-Shamaa, Sarmad; Symons, Sean P; Black, Sandra E; Freedman, Morris (J Alzheimers Dis, 2021)
BACKGROUND: In 2015, a patient in hospice with Alzheimer's disease (AD) was treated with ionizing radiation to her brain using repeated CT scans. Improvement in cognition, speech, movement, and appetite was observed. These improvements were so momentous that she was discharged from the hospice to a long-term care home. Based on this case, we conducted a pilot clinical trial to examine the effect of low-dose ionizing radiation (LDIR) in severe AD. OBJECTIVE: To determine whether the previously reported benefits of LDIR in a single case with AD could be observed again in other cases with AD when the same treatments are given. METHODS: In this single-arm study, four patients were treated with three consecutive treatments of LDIR, each spaced two weeks apart. Qualitative changes in communication and behavior with close relatives were observed and recorded. Quantitative measures of cognition and behavior were administered pre and post LDIR treatments. RESULTS: Minor improvements on quantitative measures were noted in three of the four patients following treatment. However, the qualitative observations of cognition and behavior suggested remarkable improvements within days post-treatment, including greater overall alertness. One patient showed no change. CONCLUSION: LDIR may be a promising, albeit controversial therapy for AD. Trials of patients with less severe AD, double-blind and placebo-controlled, should be carried out to determine the benefits of LDIR. Quantitative measures are needed that are sensitive to the remarkable changes induced by LDIR, such as biological markers of oxidative stress that are associated with AD.
Keywords: Aged, 80 and over; Alzheimer Disease; Cranial Irradiation; Female; Humans; Male; Pilot Projects; Radiation, Ionizing

Memory-Related Frontal Brainwaves Predict Transition to Mild Cognitive Impairment in Healthy Older Individuals Five Years Before Diagnosis. - Jiang, Yang; Li, Juan; Schmitt, Frederick A; Jicha, Gregory A; Munro, Nancy B; Zhao, Xiaopeng; Smith, Charles D; Kryscio, Richard J; Abner, Erin L (J Alzheimers Dis, 2021)
BACKGROUND: Early prognosis of high-risk older adults for amnestic mild cognitive impairment (aMCI), using noninvasive and sensitive neuromarkers, is key for early prevention of Alzheimer's disease. We have developed individualized measures in electrophysiological brain signals during working memory that distinguish patients with aMCI from age-matched cognitively intact older individuals. OBJECTIVE: Here we test longitudinally the prognosis of the baseline neuromarkers for aMCI risk. We hypothesized that the older individuals diagnosed with incident aMCI already have aMCI-like brain signatures years before diagnosis. METHODS: Electroencephalogram (EEG) and memory performance were recorded during a working memory task at baseline. The individualized baseline neuromarkers, annual cognitive status, and longitudinal changes in memory recall scores up to 10 years were analyzed. RESULTS: Seven of the 19 cognitively normal older adults were diagnosed with incident aMCI for a median 5.2 years later. The seven converters' frontal brainwaves were statistically identical to those patients with diagnosed aMCI (n = 14) at baseline. Importantly, the converters' baseline memory-related brainwaves (reduced mean frontal responses to memory targets) were significantly different from those who remained normal. Furthermore, differentiation pattern of left frontal memory-related responses (targets versus nontargets) was associated with an increased risk hazard of aMCI (HR = 1.47, 95% CI 1.03, 2.08). CONCLUSION: The memory-related neuromarkers detect MCI-like brain signatures about five years before diagnosis. The individualized frontal neuromarkers index increased MCI risk at baseline. These noninvasive neuromarkers during our Bluegrass memory task have great potential to be used repeatedly for individualized prognosis of MCI risk and progression before clinical diagnosis.
Keywords: Aged; Brain Waves; Cognition; Cognitive Dysfunction; Electroencephalography; Female; Humans; Longitudinal Studies; Male; Memory, Short-Term; Neuropsychological Tests; Prodromal Symptoms

Modifiable Barriers for Recruitment and Retention of Older Adults Participants from Underrepresented Minorities in Alzheimer's Disease Research. - Indorewalla, Khushnoo K; O'Connor, Maureen K; Budson, Andrew E; Guess DiTerlizzi, Christina; Jackson, Jonathan (J Alzheimers Dis, 2021)
Clinical Alzheimer's disease (AD) trials currently face a critical shortfall of thousands of eligible participants, which inflates the duration and cost of the clinical study as well as threatens the scientific merit of promising clinical interventions. This recruitment crisis is further compounded by the fact that underrepresented and marginalized populations-particularly those identifying as a racial or ethnic minority, those with low socioeconomic status, or living in rural areas-have been historically underrepresented in ongoing AD clinical trials despite overwhelming evidence that such populations are at increased risk for developing dementia. As a result of various recruitment barriers, current AD clinical studies frequently reflect a decreasingly representative segment of the US population, which threatens the overall generalizability of these findings. The current narrative review provides an updated examination and critique of common recruitment barriers and potential solutions, as well as a discussion of theoretical approaches that may address barriers disproportionately experienced by underrepresented communities. AD clinical researchers are encouraged to take purposive action aimed at increasing diversity of enrolled AD clinical trial cohorts by actively identifying and quantifying barriers to research participation-especially recruitment barriers and health disparities that disproportionately prevent underrepresented and marginalized populations from participating in research. Furthermore, researchers are encouraged to closely track which individuals who express interest in AD research ultimately enroll in research studies to examine whether AD research participation is appropriately representative of the intended population for whom these new and novel AD interventions are being designed.
Keywords: Alzheimer Disease; Clinical Trials as Topic; Humans; Minority Groups; Patient Selection

Neuropsychiatric Symptoms in Patients with Dementia Associated with Increased Psychological Distress in Caregivers During the COVID-19 Pandemic. - Borelli, Wyllians Vendramini; Augustin, Marina Coutinho; de Oliveira, Paola Bell Felix; Reggiani, Lorenzo Casagrande; Bandeira-de-Mello, Renato Gorga; Schumacher-Schuh, Artur Francisco; Chaves, Marcia Lorena Fagundes; Castilhos, Raphael Machado (J Alzheimers Dis, 2021)
BACKGROUND: The social isolation imposed by COVID-19 pandemic can have a major impact on the mental health of dementia patients and their caregivers. OBJECTIVE: We aim to evaluate the neurological decline of patients with dementia and the caregivers' burden during the pandemic. METHODS: We performed a cross-sectional study. Caregivers of dementia patients following in the outpatient clinic were included. A structured telephone interview composed of the Neuropsychiatric Inventory Questionnaire (NPI-Q), Zarit Burden Interview (ZBI), Beck Depression (BDI) and Anxiety (BAI) Inventories to address cognitive, behavioral, and functional changes associated with social distancing during the Sars-Cov-2 outbreak. Patients were divided in two groups according to caregivers' report: with perceived Altered Cognition (AC) and Stable Cognition (SC). RESULTS: A total of 58 patients (median age: 57 years [21-87], 58.6%females) and caregivers (median age: 76.5 years [55-89], 79.3%females) were included. Cognitive decline was shown by most patients (53.4%), as well as behavioral symptoms (48.3%), especially apathy/depression (24.1%), and functional decline (34.5%). The AC group (n = 31) presented increased behavioral (67.7%versus 25.9%, p = 0.002) and functional (61.3%versus 3.7%, p < 0.001) changes when compared to the SC group. In the AC group, ZBI, BDI, NPI-Q caregiver distress, and NPI-Q patient's severity of symptoms scores were worse than the SC group (p < 0.005 for all). CONCLUSION: Patients' neuropsychiatric worsening and caregiver burden were frequent during the pandemic. Worsening of cognition was associated with increased caregivers' psychological distress.
Keywords: Adult; Aged; Aged, 80 and over; Brazil; Caregivers; COVID-19; Cross-Sectional Studies; Dementia; Female; Humans; Male; Mental Disorders; Middle Aged; Outpatient Clinics, Hospital; Pandemics; Psychological Distress; Social Isolation; Young Adult

A Novel Approach to the Treatment and Prevention of Alzheimer's Disease Based on the Pathology and Microbiology. - Allen, Herbert B (J Alzheimers Dis, 2021)
Utilizing the pathology and microbiology found in tissue from patients with documented Alzheimer's disease (AD), the pathogenesis of this fateful disorder has been made clear. Borrelia burgdorferi and Treponema denticola spirochetes enter the brain, mostly via neuronal pathways and the entorhinal circulation. These organisms easily pass through the blood-brain barrier and have an affinity for neural tissue. Once in the brain, the spirochetes make intra- and extracellular biofilms, and it is the biofilms that create the pathology. Specifically, it is the intracellular biofilms that are ultimately responsible for neurofibrillary tangles and dendritic disintegration. The extracellular biofilms are responsible for the inflammation that initially is generated by the first responder, Toll-like receptor 2. The hypothesis that arises from this work is two-pronged: one is related to prevention; the other to treatment. Regarding prevention, it is very likely possible that AD could be prevented by periodic administration of penicillin (PCN), which would kill the spirochetes before they made biofilms; this would prevent the disease and would not allow any of the above deleterious changes generated by the biofilms to occur. As regards treatment, it may be possible to slow or prevent further decline in early AD by administration of PCN together with a biofilm disperser. The disperser would disrupt the biofilm coating and enable the PCN to kill the spirochetes. This protocol could be administered in a trial with the control arm utilizing the current treatment. The progress of the treatment could be evaluated by one of the current blood tests that is semi-quantitative. The specific protocols are listed.
Keywords: Alzheimer Disease; Biofilms; Borrelia burgdorferi; Brain; Humans; Inflammation; Neurons; Penicillins; Plaque, Amyloid; tau Proteins; Treponema denticola

Plasma Biomarkers of Alzheimer's Disease in African Americans. - Deniz, Kaancan; Ho, Charlotte C G; Malphrus, Kimberly G; Reddy, Joseph S; Nguyen, Thuy; Carnwath, Troy P; Crook, Julia E; Lucas, John A; Graff-Radford, Neill R; Carrasquillo, Minerva M; Ertekin-Taner, Nilufer (J Alzheimers Dis, 2021)
BACKGROUND/OBJECTIVE: The aim of this study was to determine if plasma concentrations of 5 surrogate markers of Alzheimer's disease (AD) pathology and neuroinflammation are associated with disease status in African Americans. METHODS: We evaluated 321 African Americans (159 AD, 162 controls) from the Florida Consortium for African-American Alzheimer's Disease Studies (FCA3DS). Five plasma proteins reflecting AD neuropathology or inflammation (Aβ42, tau, IL6, IL10, TNFα) were tested for associations with AD, age, sex, APOE and MAPT genotypes, and for pairwise correlations. RESULTS: Plasma tau levels were higher in AD when adjusted for biological and technical covariates. APOEɛ4 was associated with lower plasma Aβ42 and tau levels. Older age was associated with higher plasma Aβ42, tau, and TNFα. Females had lower IL10 levels. Inflammatory proteins had strong pairwise correlations amongst themselves and with Aβ42. CONCLUSION: We identified effects of demographic and genetic variants on five potential plasma biomarkers in African Americans. Plasma inflammatory biomarkers and Aβ42 may reflect correlated pathologies and elevated plasma tau may be a biomarker of AD in this population.
Keywords: African Americans; Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Apolipoproteins E; Case-Control Studies; Female; Humans; Interleukin-10; Interleukin-6; Male; Middle Aged; Peptide Fragments; tau Proteins; Tumor Necrosis Factor-alpha

Polyphenols as Potential Metal Chelation Compounds Against Alzheimer's Disease. - Lakey-Beitia, Johant; Burillo, Andrea M; La Penna, Giovanni; Hegde, Muralidhar L; Rao, K S (J Alzheimers Dis, 2021)
Alzheimer's disease (AD) is the most common neurodegenerative disease affecting more than 50 million people worldwide. The pathology of this multifactorial disease is primarily characterized by the formation of amyloid-β (Aβ) aggregates; however, other etiological factors including metal dyshomeostasis, specifically copper (Cu), zinc (Zn), and iron (Fe), play critical role in disease progression. Because these transition metal ions are important for cellular function, their imbalance can cause oxidative stress that leads to cellular death and eventual cognitive decay. Importantly, these transition metal ions can interact with the amyloid-β protein precursor (AβPP) and Aβ42 peptide, affecting Aβ aggregation and increasing its neurotoxicity. Considering how metal dyshomeostasis may substantially contribute to AD, this review discusses polyphenols and the underlying chemical principles that may enable them to act as natural chelators. Furthermore, polyphenols have various therapeutic effects, including antioxidant activity, metal chelation, mitochondrial function, and anti-amyloidogenic activity. These combined therapeutic effects of polyphenols make them strong candidates for a moderate chelation-based therapy for AD.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Antioxidants; Chelating Agents; Copper; Humans; Oxidative Stress; Polyphenols; Zinc

Porphyromonas gingivalis Outer Membrane Vesicles as the Major Driver of and Explanation for Neuropathogenesis, the Cholinergic Hypothesis, Iron Dyshomeostasis, and Salivary Lactoferrin in Alzheimer's Disease. - Nara, Peter L; Sindelar, Daniel; Penn, Marc S; Potempa, Jan; Griffin, W Sue T (J Alzheimers Dis, 2021)
Porphyromonas gingivalis (Pg) is a primary oral pathogen in the widespread biofilm-induced "chronic" multi-systems inflammatory disease(s) including Alzheimer's disease (AD). It is possibly the only second identified unique example of a biological extremophile in the human body. Having a better understanding of the key microbiological and genetic mechanisms of its pathogenesis and disease induction are central to its future diagnosis, treatment, and possible prevention. The published literature around the role of Pg in AD highlights the bacteria's direct role within the brain to cause disease. The available evidence, although somewhat adopted, does not fully support this as the major process. There are alternative pathogenic/virulence features associated with Pg that have been overlooked and may better explain the pathogenic processes found in the "infection hypothesis" of AD. A better explanation is offered here for the discrepancy in the relatively low amounts of "Pg bacteria" residing in the brain compared to the rather florid amounts and broad distribution of one or more of its major bacterial protein toxins. Related to this, the "Gingipains Hypothesis", AD-related iron dyshomeostasis, and the early reduced salivary lactoferrin, along with the resurrection of the Cholinergic Hypothesis may now be integrated into one working model. The current paper suggests the highly evolved and developed Type IX secretory cargo system of Pg producing outer membrane vesicles may better explain the observed diseases. Thus it is hoped this paper can provide a unifying model for the sporadic form of AD and guide the direction of research, treatment, and possible prevention.
Keywords: Alzheimer Disease; Anti-Infective Agents; Bacterial Outer Membrane Proteins; Bacteroidaceae Infections; Brain; Cholinergic Agents; Extremophiles; Humans; Iron; Lactoferrin; Porphyromonas gingivalis; Saliva

Primary Prevention of Dementia: An Ethical Review. - Horstkötter, Dorothee; Deckers, Kay; Köhler, Sebastian (J Alzheimers Dis, 2021)
Dementia poses important medical and societal challenges, and of all health risks people face in life, dementia is one of the most feared. Recent research indicates that up to about 40% of all cases of dementia might be preventable. A series of environmental, social, and medical risk-factors have been identified that should be targeted from midlife onwards when people are still cognitively healthy. At first glance, this seems not merely advisable, but even imperative. However, these new developments trigger a series of new ethical questions and concerns which have hardly been addressed to date. Pro-active ethical reflection, however, is crucial to ensure that the interests and well-being of those affected, ultimately all of us, are adequately respected. This is the goal of the current contribution. Against the background of a concrete case in primary dementia prevention, it provides a systematic overview of the current ethical literature and sketches an ethical research agenda. First, possible benefits of increased well-being must be balanced with the burdens of being engaged in particularly long-term interventions for which it is unclear whether they will ever pay out on a personal level. Second, while knowledge about one's options to maintain brain health might empower people, it might also undermine autonomy, put high social pressure on people, medicalize healthy adults, and stigmatize those who still develop dementia. Third, while synergistic effects might occur, the ideals of dementia prevention might also conflict with other health and non-health related values people hold in life.
Keywords: Dementia; Ethical Review; Humans; Life Style; Primary Prevention

Quality of Life in Advanced Dementia with Late Onset, Young Onset, and Very Young Onset. - Hartmann, Julia; Roßmeier, Carola; Riedl, Lina; Dorn, Bianca; Fischer, Julia; Slawik, Till; Fleischhaker, Mareike; Hartmann, Florentine; Egert-Schwender, Silvia; Kehl, Victoria; Haller, Bernhard; Schneider-Schelte, Helga; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Advanced stages of dementia are characterized by severe cognitive and physical impairment. It has not yet been investigated whether persons with young onset dementia (YOD) and late onset dementia (LOD) differ in advanced disease stages. OBJECTIVES: To compare quality of life (QoL) between persons with advanced YOD and LOD; to explore the determinants of QoL; to investigate whether YOD and LOD differ with regard to symptoms and care. METHODS: The study was performed in the context of EPYLOGE (IssuEs in Palliative care for persons in advanced and terminal stages of YOD and LOD in Germany). Persons with advanced dementia (PWAD) were assessed and caregivers were interviewed. QoL was measured with the proxy rating Quality of Life in Late Stage Dementia (QUALID) scale. RESULTS: 93 persons with YOD and 98 with LOD were included. No significant differences in QoL were detected. Determinants of QoL were similar in YOD and LOD. Behavioral and psychological symptoms of dementia (BPSD), suffering and other distressing symptoms were associated with a lower QoL. In YOD but not in LOD antipsychotic treatment was associated with low QoL. The group of persons who were younger than 65 years at the time of the study visit experienced significantly more distressing symptoms than older PWAD. CONCLUSION: Overall, persons with advanced YOD do not appear to be disadvantaged compared to old and oldest PWAD. Special attention, however, must be paid to the group of the very young persons who seem to be particularly vulnerable.
Keywords: Adult; Age of Onset; Aged; Aged, 80 and over; Antipsychotic Agents; Behavioral Symptoms; Caregivers; Dementia; Disease Progression; Female; Germany; Home Care Services; Humans; Individuality; Male; Middle Aged; Pain; Palliative Care; Psychotropic Drugs; Quality of Life

Race/Ethnic Disparities in Mild Cognitive Impairment and Dementia: The Northern Manhattan Study. - Wright, Clinton B; DeRosa, Janet T; Moon, Michelle P; Strobino, Kevin; DeCarli, Charles; Cheung, Ying Kuen; Assuras, Stephanie; Levin, Bonnie; Stern, Yaakov; Sun, Xiaoyan; Rundek, Tatjana; Elkind, Mitchell S V; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Variability in dementia rates across racial and ethnic groups has been estimated at 60%. Studies suggest disparities in Caribbean Hispanic and Black populations, but community-based data are limited. OBJECTIVE: Estimate the prevalence of mild cognitive impairment (MCI) and dementia in the racially and ethnically diverse community-based Northern Manhattan Study cohort and examine sociodemographic, vascular risk factor, and brain imaging correlates. METHODS: Cases of MCI and dementia were adjudicated by a team of neuropsychologists and neurologists and prevalence was estimated across race/ethnic groups. Ordinal proportional odds models were used to estimate race/ethnic differences in the prevalence of MCI or dementia adjusting for sociodemographic variables (model 1), model 1 plus potentially modifiable vascular risk factors (model 2), and model 1 plus structural imaging markers of brain integrity (model 3). RESULTS: There were 989 participants with cognitive outcome determinations (mean age 69±9 years; 68% Hispanic, 16% Black, 14% White; 62% women; mean (±SD) follow-up five (±0.6) years). Hispanic and Black participants had greater likelihood of MCI (20%) and dementia (5%) than White participants accounting for age and education differences. Hispanic participants had greater odds of MCI or dementia than both White and Black participants adjusting for sociodemographic variables, vascular risk factors, and brain imaging factors. White matter hyperintensity burden was significantly associated with greater odds of MCI or dementia (OR = 1.3, 1.1 to 1.6), but there was no significant interaction by race/ethnicity. CONCLUSION: In this diverse community-based cohort, cross-sectional data revealed significant race/ethnic disparities in the prevalence of MCI and dementia. Longer follow-up and incidence data are needed to further clarify these relationships.
Keywords: Aged; Aged, 80 and over; Cognitive Dysfunction; Cohort Studies; Cross-Sectional Studies; Dementia; Ethnicity; Female; Humans; Male; Middle Aged; New York City; Prevalence

The Right Temporal Variant of Frontotemporal Dementia Is Not Genetically Sporadic: A Case Series. - Ulugut Erkoyun, Hulya; van der Lee, Sven J; Nijmeijer, Bas; van Spaendonk, Rosalina; Nelissen, Anne; Scarioni, Marta; Dijkstra, Anke; Samancı, Bedia; Gürvit, Hakan; Yıldırım, Zerrin; Tepgeç, Fatih; Bilgic, Basar; et al. (J Alzheimers Dis, 2021)
BACKGROUND: Right temporal variant frontotemporal dementia (rtvFTD) has been generally considered as a right sided variant of semantic variant primary progressive aphasia (svPPA), which is a genetically sporadic disorder. Recently, we have shown that rtvFTD has a unique clinical syndrome compared to svPPA and behavioral variant frontotemporal dementia. OBJECTIVE: We challenge the assumption that rtvFTD is a sporadic, non-familial variant of FTD by identifying potential autosomal dominant inheritance and related genes in rtvFTD. METHODS: We collected all subjects with a diagnosis of FTD or primary progressive aphasia who had undergone genetic screening (n = 284) and subsequently who had a genetic variant (n = 48) with a diagnosis of rtvFTD (n = 6) in 2 specialized memory clinics. RESULTS: Genetic variants in FTD related genes were found in 33% of genetically screened rtvFTD cases; including MAPT (n = 4), GRN (n = 1), and TARDBP (n = 1) genes, whereas only one svPPA case had a genetic variant in our combined cohorts. Additionally, 4 out of 6 rtvFTD subjects had a strong family history for dementia. CONCLUSION: Our results demonstrate that rtvFTD, unlike svPPA, is not a pure sporadic, but a heterogeneous potential genetic variant of FTD, and screening for genetic causes for FTD should be performed in patients with rtvFTD.
Keywords: Aphasia, Primary Progressive; DNA-Binding Proteins; Female; Frontotemporal Dementia; Functional Laterality; Genetic Testing; Genetic Variation; Gyrus Cinguli; Humans; Male; Middle Aged; Progranulins; tau Proteins

A Super-Resolved View of the Alzheimer's Disease-Related Amyloidogenic Pathway in Hippocampal Neurons. - Yu, Yang; Gao, Yang; Winblad, Bengt; Tjernberg, Lars O; Schedin-Weiss, Sophia (J Alzheimers Dis, 2021)
BACKGROUND: Processing of the amyloid-β protein precursor (AβPP) is neurophysiologically important due to the resulting fragments that regulate synapse biology, as well as potentially harmful due to generation of the 42 amino acid long amyloid β-peptide (Aβ42), which is a key player in Alzheimer's disease. OBJECTIVE: Our aim was to clarify the subcellular locations of the fragments involved in the amyloidogenic pathway in primary neurons with a focus on Aβ42 and its immediate substrate AβPP C-terminal fragment (APP-CTF). To overcome the difficulties of resolving these compartments due to their small size, we used super-resolution microscopy. METHODS: Mouse primary hippocampal neurons were immunolabelled and imaged by stimulated emission depletion (STED) microscopy, including three-dimensional three-channel imaging, and quantitative image analyses. RESULTS: The first (β-secretase) and second (γ-secretase) cleavages of AβPP were localized to functionally and distally distinct compartments. The β-secretase cleavage was observed in early endosomes in soma, where we were able to show that the liberated N- and C-terminal fragments were sorted into distinct vesicles budding from the early endosomes. Lack of colocalization of Aβ42 and APP-CTF in soma suggested that γ-secretase cleavage occurs in neurites. Indeed, APP-CTF was, in line with Aβ42 in our previous study, enriched in the presynapse but absent from the postsynapse. In contrast, full-length AβPP was not detected in either the pre- or the postsynaptic side of the synapse. Furthermore, we observed that endogenously produced and endocytosed Aβ42 were localized in different compartments. CONCLUSION: These findings provide critical super-resolved insight into amyloidogenic AβPP processing in primary neurons.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Amyloid beta-Protein Precursor; Amyloid Precursor Protein Secretases; Amyloidogenic Proteins; Animals; Cells, Cultured; Hippocampus; Humans; Mice; Mice, Inbred C57BL; Microscopy; Neurons; Peptide Fragments; Protein Transport

tRNA-Derived Fragments in Alzheimer's Disease: Implications for New Disease Biomarkers and Neuropathological Mechanisms. - Wu, Wenzhe; Lee, Inhan; Spratt, Heidi; Fang, Xiang; Bao, Xiaoyong (J Alzheimers Dis, 2021)
BACKGROUND: Alzheimer's disease (AD) is the most common type of dementia caused by irreversible neurodegeneration, with the onset mechanisms elusive. tRNA-derived RNA fragments (tRFs), a recently discovered family of small non-coding RNAs (sncRNAs), have been found to associate with many human diseases, including infectious, metabolic, and neurological diseases. However, whether tRFs play a role in human AD development is not known. OBJECTIVE: This study aimed to explore whether tRFs are involved in human AD. METHODS: Thirty-four postmortem human hippocampus samples were used. The expression of Drosha, Dicer, and angiogenin (ANG), three ribonucleases responsible for the biogenesis of sncRNAs, was determined by qRT-PCR and western blot. The tRFs in the hippocampus was detected by qRT-PCR or northern blot. We also used qRT-PCR to quantify NOP2/Sun RNA methyltransferase 2 (NSun2) and polyadenylation factor I subunit 1 (CLP1), two tRNA modification enzymes. RESULTS: tRFs derived from a subset of tRNAs are significantly altered in the hippocampus of AD patients. The expression change of some tRFs showed age- and disease stage-dependent. ANG is significantly enhanced in AD, suggesting its role in inducing tRFs in AD. The expression of NSun2 in AD patients younger than 65 was significantly decreased. According to a previous report supporting NSun2-mediated tRNA methylation modification making tRNA less susceptible to ANG-mediated cleavage, our results suggested that the decrease in NSun2 may make tRNAs less methylated and subsequently enhanced tRF production from ANG-mediated tRNA cleavage. CONCLUSION: Our studies demonstrated for the first time the involvement of tRFs in human AD.
Keywords: Aged; Alzheimer Disease; Biomarkers; Blotting, Northern; Case-Control Studies; Hippocampus; Humans; Polymerase Chain Reaction; RNA, Small Untranslated; RNA, Transfer

Awareness of the COVID-19 Outbreak and Resultant Depressive Tendencies in Patients with Severe Alzheimer's Disease. - Tsugawa, Akito; Sakurai, Shu; Inagawa, Yuta; Hirose, Daisuke; Kaneko, Yoshitsugu; Ogawa, Yusuke; Serisawa, Shuntaro; Takenoshita, Naoto; Sakurai, Hirofumi; Kanetaka, Hidekazu; Hirao, Kentaro; Shimizu, Soichiro (J Alzheimers Dis, 2020)
The ongoing coronavirus disease 2019 (COVID-19) pandemic has substantially affected patients with dementia and their caregivers. However, we found not all Alzheimer's disease (AD) patients were afraid of COVID-19 infection. Therefore, we investigated the association between rate of awareness of COVID-19 and depressive tendency in AD. 126 consecutive outpatients with AD were enrolled in this study from May 25, on the day when the declaration of emergency was lifted in Japan, through June 30, 2020. In addition to routine psychological tests, the participants were asked the following two questions: "Do you know COVID-19?" and "Why are you wearing a face mask?". Moderate to severe AD patients were found to have a low COVID-19 recognition rate and did not fully understand why they were wearing face masks. In addition, because they did not understand the seriousness of the COVID-19 outbreak, their Geriatric Depression Scale scores were also substantially lower. These results may appear to simply indicate that people with severe dementia are unaware of current events. However, these results provide insights into how to care for patients with dementia and how to allocate the time and support of our limited staff during the COVID-19 outbreak.
Keywords: Aged; Alzheimer Disease; Awareness; Betacoronavirus; Caregivers; Communicable Disease Control; Coronavirus Infections; COVID-19; Female; Humans; Japan; Male; Mental Competency; Pandemics; Patient Care; Pneumonia, Viral; Psychosocial Support Systems; SARS-CoV-2; Severity of Illness Index

Cognitive Impairment Is a Common Comorbidity in Deceased COVID-19 Patients: A Hospital-Based Retrospective Cohort Study. - Martín-Jiménez, Paloma; Muñoz-García, Mariana I; Seoane, David; Roca-Rodríguez, Lucas; García-Reyne, Ana; Lalueza, Antonio; Maestro, Guillermo; Folgueira, Dolores; Blanco-Palmero, Víctor A; Herrero-San Martín, Alejandro; Llamas-Velasco, Sara; Pérez-Martínez, David A; et al. (J Alzheimers Dis, 2020)
We analyzed the frequency of cognitive impairment (CI) in deceased COVID-19 patients at a tertiary hospital in Spain. Among the 477 adult cases who died after admission from March 1 to March 31, 2020, 281 had confirmed COVID-19. CI (21.1% dementia and 8.9% mild cognitive impairment) was a common comorbidity. Subjects with CI were older, tended to live in nursing homes, had shorter time from symptom onset to death, and were rarely admitted to the ICU, receiving palliative care more often. CI is a frequent comorbidity in deceased COVID-19 subjects and is associated with differences in care.
Keywords: Adolescent; Adult; Age Factors; Aged; Aged, 80 and over; Cognitive Dysfunction; Comorbidity; COVID-19; Female; Hospital Mortality; Hospitals; Humans; Male; Middle Aged; Palliative Care; Patient Admission; Retrospective Studies; Spain; Young Adult

Comparative Cognitive Effects of Choreographed Exercise and Multimodal Physical Therapy in Older Adults with Amnestic Mild Cognitive Impairment: Randomized Clinical Trial. - Bisbe, Marta; Fuente-Vidal, Andrea; López, Elisabet; Moreno, Marta; Naya, Marian; de Benetti, Claudio; Milà, Raimon; Bruna, Olga; Boada, Merce; Alegret, Montserrat (J Alzheimers Dis, 2020)
BACKGROUND: Recent research on mild cognitive impairment (MCI) has primarily focused on searching for measures to prevent or delay the progression of MCI to dementia. Physical exercise has shown to be effective in the prevention of age-related cognitive decline in elderly adults with MCI. However, the most effective type and dose of exercise for the improvement of cognition are yet to be determined. OBJECTIVE: To compare the cognitive effects of choreographed exercise (Choreography group) with a multimodal physical therapy program (Physical Therapy group) in elderly adults with amnestic MCI, a population with an increased risk of developing dementia. METHODS: We conducted a randomized clinical trial with two parallel groups under allocation concealment and assessor blinding. Participants were allocated into Choreography or Physical Therapy group and performed exercises twice per week in 60-minute sessions during 12 weeks. RESULTS: Thirty-six participants with amnestic MCI, ages 65 to 85, were assessed at baseline and after 12 weeks of intervention, by comprehensive validated neuropsychological and physical assessments. A Repeated measures General Lineal Model showed statistically significant differences in cognitive and physical outcomes. Both groups significantly improved in visual delayed recall. The Choreography group exhibited significantly more benefits on verbal recognition memory than the Physical Therapy group. CONCLUSION: Greater cognitive benefits were achieved in the choreographic intervention than in the multimodal physical therapy, mainly in those functions more related to the risk of conversion to dementia. Additional studies are needed to confirm whether the observed effects are related to delayed onset of Alzheimer's disease in elderly adults with amnestic MCI.
Keywords: Aged; Aged, 80 and over; Cognitive Dysfunction; Combined Modality Therapy; Dance Therapy; Exercise Therapy; Female; Humans; Linear Models; Male; Neuropsychological Tests; Physical Therapy Modalities; Single-Blind Method

COVID-19: Review of a 21st Century Pandemic from Etiology to Neuro-psychiatric Implications. - Yamamoto, Vicky; Bolanos, Joe F; Fiallos, John; Strand, Susanne E; Morris, Kevin; Shahrokhinia, Sanam; Cushing, Tim R; Hopp, Lawrence; Tiwari, Ambooj; Hariri, Robert; Sokolov, Rick; Wheeler, Christopher; et al. (J Alzheimers Dis, 2020)
COVID-19 is a severe infectious disease that has claimed >150,000 lives and infected millions in the United States thus far, especially the elderly population. Emerging evidence has shown the virus to cause hemorrhagic and immunologic responses, which impact all organs, including lungs, kidneys, and the brain, as well as extremities. SARS-CoV-2 also affects patients', families', and society's mental health at large. There is growing evidence of re-infection in some patients. The goal of this paper is to provide a comprehensive review of SARS-CoV-2-induced disease, its mechanism of infection, diagnostics, therapeutics, and treatment strategies, while also focusing on less attended aspects by previous studies, including nutritional support, psychological, and rehabilitation of the pandemic and its management. We performed a systematic review of >1,000 articles and included 425 references from online databases, including, PubMed, Google Scholar, and California Baptist University's library. COVID-19 patients go through acute respiratory distress syndrome, cytokine storm, acute hypercoagulable state, and autonomic dysfunction, which must be managed by a multidisciplinary team including nursing, nutrition, and rehabilitation. The elderly population and those who are suffering from Alzheimer's disease and dementia related illnesses seem to be at the higher risk. There are 28 vaccines under development, and new treatment strategies/protocols are being investigated. The future management for COVID-19 should include B-cell and T-cell immunotherapy in combination with emerging prophylaxis. The mental health and illness aspect of COVID-19 are among the most important side effects of this pandemic which requires a national plan for prevention, diagnosis and treatment.
Keywords: Coronavirus Infections; COVID-19; Humans; Immunotherapy; Mental Health; Nutritional Support; Pandemics; Pneumonia, Viral

Death Rate Due to COVID-19 in Alzheimer's Disease and Frontotemporal Dementia. - Matías-Guiu, Jordi A; Pytel, Vanesa; Matías-Guiu, Jorge (J Alzheimers Dis, 2020)
We aimed to evaluate the frequency and mortality of COVID-19 in patients with Alzheimer's disease (AD) and frontotemporal dementia (FTD). We conducted an observational case series. We enrolled 204 patients, 15.2% of whom were diagnosed with COVID-19, and 41.9% of patients with the infection died. Patients with AD were older than patients with FTD (80.36±8.77 versus 72.00±8.35 years old) and had a higher prevalence of arterial hypertension (55.8% versus 26.3%). COVID-19 occurred in 7.3% of patients living at home, but 72.0% of those living at care homes. Living in care facilities and diagnosis of AD were independently associated with a higher probability of death. We found that living in care homes is the most relevant factor for an increased risk of COVID-19 infection and death, with AD patients exhibiting a higher risk than those with FTD.
Keywords: Age Factors; Aged; Aged, 80 and over; Alzheimer Disease; Coronavirus Infections; COVID-19; Female; Frontotemporal Dementia; Humans; Hypertension; Independent Living; Male; Nursing Homes; Pandemics; Pneumonia, Viral; Prevalence; Risk Factors

Dementia Care in the Time of COVID-19 Pandemic. - Tousi, Babak (J Alzheimers Dis, 2020)
Patients with dementia are particularly vulnerable during the COVID-19 pandemic. The initial response to COVID-19 promoted behavioral changes in both society and healthcare, while a long-term solution is sought by prioritizing societal values. In addition, there has been disruption to clinical care and clinical research. This pandemic might have significantly changed the care for our patients with dementia toward increased acceptance of telemedicine by the patients and providers, and its utilization in both clinical care and research.
Keywords: Betacoronavirus; Coronavirus Infections; Dementia; Health Services Accessibility; Humans; Pandemics; Pneumonia, Viral; Telemedicine

Dementia Care in Times of COVID-19: Experience at Fundació ACE in Barcelona, Spain. - Benaque, Alba; Gurruchaga, Miren Jone; Abdelnour, Carla; Hernandez, Isabel; Cañabate, Pilar; Alegret, Montserrat; Rodríguez, Isabel; Rosende-Roca, Maitee; Tartari, Juan Pablo; Esteban, Ester; López, Rogelio; Gil, Silvia; et al. (J Alzheimers Dis, 2020)
BACKGROUND: Fundació ACE is a non-profit organization providing care based on a holistic model to persons with cognitive disorders and their families for 25 years in Barcelona, Spain. Delivering care to this vulnerable population amidst the COVID-19 pandemic has represented a major challenge to our institution. OBJECTIVE: To share our experience in adapting our model of care to the new situation to ensure continuity of care. METHODS: We detail the sequence of events and the actions taken within Fundació ACE to swiftly adapt our face-to-face model of care to one based on telemedicine consultations. We characterize individuals under follow-up by the Memory Unit from 2017 to 2019 and compare the number of weekly visits in 2020 performed before and after the lockdown was imposed. RESULTS: The total number of individuals being actively followed by Fundació ACE Memory Unit grew from 6,928 in 2017 to 8,147 in 2019. Among those newly diagnosed in 2019, most patients had mild cognitive impairment or mild dementia (42% and 25%, respectively). Weekly visits dropped by 60% following the suspension of face-to-face activity. However, by April 24 we were able to perform 78% of the visits we averaged in the weeks before confinement began. DISCUSSION: We have shown that Fundació ACE model of care has been able to successfully adapt to a health and social critical situation as COVID-19 pandemic. Overall, we were able to guarantee the continuity of care while preserving the safety of patients, families, and professionals. We also seized the opportunity to improve our model of care.
Keywords: Aged; Aged, 80 and over; Betacoronavirus; Coronavirus Infections; COVID-19; Dementia; Female; Follow-Up Studies; Holistic Health; Humans; Male; Pandemics; Patient-Centered Care; Pneumonia, Viral; SARS-CoV-2; Spain; Telemedicine

Dementia in the COVID-19 Period. - Korczyn, Amos D (J Alzheimers Dis, 2020)
Keywords: Betacoronavirus; Coronavirus; Coronavirus Infections; COVID-19; Dementia; Humans; Nervous System Diseases; Pandemics; Pneumonia, Viral; SARS-CoV-2; Telemedicine

The Effects of Confinement on Neuropsychiatric Symptoms in Alzheimer's Disease During the COVID-19 Crisis. - Boutoleau-Bretonnière, Claire; Pouclet-Courtemanche, Hélene; Gillet, Aurelie; Bernard, Amelie; Deruet, Anne Laure; Gouraud, Ines; Mazoue, Aurelien; Lamy, Estelle; Rocher, Laetitia; Kapogiannis, Dimitrios; El Haj, Mohamad (J Alzheimers Dis, 2020)
BACKGROUND: Neuropsychiatric symptoms, such as depression, anxiety, apathy, agitation, and hallucinations, are frequent in Alzheimer's disease (AD) and their prevalence tends to increase with external stressors. OBJECTIVE: We offer the first investigation of the effects of confinement during the COVID-19 crisis on neuropsychiatric symptoms in patients with AD. METHODS: We contacted caregivers of 38 patients with AD who were confined to their homes for nearly two months and asked them to report whether patients experienced any change in neuropsychiatric symptoms during, compared to before, the confinement and rate its severity and impact on themselves using the Neuropsychiatric Inventory-Questionnaire. RESULTS: Among the 38 patients, only 10 demonstrated neuropsychiatric changes during the confinement. Cognitive function of these 10 patients, assessed with the Mini-Mental State Examination, was worse than that of patients who did not demonstrate neuropsychiatric changes. Interestingly, among the 10 patients with neuropsychiatric changes, the duration of confinement significantly correlated with the severity of symptoms as well as with their caregivers' distress. DISCUSSION: The confinement seems to impact neuropsychiatric symptomatology in AD patients with low baseline cognitive function.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Betacoronavirus; Cohort Studies; Coronavirus Infections; COVID-19; Female; Humans; Male; Mental Disorders; Mental Status and Dementia Tests; Middle Aged; Pandemics; Pneumonia, Viral; Quarantine; SARS-CoV-2

Environmental Nanoparticles, SARS-CoV-2 Brain Involvement, and Potential Acceleration of Alzheimer's and Parkinson's Diseases in Young Urbanites Exposed to Air Pollution. - Calderón-Garcidueñas, Lilian; Torres-Jardón, Ricardo; Franco-Lira, Maricela; Kulesza, Randy; González-Maciel, Angelica; Reynoso-Robles, Rafael; Brito-Aguilar, Rafael; García-Arreola, Berenice; Revueltas-Ficachi, Paula; Barrera-Velázquez, Juana Adriana; García-Alonso, Griselda; García-Rojas, Edgar; et al. (J Alzheimers Dis, 2020)
Alzheimer's and Parkinson's diseases (AD, PD) have a pediatric and young adult onset in Metropolitan Mexico City (MMC). The SARS-CoV-2 neurotropic RNA virus is triggering neurological complications and deep concern regarding acceleration of neuroinflammatory and neurodegenerative processes already in progress. This review, based on our MMC experience, will discuss two major issues: 1) why residents chronically exposed to air pollution are likely to be more susceptible to SARS-CoV-2 systemic and brain effects and 2) why young people with AD and PD already in progress will accelerate neurodegenerative processes. Secondary mental consequences of social distancing and isolation, fear, financial insecurity, violence, poor health support, and lack of understanding of the complex crisis are expected in MMC residents infected or free of SARS-CoV-2. MMC residents with pre-SARS-CoV-2 accumulation of misfolded proteins diagnostic of AD and PD and metal-rich, magnetic nanoparticles damaging key neural organelles are an ideal host for neurotropic SARS-CoV-2 RNA virus invading the body through the same portals damaged by nanoparticles: nasal olfactory epithelium, the gastrointestinal tract, and the alveolar-capillary portal. We urgently need MMC multicenter retrospective-prospective neurological and psychiatric population follow-up and intervention strategies in place in case of acceleration of neurodegenerative processes, increased risk of suicide, and mental disease worsening. Identification of vulnerable populations and continuous effort to lower air pollution ought to be critical steps.
Keywords: Adult; Air Pollution; Alzheimer Disease; Brain Diseases; Coronavirus Infections; COVID-19; Disease Progression; Environmental Pollutants; Humans; Middle Aged; Nanoparticles; Pandemics; Parkinson Disease; Pneumonia, Viral; Suicide; Urban Population

Neurobiology of COVID-19. - Fotuhi, Majid; Mian, Ali; Meysami, Somayeh; Raji, Cyrus A (J Alzheimers Dis, 2020)
Anosmia, stroke, paralysis, cranial nerve deficits, encephalopathy, delirium, meningitis, and seizures are some of the neurological complications in patients with coronavirus disease-19 (COVID-19) which is caused by acute respiratory syndrome coronavirus 2 (SARS-Cov2). There remains a challenge to determine the extent to which neurological abnormalities in COVID-19 are caused by SARS-Cov2 itself, the exaggerated cytokine response it triggers, and/or the resulting hypercoagulapathy and formation of blood clots in blood vessels throughout the body and the brain. In this article, we review the reports that address neurological manifestations in patients with COVID-19 who may present with acute neurological symptoms (e.g., stroke), even without typical respiratory symptoms such as fever, cough, or shortness of breath. Next, we discuss the different neurobiological processes and mechanisms that may underlie the link between SARS-Cov2 and COVID-19 in the brain, cranial nerves, peripheral nerves, and muscles. Finally, we propose a basic "NeuroCovid" classification scheme that integrates these concepts and highlights some of the short-term challenges for the practice of neurology today and the long-term sequalae of COVID-19 such as depression, OCD, insomnia, cognitive decline, accelerated aging, Parkinson's disease, or Alzheimer's disease in the future. In doing so, we intend to provide a basis from which to build on future hypotheses and investigations regarding SARS-Cov2 and the nervous system.
Keywords: Betacoronavirus; Brain; Coronavirus Infections; COVID-19; Humans; Inflammation Mediators; Nervous System Diseases; Pandemics; Pneumonia, Viral; SARS-CoV-2

Potential Novel Role of COVID-19 in Alzheimer's Disease and Preventative Mitigation Strategies. - Naughton, Sean X; Raval, Urdhva; Pasinetti, Giulio M (J Alzheimers Dis, 2020)
There are a number of potential implications for the field of Alzheimer's disease (AD) stemming from the global spread of SARS-CoV-2. Neuroinflammation is known to be a prominent feature of neurodegeneration and plays a major role in AD pathology. Immune response and excessive inflammation in COVID-19 may also accelerate the progression of brain inflammatory neurodegeneration, and elderly individuals are more susceptible to severe outcomes after SARS-CoV-2 infection. Individuals with type 2 diabetes (T2D) are at an increased risk for AD as well as severe outcomes after SARS-CoV-2 infection. Genetic and socioeconomic factors influencing the rates of T2D, AD, and COVID-19 severity may create an exceptionally high-risk profile for certain demographics such as African Americans and Hispanic Americans. Type I interferon response plays an important role in both host response to viral infection, as well as AD pathology and may be a sensible therapeutic target in both AD and COVID-19.
Keywords: Aged; Alzheimer Disease; Betacoronavirus; Coronavirus Infections; COVID-19; Diabetes Mellitus, Type 2; Humans; Interferon Type I; Pandemics; Pneumonia, Viral; SARS-CoV-2; Synapses

Resilience of Alzheimer's Disease to COVID-19. - Li, Jingwen; Long, Xi; Huang, Heqing; Tang, Jine; Zhu, Chunli; Hu, Shaoping; Wu, Jing; Li, Jinghong; Lin, Zhicheng; Xiong, Nian (J Alzheimers Dis, 2020)
BACKGROUND: Facing the novel coronavirus disease 2019 (COVID-19), most vulnerable individuals are seniors, especially those with comorbidities. More attention needs to been paid to the COVID-19 patients with Alzheimer's disease (AD), which is the top age-related neurodegenerative disease. OBJECTIVE: Since it is unclear whether AD patients are prone to COVID-19 infection and progression to severe stages, we report for the first time a retrospective analysis of the clinical characteristics of AD patients with COVID-19 pneumonia. METHODS: We conducted a retrospective cohort study of the clinical data of 19 AD patients with COVID-19 pneumonia, compared with 23 non-AD COVID-19 patients admitted at the same time to our hospital. Demographic, clinical, laboratory, radiological, and treatment data were collected and analyzed. RESULTS: Between AD patients and non-AD patients with COVID-19 pneumonia, the pneumonia severity was not significantly different. AD patients had a higher clustering onset than non-AD patients. The median duration from symptom onset to hospitalization were shorter in AD patients than non-AD patients, indicating the former were sent to the hospital by their family or from nursing home earlier than the later. The median duration from hospitalization to discharge seemed shorter in AD patients than non-AD patients. Dementia patients seemed less likely to report fatigue. It is noticed that more AD patients might have pericardial effusion than the non-AD patients. CONCLUSION: AD patients with COVID-19 were in milder conditions with a better prognosis than non-AD patients. AD patients who had adequate access to healthcare showed resilience to COVID-19 with shorter hospital stays.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cluster Analysis; Cohort Studies; Coronavirus Infections; COVID-19; Disease Progression; Fatigue; Female; Humans; Length of Stay; Male; Middle Aged; Pandemics; Patient Discharge; Pleural Effusion; Pneumonia; Pneumonia, Viral; Prognosis; Resilience, Psychological

Telemedicine for Delivery of Care in Frontotemporal Lobar Degeneration During COVID-19 Pandemic: Results from Southern Italy. - Capozzo, Rosa; Zoccolella, Stefano; Frisullo, Maria Elisa; Barone, Roberta; Dell'Abate, Maria Teresa; Barulli, Maria Rosaria; Musio, Marco; Accogli, Miriam; Logroscino, Giancarlo (J Alzheimers Dis, 2020)
BACKGROUND: The COVID-19 pandemic is changing clinical practice in neurology, after the governments decided the introduction of social distancing and interruption of medical non-emergency services in many countries. Teleneurology is an effective tool for the remote evaluation of patients but its adoption for frontotemporal lobar dementia (FTD) is in a preliminary stage. OBJECTIVE: We evaluated multidisciplinary assessment of patients with FTD using telehealth during the COVID-19 pandemic. METHODS: All patients received a diagnosis of FTD during 2018-2019 according to international criteria. A structured questionnaire and Clinical Dementia Rating Scale (CDR)-FTD were used by the neurologist with patients and/or caregivers. Index symptoms of COVID-19 infection were searched. RESULTS: Twenty-eight clinical interviews were completed with caregivers and four with both patients/caregivers. Most patients and caregivers were satisfied with the neurological interview and expressed their willingness to continue to be included in remote evaluation programs (90%). Fifty percent of patients experienced significant worsening of clinical picture and quality of life since the start of social distancing. The CDR-FTD scale revealed a significant worsening of behavior (p = 0.01) and language functions (p = 0.009), compared to the last in-person evaluation at the center. One patient presented index symptoms of COVID-19 infection and was confirmed to be positive for COVID-19 with pharyngeal swab. CONCLUSION: The study was conducted in Italy, one of the countries hit particularly hard by the COVID-19 pandemic, with interruption of all non-emergency medical services. Our study indicates that telemedicine is a valid tool to triage patients with FTD to increase practice outreach and efficiency.
Keywords: Aged; Aged, 80 and over; Behavior; Coronavirus Infections; COVID-19; Delivery of Health Care; Disease Progression; Female; Frontotemporal Lobar Degeneration; Humans; Italy; Language; Male; Mental Status and Dementia Tests; Middle Aged; Pandemics; Pneumonia, Viral; Quality of Life; Quarantine; Surveys and Questionnaires; Telemedicine; Triage

11C-CFT-PET in Presymptomatic FTDP-17: A Potential Biomarker Predicting Onset. - Wu, Liyong; Liu, Jia; Feng, Xueyan; Dong, Jing; Qin, Wei; Liu, Yang; Wang, Jingjuan; Lu, Jie; Chen, Kewei; Wang, Yuping; Jia, Jianping (J Alzheimers Dis, 2018)
Frontotemporal dementia with parkinsonism-linked to chromosome 17 (FTDP-17) is a rare autosomal dominant neurodegenerative disorder. Most patients with FTDP-17 carry the mutation in the microtubule-associated protein tau (MAPT) gene. Striatum is predominantly and early affected in FTDP-17. Five family members (two symptomatic patients and three presymptomatic mutation carriers) from a Chinese pedigree of FTDP-17 with N279K mutation in MAPT were enrolled. Parkinsonism was the initial symptom for symptomatic patients. 2b-carbomethoxy-3b-(4-trimethylstannylphenyl) tropane (11C-CFT) uptake was obviously affected in the putamen of two presymptomatic mutation carriers. Presymptomatic case 3, whose 11C-CFT uptake in the right putamen was normal at baseline, was still free of parkinsonism during follow-up. In conclusion, 11C-CFT-positron emission tomography could be a potential biomarker for the presymptomatic stage of FTDP-17 to predict the disease onset.
Keywords: Adult; Biomarkers; Brain; Carbon Radioisotopes; Female; Frontotemporal Dementia; Heterozygote; Humans; Male; Middle Aged; Mutation; Parkinsonian Disorders; Pedigree; Positron-Emission Tomography; tau Proteins

Alzheimer-Like Pattern of Hypometabolism Emerges with Elevated Amyloid-β Burden in Down Syndrome. - Lao, Patrick J; Handen, Ben L; Betthauser, Tobey J; Mihaila, Iulia; Hartley, Sigan L; Cohen, Annie D; Tudorascu, Dana L; Bulova, Peter D; Lopresti, Brian J; Tumuluru, Rameshwari V; Murali, Dhanabalan; Mathis, Chester A; et al. (J Alzheimers Dis, 2018)
BACKGROUND: The Down syndrome (DS) population is genetically predisposed to amyloid-β protein precursor overproduction and Alzheimer's disease (AD). OBJECTIVE: The temporal ordering and spatial association between amyloid-β, glucose metabolism, and gray matter (GM) volume in the DS population can provide insight into those associations in the more common sporadic AD. METHODS: Twenty-four adults (13 male, 11 female; 39±7 years) with DS underwent [11C]PiB, [18F]FDG, and volumetric MRI scans. Voxel-wise associations between PiB SUVR, FDG SUVR, and GM volume were investigated, with and without individual adjustments for variables of interest. RESULTS: Positive associations of PiB and age were widespread throughout the neocortex and striatum. Negative associations of FDG and age (frontal, parietal, and temporal cortex) and of GM volume and age (frontal and insular cortex) were observed. PiB and FDG were negatively associated in parietal cortex, after adjustment for GM volume. CONCLUSIONS: In adults with DS, early amyloid-β accumulation in the striatum is divergent from sporadic AD; however, despite the early striatal amyloid-β, glucose hypometabolism was confined to the typical AD-associated regions, which occurs similarly in autosomal dominant AD. Importantly, the glucose hypometabolism was not explained solely by increased partial volume effect due to GM volume reductions.
Keywords: Adult; Alzheimer Disease; Amyloid beta-Peptides; Down Syndrome; Female; Fluorodeoxyglucose F18; Gray Matter; Humans; Linear Models; Longitudinal Studies; Magnetic Resonance Imaging; Male; Middle Aged; Positron-Emission Tomography; Radiopharmaceuticals; United States

Alzheimer's Disease rs11767557 Variant Regulates EPHA1 Gene Expression Specifically in Human Whole Blood. - Liu, Guiyou; Zhang, Yan; Wang, Longcai; Xu, Jianyong; Chen, Xiaoyun; Bao, Yunjuan; Hu, Yang; Jin, Shuilin; Tian, Rui; Bai, Weiyang; Zhou, Wenyang; Wang, Tao; et al. (J Alzheimers Dis, 2018)
Large-scale genome-wide association studies have reported EPHA1 rs11767557 variant to be associated with Alzheimer's disease (AD) risk in the European population. However, it is still unclear how this variant functionally contributes to the underlying disease pathogenesis. The rs11767557 variant is located approximately 3 kb upstream of EPHA1 gene. We think that rs11767557 may modify the expression of nearby genes such as EPHA1 and further cause AD risk. Until now, the potential association between rs11767557 and the expression of nearby genes has not been reported in previous studies. Here, we evaluate the potential expression association between rs11767557 and EPHA1 using multiple large-scale eQTLs datasets in human brain tissues and the whole blood. The results show that rs11767557 variant could significantly regulate EPHA1 gene expression specifically in human whole blood. These findings may further provide important supplementary information about the regulating mechanisms of rs11767557 variant in AD risk.
Keywords: Alzheimer Disease; Case-Control Studies; China; Gene Expression; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Linkage Disequilibrium; Polymorphism, Single Nucleotide; Receptor, EphA1; Risk Assessment

Antemortem-Postmortem Correlation of Florbetapir (18F) PET Amyloid Imaging with Quantitative Biochemical Measures of Aβ42 but not Aβ40. - Beach, Thomas G; Maarouf, Chera L; Intorcia, Anthony; Sue, Lucia I; Serrano, Geidy E; Lu, Ming; Joshi, Abhinay; Pontecorvo, Michael J; Roher, Alex E (J Alzheimers Dis, 2018)
Amyloid imaging demonstrates the in vivo presence of amyloid-β (Aβ) deposits in the aging human brain but it is still unknown which structural forms and modifications of Aβ are detected. In Alzheimer's disease, most amyloid deposits are predominantly composed of Aβ ending at amino acid residues Val40 or Ala42. It has been reported that Aβ40 is largely restricted to neuritic plaques while Aβ42 may be deposited in amyloid plaques of all types, and is often the sole component of diffuse plaques. The distinction is important as it is mainly the neuritic plaques that correlate with cognitive impairment while diffuse plaques may be the initial type of Aβ deposited. Whether PET amyloid ligands such as florbetapir-18F (Amyvid) are partially or wholly selective for brain deposits of Aβ40 or Aβ42 is currently unknown. We compared antemortem florbetapir PET cortical/cerebellar signal intensity (SUVr) of 55 subjects with postmortem biochemical (ELISA) measurements employing specific antibodies against Aβ40 and Aβ42. Spearman's univariable correlations were significant for both Aβ40 and Aβ42, but were much stronger for Aβ42. Multiple linear regression showed significance only for Aβ42. These results suggest that florbetapir binds only weakly, if at all, to Aβ40. This may be in part due to the higher likelihood for Aβ42 to be present in a β-pleated sheet tertiary structure, or to differences between Aβ40 and Aβ42 in β-pleated sheet tertiary or quaternary structure.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Amyloidosis; Aniline Compounds; Autopsy; Brain; Ethylene Glycols; Humans; Linear Models; Peptide Fragments; Plaque, Amyloid; Positron-Emission Tomography

Aphasia in Progressive Supranuclear Palsy: As Severe as Progressive Non-Fluent Aphasia. - Burrell, James R; Ballard, Kirrie J; Halliday, Glenda M; Hodges, John R (J Alzheimers Dis, 2018)
BACKGROUND: Adynamic speech is characteristic of progressive supranuclear palsy (PSP), but higher language deficits have been reported inconsistently, in the context of clinical and pathological overlaps with progressive non-fluent aphasia (PNFA). OBJECTIVE: The present study tested two hypotheses: 1) PSP and PNFA display impaired single word repetition, object naming, semantic knowledge, and syntactic comprehension; and 2) PSP have reduced speed on timed cognitive tasks. METHODS: Structured clinical and neuropsychological assessments of language were performed on patients with clinically defined PSP and PNFA. Language was tested using the Sydney Language Battery (SYDBAT) and the Test of Reception of Grammar (TROG). RESULTS: In total, 144 participants were studied (PSP 22, PNFA 29, and Control 93). PSP patients had prominent eye movement abnormalities, parkinsonism, and falls. All 4 PSP patients who underwent postmortem examination had 4-Repeat tauopathy, with PSP pathology in 3. The frequency and severity of impairment on the SYDBAT (naming, word comprehension, semantic association), and TROG (syntactic comprehension) did not differ between PSP and PNFA, but PSP were significantly slower on timed non-language cognitive tests. CONCLUSION: Tested formally, aphasia may be seen in PSP, with a severity similar to that seen in PNFA.
Keywords: Aged; Aged, 80 and over; Case-Control Studies; Cognition; Female; Humans; Language Tests; Male; Middle Aged; Primary Progressive Nonfluent Aphasia; Semantics; Speech; Supranuclear Palsy, Progressive

An Aspartyl Cathepsin Targeted PET Agent: Application in an Alzheimer's Disease Mouse Model. - Snir, Jonatan A; Suchy, Mojmir; Bindseil, Geron A; Kovacs, Michael; Chronik, Blaine A; Hudson, Robert H E; Pasternak, Stephen H; Bartha, Robert (J Alzheimers Dis, 2018)
BACKGROUND: Early detection of Alzheimer's disease (AD) pathology is a serious challenge for both diagnosis and clinical trials. The aspartyl protease, Cathepsin D (CatD), is overexpressed in AD and could be a biomarker of disease. We have previously designed a unique contrast agent (CA) for dual-optical and magnetic resonance imaging of the activity of the CatD class of enzymes. OBJECTIVE: To compare the uptake and retention of a novel, more sensitive, and clinically-translatable 68Ga PET tracer targeting CatD activity in 5XFAD mice and non-Tg littermates. METHODS: The targeted CA consisted of an HIV-1 Tat cell penetrating peptide (CPP) conjugated to a specialized cleavage sequence targeting aspartyl cathepsins and a DOTA conjugate chelating 68Ga. PET images were acquired using a Siemens Inveon preclinical microPET in female Tg AD mice and non-Tg age matched female littermates (n = 5-8) following intravenous CA administration at 2, 6, and 9 months of age. Additionally, 18F fluorodeoxyglucose (FDG) PET imaging was performed at 10 months to measure glucose uptake. RESULTS: The Tg mice showed significantly higher relative uptake rate of the targeting CA in the forebrain relative to hindbrain at all ages compared to controls, consistent with histology. In contrast, no differences were seen in CA uptake in other organs. Additionally, the Tg mice did not show any differences in relative uptake of FDG at 10 months of age in the forebrain relative to the hindbrain compared to age matched non-Tg controls. CONCLUSIONS: Elevated aspartryl cathepsin activity was detected in vivo in the 5XFAD mouse model of AD using a novel targeted PET contrast agent.
Keywords: Alzheimer Disease; Animals; Brain; Cathepsin D; Contrast Media; Disease Models, Animal; Female; Fluorodeoxyglucose F18; Glucose; Mice; Mice, Transgenic; Positron-Emission Tomography

Assay of Plasma Phosphorylated Tau Protein (Threonine 181) and Total Tau Protein in Early-Stage Alzheimer's Disease. - Yang, Che-Chuan; Chiu, Ming-Jang; Chen, Ta-Fu; Chang, Hui-Ling; Liu, Bing-Hsien; Yang, Shieh-Yueh (J Alzheimers Dis, 2018)
The feasibility of assaying plasma phosphorylated tau protein (threonine 181), denoted p-tau181, using immunomagnetic reduction (IMR) is explored. The reagent for assaying p-tau181 with IMR was synthesized, and its analytic performances were characterized. Seventy-three subjects were recruited. Each participant was examined with neuropsychological tests, magnetic resonance imaging, and IMR assay for plasma p-tau181. Using commercially available IMR kits, the plasma total tau protein (T-tau) of each subject was assayed. The dynamic range for assaying p-tau181 using IMR was 1.96×10-2 pg/ml to 104 pg/ml. There was no significant interference from total tau protein in the assay of p-tau181. The measured concentrations of plasma p-tau181 were 2.46±1.09 pg/ml for healthy controls, 4.41±1.85 pg/ml for MCI due to AD, and 6.14±1.59 pg/ml for very mild AD. Meanwhile, the measured concentrations of plasma T-tau were 18.85±10.16 pg/ml for healthy controls, 32.98±10.18 pg/ml for MCI due to AD, and 37.54±12.29 pg/ml for very mild AD. A significant difference in plasma p-tau181 was observed between healthy controls and MCI due to AD (p < 0.001) and between MCI due to AD and very mild AD (p < 0.001). However, for the plasma T-tau concentration, a significant difference existed only between healthy controls and MCI due to AD (p < 0.001). This implies that the plasma p-tau181 level is correlated more to AD severity than plasma T-tau is. Additionally, p-tau181 was observed as approximately 14% of T-tau in human plasma.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Case-Control Studies; Female; Humans; Magnetic Resonance Imaging; Male; Middle Aged; Neuropsychological Tests; Phosphorylation; tau Proteins

Assessment of the Genetic Architecture of Alzheimer's Disease Risk in Rate of Memory Decline. - Del-Aguila, Jorge L; Fernández, Maria Victoria; Schindler, Suzanne; Ibanez, Laura; Deming, Yuetiva; Ma, Shengmei; Saef, Ben; Black, Kathleen; Budde, John; Norton, Joanne; Chasse, Rachel; Harari, Oscar; et al. (J Alzheimers Dis, 2018)
Many genetic studies for Alzheimer's disease (AD) have been focused on the identification of common genetic variants associated with AD risk and not on other aspects of the disease, such as age at onset or rate of dementia progression. There are multiple approaches to untangling the genetic architecture of these phenotypes. We hypothesized that the genetic architecture of rate of progression is different than the risk for developing AD dementia. To test this hypothesis, we used longitudinal clinical data from ADNI and the Knight-ADRC at Washington University, and we calculated PRS (polygenic risk score) based on the IGAP study to compare the genetic architecture of AD risk and dementia progression. Dementia progression was measured by the change of Clinical Dementia Rating Sum of Boxes (CDR)-SB per year. Out of the 21 loci for AD risk, no association with the rate of dementia progression was found. The PRS rate was significantly associated with the rate of dementia progression (β= 0.146, p = 0.03). In the case of rare variants, TREM2 (β= 0.309, p = 0.02) was also associated with the rate of dementia progression. TREM2 variant carriers showed a 23% faster rate of dementia compared with non-variant carriers. In conclusion, our results indicate that the recently identified common and rare variants for AD susceptibility have a limited impact on the rate of dementia progression in AD patients.
Keywords: Age of Onset; Aged; Aged, 80 and over; Alzheimer Disease; Dementia; Disease Progression; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Heterozygote; Humans; Longitudinal Studies; Male; Membrane Glycoproteins; Memory Disorders; Middle Aged; Polymorphism, Single Nucleotide; Receptors, Immunologic; Risk Assessment

Association between α-Klotho and Deep White Matter Lesions in the Brain: A Pilot Case Control Study Using Brain MRI. - Kuriyama, Nagato; Ozaki, Etsuko; Mizuno, Toshiki; Ihara, Masafumi; Mizuno, Shigeto; Koyama, Teruhide; Matsui, Daisuke; Watanabe, Isao; Akazawa, Kentaro; Takeda, Kazuo; Takada, Akihiro; Inaba, Masaaki; et al. (J Alzheimers Dis, 2018)
BACKGROUND: The anti-aging protein, α-Klotho, may be involved in cognitive decline and has potential as a surrogate marker that reflects dementia. However, the role of α-Klotho in the brain has not been sufficiently investigated. OBJECTIVE: Here, we investigated the association between α-Klotho and cognitive decline that is associated with cerebral deep white matter lesions (DWMLs). METHODS: Two hundred-eighty participants (187 males and 93 females, mean age: 70.8 years old) were evaluated for DWMLs, and the Fazekas scale (Grade) was assessed following brain magnetic resonance imaging. A questionnaire concerning lifestyle and neuropsychological tests was administered, and their associations with the blood α-Klotho level were retrospectively investigated. RESULTS: The α-Klotho level was 685.1 pg/mL in Grade 0 (68 subjects), 634.1 in G1 (134), 596.0 in G2 (62), and 571.6 in G3 (16), showing that the level significantly decreased with advanced grades. Significant correlations were noted between the α-Klotho level and higher brain function tests including the Mini-Mental State Examination and word fluency tests (p < 0.05). When a 90th percentile value of the level in the G0 group (400 pg/mL) or lower was defined as a low α-Klotho level, the odds ratio of the high-grade G3 group was 2.9 (95% confidence interval: 1.4-7.8) (after correction for age, sex, hypertension, and chronic kidney disease), which was significant. CONCLUSION: A reduced blood α-Klotho level was correlated with grading of cerebral DWMLs and was accompanied by cognitive decline as an independent risk factor. The α-Klotho level may serve as a useful clinical index of vascular cognitive impairment.
Keywords: Aged; Aged, 80 and over; Apolipoprotein E4; Brain; C-Reactive Protein; Case-Control Studies; Cognition Disorders; Female; Glucuronidase; Humans; Image Processing, Computer-Assisted; Leukoencephalopathies; Magnetic Resonance Imaging; Male; Mental Status Schedule; Middle Aged; Neuropsychological Tests; Pilot Projects; Severity of Illness Index

Association of Cerebrospinal Fluid (CSF) Insulin with Cognitive Performance and CSF Biomarkers of Alzheimer's Disease. - Geijselaers, Stefan L C; Aalten, Pauline; Ramakers, Inez H G B; De Deyn, Peter Paul; Heijboer, Annemieke C; Koek, Huiberdina L; OldeRikkert, Marcel G M; Papma, Janne M; Reesink, Fransje E; Smits, Lieke L; Stehouwer, Coen D A; Teunissen, Charlotte E; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Abnormal insulin signaling in the brain has been linked to Alzheimer's disease (AD). OBJECTIVE: To evaluate whether cerebrospinal fluid (CSF) insulin levels are associated with cognitive performance and CSF amyloid-β and Tau. Additionally, we explore whether any such association differs by sex or APOE ɛ4 genotype. METHODS: From 258 individuals participating in the Parelsnoer Institute Neurodegenerative Diseases, a nationwide multicenter memory clinic population, we selected 138 individuals (mean age 66±9 years, 65.2% male) diagnosed with subjective cognitive impairment (n = 45), amnestic mild cognitive impairment (n = 44), or AD (n = 49), who completed a neuropsychological assessment, including tests of global cognition and memory performance, and who underwent lumbar puncture. We measured CSF levels of insulin, amyloid-β1-42, total (t-)Tau, and phosphorylated (p-)Tau. RESULTS: CSF insulin levels did not differ between the diagnostic groups (p = 0.136). Across the whole study population, CSF insulin was unrelated to cognitive performance and CSF biomarkers of AD, after adjustment for age, sex, body mass index, diabetes status, and clinic site (all p≥0.131). Importantly, however, we observed effect modification by sex and APOE ɛ4 genotype. Specifically, among women, higher insulin levels in the CSF were associated with worse global cognition (standardized regression coefficient -0.483; p = 0.008) and higher p-Tau levels (0.353; p = 0.040). Among non-carriers of the APOE ɛ4 allele, higher CSF insulin was associated with higher t-Tau (0.287; p = 0.008) and p-Tau (0.246; p = 0.029). CONCLUSION: Our findings provide further evidence for a relationship between brain insulin signaling and AD pathology. It also highlights the need to consider sex and APOE ɛ4 genotype when assessing the role of insulin.
Keywords: Aged; Alzheimer Disease; Amyloid beta-Peptides; Apolipoprotein E4; Brain; Cognition Disorders; Female; Humans; Insulin; Male; Mental Status Schedule; Middle Aged; Neuropsychological Tests; Peptide Fragments; Signal Transduction; tau Proteins

Association of the New Variant Tyr424Asp at TBK1 Gene with Amyotrophic Lateral Sclerosis and Cognitive Decline. - Piaceri, Irene; Bessi, Valentina; Matà, Sabrina; Polito, Cristina; Tedde, Andrea; Berti, Valentina; Bagnoli, Silvia; Braccia, Arianna; Del Mastio, Monica; Pignone, Alberto Moggi; Pupi, Alberto; Sorbi, Sandro; et al. (J Alzheimers Dis, 2018)
A new risk gene associated with amyotrophic lateral sclerosis (ALS) has recently been identified: the Tank-binding kinase 1 (TBK1) gene. Up to now, 90 TBK1 variants have been described in ALS patients with or without frontotemporal dementia (FTD), thus making TBK1 the third or fourth most frequent genetic cause of ALS and FTD. A point mutation analysis in a cohort of 69 Italian ALS patients was performed in order to analyze the frequency of TBK1 mutations and the correlation with clinical phenotypes. The analysis identified the novel variant p.Tyr424Asp in a patient with a rapid progression of the disease. Our data supports the implication of TBK1 in ALS pathogenesis in Italy.
Keywords: Aged; Amyotrophic Lateral Sclerosis; Aspartic Acid; C9orf72 Protein; Cognitive Dysfunction; DNA Mutational Analysis; Female; Fluorodeoxyglucose F18; Genetic Association Studies; Genetic Predisposition to Disease; Humans; Italy; Male; Mental Status and Dementia Tests; Middle Aged; Mutation; Neuropsychological Tests; Positron-Emission Tomography; Protein-Serine-Threonine Kinases; Tyrosine

Associations between Use of Specific Analgesics and Concentrations of Amyloid-β 42 or Phospho-Tau in Regions of Human Cerebral Cortex. - Flanagan, Margaret E; Larson, Eric B; Walker, Rod L; Keene, C Dirk; Postupna, Nadia; Cholerton, Brenna; Sonnen, Joshua A; Dublin, Sascha; Crane, Paul K; Montine, Thomas J (J Alzheimers Dis, 2018)
Analgesics are commonly used by older adults, raising the question of whether their use might contribute to dementia risk and neuropathologic changes of Alzheimer's disease (AD). The Adult Changes in Thought (ACT) study is a population-based study of brain aging and incident dementia among people 65 years or older who are community dwelling and not demented at entry. Amyloid-β (Aβ)42 and phospho-tau were quantified using Histelide in regions of cerebral cortex from 420 brain autopsies. Total standard daily doses of prescription opioid and non-aspirin nonsteroidal anti-inflammatory drug (NSAID) exposure during a defined 10-year exposure window were identified using automated pharmacy dispensing data and used to classify people as having no/low, intermediate, or high exposure. People with high NSAID exposure had significantly greater Aβ42 concentration in middle frontal gyrus and superior and middle temporal gyri, but not inferior parietal lobule; no Aβ42 regional concentration was associated with prescription opioid usage. People with high opioid usage had significantly greater concentration of phospho-tau in middle frontal gyrus than people with little-to-no opioid usage. Consistent with our previous studies, findings suggest that high levels of NSAID use in older individuals may promote Aβ42 accumulation in cerebral cortex.
Keywords: Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Analgesics; Analgesics, Opioid; Anti-Inflammatory Agents, Non-Steroidal; Autopsy; Cerebral Cortex; Female; Humans; Logistic Models; Male; Peptide Fragments; Prospective Studies; tau Proteins

Associations of Dietary Protein and Fiber Intake with Brain and Blood Amyloid-β. - Fernando, W M A D Binosha; Rainey-Smith, Stephanie R; Gardener, Samantha L; Villemagne, Victor L; Burnham, Samantha C; Macaulay, S Lance; Brown, Belinda M; Gupta, Veer Bala; Sohrabi, Hamid R; Weinborn, Michael; Taddei, Kevin; Laws, Simon M; et al. (J Alzheimers Dis, 2018)
Accumulating evidence suggests a diet high in protein and fiber may confer some protection against Alzheimer's disease (AD). However, no human studies to-date have assessed the relationship between protein and fiber intake, and plasma and brain amyloid-β (Aβ). Consequently, this cross-sectional study, investigated the association of self-reported dietary intakes of protein and fiber, with plasma and brain Aβ burden (n = 541, and n = 162 respectively), in a well-characterized cohort of cognitively normal older adults, drawn from the larger Australian Imaging, Biomarkers and Lifestyle (AIBL) study of aging. We observed 12.59 and 8.43 higher odds of 'high' brain Aβ burden (PiB PET SUVR≥1.5) if protein intake fell in the lowest and middle tertile, respectively, compared to the highest tertile (p = 0.008; p = 0.013). Thus, in this cohort, the more protein consumed, the less likelihood of 'high' Aβ burden in the brain. No other significant associations were observed. The results of this study highlight the potentially protective impact of high dietary protein intake on brain Aβ burden in older adults, before objective memory decline is apparent. While longitudinal validation is required, these findings may assist in the development of dietary approaches aimed at preventing or delaying AD onset.
Keywords: Aged; Alzheimer Disease; Amyloid beta-Peptides; Australia; Biomarkers; Brain; Cognition; Cohort Studies; Cross-Sectional Studies; Dietary Fiber; Dietary Proteins; Female; Humans; Logistic Models; Male; Middle Aged; Neuropsychological Tests; Positron-Emission Tomography

Cerebrospinal Fluid Amyloid-β Levels are Increased in Patients with Insomnia. - Chen, Dong-Wan; Wang, Jun; Zhang, Li-Li; Wang, Yan-Jiang; Gao, Chang-Yue (J Alzheimers Dis, 2018)
Previous studies demonstrate that patients with sleep disorders are at risk of developing Alzheimer's disease (AD), with the mechanism unknown. It is suggested that acute sleep deprivation induces an increase of amyloid-β (Aβ), the major pathological agent in AD, in the cerebrospinal fluid (CSF). In the present study, we recruited 23 patients with chronic insomnia aged between 46 to 67 years and 23 healthy controls aged between 43 to 67 years. We investigated the CSF levels of Aβ and tau, another pathological hallmark in the AD pathogenesis. We found that CSF Aβ42 levels were significantly increased in insomnia patients. However, no significant difference was found in Aβ40, total tau (t-Tau), and phosphorylated tau (p-Tau) between the two groups. Furthermore, we found that CSF Aβ40 and Aβ42 levels are significantly correlated with the sleep quality, as reflected by the Pittsburgh Sleep Quality Index (PSQI) scores. But no significant correlation was found in CSF t-Tau and p-Tau levels with PSQI. Our results indicate that chronic sleep disorders may induce the disruption of Aβ metabolism in the brain, thus increase the risk for developing AD.
Keywords: Adult; Aged; Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Female; Humans; Male; Middle Aged; Phosphorylation; Sleep Initiation and Maintenance Disorders; tau Proteins

Cerebrospinal Fluid, MRI, and Florbetaben-PET in Cerebral Amyloid Angiopathy-Related Inflammation. - Renard, Dimitri; Collombier, Laurent; Demattei, Christophe; Wacongne, Anne; Charif, Mahmoud; Ayrignac, Xavier; Azakri, Souhayla; Gaillard, Nicolas; Boudousq, Vincent; Lehmann, Sylvain; Menjot de Champfleur, Nicolas; Thouvenot, Eric (J Alzheimers Dis, 2018)
BACKGROUND: Cerebral amyloid angiopathy-related inflammation (CAA-ri) is associated with a cerebrospinal fluid (CSF) biomarker profile similar to that observed in CAA. Few CAA-ri patients have been studied by fibrillar amyloid-β (Aβ) imaging (using 11C-Pittsburgh compound B and 18F-florbetapir, but not 18F-florbetaben). OBJECTIVE: To describe CSF biomarkers, magnetic resonance imaging (MRI), and 18F-florbetaben (FBB)-positron emission tomography (PET) changes in CAA-ri patients. METHODS: CSF levels of total tau, phosphorylated tau, Aβ1-42, and Aβ1-40, MRI (cerebral microbleeds count on susceptibility-weighted imaging and semi-quantitative analysis of fluid-attenuation inversion recovery white matter hyperintensities), and FBB-PET (using both cerebellar cortex and pons to calculate standardized uptake value ratios) were analyzed in nine consecutive CAA-ri patients. RESULTS: A median number of 769 cerebral microbleeds/patient were counted on MRI. When using the pons as reference region, amyloid load on FBB-PET was very strongly correlated to CSF Aβ1-40 levels (rho = -0.83, p = 0.008) and moderately correlated to cerebral microbleed numbers in the occipital lobes (rho = 0.59, p = 0.001), while comparisons with other CSF biomarkers were not statistically significant (total tau, rho = -0.63, p = 0.076; phosphorylated tau, rho = -0.68, p = 0.05; Aβ1-42, rho = -0.59, p = 0.09). All correlations were weaker, and not statistically significant, when using the cerebellum as reference region. A non-significant correlation (rho = -0.50, p = 0.18) was observed between CSF Aβ1-40 levels and cerebral microbleed numbers. CONCLUSION: In CAA-ri, CSF Aβ1-40 levels correlated well with amyloid load assessed by FBB-PET when the pons was used as reference, and to a lesser degree with cerebral microbleeds count on MRI. This confirms earlier data on CSF Aβ1-40 as an in vivo marker for CAA and CAA-ri.
Keywords: Aged; Aged, 80 and over; Amyloid beta-Peptides; Aniline Compounds; Biomarkers; Brain; Cerebral Amyloid Angiopathy; Female; Humans; Magnetic Resonance Imaging; Male; Middle Aged; Multivariate Analysis; Positron-Emission Tomography; Prospective Studies; Stilbenes; tau Proteins; Vasculitis, Central Nervous System

Circulating Progenitor Cells Correlate with Memory, Posterior Cortical Thickness, and Hippocampal Perfusion. - Nation, Daniel A; Tan, Alick; Dutt, Shubir; McIntosh, Elissa C; Yew, Belinda; Ho, Jean K; Blanken, Anna E; Jang, Jung Yun; Rodgers, Kathleen E; Gaubert, Aimée (J Alzheimers Dis, 2018)
BACKGROUND: Bone marrow-derived progenitor cells survey the vasculature and home to sites of tissue injury where they can promote repair and regeneration. It has been hypothesized that these cells may play a protective role neurodegenerative and vascular cognitive impairment. OBJECTIVE: To evaluate progenitor cell levels in older adults with and without mild cognitive impairment (MCI), and to relate circulating levels to memory, brain volume, white matter lesion volume, and cerebral perfusion. METHOD: Thirty-two older adults, free of stroke and cardiovascular disease, were recruited from the community and evaluated for diagnosis of MCI versus cognitively normal (CN). Participants underwent brain MRI and blood samples were taken to quantify progenitor reserve using flow cytometry (CD34+, CD34+CD133+, and CD34+CD133+CD309+ cells). RESULTS: Participants with MCI (n = 10) exhibited depletion of all CPC markers relative to those who were CN (n = 22), after controlling for age, sex, and education. Post-hoc age, sex, and education matched comparisons (n = 10 MCI, n = 10 CN) also revealed the same pattern of results. Depletion of CD34+ cells correlated with memory performance, left posterior cortical thickness, and bilateral hippocampal perfusion. Participants exhibited low levels of vascular risk and white matter lesion burden that did not correlate with progenitor levels. CONCLUSIONS: Circulating progenitor cells are associated with cognitive impairment, memory, cortical atrophy, and hippocampal perfusion. We hypothesize that progenitor depletion contributes to, or is triggered by, cognitive decline and cortical atrophy. Further study of progenitor cell depletion in older adults may benefit efforts to prevent or delay dementia.
Keywords: Aged; Aged, 80 and over; Antigens, CD; Apolipoproteins E; Cerebral Cortex; Cognitive Dysfunction; Female; Flow Cytometry; Hippocampus; Humans; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Male; Middle Aged; Neuropsychological Tests; Perfusion; Stem Cells; White Matter

A Clinically-Translatable Machine Learning Algorithm for the Prediction of Alzheimer's Disease Conversion in Individuals with Mild and Premild Cognitive Impairment. - Grassi, Massimiliano; Perna, Giampaolo; Caldirola, Daniela; Schruers, Koen; Duara, Ranjan; Loewenstein, David A (J Alzheimers Dis, 2018)
BACKGROUND: Available therapies for Alzheimer's disease (AD) can only alleviate and delay the advance of symptoms, with the greatest impact eventually achieved when provided at an early stage. Thus, early identification of which subjects at high risk, e.g., with MCI, will later develop AD is of key importance. Currently available machine learning algorithms achieve only limited predictive accuracy or they are based on expensive and hard-to-collect information. OBJECTIVE: The current study aims to develop an algorithm for a 3-year prediction of conversion to AD in MCI and PreMCI subjects based only on non-invasively and effectively collectable predictors. METHODS: A dataset of 123 MCI/PreMCI subjects was used to train different machine learning techniques. Baseline information regarding sociodemographic characteristics, clinical and neuropsychological test scores, cardiovascular risk indexes, and a visual rating scale for brain atrophy was used to extract 36 predictors. Leave-pair-out-cross-validation was employed as validation strategy and a recursive feature elimination procedure was applied to identify a relevant subset of predictors. RESULTS: 16 predictors were selected from all domains excluding sociodemographic information. The best model resulted a support vector machine with radial-basis function kernel (whole sample: AUC = 0.962, best balanced accuracy = 0.913; MCI sub-group alone: AUC = 0.914, best balanced accuracy = 0.874). CONCLUSIONS: Our algorithm shows very high cross-validated performances that outperform the vast majority of the currently available algorithms, and all those which use only non-invasive and effectively assessable predictors. Further testing and optimization in independent samples will warrant its application in both clinical practice and clinical trials.
Keywords: Aged; Aged, 80 and over; Algorithms; Alzheimer Disease; Area Under Curve; Atrophy; Brain; Cognitive Dysfunction; Disease Progression; Female; Humans; Logistic Models; Machine Learning; Magnetic Resonance Imaging; Male; Neuropsychological Tests; Predictive Value of Tests; Prognosis; Regression Analysis; Sensitivity and Specificity; Support Vector Machine

Clinic-Based Validation of Cerebrospinal Fluid Biomarkers with Florbetapir PET for Diagnosis of Dementia. - Álvarez, Ignacio; Aguilar, Miquel; González, Jose Manuel; Ysamat, Montse; Lorenzo-Bosquet, Carles; Alonso, Alvaro; Tartari, Juan Pablo; Romero, Silvia; Diez-Fairen, Monica; Carcel, Maria; Pujalte, Francisco; Pastor, Pau (J Alzheimers Dis, 2018)
BACKGROUND: Cerebrospinal fluid (CSF) biomarker studies have shown variable accuracy for diagnosis of Alzheimer's disease (AD); therefore, internal validation is recommended. OBJECTIVE: To investigate the correlation between CSF biomarkers and cerebral 18-Florbetapir positron emission tomography (Amyloid-PET) and calculate their sensitivity and specificity to obtain the optimal clinical cut-off points to diagnose the etiology of cognitive impairment. METHODS: We performed Amyloid-PET scans and CSF biomarker levels analyses in 68 subjects (50 with mild cognitive impairment, 11 with AD dementia, and 7 with non-AD dementia). Visual examination of Amyloid-PET scans was performed. CSF analyses were performed using standard sandwich ELISA. RESULTS: Amyloid-PET was positive in 36 subjects, negative in 26, and inconclusive in 6. Optimal clinical cut-off points for CSF markers were the following: amyloid-β 1-42 (Aβ42) = 629 pg/ml, total tau (t-tau) = 532 pg/ml, phosphorylated tau (p-tau) = 88 pg/ml, and t-tau/Aβ42 ratio = 0.58. T-tau/Aβ42 ratio showed the best sensitivity and specificity (92 and 84%, respectively). T-tau and p-tau CSF levels (r2 = 0.867) followed by the t-tau and t-tau/Aβ42 CSF ratio (r2 = 0.666) showed the strongest inter-marker correlation. Interestingly, subjects with inconclusive Amyloid-PET showed intermediate values for all CSF markers between negative and positive Amyloid-PET groups. CONCLUSIONS: CSF t-tau/Aβ42 ratio appears to be the most accurate AD CSF marker. The presence of intermediate values for CSF markers among the subjects with inconclusive Amyloid-PET suggests the presence of other dementias associated with AD pathology or intermediate phenotypes.
Keywords: Aged; Amyloid beta-Peptides; Analysis of Variance; Aniline Compounds; Apolipoproteins E; Biomarkers; Cognition Disorders; Dementia; Ethylene Glycols; Female; Humans; Male; Middle Aged; Peptide Fragments; Positron-Emission Tomography; tau Proteins

Co-Expression of Glia Maturation Factor and Apolipoprotein E4 in Alzheimer's Disease Brain. - Thangavel, Ramasamy; Bhagavan, Sachin M; Ramaswamy, Swathi Beladakere; Surpur, Spurthi; Govindarajan, Raghav; Kempuraj, Duraisamy; Zaheer, Smita; Raikwar, Sudhanshu; Ahmed, Mohammad E; Selvakumar, Govindhasamy Pushpavathi; Iyer, Shankar S; Zaheer, Asgar (J Alzheimers Dis, 2018)
Apolipoprotein E4 (ApoE4) is a major genetic risk factor for Alzheimer's disease (AD). The E4 allele of ApoE plays a crucial role in the inflammatory and neurodegenerative processes associated with AD. This is evident from the multiple effects of the ApoE isoforms in amyloid-β (Aβ) aggregation. Glia maturation factor (GMF) is a brain-specific neuroinflammatory protein that we have previously demonstrated to be significantly upregulated in various regions of AD brains compared to non-AD control brains and that it induces neurodegeneration. We have previously reported that GMF is predominantly expressed in the reactive astrocytes surrounding amyloid plaques (APs) in AD brain. In the present study, using immunohistochemical and dual immunofluorescence staining, we show the expression and colocalization of GMF and ApoE4 in AD brains. Our results show that ApoE4 is present within the APs of AD brain. Further, we found that GMF and ApoE4 were strongly expressed and co-associated in APs and in the reactive astrocytes surrounding APs in AD. An increased expression of GMF in APs and neurofibrillary tangles in the AD brain, and the co-localization of GMF and ApoE4 in APs suggest that GMF and ApoE4 together should be contributing to the neuropathological changes associated with AD.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Apolipoprotein E4; Brain; Case-Control Studies; Fluorescent Antibody Technique; Glia Maturation Factor; Humans; Neurofibrillary Tangles; Plaque, Amyloid

Cognitive Variability Predicts Incident Alzheimer's Disease and Mild Cognitive Impairment Comparable to a Cerebrospinal Fluid Biomarker. - Gleason, Carey E; Norton, Derek; Anderson, Eric D; Wahoske, Michelle; Washington, Danielle T; Umucu, Emre; Koscik, Rebecca L; Dowling, N Maritza; Johnson, Sterling C; Carlsson, Cynthia M; Asthana, Sanjay (J Alzheimers Dis, 2018)
BACKGROUND: Alzheimer's disease (AD) biomarkers are emerging as critically important for disease detection and monitoring. Most biomarkers are obtained through invasive, resource-intense procedures. A cognitive marker, intra-individual cognitive variability (IICV) may provide an alternative or adjunct marker of disease risk for individuals unable or disinclined to undergo lumbar puncture. OBJECTIVE: To contrast risk of incident AD and mild cognitive impairment (MCI) associated with IICV to risk associated with well-established biomarkers: cerebrospinal fluid (CSF) phosphorylated tau protein (p-tau181) and amyloid-β 42 (Aβ42) peptide. METHODS: Dispersion in cognitive performance, IICV, was estimated with a published algorithm, and included Trail Making Test A and B, Rey Auditory Verbal Learning Test (RAVLT), and the American National Adult Reading Test (ANART). CSF biomarkers were expressed as a ratio: p-tau181/Aβ42, wherein high values signified pathognomonic profiles. Logistic regression models included longitudinal data from 349 Alzheimer's Disease Neuroimaging Initiative (ADNI) participants who completed lumbar puncture. All subjects were cognitively healthy (n = 105) or diagnosed with MCI (n = 244) at baseline. We examined odds of conversion associated with baseline elevations in IICV and/or ratio of CSF p-tau181/Aβ42. RESULTS: When included in models alone or in combination with CSF p-tau181/Aβ42, one standard IICV unit higher was associated with an estimated odds ratio for incident AD or MCI of 2.81 (95% CI: 1.83-4.33) in the most inclusive sample, and an odds ratio of 3.41 (95% CI: 2.03-5.73) when restricted to participants with MCI. Iterative analyses suggested that IICV independently improved model fit even when individual index components were included in comparative models. CONCLUSIONS: These analyses provide preliminary support for IICV as a marker of incident AD and MCI. This easily-disseminated, non-invasive marker compared favorably to well-established CSF biomarkers.
Keywords: Aged; Aged, 80 and over; Algorithms; Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Cognitive Dysfunction; Cross-Sectional Studies; Female; Humans; Incidence; Logistic Models; Male; Middle Aged; Neuropsychological Tests; Peptide Fragments; Statistics, Nonparametric; tau Proteins

Comparison between FCSRT and LASSI-L to Detect Early Stage Alzheimer's Disease. - Matías-Guiu, Jordi A; Cabrera-Martín, María Nieves; Curiel, Rosie E; Valles-Salgado, María; Rognoni, Teresa; Moreno-Ramos, Teresa; Carreras, José Luis; Loewenstein, David A; Matías-Guiu, Jorge (J Alzheimers Dis, 2018)
BACKGROUND: The Free and Cued Selective Reminding Test (FCSRT) is the most accurate test for the diagnosis of prodromal Alzheimer's disease (AD). Recently, a novel cognitive test, the Loewenstein-Acevedo Scale for Semantic Interference and Learning (LASSI-L), has been developed in order to provide an early diagnosis. OBJECTIVE: To compare the diagnostic accuracy of the FCSRT and the LASSI-L for the diagnosis of AD in its preclinical and prodromal stages using 18F-fluorodeoxyglucose positron emission tomography (FDG-PET) as a reference. METHODS: Fifty patients consulting for subjective memory complaints without functional impairment and at risk for AD were enrolled and evaluated using FCSRT, LASSI-L, and FDG-PET. Participants were evaluated using a comprehensive neurological and neuropsychological protocol and were assessed with the FCSRT and LASSI-L. FDG-PET was acquired concomitantly and used for classification of patients as AD or non-AD according to brain metabolism using both visual and semi-quantitative methods. RESULTS: LASSI-L scores allowed a better classification of patients as AD/non-AD in comparison to FCSRT. Logistic regression analysis showed delayed recall and failure to recovery from proactive semantic interference from LASSI-L as independent statistically significant predictors, obtaining an area under the curve of 0.894. This area under the curve provided a better discrimination than the best FCSRT score (total delayed recall, area under the curve 0.708, p = 0.029). CONCLUSIONS: The LASSI-L, a cognitive stress test, was superior to FCSRT in the prediction of AD features on FDG-PET. This emphasizes the possibility to advance toward an earlier diagnosis of AD from a clinical perspective.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cues; Female; Fluorodeoxyglucose F18; Humans; Male; Memory Disorders; Mental Recall; Middle Aged; Neuropsychological Tests; Positron-Emission Tomography; Psychiatric Status Rating Scales; ROC Curve; Semantics

Complexity and Selectivity of γ-Secretase Cleavage on Multiple Substrates: Consequences in Alzheimer's Disease and Cancer. - Medoro, Alessandro; Bartollino, Silvia; Mignogna, Donatella; Passarella, Daniela; Porcile, Carola; Pagano, Aldo; Florio, Tullio; Nizzari, Mario; Guerra, Germano; Di Marco, Roberto; Intrieri, Mariano; Raimo, Gennaro; et al. (J Alzheimers Dis, 2018)
The processing of the amyloid-β protein precursor (AβPP) by β- and γ-secretases is a pivotal event in the genesis of Alzheimer's disease (AD). Besides familial mutations on the AβPP gene, or upon its overexpression, familial forms of AD are often caused by mutations or deletions in presenilin 1 (PSEN1) and 2 (PSEN2) genes: the catalytic components of the proteolytic enzyme γ-secretase (GS). The "amyloid hypothesis", modified over time, states that the aberrant processing of AβPP by GS induces the formation of specific neurotoxic soluble amyloid-β (Aβ) peptides which, in turn, cause neurodegeneration. This theory, however, has recently evidenced significant limitations and, in particular, the following issues are debated: 1) the concept and significance of presenilin's "gain of function" versus "loss of function"; and 2) the presence of several and various GS substrates, which interact with AβPP and may influence Aβ formation. The latter consideration is suggestive: despite the increasing number of GS substrates so far identified, their reciprocal interaction with AβPP itself, even in the AD field, is significantly unexplored. On the other hand, GS is also an important pharmacological target in the cancer field; inhibitors or GS activity are investigated in clinical trials for treating different tumors. Furthermore, the function of AβPP and PSENs in brain development and in neuronal migration is well known. In this review, we focused on a specific subset of GS substrates that directly interact with AβPP and are involved in its proteolysis and signaling, by evaluating their role in neurodegeneration and in cell motility or proliferation, as a possible connection between AD and cancer.
Keywords: Alzheimer Disease; Amyloid beta-Protein Precursor; Amyloid Precursor Protein Secretases; Humans; Neoplasms; Presenilin-1

Concordance Between Cerebrospinal Fluid Biomarkers with Alzheimer's Disease Pathology Between Three Independent Assay Platforms. - Doecke, James D; Rembach, Alan; Villemagne, Victor L; Varghese, Shiji; Rainey-Smith, Stephanie; Sarros, Shannon; Evered, Lisbeth A; Fowler, Christopher J; Pertile, Kelly K; Rumble, Rebecca L; Trounson, Brett; Taddei, Kevin; et al. (J Alzheimers Dis, 2018)
BACKGROUND: To enhance the accuracy of clinical diagnosis for Alzheimer's disease (AD), pre-mortem biomarkers have become increasingly important for diagnosis and for participant recruitment in disease-specific treatment trials. Cerebrospinal fluid (CSF) biomarkers provide a low-cost alternative to positron emission tomography (PET) imaging for in vivo quantification of different AD pathological hallmarks in the brains of affected subjects; however, consensus around the best platform, most informative biomarker and correlations across different methodologies are controversial. OBJECTIVE: Assessing levels of Aβ-amyloid and tau species determined using three different versions of immunoassays, the current study explored the ability of CSF biomarkers to predict PET Aβ-amyloid (32 Aβ-amyloid-and 45 Aβ-amyloid+), as well as concordance between CSF biomarker levels and PET Aβ-amyloid imaging. METHODS: Prediction and concordance analyses were performed using a sub-cohort of 77 individuals (48 healthy controls, 15 with mild cognitive impairment, and 14 with AD) from the Australian Imaging Biomarker and Lifestyle study of aging. RESULTS: Across all three platforms, the T-tau/Aβ42 ratio biomarker had modestly higher correlation with SUVR/BeCKeT (ρ= 0.69-0.8) as compared with Aβ42 alone (ρ= 0.66-0.75). Differences in CSF biomarker levels between the PET Aβ-amyloid-and Aβ-amyloid+ groups were strongest for the Aβ42/Aβ40 and T-tau/Aβ42 ratios (p < 0.0001); however, comparison of predictive models for PET Aβ-amyloid showed no difference between Aβ42 alone and the T-tau/Aβ42 ratio. CONCLUSION: This study confirms strong concordance between CSF biomarkers and PET Aβ-amyloid status is independent of immunoassay platform, supporting their utility as biomarkers in clinical practice for the diagnosis of AD and for participant enrichment in clinical trials.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Cognition Disorders; Female; Humans; Male; Mental Status Schedule; Peptide Fragments; Positron-Emission Tomography; ROC Curve; tau Proteins

Decreased Prefrontal Activation during Matrix Reasoning in Predementia Progranulin Mutation Carriers. - Alexander, Courtney; Zeithamova, Dagmar; Hsiung, Ging-Yuek R; Mackenzie, Ian R; Jacova, Claudia (J Alzheimers Dis, 2018)
We tested the potential of task-based functional neuroimaging as a biomarker of emerging prefrontal brain changes in progranulin (GRN) mutations carriers. Five GRN mutation carriers free of frontotemporal dementia (FTD) and 11 non-carriers from families with FTD-GRN underwent functional MRI while solving matrix-reasoning problems. Mutation carriers displayed slower responses for more difficult problems and lower lateral prefrontal activation across all problems. Overall task-evoked posterior ventrolateral prefrontal activation predicted mutation status with 100% sensitivity and 91% specificity. Volumetric differences did not account for activation differences. Prefrontal activation may have utility as a biomarker in GRN mutation.
Keywords: Adult; Biomarkers; Female; Frontotemporal Dementia; Functional Neuroimaging; Heterozygote; Humans; Magnetic Resonance Imaging; Male; Middle Aged; Mutation; Prefrontal Cortex; Progranulins

Deep Brain Stimulation of Frontal Lobe Networks to Treat Alzheimer's Disease. - Scharre, Douglas W; Weichart, Emily; Nielson, Dylan; Zhang, Jun; Agrawal, Punit; Sederberg, Per B; Knopp, Michael V; Rezai, Ali R (J Alzheimers Dis, 2018)
The study objective was to evaluate the safety and efficacy of deep brain stimulation (DBS) at the ventral capsule/ventral striatum (VC/VS) region to specifically modulate frontal lobe behavioral and cognitive networks as a novel treatment approach for Alzheimer's disease (AD) patients. This is a non-randomized phase I prospective open label interventional trial of three subjects with matched comparison groups. AD participants given DBS for at least 18 months at the VC/VS target were compared on the Clinical Dementia Rating-Sum of Boxes (CDR-SB), our primary outcome clinical measure, to matched groups without DBS from the AD Neuroimaging Initiative (ADNI) cohort. Serial 2-Deoxy-2-[18F]fluoro-D-glucose (FDG) positron emission tomography (PET) images of AD participants were also compared longitudinally over time. Three AD DBS participants were matched to subjects from the ADNI cohort. All participants tolerated DBS well without significant adverse events. All three AD DBS participants had less performance decline and two of them meaningfully less decline over time on our primary outcome measure, CDR-SB, relative to matched comparison groups from the ADNI using score trajectory slopes. Minimal changes or increased metabolism on FDG-PET were seen in frontal cortical regions after chronic DBS at the VC/VS target. The first use of DBS in AD at a frontal lobe behavior regulation target (VC/VS) was well-tolerated and revealed less performance decline in CDR-SB. Frontal network modulation to improve executive and behavioral deficits should be furthered studied in AD.
Keywords: Aged; Alzheimer Disease; Deep Brain Stimulation; Female; Frontal Lobe; Humans; Male; Middle Aged; Ohio; Pilot Projects; Positron-Emission Tomography; Prospective Studies

Delirium Severity Post-Surgery and its Relationship with Long-Term Cognitive Decline in a Cohort of Patients without Dementia. - Vasunilashorn, Sarinnapha M; Fong, Tamara G; Albuquerque, Asha; Marcantonio, Edward R; Schmitt, Eva M; Tommet, Douglas; Gou, Yun; Travison, Thomas G; Jones, Richard N; Inouye, Sharon K (J Alzheimers Dis, 2018)
BACKGROUND: Delirium has been associated with more rapid cognitive decline. However, it is unknown whether increased delirium severity is associated with a higher rate of long-term cognitive decline. OBJECTIVE: To evaluate delirium severity and the presence and rate of cognitive decline over 36 months following surgery. METHODS: We examined patients from the Successful Aging after Elective Surgery Study, who were age ≥70 years undergoing major elective surgery (N = 560). Delirium severity was determined by the peak Confusion Assessment Method-Severity (CAM-S) score for each patient's hospitalization and grouped based on the sample distribution: scores of 0-2, 3-7, and 8-19. A neuropsychological composite, General Cognitive Performance (GCP), and proxy-reported Informant Questionnaire for Cognitive Decline (IQCODE) were used to examine cognitive outcomes following surgery at 0, 1, and 2 months, and then every 6 months for up to 3 years. RESULTS: No significant cognitive decline was observed for patients with peak CAM-S scores 0-2 (-0.17 GCP units/year, 95% confidence interval [CI] -0.35, 0.01). GCP scores decreased significantly in the group with peak CAM-S scores 3-7 (-0.30 GCP units/year, 95% CI -0.51, -0.09), and decreased almost three times faster in the highest delirium severity group (peak CAM-S scores 8-19; -0.82 GCP units/year, 95% CI -1.28, -0.37). A similar association was found for delirium severity and the proportion of patients who developed IQCODE impairment over time. CONCLUSION: Patients with the highest delirium severity experienced the greatest rate of cognitive decline, which exceeds the rate previously observed for patients with dementia, on serial neuropsychological testing administered over 3 years, with a dose-response relationship between delirium severity and long-term cognitive decline.
Keywords: Aged; Aged, 80 and over; Cognitive Dysfunction; Cohort Studies; Delirium; Elective Surgical Procedures; Female; Humans; Male; Neuropsychological Tests; Postoperative Complications; Severity of Illness Index

Designing an Internet-Based Multidomain Intervention for the Prevention of Cardiovascular Disease and Cognitive Impairment in Older Adults: The HATICE Trial. - Barbera, Mariagnese; Mangialasche, Francesca; Jongstra, Susan; Guillemont, Juliette; Ngandu, Tiia; Beishuizen, Cathrien; Coley, Nicola; Brayne, Carol; Andrieu, Sandrine; Richard, Edo; Soininen, Hilkka; Kivipelto, Miia (J Alzheimers Dis, 2018)
BACKGROUND: Many dementia and cardiovascular disease (CVD) cases in older adults are attributable to modifiable vascular and lifestyle-related risk factors, providing opportunities for prevention. In the Healthy Aging Through Internet Counselling in the Elderly (HATICE) randomized controlled trial, an internet-based multidomain intervention is being tested to improve the cardiovascular risk (CVR) profile of older adults. OBJECTIVE: To design a multidomain intervention to improve CVR, based on the guidelines for CVR management, and administered through a coach-supported, interactive, platform to over 2500 community-dwellers aged 65+ in three European countries. METHODS: A comparative analysis of national and European guidelines for primary and secondary CVD prevention was performed. Results were used to define the content of the intervention. RESULTS: The intervention design focused on promoting awareness and self-management of hypertension, dyslipidemia, diabetes mellitus, and overweight, and supporting smoking cessation, physical activity, and healthy diet. Overall, available guidelines lacked specific recommendations for CVR management in older adults. The comparative analysis of the guidelines showed general consistency for lifestyle-related recommendations. Key differences, identified mostly in methods used to assess the overall CVR, did not hamper the intervention design. Minor country-specific adaptations were implemented to maximize the intervention feasibility in each country. CONCLUSION: Despite differences in CVR management within the countries considered, it was possible to design and implement the HATICE multidomain intervention. The study can help define preventative strategies for dementia and CVD that are applicable internationally.
Keywords: Aged; Aged, 80 and over; Cardiovascular Diseases; Cognitive Dysfunction; Counseling; Europe; Exercise; Female; Healthy Aging; Humans; Internet; Life Style; Male; Practice Guidelines as Topic; Risk Factors; Telemedicine

Development of a High-Sensitivity Method for the Measurement of Human Nasal Aβ42, Tau, and Phosphorylated Tau. - Liu, Ziyi; Kameshima, Naoko; Nanjo, Toshifumi; Shiino, Akihiko; Kato, Tomoko; Shimizu, Shino; Shimizu, Takeshi; Tanaka, Sachiko; Miura, Katsuyuki; Tooyama, Ikuo (J Alzheimers Dis, 2018)
Cost-effective and feasible methods for early diagnosis of Alzheimer's disease (AD) are needed. We present two methods to measure AD-related biomarkers simultaneously from one nasal smear for the purpose of diagnosing AD. Japanese men and women aged 63-85 years old were recruited in 2015-2016 for this case-control study. A total of 25 AD cases and 25 controls (22 men and 28 women) participated in this research. Nasal smears were collected from the common nasal meatus, inferior concha, middle nasal meatus, and olfactory cleft, and the proteins in the samples were analyzed by two methods, which we named PGD (Pre-treatment with guanidine- n-Dodecyl-beta-D-maltoside solution) method 1 (PGD-I) and 2 (PGD-II). The PGD-I method measured total tau and amyloid-β (Aβ)42, but no differences in median levels of total tau and Aβ42 between AD cases and controls were found in any of the nasal locations. The PGD-II method measured Aβ42, total tau, and phosphorylated tau, but levels of Aβ40 in all nasal locations of both groups were near zero. Median levels of phosphorylated tau to total tau (p-tau/t-tau) ratios in the middle nasal meatus and in the olfactory cleft were significantly higher in AD cases than in controls, and could significantly predict AD. To assess diagnostic reliability, areas under the ROC curve were 0.74 (95% CL = 0.52-0.95, p = 0.030) for the middle nasal meatus and 0.72 (95% CL = 0.52-0.92, p = 0.029) for the olfactory cleft. Thus, PGD-I and PGD-II can detect AD-related biomarkers in nasal smears and PGD-II may be a useful tool for diagnosing AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Case-Control Studies; Female; Humans; Male; Middle Aged; Nasal Mucosa; Peptide Fragments; Phosphorylation; Reproducibility of Results; ROC Curve; tau Proteins

The Diagnostic and Prognostic Value of a Dual-Tasking Paradigm in a Memory Clinic. - Nielsen, Malene Schjnning; Simonsen, Anja Hviid; Siersma, Volkert; Hasselbalch, Steen Gregers; Hoegh, Peter (J Alzheimers Dis, 2018)
BACKGROUND: Daily living requires the ability to perform dual-tasking. As cognitive skills decrease in dementia, performing a cognitive and motor task simultaneously become increasingly challenging and subtle gait abnormalities may even be present in pre-dementia stages. Therefore, a dual-tasking paradigm, such as the Timed Up and Go-Dual Task (TUG-DT), may be useful in the diagnostic assessment of mild cognitive impairment (MCI). OBJECTIVE: To investigate the diagnostic and prognostic ability of a dual-tasking paradigm in patients with MCI or mild Alzheimer's disease (AD) and to evaluate the association between the dual-tasking paradigm and cerebrospinal fluid (CSF) AD biomarkers. METHODS: The study is a prospective cohort study conducted in a clinical setting in two memory clinics. Eighty-six patients were included (28 MCI, 17 AD, 41 healthy controls (HC)). The ability to perform dual-tasking was evaluated by the TUG-DT. Patients underwent a standardized diagnostic assessment and were evaluated to determine progression yearly. RESULTS: ROC curve analysis illustrated a high discriminative ability of the dual-tasking paradigm in separating MCI patients from HC (AUC: 0.78, AUC: 0.82) and a moderate discriminative ability in separating MCI from AD (AUC: 0.73, AUC: 0.55). Performance discriminated clearly between all groups (p < 0.01). Logistic regression analyses revealed a low prognostic value of the dual-tasking paradigm for progression and rate of cognitive decline. A moderately strong correlation between the dual-tasking paradigm and CSF AD biomarkers was observed. CONCLUSION: In our study, we found that patients with MCI and mild AD have increasing difficulties in dual-tasking compared to healthy elderly. Hence, the dual-tasking paradigm may be a potential complement in the diagnostic assessment in a typical clinical setting.
Keywords: Aged; Alzheimer Disease; Biomarkers; Case-Control Studies; Cognitive Dysfunction; Disease Progression; Female; Humans; Logistic Models; Male; Memory; Middle Aged; Neuropsychological Tests; Prognosis; Prospective Studies; ROC Curve

Differences in Synaptic Dysfunction Between rTg4510 and APP/PS1 Mouse Models of Alzheimer's Disease. - Gelman, Simon; Palma, Jonathan; Tombaugh, Geoffrey; Ghavami, Afshin (J Alzheimers Dis, 2018)
Genetically modified mice have provided insights into the progression and pathology of Alzheimer's disease (AD). Here, we have examined two mouse models of AD: the rTg4510 mouse, which overexpresses mutant human Tau gene, and the APP/PS1 mouse, which overexpresses mutant human genes for amyloid precursor protein and presenilin 1. Both models exhibit deficits in hippocampal function, but comparative analyses of these deficits are sparse. We used extracellular field potential recordings in hippocampal slices to study basal synaptic transmission (BST), paired-pulse facilitation (PPF), and long-term potentiation (LTP) at the Schaffer collateral-CA1 pyramidal cell synapses in both models. We found that 6-7, but not 2-3-month-old rTg4510 mice exhibited reduced pre-synaptic activation (fiber volley (FV) amplitude, ∼50%) and field excitatory post-synaptic potential (fEPSP) slope (∼40%) compared to wild-type controls. In contrast to previous reports, BST, when controlled for FV amplitude, was not altered in rTg4510. APP/PS1 mice (2-3 mo and 8-10 mo) had unchanged FV amplitude compared to wild-type controls, while fEPSP slope was reduced by ∼34% in older mice, indicating a deficit in BST. PPF was unchanged in 8-10-month-old APP/PS1 mice, but was reduced in 6-7-month-old rTg4510 mice. LTP was reduced only in older rTg4510 and APP/PS1 mice. Our data suggest that BST deficits appear earlier in APP/PS1 than in rTg4510, which exhibited no BST deficits at the ages tested. However, FV and synaptic plasticity deficits developed earlier in rTg4510. These findings highlight fundamental differences in the progression of synaptic pathology in two genetically distinct models of AD.
Keywords: Age Factors; Alzheimer Disease; Amyloid beta-Protein Precursor; Analysis of Variance; Animals; Biophysics; Disease Models, Animal; Electric Stimulation; Excitatory Postsynaptic Potentials; Hippocampus; Humans; Mice; Mice, Transgenic; Mutation; Presenilin-1; Synapses; Synaptic Transmission; tau Proteins

Differential Pattern of Phospholipid Profile in the Temporal Cortex from E280A-Familiar and Sporadic Alzheimer's Disease Brains. - Villamil-Ortiz, Javier Gustavo; Barrera-Ocampo, Alvaro; Arias-Londoño, Julián David; Villegas, Andrés; Lopera, Francisco; Cardona-Gómez, Gloria Patricia (J Alzheimers Dis, 2018)
Lipids are considered important factors in the pathogenesis of Alzheimer's disease (AD). In this study, we realized a comparative analysis of the phospholipid profile and phospholipid composition of the temporal cortex from E280A-familiar AD (FAD), sporadic AD (SAD), and healthy human brains. Findings showed a significant decrease of lysophosphatidylcholine and phosphatidylethanolamine formed by low levels of polyunsaturated fatty acids (20 : 4, 22 : 6) in AD brains. However, phosphatidylethanolamine-ceramide and phosphoglycerol were significantly increased in SAD, conformed by high levels of (18 : 0/18 : 1) and (30/32/36 : 0/1/2), respectively. Together, the findings suggest a deficiency in lysophosphacholine and phosphatidylethanolamine, and alteration in the balance between poly- and unsaturated fatty acids in both types of AD, and a differential pattern of phospholipid profile and fatty acid composition between E280A FAD and SAD human brains.
Keywords: Adult; Aged; Aged, 80 and over; Alanine; Alzheimer Disease; Analysis of Variance; Fatty Acids; Female; Gene Expression Regulation; Glutamic Acid; Humans; Lysophosphatidylcholines; Male; Mass Spectrometry; Middle Aged; Mutation; Phosphatidylethanolamines; Phospholipids; Presenilin-1; Temporal Lobe

Dilated Perivascular Spaces in the Centrum Semiovale Begin to Develop in Middle Age. - Ishikawa, Masatsune; Yamada, Shigeki; Yamamoto, Kazuo (J Alzheimers Dis, 2018)
BACKGROUND: Dilated perivascular spaces in the centrum semiovale (CSO-PVS) are closely related to small vessel disease. However, recent studies have revealed that cerebral amyloid angiopathy can cause dilation of the CSO-PVS and obstruction of interstitial fluid flow along the intramural periarterial drainage. OBJECTIVE: To examine the severity and age-related prevalence of CSO-PVS through magnetic resonance imaging (MRI) and investigate their clinically relevant factors. METHODS: This study included 1,060 subjects who participated in our brain program. The subjects ranged from 23 to 83 years in age and were active in society. The frequencies of the MRI abnormalities of small vessel diseases, including CSO-PVS, were examined. The CSO-PVS severity was classified into three grades: G0, G1, G2, according to the visual rating. The subjects were divided into five age groups and their age-related frequencies were also studied. Using the clinico-laboratory data of 712 subjects, the clinically relevant factors of CSO-PVS were investigated using logistic regression analysis. RESULTS: The frequencies of all G0 ("normal") MRI abnormalities significantly decreased with age. A high prevalence of G2 CSO-PVS was observed (24%) in the youngest group aged≤39 years, whereas other MRI abnormalities in this group were not or rarely observed. In multivariable logistic regression analyses, G2 CSO-PVS was found to be closely associated with age, hypertension, and the estimated glomerular filtration ratio. CONCLUSIONS: This study reveals that CSO-PVS begin to develop in subjects aged less than 39 years. Age-related changes are involved. Further studies are necessary to elucidate the pathophysiological role of the CSO-PVS.
Keywords: Adult; Aged; Aged, 80 and over; Aging; Cerebral Amyloid Angiopathy; Corpus Callosum; Cross-Sectional Studies; Female; Humans; Japan; Logistic Models; Magnetic Resonance Imaging; Male; Middle Aged; Multivariate Analysis; Prospective Studies; Young Adult

Dysregulation and Dislocation of SFPQ Disturbed DNA Organization in Alzheimer's Disease and Frontotemporal Dementia. - Lu, Jing; Shu, Runzhe; Zhu, Yan (J Alzheimers Dis, 2018)
SFPQ (Splicing factor proline- and glutamine-rich) is a DNA and RNA binding protein involved in transcription, pre-mRNA splicing, and DNA damage repair. SFPQ was found dysregulated in a few tauopathies such as Alzheimer's disease (AD) and frontotemporal dementia (FTD). In addition, knock-down of SFPQ induced FTD-like behavior in mouse. To confirm the role of SFPQ in AD and FTD, we analyzed the brain sections from the AD and FTD brain samples with SFPQ upregulation and dislocation. Specifically, we observed SFPQ dislocated to the cytoplasm and nuclear envelopes, and DNA structures and organizations were associated with these dislocation phenotypes in AD and FTD brains. Consistently, we also found decreased DAPI intensities and smaller chromocenters associated with SFPQ dislocation in nerural-2a (N2a) cells. As the upregulation and hyperphosphorylation of tau protein is a hallmark of AD and FTD, our study sought to investigate potential interactions between tau and SFPQ by co-transfection and co-immunoprecipitation assays in N2a cells. SFPQ dislocation was found enhanced with tau co-transfection and tau co-transfection further resulted in extended DNA disorganization in N2a cells. Overall, our results indicate that dysregulation and dislocation of SFPQ and subsequent DNA disorganization might be a novel pathway in the progression of AD and FTD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Animals; Brain; Cell Line, Tumor; DNA Damage; Female; Frontotemporal Dementia; Gene Expression Regulation; Humans; Male; Mice; PTB-Associated Splicing Factor; tau Proteins; Translocation, Genetic

Early Stage Alterations in CA1 Extracellular Region Proteins Indicate Dysregulation of IL6 and Iron Homeostasis in the 5XFAD Alzheimer's Disease Mouse Model. - Gurel, Busra; Cansev, Mehmet; Sevinc, Cansu; Kelestemur, Seda; Ocalan, Busra; Cakir, Aysen; Aydin, Sami; Kahveci, Nevzat; Ozansoy, Mehmet; Taskapilioglu, Ozlem; Ulus, Ismail Hakki; Başar, Merve Karayel; et al. (J Alzheimers Dis, 2018)
In recent years, an increasing number of research papers revealed that the compositional and volumetric alterations in the extracellular matrix are the consequences of aging and may be related to Alzheimer's disease (AD). In this study, we aimed to demonstrate the alterations in hippocampal extracellular fluid proteins in vivo using the 5XFAD mouse model. Samples were obtained from hippocampi of 5XFAD mice (n = 6) and their non-transgenic littermates by intracerebral push-pull perfusion technique at 3 months of age, representing the pre-pathological stage of the AD. Proteins in the hippocampal perfusates were analyzed by Ultra Performance Liquid Chromatography-Electrospray Ionization Quadrupole Time-of-Flight Mass Spectrometry (UPLC-ESI-qTOF-MS/MS). 178 proteins were identified and 19 proteins of them were found to be statistically significantly altered (p≤0.05, fold change ≥40%, unique peptide count ≥3) in the hippocampal CA1 extracellular fluid of the 5XFAD mouse model. Ingenuity pathway analysis of the protein expression results identified IL6 as an upstream regulator. The upregulation of IL6 was validated by immunohistochemical staining of the hippocampus and cortex of the 5XFAD mice prior to Aβ plaque formation. Furthermore, the iron level in the hippocampus was measured by inductively coupled plasma-mass spectrometry as IL6 is mentioned in several studies to take part in iron homeostasis and inflammation and found to be increased in 5XFAD mice hippocampus. Alterations in extracellular matrix proteins in addition to increasing amount of hippocampal IL6 and iron in the early stages of AD may reveal inflammation-mediated iron dyshomeostasis in the early stages of neurodegeneration.
Keywords: Alzheimer Disease; Animals; CA1 Region, Hippocampal; Chromatography, Liquid; Disease Models, Animal; Female; Homeostasis; Interleukin-6; Iron; Mice; Mice, Transgenic; Proteomics; Tandem Mass Spectrometry

Effects of Physical Exercise on Alzheimer's Disease Biomarkers: A Systematic Review of Intervention Studies. - Frederiksen, Kristian Steen; Gjerum, Le; Waldemar, Gunhild; Hasselbalch, Steen Gregers (J Alzheimers Dis, 2018)
Physical exercise may be an important adjunct to pharmacological treatment of Alzheimer's disease (AD). Animal studies indicate that exercise may be disease modifying through several mechanisms including reduction of AD pathology. We carried out a systematic review of intervention studies of physical exercise with hippocampal volume (on MRI), amyloid-β, total tau, phosphorylated tau in cerebrospinal fluid (CSF), 18F-FDG-PET or amyloid PET as outcome measures in healthy subjects, patients with subjective memory complaints, mild cognitive impairment, or AD. We identified a total of 8 studies of which 6 investigated the effects of exercise on hippocampal volume in healthy subjects and 1 on CSF biomarkers and 1 on hippocampal volume in AD, and none investigating the remaining outcome measures or patient groups. Methodological quality of identified studies was generally low. One study found a detrimental effect on hippocampal volume and one found a positive effect, whereas the remaining studies did not find an effect of exercise on outcome measures. The present systematic study identified a relatively small number of studies, which did not support an effect of exercise on hippocampal volume. Methodological issues such small to moderate sample sizes and inadequate ramdomization procedures further limits conclusions. Our findings highlight the difficulties in conducting high quality studies of exercise and further studies are needed before definite conclusions may be reached.
Keywords: Alzheimer Disease; Biomarkers; Exercise; Hippocampus; Humans; Outcome Assessment (Health Care); Physical Therapy Modalities

Endogenous Murine Amyloid-β Peptide Assembles into Aggregates in the Aged C57BL/6J Mouse Suggesting These Animals as a Model to Study Pathogenesis of Amyloid-β Plaque Formation. - Ahlemeyer, Barbara; Halupczok, Sascha; Rodenberg-Frank, Elke; Valerius, Klaus-Peter; Baumgart-Vogt, Eveline (J Alzheimers Dis, 2018)
Amyloid-β peptide (Aβ), paired helical filament-tau (PHF-tau), and α-synuclein are in the focus of neuroscience research because they aggregate in brains of patients with Alzheimer's and Parkinson's diseases. For this purpose, transgenic mouse models were used containing the human genes for AβPP/presenilin/tau or α-synuclein with the most frequent mutations. This is not ideal because most patients develop sporadic forms of the diseases with no causative single gene defect and furthermore the aggregation of human proteins in man is not necessarily the same in rodents. We hypothesized that for such cases the aged mouse could be an alternative model and analyzed the distribution of endogenous Aβ, PHF-tau, and α-synuclein in mouse brains at different ages. Whereas Aβ was below detectable levels at birth, it was present at high levels in the 15-month-old mouse. Aβ was found in the cytosol and lysosomes of neurons of the temporal cortex, cingulate area, pons, and cerebellum as well as extracellularly in the periventricular zone. Contrary to Aβ, mouse brain was devoid of PHF-tau-positive neurofibrillary tangles. α-Synuclein was detectable in the newborn mouse with highest levels in the marginal zone of the lateral cortex and average levels in the hippocampus, pons, and cerebellum. Brain-area specific differences in the α-synuclein level persisted up to 15 months of age, but increased 3-fold in all areas over time. α-Synuclein resided in the neuropil, but not in intracellular aggregates even in the aged mouse. We suggest the aged mouse as a model to study Aβ plaque formation.
Keywords: Age Factors; Aged; Aged, 80 and over; alpha-Synuclein; Alzheimer Disease; Amyloid beta-Peptides; Animals; Brain; Disease Models, Animal; Female; Humans; Male; Mice; Mice, Inbred C57BL; Mice, Transgenic; Neurofibrillary Tangles; Neurons; Plaque, Amyloid; tau Proteins

Epigenetic Drug Repositioning for Alzheimer's Disease Based on Epigenetic Targets in Human Interactome. - Chatterjee, Paulami; Roy, Debjani; Rathi, Nitin (J Alzheimers Dis, 2018)
BACKGROUND: Epigenetics has emerged as an important field in drug discovery. Alzheimer's disease (AD), the leading neurodegenerative disorder throughout the world, is shown to have an epigenetic basis. Currently, there are very few effective epigenetic drugs available for AD. OBJECTIVE: In this work, for the first time we have proposed 14 AD repositioning epigenetic drugs and identified their targets from extensive human interactome. METHODS: Interacting partners of the AD epigenetic proteins were identified from the extensive human interactome to construct Epigenetic Protein-Protein Interaction Network (EP-PPIN). Epigenetic Drug-Target Network (EP-DTN) was constructed with the drugs associated with the proteins of EP-PPIN. Regulation of non-coding RNAs associated with the target proteins of these drugs was also studied. AD related target proteins, epigenetic targets, enriched pathways, and functional categories of the proposed repositioning drugs were also studied. RESULTS: The proposed 14 AD epigenetic repositioning drugs have overlapping targets and miRs with known AD epigenetic targets and miRs. Furthermore, several shared functional categories and enriched pathways were obtained for these drugs with FDA approved epigenetic drugs and known AD drugs. CONCLUSIONS: The findings of our work might provide insight into future AD epigenetic-therapeutics.
Keywords: Alzheimer Disease; Antipsychotic Agents; Computational Biology; Drug Repositioning; Epigenesis, Genetic; Epigenomics; Humans; MicroRNAs; Protein Interaction Maps; PubMed

Erythromyeloid-Derived TREM2: A Major Determinant of Alzheimer's Disease Pathology in Down Syndrome. - Raha-Chowdhury, Ruma; Henderson, James W; Raha, Animesh Alexander; Stott, Simon R W; Vuono, Romina; Foscarin, Simona; Wilson, Liam; Annus, Tiina; Fincham, Robert; Allinson, Kieren; Devalia, Vinod; Friedland, Robert P; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Down syndrome (DS; trisomy 21) individuals have a spectrum of hematopoietic and neuronal dysfunctions and by the time they reach the age of 40 years, almost all develop Alzheimer's disease (AD) neuropathology which includes senile plaques and neurofibrillary tangles. Inflammation and innate immunity are key players in AD and DS. Triggering receptor expressed in myeloid cells-2 (TREM2) variants have been identified as risk factors for AD and other neurodegenerative diseases. OBJECTIVE: To investigate the effects of TREM2 and the AD-associated R47H mutation on brain pathology and hematopoietic state in AD and DS. METHODS: We analyzed peripheral blood, bone marrow, and brain tissue from DS, AD, and age-matched control subjects by immunohistochemistry and western blotting. TREM2-related phagocytosis was investigated using a human myeloid cell line. RESULTS: TREM2 protein levels in brain and sera declined with age and disease progression in DS. We observed soluble TREM2 in brain parenchyma that may be carried by a subset of microglia, macrophages, or exosomes. Two DS cases had the AD-associated TREM2-R47H mutation, which manifested a morphologically extreme phenotype of megakaryocytes and erythrocytes in addition to impaired trafficking of TREM2 to the erythroid membrane. TREM2 was shown to be involved in phagocytosis of red blood cells. TREM2 was seen in early and late endosomes. Silencing TREM2 using siRNA in THP1 cells resulted in significant cell death. CONCLUSION: We provide evidence that peripheral TREM2 originating from erythromyeloid cells significantly determines AD neuropathology in DS subjects. Understanding the molecular signaling pathways mediated by TREM2 may reveal novel therapeutic targets.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Brain; Cell Line; Disease Progression; Down Syndrome; Exosomes; Female; Humans; Immunity, Innate; Macrophages; Male; Membrane Glycoproteins; Microglia; Middle Aged; Phagocytosis; Polymorphism, Single Nucleotide; Receptors, Immunologic

Examining the Relationship between Trace Lithium in Drinking Water and the Rising Rates of Age-Adjusted Alzheimer's Disease Mortality in Texas. - Fajardo, Val Andrew; Fajardo, Val Andrei; LeBlanc, Paul J; MacPherson, Rebecca E K (J Alzheimers Dis, 2018)
BACKGROUND: Alzheimer's disease (AD) mortality rates have steadily increased over time. Lithium, the current gold standard treatment for bipolar disorder, can exert neuroprotective effects against AD. OBJECTIVE: We examined the relationship between trace levels of lithium in drinking water and changes in AD mortality across several Texas counties. METHODS: 6,180 water samples from public wells since 2007 were obtained and averaged for 234 of 254 Texas counties. Changes in AD mortality rates were calculated by subtracting aggregated age-adjusted mortality rates obtained between 2000-2006 from those obtained between 2009-2015. Using aggregated rates maximized the number of counties with reliable mortality data. Correlational analyses between average lithium concentrations and changes in AD mortality were performed while also adjusting for gender, race, education, rural living, air pollution, physical inactivity, obesity, and type 2 diabetes. RESULTS: Age-adjusted AD mortality rate was significantly increased over time (+27%, p < 0.001). Changes in AD mortality were negatively correlated with trace lithium levels (p = 0.01, r = -0.20), and statistical significance was maintained after controlling for most risk factors except for physical inactivity, obesity, and type 2 diabetes. Furthermore, the prevalence of obesity and type 2 diabetes positively correlated with changes in AD mortality (p = 0.01 and 0.03, respectively), but also negatively correlated with trace lithium in drinking water (p = 0.05 and <0.0001, respectively). CONCLUSION: Trace lithium in water is negatively linked with changes in AD mortality, as well as obesity and type 2 diabetes, which are important risk factors for AD.
Keywords: Adult; Age Factors; Alzheimer Disease; Drinking Water; Female; Humans; Lithium; Longitudinal Studies; Male; Obesity; Prevalence; Risk Factors; Statistics as Topic; Texas; Young Adult

Executive Dysfunction Detected with the Frontal Assessment Battery in Alzheimer's Disease Versus Vascular Dementia. - D'Onofrio, Grazia; Panza, Francesco; Sancarlo, Daniele; Addante, Filomena; Solfrizzi, Vincenzo; Cantarini, Chiara; Mangiacotti, Antonio; Lauriola, Michele; Cascavilla, Leandro; Paris, Francesco; Lozupone, Madia; Daniele, Antonio; et al. (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) and vascular dementia (VaD) lead to progressive decline in executive function. We estimated the prevalence of executive dysfunction in AD and VaD patients, investigating cognitive, functional, and clinical correlates and also using a multidimensional approach based on a standardized comprehensive geriatric assessment (CGA). We included 215 patients (115 AD patients and 100 VaD patients) consecutively evaluated with a complete cognitive and affective assessment, a CGA, and the Frontal Assessment Battery (FAB) with six subtests investigating conceptualization, mental flexibility, motor programming, sensitivity to interference, inhibitory control, and environmental autonomy. The prevalence of dysexecutive syndrome screened with a FAB score <12 points was high in both AD (97 patients) and VaD (77 patients) (84.3% versus 77.0%, p = 0.171). AD patients were significantly younger, with higher grade of cognitive impairment and less severe comorbidity and polypharmacy than VaD patients. AD patients showed a significantly higher impairment in FAB total score and five FAB subtests (conceptualization, motor programming, sensitivity to interference, inhibitory control, and environmental autonomy) than VaD patients. These findings were largely confirmed in a sub-analysis conducted subdividing the sample in mild and moderate-to-severe demented patients and suggesting that in moderate-to-severe AD there was higher impairment in FAB total score and four FAB subtests (conceptualization, sensitivity to interference, inhibitory control, and environmental autonomy). Executive dysfunction could be greater in AD patients with moderate-to-severe dementia compared to VaD patients, although our groups were also not matched for age, comorbidity or polypharmacy, which could also exert an effect.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cognitive Dysfunction; Comorbidity; Dementia, Vascular; Executive Function; Female; Frontal Lobe; Geriatric Assessment; Humans; Logistic Models; Male; Polypharmacy; Severity of Illness Index

The First Historically Reported Italian Family with FTD/ALS Teaches a Lesson on C9orf72 RE: Clinical Heterogeneity and Oligogenic Inheritance. - Giannoccaro, Maria Pia; Bartoletti-Stella, Anna; Piras, Silvia; Casalena, Alfonsina; Oppi, Federico; Ambrosetto, Giovanni; Montagna, Pasquale; Liguori, Rocco; Parchi, Piero; Capellari, Sabina (J Alzheimers Dis, 2018)
BACKGROUND: In 1969, Dazzi and Finizio reported the second observation of frontotemporal dementia (FTD) - amyotrophic lateral sclerosis (ALS) association in a large Italian kindred affected by an autosomal dominant form of ALS with high penetrance, frequent bulbar onset, and frequent cognitive decline. OBJECTIVE: To expand the original characterization of this family and report the link with the C9orf72 repeat expansion (RE). METHODS: We followed or reviewed the medical records of thirteen patients belonging to the original family and performed genetic analyses in four individuals. RESULTS: Eight patients presented with ALS, four with FTD, and one with schizophrenia. The C9orf72 RE was found in three patients but not in the healthy survivor. Additionally, we found a novel possible pathogenic variant in the ITM2B gene in one patient with a complex phenotype, associating movement disorders, psychiatric and cognitive features, deafness, and optic atrophy. The neuropathological examination of this patient did not show the classical features of ITM2B mutation related dementias suggesting that the putative pathogenic mechanism does not involve cellular mislocalization of the protein or the formation of amyloid plaques. CONCLUSION: We showed that the original Italian pedigree described with FTD/ALS carries the C9orf72 RE. Moreover, the finding of an additional mutation in another dementia causing gene in a patient with a more complex phenotype suggests a possible role of genetic modifiers in the disease. Together with other reports showing the coexistence of mutations in multiple ALS/FTD causative genes in the same family, our study supports an oligogenic etiology of ALS/FTD.
Keywords: Adult; Amyotrophic Lateral Sclerosis; C9orf72 Protein; Cerebral Cortex; DNA Repeat Expansion; Female; Frontotemporal Dementia; Genetic Testing; Humans; Male; Membrane Glycoproteins; Middle Aged; Multifactorial Inheritance; Mutation; Pedigree

Free Heme and Amyloid-β: A Fatal Liaison in Alzheimer's Disease. - Chiziane, Elisabeth; Telemann, Henriette; Krueger, Martin; Adler, Juliane; Arnhold, Jürgen; Alia, A; Flemmig, Jörg (J Alzheimers Dis, 2018)
While the etiology of Alzheimer's disease (AD) is still unknown, an increased formation of amyloid-β (Aβ) peptide and oxidative processes are major pathological mechanism of the disease. The interaction of Aβ with free heme leads to the formation of peroxidase-active Aβ-heme complexes. However, enzyme-kinetic data and systematic mutational studies are still missing. These aspects were addressed in this study to evaluate the role of Aβ-heme complexes in AD. The enzyme-kinetic measurements showed peroxidase-specific pH- and H2O2-dependencies. In addition, the enzymatic activity of Aβ-heme complexes constantly increased at higher peptide excess. Moreover, the role of the Aβ sequence for the named enzymatic activity was tested, depicting human-specific R5, Y10, and H13 as essential amino acids. Also by studying Y10 as an endogenous peroxidase substrate for Aβ-heme complexes, ratio-specific effects were observed, showing an optimal dityrosine formation at an about 40-fold peptide excess. As dityrosine formation promotes Aβ fibrillation while free heme disturbs protein aggregation, we also investigated the effect of Aβ-heme complex-derived peroxidase activity on the formation of Aβ fibrils. The fluorescence measurements showed a different fibrillation behavior at strong peroxidase activity, leading also to altered fibril morphologies. The latter was detected by electron microscopy. As illustrated by selected in vivo measurements on a mouse model of AD, the disease is also characterized by Aβ-derived microvessel destructions and hemolytic processes. Thus, thrombo-hemorrhagic events are discussed as a source for free heme in brain tissue. In summary, we suggest the formation and enzymatic activity of Aβ-heme complexes as pathological key features of AD.
Keywords: Alzheimer Disease; Amino Acid Sequence; Amyloid; Amyloid beta-Peptides; Animals; Brain; Disease Models, Animal; Heme; Humans; Hydrogen Peroxide; Mice; Mice, Transgenic; Oxidation-Reduction; Peptide Fragments; Peroxidases

Frequency of Cardiovascular Genetic Risk Factors in a Calabrian Population and Their Effects on Dementia. - Maletta, Raffaele; Smirne, Nicoletta; Bernardi, Livia; Anfossi, Maria; Gallo, Maura; Conidi, Maria Elena; Colao, Rosanna; Puccio, Gianfranco; Curcio, Sabrina A M; Laganà, Valentina; Frangipane, Francesca; Cupidi, Chiara; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Several genetic variants playing a key role in cholesterol levels, blood pressure, and vascular dysfunction influence the risk of Alzheimer's disease (AD) and vascular dementia (VaD). The many meta-analysis studies carried out on large numbers of samples in different populations have not provided clear results to date, because a trans-ethnic shift of risk genotypes in different populations is often observed. OBJECTIVES: To determine genotypes allele frequencies of the polymorphisms most frequently identified to be correlated with cardio-cerebrovascular disease and AD in a Southern Italy population and to investigate their possible association with dementia. METHODS: The genotype and allele frequencies of 13 cardio-cerebrovascular risk polymorphisms were assessed and their possible association with dementia was investigated in a case-control study, including 221 consecutive unrelated subjects diagnosed with dementia (120 subjects affected by AD, 55 by frontotemporal dementia, and 33 by vascular dementia) and 218 matched controls of Calabrian origin. RESULTS: Carriers of at least one APOEɛ4 allele resulted to be at higher risk of AD [OR(95% CI) = 2.721(1.477-5.011)] and VaD [OR(95% CI) = 6.205(2.356-16.342)] compared to non-carriers. Individuals with the IV genotype of the CETP polymorphism were more likely to have AD [OR(95% CI) = 2.427(1.364-4.319)] and VaD [OR(95% CI) = 3.649(1.455-9.152)] compared to subjects with the II-VV genotypes. CONCLUSION: CETP I405V polymorphism is likely a risk factor for AD and VaD in our cohort, independent of APOEɛ4 status. Unmodifiable genetic risk factors should be taken into account to promote a healthy lifestyle to prevent dementia.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Apolipoprotein E4; Case-Control Studies; Cholesterol Ester Transfer Proteins; Cohort Studies; Dementia, Vascular; Female; Frontotemporal Dementia; Gene Frequency; Humans; Italy; Male; Middle Aged; Polymorphism, Genetic; Risk Factors

GDF11 Rejuvenates Cerebrovascular Structure and Function in an Animal Model of Alzheimer's Disease. - Zhang, Wei; Guo, Yi; Li, Bo; Zhang, Qi; Liu, Jian-Hui; Gu, Guo-Jun; Wang, Jin-Hong; Bao, Rui-Kang; Chen, Yu-Jie; Xu, Jian-Rong (J Alzheimers Dis, 2018)
Cerebral amyloid angiopathy (CAA) is present in up to 90% of patients with Alzheimer's disease (AD), and may interact with classical neuropathology to exacerbate cognitive decline. Since growth differentiation factor 11 (GDF11) can activate vascular remodeling, we tested its effects on cognitive function and neuroinflammatory changes of AD model mice. We intravenously administered GDF11 or vehicle daily to 12-month-old transgenic mice overexpressing the amyloid-β protein precursor (AβPP)/PS1). Cognitive function was monitored using the Morris water maze, and after conclusion of the treatment, we assessed the morphology and presence of inflammatory markers in the cerebral vasculature. Subchronic treatment of adult AβPP/PS1 mice with GDF11 rescued cognitive function and ameliorated cerebrovascular function. In particular, the de novo genesis of small blood vessels and the expression of vascular-related proteins were significantly higher than in the vehicle-treated AβPP/PS1 mice, whereas the expressions of the inflammatory markers Iba-1 and GFAP significantly decreased in proportion to the lower ratio of two forms of amyloid-β (Aβ40/42). Daily intravenous treatment with GDF11-injection can rejuvenate respects of cognition and cerebrovascular changes in AD mice.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; Behavior, Animal; Cerebral Amyloid Angiopathy; Disease Models, Animal; Growth Differentiation Factors; Maze Learning; Mice; Mice, Transgenic; Prefrontal Cortex; Presenilin-1

Gradual Cerebral Hypoperfusion Impairs Fear Conditioning and Object Recognition Learning and Memory in Mice: Potential Roles of Neurodegeneration and Cholinergic Dysfunction. - Mehla, Jogender; Lacoursiere, Sean; Stuart, Emily; McDonald, Robert J; Mohajerani, Majid H (J Alzheimers Dis, 2018)
In the present study, male C57BL/6J mice were subjected to gradual cerebral hypoperfusion by implanting an ameroid constrictor (AC) on the left common carotid artery (CCA) and a stenosis on the right CCA. In the sham group, all surgical procedures were kept the same except no AC was implanted and stenosis was not performed. One month following the surgical procedures, fear conditioning and object recognition tests were conducted to evaluate learning and memory functions and motor functions were assessed using a balance beam test. At the experimental endpoint, mice were perfused and brains were collected for immunostaining and histology. Learning and memory as well as motor functions were significantly impaired in the hypoperfusion group. The immunoreactivity to choline acetyltransferase was decreased in dorsal striatum and basal forebrain of the hypoperfusion group indicating that cholinergic tone in these brain regions was compromised. In addition, an increased number of Fluoro-Jade positive neurons was also found in cerebral cortex, dorsal striatum and hippocampus indicating neurodegeneration in these brain regions. Based on this pattern of data, we argued that this mouse model would be a useful tool to investigate the therapeutic interventions for the treatment of vascular dementia. Additionally, this model could be employed to exploit the effect of microvascular occlusions on cognitive impairment in the absence and presence of Alzheimer's disease pathology.
Keywords: Animals; Brain; Carotid Stenosis; Cerebrovascular Circulation; Choline O-Acetyltransferase; Conditioning (Psychology); Disease Models, Animal; Fear; Fluoresceins; Learning Disorders; Male; Mice; Mice, Inbred C57BL; Phosphopyruvate Hydratase; Postural Balance; Recognition (Psychology)

The Heritability of Frontotemporal Lobar Degeneration: Validation of Pedigree Classification Criteria in a Northern Italy Cohort. - Fostinelli, Silvia; Ciani, Miriam; Zanardini, Roberta; Zanetti, Orazio; Binetti, Giuliano; Ghidoni, Roberta; Benussi, Luisa (J Alzheimers Dis, 2018)
A large portion of frontotemporal lobar degeneration (FTLD) patients has a family history of disease and the presence of a pathogenic mutation confirms the clinical diagnosis. Recently, standardized criteria to evaluate FTLD pedigree, based on first- and second-degree affected relatives, their age at onset, and clinical phenotype, were proposed and validated in an American cohort. Herein we applied these criteria to 402 Italian FTLD pedigrees and assessed mutation frequencies in GRN, C9orf72, and MAPT genes with the aim of validating these criteria. Moreover, we evaluated whether genetic counseling requests reflect the estimated family risk. 12.4% of pedigrees had high family history, 6.5% medium, 15.4% low; 39% were apparent sporadic cases and 26.6% had family history of unknown significance. Mutations frequencies were in line with the categorization proposed: the highest rate was found in the most at-risk families (74%) and decreased in other categories (medium: 15.4%; low: 9.7%; sporadic: 1.3%). Mutation carriers with unknown family history (5.6%) were mostly early-onset patients. Detected mutation frequency was comparable with the US-cohort (13.7%), but mutations distribution among genes was different, with higher frequency of GRN mutations (9.4%) in our cohort. An elevated proportion of FTLD patients belonging to "high risk" pedigrees asked for genetic counseling (42%); requests decreased according to the estimated family risk (medium: 26.9%; low: 17.7%; sporadic: 5.1%). In conclusion, the proposed pedigree classification criteria, herein further validated, should be incorporated in the FTLD diagnostic work-up. Moreover, our data suggest to extend genetic screening to early-onset patients with unknown family history.
Keywords: Age of Onset; Aged; C9orf72 Protein; Cohort Studies; Female; Frontotemporal Lobar Degeneration; Genetic Counseling; Genetic Testing; Humans; Italy; Male; Middle Aged; Mutation; Pedigree; Progranulins; tau Proteins

The Impact of Music on the Self in Dementia. - Baird, Amee; Thompson, William Forde (J Alzheimers Dis, 2018)
In this review, we consider how the onset and progression of dementia can disrupt one's sense of self, and propose that music is an ideal tool for alleviating this distressing symptom. Various aspects of the self can be impaired in people with dementia, depending on how the self is defined. There are anecdotal reports that music can 'bring people back to themselves' in the face of dementia, but there have been scarce empirical investigations of this topic. Motivated by a consideration of the existing literature, we outline a novel theoretical framework that accounts for the relationship between music and the self in people with dementia. We propose that music has a number of 'design features' that make it uniquely equipped to engage multiple aspects of the self. We suggest that each design feature interacts with different aspects of the self to varying degrees, promoting overall wellbeing. We discuss how existing research on music and dementia fits within this framework, and describe two case studies in which music was an ideal stimulus for reaffirming their sense of self. Our framework may be useful for the diagnosis and treatment of impairments of self in people with dementia, and highlights how music, given its ability to engage all aspects of the self simultaneously, can result in an overall enhanced sense of self.
Keywords: Consciousness; Dementia; Humans; Music; Music Therapy; Personality

Impaired IL-17 Production in Gut-Residing Immune Cells of 5xFAD Mice with Alzheimer's Disease Pathology. - Saksida, Tamara; Koprivica, Ivan; Vujičić, Milica; Stošić-Grujičić, Stanislava; Perović, Milka; Kanazir, Selma; Stojanović, Ivana (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) is characterized by accumulation of amyloid-β plaques that further promotes microglia-mediated neuroinflammatory responses and inflammation in the brain. Emerging data are revealing the relation between gut-associated lymphoid tissue (GALT) cells and CNS, as effector cells primed in the gut might home to the brain. This study aimed to determine cell composition of GALT in 5xFAD mice, an established model for AD. Immune cells isolated from Peyer's patches (PP) and mesenteric lymph nodes (MLN) were stained with surface and intracellular markers for T helper (Th) subpopulations, B lymphocytes and macrophages and analyzed cytofluorimetrically, while cytokine expression and production were determined by qPCR and ELISA, respectively. Inflammation was detected in GALT of 5xFAD mice with established AD pathology. Although the production of IFN-γ, IL-4, and IL-10 was comparable between the strains, lower IL-17 production was observed in PP and MLN cells. This phenomenon could not be attributed to a lower abundance of Th17 cells, or cytokines that initiate their formation or propagation (TGF-β, IL-6, and IL-23). Also, reduced IL-17 production was not a consequence of altered Il-17 mRNA transcription or deficiency of Rorγt, a key transcription factor for IL-17. However, the expression of miR-155 (a non-coding micro RNA that promotes the development of Th17 cells), was significantly lower in MLN cells of 5xFAD mice. In contrast, mice without AD neuropathology did not have inflammation in GALT or altered Th17 numbers, nor decreased IL-17 production. In conclusion, the observed changes in GALT of 5xFAD mice mirror the disease progression and might reflect inadequate immune surveillance in the gut and lead to enhanced AD pathology.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; B-Lymphocytes; Disease Models, Animal; Female; Interleukin-17; Lymph Nodes; Male; Mice; Mice, Transgenic; MicroRNAs; Peyer's Patches; Th17 Cells

In vivo Depiction of α7 Nicotinic Receptor Loss for Cognitive Decline in Alzheimer's Disease. - Nakaizumi, Kyoko; Ouchi, Yasuomi; Terada, Tatsuhiro; Yoshikawa, Etsuji; Kakimoto, Akihiro; Isobe, Takashi; Bunai, Tomoyasu; Yokokura, Masamichi; Suzuki, Katsuaki; Magata, Yasuhiro (J Alzheimers Dis, 2018)
BACKGROUND: The α7 subtype of the nicotinic acetylcholine receptor (nAChR) is considered important in higher cognitive functions, and cholinergic loss underpins the pathophysiology of Alzheimer's disease (AD). However, the relationships between α7 nAChR function and clinical functions or amyloid-β (Aβ) deposition remain to be explored in the living AD brain. OBJECTIVE: We aimed to elucidate the relationship between α7 nAChR availability in the specific cholinergic region and cognitive decline in the Aβ-confirmed AD brain. METHODS: Twenty AD patients and ten age-matched healthy subjects were examined. The α7-nAChR availability and Aβ deposition were evaluated using positron emission tomography with an α7 nAChR radiotracer 11C-(R)-MeQAA and 11C-Pittsburg compound B (11C-PiB), respectively. Semi-quantified values of tracer binding were estimated with a simplified reference tissue method for BPND of 11C-(R)-MeQAA and a tissue ratio method for SUVR of 11C-PiB. These parameters and clinical scores were compared voxel-wise using a statistical parametric mapping method. RESULTS: The levels of 11C-(R)-MeQAA BPND in the temporal and prefrontal cholinergic projection regions were significantly lower in AD, and negative correlations were found between 11C-PiB SUVR and 11C-(R)-MeQAA BPND in the region of the nucleus basalis magnocellularis and medial prefrontal cortex. Levels of 11C-(R)-MeQAA BPND were significantly correlated with memory and frontal function scores in AD. CONCLUSION: The association between Aβ burden and α7-nAChR reduction in the basal forebrain cholinergic system was highlighted in relation to cognitive decline in AD. This suggests that Aβ-linked α7-nAChR reduction is clinico-pathophyisologically important for considering a good therapeutic target in AD.
Keywords: Adult; Aged; alpha7 Nicotinic Acetylcholine Receptor; Alzheimer Disease; Brain; Case-Control Studies; Cognitive Dysfunction; Female; Humans; Male; Middle Aged; Positron-Emission Tomography; Young Adult

In Vivo Visualization of Tau Accumulation, Microglial Activation, and Brain Atrophy in a Mouse Model of Tauopathy rTg4510. - Ishikawa, Ai; Tokunaga, Masaki; Maeda, Jun; Minamihisamatsu, Takeharu; Shimojo, Masafumi; Takuwa, Hiroyuki; Ono, Maiko; Ni, Ruiqing; Hirano, Shigeki; Kuwabara, Satoshi; Ji, Bin; Zhang, Ming-Rong; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Tau imaging using PET is a promising tool for the diagnosis and evaluation of tau-related neurodegenerative disorders, but the relationship among PET-detectable tau, neuroinflammation, and neurodegeneration is not yet fully understood. OBJECTIVE: We aimed to elucidate sequential changes in tau accumulation, neuroinflammation, and brain atrophy by PET and MRI in a tauopathy mouse model. METHODS: rTg4510 transgenic (tg) mice expressing P301L mutated tau and non-tg mice were examined with brain MRI and PET imaging (analyzed numbers: tg = 17, non-tg = 13; age 2.5∼14 months). As PET probes, [11C]PBB3 (Pyridinyl-Butadienyl-Benzothiazole 3) and [11C]AC-5216 were used to visualize tau pathology and 18-kDa translocator protein (TSPO) neuroinflammation. Tau pathology and microglia activation were subsequently analyzed by histochemistry. RESULTS: PET studies revealed age-dependent increases in [11C]PBB3 and [11C]AC-5216 signals, which were correlated with age-dependent volume reduction in the forebrain on MRI. However, the increase in [11C]PBB3 signals reached a plateau at age 7 months, and therefore its significant correlation with [11C]AC-5216 disappeared after age 7 months. In contrast, [11C]AC-5216 showed a strong correlation with both age and volume reduction until age 14 months. Histochemical analyses confirmed the relevance of pathological tau accumulation and elevated TSPO immunoreactivity in putative microglia. CONCLUSION: Our results showed that tau accumulation is associated with neuroinflammation and brain atrophy in a tauopathy mouse model. The time-course of the [11C]PBB3- and TSPO-PET finding suggests that tau deposition triggers progressive neuroinflammation, and the sequential changes can be evaluated in vivo in mouse brains.
Keywords: Animals; Atrophy; Benzothiazoles; Brain; Disease Models, Animal; Female; Magnetic Resonance Imaging; Male; Mice; Mice, Transgenic; Microglia; Positron-Emission Tomography; Receptors, GABA; tau Proteins; Tauopathies

Increased Foxo3a Nuclear Translocation and Activity is an Early Neuronal Response to βγ-Secretase-Mediated Processing of the Amyloid-β Protein Precursor: Utility of an AβPP-GAL4 Reporter Assay. - Law, Bernard M; Guest, Amy L; Pullen, Matthew W J; Perkinton, Michael S; Williams, Robert J (J Alzheimers Dis, 2018)
Sequential cleavage of the amyloid-β protein precursor (AβPP) by BACE1 (β-secretase) followed by theγ-secretase complex, is strongly implicated in Alzheimer's disease (AD) but the initial cellular responses to these cleavage events are not fully defined. β-secretase-mediated AβPP processing yields an extracellular domain (sAβPPβ) and a C-terminal fragment of AβPP of 99 amino acids (C99). Subsequent cleavage by γ-secretase produces amyloid-β (Aβ) and an AβPP intracellular domain (AICD). A cellular screen based on the generation of AICD from an AβPP-Gal4 fusion protein was adapted by introducing familial AD (FAD) mutations into the AβPP sequence and linking the assay to Gal4-UAS driven luciferase and GFP expression, to identify responses immediately downstream of AβPP processing in neurons with a focus on the transcription factor Foxo3a which has been implicated in neurodegeneration. The K670N/M671L, E682K, E693G, and V717I FAD mutations and the A673T protective mutation, were introduced into the AβPP sequence by site directed mutagenesis. When expressed in mouse cortical neurons, AβPP-Gal4-UAS driven luciferase and GFP expression was substantially reduced by γ-secretase inhibitors, lowered by β-secretase inhibitors, and enhanced by α-secretase inhibitors suggesting that AICD is a product of the βγ-secretase pathway. AβPP-Gal4-UAS driven GFP expression was exploited to identify individual neurons undergoing amyloidogenic AβPP processing, revealing increased nuclear localization of Foxo3a and enhanced Foxo3a-mediated transcription downstream of AICD production. Foxo3a translocation was not driven by AICD directly but correlated with reduced Akt phosphorylation. Collectively this suggests that βγ-secretase-mediated AβPP processing couples to Foxo3a which could be an early neuronal signaling response in AD.
Keywords: Alzheimer Disease; Amyloid beta-Protein Precursor; Amyloid Precursor Protein Secretases; Animals; Disease Models, Animal; Forkhead Box Protein O3; Mice; Mutagenesis, Site-Directed; Mutation; Neurons; Phosphorylation; Protein Transport; Signal Transduction

Interactions between Atrial Fibrillation, Cardiovascular Risk Factors, and ApoE Genotype in Promoting Cognitive Decline in Patients with Alzheimer's Disease: A Prospective Cohort Study. - Falsetti, Lorenzo; Viticchi, Giovanna; Buratti, Laura; Grigioni, Francesco; Capucci, Alessandro; Silvestrini, Mauro (J Alzheimers Dis, 2018)
BACKGROUND: An association between non-valvular atrial fibrillation (NVAF) and cognitive impairment has been hypothesized. OBJECTIVE: We sought to evaluate whether and how permanent NVAF (pNVAF) is associated with progression of cognitive impairment in patients with Alzheimer's disease (AD) in the presence of vascular or genetic risk factors. METHODS: 310 consecutive patients affected by mild-moderate AD were included and followed for a 24-month period. At the end of the follow-up, based on the results of the neuropsychological evaluation patients were classified as stable or deteriorated to severe AD. Clinical history, therapy, time in therapeutic range for anticoagulation, Framingham cardiovascular risk profile (FCRP), CHA2DS2-VASc score, Mini-Mental State Examination (MMSE), ApoE genotype, brain CT-scan, carotid ultrasound, and ECG were collected. Binary logistic and path analysis were adopted to assess relationships between pNVAF, ApoE, and cognitive outcome. RESULTS: Despite anticoagulant therapy, pNVAF was associated with lower entry MMSE, higher mean intima-media thickness (mIMT) and higher FCRP. Among patients carrying ApoE ɛ4 allele and affected by pNVAF, the lowest MMSE (14.90±7.62) and the highest mIMT (1.16±0.17 mm) and FCRP (26.24±3.96) values were detected. In this group, the risk of cognitive deterioration reached the highest probability. pNVAF was associated with an increased cognitive deterioration in subjects with high FCRP, CHA2DS2-VASc, or mIMT. CONCLUSIONS: pNVAF seems to identify AD patients with a significant atherosclerotic burden and reduced cognitive performances. The interaction between pNVAF and ApoE ɛ4 genotype, especially with aggregated risk factors and an advanced stage of vascular damage is associated with higher risk of fast cognitive deterioration.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Apolipoprotein E4; Atherosclerosis; Atrial Fibrillation; Carotid Intima-Media Thickness; Cognitive Dysfunction; Disease Progression; Female; Humans; Logistic Models; Magnetic Resonance Imaging; Male; Neuropsychological Tests; Prospective Studies; Risk Factors; Tomography, X-Ray Computed

Lentivirus-Mediated HDAC3 Inhibition Attenuates Oxidative Stress in APPswe/PS1dE9 Mice. - Yu, Linjie; Liu, Yi; Jin, Yuexinzi; Cao, Xiang; Chen, Jian; Jin, Jiali; Gu, Yue; Bao, Xinyu; Ren, Zhuoying; Xu, Yun; Zhu, Xiaolei (J Alzheimers Dis, 2018)
Amyloid-β (Aβ) induces a burst of oxidative stress and plays a critical role in the pathogenesis of Alzheimer's disease (AD). Our previous results have shown that histone deacetylase 3 (HDAC3) inhibition ameliorates spatial memory deficits and decreases the Aβ burden in the brains of 9-month-old APPswe/PS1dE9 (APP/PS1) mice. In this study, we investigated the role of HDAC3 inhibition in oxidative stress in vivo and in vitro models of AD. HDAC3 was detected mainly in the neurons, and HDAC3 inhibition significantly decreased reactive oxygen species generation and improved primary cortical neuron viability. In addition, HDAC3 inhibition attenuated spatial memory dysfunction in 6-month-old APP/PS1 mice, and decreased the apoptotic rate in the hippocampi as demonstrated by TUNEL staining. HDAC3 inhibition also reduced markers of lipid peroxidation, protein oxidation, and DNA/RNA oxidation in the hippocampi of APP/PS1 mice. Moreover, HDAC3 inhibition inactivated the c-Abl/MST1/YAP signaling pathway in the hippocampi of APP/PS1 mice. In conclusion, our data show that HDAC3 inhibition can attenuate spatial memory deficits and inhibit oxidative stress in APP/PS1 mice; these results indicate a potential strategy for AD treatment.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; Disease Models, Animal; Hippocampus; Histone Deacetylases; Lentivirus; Male; Maze Learning; Mice; Mice, Inbred C57BL; Mice, Transgenic; Neurons; Oxidative Stress; Plaque, Amyloid; Primary Cell Culture; Reactive Oxygen Species; Spatial Memory; tau Proteins

A Link between Subjective Perceptions of Memory and Physical Function: Implications for Subjective Cognitive Decline. - Cosentino, Stephanie; Devanand, Davangere; Gurland, Barry (J Alzheimers Dis, 2018)
Subjective impairment in memory is a frequently defining feature of subjective cognitive decline (SCD), a state hypothesized to precede objectively apparent cognitive symptoms of Alzheimer's disease (AD) and to hold promise as a non-invasive, inexpensive, preclinical indicator of AD. However, a full model of the factors that contribute to subjective memory (SM), and therefore to SCD, has yet to be articulated. While SM impairment is widely known to be associated with negative affect, the extent to which SM functioning may also reflect other factors, particularly subjective beliefs or perceptions about one's health, is not known. To examine the extent to which SM is associated with subjective perceptions of health more broadly, the current study investigated the link between SM and subjective physical functioning (independent of depressive affect, and objective cognitive and physical function) in an ethnically diverse sample of 471 older adults enrolled in the population-based Northern Manhattan Aging Project. 199 (42%) participants endorsed no difficulty on a 5-point SM index while 272 (58%) endorsed some degree of difficulty. As hypothesized, SM correlated with both depression and subjective physical function, but not with age, education, global cognition, or objective physical function. When objective and subjective physical function were entered in two separate, adjusted linear regressions predicting SM, only subjective physical function and depressive affect independently predicted SM. Subjective perceptions of memory appear to reflect individuals' broader health perceptions in part. Articulating the various correlates of SM will improve identification of SCD specific to preclinical AD.
Keywords: Aged; Aged, 80 and over; Cognitive Dysfunction; Executive Function; Female; Humans; Linear Models; Male; Memory; Neuropsychological Tests; New York City; Perception

Longitudinal Changes in Serum Glucose Levels are Associated with Metabolic Changes in Alzheimer's Disease Related Brain Regions. - Burns, Christine M; Kaszniak, Alfred W; Chen, Kewei; Lee, Wendy; Bandy, Daniel J; Caselli, Richard J; Reiman, Eric M (J Alzheimers Dis, 2018)
BACKGROUND: The association between longitudinal changes in serum glucose level and longitudinal changes in [18F] Fluorodeoxyglucose-PET (FDG PET) measurements of Alzheimer's disease (AD) risk are unknown. OBJECTIVE: To investigate whether variation in serum glucose levels across time are associated with changes in FDG PET measurements of cerebral metabolic rate for glucose (rCMRgl) in brain regions preferentially affected by Alzheimer's disease (AD). METHODS: Participants are a subset of a prospective cohort study investigating FDG PET, apolipoprotein E (APOE) ɛ4, and risk for AD which includes data from baseline, interim, and follow up visits over 4.4±1.0-years. An automated brain-mapping algorithm was utilized to characterize and compare associations between longitudinal changes in serum glucose levels and longitudinal changes in rCMRgl. RESULTS: This study included 80 adults aged 61.5±5 years, including 38 carriers and 42 non-carriers of the APOE ɛ4 allele. Longitudinal increases in serum glucose levels were associated with longitudinal CMRgl decline in the vicinity of parietotemporal, precuneus/posterior cingulate, and prefrontal brain regions preferentially affected by AD (p < 0.05, corrected for multiple comparisons). Findings remained significant when controlled for APOE ɛ4 status and baseline and advancing age. CONCLUSIONS: Additional studies are needed to clarify and confirm the relationship between longitudinal changes in peripheral glucose and FDG PET measurements of AD risk. Future findings will set the stage on the use of FDG PET in the evaluation of possible interventions that target risk factors for the development of AD.
Keywords: Aged; Alzheimer Disease; Apolipoprotein E4; Blood Glucose; Brain; Brain Mapping; Female; Fluorodeoxyglucose F18; Heterozygote; Humans; Longitudinal Studies; Male; Middle Aged; Positron-Emission Tomography; Prospective Studies; Radiopharmaceuticals

Longitudinal Neuroimaging Analysis in Mild-Moderate Alzheimer's Disease Patients Treated with Plasma Exchange with 5% Human Albumin. - Cuberas-Borrós, Gemma; Roca, Isabel; Boada, Merce; Tárraga, Lluís; Hernandez, Isabel; Buendia, Mar; Rubio, Lourdes; Torres, Gustavo; Bittini, Ángel; Guzmán-de-Villoria, Juan A; Pujadas, Francesc; Torres, Mireia; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Recently, modifications of Aβ1-42 levels in CSF and plasma associated with improvement in memory and language functions have been observed in patients with mild-moderate Alzheimer's disease (AD) treated with plasma exchange (PE) with albumin replacement. OBJECTIVE: To detect structural and functional brain changes in PE-treated AD patients as part of a Phase II clinical trial. METHODS: Patients received between 3 and 18 PE with albumin (Albutein® 5%, Grifols) or sham-PE (controls) for 21 weeks (divided in one intensive and two maintenance periods) followed by 6-month follow-up. Brain perfusion assessed by SPECT scans using an automated software (NeuroGam®) and brain structural changes assessed by MRI were performed at weeks 0 (baseline), 21, and 44 (with additional SPECT at weeks 9 and 33). Statistical parametric mapping (voxel-based analysis, SPM) and Z-scores calculations were applied to investigate changes to baseline. RESULTS: 42 patients were recruited (39 evaluable; 37 analyzed: 18 PE-treated; 19 controls). There was a trend toward decreasing hippocampi and total intracranial volume for both patient groups during the study (p < 0.05). After six months, PE-treated patients had less cerebral perfusion loss than controls in frontal, temporal, and parietal areas, and perfusion stabilization in Brodmann area BA38-R during the PE-treatment period (p < 0.05). SPM analysis showed stabilization or absence of progression of perfusion loss in PE-treated patients until week 21, not observed in controls. CONCLUSIONS: Mild-moderate AD patients showed decreased brain volume and impairment of brain perfusion as expected for the progression of the disease. PE-treatment with albumin replacement favored the stabilization of perfusion.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Female; Humans; Longitudinal Studies; Magnetic Resonance Imaging; Male; Middle Aged; Neuroimaging; Plasma Exchange; Serum Albumin, Human; Time Factors; Tomography, Emission-Computed, Single-Photon; Treatment Outcome

A Longitudinal Study of Total and Phosphorylated α-Synuclein with Other Biomarkers in Cerebrospinal Fluid of Alzheimer's Disease and Mild Cognitive Impairment. - Wang, Hua; Stewart, Tessandra; Toledo, Jon B; Ginghina, Carmen; Tang, Lu; Atik, Anzari; Aro, Patrick; Shaw, Leslie M; Trojanowski, John Q; Galasko, Douglas R; Edland, Steven; Jensen, Poul H; et al. (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) features a dynamic sequence of amyloid deposition, neurodegeneration, and cognitive impairment. A significant fraction of AD brains also displays Lewy body pathology, suggesting that addition of classically Parkinson's disease-related proteins to the AD biomarker panel may be of value. To determine whether addition of cerebrospinal fluid (CSF) total α-synuclein and its form phosphorylated at S129 (pS129) to the AD biomarker panel [Amyloid-β1-42 (Aβ42), tau, and phosphorylated tau (p-tau181)] improves its performance, we examined CSF samples collected longitudinally up to 7 years as part of the Alzheimer's Disease Neuroimaging Initiative. From 87 AD, 177 mild cognitive impairment (MCI), and 104 age-matched healthy controls, 792 baseline and longitudinal CSF samples were tested for total α-synuclein, pS129, Aβ42, tau, and p-tau181. pS129, but not total α-synuclein, was weakly associated with diagnosis at baseline when t-tau/Aβ42 was included in the statistical model (β= 0.0026, p = 0.041, 95% CI [(0.0001)-(0.005)]). CSF α-synuclein predicted Alzheimer's Disease Assessment Scale-Cognitive (β= -0.59, p = 0.0015, 95% CI [(-0.96)-(-0.23)]), memory (β= 0.4, p = 0.00025, 95% CI [(0.16)-(0.59)]), and executive (0.62,<0.0001, 95% CI [(0.31)-(0.93)]) function composite scores, and progression from MCI to AD (β= 0.019, p = 0.0011, 95% CI [(0.002)-(0.20)]). pS129 was associated with executive function (β= -2.55, p = 0.0085, 95% CI [(-4.45)-(-0.66)]). Lower values in the mismatch between α-synuclein and p-tau181 predicted faster cognitive decline (β= 0.64, p = 0.0012, 95% CI [(0.48)-(0.84)]). Longitudinal biomarker changes did not differ between groups, and may not reflect AD progression. The α-synuclein-p-tau181-Mismatch could better predict longitudinal cognitive changes than classical AD markers alone, and its pathological correlates should be investigated further.
Keywords: Aged; Aged, 80 and over; alpha-Synuclein; Alzheimer Disease; Biomarkers; Cognitive Dysfunction; Cross-Sectional Studies; Disease Progression; Executive Function; Female; Humans; Linear Models; Longitudinal Studies; Male; Memory Disorders; Multivariate Analysis; Neuropsychological Tests; Phosphorylation; tau Proteins

Low Prevalence of Cancer in Patients with Frontotemporal Lobar Degeneration. - Katisko, Kasper; Haapasalo, Annakaisa; Koivisto, Anne; Krüger, Johanna; Hartikainen, Päivi; Korhonen, Ville; Helisalmi, Seppo; Herukka, Sanna-Kaisa; Remes, Anne M; Solje, Eino (J Alzheimers Dis, 2018)
Several studies have reported reduced risk of cancer in patients with Alzheimer's disease (AD) or Parkinson's disease. The relationship between cancer and frontotemporal lobar degeneration (FTLD) has not been previously reported. Here, our aim was to evaluate the occurrence of cancer in Finnish FTLD patients with a high proportion of C9ORF72 repeat expansion carriers in comparison to age- and sex-matched group of AD patients and control subjects classified as not cognitively impaired (NCI). The prevalence of cancer was 9.7% in FTLD, 18.7% in AD, and 17.4% in NCI (FTLD versus AD p = 0.012, FTLD versus NCI p = 0.029) groups. No differences were observed between C9ORF72 repeat expansion carriers and non-carriers inside the FTLD group. To our knowledge, this is the first study showing significantly lower prevalence of cancer in FTLD patients compared to patients with AD or NCI subjects. Our data suggest an inverse association between neurodegeneration and cancer and that FTLD-specific mechanisms may underlie the especially strong inverse association observed in this study.
Keywords: Aged; Alzheimer Disease; C9orf72 Protein; DNA Repeat Expansion; Female; Finland; Frontotemporal Lobar Degeneration; Heterozygote; Humans; Male; Middle Aged; Neoplasms; Prevalence

Meta-Analysis of Personality Traits in Alzheimer's Disease: A Comparison with Healthy Subjects. - D'Iorio, Alfonsina; Garramone, Federica; Piscopo, Fausta; Baiano, Chiara; Raimo, Simona; Santangelo, Gabriella (J Alzheimers Dis, 2018)
BACKGROUND: The role of specific personality traits as factor risks of Alzheimer's disease (AD) has been consistently found, whereas personality traits specifically related to AD (after the diagnosis) have not been outlined yet. OBJECTIVE: A meta-analysis of published studies was performed to determine whether AD patients have a distinctive personality trait profile compared to healthy subjects (HC), similar to or different from a premorbid personality profile consistently reported in previous studies. METHODS: A systematic literature search was performed using PsycInfo (PROQUEST), PubMed, and Scopus. The meta-analysis pooled results from primary studies using Hedges' g unbiased approach. RESULTS: The meta-analysis included 10 primary studies and revealed that, when the personality was evaluated by informant-rated measures, AD patients had significantly higher levels of Neuroticism, lower levels of Openness, Agreeableness, Conscientiousness, and Extraversion than HCs. When the personality was evaluated by self-rated measures, the results obtained from informants were confirmed for Neuroticism, Openness, and Extraversion but not for Agreeableness and Conscientiousness where AD patients and HCs achieved similar scores. CONCLUSIONS: The meta-analysis revealed that high Neuroticism and low Openness and Extraversion are distinctive personality traits significantly associated with a diagnosis of AD when evaluated both self-rated and informant-rated measures. This personality trait profile is similar to premorbid one, which contributes to development of AD over time. Therefore, our findings indirectly support the idea of specific premorbid personality traits as harbingers of AD.
Keywords: Alzheimer Disease; Case-Control Studies; Humans; Personality; Personality Inventory

microRNA 221 Targets ADAM10 mRNA and is Downregulated in Alzheimer's Disease. - Manzine, Patricia R; Pelucchi, Silvia; Horst, Maria A; Vale, Francisco A C; Pavarini, Sofia C I; Audano, Matteo; Mitro, Nico; Di Luca, Monica; Marcello, Elena; Cominetti, Márcia R (J Alzheimers Dis, 2018)
ADAM10 is the α-secretase that cleaves amyloid-β protein precursor in the non-amyloidogenic pathway in Alzheimer's disease (AD) and is known to be regulated by different microRNAs (miRNAs), which are post-transcriptional regulators related to several biological and pathological processes, including AD. Here we proposed to explore and validate miRNAs that have direct or indirect relations to the AD pathophysiology and ADAM10 gene. Approximately 700 miRNAs were analyzed and 21 differentially expressed miRNAs were validated in a sample of 21 AD subjects and 17 cognitively healthy matched controls. SH-SY5Y cells were transfected with miR-144-5p, miR-221, and miR-374 mimics and inhibitors, and ADAM10 protein levels were evaluated. miR-144-5p, miR-221, and miR-374 were downregulated in AD. The overexpression of miR-221 in SH-SY5Y cells resulted in ADAM10 reduction and its inhibition in ADAM10 increased. These findings show that miR-221 can be a new potential therapeutic target for increasing ADAM10 levels in AD. In addition, these results can contribute to the better understanding of ADAM10 post-transcriptional regulation.
Keywords: ADAM10 Protein; Aged; Aged, 80 and over; Alzheimer Disease; Cell Line, Tumor; Cohort Studies; Down-Regulation; Female; Humans; Male; MicroRNAs; Middle Aged; Neuroblastoma; Psychiatric Status Rating Scales; RNA, Messenger; ROC Curve; Transfection

A Natural Benzofuran from the Patagonic Aleurodiscus vitellinus Fungus has Potent Neuroprotective Properties on a Cellular Model of Amyloid-β Peptide Toxicity. - González-Ramírez, Mariela; Gavilán, Javiera; Silva-Grecchi, Tiare; Cajas-Madriaga, Daniel; Triviño, Sergio; Becerra, José; Saez-Orellana, Francisco; Pérez, Claudia; Fuentealba, Jorge (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) is characterized by amyloid plaques that form due to an increase in amyloid-β peptide (Aβ) aggregation. One strategy in the search of new treatments for AD focuses on compounds that decrease Aβ accumulation. Compounds containing a benzofuran ring have been described to play an important role in decreasing Aβ-induced toxicity; however, only synthetic benzofurans have been tested thus far. The aim of the present study was to examine the in vitro neuroprotective properties of fomannoxin (Fx), a natural benzofuran isolated from cultures of the Andean-Patagonian fungi Aleurodiscus vitellinus, and evaluate its effect on Aβ peptide. We tested the effect of Fx at a wide concentration range (10-11-10-4 M) in PC-12 cells, and found the compound did not alter cellular viability. Fx also showed a concentration-dependent effect on the Aβ-induced toxicity in PC12 cells, showing viability above 100% at 10-6 M. We then measured the effect of Fx (10-7-10-5 M) on the frequency of cytosolic Ca2+ transients in rat hippocampal neurons at both acute and chronic (24 h) times. Acute incubation with Fx increased the frequency of cytosolic Ca2+ transients to values around 200%, whereas chronic incubation with Fx increased the frequency of Ca2+ transients. Finally, the Aβ-induced decrease in intracellular Ca2+ transients was prevented when Fx (10-6 M) was co-incubated with Aβ (5×10-6 M). The results suggest a potent neuroprotective effect of this naturally occurring benzofuran against Aβ peptide toxicity that could be mediated by an interference with it binding to plasma membrane, and lead Fx as new chemical entity to develop pharmacological tools against Aβ peptide neurotoxicity.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; Basidiomycota; Benzofurans; Cell Survival; Hippocampus; Neurons; Neuroprotective Agents; PC12 Cells; Plaque, Amyloid; Rats

Neuroanatomical Comparison of the "Word" and "Picture" Versions of the Free and Cued Selective Reminding Test in Alzheimer's Disease. - Slachevsky, Andrea; Barraza, Paulo; Hornberger, Michael; Muñoz-Neira, Carlos; Flanagan, Emma; Henriquez, Fernando; Bravo, Eduardo; Farías, Mauricio; Delgado, Carolina (J Alzheimers Dis, 2018)
Episodic memory tests with cued recall, such as the Free and Cued Selective Reminding Test (FCSRT), allow for the delineation of hippocampal and prefrontal atrophy contributions to memory performance in Alzheimer's disease (AD). Both Word and Picture versions of the test exist but show different profiles, with the Picture version usually scoring higher across different cohorts. One possible explanation for this divergent performance between the different modality versions of the test might be that they rely on different sets of neural correlates. The current study explores this by contrasting the neural correlates of the Word and Picture versions of the FCSRT with voxel-based morphometry (VBM) in AD and healthy subjects. We predicted that the Picture version would be associated with different cortical regions than the Word version, which might be more hippocampal-centric. When comparing 35 AD patients and 34 controls, AD patients exhibited impairments on both versions of the FCSRT and both groups performed higher in the Picture version. A region of interest analysis based on prior work revealed significant correlations between free recall of either version with atrophy of the temporal pole and hippocampal regions. Thus, contrary to expectations, performance on both the Word and the Picture version of the FCSRT is associated with largely overlapping networks. Free recall is associated with hippocampal volume and might be properly considered as an indicator of hippocampal structural integrity.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Biomarkers; Case-Control Studies; Cues; Female; Hippocampus; Humans; Magnetic Resonance Imaging; Male; Memory, Episodic; Mental Recall; Middle Aged; Neuropsychological Tests; Photic Stimulation

A Novel Antibody Targeting Tau Phosphorylated at Serine 235 Detects Neurofibrillary Tangles. - Brici, David; Götz, Jürgen; Nisbet, Rebecca M (J Alzheimers Dis, 2018)
Alzheimer's disease is characterized by two main pathological hallmarks in the human brain: the extracellular deposition of amyloid-β as plaques and the intracellular accumulation of the hyperphosphorylated protein tau as neurofibrillary tangles (NFTs). Phosphorylated tau (p-tau) specific-antibodies and silver staining have been used to reveal three morphological stages of NFT formation: pre-NFTs, intraneuronal NFTs (iNFTs), and extraneuronal NFTs (eNFTs). Here we characterize a novel monoclonal antibody, RN235, which is specific for tau phosphorylated at serine 235, and detects iNFTs and eNFTs in brain tissue, suggesting that phosphorylation at this site is indicative of late stage changes in tau.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Animals; Antibodies, Monoclonal; Antibody Specificity; Brain; Disease Models, Animal; Humans; Mice; Neurofibrillary Tangles; Phosphorylation; Plaque, Amyloid; tau Proteins

Ozone Atmospheric Pollution and Alzheimer's Disease: From Epidemiological Facts to Molecular Mechanisms. - Croze, Marine L; Zimmer, Luc (J Alzheimers Dis, 2018)
Atmospheric pollution is a well-known environmental hazard, especially in developing countries where millions of people are exposed to airborne pollutant levels above safety standards. Accordingly, several epidemiological and animal studies confirmed its role in respiratory and cardiovascular pathologies and identified a strong link between ambient air pollution exposure and adverse health outcomes such as hospitalization and mortality. More recently, the potential deleterious effect of air pollution inhalation on the central nervous system was also investigated and mounting evidence supports a link between air pollution exposure and neurodegenerative pathologies, especially Alzheimer's disease (AD). The focus of this review is to highlight the possible link between ozone air pollution exposure and AD incidence. This review's approach will go from observational and epidemiological facts to the proposal of molecular mechanisms. First, epidemiological and postmortem human study data concerning residents of ozone-severely polluted megacities will be presented and discussed. Then, the more particular role of ozone air pollution in AD pathology will be described and evidenced by toxicological studies in rat or mouse with ozone pollution exposure only. The experimental paradigms used to reproduce in rodent the human exposure to ozone air pollution will be described. Finally, current insights into the molecular mechanisms through which ozone inhalation can affect the brain and play a role in AD development or progression will be recapitulated.
Keywords: Air Pollution; Alzheimer Disease; Animals; Central Nervous System; Humans; Incidence; Inhalation Exposure; Ozone; Particulate Matter

Palmitoylethanolamide Blunts Amyloid-β42-Induced Astrocyte Activation and Improves Neuronal Survival in Primary Mouse Cortical Astrocyte-Neuron Co-Cultures. - Beggiato, Sarah; Borelli, Andrea Celeste; Ferraro, Luca; Tanganelli, Sergio; Antonelli, Tiziana; Tomasini, Maria Cristina (J Alzheimers Dis, 2018)
BACKGROUND: Based on the pivotal role of astrocytes in brain homeostasis and the strong metabolic cooperation existing between neurons and astrocytes, it has been suggested that astrocytic dysfunctions might cause and/or contribute to neuroinflammation and neurodegenerative processes. Therapeutic approaches aimed at both neuroprotection and neuroinflammation reduction may prove particularly effective in slowing the progression of these diseases. The endogenous lipid mediator palmitoylethanolamide (PEA) displayed neuroprotective and anti(neuro)inflammatory properties, and demonstrated interesting potential as a novel treatment for Alzheimer's disease. OBJECTIVE AND METHODS: We firstly evaluated whether astrocytes could participate in regulating the Aβ42-induced neuronal damage, by using primary mouse astrocytes cell cultures and mixed astrocytes-neurons cultures. Furthermore, the possible protective effects of PEA against Aβ42-induced neuronal toxicity have also been investigated by evaluating neuronal viability, apoptosis, and morphometric parameters. RESULTS: The presence of astrocytes pre-exposed to Aβ42 (0.5μM; 24 h) induced a reduction of neuronal viability in primary mouse astrocytes-neurons co-cultures. Furthermore, under these experimental conditions, an increase in the number of neuronal apoptotic nuclei and a decrease in the number of MAP-2 positive neurons were observed. Finally, astrocytic Aβ42 pre-exposure induced an increase in the number of neurite aggregations/100μm as compared to control (i.e., untreated) astrocytes-neurons co-cultures. These effects were not observed in neurons cultured in the presence of astrocytes pre-exposed to PEA (0.1μM), applied 1 h before and maintained during Aβ42 treatment. CONCLUSION: Astrocytes contribute to Aβ42-induced neurotoxicity and PEA, by blunting Aβ42-induced astrocyte activation, improved neuronal survival in mouse astrocyte-neuron co-cultures.
Keywords: Amyloid beta-Peptides; Analysis of Variance; Animals; Animals, Newborn; Anti-Inflammatory Agents, Non-Steroidal; Astrocytes; Cell Survival; Cells, Cultured; Cerebral Cortex; Coculture Techniques; Ethanolamines; Mice; Mice, Inbred C57BL; Microtubule-Associated Proteins; Neurons; Palmitic Acids; Peptide Fragments; Time Factors

Pramlintide: The Effects of a Single Drug Injection on Blood Phosphatidylcholine Profile for Alzheimer's Disease. - Tao, Qiushan; Zhu, Haihao; Chen, Xi; Stern, Robert A; Kowall, Neil; Au, Rhoda; Blusztajn, Jan Krzysztof; Qiu, Wei Qiao (J Alzheimers Dis, 2018)
Studies suggest that a single injection of pramlintide, an amylin analog, induces changes in Alzheimer's disease (AD) biomarkers in the blood of AD mouse models and AD patients. The aim of this study was to examine whether a pramlintide challenge combined with a phosphatidylcholine (PC) profile diagnoses of AD and mild cognitive impairment (MCI) better than PC alone. Non-diabetic subjects with cognitive status were administered a single subcutaneous injection of 60 mcg of pramlintide under fasting condition. A total of 71 PCs, amyloid-β peptide (Aβ), and total tau (t-tau) in plasma at different time points were measured and treated as individual variables. A single injection of pramlintide altered the levels of 7 PCs in the blood, while a pramlintide injection plus food modulated the levels of 10 PCs in the blood (p < 0.05). The levels of 2 PCs in MCI and 12 PCs in AD in the pramlintide challenge were significantly lower than the ones in controls. We found that while some PCs were associated with only Aβ levels, other PCs were associated with both Aβ and t-tau levels. A receiver operating characteristic analysis of the PCs was combined with the Aβ and t-tau data to produce an area under the curve predictive value of 0.9799 between MCI subjects and controls, 0.9794 between AD subjects and controls, and 0.9490 between AD and MCI subjects. A combination of AD biomarkers and a group of PCs post a pramlintide challenge may provide a valuable diagnostic and prognostic test for AD and MCI.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Cognitive Dysfunction; Female; Humans; Islet Amyloid Polypeptide; Logistic Models; Male; Middle Aged; Phosphatidylcholines; ROC Curve; tau Proteins

Prediction of Alzheimer's Dementia in Patients with Amnestic Mild Cognitive Impairment in Clinical Routine: Incremental Value of Biomarkers of Neurodegeneration and Brain Amyloidosis Added Stepwise to Cognitive Status. - Lange, Catharina; Suppa, Per; Pietrzyk, Uwe; Makowski, Marcus R; Spies, Lothar; Peters, Oliver; Buchert, Ralph (J Alzheimers Dis, 2018)
The aim of this study was to evaluate the incremental benefit of biomarkers for prediction of Alzheimer's disease dementia (ADD) in patients with mild cognitive impairment (MCI) when added stepwise in the order of their collection in clinical routine. The model started with cognitive status characterized by the ADAS-13 score. Hippocampus volume (HV), cerebrospinal fluid (CSF) phospho-tau (pTau), and the FDG t-sum score in an AD meta-region-of-interest were compared as neurodegeneration markers. CSF-Aβ1-42 was used as amyloidosis marker. The incremental prognostic benefit from these markers was assessed by stepwise Kaplan-Meier survival analysis in 402 ADNI MCI subjects. Predefined cutoffs were used to dichotomize patients as 'negative' or 'positive' for AD characteristic alteration with respect to each marker. Among the neurodegeneration markers, CSF-pTau provided the best incremental risk stratification when added to ADAS-13. FDG PET outperformed HV only in MCI subjects with relatively preserved cognition. Adding CSF-Aβ provided further risk stratification in pTau-positive subjects, independent of their cognitive status. Stepwise integration of biomarkers allows stepwise refinement of risk estimates for MCI-to-ADD progression. Incremental benefit strongly depends on the patient's status according to the preceding diagnostic steps. The stepwise Kaplan-Meier curves might be useful to optimize diagnostic workflow in individual patients.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloidosis; Brain; Cognitive Dysfunction; Female; Fluorodeoxyglucose F18; Humans; Imaging, Three-Dimensional; Longitudinal Studies; Magnetic Resonance Imaging; Male; Middle Aged; Neuropsychological Tests; Positron-Emission Tomography; Survival Analysis; tau Proteins

Prevalence of Delirium in a Population of Elderly Outpatients with Dementia: A Retrospective Study. - Addesi, Desirée; Maio, Raffaele; Smirne, Nicoletta; Laganà, Valentina; Altomari, Natalia; Puccio, Gianfranco; Colao, Rosanna; Cupidi, Chiara; Perticone, Francesco; Bruni, Amalia Cecilia (J Alzheimers Dis, 2018)
BACKGROUND: Delirium is a multifactorial geriatric syndrome and often occurs in patients with cognitive impairment. It also remains under-recognized, specifically in elderly outpatients, because signs of delirium might overlap with symptoms of dementia. OBJECTIVE: The aim of the present study is to retrospectively apply the chart-based delirium instrument on a cohort of elderly outpatients with dementia, to assess prevalence and features of delirium in this population. METHODS: We randomly selected 650 medical records of outpatients referred to the "Neurogenetic Regional Centre" (CRN) of Lamezia Terme. Each evaluation included demographics, medical history, drugs, type and severity of dementia, and cognitive and functional status. Delirium was identified by the application of the chart-based delirium instrument. RESULTS: The prevalence of delirium was 13.3%. The study population was divided, according to the presence of delirium, into two subgroups. Compared to the no delirium group, the delirium group was significantly older and had greater cognitive impairment with lower MMSE scores both at baseline and at the end of the follow up. They also had a significant lower score on the ADL and IADL. In this group, a higher intake of antihypertensive and antipsychotic drugs, together with a lower intake of cholinesterase inhibitors and memantine, was observed. CONCLUSIONS: In this study, the chart-based delirium instrument was applied to an outpatient population affected by dementia and followed for a long time. Our data confirm the importance that age and frailty play on the genesis of delirium and suggest attention should be paid to the pharmacological treatment of these patients.
Keywords: Aged; Aged, 80 and over; Antipsychotic Agents; Cohort Studies; Delirium; Dementia; Female; Geriatric Assessment; Humans; Male; Outpatients; Prevalence; Severity of Illness Index

Prevalence of Potentially Inappropriate Medication Use in Older Inpatients with and without Cognitive Impairment: A Systematic Review. - Redston, Mitchell R; Hilmer, Sarah N; McLachlan, Andrew J; Clough, Alexander J; Gnjidic, Danijela (J Alzheimers Dis, 2018)
BACKGROUND: Older people with cognitive impairment, including dementia and delirium, are high users of acute care services internationally. Potentially inappropriate medication (PIM) use may be associated with adverse outcomes, including hospital re-admission, functional disability, and mortality. OBJECTIVE: This systematic review aimed to quantify and compare the prevalence of PIMs in older inpatients with and without cognitive impairment. METHODS: A systematic search of observational studies was performed independently assessed by two reviewers in Embase, Medline, PsycINFO, International Pharmaceutical Abstracts, Scopus, and Informit. Articles published in English during the period January 2007-June 2017 that reported PIM prevalence in hospital inpatients ≥ 65 years were included. PIMs were defined as the presence of polypharmacy (multiple medication use) and using implicit or explicit tools, such as the Beers criteria, and 'Screening Tool of Older Person's Prescriptions' (STOPP). RESULTS: 47 articles were included. In studies measuring polypharmacy (n = 15), the prevalence of PIMs ranged from 53.2% to 89.8% and 30.4% to 97.1% for inpatients with and without cognitive impairment, respectively, and 24.0% to 80.0% when cognitive status was unreported. In studies employing explicit and implicit tools (n = 35), the prevalence of PIMs when cognitive impairment was reported ranged from 20.6% to 80.5% using the Beers criteria, and 39.3% to 88.5% using STOPP. When cognitive status was unreported, the prevalence of PIMs ranged from 7.0% to 79.2% using the Beers criteria, and 20.0% to 63.4% using STOPP. CONCLUSION: Our findings suggest a high prevalence of PIMs in older inpatients with and without cognitive impairment. Future studies should investigate the impact of PIM use on patient-centered outcomes, such as functional status and quality of life, to inform enhanced acute care services.
Keywords: Aged; Cognitive Dysfunction; Dementia; Humans; Inpatients; Polypharmacy; Potentially Inappropriate Medication List; Prevalence; Quality of Life

Real World Recruiting of Older Subjects with Mild Cognitive Impairment for Exercise Trials: Community Readiness is Pivotal. - Sanders, Marit L; Stuckenschneider, Tim; Devenney, Kate E; Lawlor, Brian; Schneider, Stefan; Olde Rikkert, Marcel G M (J Alzheimers Dis, 2018)
Prevention trials in subjects with mild cognitive impairment (MCI), especially lifestyle interventions, can be difficult to carry out, particularly the recruitment and retention of subjects. We experienced these challenges in our multi-site one-year exercise trial in MCI, NeuroExercise. Trial recruitment rates differed significantly across sites; the non-medical sport university site, providing free access to a range of group exercise in a sports environment, proved far more successful than memory clinics linked to hospitals. This suggests that non-medical settings and a non-medical research community facilitating physical activities may be important factors in recruitment of subjects with MCI for large prevention trials.
Keywords: Aged; Cognitive Dysfunction; Europe; Exercise; Female; Humans; Life Style; Male; Middle Aged; Patient Selection

The Relevance of Iron in the Pathogenesis of Multiple System Atrophy: A Viewpoint. - Kaindlstorfer, Christine; Jellinger, Kurt A; Eschlböck, Sabine; Stefanova, Nadia; Weiss, Günter; Wenning, Gregor K (J Alzheimers Dis, 2018)
Iron is essential for cellular development and maintenance of multiple physiological processes in the central nervous system. The disturbance of its homeostasis leads to abnormal iron deposition in the brain and causes neurotoxicity via generation of free radicals and oxidative stress. Iron toxicity has been established in the pathogenesis of Parkinson's disease; however, its contribution to multiple system atrophy (MSA) remains elusive. MSA is characterized by cytoplasmic inclusions of misfolded α-synuclein (α-SYN) in oligodendrocytes referred to as glial cytoplasmic inclusions (GCIs). Remarkably, the oligodendrocytes possess high amounts of iron, which together with GCI pathology make a contribution toward MSA pathogenesis likely. Consistent with this observation, the GCI density is associated with neurodegeneration in central autonomic networks as well as olivopontocerebellar and striatonigral pathways. Iron converts native α-SYN into a β-sheet conformation and promotes its aggregation either directly or via increasing levels of oxidative stress. Interestingly, α-SYN possesses ferrireductase activity and α-SYN expression underlies iron mediated translational control via RNA stem loop structures. Despite a correlation between progressive putaminal atrophy and iron accumulation as well as clinical decline, it remains unclear whether pathologic iron accumulation in MSA is a secondary event in the cascade of neuronal degeneration rather than a primary cause. This review summarizes the current knowledge of iron in MSA and gives evidence for perturbed iron homeostasis as a potential pathogenic factor in MSA-associated neurodegeneration.
Keywords: alpha-Synuclein; Brain; Humans; Inclusion Bodies; Iron; Magnetic Resonance Imaging; Multiple System Atrophy; Oligodendroglia; Parkinsonian Disorders

Revolution of Alzheimer Precision Neurology. Passageway of Systems Biology and Neurophysiology. - Hampel, Harald; Toschi, Nicola; Babiloni, Claudio; Baldacci, Filippo; Black, Keith L; Bokde, Arun L W; Bun, René S; Cacciola, Francesco; Cavedo, Enrica; Chiesa, Patrizia A; Colliot, Olivier; Coman, Cristina-Maria; et al. (J Alzheimers Dis, 2018)
The Precision Neurology development process implements systems theory with system biology and neurophysiology in a parallel, bidirectional research path: a combined hypothesis-driven investigation of systems dysfunction within distinct molecular, cellular, and large-scale neural network systems in both animal models as well as through tests for the usefulness of these candidate dynamic systems biomarkers in different diseases and subgroups at different stages of pathophysiological progression. This translational research path is paralleled by an "omics"-based, hypothesis-free, exploratory research pathway, which will collect multimodal data from progressing asymptomatic, preclinical, and clinical neurodegenerative disease (ND) populations, within the wide continuous biological and clinical spectrum of ND, applying high-throughput and high-content technologies combined with powerful computational and statistical modeling tools, aimed at identifying novel dysfunctional systems and predictive marker signatures associated with ND. The goals are to identify common biological denominators or differentiating classifiers across the continuum of ND during detectable stages of pathophysiological progression, characterize systems-based intermediate endophenotypes, validate multi-modal novel diagnostic systems biomarkers, and advance clinical intervention trial designs by utilizing systems-based intermediate endophenotypes and candidate surrogate markers. Achieving these goals is key to the ultimate development of early and effective individualized treatment of ND, such as Alzheimer's disease. The Alzheimer Precision Medicine Initiative (APMI) and cohort program (APMI-CP), as well as the Paris based core of the Sorbonne University Clinical Research Group "Alzheimer Precision Medicine" (GRC-APM) were recently launched to facilitate the passageway from conventional clinical diagnostic and drug development toward breakthrough innovation based on the investigation of the comprehensive biological nature of aging individuals. The APMI movement is gaining momentum to systematically apply both systems neurophysiology and systems biology in exploratory translational neuroscience research on ND.
Keywords: Alzheimer Disease; Animals; Brain; Humans; Neurology; Neurophysiology; Precision Medicine; Systems Biology; Translational Medical Research

Role of ASK1/p38 Cascade in a Mouse Model of Alzheimer's Disease and Brain Aging. - Hasegawa, Yu; Toyama, Kensuke; Uekawa, Ken; Ichijo, Hidenori; Kim-Mitsuyama, Shokei (J Alzheimers Dis, 2018)
To examine the role of ASK1 in Alzheimer's disease (AD), we generated 5XFAD mice deficient in ASK1 and investigated the characteristics of old 5XFAD and wild-type mice with ASK1 deficiency. ASK1 deficiency improved cognitive function in 24-month-old 5XFAD mice, which was associated with the reduction of phosphorylated p38. Thus, ASK1/p38 cascade seems to play some role in the pathogenesis of AD in mice. In 24-month-old wild-type mice, ASK1 deficiency increased cerebral vasoreactivity to acetazolamide and significantly reduced brain soluble Aβ, which were also associated with the reduction of phosphorylated p38. Thus, ASK1/p38 cascade may contribute to brain aging of wild-type mice. Collectively, our present results provided the evidence suggesting the involvement of ASK1/p38 cascade in AD and brain aging.
Keywords: Aging; Alzheimer Disease; Amyloid beta-Protein Precursor; Amyloid Precursor Protein Secretases; Animals; Aspartic Acid Endopeptidases; Avoidance Learning; Disease Models, Animal; Gene Expression Regulation; MAP Kinase Kinase Kinase 5; MAP Kinase Signaling System; Mice; Mice, Inbred C57BL; Mice, Transgenic; Presenilin-1; Reaction Time

The Role of Verb Fluency in the Detection of Early Cognitive Impairment in Alzheimer's Disease. - Alegret, Montserrat; Peretó, Mar; Pérez, Alba; Valero, Sergi; Espinosa, Ana; Ortega, Gemma; Hernandez, Isabel; Mauleón, Ana; Rosende-Roca, Maitee; Vargas, Liliana; Rodríguez-Gómez, Octavio; Abdelnour, Carla; et al. (J Alzheimers Dis, 2018)
BACKGROUND: Verb fluency (VF) is the less commonly used fluency test, despite several studies suggesting its potential as a neuropsychological assessment tool. OBJECTIVE: To investigate the presence of VF deficits in mild cognitive impairment (MCI) and mild Alzheimer's disease (AD) dementia; to assess the usefulness of VF in the detection of cognitively healthy (CH) people who will convert to MCI, and from MCI to dementia; and to establish the VF cut-offs useful in the cognitive assessment of Spanish population. METHODS: 568 CH, 885 MCI, and 367 mild AD dementia individuals were administered the VF test and a complete neuropsychological battery. Longitudinal analyses were performed in 231 CH and 667 MCI subjects to search for VF predictors of diagnosis conversion. RESULTS: A worsening on VF performance from CH, MCI to AD dementia groups was found. Lower performances on VF were significantly related to conversion from CH to MCI/MCI to dementia. When the effect of time to conversion was analyzed, a significant effect of VF was found on the faster conversion from CH to MCI, but not from MCI to dementia. Moreover, VF cut-off scores and sensitivity/specificity values were calculated for 6 conditions (3 age ranges by 2 educational levels). CONCLUSION: The VF test may be a useful tool for the differential diagnosis of cognitive failure in the elderly. Since VF deficits seem to take place in early stages of the disease, it is a suitable neuropsychological tool for the detection not only of CH people who will convert to MCI, but also from MCI to dementia.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Case-Control Studies; Cognitive Dysfunction; Cross-Sectional Studies; Early Diagnosis; Executive Function; Female; Humans; Language Tests; Logistic Models; Longitudinal Studies; Male; Middle Aged; Proportional Hazards Models; Sensitivity and Specificity; Spain

Serum C-Peptide, Visfatin, Resistin, and Ghrelin are Altered in Sporadic and GRN-Associated Frontotemporal Lobar Degeneration. - Zanardini, Roberta; Benussi, Luisa; Fostinelli, Silvia; Saraceno, Claudia; Ciani, Miriam; Borroni, Barbara; Padovani, Alessandro; Binetti, Giuliano; Ghidoni, Roberta (J Alzheimers Dis, 2018)
Frontotemporal lobar degeneration (FTLD) is a group of complex neurodegenerative disease characterized by progressive deterioration of the frontal and anterior temporal lobes of the brain resulting in different heterogeneous conditions, mainly characterized by personality changes, behavioral disturbances, such as binge eating, and deficits in language and executive functions. Null mutations in progranulin gene (GRN) are one of the most frequent genetic determinants in familial frontotemporal dementia. Recently, progranulin was recognized as an adipokine involved in diet-induced obesity and insulin resistance revealing its metabolic function. Increasing evidence suggests that neurodegenerative dementias are associated with a higher prevalence of metabolic changes than in the general population. According to these findings, the aim of this study is to investigate putative alterations in markers linked to metabolic functions (i.e., C-peptide, ghrelin, glucose-dependent insulinotropic polypeptide, glucagon-like peptide-1, glucagon, insulin, resistin, and three adipokines as visfatin, leptin, and plasminogen activator inhibitor-1 total) in sporadic and GRN-related FTLD. We found that 1) C-peptide is increased in sporadic and GRN-mutated FTLD patients; in addition, we demonstrated an anticipation of the disease in patients with the highest C-peptide concentrations; 2) visfatin is slightly reduced in the whole FTLD group; 3) resistin, an adipokine involved in inflammatory-related diseases, is specifically increased in FTLD due to GRN null mutations; 4) ghrelin concentration is specifically increased in pre-symptomatic subjects and FTLD patients with GRN mutations. These findings support the hypothesis that alterations in metabolic pattern are involved in FTLD progression highlighting novel putative targets for the development of preventive and personalized therapies.
Keywords: Aged; Biomarkers; C-Peptide; Female; Frontotemporal Lobar Degeneration; Ghrelin; Humans; Kaplan-Meier Estimate; Male; Middle Aged; Mutation; Nicotinamide Phosphoribosyltransferase; Progranulins; Resistin

Serum Non-Ceruloplasmin Non-Albumin Copper Elevation in Mild Cognitive Impairment and Dementia due to Alzheimer's Disease: A Case Control Study. - Rozzini, Luca; Lanfranchi, Francesco; Pilotto, Andrea; Catalani, Simona; Gilberti, Maria Enrica; Paganelli, Matteo; Apostoli, Pietro; Padovani, Alessandro (J Alzheimers Dis, 2018)
Several studies showed high serum copper levels in Alzheimer's disease (AD). The present study applied a newly developed method to detect serum copper free from proteins (free-Cu). Forty-four patients affected by dementia due to AD, thirty-six patients affected by mild cognitive impairment (MCI) due to AD, and twenty-eight healthy controls underwent clinical, cognitive, and MRI assessment. The new method showed higher free-Cu concentrations in MCI and dementia due to AD compared to controls (p < 0.0001). No correlation between copper levels, cognitive or MRI measures were found.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Case-Control Studies; Cognitive Dysfunction; Copper; Female; Humans; Magnetic Resonance Imaging; Male; Psychiatric Status Rating Scales

SIRT1 Deacetylates SC35 and Suppresses Its Function in Tau Exon 10 Inclusion. - Yin, Xiaomin; Jiang, Xiaosu; Wang, Jia; Qian, Shuo; Liu, Fei; Qian, Wei (J Alzheimers Dis, 2018)
Approximately equal amounts of 3R-tau and 4R-tau resulting from alternative splicing of tau exon 10 is necessary to maintain normal brain function. Dysregulation of alternative splicing of tau exon 10 and the imbalance of 3R-tau/4R-tau have been seen in inherited and sporadic tauopathies. Splicing factor SC35 (also name as SRSF2) plays an important role in promoting tau exon 10 inclusion. SC35 is post-translationally modified by phosphorylation and acetylation, but the role of acetylation in SC35-medicated tau exon 10 inclusion is unknown. Sirtuin type 1 (SIRT1) is an enzyme that deacetylates proteins and associates with age-related disease such as Alzheimer's disease. In the present study, we determined the role of SIRT1 in SC35 acetylation and in the alternative splicing of tau exon 10. We found that SIRT1 interacts with and deacetylates SC35, and inhibits SC35-promoted tau exon 10 inclusion. Substituting K52 residue of SC35 by arginine impairs the role of SC35 in tau exon 10 inclusion. These results suggest that SIRT1 may serve as a therapeutic target for tauopathy by regulating SC35-mediated tau exon 10 splicing.
Keywords: Alternative Splicing; Alzheimer Disease; Exons; HEK293 Cells; HeLa Cells; Humans; Phosphorylation; Ribonucleoproteins; Serine-Arginine Splicing Factors; Sirtuin 1; tau Proteins; Tauopathies

SORL1 Variants in Familial Alzheimer's Disease. - Gómez-Tortosa, Estrella; Ruggiero, María; Sainz, Ma José; Villarejo-Galende, Alberto; Prieto-Jurczynska, Cristina; Venegas Pérez, Begoña; Ordás, Carlos; Agüero, Pablo; Guerrero-López, Rosa; Pérez-Pérez, Julián (J Alzheimers Dis, 2018)
The SORL1 gene encodes a protein involved in the amyloidogenic process, and its variants have been associated with Alzheimer's disease (AD) physiopathology. We screened for SORL1 variants in 124 familial (44 early- and 80 late-onset) dementia of Alzheimer type (DAT) cases. Nine potentially pathogenic changes (three not previously reported and six rare variants) were found in nine probands (7%). After screening the control population and siblings (presence in at least 1/200 controls and/or absence of segregation pattern), a causal relationship with the disease was considered unlikely in six variants and uncertain in one. The change Trp848Ter and a splice-site variant remained likely correlated with the disease. SORL1 mutations are present in 7% of our familial DAT cohort, though in most cases cannot be considered the direct cause of the disease.
Keywords: Aged; Alzheimer Disease; Case-Control Studies; Female; Gene Frequency; Genetic Predisposition to Disease; Humans; LDL-Receptor Related Proteins; Male; Membrane Transport Proteins; Middle Aged; Mutation; Polymorphism, Single Nucleotide; Siblings; Spain

SPARCL1 Accelerates Symptom Onset in Alzheimer's Disease and Influences Brain Structure and Function During Aging. - Seddighi, Sahba; Varma, Vijay R; An, Yang; Varma, Sudhir; Beason-Held, Lori L; Tanaka, Toshiko; Kitner-Triolo, Melissa H; Kraut, Michael A; Davatzikos, Christos; Thambisetty, Madhav (J Alzheimers Dis, 2018)
We recently reported that alpha-2 macroglobulin (A2M) is a biomarker of neuronal injury in Alzheimer's disease (AD) and identified a network of nine genes co-expressed with A2M in the brain. This network includes the gene encoding SPARCL1, a protein implicated in synaptic maintenance. Here, we examine whether SPARCL1 is associated with longitudinal changes in brain structure and function in older individuals at risk for AD in the Baltimore Longitudinal Study of Aging. Using data from the Gene-Tissue Expression Project, we first identified two single nucleotide polymorphisms (SNPs), rs9998212 and rs7695558, associated with lower brain SPARCL1 gene expression. We then analyzed longitudinal trajectories of cognitive performance in 591 participants who remained cognitively normal (average follow-up interval: 11.8 years) and 129 subjects who eventually developed MCI or AD (average follow-up interval: 9.4 years). Cognitively normal minor allele carriers of rs7695558 who developed incident AD showed accelerated memory loss prior to disease onset. Next, we compared longitudinal changes in brain volumes (MRI; n = 120 participants; follow-up = 6.4 years; 826 scans) and resting-state cerebral blood flow (rCBF; 15O-water PET; n = 81 participants; follow-up = 7.7 years; 664 scans) in cognitively normal participants. Cognitively normal minor allele carriers of rs9998212 showed accelerated atrophy in several global, lobar, and regional brain volumes. Minor allele carriers of both SNPs showed longitudinal changes in rCBF in several brain regions, including those vulnerable to AD pathology. Our findings suggest that SPARCL1 accelerates AD pathogenesis and thus link neuroinflammation with widespread changes in brain structure and function during aging.
Keywords: Aged; Aged, 80 and over; Aging; Alzheimer Disease; Brain; Calcium-Binding Proteins; Cerebrovascular Circulation; Cognition Disorders; Extracellular Matrix Proteins; Female; Humans; Independent Living; Longitudinal Studies; Magnetic Resonance Imaging; Male; Middle Aged; Neuropsychological Tests; Polymorphism, Single Nucleotide; Positron-Emission Tomography

Synthetic Fragment of Receptor for Advanced Glycation End Products Prevents Memory Loss and Protects Brain Neurons in Olfactory Bulbectomized Mice. - Volpina, Olga M; Samokhin, Alexandr N; Koroev, Dmitriy O; Nesterova, Inna V; Volkova, Tatyana D; Medvinskaya, Natalia I; Nekrasov, Pavel V; Tatarnikova, Olga G; Kamynina, Anna V; Balasanyants, Samson M; Voronina, Tamara A; Kulikov, Alexey M; et al. (J Alzheimers Dis, 2018)
Activation of receptor for advanced glycation end products (RAGE) plays an essential role in the development of Alzheimer's disease (AD). It is known that the soluble isoform of the receptor binds to ligands and prevents negative effects of the receptor activation. We proposed that peptide fragments from RAGE prevent negative effects of the receptor activation during AD neurodegeneration. We have synthesized peptide fragments from surface-exposed regions of RAGE. Peptides were intranasally administrated into olfactory bulbectomized (OBX) mice, which developed some characteristics similar to AD neurodegeneration. We have found that only insertion of fragment (60-76) prevents the memory of OBX mice. Immunization of OBX mice with peptides showed that again only (60-76) peptide protected the memory of animals. Both intranasal insertion and immunization decreased the amyloid-β (Aβ) level in the brain. Activity of shortened fragments of (60-76) peptide was tested and showed only the (60-70) peptide is responsible for manifestation of activity. Intranasal administration of (60-76) peptide shows most protective effect on morpho-functional characteristics of neurons in the cortex and hippocampal areas. Using Flu-(60-76) peptide, we revealed its penetration in the brain of OBX mice as well as colocalization of Flu-labeled peptide with Aβ in the brain regions in transgenic mice. Flu-(60-76) peptide complex with trimer of Aβ was detected by SDS-PAGE. These data indicate that Aβ can be one of the molecular target of (60-70) peptide. These findings provide a new peptide molecule for design of anti-AD drug and for investigation of RAGE activation ways in progression of AD neurodegeneration.
Keywords: Administration, Intranasal; Animals; Behavior, Animal; Brain; Disease Models, Animal; Male; Maze Learning; Memory Disorders; Mice; Mice, Transgenic; Neurons; Olfactory Bulb; Peptide Fragments; Receptor for Advanced Glycation End Products

Tau and Amyloid Positron Emission Tomography Imaging Predict Driving Performance Among Older Adults with and without Preclinical Alzheimer's Disease. - Roe, Catherine M; Babulal, Ganesh M; Mishra, Shruti; Gordon, Brian A; Stout, Sarah H; Ott, Brian R; Carr, David B; Ances, Beau M; Morris, John C; Benzinger, Tammie L S (J Alzheimers Dis, 2018)
Abnormal levels of Alzheimer's disease (AD) biomarkers, measured by positron emission tomography imaging using amyloid-based radiotracers and cerebrospinal fluid, are associated with impaired driving performance in older adults. We examined whether preclinical AD staging, defined using amyloid imaging and tau imaging using the radiotracer T807 (AKA flortaucipir or AV-1451), was associated with receiving a marginal/fail rating on a standardized road test (n = 42). Participants at Stage 2 (positive amyloid and tau scans) of preclinical AD were more likely to receive a marginal/fail rating compared to participants at Stage 0 or 1. Stage 2 preclinical AD may manifest in worse driving performance.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid; Automobile Driving; Biomarkers; Carbolines; Female; Humans; Logistic Models; Male; Neuroimaging; Positron-Emission Tomography; tau Proteins

Tauopathies: Mechanisms and Therapeutic Strategies. - Tan, Chen-Chen; Zhang, Xiao-Yan; Tan, Lan; Yu, Jin-Tai (J Alzheimers Dis, 2018)
Tauopathies are morphologically, biochemically, and clinically heterogeneous neurodegenerative diseases defined by the accumulation of abnormal tau proteins in the brain. There is no effective method to prevent and reverse the tauopathies, but this gloomy picture has been changed by recent research advances. Evidences from genetic studies, experimental animal models, and molecular and cell biology have shed light on the main mechanisms of the diseases. The development of radiology and biochemistry, especially the development of PET imaging, will provide important biomarkers for the clinical diagnosis and treatment. Given the central role of tau in tauopathies, many treatments have constantly emerged, including targeting phosphorylation, targeting aggregation, increasing microtubule stabilization, tau immunization, clearance of tau, anti-inflammatory treatment, and other therapeutics. There is still a long way to go before we obtain drug therapy targeted at multifactor mechanisms.
Keywords: Animals; Biomarkers; Brain; Disease Models, Animal; Humans; Neuroimaging; Phosphorylation; Positron-Emission Tomography; tau Proteins; Tauopathies

Ubisol-Q10 (a Nanomicellar Water-Soluble Formulation of CoQ10) Treatment Inhibits Alzheimer-Type Behavioral and Pathological Symptoms in a Double Transgenic Mouse (TgAPEswe, PSEN1dE9) Model of Alzheimer's Disease. - Muthukumaran, Krithika; Kanwar, Annie; Vegh, Caleb; Marginean, Alexandra; Elliott, Austin; Guilbeault, Nicholas; Badour, Alexander; Sikorska, Marianna; Cohen, Jerome; Pandey, Siyaram (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) is one of the most common neurodegenerative pathologies for which there are no effective therapies to halt disease progression. Given the increase in the incidence of this disorder, there is an urgent need for pharmacological intervention. Unfortunately, recent clinical trials produced disappointing results. Molecular mechanisms of AD are converging on the notion that mitochondrial dysfunction, oxidative stress, and accumulation of dysfunctional proteins are involved in AD pathology. Previously, we have shown that a water-soluble formulation of Coenzyme Q10 (Ubisol-Q10), an integral part of the electron transport chain, stabilizes mitochondria and prevents neuronal cell death caused by neurotoxins or oxidative stress both in vitro and in vivo. In this study, we evaluated the neuroprotective effects of Ubisol-Q10 treatment in double transgenic AD mice. In the present study, we report that providing Ubisol-Q10 in drinking water (at a dose of ∼6 mg/kg/day) reduced circulating amyloid-β (Aβ) peptide, improved long term memory, preserved working spatial memory, and drastically inhibited Aβ plaque formation in 18-month-old transgenic mice compared to an untreated transgenic group. Thus Ubisol-Q10 supplementation has the potential to inhibit the progression of neurodegeneration, leading to a better quality of life for humans suffering with AD.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Amyloid beta-Protein Precursor; Animals; Disease Models, Animal; Male; Maze Learning; Memory; Memory Disorders; Mice; Mice, Transgenic; Microglia; Mutation; Nerve Tissue Proteins; Peptide Fragments; Presenilin-1; Ubiquinone; Vitamins

The Uniform Data Set, Czech Version: Normative Data in Older Adults from an International Perspective. - Nikolai, Tomas; Stepankova, Hana; Kopecek, Miloslav; Sulc, Zdenek; Vyhnálek, Martin; Bezdicek, Ondrej (J Alzheimers Dis, 2018)
BACKGROUND: Outside of the United States, international perspectives on normative data for neuropsychological test performance, within diverse populations, have been scarce. The neuropsychological test battery from the Uniform Data Set (UDS) of the Alzheimer's Disease Centers (ADC) program of the United States National Institute on Aging (NIA) is one of the most sensitive batteries for the evaluation of both normal cognitive aging and pathological cognitive decline. OBJECTIVE: This study aimed to determine the feasibility of the Czech Neuropsychological Test Battery from the Uniform Data Set (UDS-Cz 2.0), while also evaluating the results obtained from an international perspective. METHODS: This paper describes data from 520 cognitively normal participants. Regression analyses were used to describe the influence of demographic variables on UDS-Cz test performance. RESULTS: Cognitive performance on all measures declined with age, with patient education level serving as a protective factor. Therefore, the present study provides normative data for the UDS-Cz, adjusted for the demographic variables of age and education. CONCLUSION: The present study determines the psychometric properties of the UDS-Cz and establishes normative values in the aging Czech population, which can be used in clinical settings.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cognition; Czech Republic; Female; Humans; Internationality; Male; Middle Aged; National Institute on Aging (U.S.); Neuropsychological Tests; Psychometrics; Reference Values; Regression Analysis; United States

Vestibular Loss Predicts Poorer Spatial Cognition in Patients with Alzheimer's Disease. - Wei, Eric X; Oh, Esther S; Harun, Aisha; Ehrenburg, Matthew; Agrawal, Yuri (J Alzheimers Dis, 2018)
The vestibular system is an important contributor to balance control, spatial orientation, and falls risk. Recent evidence has shown that Alzheimer's disease (AD) patients have a higher prevalence of vestibular impairment relative to healthy controls. We sought to evaluate whether vestibular loss is specifically associated with poor spatial cognitive skills among patients with mild cognitive impairment (MCI) and AD. We enrolled 50 patients (22 MCI and 28 AD) from an interdisciplinary Memory Clinic and measured vestibular physiologic function in all patients. Spatial cognitive function was assessed using the Money Road Map Test (MRMT) and the Trail Making Test Part B (TMT-B). General cognitive function was assessed with the Mini-Mental Status Examination (MMSE). In multivariable linear regression analyses adjusted for age, gender, education level, and MMSE, MCI and AD patients with vestibular loss made significantly more errors on the MRMT relative to patients with normal vestibular function (β= 7.3, 95% CI 2.4, 12.1 for unilateral vestibular loss and β= 6.4, 95% CI 1.9, 10.9 for bilateral vestibular loss). We further stratified AD patients into "spatially normal" and "spatially impaired" groups based on MRMT performance, and found that the prevalence of vestibular loss was significantly higher in the spatially impaired AD group relative to the spatially normal AD group. These findings support the hypothesis that vestibular loss contributes specifically to a decline in spatial cognitive ability in MCI and AD patients, independently of general cognitive decline, and may predict a "spatially impaired" subtype of AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Bilateral Vestibulopathy; Cognitive Dysfunction; Cross-Sectional Studies; Female; Humans; Linear Models; Male; Multivariate Analysis; Neuropsychological Tests; Prospective Studies; Spatial Navigation; Vestibular Function Tests

Visit-To-Visit Blood Pressure Variability and the Risk of Dementia in Older People. - van Middelaar, Tessa; van Dalen, Jan W; van Gool, Willem A; van den Born, Bert-Jan H; van Vught, Lonneke A; Moll van Charante, Eric P; Richard, Edo (J Alzheimers Dis, 2018)
BACKGROUND: High visit-to-visit variability (VVV) in blood pressure (BP) is associated with cerebrovascular lesions on neuroimaging. OBJECTIVE: Our primary objective was to investigate whether VVV is associated with incident all-cause dementia. As a secondary objective, we studied the association of VVV with cognitive decline and cardiovascular disease (CVD). METHODS: We included community-dwelling people (age 70-78 year) from the 'Prevention of Dementia by Intensive Vascular Care' (preDIVA) trial with three to five 2-yearly BP measurements during 6-8 years follow-up. VVV was defined using coefficient of variation (CV; SD/mean×100). Cognitive decline was assessed using the Mini-Mental State Examination (MMSE). Incident CVD was defined as myocardial infarction or stroke. We used a Cox proportional hazard regression and mixed-effects model adjusted for sociodemographic factors and cardiovascular risk factors. RESULTS: In 2,305 participants (aged 74.2±2.5), mean systolic BP over all available visits was 150.1 mmHg (SD 13.6), yielding a CV of 9.0. After 6.4 years (SD 0.8) follow-up, 110 (4.8%) participants developed dementia and 140 (6.1%) CVD. Higher VVV was not associated with increased risk of dementia (hazard ratio [HR] 1.00 per point CV increase; 95% confidence interval [CI] 0.96-1.05), although the highest quartile of VVV was associated with stronger decline in MMSE (β -0.09, 95% CI -0.17 to -0.01). Higher VVV was associated with incident CVD (HR 1.07; 95% CI 1.04-1.11). CONCLUSION: In our study among older people, high VVV is not associated with incident all-cause dementia. It is associated with decline in MMSE and incident CVD.
Keywords: Aged; Antihypertensive Agents; Blood Pressure; Cardiovascular Diseases; Dementia; Female; Humans; Hypertension; Incidence; Male; Netherlands; Proportional Hazards Models; Risk Factors

White Matter Hyperintensity Predicts the Risk of Incident Cognitive Decline in Community Dwelling Elderly. - Ding, Ding; Xiong, Yunyun; Zhao, Qianhua; Guo, Qihao; Chu, Shuguang; Chu, Winnie W C; Luo, Jianfeng; Liang, Xiaoniu; Zheng, Li; Hong, Zhen; Wong, Lawrence K S; Mok, Vincent C T (J Alzheimers Dis, 2018)
BACKGROUND: Unlike western countries, data on white matter hyperintensity (WMH) in community dwelling elderly in Asian population is very limited. OBJECTIVE: To examine the relation between baseline WMH burden and the risk of incident cognitive decline in a community-based cohort with Chinese-dwelling elderly. METHODS: We prospectively evaluated the incident cognitive decline for 226 participants in the Shanghai Aging Study. Baseline WMH severity was visually rated by the age-related white matter changes (ARWMC) scale based on MRI. Cox proportional hazards regression model was used to estimate the relative risk (RR) of total ARWMC scale, global ARWMC score, presence of lacune and microbleed, for incident cognitive decline by adjusting potential confounders. RESULTS: Forty subjects were identified with incident cognitive decline (new onset 34 mild cognitive impairment and 6 dementia) during a median duration of 6 years follow-up. The incidence of cognitive decline was 3.0 (95% confidence interval [CI] 2.2-4.1) per 100 person-years. Increasing total ARWMC scale [RR1.21 (95% CI 1.06-1.39), p = 0.004)], confluent WMH [RR3.16 (95% CI 1.50-6.64), p = 0.002), and presence of lacunes [RR 2.73 (95% CI 1.21-6.15)] at baseline were independent predictors of incident cognitive decline. CONCLUSION: Our study demonstrated that confluent WMH may increase the risk of incident cognitive decline by 3 folds in community dwelling subjects. Small vessel disease may cause heavy burden of cognitive impairment in the elderly in China.
Keywords: Aged; China; Cognitive Dysfunction; Female; Humans; Independent Living; Kaplan-Meier Estimate; Magnetic Resonance Imaging; Male; Middle Aged; Neuropsychological Tests; Proportional Hazards Models; Prospective Studies; Risk Factors; White Matter

Word and Picture Version of the Free and Cued Selective Reminding Test (FCSRT): Is There Any Difference? - Arighi, Andrea; Carandini, Tiziana; Mercurio, Matteo; Carpani, Giovanni; Pietroboni, Anna Margherita; Fumagalli, Giorgio; Ghezzi, Laura; Basilico, Paola; Calvi, Alberto; Scarioni, Marta; De Riz, Milena; Fenoglio, Chiara; et al. (J Alzheimers Dis, 2018)
The Free and Cued Selective Reminding Test (FCSRT) is the most commonly used neuropsychological test to evaluate episodic memory. Two variants of FCSRT exist, using the recall of words (FCSRT-w) or pictures (FCSRT-p). Fourteen patients with mild cognitive impairment underwent neuropsychological evaluation and brain magnetic resonance. We found differences in FCSRT-w and FCSRT-p variants scores. FCSRT-p was correlated with atrophy in areas involved in visual stimuli processing while FCSRT-w was correlated to hippocampal atrophy. Our study suggests that FCSRT-w and FCSRT-p scores are not equivalent, but a larger cohort of patients is needed to validate these results.
Keywords: Aged; Aged, 80 and over; Association Learning; Cognitive Dysfunction; Cues; Female; Humans; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Male; Mental Recall; Middle Aged; Neuropsychological Tests; Photic Stimulation; Vocabulary

18F-AV-1451 PET Imaging in Three Patients with Probable Cerebral Amyloid Angiopathy. - Kim, Hee Jin; Cho, Hanna; Werring, David J; Jang, Young Kyoung; Kim, Yeo Jin; Lee, Jin San; Lee, Juyoun; Jun, Soomin; Park, Seongbeom; Ryu, Young Hoon; Choi, Jae Yong; Cho, Young Seok; et al. (J Alzheimers Dis, 2017)
Cerebrovascular deposition of amyloid-β, known as cerebral amyloid angiopathy (CAA), is associated with MRI findings of lobar hemorrhage, cerebral microbleeds, and cortical superficial siderosis. Although pathological studies suggest that tau may co-localize with vascular amyloid, this has not yet been investigated in CAA in vivo. Three patients with probable CAA underwent 11C-Pittsburgh Compound B (PiB) PET or 18F-florbetaben PET to evaluate amyloid burden, and 18F-AV-1451 PET to evaluate paired helical filament tau burden. Regions that had cerebral microbleeds or cortical superficial siderosis largely overlapped with those showing increased 18F-AV-1451. Our preliminary study raised the possibility that lobar cerebral microbleeds, and cortical superficial siderosis, which are characteristic markers of vascular amyloid, may be associated with local production of paired helical filament tau.
Keywords: Aged; Aged, 80 and over; Aniline Compounds; Brain; Carbolines; Cerebral Amyloid Angiopathy; Female; Humans; Image Processing, Computer-Assisted; Male; Positron-Emission Tomography; Thiazoles

Amyloid-β Deposition and Long-Term Progression in Mild Cognitive Impairment due to Alzheimer's Disease Defined with Amyloid PET Imaging. - Hatashita, Shizuo; Wakebe, Daichi (J Alzheimers Dis, 2017)
The aim was to evaluate brain amyloid-β (Aβ) deposition in patients with mild cognitive impairment (MCI) due to Alzheimer's disease (AD) using amyloid PET imaging and clarify the relationship between the annual change in Aβ deposition and disease progression. Forty-eight MCI patients underwent neuropsychological assessment and amyloid PET imaging using [11C]-PIB over a follow-up of 5.7±1.5 years. Thirty-nine MCI patients who had an amyloid-positive scan were defined as MCI due to AD, and 9 MCI patients who had an amyloid-negative scan were included. Regions of interest were defined on co-registered MRI, and the PIB standardized uptake value ratio (SUVR) on the same regions was used over follow-up. Annual change in PIB SUVR was calculated. Patients with MCI due to AD had higher baseline PIB SUVR (1.81±0.32, n = 39, p < 0.01) and a greater annual rate of change in PIB SUVR (0.044±0.027, n = 39, p < 0.01) compared to amyloid-negative MCI patients. Twenty-eight (71.8%) progressed to AD. In patients who progressed during a short duration of 1.7±0.8 years, the annual rate of increase in PIB SUVR was 0.101±0.094 (n = 16, p < 0.05), which was greater compared to patients with long conversion or stable patients. There was a negative correlation between the annual rate of increase in PIB SUVR and duration of progression to AD among individual MCI converters (r = -0.47, n = 28, p < 0.05). The patients defined as MCI due to AD could progress to AD with a shorter period if they have a greater increased annual rate in brain Aβ deposition.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid; Aniline Compounds; Cognitive Dysfunction; Disease Progression; Female; Follow-Up Studies; Humans; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Male; Mental Status Schedule; Middle Aged; Positron-Emission Tomography; Thiazoles

Exercise Training and Functional Connectivity Changes in Mild Cognitive Impairment and Healthy Elders. - Chirles, Theresa J; Reiter, Katherine; Weiss, Lauren R; Alfini, Alfonso J; Nielson, Kristy A; Smith, J Carson (J Alzheimers Dis, 2017)
BACKGROUND: Effective interventions are needed to improve brain function in mild cognitive impairment (MCI), an early stage of Alzheimer's disease (AD). The posterior cingulate cortex (PCC)/precuneus is a hub of the default mode network (DMN) and is preferentially vulnerable to disruption of functional connectivity in MCI and AD. OBJECTIVE: We investigated whether 12 weeks of aerobic exercise could enhance functional connectivity of the PCC/precuneus in MCI and healthy elders. METHODS: Sixteen MCI and 16 healthy elders (age range = 60-88) engaged in a supervised 12-week walking exercise intervention. Functional MRI was acquired at rest; the PCC/precuneus was used as a seed for correlated brain activity maps. RESULTS: A linear mixed effects model revealed a significant interaction in the right parietal lobe: the MCI group showed increased connectivity while the healthy elders showed decreased connectivity. In addition, both groups showed increased connectivity with the left postcentral gyrus. Comparing pre to post intervention changes within each group, the MCI group showed increased connectivity in 10 regions spanning frontal, parietal, temporal and insular lobes, and the cerebellum. Healthy elders did not demonstrate any significant connectivity changes. CONCLUSION: The observed results show increased functional connectivity of the PCC/precuneus in individuals with MCI after 12 weeks of moderate intensity walking exercise training. The protective effects of exercise training on cognition may be realized through the enhancement of neural recruitment mechanisms, which may possibly increase cognitive reserve. Whether these effects of exercise training may delay further cognitive decline in patients diagnosed with MCI remains to be demonstrated.
Keywords: Aged; Aged, 80 and over; Cognitive Dysfunction; Exercise; Exercise Test; Female; Gyrus Cinguli; Humans; Image Processing, Computer-Assisted; Linear Models; Magnetic Resonance Imaging; Male; Middle Aged; Neuropsychological Tests; Oxygen; Psychiatric Status Rating Scales

Family History of Alzheimer's Disease is Associated with Impaired Perceptual Discrimination of Novel Objects. - Mason, Emily J; Hussey, Erin P; Molitor, Robert J; Ko, Philip C; Donahue, Manus J; Ally, Brandon A (J Alzheimers Dis, 2017)
Early detection may be the key to developing therapies that will combat Alzheimer's disease (AD). It has been consistently demonstrated that one of the main pathologies of AD, tau, is present in the brain decades before a clinical diagnosis. Tau pathology follows a stereotypical route through the medial temporal lobe beginning in the entorhinal and perirhinal cortices. If early pathology leads to very subtle changes in behavior, it may be possible to detect these changes in subjects years before a clinical diagnosis can currently be made. We aimed to discover if cognitively normal middle-aged adults (40-60 years old) at increased risk for AD due to family history would have impaired performance on a cognitive task known to challenge the perirhinal cortex. Using an oddity detection task, we found that subjects with a family history of AD had lowered accuracy without demonstrating differences in rate of acquisition. There were no differences between subjects' medial temporal lobe volume or cortical thickness, indicating that the changes in behavior were not due to significant atrophy. These results demonstrate that subtle changes in perceptual processing are detectable years before a typical diagnosis even when there are no differences detectable in structural imaging data. Anatomically-targeted cognitive testing may be useful in identifying subjects in the earliest stages of AD.
Keywords: Adult; Alzheimer Disease; Cerebral Cortex; Discrimination (Psychology); Family Health; Female; Humans; Magnetic Resonance Imaging; Male; Middle Aged; Neuropsychological Tests; Perceptual Disorders; Photic Stimulation; Recognition (Psychology); Signal Detection, Psychological

Humanin Specifically Interacts with Amyloid-β Oligomers and Counteracts Their in vivo Toxicity. - Romeo, Margherita; Stravalaci, Matteo; Beeg, Marten; Rossi, Alessandro; Fiordaliso, Fabio; Corbelli, Alessandro; Salmona, Mario; Gobbi, Marco; Cagnotto, Alfredo; Diomede, Luisa (J Alzheimers Dis, 2017)
The 24-residue peptide humanin (HN) has been proposed as a peptide-based inhibitor able to interact directly with amyloid-β (Aβ) oligomers and interfere with the formation and/or biological properties of toxic Aβ species. When administered exogenously, HN, or its synthetic S14G-derivative (HNG), exerted multiple cytoprotective effects, counteracting the Aβ-induced toxicity. Whether these peptides interact directly with Aβ, particularly with the soluble oligomeric assemblies, remains largely unknown. We here investigated the ability of HN and HNG to interact directly with highly aggregating Aβ42, and interfere with the formation and toxicity of its oligomers. Experiments were run in cell-free conditions and in vivo in a transgenic C. elegans strain in which the Aβ toxicity was specifically due to oligomeric species. Thioflavin-T assay indicated that both HN and HNG delay the formation and reduce the final amount of Aβ42 fibrils. In vitro surface plasmon resonance studies indicated that they interact with Aβ42 oligomers favoring the formation of amorphous larger assemblies, observed with turbidity and electron microscopy. In vivo studies indicated that both HN and HNG decrease the relative abundance of A11-positive prefibrillar oligomers as well as OC-positive fibrillar oligomers and had similar protective effects. However, while HN possibly decreased the oligomers by promoting their assembly into larger aggregates, the reduction of oligomers caused by HNG can be ascribed to a marked decrease of the total Aβ levels, likely the consequence of the HNG-induced overexpression of the Aβ-degrading enzyme neprilysin. These findings provide information on the mechanisms underlying the anti-oligomeric effects of HN and HNG and illustrate the role of S14G substitution in regulating the in vivo mechanism of action.
Keywords: Amyloid beta-Peptides; Animals; Animals, Genetically Modified; Caenorhabditis elegans; Caenorhabditis elegans Proteins; Circular Dichroism; Disease Models, Animal; Dose-Response Relationship, Drug; Gene Expression Regulation; Humans; Intracellular Signaling Peptides and Proteins; Microscopy, Atomic Force; Microscopy, Electron, Transmission; Neprilysin; Paralysis; Peptide Fragments; Surface Plasmon Resonance

Low Florbetapir PET Uptake and Normal Aβ1-42 Cerebrospinal Fluid in an APP Ala713Thr Mutation Carrier. - Lombardi, Gemma; Berti, Valentina; Tedde, Andrea; Bagnoli, Silvia; Piaceri, Irene; Polito, Cristina; Lucidi, Giulia; Ferrari, Camilla; Ginestroni, Andrea; Moretti, Marco; Pupi, Alberto; Nacmias, Benedetta; et al. (J Alzheimers Dis, 2017)
According to the literature, the APP Ala713Thr mutation is associated with Alzheimer's disease and cerebral amyloid angiopathy. We describe a case of dementia clinically compatible with frontotemporal dementia in an APP Ala713Thr mutation carrier in which both [18F]Florbetapir PET uptake and Aβ1-42 cerebrospinal fluid levels were normal. Further evidences are required to establish if this association is only incidental.
Keywords: Alanine; Alzheimer Disease; Amyloid beta-Peptides; Amyloid beta-Protein Precursor; Aniline Compounds; Brain; Ethylene Glycols; Humans; Male; Middle Aged; Mutation; Peptide Fragments; Positron-Emission Tomography; Threonine

Modulating the Balance of Synaptic and Extrasynaptic NMDA Receptors Shows Positive Effects against Amyloid-β-Induced Neurotoxicity. - Huang, Yan; Shen, Wei; Su, Jie; Cheng, Bin; Li, Dong; Liu, Gang; Zhou, Wen-Xia; Zhang, Yong-Xiang (J Alzheimers Dis, 2017)
Alzheimer's disease (AD) patients suffer a disturbance in the balance between synaptic (GluN2A, mediating the protective pathway) and extrasynaptic NMDA receptors (NMDARs) (GluN2B, mediating the excitotoxic pathway), and, therefore, restoring the balance of GluN2A and GluN2B should be beneficial for AD. In this study, the GluN2B-selective antagonist, ifenprodil, and the non-selective NMDAR agonist, NMDA, had little effect on amyloid-β (Aβ)-induced long-term potentiation deficits. Enhancing the activity of GluN2A had a protective effect against Aβ, and specific activation of GluN2A and inhibition of GluN2B showed a better protective effect. In Aβ ICV-injected animals, the combination of ifenprodil and D-cycloserine (a co-activator of NMDRs similar to D-serine) led to greater improvement in behavior tests (nest building, novel object recognition, and Morris water maze) than ifenprodil (Morris water maze) or D-cycloserine (nest building) alone. Signal pathway analysis showed that Aβ disturbed the GluN2A/GluN2B-related pathway. The ratio of GluN2A to GluN2B decreased in Aβ-treated animals, and TORC dephosphorylation and ERK1/2 activation, which could be initiated by GluN2A, also decreased in the hippocampal tissues of Aβ-treated animals. As a result, the activation of CREB and the content of brain-derived BDNF decreased. The combination of ifenprodil and D-cycloserine reversed the signal pathway more significantly than ifenprodil or D-cycloserine alone, indicating that Aβ-induced toxicology was mediated both by functionally inhibiting GluN2A and enhancing GluN2B. These results indicate that enhancing synaptic NMDARs and inhibiting extrasynaptic NMDARs concurrently showed protective effects against Aβ-induced neurotoxicity, suggesting that modulation of the balance between GluN2A and GluN2B could be a potential strategy for AD drug development and therapy.
Keywords: Amyloid beta-Peptides; Animals; Antimetabolites; Cycloserine; Disease Models, Animal; Excitatory Amino Acid Antagonists; Excitatory Postsynaptic Potentials; Hippocampus; Locomotion; Male; Maze Learning; N-Methylaspartate; Nesting Behavior; Neurotoxicity Syndromes; Peptide Fragments; Piperidines; Rats; Rats, Wistar; Receptors, N-Methyl-D-Aspartate; Recognition (Psychology); Signal Transduction; Synapses

Palmitate Increases β-site AβPP-Cleavage Enzyme 1 Activity and Amyloid-β Genesis by Evoking Endoplasmic Reticulum Stress and Subsequent C/EBP Homologous Protein Activation. - Marwarha, Gurdeep; Rostad, Stephen; Lilek, Jaclyn; Kleinjan, Mason; Schommer, Jared; Ghribi, Othman (J Alzheimers Dis, 2017)
Epidemiological studies implicate diets rich in saturated free fatty acids (sFFA) as a potential risk factor for developing Alzheimer's disease (AD). In particular, high plasma levels of the sFFA palmitic acid (palmitate) were shown to inversely correlate with cognitive function. However, the cellular mechanisms by which sFFA may increase the risk for AD are not well known. Endoplasmic reticulum (ER) stress has emerged as one of the signaling pathways initiating and fostering the neurodegenerative changes in AD by increasing the aspartyl protease β-site AβPP cleaving enzyme 1 (BACE1) and amyloid-β (Aβ) genesis. In this study, we determined the extent to which palmitate increases BACE1 and Aβ levels in vitro and in vivo as well as the potential role of ER stress as cellular mechanism underlying palmitate effects. We demonstrate, in palmitate-treated SH-SY5Y neuroblastoma cells and in the hippocampi of palmitate-enriched diet-fed mice, that palmitate evokes the activation of the C/EBP Homologous Protein (CHOP), a transcription factor that is specifically responsive to ER stress. Induction of CHOP expression is associated with increased BACE1 mRNA, protein and activity levels, and subsequent enhanced amyloidogenic processing of amyloid-β protein precursor (AβPP) that culminates in a substantial increase in Aβ genesis. We further show that CHOP is an indispensable molecular mediator of palmitate-induced upregulation in BACE1 activity and Aβ genesis. Indeed, we show that Chop-/- mice and CHOP knocked-down SH-SY5Y neuroblastoma cells do not exhibit the same commensurate degree of palmitate-induced increase in BACE1 expression levels and Aβ genesis.
Keywords: Amyloid beta-Peptides; Amyloid beta-Protein Precursor; Amyloid Precursor Protein Secretases; Animals; Aspartic Acid Endopeptidases; Cell Line, Tumor; Dose-Response Relationship, Drug; Endoplasmic Reticulum Stress; Gene Expression Regulation; Hippocampus; Humans; Male; Mice; Mice, Inbred C57BL; Mice, Transgenic; Mutation; Neuroblastoma; Palmitates; RNA, Messenger; Signal Transduction; Transcription Factor CHOP; Transcription Factors; Transfection

PCSK9 Promotes oxLDL-Induced PC12 Cell Apoptosis Through the Bcl-2/Bax-Caspase 9/3 Signaling Pathway. - Liu, Lu-Shan; Bai, Xue-Qin; Gao, Ya; Wu, Qi; Ren, Zhong; Li, Qing; Pan, Li-Hong; He, Ni-Ya; Peng, Juan; Tang, Zhi-Han (J Alzheimers Dis, 2017)
BACKGROUND: Hyperlipidemia is a risk factor for neurodegenerative diseases. Proprotein convertase subtilisin / Kexin type 9 (PCSK9) degrades hepatic low-density lipoprotein receptor (LDLR) to regulate lipid metabolism. It is unclear if PCSK9 plays a role in neurodegenerative diseases. OBJECTIVE: This study was designed to determine whether PCSK9 is crucial between hyperlipidemia and Alzheimer's disease. The interrelationship between PCSK9 and neuronal apoptosis was explored in PC12 cells in response to treatment with oxidized low-density lipoprotein (oxLDL). METHODS: Cultured PC12 cells were serum-starved and incubated with different concentrations of oxLDL for 24 h. Intracytoplasmic lipid droplets were observed by oil red O staining. Morphological assessment of apoptotic cells was performed using Hoechst 33258 staining and flow cytometry analysis. The expression of mRNA and protein was detected by reverse-transcription polymerase chain reaction (RT-PCR) and western blot analyses, respectively. Transfection of small interfering RNA (siRNA) into PC12 cells was conducted using HiperFect Transfection Reagent. Concentrations of Aβ40 and Aβ42 were detected by enzyme-linked immunosorbent assay (ELISA) kit. RESULTS: Intracellular lipid content, the number of apoptotic cells, and PCSK9 expression were increased in PC12 cells after oxLDL treatment. Transfection with PCSK9 siRNA reduced the oxLDL-induced apoptosis of PC12 cells. We further confirmed the involvement of Bcl-2/Bax-Caspase (9, 3) signaling pathway in the regulation of PC12 cells apoptosis.β-Secretase 1, another target gene of PCSK9, was downregulated in PC12 cells in response to oxLDL treatment. Aβ40 and Aβ42 contents were also decreased. CONCLUSION: PCSK9 promotes oxLDL-induced PC12 cell apoptosis through the Bcl-2/Bax-Caspase 9/3 signaling pathway.
Keywords: Amyloid beta-Peptides; Analysis of Variance; Animals; Apoptosis; bcl-2-Associated X Protein; Caspases; Culture Media, Serum-Free; Dose-Response Relationship, Drug; Flow Cytometry; Lipid Metabolism; Lipoproteins, LDL; PC12 Cells; Peptide Fragments; Proprotein Convertase 9; Proto-Oncogene Proteins c-bcl-2; Rats; RNA, Messenger; RNA, Small Interfering; Signal Transduction; Transfection

The Progression of Alzheimer's Disease: Are Fast Decliners Really Fast? A Four-Year Follow-Up. - Barocco, Federica; Spallazzi, Marco; Concari, Letizia; Gardini, Simona; Pelosi, Annalisa; Caffarra, Paolo (J Alzheimers Dis, 2017)
BACKGROUND: The rate of cognitive and functional decline in Alzheimer's disease (AD) changes across individuals. OBJECTIVES: Our purpose was to assess whether the concept of "fast decline" really fits its definition and whether cognitive and functional variables at onset can predict the progression of AD. METHODS: 324 AD patients were included. We retrospectively examined their Mini-Mental State Examination (MMSE) total score and sub-items, Activities of Daily Living (ADL), and Instrumental Activities of Daily Living (IADL) at baseline and every six months for a 4-year follow-up. Patients were divided into "fast decliners" (n = 62), defined by a loss ≥5 points on the MMSE score within the first year from the baseline; "intermediate decliners" (n = 37), by a loss ≥5 points after the first year and before the 18th month; or "slow decliners" (n = 225), composed of the remaining patients. RESULTS: At baseline, the groups did not differ on demographic, clinical, and cognitive variables. The decline at the end of the 4-year follow-up period seems to be similar among the different decline clusters. Predictors of disease progression have not been identified; only the MMSE total score at 12 months <14/30 was indicative of a poor prognosis. CONCLUSIONS: Even with the limitation due to the small sample size, the lack of differences in the disease progression in time in the different clusters suggest the inconsistency of the so-called "fast decliners". This study was unable to show any significant difference among clusters of AD progression within a 4-year time interval. Further studies should better clarify whether a more consistent distinction exists between slow and fast decliners.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Alzheimer Disease; Analysis of Variance; Cognition Disorders; Disease Progression; Female; Humans; Longitudinal Studies; Male; Psychiatric Status Rating Scales; ROC Curve; Time Factors

Role of Suppressor of Cytokine Signaling 3 (SOCS3) in Altering Activated Microglia Phenotype in APPswe/PS1dE9 Mice. - Iwahara, Naotoshi; Hisahara, Shin; Kawamata, Jun; Matsumura, Akihiro; Yokokawa, Kazuki; Saito, Taro; Fujikura, Mai; Manabe, Tatsuo; Suzuki, Hiromi; Matsushita, Takashi; Suzuki, Syuuichirou; Shimohama, Shun (J Alzheimers Dis, 2017)
In response to changes of the central nervous system environment, microglia are capable of acquiring diverse phenotypes for cytotoxic or immune regulation and resolution of injury. Alzheimer's disease (AD) pathology also induces several microglial activations, resulting in production of pro-inflammatory cytokines and reactive oxygen species or clearance of amyloid-β (Aβ) through phagocytosis. We previously demonstrated that microglial activation and increase in oxidative stress started from the middle age in APPswe/PS1dE9 mice, and hypothesized that M1 activation occurs in middle-aged AD mice by Aβ stimulation. In the present study, we analyzed in vivo expressions of pro-inflammatory cytokines (M1 microglial markers), M2 microglial markers, and suppressor of cytokine signaling (SOCS) family, and examined the microglial phenotypic profile in APPswe/PS1dE9 mice. Then we compared the in vitro gene expression patterns of Aβ- and lipopolysaccharide (LPS)-stimulated primary-cultured microglia. Microglia in APPswe/PS1dE9 mice exhibited an M1-like phenotype, expressing tumor necrosis factor α (TNFα) but not interleukin 6 (IL6). Aβ-stimulated primary-cultured microglia also expressed TNFα but not IL6, whereas LPS-stimulated primary-cultured microglia expressed both pro-inflammatory cytokines. Furthermore, both microglia in APPswe/PS1dE9 mice and Aβ-stimulated primary-cultured microglia expressed SOCS3. Reduction of SOCS3 expression in Aβ-challenged primary-cultured microglia resulted in upregulation of IL6 expression. Our findings indicate that SOCS3 suppresses complete polarization to M1 phenotype through blocking IL6 production, and Aβ-challenged primary-cultured microglia replicate the in vivo gene expression pattern of microglia in APPswe/PS1dE9 mice. Aβ may induce the M1-like phenotype through blocking of IL6 by SOCS3.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Amyloid beta-Protein Precursor; Animals; Brain; Cells, Cultured; Disease Models, Animal; Female; Humans; Interleukin-6; Lipopolysaccharides; Male; Mice, Inbred C57BL; Mice, Transgenic; Microglia; Neurons; Presenilin-1; Suppressor of Cytokine Signaling 3 Protein; Tumor Necrosis Factor-alpha

Sleep Deprivation Induced Plasma Amyloid-β Transport Disturbance in Healthy Young Adults. - Wei, Meng; Zhao, Beiyu; Huo, Kang; Deng, Yongning; Shang, Suhang; Liu, Jie; Li, Yanbo; Ma, Louyan; Jiang, Yu; Dang, Liangjun; Chen, Chen; Wei, Shan; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Sleep is an important physiological process and beneficial in the removal of brain metabolites and functional recovery. Prior studies have shown that sleep disorders are significant risk factors for Alzheimer's disease (AD). OBJECTIVE: The present study was designed to characterize the effect of short-term total sleep deprivation (TSD) on plasma amyloid-β (Aβ) concentrations. METHODS: A clinical trial was conducted between March 1, 2016, and April 1, 2016. Twenty volunteers (age 27.3±3.4 years) with normal cognitive function and sleeping habits were recruited from the local population. Participants underwent 24 h of TSD. Periprocedural blood samples were collected to compare the changes of plasma Aβ42, Aβ40, low-density lipoprotein receptor-related protein (sLRP-1), soluble receptors for advanced glycation end products (sRAGE), and serum superoxide dismutase (SOD) and malonaldehyde (MDA). RESULTS: TSD increased morning plasma Aβ40 levels by 32.6% (p < 0.001) and decreased the Aβ42/Aβ40 ratio by 19.3% (p < 0.001). A positive relationship was found between TSD duration and plasma Aβ40 level (r = 0.51, p < 0.001) and Aβ40/Aβ42 ratio (r = 0.25, p = 0.003). Plasma concentrations of sLRP1 (p = 0.018) and sRAGE (p = 0.001) decreased significantly after TSD. Aβ40 and Aβ42 plasma concentrations correlated with plasma levels of sLRP1 and sRAGE. Serum SOD decreased after TSD (p = 0.005), whereas serum MDA was increased (p = 0.001). CONCLUSION: Sleep deprivation can lead to an elevation of plasma Aβ40 and decrease of the Aβ42/Aβ40 ratio. The underlying mechanisms may be related to increased oxidative stress and impaired peripheral Aβ clearance as pathomechanisms of AD.
Keywords: Adult; Amyloid beta-Peptides; Female; Humans; Low Density Lipoprotein Receptor-Related Protein-1; Male; Malondialdehyde; Peptide Fragments; Receptor for Advanced Glycation End Products; Sleep Deprivation; Superoxide Dismutase; Time Factors; Young Adult

Trends, Predictors, and Outcomes of Healthcare Resources Used in Patients Hospitalized with Alzheimer's Disease with at Least One Procedure: The Nationwide Inpatient Sample. - Beydoun, May A; Gamaldo, Alyssa A; Beydoun, Hind A; Shaked, Danielle; Zonderman, Alan B; Eid, Shaker M (J Alzheimers Dis, 2017)
We assessed trends, predictors and outcomes of resource utilization in hospital inpatient discharges with a principal diagnosis of Alzheimer's disease (AD) with at least one procedure. Using Nationwide Inpatient Sample data (NIS, 2002-2012), discharges primarily diagnosed with AD, aged ≥60 y and with ≥1 procedure, were selected (Weighted N = 92,300). Hospital resource utilization were assessed using ICD-9-CM codes, while hospitalization outcomes included total charges (TC, 2012$), length of stay (LOS, days), and mortality risk (MR, %). Brain and respiratory/gastrointestinal procedure utilization both dropped annually by 3-7%, while cardiovascular procedures/evaluations, blood evaluations, blood transfusion, and resuscitation ("CVD/Blood") as well as neurophysiological and psychological evaluation and treatment ("Neuro") procedures increased by 5-8%. Total charges, length of stay, and mortality risk were all markedly higher with use of respiratory/gastrointestinal procedures as opposed to being reduced with use of "Brain" procedures. Procedure count was positively associated with all three hospitalization outcomes. In sum, patterns of hospital resources that were used among AD inpatients changed over-time, and were associated with hospitalization outcomes such as total charges, length of stay, and mortality risk.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Female; Health Resources; Hospitalization; Humans; Inpatients; Length of Stay; Male; Middle Aged; Morbidity; Outcome Assessment (Health Care); Predictive Value of Tests; United States

Triceps and Subscapular Skinfold in Men Aged 40-65 and Dementia Prevalence 36 Years Later. - Ravona-Springer, Ramit; Schnaider-Beeri, Michal; Goldbourt, Uri (J Alzheimers Dis, 2017)
BACKGROUND: The relationship of obesity with risk for dementia is complex and may change with age. OBJECTIVE: To analyze the relationship between measures of obesity at age 40-65 and dementia prevalence in survivors 36 years later. METHODS: Obesity-related measures of triceps and subscapular skinfold thickness were assessed in 1963 in n = 9,760 men aged 40-65 participating in the Israel Ischemic Heart Disease study. Cognitive evaluation and assessment of dementia prevalence were performed in n = 1,643 participants of the original cohort who survived until 1999/2000 (age ≥76 years) and had anthropometric measures in 1963. RESULTS: Age-adjusted prevalence of dementia in survivors in 1999/2000 by baseline triceps skinfold quintile was 20.5%, 21.2%, 17.6%, 15.6%, and 14.5%, respectively, from lowest to highest (p = 0.006 in trend test). Using logistic regression, a 6-mm increment of triceps skinfold was associated with an age and BMI-adjusted odds ratio of 0.81 (95% CI, 0.70-0.94) for dementia prevalence among survivors. Age-adjusted risk for dementia by subscapular skinfold quintile demonstrated 20.5%, 17.1%, 15.7%, 19.4%, and 18.1%, respectively, in groups of subjects by subscapular skinfold quintile from lowest to highest (p = 0.6 in trend test). CONCLUSIONS: Lower triceps skinfold at age 40-65, reflecting diminished peripheral fat, was associated with higher dementia prevalence in late life, potentially suggesting a protective role of peripheral fat to brain health.
Keywords: Adipose Tissue; Aged; Anthropometry; Arm; Body Mass Index; Dementia; Exercise; Humans; Israel; Leisure Activities; Longitudinal Studies; Male; Middle Aged; Muscle, Skeletal; Obesity; Odds Ratio; Prevalence; Shoulder; Skinfold Thickness; Social Class

Accurate Prediction of Conversion to Alzheimer's Disease using Imaging, Genetic, and Neuropsychological Biomarkers. - Dukart, Juergen; Sambataro, Fabio; Bertolino, Alessandro (J Alzheimers Dis, 2016)
A variety of imaging, neuropsychological, and genetic biomarkers have been suggested as potential biomarkers for the identification of mild cognitive impairment (MCI) in patients who later develop Alzheimer's disease (AD). Here, we systematically evaluated the most promising combinations of these biomarkers regarding discrimination between stable and converter MCI and reflection of disease staging. Alzheimer's Disease Neuroimaging Initiative data of AD (n = 144), controls (n = 112), stable (n = 265) and converter (n = 177) MCI, for which apolipoprotein E status, neuropsychological evaluation, and structural, glucose, and amyloid imaging were available, were included in this study. Naïve Bayes classifiers were built on AD and controls data for all possible combinations of these biomarkers, with and without stratification by amyloid status. All classifiers were then applied to the MCI cohorts. We obtained an accuracy of 76% for discrimination between converter and stable MCI with glucose positron emission tomography as a single biomarker. This accuracy increased to about 87% when including further imaging modalities and genetic information. We also identified several biomarker combinations as strong predictors of time to conversion. Use of amyloid validated training data resulted in increased sensitivities and decreased specificities for differentiation between stable and converter MCI when amyloid was included as a biomarker but not for other classifier combinations. Our results indicate that fully independent classifiers built only on AD and controls data and combining imaging, genetic, and/or neuropsychological biomarkers can more reliably discriminate between stable and converter MCI than single modality classifiers. Several biomarker combinations are identified as strongly predictive for the time to conversion to AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Apolipoproteins E; Area Under Curve; Brain; Cognitive Dysfunction; Disease Progression; Female; Fluorodeoxyglucose F18; Follow-Up Studies; Humans; Magnetic Resonance Imaging; Male; Middle Aged; Neuropsychological Tests; Positron-Emission Tomography; Prognosis; Radiopharmaceuticals; ROC Curve; Sensitivity and Specificity

Activation of p53 in Down Syndrome and in the Ts65Dn Mouse Brain is Associated with a Pro-Apoptotic Phenotype. - Tramutola, Antonella; Pupo, Gilda; Di Domenico, Fabio; Barone, Eugenio; Arena, Andrea; Lanzillotta, Chiara; Broekaart, Diede; Blarzino, Carla; Head, Elizabeth; Butterfield, D Allan; Perluigi, Marzia (J Alzheimers Dis, 2016)
Down syndrome (DS) is the most common genetic cause of intellectual disability, resulting from trisomy of chromosome 21. The main feature of DS neuropathology includes early onset of Alzheimer's disease (AD), with deposition of senile plaques and tangles. We hypothesized that apoptosis may be activated in the presence of AD neuropathology in DS, thus we measured proteins associated with upstream and downstream pathways of p53 in the frontal cortex from DS cases with and without AD pathology and from Ts65Dn mice, at different ages. We observed increased acetylation and phosphorylation of p53, coupled to reduced MDM2/p53 complex level and lower levels of SIRT1. Activation of p53 was associated with a number of targets (BAX, PARP1, caspase-3, p21, heat shock proteins, and PGC1α) that were modulated in both DS and DS/AD compared with age-matched controls. In particular, the most relevant changes (increased p-p53 and acetyl-p53 and reduced formation of MDM2/p53 complex) were found to be modified only in the presence of AD pathology in DS. In addition, a similar pattern of alterations in the p53 pathway was found in Ts65Dn mice. These results suggest that p53 may integrate different signals, which can result in a pro-apoptotic-phenotype contributing to AD neuropathology in people with DS.
Keywords: Acetylation; Alzheimer Disease; Animals; Apoptosis; Blotting, Western; Disease Models, Animal; Down Syndrome; Female; Frontal Lobe; Humans; Immunoprecipitation; Male; Mice, Inbred C3H; Mice, Inbred C57BL; Mice, Transgenic; Middle Aged; Phenotype; Phosphorylation; Tumor Suppressor Protein p53; Young Adult

Activities of Daily Living and Depressive Symptoms in Patients with Subjective Cognitive Decline, Mild Cognitive Impairment, and Alzheimer's Disease. - Stogmann, Elisabeth; Moser, Doris; Klug, Stefanie; Gleiss, Andreas; Auff, Eduard; Dal-Bianco, Peter; Pusswald, Gisela; Lehrner, Johann (J Alzheimers Dis, 2016)
BACKGROUND: Subjective cognitive decline (SCD) may be an early indicator for an increased risk of dementia. The exact definition of SCD remains unclear and has recently become a major research interest. OBJECTIVES: To determine impairments in activities of daily living (ADL) and depressive symptoms in elderly individuals with SCD, mild cognitive impairment (MCI), and Alzheimer's disease (AD). METHODS: We included 752 consecutive patients suffering from SCD, non-amnestic (naMCI) or amnestic MCI (aMCI), AD, and 343 healthy controls into this prospective cohort study. A neuropsychological test battery, B-ADL and BDI-II was performed. RESULTS: SCD patients showed a decreased performance in ADL compared to controls. Performance in ADL declined concurrently with cognitive abilities along the controls-SCD-naMCI-aMCI-AD continuum. Individuals with cognitive complains, no matter if SCD, MCI, or AD patients, reported more often depressive symptoms compared to healthy controls without complaints. Within all five cognitive subgroups, patients with depressive symptoms reported more difficulties in ADL in comparison to patients without depressive symptoms. Adjusting for depressive symptoms, there was no significant group difference between the control versus the SCD group (OR 1.1, CI 0.6-1.7). CONCLUSIONS: SCD is a heterogeneous clinical condition. Specific features such as slightly impaired ADL and depressive symptoms are associated with SCD. Clinical markers may serve as an indicator for preclinical AD and in combination with biomarkers guide to an early diagnosis of a progressive neurodegenerative disease.
Keywords: Activities of Daily Living; Aged; Alzheimer Disease; Cognitive Dysfunction; Depression; Female; Humans; Male; Middle Aged; Neuropsychological Tests; Odds Ratio; Perception; Prospective Studies

Age and its association with low insulin and high amyloid-β peptides in blood. - Li, Huajie; Zhu, Haihao; Wallack, Max; Mwamburi, Mkaya; Abdul-Hay, Samer O; Leissring, Malcolm A; Qiu, Wei Qiao (J Alzheimers Dis, 2016)
Age is the major risk factor for developing Alzheimer's disease (AD), and modifying age-related factors may help to delay the onset of the disease. The goal of this study was to investigate the relationship between age and the metabolic factors related to the risk of developing AD. The concentrations of insulin, amylin, and amyloid-β peptide (Aβ) in plasma were measured. We further measured the activity of serum Aβ degradation by using fluorescein- and biotin-labeled Aβ40. Apolipoprotein E4 allele (ApoE4) and cognitive impairment were characterized. Subjects were divided into three age groups: 60-70, 70-80, and ≥80 years old. We found that the older the subjects, the lower the concentration of insulin (p = 0.001) and the higher the concentration of Aβ1-40 (p = 0.004) in plasma. However, age was not associated with the concentration of another pancreatic peptide, amylin, and only marginally with Aβ1-42. These relationships remained in the absence of diabetes, cardiovascular disease, and stroke, and regardless of the presence of ApoE4 and cognitive impairment. Both age and ApoE4 were inversely associated with, while insulin was positively associated with, the activities of Aβ degradation in serum. Our study suggested that low concentration of insulin and high concentration of Aβ40 are aging factors related to the risk of AD.
Keywords: Age Distribution; Aged; Aged, 80 and over; Aging; Alzheimer Disease; Amyloid beta-Peptides; Apolipoprotein E4; Biomarkers; Cognition Disorders; Cross-Sectional Studies; Female; Humans; Insulin; Islet Amyloid Polypeptide; Linear Models; Male; Middle Aged; Multivariate Analysis; Peptide Fragments

Age-Dependent Regulation of the Blood-Brain Barrier Influx/Efflux Equilibrium of Amyloid-β Peptide in a Mouse Model of Alzheimer's Disease (3xTg-AD). - Do, Tuan Minh; Dodacki, Agnès; Alata, Wael; Calon, Frederic; Nicolic, Sophie; Scherrmann, Jean-Michel; Farinotti, Robert; Bourasset, Fanchon (J Alzheimers Dis, 2016)
The involvement of transporters located at the blood-brain barrier (BBB) has been suggested in the control of cerebral Aβ levels, and thereby in Alzheimer's disease (AD). However, little is known about the regulation of these transporters at the BBB in animal models of AD. In this study, we investigated the BBB expression of Aβ influx (Rage) and efflux (Abcb1-Abcg2-Abcg4-Lrp-1) transporters and cholesterol transporter (Abca1) in 3-18-month-old 3xTg-AD and control mice. The age-dependent effect of BBB transporters regulation on the brain uptake clearance (Clup) of [3H]cholesterol and [3H]Aβ1 - 40 was then evaluated in these mice, using the in situ brain perfusion technique. Our data suggest that transgenes expression led to the BBB increase in Aβ influx receptor (Rage) and decrease in efflux receptor (Lrp-1). Our data also indicate that mice have mechanisms counteracting this increased net influx. Indeed, Abcg4 and Abca1 are up regulated in 3- and 3/6-month-old 3xTg-AD mice, respectively. Our data show that the balance between the BBB influx and efflux of Aβ is maintained in 3 and 6-month-old 3xTg-AD mice, suggesting that Abcg4 and Abca1 control the efflux of Aβ through the BBB by a direct (Abcg4) or indirect (Abca1) mechanism. At 18 months, the BBB Aβ efflux is significantly increased in 3xTg-AD mice compared to controls. This could result from the significant up-regulation of both Abcg2 and Abcb1 in 3xTg-AD mice compared to control mice. Thus, age-dependent regulation of several Aβ and cholesterol transporters at the BBB could ultimately limit the brain accumulation of Aβ.
Keywords: Aging; Alzheimer Disease; Amyloid beta-Peptides; Animals; ATP Binding Cassette Transporter, Sub-Family G, Member 1; ATP Binding Cassette Transporter, Sub-Family G, Member 2; ATP-Binding Cassette Transporters; Biological Transport; Blood-Brain Barrier; Brain; Carbon Isotopes; Cholesterol; Disease Models, Animal; Humans; Lipoproteins; Mice; Mice, Transgenic; P-Glycoproteins; Peptide Fragments; Receptors, LDL; Sucrose; Tritium; Tumor Suppressor Proteins

Aging as a Precipitating Factor in Chronic Restraint Stress-Induced Tau Aggregation Pathology, and the Protective Effects of Rosmarinic Acid. - Shan, Ye; Wang, Dan-Dan; Xu, Yu-Xia; Wang, Chu; Cao, Lan; Liu, Yun-Sheng; Zhu, Cui-Qing (J Alzheimers Dis, 2016)
Stress is an important risk factor of Alzheimer's disease (AD). It has been evidenced that stress could induce tau phosphorylation and increase tau insolubility in brain; however, little is known about the interactional effect of stress with aging on tauopathy. Therefore, we explored the effects of aging on stress-induced tauopathy and the potential mechanism in mouse model of chronic restraint stress (CRS). Here we found that in general, the level of phosphorylated tau (P-tau) was higher in brain of middle-aged mice than that in adult mice under physiological conditions. CRS-induced tau phosphorylation and its insolubility were more prominent in middle-aged mice. The increase of AT8-labeled insoluble P-tau was dramatic in middle-aged mice, which was highly ubiquitinated but did not form PHF structures. The levels of chaperones were relatively lower in middle-aged mice brain; CRS further reduced the expression, especially for HDJ2/HSP40. CRS also suppressed the expression of Pin1, the peptidylprolyl cis/trans isomerase, in middle-aged mice but not in adult mice. Downregulation of HSP40 or Pin1 caused an increase of transfected extraneous tau in 293 cells. Rosmarinic acid (RA) could effectively suppress the elevation of P-tau and insoluble P-tau formation induced by CRS, and reversed the abnormal changes of chaperones and Pin1 particularly in middle-aged mice. Taken together, our findings provided evidence that aging could be a promoting factor in stress-induced tauopathy, which was relevant with malregulation of chaperones and Pin1, and RA might be a promising beneficial agent for stress-induced tauopathy.
Keywords: Aging; Animals; Antioxidants; Brain; Cinnamates; Corticotropin-Releasing Hormone; Depsides; Disease Models, Animal; HEK293 Cells; HSP90 Heat-Shock Proteins; Humans; Male; Mice; Mice, Inbred C57BL; Microscopy, Immunoelectron; NIMA-Interacting Peptidylprolyl Isomerase; Peptidylprolyl Isomerase; Phosphorylation; Precipitating Factors; Receptors, Corticotropin; Restraint, Physical; Stress, Psychological; tau Proteins; Transfection

Alterations in the Levels of Amyloid-β, Phospholipid Hydroperoxide, and Plasmalogen in the Blood of Patients with Alzheimer's Disease: Possible Interactions between Amyloid-β and These Lipids. - Yamashita, Shinji; Kiko, Takehiro; Fujiwara, Hironori; Hashimoto, Michio; Nakagawa, Kiyotaka; Kinoshita, Mikio; Furukawa, Katsutoshi; Arai, Hiroyuki; Miyazawa, Teruo (J Alzheimers Dis, 2016)
Aside from accumulation of amyloid-β (Aβ) peptide in the brain, Alzheimer's disease (AD) has been reported as being associated with peroxidation of major phospholipids (e.g., phosphatidylcholine (PtdCho)) and degradation of antioxidative phospholipids (e.g., ethanolamine plasmalogen (PlsEtn)). In addition to its presence in the brain, Aβ is also found in blood; however, there is still little information about the levels of PtdCho hydroperoxide (PCOOH) and PlsEtn in the blood of patients with AD. In this study, by assuming a possible interaction among Aβ, PCOOH, and PlsEtn in blood circulation, we evaluated the levels of these molecules and correlations in blood samples that had been obtained from our former AD study for PCOOH measurement (Kiko et al., J Alzheimers Dis28, 593-600, 2012). We found that when compared to controls, plasma from patients with AD showed lower concentrations of PlsEtn species, especially PlsEtn bearing the docosahexaenoic acid (DHA) moiety. In addition, lower PlsEtn and higher PCOOH levels were observed in red blood cells (RBCs) of patients with AD. In both AD and control blood samples, RBC PCOOH levels tended to correlate with plasma levels of Aβ40, and each PlsEtn species showed different correlations with plasma Aβ. These results, together with in vitro data suggesting Aβ aggregation due to a decrease in levels of PlsEtn having DHA, led us to deduce that Aβ is involved in alterations in levels of PCOOH and PlsEtn species observed in the blood of patients with AD.
Keywords: Aged; Amyloid beta-Peptides; Female; Humans; Hydrogen Peroxide; Male; Phosphatidylcholines; Plasmalogens

Altered Affective Evaluations of Smells in Alzheimer's Disease. - Joussain, Pauline; Bessy, Marion; Fournel, Arnaud; Ferdenzi, Camille; Rouby, Catherine; Delphin-Combe, Floriane; Krolak-Salmon, Pierre; Bensafi, Moustafa (J Alzheimers Dis, 2016)
BACKGROUND: Studies of olfaction in Alzheimer's disease (AD) mainly focused on deficits in odor detection and identification, with very few investigations of olfactory emotional changes and their consequences for hedonics. OBJECTIVE: The aim of the present study was to characterize affective evaluations of odors in AD patients. METHODS: To this end, 20 AD patients and 20 matched controls were tested. Participants were screened for odor detection and identification ability and then asked to rate the intensity, pleasantness, and edibility of 20 odorants. RESULTS: Results showed that, overall, AD patients had lower detection ability and perceived all odors as weaker than controls. As expected, they had lower identification ability on both cued and non-cued tasks. In addition, when smelling pleasant odors, patients had significantly lower hedonic ratings than controls (p <  0.02), whereas no group difference was found for neutral or unpleasant odors (p >  0.05 in both cases). Moreover, an analysis combining both intensity and pleasantness ratings showed that whereas intensity increased as a function of pleasantness and unpleasantness in controls, this quadratic relationship was not observed in AD patients. CONCLUSIONS: The study suggests that the simplest categorization criteria of odors (intensity and hedonic valence) are impaired in AD patients (especially for pleasant odors).
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Analysis of Variance; Case-Control Studies; Emotions; Female; Humans; Male; Mood Disorders; Odorants; Olfaction Disorders; Psychiatric Status Rating Scales; Smell; Surveys and Questionnaires

Altered sense of humor in dementia. - Clark, Camilla N; Nicholas, Jennifer M; Gordon, Elizabeth; Golden, Hannah L; Cohen, Miriam H; Woodward, Felix J; Macpherson, Kirsty; Slattery, Catherine F; Mummery, Catherine J; Schott, Jonathan M; Rohrer, Jonathan D; Warren, Jason D (J Alzheimers Dis, 2016)
Sense of humor is potentially relevant to social functioning in dementias, but has been little studied in these diseases. We designed a semi-structured informant questionnaire to assess humor behavior and preferences in patients with behavioral variant frontotemporal dementia (bvFTD; n = 15), semantic dementia (SD; n = 7), progressive nonfluent aphasia (PNFA; n = 10), and Alzheimer's disease (AD; n = 16) versus healthy age-matched individuals (n = 21). Altered (including frankly inappropriate) humor responses were significantly more frequent in bvFTD and SD (all patients) than PNFA or AD (around 40% of patients). All patient groups liked satirical and absurdist comedy significantly less than did healthy controls. This pattern was reported premorbidly for satirical comedy in bvFTD, PNFA, and AD. Liking for slapstick comedy did not differ between groups. Altered sense of humor is particularly salient in bvFTD and SD, but also frequent in AD and PNFA. Humor may be a sensitive probe of social cognitive impairment in dementia, with diagnostic, biomarker and social implications.
Keywords: Aged; Alzheimer Disease; Case-Control Studies; Cognition Disorders; Emotions; Female; Frontotemporal Dementia; Humans; Male; Middle Aged; Neuropsychological Tests; Primary Progressive Nonfluent Aphasia; Psychiatric Status Rating Scales; Surveys and Questionnaires

Anemia and Mild Cognitive Impairment in the German General Population. - Dlugaj, Martha; Winkler, Angela; Weimar, Christian; Dürig, Jan; Broecker-Preuss, Martina; Dragano, Nico; Moebus, Susanne; Jöckel, Karl-Heinz; Erbel, Raimund; Eisele, Lewin (J Alzheimers Dis, 2016)
There is increasing evidence that anemia is associated with cognitive impairment. Therefore, the aim of the study was to examine the cross-sectional association of anemia as well as the persistence of anemia over the last five years with mild cognitive impairment (MCI) and MCI subtypes (amnestic/non-amnestic MCI (aMCI/naMCI)). Out of 4,157 participants (50% men, 50-80 years) of the second examination (t1) of a cohort study (baseline (t0) 2000-2003), we included 4,033 participants with available hemoglobin information and complete cognitive assessment. Anemia was defined as hemoglobin <13 g/dl in men (n = 84) and <12 g/dl in women (n = 79). Group comparisons were used to compare the cognitive subtests. To determine the association of MCI with anemia at t1, with anemia five years prior to the cognitive assessment (t0) and anemia at both time points, we used logistic regression models and included 579 participants with MCI and 1,438 cognitively normal participants out of the total cohort. Anemic participants showed lower performances in verbal memory and executive functions. The fully adjusted odds ratios (OR) for MCI, aMCI, and naMCI in anemic versus non-anemic participants were 1.92 (95% -CI, 1.09-3.39), 1.96 (1.00-3.87), and 1.88 (0.91-3.87). Anemia at both times points showed a non-significant association with naMCI (OR 3.74, 0.94-14.81, fully adjusted). Our results suggest that anemia is associated with an increased risk of MCI independent of traditional cardiovascular risk factors. The association of anemia and MCI has important clinical relevance, because many causes of anemia can be treated effectively.
Keywords: Aged; Aged, 80 and over; Anemia; Cognitive Dysfunction; Cohort Studies; Executive Function; Female; Follow-Up Studies; Germany; Humans; Male; Memory; Middle Aged; Neuropsychological Tests; Prevalence; Speech Perception

Anti-Correlated Cerebrospinal Fluid Biomarker Trajectories in Preclinical Alzheimer's Disease. - Gomar, Jesus J; Conejero-Goldberg, Concepcion; Davies, Peter; Goldberg, Terry E (J Alzheimers Dis, 2016)
BACKGROUND: The earliest stage of preclinical Alzheimer's disease (AD) is defined by low levels of cerebrospinal fluid (CSF) amyloid-β (Aβ42). However, covariance in longitudinal dynamic change of Aβ42 and tau in incipient preclinical AD is poorly understood. OBJECTIVE: To examine dynamic interrelationships between Aβ42 and tau in preclinical AD. METHODS: We followed 47 cognitively intact participants (CI) with available CSF data over four years in ADNI. Based on longitudinal Aβ42 levels in CSF, CI were classified into three groups: 1) Aβ42 stable with normal levels of Aβ42 over time (n = 15); 2) Aβ42 declining with normal Aβ42 levels at baseline but showing decline over time (n = 14); and 3) Aβ42 levels consistently abnormal (n = 18). RESULTS: In the Aβ42 declining group, suggestive of incipient preclinical AD, CSF phosphorylated tau (p-tau) showed a similar longitudinal pattern of increasing abnormality over time (p = 0.0001). Correlation between longitudinal slopes of Aβ42 and p-tau confirmed that both trajectories were anti-correlated (rho = -0.60; p = 0.02). Regression analysis showed that Aβ42 slope (decreasing Aβ42) predicted p-tau slope (increasing p-tau) (R2 = 0.47, p = 0.03). Atrophy in the hippocampus was predicted by the interaction of Aβ42 and p-tau slopes (p <  0.0001) only in this incipient preclinical AD group. In all groups combined, memory decline was predicted by p-tau. CONCLUSIONS: The evolution of Aβ42 and p-tau CSF biomarkers in CI subjects follows an anti-correlated trajectory, i.e., as Aβ42 declined, p-tau increased, and thus was suggestive of strong temporal coincidence. Rapid pathogenic cross-talk between Aβ42 and p-tau thus may be evident in very early stages of preclinical AD.
Keywords: Adult; Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Atrophy; Brain; Disease Progression; Female; Humans; Longitudinal Studies; Magnetic Resonance Imaging; Male; Middle Aged; Neuropsychological Tests; Peptide Fragments; Prodromal Symptoms; Regression Analysis; Statistics, Nonparametric; tau Proteins

Apathy and Attentional Biases in Alzheimer's Disease. - Chau, Sarah A; Chung, Jonathan; Herrmann, Nathan; Eizenman, Moshe; Lanctôt, Krista L (J Alzheimers Dis, 2016)
BACKGROUND: Apathy, one of the most prevalent neuropsychiatric symptoms in Alzheimer's disease (AD), can be difficult to assess as cognition deteriorates. There is a need for more objective assessments that do not rely on patient insight, communicative capacities, or caregiver observation. OBJECTIVE: We measured visual scanning behavior, using an eye-tracker, to explore attentional bias in the presence of competing stimuli to assess apathy in AD patients. METHODS: Mild-to-moderate AD patients (Standardized Mini-Mental Status Examination, sMMSE >10) were assessed for apathy (Neuropsychiatric Inventory [NPI] apathy, Apathy Evaluation Scale [AES]). Participants were presented with 16 slides, each containing 4 images of different emotional themes (2 neutral, 1 social, 1 dysphoric). The duration of time spent, and fixation frequency on images were measured. RESULTS: Of the 36 AD patients (14 females, age = 78.2±7.8, sMMSE = 22.4±3.5) included, 17 had significant apathy (based on NPI apathy ≥4) and 19 did not. These groups had comparable age and sMMSE. Repeated-measures analysis of covariance models, controlling for total NPI, showed group (apathetic versus non-apathetic) by image (social versus dysphoric) interactions for duration (F(1,32) = 4.31, p = 0.046) and fixation frequency (F(1,32) = 11.34, p = 0.002). Apathetic patients demonstrated reduced duration and fixation frequency on social images compared with non-apathetic patients. Additionally, linear regression models suggest that more severe apathy predicted decreasing fixation frequency on social images (R2 = 0.26, Adjusted R2 = 0.19, F(3,32) = 3.65, p = 0.023). CONCLUSION: These results suggest that diminished attentional bias toward social-themed stimuli is a marker of apathy in AD. Measurements of visual scanning behavior may have the potential to predict and monitor treatment response in apathy.
Keywords: Aged; Alzheimer Disease; Apathy; Attentional Bias; Cognition; Cross-Sectional Studies; Emotions; Eye Movement Measurements; Eye Movements; Female; Humans; Linear Models; Male; Neuropsychological Tests; Photic Stimulation; Severity of Illness Index; Social Perception

Apolipoprotein E Related Co-Morbidities and Alzheimer's Disease. - Singhrao, Sim K; Harding, Alice; Chukkapalli, Sasanka; Olsen, Ingar; Kesavalu, Lakshmyya; Crean, StJohn (J Alzheimers Dis, 2016)
The primary goal of advancement in clinical services is to provide a health care system that enhances an individual's quality of life. Incidence of diabetes mellitus, cardiovascular disease, and associated dementia coupled with the advancing age of the population, have led to an increase in the worldwide challenge to the healthcare system. In order to overcome these challenges, prior knowledge of common, reliable risk factors and their effectors is essential. Oral health constitutes one such relatively unexplored but indispensable risk factor for aforementioned co-morbidities, in the form of poor oral hygiene and tooth loss during aging. Behavioral traits such as low education, smoking, poor diet, neglect of oral health, lack of exercise, and hypertension are few of the risk factors that are shared commonly among these conditions. In addition, common genetic susceptibility traits such as the apolipoprotein E gene, together with an individual's lifestyle can also influence the development of co-morbidities such as periodontitis, atherosclerosis/stroke, diabetes, and Alzheimer's disease. This review specifically addresses the susceptibility of apolipoprotein E gene allele 4 as the plausible commonality for the etiology of co-morbidities that eventually result from periodontal diseases and ultimately progress to dementia.
Keywords: Aging; Alzheimer Disease; Animals; Apolipoprotein E4; Cardiovascular Diseases; Comorbidity; Diabetes Mellitus, Type 2; Humans; Mice; Periodontal Diseases

Apolipoprotein ɛ4 is Associated with Dementia and Cognitive Impairment Predominantly Due to Alzheimer's Disease and Not with Vascular Cognitive Impairment: A Singapore-Based Cohort. - Chai, Yuek Ling; Yeo, Hazel Kai-Hui; Wang, Jiehao; Hilal, Saima; Ikram, Mohammad Kamran; Venketasubramanian, Narayanaswamy; Wong, Boon-Seng; Chen, Christopher Li-Hsian (J Alzheimers Dis, 2016)
BACKGROUND AND OBJECTIVE: While the association for apolipoprotein ɛ4 allele (APOE4) with Alzheimer's disease (AD) has been consistently confirmed, the association with vascular cognitive impairment (VCI) is unclear. We therefore explored the relationship of APOE with both AD and cerebrovascular disease (CeVD) by examining the prevalence of APOE4 in AD, AD with CeVD and vascular dementia (VaD), as well as in cognitive impairment no dementia (CIND) with and without CeVD. METHODS: We performed a case-control study with subjects recruited from memory clinics and the community. All subjects underwent standardized brain neuroimaging, clinical and neuropsychological assessments, following which they were classified using research criteria. RESULTS: A total of 411 subjects; 92 controls with no cognitive impairment (NCI), 77 CIND without CeVD, 87 CIND with CeVD, 55 AD without CeVD, 68 AD with CeVD, and 32 VaD patients were recruited. Compared to NCI (16.3%), the prevalence of APOE4 carriers was significantly higher only in CIND (37.7%) and AD in the absence of CeVD (45.5%), but not in the three subgroups of VCI, namely CIND with CeVD (20.7%), AD with CeVD (27.9%) and VaD (25.0%). Logistic regression analyses also showed that APOE4 carriers were more likely to have CIND without CeVD (Odds Ratio [OR]: 3.34; 95% Confidence Interval [CI]: 1.59-7.03) and AD without CeVD (OR: 7.21; 95% CI: 2.74-18.98), but no such association was observed in the VCI subgroups. CONCLUSION: APOE4 is significantly associated with dementia and CIND due to AD pathology, but not with VCI.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Analysis of Variance; Apolipoprotein E4; Cognition Disorders; Cohort Studies; Dementia; Female; Genetic Association Studies; Genotype; Humans; Male; Middle Aged; Neuroimaging; Neuropsychological Tests; Psychiatric Status Rating Scales; Singapore; Vascular Diseases

Application of the IWG-2 Diagnostic Criteria for Alzheimer's Disease to the ADNI. - Wang, Hui-Fu; Tan, Lan; Cao, Lei; Zhu, Xi-Chen; Jiang, Teng; Tan, Meng-Shan; Liu, Ying; Wang, Chong; Tsai, Richard M; Jia, Jian-Ping; Yu, Jin-Tai (J Alzheimers Dis, 2016)
BACKGROUND: The International Working Group (IWG) recently proposed the revised diagnostic criteria for Alzheimer's disease (AD) to define and refine several types of AD, and to reclassify AD-related biomarkers into diagnostic and progression markers, but its performance is not known. OBJECTIVE: This study was designed to describe the application of the revised IWG criteria in the Alzheimer's Disease Neuroimaging Initiative (ADNI) dataset, and to ascertain whether diagnostic and progression markers show significant differences in their relationships to AD severity and progression. METHODS: Based on the requirements of the refined criteria, 857 ADNI subjects with memory evaluation and at least one pathophysiological marker (CSF or amyloid imaging biomarkers) were eligible and reclassified in this study, and we calculated the associations of diagnostic (CSF and amyloid PET) and progression markers (MRI and fluorodeoxyglucose-PET) with AD severity and progression respectively. RESULTS: The majority (84.2% ) of ADNI AD group (n = 117) and 173 MCI (37.4% ) subjects in ADNI met the definition of typical AD; and 105 cognitively normal (41.0% ) individuals were diagnosed as asymptomatic AD. Furthermore, diagnostic and progression markers showed significant differences when correlated to AD severity and progression. CONCLUSION: A large proportion of AD dementia subjects were categorized as typical AD, and the revised criteria could identify typical AD from MCI status as well as asymptomatic AD at the asymptomatic stage. Moreover, the significant differences between diagnostic and progression markers further supported the new biomarkers categorization in the refined criteria.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid Precursor Protein Secretases; Aspartic Acid Endopeptidases; Cognitive Dysfunction; Databases, Factual; Disease Progression; Female; Humans; Longitudinal Studies; Male; Multicenter Studies as Topic; Neuroimaging; Psychiatric Status Rating Scales; tau Proteins

Association between Coffee Consumption and Incident Risk of Disabling Dementia in Elderly Japanese: The Ohsaki Cohort 2006 Study. - Sugiyama, Kemmyo; Tomata, Yasutake; Kaiho, Yu; Honkura, Kenji; Sugawara, Yumi; Tsuji, Ichiro (J Alzheimers Dis, 2016)
Epidemiological studies of the association between coffee consumption and dementia have yielded inconsistent results. Therefore, we investigated the association between coffee consumption and incident risk of dementia in an elderly Japanese population. 23,091 subjects aged ≥65 y living in Ohsaki City, northeastern Japan, responded to the baseline survey in 2006. Of these, we analyzed 13,137 subjects who gave informed consent and were not disabled at baseline. The outcome was the incidence of disabling dementia defined by usage of the Long-term Care Insurance database. We used the Cox proportional hazards regression model for multivariate analysis. During 5.7 y of follow-up period, we identified 1,107 cases of incident dementia. Overall, coffee consumption was significantly associated with a lower risk of incident dementia. The multivariate-adjusted HRs for the incidence of dementia according to coffee consumption categories (never, occasionally, 1-2 cups/d, and ≥3 cups/d) were 1.00, 0.73 (95% CI, 0.62-0.86), 0.72 (95% CI, 0.61-0.84), and 0.82 (95% CI, 0.65-1.02; p for trend = 0.009), respectively. In addition, this significant inverse association was more remarkable among women, non-smokers, and non-drinkers. Coffee consumption is significantly associated with a lower risk of incident dementia.
Keywords: Aged; Aged, 80 and over; Coffee; Dementia; Female; Health Surveys; Humans; Incidence; Japan; Male; Prospective Studies; Risk Factors

Association Between Serum Ceruloplasmin Specific Activity and Risk of Alzheimer's Disease. - Siotto, Mariacristina; Simonelli, Ilaria; Pasqualetti, Patrizio; Mariani, Stefania; Caprara, Deborah; Bucossi, Serena; Ventriglia, Mariacarla; Molinario, Rossana; Antenucci, Mirca; Rongioletti, Mauro; Rossini, Paolo Maria; Squitti, Rosanna (J Alzheimers Dis, 2016)
Meta-analyses demonstrate copper involvement in Alzheimer's disease (AD), and the systemic ceruloplasmin status in relation to copper is an emerging issue. To deepen this matter, we evaluated levels of ceruloplasmin concentration, ceruloplasmin activity, ceruloplasmin specific activity (eCp/iCp), copper, non-ceruloplasmin copper iron, transferrin, the ceruloplasmin/transferrin ratio, and the APOE genotype in a sample of 84 AD patients and 58 healthy volunteers. From the univariate logistic analyses we found that ceruloplasmin concentration, eCp/iCp, copper, transferrin, the ceruloplasmin/transferrin ratio, and the APOE genotype were significantly associated with the probability of AD. In the multivariable logistic regression analysis, we selected the best subset of biological predictors by the forward stepwise procedure. The analysis showed a decrease of the risk of having AD for eCp/iCp (p = 0.001) and an increase of this risk for non-ceruloplasmin copper (p = 0.008), age (p = 0.001), and APOE-ɛ4 allele (p <  0.001). The estimated model showed a good power in discriminating AD patients from healthy controls (area under curve: 88% ; sensitivity: 66% ; specificity 93%). These data strength the breakdown of copper homeostasis and propose eCp/iCp as a reliable marker of ceruloplasmin status.
Keywords: Aged; Alzheimer Disease; Apolipoprotein E4; Area Under Curve; Biomarkers; Blood Chemical Analysis; Ceruloplasmin; Copper; Female; Genotype; Genotyping Techniques; Humans; Logistic Models; Male; Multivariate Analysis; Prognosis; Risk; ROC Curve; Sensitivity and Specificity; Transferrin

Association of Frontotemporal Dementia GWAS Loci with Late-Onset Alzheimer's Disease in a Northern Han Chinese Population. - Tan, Chen-Chen; Wan, Yu; Tan, Meng-Shan; Zhang, Wei; Wang, Zi-Xuan; Sun, Fu-Rong; Miao, Dan; Tan, Lan; Yu, Jin-Tai (J Alzheimers Dis, 2016)
BACKGROUND: Both Alzheimer's disease (AD) and frontotemporal dementia (FTD) are a class of neurodegenerative diseases. Strong similarities in cerebrospinal fluid biomarker, imaging markers, and disease progression profiles suggest that some or most of the pathophysiology is shared between AD and FTD. A recent large genome-wide association study reported several single nucleotide polymorphisms (SNPs) at the RAB38, RAB38/CTSC, HLA-DRA/HLA-DRB5, and BTNL2 in association with FTD. OBJECTIVE: To explore whether these SNPs are associated with AD risk. METHODS: We conducted a case-control study to investigate the association of FTD-associated loci in 2338 Han Chinese subjects. RESULTS: We observed significant differences in genotype distributions of rs302668 (pc = 0.025), rs9268877 (pc = 0.025), rs9268856 (p <  0.001), and rs1980493 (pc = 0.045) between cases and controls. The SNPs rs16913634 for RAB38/CTSC was unrelated to LOAD risk (p = 0.088). CONCLUSION: The SNPs rs302668 in RAB38, rs9268877 and rs9268856 polymorphism in HLA-DRA/HLA-DRB5, and rs1980493 polymorphism in BTNL2 might play a role in the susceptibility to late-onset AD in the Han Chinese population.
Keywords: Age of Onset; Aged; Alzheimer Disease; Apolipoprotein E4; Asian Continental Ancestry Group; Case-Control Studies; China; Female; Frontotemporal Dementia; Gene Frequency; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Genotyping Techniques; Humans; Linkage Disequilibrium; Male; Mental Status Schedule; Polymorphism, Single Nucleotide

Associations between Neuropsychiatric Symptoms and Cerebral Amyloid Deposition in Cognitively Impaired Elderly People. - Bensamoun, David; Guignard, Renaud; Furst, Ansgar J; Derreumaux, Alexandre; Manera, Valeria; Darcourt, Jacques; Benoit, Michel; Robert, Philippe H; David, Renaud (J Alzheimers Dis, 2016)
BACKGROUND: Neuropsychiatric symptoms, also known as behavioral and psychological symptoms of dementia (BPSD), affect the majority of patients with dementia, and result in a greater cognitive and functional impairment. OBJECTIVE: To investigate associations between BPSD and amyloid cerebral deposition as measured by 18F-Florbetapir-PET quantitative uptake in elderly subjects with and without cognitive impairment. METHODS: Participants with cognitive impairment [mild cognitive impairment (MCI) or Alzheimer's disease (AD)] and healthy controls (HC) from the ADNI cohort (Alzheimer Disease Neuroimaging Initiative) who underwent an 18F-florbetapir PET scan between May 2010 and March 2014 were included. Clinical assessments included the Clinical Dementia Rating, the Mini-Mental State Examination (MMSE), and the Neuropsychiatric Inventory. Freesurfer software was used to extract PET counts based on T1-based structural ROI (frontal, cingulate, parietal, and temporal). Spearman's partial correlation scores between BPSD severity and regional amyloid uptake were calculated. RESULTS: Data for 657 participants [age = 72.6 (7.19); MMSE = 27.4 (2.67)] were analyzed, including 230 HC [age = 73.1 (6.02); MMSE = 29 (1.21)], 308 MCI [age = 71.5 (7.44); MMSE = 28.0 (1.75)], and 119 AD subjects [age = 74.7 (8.05); MMSE = 23.1 (2.08)]. Considering all diagnostic groups together, positive significant correlations were found between anxiety and 18F-florbetapir uptake in the frontal (r = 0.102; p = 0.009), cingulate (r = 0.083; p = 0.034), and global cerebral uptake (r = 0.099; p = 0.011); between irritability and frontal (r = 0.089; p = 0.023), cingulate (r = 0.085; p = 0.030), parietal (r = 0.087; p = 0.025), and global cerebral uptake (r = 0.093; p = 0.017); in the MCI subgroup, between anxiety and frontal (r = 0.126; p = 0.03) and global uptake (r = 0.14; p = 0.013); in the AD subgroup, between irritability and parietal uptake (r = 0.201; p = 0.03). CONCLUSION: Anxiety and irritability are associated with greater amyloid deposition in the neurodegenerative process leading to AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloidogenic Proteins; Cerebral Cortex; Cognition Disorders; Cohort Studies; Female; Fluorodeoxyglucose F18; Humans; Male; Mental Status Schedule; Mood Disorders; Neuropsychological Tests; Positron-Emission Tomography

Associations between Serum Omega-3 Fatty Acid Levels and Cognitive Functions among Community-Dwelling Octogenarians in Okinawa, Japan: The KOCOA Study. - Nishihira, Junko; Tokashiki, Takashi; Higashiuesato, Yasushi; Willcox, Donald Craig; Mattek, Nora; Shinto, Lynne; Ohya, Yusuke; Dodge, Hiroko H (J Alzheimers Dis, 2016)
BACKGROUND: Epidemiological studies have found frequent consumption of fatty fish is protective against cognitive decline. However, the association between circulating omega-3 polyunsaturated fatty acid (PUFA) levels and cognitive functions among the oldest old is not well known. OBJECTIVE: To examine the association between serum PUFA levels and cognitive function among community-dwelling, non-demented elderly aged over 80 years old. METHODS: The data came from the Keys to Optimal Cognitive Aging (KOCOA) study; an ongoing cohort of relatively healthy volunteers aged over 80 years old, living in Okinawa, Japan. One hundred eighty five participants (mean age 84.1±3.4 years) assessed in 2011 who were free from frank dementia (defined as Clinical Dementia Rating <1.0) were used for the current cross-sectional study. We examined whether serum omega-3 PUFAs (docosahexaenoic acid [DHA] and eicosapentaenoic acid [EPA]), arachidonic acid (AA), EPA/AA ratio, DHA/AA ratio, and DHA+EPA are associated with (1) age and (2) global cognitive function (Japanese MMSE) and executive function (Verbal Fluency Letter). Data was analyzed univariately by t-test and multivariately by cumulative logistic regression models controlling for age, gender, years of education, obesity, hypertension, diabetes, and dyslipidemia. RESULTS: Serum DHA levels decreased with increasing age (p = 0.04). Higher global cognitive function was associated with higher levels of serum EPA (p = 0.03) and DHA + EPA (p = 0.03) after controlling for confounders. CONCLUSIONS: Higher serum EPA and DHA + EPA levels were independently associated with better scores on global cognitive function among the oldest old, free from dementia. Longitudinal follow-up studies are warranted.
Keywords: Age Factors; Aged, 80 and over; Arachidonic Acid; Blood Chemical Analysis; Cognition; Cross-Sectional Studies; Educational Status; Fatty Acids, Omega-3; Female; Humans; Japan; Logistic Models; Male; Mental Status Schedule; Obesity; Prospective Studies; Sex Factors

Astrocytes release HspB1 in response to amyloid-β exposure in vitro. - Nafar, Firoozeh; Williams, J Bradley; Mearow, Karen M (J Alzheimers Dis, 2016)
Although heat shock proteins are thought to function primarily as intracellular chaperones, the release and potential extracellular functions of heat shock proteins have been the focus of an increasing number of studies. Our particular interest is HspB1 (Hsp25/27) and as astrocytes are an in vivo source of HspB1 it is a reasonable possibility they could release HspB1 in response to local stresses. Using primary cultures of rat cortical astrocytes, we investigated the extracellular release of HspB1 with exposure to amyloid-β (Aβ). In order to assess potential mechanisms of release, we cotreated the cells with compounds that can modulate protein secretion including Brefeldin A, Methyl β-cyclodextrin, and MAP kinase inhibitors. Exposure to Aβ (0.1, 1.0, 2.0 μM) for 24-48 h resulted in a selective release of HspB1 that was insensitive to BFA treatment; none of the other inhibitors had any detectable influence. Protease protection assays indicated that some of the released HspB1 was associated with a membrane bound fraction, and analysis of exosomal preparations indicated the presence of HspB1 in exosomes. Finally, immunoprecipitation experiments demonstrated that the extracellular HspB1 was able to interact with extracellular Aβ. In summary, Aβ can stimulate release of HspB1 from astrocytes, this release is insensitive to Golgi or lipid raft disruption, and HspB1 can be found either free in the medium or associated with exosomes. This release suggests that there is a potential for extracellular HspB1 to be able to bind and sequester extracellular Aβ.
Keywords: Amyloid beta-Peptides; Animals; Astrocytes; Cells, Cultured; HSP27 Heat-Shock Proteins; Protein Transport; Rats

AZD3293: A Novel, Orally Active BACE1 Inhibitor with High Potency and Permeability and Markedly Slow Off-Rate Kinetics. - Eketjäll, Susanna; Janson, Juliette; Kaspersson, Karin; Bogstedt, Anna; Jeppsson, Fredrik; Fälting, Johanna; Haeberlein, Samantha Budd; Kugler, Alan R; Alexander, Robert C; Cebers, Gvido (J Alzheimers Dis, 2016)
A growing body of pathological, biomarker, genetic, and mechanistic data suggests that amyloid accumulation, as a result of changes in production, processing, and/or clearance of brain amyloid-β peptide (Aβ) concentrations, plays a key role in the pathogenesis of Alzheimer's disease (AD). Beta-secretase 1 (BACE1) mediates the first step in the processing of amyloid-β protein precursor (AβPP) to Aβ peptides, with the soluble N terminal fragment of AβPP (sAβPPβ) as a direct product, and BACE1 inhibition is an attractive target for therapeutic intervention to reduce the production of Aβ. Here, we report the in vitro and in vivo pharmacological profile of AZD3293, a potent, highly permeable, orally active, blood-brain barrier (BBB) penetrating, BACE1 inhibitor with unique slow off-rate kinetics. The in vitro potency of AZD3293 was demonstrated in several cellular models, including primary cortical neurons. In vivo in mice, guinea pigs, and dogs, AZD3293 displayed significant dose- and time-dependent reductions in plasma, cerebrospinal fluid, and brain concentrations of Aβ40, Aβ42, and sAβPPβ. The in vitro potency of AZD3293 in mouse and guinea pig primary cortical neuronal cells was correlated to the in vivo potency expressed as free AZD3293 concentrations in mouse and guinea pig brains. In mice and dogs, the slow off-rate from BACE1 may have translated into a prolongation of the observed effect beyond the turnover rate of Aβ. The preclinical data strongly support the clinical development of AZD3293, and patients with AD are currently being recruited into a combined Phase 2/3 study to test the disease-modifying properties of AZD3293.
Keywords: Administration, Oral; Amyloid beta-Peptides; Amyloid Precursor Protein Secretases; Animals; Blood Chemical Analysis; Blood-Brain Barrier; Brain; Dogs; Dose-Response Relationship, Drug; Drug Evaluation, Preclinical; Enzyme Inhibitors; Female; Guinea Pigs; Humans; Imidazoles; Kinetics; Male; Mice, Inbred C57BL; Peptide Fragments; Spiro Compounds

Beneficial Effects of an Integrated Psychostimulation Program in Patients with Alzheimer's Disease. - Ibarria, Marta; Alegret, Montserrat; Valero, Sergi; Morera, Amèrica; Guitart, Marina; Cañabate, Pilar; Moreno, Mariola; Lara, Susana; Diego, Susana; Hernández, Joan; Tantinyá, Natàlia; Vera, Maribel; et al. (J Alzheimers Dis, 2016)
BACKGROUND: The existing pharmacological treatments for Alzheimer's disease (AD) can only slow the progression of symptoms or delay admission to long-term care facilities. The beneficial effects of non-drug treatments are poorly studied. OBJECTIVE: To describe the effects of an Integrated Psychostimulation Program (IPP) in patients with mild-moderate AD treated with acetylcholinesterase inhibitors; and to identify factors related to greater benefit of the IPP. METHODS: 206 patients (mean age = 75.9 years; MMSE = 19.6) were evaluated before starting the IPP and 3, 6, 9, and 12 months later. Measures included: Mini-Mental State Examination (MMSE), Cognitive Subscale of Alzheimer's Disease Assessment Scale (ADAS-Cog), Rapid Disability Rating Scale (RDRS-2), and Neuropsychiatric Inventory Questionnaire (NPI-Q). RESULTS: Patients remained cognitively stable (MMSE/ADAS-Cog) for more than 6 months and significantly worsened at 9-month and 12-month follow-ups, without clinically significant functional changes (RDRS-2) or psychiatric symptoms(NPI-Q). The mean annual change on MMSE and ADAS-Cog were 2.06 and 3.56 points, respectively, lower than the annual decline demonstrated previously in similar patients (2.4 and 4.5, respectively). 42.7% of patients maintained or improved global cognitive scores between baseline and 12-month follow-up. The patients who maintained cognitive functions were older than those who did not (77.5 versus 74.7 years). CONCLUSIONS: The IPP may be an effective treatment to maintain cognition, functionality, and psychiatric symptoms in AD patients pharmacologically treated, and older age seems to increase beneficial effects of IPP.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Alzheimer Disease; Cholinesterase Inhibitors; Cognition; Combined Modality Therapy; Disease Progression; Female; Humans; Male; Neuropsychological Tests; Psychotherapy; Severity of Illness Index; Treatment Outcome

Biomarkers Differentiating Dementia with Lewy Bodies from Other Dementias: A Meta-Analysis. - Mishima, Aki; Nihashi, Takashi; Ando, Yoshio; Kawai, Hisashi; Kato, Takashi; Ito, Kengo; Terasawa, Teruhiko (J Alzheimers Dis, 2016)
BACKGROUND: Several nuclear imaging and cerebrospinal fluid (CSF) biomarkers are under investigation, aimed at facilitating the differential diagnosis of dementias. OBJECTIVE: To quantitatively synthesize data on test performance in differentiating dementia with Lewy bodies (DLB) from other dementias. METHODS: We searched PubMed (January 2000- March 2015) for English-language publications that assessed a selected set of five imaging and three CSF biomarkers for this purpose. We meta-analyzed measures of agreement between biomarker results and clinical diagnosis. RESULTS: Forty-five publications were eligible. The majority of evidence was based on studies that enrolled representative disease populations. For differentiating between DLB and Alzheimer's disease (AD) or other dementias, metaiodobenzylguanidine scintigraphy and dopamine transporter (DAT) single photon emission computed tomography (SPECT) showed, respectively, excellent (summary kappa = 0.85; 95% confidence interval [95% CI], 0.74-0.96) and good (summary kappa = 0.71; 95% CI, 0.43-0.99) agreement. Metaiodobenzylguanidine scintigraphy appeared superior to fluorodeoxyglucose- positron emission tomography (summary kappa = 0.53; 95% CI, 0.36-0.69) and cerebral blood flow SPECT (summary kappa = 0.40; 95% CI, 0.33-0.47). For differentiating DLB from AD, CSF t-tau levels (summary kappa = 0.68; 95% CI, 0.55-0.82) performed comparably to metaiodobenzylguanidine scintigraphy and DAT SPECT. Sparse direct comparative evidence failed to corroborate these indirect comparisons. CONCLUSION: Metaiodobenzylguanidine scintigraphy and DAT SPECT are highly concordant with clinical diagnosis in differentiating DLB from other dementias. However, given the limitations in the study design, the applicability of these results to real-world differential diagnosis remains unclear. Prospective studies targeting patients with atypical presentations that adopt gold standard tests would reliably estimate the true test performance of these promising biomarkers.
Keywords: Biomarkers; Dementia; Diagnosis, Differential; Humans; Lewy Bodies; PubMed; Radionuclide Imaging; Retrospective Studies

Blood-Borne Activity-Dependent Neuroprotective Protein (ADNP) is Correlated with Premorbid Intelligence, Clinical Stage, and Alzheimer's Disease Biomarkers. - Malishkevich, Anna; Marshall, Gad A; Schultz, Aaron P; Sperling, Reisa A; Aharon-Peretz, Judith; Gozes, Illana (J Alzheimers Dis, 2016)
Biomarkers for Alzheimer's disease (AD) are vital for disease detection in the clinical setting. Discovered in our laboratory, activity-dependent neuroprotective protein (ADNP) is essential for brain formation and linked to cognitive functions. Here, we revealed that blood borne expression of ADNP and its paralog ADNP2 is correlated with premorbid intelligence, AD pathology, and clinical stage. Age adjustment showed significant associations between: 1) higher premorbid intelligence and greater serum ADNP, and 2) greater cortical amyloid and lower ADNP and ADNP2 mRNAs. Significant increases in ADNP mRNA levels were observed in patients ranging from mild cognitive impairment (MCI) to AD dementia. ADNP2 transcripts showed high correlation with ADNP transcripts, especially in AD dementia lymphocytes. ADNP plasma/serum and lymphocyte mRNA levels discriminated well between cognitively normal elderly, MCI, and AD dementia participants. Measuring ADNP blood-borne levels could bring us a step closer to effectively screening and tracking AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Chi-Square Distribution; Cognitive Dysfunction; Cohort Studies; Female; Homeodomain Proteins; Humans; Independent Living; Intelligence; Male; Mental Status Schedule; Middle Aged; Nerve Tissue Proteins; Peptide Fragments; RNA, Messenger; tau Proteins

Brain Metabolism Correlates of the Free and Cued Selective Reminding Test in Mild Cognitive Impairment. - Caffarra, Paolo; Ghetti, Caterina; Ruffini, Livia; Spallazzi, Marco; Spotti, Annamaria; Barocco, Federica; Guzzo, Caterina; Marchi, Massimo; Gardini, Simona (J Alzheimers Dis, 2016)
Free and Cued Selective Reminding Test (FCSRT) measures immediate and delayed episodic memory and cueing sensitivity and is suitable to detect prodromal Alzheimer's disease (AD). The present study aimed at investigating the segregation effect of FCSRT scores on brain metabolism of memory-related structures, usually affected by AD pathology, in the Mild Cognitive Impairment (MCI) stage. A cohort of forty-eight MCI patients underwent FCSRT and 18F-FDG-PET. Multiple regression analysis showed that Immediate Free Recall correlated with brain metabolism in the bilateral anterior cingulate and delayed free recall with the left anterior cingulate and medial frontal gyrus, whereas semantic cueing sensitivity with the left posterior cingulate. FCSRT in MCI is associated with neuro-functional activity of specific regions of memory-related structures connected to hippocampal formation, such as the cingulate cortex, usually damaged in AD.
Keywords: Aged; Brain; Cognitive Dysfunction; Cues; Female; Fluorodeoxyglucose F18; Humans; Male; Memory Disorders; Memory, Episodic; Mental Recall; Middle Aged; Neuropsychological Tests; Positron-Emission Tomography

Brain-Specific Basal and Novelty-Induced Alternations in PI3K-Akt and MAPK/ERK Signaling in a Middle-Aged AβPP/PS1 Mouse Model of Alzheimer's Disease. - Guillot, Florence; Kemppainen, Susanna; Lavasseur, Gregoire; Miettinen, Pasi O; Laroche, Serge; Tanila, Heikki; Davis, Sabrina (J Alzheimers Dis, 2016)
Although it is well established that insulin/IGF and BDNF signaling are dysfunctionally regulated in Alzheimer's disease, there are very few studies documenting changes in major target proteins in different murine models of the disease. We investigated a panel of proteins in the PI3K-Akt and MAPK/ERK cascades in parietal cortex, dentate gyrus and CA1 in 13-month-old AβPP/PS1 transgenic mice to determine whether amyloid pathology is associated with basal dysregulation of these proteins or following exposure to novelty. The most striking effect we found was that there was little common regulation of proteins either by pathology alone or exposure to novelty across the three structures, suggesting dysfunctional mechanisms that occur simultaneously have important structure specificity. CA1 shared certain dysfunctional regulation of proteins in the MAPK/ERK cascade, but shared dysfunctional regulation of the PI3K/Akt cascade with the dentate gyrus. Changes in ERK/CREB in transgenic mice did not result in coordinated dysfunction of the downstream transcription factor, Egr1, as it was overexpressed in a normal manner following exposure to novelty. In the PI3K-Akt cascade, there was a flagrant increase in the levels of proteins associated with inflammation, such as NFκB, and structure specific regulation of proteins associated with autophagy, such as mTOR and FOXO1 and lack of regulation of Beclin-1. Finally, Beclin-1 was increased by novelty in wild-type mice but deficient in transgenic mice. Results are interpreted in terms of structure-specific dysfunctional regulation of signaling mechanisms associated with Alzheimer's disease.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; Brain; Disease Models, Animal; Gene Expression Regulation; Humans; Male; Mice; Mice, Inbred C57BL; Mice, Transgenic; Mitogen-Activated Protein Kinase Kinases; Mutation; Oncogene Protein v-akt; Phosphatidylinositol 3-Kinases; Presenilin-1; Signal Transduction

Bridging Integrator 1 (BIN1) Genotypes Mediate Alzheimer's Disease Risk by Altering Neuronal Degeneration. - Wang, Hui-Fu; Wan, Yu; Hao, Xiao-Ke; Cao, Lei; Zhu, Xi-Chen; Jiang, Teng; Tan, Meng-Shan; Tan, Lin; Zhang, Dao-Qiang; Tan, Lan; Yu, Jin-Tai (J Alzheimers Dis, 2016)
BACKGROUND: Bridging integrator 1 (BIN1) has been identified as one of the most associated loci for Alzheimer's disease (AD), and recently was reported to modulate tau pathology to mediate AD in vitro. However, the effects of BIN1 on the AD related biomarkers in AD continuum were not specifically assessed. OBJECTIVE: We explored the effects of BIN1 loci on AD specific biomarkers (CSF proteins, brain structures, glucose and amyloid-β (Aβ) metabolisms) to investigate the role BIN1 in AD pathogenesis. METHODS: We calculated the associations of BIN1 loci with these markers at baseline and follow-up in multiple linear models in 812 ADNI subjects. RESULTS: BIN1 loci were significantly associated with the levels of T-tau (rs744373: pc = 0.047, rs13031703: pc = 0.042) and P-tau (rs744373: pc = 0.044, rs13031703: pc = 0.019), but not with Aβ in CSF test. BIN1 genotypes were strongly related to atrophy of hippocampus (rs7561528: pc = 0.011), CA1 (rs1469980: pc = 0.029) and parahippocampus (rs72838284, pc = 0.017) on MRI, and to glucose metabolism on FDG-PET, but not to Aβ deposition on AV45-PET imaging. Furthermore, haplotype and subgroup analysis confirmed these significant findings. In addition, the loci associated with these markers were also identified to influence the risk for AD in the meta-analysis of 74 046 European individuals. CONCLUSION: This study supported that BIN1 contributes to the risk of AD by altering neural degeneration (abnormal tau, brain atrophy and glucose metabolism) but not Aβ pathology.
Keywords: Adaptor Proteins, Signal Transducing; Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Brain; Databases, Factual; European Continental Ancestry Group; Female; Follow-Up Studies; Genetic Predisposition to Disease; Glucose; Humans; Longitudinal Studies; Magnetic Resonance Imaging; Male; Middle Aged; Nerve Degeneration; Nuclear Proteins; Polymorphism, Single Nucleotide; Positron-Emission Tomography; Risk; tau Proteins; Tumor Suppressor Proteins

Cannabinoid Receptor 2 Participates in Amyloid-β Processing in a Mouse Model of Alzheimer's Disease but Plays a Minor Role in the Therapeutic Properties of a Cannabis-Based Medicine. - Aso, Ester; Andrés-Benito, Pol; Carmona, Margarita; Maldonado, Rafael; Ferrer, Isidre (J Alzheimers Dis, 2016)
The endogenous cannabinoid system represents a promising therapeutic target to modify neurodegenerative pathways linked to Alzheimer's disease (AD). The aim of the present study was to evaluate the specific contribution of CB2 receptor to the progression of AD-like pathology and its role in the positive effect of a cannabis-based medicine (1:1 combination of Δ9-tetrahidrocannabinol and cannabidiol) previously demonstrated to be beneficial in the AβPP/PS1 transgenic model of the disease. A new mouse strain was generated by crossing AβPP/PS1 transgenic mice with CB2 knockout mice. Results show that lack of CB2 exacerbates cortical Aβ deposition and increases the levels of soluble Aβ40. However, CB2 receptor deficiency does not affect the viability of AβPP/PS1 mice, does not accelerate their memory impairment, does not modify tau hyperphosphorylation in dystrophic neurites associated to Aβ plaques, and does not attenuate the positive cognitive effect induced by the cannabis-based medicine in these animals. These findings suggest a minor role for the CB2 receptor in the therapeutic effect of the cannabis-based medicine in AβPP/PS1 mice, but also constitute evidence of a link between CB2 receptor and Aβ processing.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; Brain; Cannabidiol; Cognition; Disease Models, Animal; Dronabinol; Humans; Male; Medical Marijuana; Memory; Mice, Inbred C57BL; Mice, Transgenic; Nootropic Agents; Presenilin-1; Random Allocation; Receptor, Cannabinoid, CB2; tau Proteins; Treatment Outcome

Capillary amyloid-β protein deposition in a population-based study (Vantaa 85+). - Mäkelä, Mira; Paetau, Anders; Polvikoski, Tuomo; Myllykangas, Liisa; Tanskanen, Maarit (J Alzheimers Dis, 2016)
BACKGROUND: Capillary amyloid-β (capAβ) deposition in the cerebral cortex is the neuropathological feature providing the basis for categorizing cerebral amyloid angiopathy (CAA) into two distinct types, CAA-Type1 with capAβ and CAA-Type2 without capAβ. OBJECTIVE: We investigated the neuropathological and clinical characteristics of capAβ deposition in a prospective population-based study. METHODS: Vantaa 85+ includes 601 individuals aged ≥85 years, of which 300 were studied clinically and neuropathologically. 278 subjects were analyzed for the apolipoprotein E (APOE) genotype. The diagnosis of capAβ was determined using immunohistochemistry against Aβ, and of CAA using Congo red confirmed by Aβ immunohistochemistry, both analyzed in six brain areas. The severity of capAβ was graded semi-quantitatively, and the severity of CAA was based on the percentage of affected vessels. Alzheimer's disease (AD)-type neuropathology (CERAD score and Braak stage) was analyzed using standard methods. RESULTS: CAA-Type1 was present in 86/300, CAA-Type2 in 135/300, and 79/300 had no CAA. CapAβ was most frequent in the occipital lobe (79/86). CAA-Type1 was associated with the severity of CAA (p <  0.001), dementia (p <  0.001), severe AD-type neuropathology (p-value 0.09 for CERAD C and 0.017 for Braak stages V-VI), and APOE ɛ4 allele carrier status (p <  0.001). CONCLUSIONS: This population-based study confirmed the presence of distinct CAA-Type1 and its association with the severity of CAA, severe AD-type neuropathology, and the APOE ɛ4 carrier status. Both the severity and localization of the deposition seemed to determine the clinical significance of capAβ.
Keywords: Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Apolipoprotein E4; Autopsy; Capillaries; Cerebral Amyloid Angiopathy; Female; Finland; Genotype; Humans; Immunohistochemistry; Logistic Models; Male; Multivariate Analysis; Occipital Lobe; Prospective Studies; Severity of Illness Index

Cerebral Small Vessel Disease and Motoric Cognitive Risk Syndrome: Results from the Kerala-Einstein Study. - Wang, Nan; Allali, Gilles; Kesavadas, Chandrasekharan; Noone, Mohan L; Pradeep, Vayyattu G; Blumen, Helena M; Verghese, Joe (J Alzheimers Dis, 2016)
BACKGROUND: The contribution of cerebral small vessel disease to cognitive decline, especially in non-Caucasian populations, is not well established. OBJECTIVE: We examined the relationship between cerebral small vessel disease and motoric cognitive risk syndrome (MCR), a recently described pre-dementia syndrome, in Indian seniors. METHODS: 139 participants (mean age 66.6 ± 5.4 y, 33.1% female) participating in the Kerala-Einstein study in Southern India were examined in a cross-sectional study. The presence of cerebral small vessel disease (lacunar infarcts and cerebral microbleeds (CMB)) and white matter hyperintensities on MRI was ascertained by raters blinded to clinical information. MCR was defined by the presence of cognitive complaints and slow gait in older adults without dementia or mobility disability. RESULTS: Thirty-eight (27.3%) participants met MCR criteria. The overall prevalence of lacunar infarcts and CMB was 49.6% and 9.4% , respectively. Lacunar infarcts in the frontal lobe, but no other brain regions, were associated with MCR even after adjusting for vascular risk factors and presence of white matter hyperintensities (adjusted Odds Ratio (aOR): 4.67, 95% CI: 1.69-12.94). Frontal lacunar infarcts were associated with slow gait (aOR: 3.98, 95% CI: 1.46-10.79) and poor performance on memory test (β: -1.24, 95% CI: -2.42 to -0.05), but not with cognitive complaints or non-memory tests. No association of CMB was found with MCR, individual MCR criterion or cognitive tests. CONCLUSIONS: Frontal lacunar infarcts are associated with MCR in Indian seniors, perhaps, by contributing to slow gait and poor memory function.
Keywords: Aged; Brain; Cerebral Small Vessel Diseases; Cognition Disorders; Female; Humans; Image Processing, Computer-Assisted; India; Magnetic Resonance Imaging; Male; Middle Aged; Neuropsychological Tests; Psychiatric Status Rating Scales; Risk Factors; Stroke, Lacunar; White Matter

Cerebrospinal Fluid Anti-Amyloid-β Autoantibodies and Amyloid PET in Cerebral Amyloid Angiopathy-Related Inflammation. - Carmona-Iragui, María; Fernández-Arcos, Ana; Alcolea, Daniel; Piazza, Fabrizio; Morenas-Rodriguez, Estrella; Antón-Aguirre, Sofía; Sala, Isabel; Clarimón, Jordi; Dols-Icardo, Oriol; Camacho, Valle; Sampedro, Frederic; Munuera, Josep; et al. (J Alzheimers Dis, 2016)
We report a biomarker and genetic evaluation of four patients with cerebral amyloid angiopathy-related inflammation (CAA-ri) treated with corticosteroids. Patients presented with focal symptomatology and cognitive impairment. MRI revealed cortical microbleeds and asymmetrical hyperintense white matter lesions (WML). Cerebrospinal fluid (CSF) biomarker analyses showed increased anti-Aβ autoantibodies, t-Tau, and p-Tau and decreased Aβ40 and Aβ42. After treatment, focal symptomatology disappeared, and WML and anti-Aβ autoantibodies decreased. The APOEɛ4 allele was overrepresented. Florbetapir-PET showed cortical deposition with lower retention in swollen areas. In the case of suspected CAA-ri, both CSF anti-Aβ autoantibodies levels and Florbetapir-PET could provide highly useful data to guide the correct diagnosis.
Keywords: Aged; Amyloid beta-Peptides; Aniline Compounds; Apolipoproteins E; Autoantibodies; Cerebral Amyloid Angiopathy; Ethylene Glycols; Female; Humans; Magnetic Resonance Imaging; Male; Meningoencephalitis; Peptide Fragments; Positron-Emission Tomography; Statistics, Nonparametric; tau Proteins

Cerebrospinal Fluid Fatty Acid-Binding Protein 3 is Related to Dementia Development in a Population-Based Sample of Older Adult Women Followed for 8 Years. - Bjerke, Maria; Kern, Silke; Blennow, Kaj; Zetterberg, Henrik; Waern, Margda; Börjesson-Hanson, Anne; Östling, Svante; Kern, Jürgen; Skoog, Ingmar (J Alzheimers Dis, 2016)
BACKGROUND: Increased fatty acid-binding protein 3 (FABP-3) levels have been reported in neurodegenerative diseases, including Alzheimer's disease (AD). Cerebrospinal fluid (CSF) FABP-3 has therefore been proposed as a putative marker for dementia. Population-based studies examining whether CSF FABP-3 predicts later development of dementia are lacking. OBJECTIVE: The aim of this study was to examine CSF levels of FABP-3 in relation to later development of dementia in elderly women and in relation to Aβ42, T-tau, P-tau181, and CSF: serum albumin ratio. METHODS: 86 non-demented women aged 70-84 years who participated in the Prospective Population Study of Women in Gothenburg, Sweden took part in a lumbar puncture in 1992-93. CSF-FABP-3, Aβ42, T-tau, P-tau181, and the CSF: serum albumin ratio were measured at baseline. Participants were examined with a neuropsychiatric exam at baseline and at follow-up in 2000. Dementia was diagnosed in accordance with DSM-III-R criteria. RESULTS: Between 1992 and 2000, 8 women developed dementia (4 AD, 3 vascular dementia, 1 mixed vascular dementia and AD). Higher levels of CSF-FABP-3 at baseline were related to development of dementia (OR 1.36 CI [1.05-1.76] p = 0.022) and the subtype AD (OR 1.38 CI [1.06-1.82), p = 0.019) during follow-up. FABP-3 correlated with CSF T-tau (r = 0.88, p <  0.001), P-tau181 (r = 0.619, p <  0.001), and CSF:serum albumin ratio (r = 0.233, p = 0.031), but not with Aβ42 (r = -0.08, p = 0.444)CONCLUSION:CSF FABP-3 may be an early marker for later development of dementia, probably related to neuronal degeneration, but independent of Aβ metabolism.
Keywords: Aged; Aged, 80 and over; Albumins; Amyloid beta-Peptides; Community Health Planning; Dementia; Fatty Acid-Binding Proteins; Female; Humans; Longitudinal Studies; Peptide Fragments; Sweden; tau Proteins

Cerebrospinal Fluid Markers of Alzheimer's Disease Pathology and Microglial Activation are Associated with Altered White Matter Microstructure in Asymptomatic Adults at Risk for Alzheimer's Disease. - Melah, Kelsey E; Lu, Sharon Yuan-Fu; Hoscheidt, Siobhan M; Alexander, Andrew L; Adluru, Nagesh; Destiche, Daniel J; Carlsson, Cynthia M; Zetterberg, Henrik; Blennow, Kaj; Okonkwo, Ozioma C; Gleason, Carey E; Dowling, N Maritza; et al. (J Alzheimers Dis, 2016)
BACKGROUND: The immune response in Alzheimer's disease (AD) involves activation of microglia which may remove amyloid-β (Aβ). However, overproduction of inflammatory compounds may exacerbate neural damage in AD. AD pathology accumulates years before diagnosis, yet the extent to which neuroinflammation is involved in the earliest disease stages is unknown. OBJECTIVE: To determine whether neuroinflammation exacerbates neural damage in preclinical AD. METHODS: We utilized cerebrospinal fluid (CSF) and magnetic resonance imaging collected in 192 asymptomatic late-middle-aged adults (mean age = 60.98 years). Neuroinflammatory markers chitinase-3-like protein 1 (YKL-40) and monocyte chemoattractant protein-1 (MCP-1) in CSF were utilized as markers of neuroinflammation. Neural cell damage was assessed using CSF neurofilament light chain protein (NFL), CSF total tau (T-Tau), and neural microstructure assessed with diffusion tensor imaging (DTI). With regard to AD pathology, CSF Aβ42 and tau phosphorylated at threonine 181 (P-Tau181) were used as markers of amyloid and tau pathology, respectively. We hypothesized that higher YKL-40 and MCP-1 in the presence of AD pathology would be associated with higher NFL, T-Tau, and altered microstructure on DTI. RESULTS: Neuroinflammation was associated with markers of neural damage. Higher CSF YKL-40 was associated with both higher CSF NFL and T-Tau. Inflammation interacted with AD pathology, such that greater MCP-1 and lower Aβ42 was associated with altered microstructure in bilateral frontal and right temporal lobe and that greater MCP-1 and greater P-Tau181 was associated with altered microstructure in precuneus. CONCLUSION: Inflammation may play a role in neural damage in preclinical AD.
Keywords: Adipokines; Aged; Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Chemokine CCL2; Chitinase-3-Like Protein 1; Diffusion Tensor Imaging; Female; Hippocampus; Humans; Image Processing, Computer-Assisted; Lectins; Male; Microglia; Middle Aged; Peptide Fragments; tau Proteins; White Matter

Characteristics of Alzheimer's Disease Patients with Severe Executive Disorders. - Godefroy, Olivier; Bakchine, Serge; Verny, Marc; Delabrousse-Mayoux, Jean-Philippe; Roussel, Martine; Pere, Jean-Jacques (J Alzheimers Dis, 2016)
BACKGROUND: Executive dysfunctions in Alzheimer's disease (AD) have been assessed using variable batteries and/or in selected populations. OBJECTIVE: The primary objective of this observational study was to determine the prevalence and severity of executive dysfunction in AD patients using a previously validated battery. The secondary objective was to determine the characteristics including treatment outcomes of AD patients with severe executive dysfunction. METHODS: The study included AD patients with mild-to-moderate dementia aged 60 or over, consulting in various clinical settings including memory clinics and requiring the introduction of an antidementia drug. Executive dysfunction was examined using a validated, shortened executive battery. RESULTS: 381 patients were included. Executive dysfunctions were observed in 88.2% of the patients (95% CI: 84.9-91.4) and were severe (defined as ≥2/3 impaired scores) in 80.4% (95% CI: 76.9-84.8). Global hypoactivity with apathy was more frequent (p = 0.0001) than impairment in executive function tests. The 308 patients with severe executive dysfunction were older (p = 0.003) and had more severe dementia (p = 0.0001). Similarly, in the subset of 257 patients with mild dementia, individuals with severe executive dysfunction were older (p = 0.003) and had more severe dementia. Global hypoactivity was independently associated with difficulties in IADL and a higher caregiver burden (p = 0.0001 for both). The severity of executive dysfunction did not significantly influence the patients' outcomes at 6 months. CONCLUSIONS: Executive dysfunction is a very common disorder in a representative population of patients with mild-to-moderate AD. It was independently correlated with impaired autonomy and increased caregiver burden but did not significantly influence treatment outcomes.
Keywords: Activities of Daily Living; Aged; Alzheimer Disease; Caregivers; Cost of Illness; Executive Function; Female; Humans; Male; Mental Status Schedule; Neuropsychological Tests; Prevalence; Severity of Illness Index; Treatment Outcome

Characterization of Amyloid-β Deposits in Bovine Brains. - Vallino Costassa, Elena; Fiorini, Michele; Zanusso, Gianluigi; Peletto, Simone; Acutis, Pierluigi; Baioni, Elisa; Maurella, Cristiana; Tagliavini, Fabrizio; Catania, Marcella; Gallo, Marina; Faro, Monica Lo; Chieppa, Maria Novella; et al. (J Alzheimers Dis, 2016)
Amyloid-β (Aβ) deposits are seen in aged individuals of many mammalian species that possess the same aminoacid sequence as humans. This study describes Aβ deposition in 102 clinically characterized cattle brains from animals aged 0 to 20 years. Extracellular and intracellular Aβ deposition was detected with 4G8 antibody in the cortex, hippocampus, and cerebellum. X-34 staining failed to stain Aβ deposits, indicating the non β-pleated nature of these deposits. Western blot analysis and surface-enhanced laser desorption/ionization time-of-flight (SELDI-TOF) mass spectrometry revealed in Tris, Triton, and formic acid fractions the presence of different Aβ peptides, characterized mainly by C-terminally truncated forms. Exploration of the genetic variability of APOE, PSEN1, and PSEN2 genes involved in Alzheimer's disease pathogenesis revealed several previously unreported polymorphisms. This study demonstrates certain similarities between Aβ deposition patterns exhibited in cattle brains and those in the human brain in early stages of aging. Furthermore, the identification of the same Aβ peptides reported in humans, but unable to form aggregates, supports the hypothesis that cattle may be protected against amyloid plaque formation.
Keywords: Aging; Amyloid beta-Peptides; Animals; Apolipoproteins E; Blotting, Western; Brain; Cattle; Extracellular Space; Gene Frequency; Genotyping Techniques; Glial Fibrillary Acidic Protein; Immunohistochemistry; Intracellular Space; Neuroglia; Neurons; Polymorphism, Genetic; Presenilin-1; Presenilin-2; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization

Characterizing White Matter Tract Degeneration in Syndromic Variants of Alzheimer's Disease: A Diffusion Tensor Imaging Study. - Madhavan, Ajay; Schwarz, Christopher G; Duffy, Joseph R; Strand, Edythe A; Machulda, Mary M; Drubach, Daniel A; Kantarci, Kejal; Przybelski, Scott A; Reid, Robert I; Senjem, Matthew L; Gunter, Jeffrey L; Apostolova, Liana G; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Different clinical syndromes can arise from Alzheimer's disease (AD) neuropathology, including dementia of the Alzheimer's type (DAT), logopenic primary progressive aphasia (lvPPA), and posterior cortical atrophy (PCA). OBJECTIVE: To assess similarities and differences in patterns of white matter tract degeneration across these syndromic variants of AD. METHODS: Sixty-four subjects (22 DAT, 24 lvPPA, and 18 PCA) that had diffusion tensor imaging and showed amyloid-β deposition on PET were assessed in this case-control study. A whole-brain voxel-based analysis was performed to assess differences in fractional anisotropy, mean diffusivity, axial diffusivity, and radial diffusivity across groups. RESULTS: All three groups showed overlapping diffusion abnormalities in a network of tracts, including fornix, corpus callosum, posterior thalamic radiations, superior longitudinal fasciculus, inferior longitudinal fasciculus, inferior fronto-occipital fasciculus, and uncinate fasciculus. Subtle regional differences were also observed across groups, with DAT particularly associated with degeneration of fornix and cingulum, lvPPA with left inferior fronto-occipital fasciculus and uncinate fasciculus, and PCA with posterior thalamic radiations, superior longitudinal fasciculus, posterior cingulate, and splenium of the corpus callosum. CONCLUSION: These findings show that while each AD phenotype is associated with degeneration of a specific structural network of white matter tracts, striking spatial overlap exists among the three network patterns that may be related to AD pathology.
Keywords: Aged; Alzheimer Disease; Aniline Compounds; Anisotropy; Aphasia, Primary Progressive; Case-Control Studies; Diffusion Tensor Imaging; Female; Humans; Image Processing, Computer-Assisted; Male; Middle Aged; Nerve Fibers, Myelinated; Neurodegenerative Diseases; Neuropsychological Tests; Positron-Emission Tomography; Psychiatric Status Rating Scales; Retrospective Studies; Thiazoles; White Matter

Chronic Obstructive Pulmonary Disease as a Risk Factor for Cognitive Dysfunction: A Meta-Analysis of Current Studies. - Zhang, Ximeng; Cai, Xiaoying; Shi, Xiaolei; Zheng, Zhenyang; Zhang, Aiwu; Guo, Junliang; Fang, Yannan (J Alzheimers Dis, 2016)
Cognitive dysfunction has been shown to be associated with many risk factors, such as smoking, diabetes, and body mass index. Chronic obstructive pulmonary disease (COPD), a common disease within the elderly population, has also been found to be related to cognitive decline. However, whether COPD is a risk factor of cognitive dysfunction is not well established. The purpose of this meta-analysis is to investigate the role COPD plays in cognitive dysfunction. PubMed, Cochrane library and Web of Science databases were searched. Three cohort studies and eleven cross-sectional studies were found to be eligible. According to our results, COPD patients had a higher risk of cognitive dysfunction than controls (OR [odds ratio]: 1.72; 95% CI, 1.12-2.65; p = 0.01). The exacerbation of COPD was strongly correlated with cognitive decline. COPD patients performed worse than controls on the Mini- Mental State Examination test, but the results were not statistically significant (OR: -0.79; 95% CI, [-1.78, 0.19]; p = 0.11). Thus, more attention should be given to the occurrence of cognitive decline in COPD patients. The prevention and control of COPD exacerbation are critical.
Keywords: Cognitive Dysfunction; Humans; Pulmonary Disease, Chronic Obstructive; Risk Factors

Chronic Sleep Deprivation Exacerbates Learning-Memory Disability and Alzheimer's Disease-Like Pathologies in AβPP(swe)/PS1(ΔE9) Mice. - Qiu, Hongyan; Zhong, Rujia; Liu, Hui; Zhang, Feng; Li, Song; Le, Weidong (J Alzheimers Dis, 2016)
Recently, there is an increasing concern over the association between sleep disorders and Alzheimer's disease (AD). Clinical observations have reported that chronic sleep deprivation (SD) may serve as a risk factor for AD. However, the pathological evidence for this assumption is still lacking. In the present study, we examined the potential impacts of chronic SD on learning-memory and AD-related pathologies in AβPP(swe)/PS1(ΔE9) transgenic (TG) mice and their wild-type (WT) littermates. Results indicated that mice (both TG and WT) exposed to 2-month SD showed an altered amyloid-β protein precursor processing, an elevated level of phosphorylated tau protein, and impaired cognitive performance as compared to non-sleep deprivation (NSD) controls. Moreover, the SD-treated TG mice exhibited more amyloid-β(1-42) production and developed more senile plaques in the cortex and hippocampus than NSD-treated TG mice. In addition, SD caused a striking neuronal mitochondrial damage, caspase cascade activation, and neuronal apoptosis in the hippocampus of both TG and WT mice. More importantly, all these behavioral, neuropathological, and biochemical changes induced by chronic SD were long lasting and were irreversible during a 3-month normal housing condition. Collectively, these results indicate that chronic SD impairs learning and memory, exacerbates AD pathologies, and aggravates the mitochondria-mediated neuronal apoptosis in a long-lasting manner. Our findings provide important experimental evidence to prove that chronic SD is a risk factor for AD.
Keywords: Alzheimer Disease; Amyloid beta-Protein Precursor; Animals; Apoptosis; Brain; Cognition Disorders; Disease Models, Animal; Humans; In Situ Nick-End Labeling; Learning Disorders; Mice; Mice, Transgenic; Mitochondrial Diseases; Mutation; Phosphorylation; Plaque, Amyloid; Presenilin-1; Reversal Learning; Sleep Deprivation; tau Proteins

Cigarette Smoke-Induced Alterations in Frontal White Matter Lipid Profiles Demonstrated by MALDI-Imaging Mass Spectrometry: Relevance to Alzheimer's Disease. - Nunez, Kavin; Kay, Jared; Krotow, Alexander; Tong, Ming; Agarwal, Amit R; Cadenas, Enrique; de la Monte, Suzanne M (J Alzheimers Dis, 2016)
BACKGROUND: Meta-analysis has shown that smokers have significantly increased risks for Alzheimer's disease (AD), and neuroimaging studies showed that smoking alters white matter (WM) structural integrity. OBJECTIVE: Herein, we characterize the effects of cigarette smoke (CS) exposures and withdrawal on WM myelin lipid composition using matrix assisted laser desorption and ionization-imaging mass spectrometry (MALDI-IMS). METHODS: Young adult male A/J mice were exposed to air (8 weeks; A8), CS (4 or 8 weeks; CS4, CS8), or CS8 followed by 2 weeks recovery (CS8 + R). Frontal lobe WM was examined for indices of lipid and protein oxidation and lipid profile alterations by MALDI-IMS. Lipid ions were identified by MS/MS with the LIPID MAPS prediction tools database. Inter-group comparisons were made using principal component analysis and R-generated heatmap. RESULTS: CS increased lipid and protein adducts such that higher levels were present in CS8 compared with CS4 samples. CS8 + R reversed CS8 effects and normalized the levels of oxidative stress. MALDI-IMS demonstrated striking CS-associated alterations in WM lipid profiles characterized by either reductions or increases in phospholipids (phosphatidylinositol, phosphatidylserine, phosphatidylcholine, or phosphatidylethanolamine) and sphingolipids (sulfatides), and partial reversal of CS's inhibitory effects with recovery. The heatmap hierarchical dendrogram and PCA distinguished CS exposure, duration, and withdrawal effects on WM lipid profiles. CONCLUSION: CS-mediated WM degeneration is associated with lipid peroxidation, protein oxidative injury, and alterations in myelin lipid composition, including shifts in phospholipids and sphingolipids needed for membrane integrity, plasticity, and intracellular signaling. Future goals are to delineate WM abnormalities in AD using MALDI-IMS, and couple the findings with MRI-mass spectroscopy to improve in vivo diagnostics and early detection of brain biochemical responses to treatment.
Keywords: Aldehydes; Analysis of Variance; Animals; Dinoprost; Disease Models, Animal; Enzyme-Linked Immunosorbent Assay; Frontal Lobe; Lipid Metabolism; Male; Mice; Phospholipids; Principal Component Analysis; Protein Carbonylation; Smoking; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; Substance Withdrawal Syndrome; White Matter

Classification of Neuropsychiatric Symptoms Requiring Antipsychotic Treatment in Patients with Alzheimer's Disease: Analysis of the CATIE-AD Study. - Nagata, Tomoyuki; Shinagawa, Shunichiro; Nakajima, Shinichiro; Plitman, Eric; Mihashi, Yukiko; Hayashi, Shogo; Mimura, Masaru; Nakayama, Kazuhiko (J Alzheimers Dis, 2016)
BACKGROUND: The Neuropsychiatric Inventory (NPI) comprises 12 items, which were conventionally determined by psychopathological symptoms of patients with dementia. The clinical rating scales with structured questionnaires have been useful to evaluate neuropsychiatric symptoms (NPSs) of patients with dementia over the past twenty year. OBJECTIVE: The aim of this study was to classify the conventional NPSs in patients with Alzheimer's disease (AD) requiring antipsychotic treatment for their NPSs into distinct clusters to simplify assessment of these numerous symptoms. METHODS: Twelve items scores (product of severity and frequency of each symptom) in the NPI taken from the baseline visit were classified into subgroups by principle component analysis using data from 421 outpatients with AD enrolled in the Clinical Antipsychotic Trials of Intervention Effectiveness-Alzheimer's Disease (CATIE-AD) Phase 1. Chi square tests were conducted to examine the co-occurrence of the subgroups. RESULTS: We found four distinct clusters: aggressiveness (agitation and irritabilities), apathy and eating problems (apathy and appetite/eating disturbance), psychosis (delusions and hallucinations), and emotion and disinhibition (depression, euphoria, and disinhibition). Anxiety, aberrant motor behavior, and sleep disturbance were not included by these clusters. Apathy and eating problems, and emotion and disinhibition co-occurred (p = 0.002), whereas aggressiveness and psychosis occurred independent of the other clusters. CONCLUSIONS: Four distinct category clusters were identified from NPSs in patients with AD requiring antipsychotic treatment. Future studies should investigate psychosocial backgrounds or risk factors of each distinct cluster, in addition to their longitudinal course over treatment intervention.
Keywords: Aged; Aged, 80 and over; Aggression; Alzheimer Disease; Antipsychotic Agents; Apathy; Cluster Analysis; Female; Humans; Male; Psychiatric Status Rating Scales; Psychomotor Agitation; Psychotic Disorders; Retrospective Studies; Severity of Illness Index

Clearing Amyloid-β through PPARγ/ApoE Activation by Genistein is a Treatment of Experimental Alzheimer's Disease. - Bonet-Costa, Vicent; Herranz-Pérez, Vicente; Blanco-Gandía, MariCarmen; Mas-Bargues, Cristina; Inglés, Marta; Garcia-Tarraga, Patricia; Rodriguez-Arias, Marta; Miñarro, Jose; Borras, Consuelo; Garcia-Verdugo, Jose Manuel; Viña, Jose (J Alzheimers Dis, 2016)
Amyloid-β (Aβ) clearance from brain, which is decreased in Alzheimer's disease, is facilitated by apolipoprotein E (ApoE). ApoE is upregulated by activation of the retinoid X receptor moiety of the RXR/PPARγ dimeric receptor. Genistein, a non-toxic, well-tested, and inexpensive drug activates the other moiety of the receptor PPARγ. Treatment of an Alzheimer's disease mouse model with genistein results in a remarkable and rapid improvement in various parameters of cognition, such as hippocampal learning, recognition memory, implicit memory, and odor discrimination. This is associated with a lowering of Aβ levels in brain, in the number and the area of amyloid plaques (confirmed in vivo by positron emission tomography) as well as in microglial reactivity. Finally, incubation of primary astrocytes with genistein results in a PPARγ-mediated increased release of ApoE. Our results strongly suggest that controlled clinical trials should be performed to test the effect of genistein as treatment of human Alzheimer's disease.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; Apolipoproteins E; Astrocytes; Avoidance Learning; Brain; Cells, Cultured; Disease Models, Animal; Female; Genistein; Habituation, Psychophysiologic; Maze Learning; Mice, Inbred C57BL; Mice, Transgenic; Neuroprotective Agents; Nootropic Agents; Olfactory Perception; Plaque, Amyloid; PPAR gamma; Recognition (Psychology); Tetrahydronaphthalenes

Clinical and Demographic Factors Associated with the Cognitive and Emotional Efficacy of Regular Musical Activities in Dementia. - Särkämö, Teppo; Laitinen, Sari; Numminen, Ava; Kurki, Merja; Johnson, Julene K; Rantanen, Pekka (J Alzheimers Dis, 2016)
Recent evidence suggests that music-based interventions can be beneficial in maintaining cognitive, emotional, and social functioning in persons with dementia (PWDs). Our aim was to determine how clinical, demographic, and musical background factors influence the cognitive and emotional efficacy of caregiver-implemented musical activities in PWDs. In a randomized controlled trial, 89 PWD-caregiver dyads received a 10-week music coaching intervention involving either singing or music listening or standard care. Extensive neuropsychological testing and mood and quality of life (QoL) measures were performed before and after the intervention (n = 84) and six months later (n = 74). The potential effects of six key background variables (dementia etiology and severity, age, care situation, singing/instrument playing background) on the outcome of the intervention were assessed. Singing was beneficial especially in improving working memory in PWDs with mild dementia and in maintaining executive function and orientation in younger PWDs. Music listening was beneficial in supporting general cognition, working memory, and QoL especially in PWDs with moderate dementia not caused by Alzheimer's disease (AD) who were in institutional care. Both music interventions alleviated depression especially in PWDs with mild dementia and AD. The musical background of the PWD did not influence the efficacy of the music interventions. Our findings suggest that clinical and demographic factors can influence the cognitive and emotional efficacy of caregiver-implemented musical activities and are, therefore, recommended to take into account when applying and developing the intervention to achieve the greatest benefit.
Keywords: Aged; Aged, 80 and over; Analysis of Variance; Caregivers; Case-Control Studies; Cognition Disorders; Dementia; Executive Function; Female; Follow-Up Studies; Humans; Male; Memory, Short-Term; Middle Aged; Mood Disorders; Music Therapy; Neuropsychological Tests; Orientation; Outcome Assessment (Health Care); Psychiatric Status Rating Scales; Quality of Life

Clinical Impact of a Second FDG-PET in Atypical/Unclear Dementia Syndromes. - Bergeron, David; Beauregard, Jean-Mathieu; Guimond, Jean; Fortin, Marie-Pierre; Houde, Michèle; Poulin, Stéphane; Verret, Louis; Bouchard, Rémi W; Laforce, Robert (J Alzheimers Dis, 2016)
Diagnosis of atypical/unclear dementia is often difficult and this delays treatment initiation. Several authors have shown that beyond standard dementia workup, 18F-fluorodeoxyglucose positron emission tomography (FDG-PET) reduces the number of unclear diagnoses, leads to earlier treatment, and has a beneficial impact on families. However, it is not uncommon that the FDG-PET findings are equivocal in this setting. For those cases, a repeat FDG-PET may clarify the diagnosis and prevent treatment delay. We retrospectively assessed the clinical impact of a repeat FDG-PET in 59 patients with atypical/unclear dementia syndromes and inconclusive initial FDG-PET. Changes in primary diagnosis, diagnostic confidence, and management following the second FDG-PET were examined. Conducting a second FDG-PET reduced the number of unclear diagnoses from 80% to 34% , led to diagnostic change in 24% of cases, and treatment modification in 22% of patients. Overall, the clinical impact was higher when initial diagnostic confidence was low and the second FDG-PET repeated ≥12 months after the first one. In tertiary care memory clinic settings, when diagnostic incertitude persists despite extensive evaluation and an equivocal FDG-PET, repeating the FDG-PET 12 months later can greatly clarify the diagnosis and improve management.
Keywords: Adult; Brain; Dementia; Diagnosis, Differential; Female; Fluorodeoxyglucose F18; Humans; Male; Middle Aged; Positron-Emission Tomography; Radiopharmaceuticals; Retrospective Studies

Clinical utility of the informant AD8 as a dementia case finding instrument in primary healthcare. - Chan, Qun Lin; Xu, Xin; Shaik, Muhammad Amin; Chong, Steven Shih Tsze; Hui, Richard Jor Yeong; Chen, Christopher Li-Hsian; Dong, YanHong (J Alzheimers Dis, 2016)
The informant AD8 has excellent discriminant ability for dementia case finding in tertiary healthcare settings. However, its clinical utility for dementia case finding at the forefront of dementia management, primary healthcare, is unknown. Therefore, we recruited participants from two primary healthcare centers in Singapore and measured their performance on the Mini-Mental State Examination (MMSE), Montreal Cognitive Assessment (MoCA), Clinical Dementia Rating (CDR), and a local formal neuropsychological battery, in addition to the AD8. Logistic regression was conducted to examine the associations between demographic factors and dementia. Area under the receiver operating characteristics (ROC) curve analysis was used to establish the optimal cut-off points for dementia case finding. Of the 309 participants recruited, 243 (78.7%) had CDR = 0, 22 (7.1%) CDR = 0.5, and 44 (14.2%) CDR ≥1. Age was strongly associated with dementia, and the optimal age for dementia case finding in primary healthcare settings was ≥75 years. In this age group, the AD8 has excellent dementia case finding capability and was superior to the MMSE and equivalent to the MoCA [AD8 AUC (95% CI): 0.95 (0.91-0.99), cut-off: ≥3, sensitivity: 0.90, specificity: 0.88, PPV: 0.79 and NPV: 0.94; MMSE AUC (95% CI): 0.87 (0.79-0.94), p = 0.04; MoCA AUC (95% CI): 0.88 (0.82-0.95), p = 0.06]. In conclusion, the AD8 is well suited for dementia case finding in primary healthcare settings.
Keywords: Aged; Aged, 80 and over; Dementia; Female; Humans; Language; Logistic Models; Male; Mass Screening; Middle Aged; Neuropsychological Tests; Primary Health Care; Reproducibility of Results; ROC Curve; Sensitivity and Specificity; Singapore; Surveys and Questionnaires

The Cognitive Change Index as a Measure of Self and Informant Perception of Cognitive Decline: Relation to Neuropsychological Tests. - Rattanabannakit, Chatchawan; Risacher, Shannon L; Gao, Sujuan; Lane, Kathleen A; Brown, Steven A; McDonald, Brenna C; Unverzagt, Frederick W; Apostolova, Liana G; Saykin, Andrew J; Farlow, Martin R (J Alzheimers Dis, 2016)
BACKGROUND: The perception of cognitive decline by individuals and those who know them well ("informants") has been inconsistently associated with objective cognitive performance, but strongly associated with depressive symptoms. OBJECTIVE: We investigated associations of self-report, informant-report, and discrepancy between self- and informant-report of cognitive decline obtained from the Cognitive Change Index (CCI) with cognitive test performance and self-reported depressive symptoms. METHODS: 267 participants with normal cognition, mild cognitive impairment (MCI), or mild dementia were included from a cohort study and memory clinic. Association of test performance and self-rated depression (Geriatric Depression Scale, GDS) with CCI scores obtained from subjects (CCI-S), their informants (CCI-I), and discrepancy scores between subjects and informants (CCI-D; CCI-S minus CCI-I) were analyzed using correlation and analysis of covariance (ANCOVA) models. RESULTS: CCI-S and CCI-I scores showed high internal consistency (Cronbach alpha 0.96 and 0.98, respectively). Higher scores on CCI-S and CCI-I, and lower scores on the CCI-D, were associated with lower performance on various cognitive tests in both univariate and in ANCOVA models adjusted for age, gender, and education. Adjustment for GDS slightly weakened the relationships between CCI and test performance but most remained significant. CONCLUSION: Self- and informant-report of cognitive decline, as measured by the CCI, show moderately strong relationships with objective test performance independent of age, gender, education, and depressive symptoms. The CCI appears to be a valid cross-sectional measure of self and informant perception of cognitive decline across the continuum of functioning. Studies are needed to address the relationship of CCI scores to longitudinal outcome.
Keywords: Adult; Aged; Aged, 80 and over; Analysis of Variance; Cognitive Dysfunction; Cross-Sectional Studies; Dementia; Female; Humans; Male; Mental Status Schedule; Middle Aged; Neuropsychological Tests; Perception; Self Report

Cognitive Impairment after Mild Stroke: Development and Validation of the SIGNAL2 Risk Score. - Kandiah, Nagaendran; Chander, Russell Jude; Lin, Xuling; Ng, Aloysius; Poh, Yen Yeong; Cheong, Chin Yee; Cenina, Alvin Rae; Assam, Pryseley Nkouibert (J Alzheimers Dis, 2016)
BACKGROUND: Post stroke cognitive impairment (PSCI), an important complication of strokes, has numerous risk factors. A scale adequately classifying risk of cognitive impairment 3-6 months after mild stroke will be useful for clinicians. OBJECTIVE: To develop a risk score based on clinical and neuroimaging variables that will be useful in identifying mild ischemic stroke patients at high risk for PSCI. METHODS: The risk score development cohort comprised of a retrospective dataset of 209 mild stroke patients with MRI confirmed infarcts, without pre-stroke cognitive impairment, and evaluated within 6 months post-stroke for PSCI. Logistic regression identified factors predictive of PSCI and a risk score was developed based on regression coefficients. The risk score was checked for stability using 10-fold cross-validation and validated in an independent prospective cohort of 185 ischemic mild stroke patients. RESULTS: Within 6 months post-stroke, 37.32% developed PSCI in the retrospective dataset. A 15-point risk score based on age, education, acute cortical infarcts, white matter hyperintensity, chronic lacunes, global cortical atrophy, and intracranial large vessel stenosis was highly predictive of PSCI with an AUC of 0.829. 10.11% with low scores, 52.69% with moderate scores, and 74.07% with high scores developed PSCI. In the prospective validation cohort, the model had an AUC of 0.776, and exhibited similar accuracy and stability statistics at both 6 and 12 months. CONCLUSION: The seven item risk score adequately identified mild stroke patients who are at an increased risk of developing PSCI.
Keywords: Aged; Aging; Area Under Curve; Brain; Brain Ischemia; Cognition Disorders; Constriction, Pathologic; Educational Status; Female; Follow-Up Studies; Humans; Logistic Models; Male; Middle Aged; Prospective Studies; Retrospective Studies; Risk; Severity of Illness Index; Stroke; White Matter

Cognitive Stimulation Modulates Platelet Total Phospholipases A2 Activity in Subjects with Mild Cognitive Impairment. - Balietti, Marta; Giuli, Cinzia; Fattoretti, Patrizia; Fabbietti, Paolo; Postacchini, Demetrio; Conti, Fiorenzo (J Alzheimers Dis, 2016)
We evaluated the effect of cognitive stimulation (CS) on platelet total phospholipases A2 activity (tPLA2A) in patients with mild cognitive impairment (MCI_P). At baseline, tPLA2A negatively correlated with Mini-Mental State Examination score (MMSE_s): patients with MMSE_s <26 (Subgroup 1) had significantly higher activity than those with MMSE_s ≥26 (Subgroup 2), who had values similar to the healthy elderly. Regarding CS effect, Subgroup 1 had a significant tPLA2A reduction, whereas Subgroup 2 did not significantly changes after training. Our results showed for the first time that tPLA2A correlates with the cognitive conditions of MCI_P, and that CS acts selectively on subjects with a dysregulated tPLA2A.
Keywords: Blood Platelets; Cognition; Cognitive Dysfunction; Cognitive Therapy; Cohort Studies; Humans; Mental Status Schedule; Neuropsychological Tests; Phospholipases A2; Treatment Outcome

Cohort Effects in the Prevalence and Survival of People with Dementia in a Rural Area in Northern Sweden. - Wimo, Anders; Sjölund, Britt-Marie; Sköldunger, Anders; Qiu, Chengxuan; Klarin, Inga; Nordberg, Gunilla; von Strauss, Eva (J Alzheimers Dis, 2016)
BACKGROUND: Recent studies suggest that trends in cardiovascular risk may result in a decrease in age-specific prevalence of dementia. Studies in rural areas are rare. OBJECTIVES: To study cohort effects in dementia prevalence and survival of people with dementia in a Swedish rural area. METHODS: Participants were from the 1995-1998 Nordanstig Project (NP) (n = 303) and the 2001-2003 Swedish National study on Aging and Care in Nordanstig (SNAC-N) (n = 384). Overall 6-year dementia prevalence and mortality in NP and SNAC-N were compared for people 78 years and older. Logistic regression analyses were used to calculate odds ratios (ORs) and 95% confidence intervals (CIs) for dementia occurrence using the NP study population as the reference group. Cox regression models were used to analyze time to death. RESULTS: The crude prevalence of dementia was 21.8% in NP and 17.4% in SNAC-N. When the NP cohort was used as the reference group, the age- and gender-adjusted OR of dementia was 0.71 (95% CI 0.48-1.04) in SNAC-N; the OR was 0.47 (0.24-0.90) for men and 0.88 (0.54-1.44) for women. In the extended model, the OR of dementia was significantly lower in SNAC-N than in the NP cohort as a whole (0.63; 0.39-0.99) and in men (0.34; 0.15-0.79), but not in women (0.81; 0.46-1.44). The Cox regression models indicated that the hazard ratio of dying was lower in the SNAC-N than NP population. CONCLUSIONS: Trends toward a lower prevalence of dementia in high-income countries seem to be evident in this Swedish rural area, at least in men.
Keywords: Aged; Aged, 80 and over; Aging; Cohort Effect; Dementia; Female; Humans; Male; Prevalence; Risk Factors; Rural Population; Sex Factors; Survival Rate; Sweden

Comparing the Effects of Multisensory Stimulation and Individualized Music Sessions on Elderly People with Severe Dementia: A Randomized Controlled Trial. - Sánchez, Alba; Maseda, Ana; Marante-Moar, M Pilar; de Labra, Carmen; Lorenzo-López, Laura; Millán-Calenti, José Carlos (J Alzheimers Dis, 2016)
The objective of this study was to compare the effects of a multisensory stimulation environment (MSSE) and individualized music sessions on agitation, emotional and cognitive status, and dementia severity in a sample of institutionalized patients with severe dementia. Twenty-two participants with a diagnosis of severe or very severe dementia were randomly assigned to two groups: MSSE and individualized music sessions. Both groups participated in two 30-min weekly sessions over 16 weeks. Outcomes were agitation (Cohen-Mansfield Agitation Inventory, CMAI), mood (Cornell Scale for Depression in Dementia, CSDD), anxiety (Rating Anxiety in Dementia, RAID), cognitive function (Severe Mini-Mental State Examination, SMMSE), and the overall severity of dementia (Bedford Alzheimer Nursing Severity Scale, BANS-S). They were assessed at baseline (pre-trial), in the middle (mid-trial), at the end of the intervention (post-trial), and 8 weeks after the intervention (follow-up). Patients in the MSSE group showed significant improvement in their RAID and BANS-S scores compared with the individualized music group post- versus pre-trial. With regard to agitation, there was improvement during the intervention in both the MSSE and individualized music groups in the CMAI total score after 16 weeks of intervention, with no significant differences between the groups. The results suggest that MSSE could have better effects on anxiety symptoms and dementia severity in comparison with individualized music sessions in elderly patients with severe dementia.
Keywords: Affect; Aged; Aged, 80 and over; Anxiety; Cognition; Dementia; Environment; Female; Follow-Up Studies; Humans; Male; Mental Status Schedule; Music Therapy; Precision Medicine; Sensory Art Therapies; Severity of Illness Index; Treatment Outcome

Comparison of Different Matrices as Potential Quality Control Samples for Neurochemical Dementia Diagnostics. - Lelental, Natalia; Brandner, Sebastian; Kofanova, Olga; Blennow, Kaj; Zetterberg, Henrik; Andreasson, Ulf; Engelborghs, Sebastiaan; Mroczko, Barbara; Gabryelewicz, Tomasz; Teunissen, Charlotte; Mollenhauer, Brit; Parnetti, Lucilla; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Assay-vendor independent quality control (QC) samples for neurochemical dementia diagnostics (NDD) biomarkers are so far commercially unavailable. This requires that NDD laboratories prepare their own QC samples, for example by pooling leftover cerebrospinal fluid (CSF) samples. OBJECTIVE: To prepare and test alternative matrices for QC samples that could facilitate intra- and inter-laboratory QC of the NDD biomarkers. METHODS: Three matrices were validated in this study: (A) human pooled CSF, (B) Aβ peptides spiked into human prediluted plasma, and (C) Aβ peptides spiked into solution of bovine serum albumin in phosphate-buffered saline. All matrices were tested also after supplementation with an antibacterial agent (sodium azide). We analyzed short- and long-term stability of the biomarkers with ELISA and chemiluminescence (Fujirebio Europe, MSD, IBL International), and performed an inter-laboratory variability study. RESULTS: NDD biomarkers turned out to be stable in almost all samples stored at the tested conditions for up to 14 days as well as in samples stored deep-frozen (at - 80°C) for up to one year. Sodium azide did not influence biomarker stability. Inter-center variability of the samples sent at room temperature (pooled CSF, freeze-dried CSF, and four artificial matrices) was comparable to the results obtained on deep-frozen samples in other large-scale projects. CONCLUSION: Our results suggest that it is possible to replace self-made, CSF-based QC samples with large-scale volumes of QC materials prepared with artificial peptides and matrices. This would greatly facilitate intra- and inter-laboratory QC schedules for NDD measurements.
Keywords: Amyloid beta-Peptides; Animals; Anti-Bacterial Agents; Biomarkers; Cattle; Clinical Chemistry Tests; Dementia; Humans; Peptide Fragments; Quality Control; Reference Standards; Serum Albumin, Bovine; Sodium Azide; tau Proteins; Time Factors; Tissue Preservation

Comparison of Prefrontal Atrophy and Episodic Memory Performance in Dysexecutive Alzheimer's Disease and Behavioral-Variant Frontotemporal Dementia. - Wong, Stephanie; Bertoux, Maxime; Savage, Greg; Hodges, John R; Piguet, Olivier; Hornberger, Michael (J Alzheimers Dis, 2016)
Alzheimer's disease (AD) sometimes presents with prominent executive dysfunction and associated prefrontal cortex atrophy. The impact of such executive deficits on episodic memory performance as well as their neural correlates in AD, however, remains unclear. The aim of the current study was to investigate episodic memory and brain atrophy in AD patients with relatively spared executive functioning (SEF-AD; n = 12) and AD patients with relatively impaired executive functioning (IEF-AD; n = 23). We also compared the AD subgroups with a group of behavioral-variant frontotemporal dementia patients (bvFTD; n = 22), who typically exhibit significant executive deficits, and age-matched healthy controls (n = 38). On cognitive testing, the three patient groups showed comparable memory profiles on standard episodic memory tests, with significant impairment relative to controls. Voxel-based morphometry analyses revealed extensive prefrontal and medial temporal lobe atrophy in IEF-AD and bvFTD, whereas this was limited to the middle frontal gyrus and hippocampus in SEF-AD. Moreover, the additional prefrontal atrophy in IEF-AD and bvFTD correlated with memory performance, whereas this was not the case for SEF-AD. These findings indicate that IEF-AD patients show prefrontal atrophy in regions similar to bvFTD, and suggest that this contributes to episodic memory performance. This has implications for the differential diagnosis of bvFTD and subtypes of AD.
Keywords: Aged; Alzheimer Disease; Atrophy; Databases, Factual; Diagnosis, Differential; Executive Function; Female; Frontotemporal Dementia; Hippocampus; Humans; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Male; Memory, Episodic; Middle Aged; Neuropsychological Tests; Prefrontal Cortex

Concanavalin agglutinin levels are decreased in peripheral blood of Alzheimer's disease patients. - Sun, Xuying; Ma, Ronghong; Yao, Xiuqing; Shang, Xiaoling; Wang, Qun; Wang, Jian-Zhi; Liu, Gongping (J Alzheimers Dis, 2016)
Alzheimer's disease (AD) seriously threatens patients' lives and causes severe burden to the families. Early prevention and treatment can alleviate the development of the disease; therefore it is important to find new effective and non-traumatic biomarkers for early diagnosis. In this study, peripheral blood samples were collected from 24 AD patients and the same number of age- and gender-matched control subjects. Lectin reactive glycosylation levels including beta-D-galactosyl ricinus communis agglutinin 120 (RCA), peanut agglutinin (PNA), concanavalin agglutinin (Con A), alpha-L-fucosyl ulex europeus agglutinin (UEA), dolichos biflorus agglutinin (DBA), and galanthus nivalis (GNL), in the red blood cells of peripheral blood were examined by western blotting. We found that lectin levels were altered with aging and gender; some lectin levels were different between AD patients and the control subjects. Only Con A levels were significantly decreased in AD patients compared to age-matched control subjects. These results suggest that Con A levels in peripheral blood may be a potent diagnostic marker for AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Biomarkers; Case-Control Studies; Concanavalin A; Female; Humans; Lectins; Male; Plant Lectins

Cost Related to Dementia in the Young and the Impact of Etiological Subtype on Cost. - Kandiah, Nagaendran; Wang, Vivian; Lin, Xuling; Nyu, Mei Mei; Lim, Linda; Ng, Adeline; Hameed, Shahul; Wee, Hwee Lin (J Alzheimers Dis, 2016)
BACKGROUND: Young onset dementia (YOD) presents in individuals who are economically productive and socially active. While the cost related to dementia in the elderly has been widely studied, the cost related to YOD is largely unknown. OBJECTIVE: To study the economic burden of community dwelling YOD in relation to late onset dementia (LOD) and cost of YOD based on etiology. METHODS: In this prospective cross-sectional study of 255 patients attending a tertiary neurology center, data on economic burden, clinical features, and caregiver burden were collected using structured financial questionnaire, standard cognitive and neuropsychiatric measures, and Zarit caregiver burden scale. Cost components were grouped into those relating to direct medical costs, direct non-medical costs, and those related to indirect costs. Cost was also categorized based on etiology of YOD. RESULTS: The mean age at symptom onset in the YOD and LOD cohort was 57.0 (SD 5.1) and 75.0 (SD 5.9) years, respectively. The median annual cost for patients with YOD was almost twice that of LOD (USD 15,815 versus USD 8,396). Indirect cost contributed heavily to cost related to YOD. Even when grouped by dementia etiology, YOD patients with Alzheimer's disease, frontotemporal dementia (FTD), and vascular dementia had higher cost compared to their elderly counterparts. Young onset FTD had the highest cost. 43.2% of YOD reported loss of employment due to dementia, which was significantly higher than that in LOD (2.4%). CONCLUSION: Patients with YOD have a high economic burden. Young patients with FTD have the highest cost followed by vascular dementia and Alzheimer's disease.
Keywords: Age of Onset; Aged; Cohort Studies; Costs and Cost Analysis; Cross-Sectional Studies; Dementia; Female; Humans; Independent Living; Male; Mental Disorders; Middle Aged; Perceptual Disorders; Prospective Studies; Psychiatric Status Rating Scales; Severity of Illness Index; Surveys and Questionnaires; Young Adult

Course and Determinants of Anosognosia in Alzheimer's Disease: A 12-Month Follow-up. - Turró-Garriga, Oriol; Garre-Olmo, Josep; Calvó-Perxas, Laia; Reñé-Ramírez, Ramón; Gascón-Bayarri, Jordi; Conde-Sala, Josep Lluís (J Alzheimers Dis, 2016)
Anosognosia in Alzheimer's disease (AD) has been associated with greater cognitive impairment and more behavioural and psychological symptoms of dementia (BPSD). This study examines the incidence, persistence, and remission rates of anosognosia over a 12-month period, as well as the related risk factors. This was an observational 12-month prospective study. The longitudinal sample comprised 177 patients with mild or moderate AD, and their respective caregivers. Anosognosia was assessed using the Anosognosia Questionnaire in Dementia, and we also evaluated cognitive status (Mini-Mental State Examination), functional disability (Disability Assessment in Dementia), and the presence of BPSD (Neuropsychiatric Inventory). Multinomial logistic regression was used to determine the variables associated with the incidence, persistence and remission of anosognosia. The prevalence of anosognosia was 39.5% (95% CI = 32.1-47.1) at baseline. At 12 months, incidence was 38.3% (95% CI = 28.6-48.0), persistence was 80.0% (95% CI = 69.9-90.1) and remission was 20.0% (95% CI = 9.9-30.1). The regression model identified lower age, more education, and the presence of delusions as variables associated with incidence, and more education, lower instrumental DAD score, and disinhibition as variables associated with persistence. No variables were associated with remission (n = 14). The presence of anosognosia in AD patients is high. Education and certain neuropsychiatric symptoms may explain a greater and earlier incidence of anosognosia. However, anosognosia also increases with greater cognitive impairment and disease severity.
Keywords: Age Factors; Aged; Agnosia; Alzheimer Disease; Disability Evaluation; Disease Progression; Educational Status; Female; Follow-Up Studies; Humans; Incidence; Logistic Models; Longitudinal Studies; Male; Mental Status Schedule; Neuropsychological Tests; Prevalence; Prospective Studies; Risk Factors; Severity of Illness Index

Cycloheximide Treatment Causes a ZVAD-Sensitive Protease-Dependent Cleavage of Human Tau in Drosophila Cells. - Geng, Junhua; Xia, Lu; Li, Wanjie; Zhao, Changqi; Dou, Fei (J Alzheimers Dis, 2016)
Neurofibrillary tangles are the main pathological feature of Alzheimer's disease. Insoluble tau protein is the major component of neurofibrillary tangles. Defects in the tau protein degradation pathway in neurons can lead to the accumulation of tau and its subsequent aggregation. Currently, contradictory results on the tau degradation pathway have been reported by different groups. This discrepancy is most likely due to different cell lines and methods used in those studies. In this study, we found that cycloheximide treatment induced mild activation of a ZVAD-sensitive protease in Drosophila Kc cells, resulting in cleavage of tau at its C-terminus; this cleavage could generate misleading tau protein degradation pattern results depending on the antibodies used in the assay. Because cycloheximide is a broadly used chemical reagent for the study of protein degradation, the unexpected artificial effect we observed here indicates that cycloheximide is not suitable for the study of tau degradation. Other methods, such as inducible expression systems and pulse-chase assays, may be more appropriate for studying tau degradation under physiological conditions.
Keywords: Animals; Apoptosis; Caspase 3; Cell Line; Cycloheximide; Drosophila; Drosophila Proteins; Drug Evaluation, Preclinical; Humans; Oligopeptides; Peptide Hydrolases; Protease Inhibitors; Protein Synthesis Inhibitors; tau Proteins; Time

Delusions in Patients with Alzheimer's Disease: A Multidimensional Approach. - D'Onofrio, Grazia; Panza, Francesco; Sancarlo, Daniele; Paris, Francesco F; Cascavilla, Leandro; Mangiacotti, Antonio; Lauriola, Michele; Paroni, Giulia H; Seripa, Davide; Greco, Antonio (J Alzheimers Dis, 2016)
In Alzheimer's disease (AD) patients with delusions, clinical outcomes and mortality result from a combination of psychological, biological, functional, and environmental factors. We determined the effect of delusions on mortality risk, clinical outcomes linked to comprehensive geriatric assessment (CGA), cognitive, depressive, and neuropsychiatric symptoms (NPS) in 380 consecutive AD patients with Mini-Mental State Examination, Clinical Dementia Rating scale, 15-item Geriatric Depression Scale, and Neuropsychiatric Inventory (NPI), assessing one-year mortality risk using the Multidimensional Prognostic Index (MPI). We included 121 AD patients with delusions (AD-D) and 259 AD patients without delusions (AD-noD). AD-D patients were significantly older, with higher age at onset and cognitive impairment, a more severe stage of dementia, and more depressive symptoms than AD-noD patients. Disease duration was slightly higher in AD-D patients than in those without delusions, although this difference was not statistically significant. At CGA, AD-D patients showed a higher grade of disability in basic and instrumental activities of daily living, and an increased risk of malnutrition and bedsores. The two groups of patients significantly differed in MPI score (AD-D: 0.65 versus AD-noD: 0.51, p <  0.0001) and MPI grade. AD-D patients showed also a significant higher score in NPI of the following NPS than AD-noD patients: hallucinations, agitation/aggression, depression mood, apathy, irritability/lability, aberrant motor activity, sleep disturbances, and eating disorders. Therefore, AD-D patients showed higher dementia severity, and higher impairment in cognitive and depressive symptoms, and several neuropsychiatric domains than AD-noD patients, and this appeared to be associated with higher multidimensional impairment and increased risk of mortality.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Delusions; Female; Humans; Male; Mental Status Schedule; Neuropsychological Tests; Prognosis; Risk; Severity of Illness Index; Time Factors

Dementia Apraxia Test (DATE): A Brief Tool to Differentiate Behavioral Variant Frontotemporal Dementia from Alzheimer's Dementia Based on Apraxia Profiles. - Johnen, Andreas; Frommeyer, Jana; Modes, Fenja; Wiendl, Heinz; Duning, Thomas; Lohmann, Hubertus (J Alzheimers Dis, 2016)
BACKGROUND: Standardized praxis assessments with modern, empirically validated screening tests have substantially improved clinical evaluation of apraxia in patients with stroke. Although apraxia may contribute to early differential diagnosis of Alzheimer's dementia (AD) and behavioral variant frontotemporal dementia (bvFTD), no comparable test is readily available to clinicians for this purpose to date. OBJECTIVE: To design a clinically useful apraxia test for the differentiation of AD and bvFTD. METHODS: 84 test items pertaining to twelve praxis subdomains were evaluated for their efficacy to discriminate between patients with bvFTD (n = 24), AD (n = 28), and elderly healthy controls (HC; n = 35). Items were then selected based on discriminative value and psychometric properties. RESULTS: Items indicative of mild AD comprised spatially complex imitation of hand and finger postures and to a lesser degree, pantomime of common object-use. Buccofacial apraxia including imitation of face postures, emblematic face postures, and repetition of multisyllabic pseudowords differentiated bvFTD from HC and AD. The final test version consisting of 20 items proved highly efficient for the discrimination of biologically confirmed dementia patients from HC (sensitivity 91% , specificity 71%) but also for differential diagnosis of bvFTD and AD (sensitivity 74% , specificity 93%). CONCLUSIONS: Assessment of praxis profiles effectively contributes to diagnosis and differential diagnosis of AD and bvFTD. The Dementia Apraxia Test (DATE) is a brief and easy to administer cognitive tool for dementia assessment, has a high inter-rater reliability (Cohen's κ= 0.885) and demonstrates content validity.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Analysis of Variance; Apraxias; Diagnosis, Differential; Female; Frontotemporal Dementia; Humans; Male; Mental Status Schedule; Middle Aged; Neuropsychological Tests; Psychometrics; Reference Values

Depressive Symptoms and Small Hippocampal Volume Accelerate the Progression to Dementia from Mild Cognitive Impairment. - Chung, Jun Ku; Plitman, Eric; Nakajima, Shinichiro; Chakravarty, M Mallar; Caravaggio, Fernando; Takeuchi, Hiroyoshi; Gerretsen, Philip; Iwata, Yusuke; Patel, Raihaan; Mulsant, Benoit H; Graff-Guerrero, Ariel (J Alzheimers Dis, 2016)
Previous studies have highlighted that decreased hippocampal volume, an early neural correlate of dementia, is commonly observed in patients with mild cognitive impairment (MCI). However, it is unclear whether neurodegenerative and resultant clinical trajectories are accelerated in MCI patients with concomitant depressive symptoms, leading to a faster conversion to dementia stages than those who are not depressed. No longitudinal study has investigated whether depressed amnestic MCI (DEP+aMCI) patients show an earlier onset of progression to dementia than non-depressed amnestic MCI (DEP-aMCI) patients and whether progressive hippocampal volume reductions are related in the conversion process. Using data from Alzheimer's Disease Neuroimaging Initiative, we examined 2-year follow-up data from 38 DEP+aMCI patients and 38 matched DEP-aMCI patients and compared their ages of conversion from aMCI to AD and trajectories of progressive hippocampal volume changes. DEP+ and DEP- patients were defined as having baseline Geriatric Depression Scale scores of 5 or above and 0, respectively. DEP+ converters showed earlier ages of conversion to dementia (p = 0.009) and greater left hippocampal volume loss than both DEP- converters and DEP+ non-converters over the 2-year period (p = 0.003, p = 0.001, respectively). These findings could not be explained by changes in total brain volume, differences in their clinical symptoms of dementia, daily functioning, or apolipoprotein E4 genotypes. No difference in conversion rate to dementia or progressive hippocampal volume change was found between DEP+ patients and DEP-patients, which suggested depressive symptoms themselves may not lead to progression of dementia from MCI. In conclusion, there is a synergistic effect of depressive symptoms and smaller left hippocampal volume in MCI patients that accelerates conversion to dementia.
Keywords: Aged; Aged, 80 and over; Cognitive Dysfunction; Dementia; Depression; Disease Progression; Female; Hippocampus; Humans; Image Processing, Computer-Assisted; Longitudinal Studies; Magnetic Resonance Imaging; Male; Middle Aged; Psychiatric Status Rating Scales

Development and Validation of the RxDx-Dementia Risk Index to Predict Dementia in Patients with Type 2 Diabetes and Hypertension. - Mehta, Hemalkumar B; Mehta, Vinay; Tsai, Chu-Lin; Chen, Hua; Aparasu, Rajender R; Johnson, Michael L (J Alzheimers Dis, 2016)
BACKGROUND: Elderly patients with type 2 diabetes mellitus and hypertension are at high risk for developing dementia. In addition to comorbid disease conditions (Dx), prescription drugs (Rx) are important risk factors for dementia. OBJECTIVE: Develop and validate the RxDx-Dementia risk index by combining diagnosis and prescription information in a single risk index to predict incident dementia, and compare its performance with diagnosis-based Charlson comorbidity score (CCS) and prescription-based chronic disease score (CDS). METHODS: Elderly patients diagnosed with type 2 diabetes mellitus and hypertension, and without prior dementia were identified from the Clinical Practice Research Datalink (2003-2012). A Cox proportional hazard model was constructed to model the time to dementia by incorporating age, gender, and 31 RxDx disease conditions as independent variables. Points were assigned to risk factors to obtain summary risk score. Discrimination and calibration of the risk index were evaluated. Different risk indices were compared against RxDx-Dementia risk index using c-statistic, net reclassification improvement (NRI) and integrated discrimination improvement (IDI). RESULTS: Of 133,176 patients with type 2 diabetes mellitus and hypertension, 3.42% patients developed dementia.The c-statistics value for RxDx-Dementia risk index was 0.806 (95% CI, 0.799-0.812). Based on the c-statistics, NRI and IDI values, the RxDx-Dementia risk index performed better compared to CCS, CDS, and their combinations. CONCLUSION: The RxDx-Dementia risk index can be a useful tool to identify hypertensive and diabetic patients who are at high risk of developing dementia. This has implications for clinical management of patients with multiple comorbid conditions as well as risk adjustment for database studies.
Keywords: Aged; Aged, 80 and over; Cohort Studies; Dementia; Diabetes Mellitus, Type 2; Female; Humans; Hypertension; Male; Middle Aged; Predictive Value of Tests; Prescription Drugs; Proportional Hazards Models; Reproducibility of Results; Risk Assessment; Risk Factors

Development of a Standardized Approach to Disclosing Amyloid Imaging Research Results in Mild Cognitive Impairment. - Lingler, Jennifer H; Butters, Meryl A; Gentry, Amanda L; Hu, Lu; Hunsaker, Amanda E; Klunk, William E; Mattos, Meghan K; Parker, Lisa A; Roberts, J Scott; Schulz, Richard (J Alzheimers Dis, 2016)
The increased use of PET amyloid imaging in clinical research has sparked numerous concerns about whether and how to return such research test results to study participants. Chief among these is the question of how best to disclose amyloid imaging research results to individuals who have cognitive symptoms that could impede comprehension of the information conveyed. We systematically developed and evaluated informational materials for use in pre-test counseling and post-test disclosures of amyloid imaging research results in mild cognitive impairment (MCI). Using simulated sessions, persons with MCI and their family care partners (N = 10 dyads) received fictitious but realistic information regarding brain amyloid status, followed by an explanation of how results impact Alzheimer's disease risk. Satisfaction surveys, comprehension assessments, and focus group data were analyzed to evaluate the materials developed. The majority of persons with MCI and their care partners comprehended and were highly satisfied with the information presented. Focus group data reinforced findings of high satisfaction and included 6 recommendations for practice: 1) offer pre-test counseling, 2) use clear graphics, 3) review participants' own brain images during disclosures, 4) offer take-home materials, 5) call participants post-disclosure to address emerging questions, and 6) communicate seamlessly with primary care providers. Further analysis of focus group data revealed that participants understood the limitations of amyloid imaging, but nevertheless viewed the prospect of learning one's amyloid status as valuable and empowering.
Keywords: Adult; Aged; Aged, 80 and over; Alzheimer Disease; Amyloid; Brain; Brain Chemistry; Cognitive Dysfunction; Disclosure; Family; Female; Focus Groups; Health Communication; Humans; Male; Middle Aged; Patient Satisfaction; Pilot Projects; Positron-Emission Tomography

Diagnostic Impact of Cerebrospinal Fluid Biomarker (Pre-)Analytical Variability in Alzheimer's Disease. - Niemantsverdriet, Ellis; Goossens, Joery; Struyfs, Hanne; Martin, Jean-Jacques; Goeman, Johan; De Deyn, Peter Paul; Vanderstichele, Hugo; Engelborghs, Sebastiaan (J Alzheimers Dis, 2016)
Intra- and inter-laboratory variability of cerebrospinal fluid (CSF) biomarker analyses remains an important issue. We investigated the clinical-diagnostic impact of CSF biomarker concentration shifts in mild cognitive impairment (MCI) and autopsy-confirmed Alzheimer's disease (AD) dementia patients. MCI patients (n = 85), autopsy-confirmed AD dementia patients (n = 72), and cognitively healthy controls (n = 100) were included in this prospective, longitudinal study. AD dementia patients were followed up until death, and controls were included from 1992 until 2003. In-house validated cutoff values of biomarkers were applied: Aβ1-42 <638.5 pg/mL, T-tau>296.5 pg/mL, P-tau(181P) >56.5 pg/mL. Both increments and decrements (from ± 5% to ± 40% ) were added to the true (=observed) CSF biomarker values, imitating the anticipated differences in biomarker concentrations. Within certain limits, the clinical diagnostic performance of AD CSF biomarkers remains largely unchanged and clinical diagnostic accuracy deviated less than 8.2% from the reference when concentration shifts ranging between -20% and +20% were added to one of the three CSF biomarkers in MCI and autopsy-confirmed AD patients. Notwithstanding the fact that (pre- and post-)analytical parameters can affect the clinical classification, the present exploratory study provides evidence that for a specific context of use, the impact on clinical accuracy of biomarker concentration shifts might be lower than originally expected. In conclusion, induced shifts of ±20% in only one of the three biomarkers has limited impact on the clinical accuracy of AD CSF biomarkers in MCI and autopsy-confirmed AD patients when using the IWG-2 criteria.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Autopsy; Cognitive Dysfunction; Enzyme-Linked Immunosorbent Assay; Exercise; Female; Follow-Up Studies; Humans; Male; Middle Aged; Peptide Fragments; Psychiatric Status Rating Scales; Retrospective Studies; Statistics, Nonparametric; tau Proteins

Diagnostic Value of Cerebrospinal Fluid Biomarkers (Phospho-Tau181, total-Tau, Aβ42, and Aβ40) in Prodromal Stage of Alzheimer's Disease and Dementia with Lewy Bodies. - Bousiges, Olivier; Cretin, Benjamin; Lavaux, Thomas; Philippi, Nathalie; Jung, Barbara; Hezard, Sylvie; Heitz, Camille; Demuynck, Catherine; Gabel, Aurelia; Martin-Hunyadi, Catherine; Blanc, Frédéric (J Alzheimers Dis, 2016)
BACKGROUND: Dementia with Lewy bodies (DLB) symptoms are close to those of Alzheimer's disease (AD), and the differential diagnosis is difficult especially early in the disease. Unfortunately, AD biomarkers in cerebrospinal fluid (CSF), and more particularly Aβ1 - 42, appear to be altered in dementia with Lewy bodies (DLB). However, the level of these biomarkers has never been studied in the prodromal stage of the disease. OBJECTIVE: To compare these biomarkers between DLB and AD, with a particular focus on the prodromal stage. METHODS: A total of 166 CSF samples were collected at the memory clinic of Strasbourg. They were obtained from prodromal DLB (pro-DLB), DLB dementia, prodromal AD (pro-AD), and AD dementia patients, and elderly controls. Phospho-Tau181, total-Tau, Aβ42, and Aβ40 were measured in the CSF. RESULTS: At the prodromal stage, contrary to AD patients, DLB patients' biomarker levels in the CSF were not altered. At the demented stage of DLB, Aβ42 levels were reduced as well as Aβ40 levels. Thus, the Aβ42/Aβ40 ratio remained unchanged between the prodromal and demented stages, contrary to what was observed in AD. Tau and Phospho-Tau181 levels were unaltered in DLB patients. CONCLUSIONS: We have shown that at the prodromal stage the DLB patients had no pathological profile. Consequently, CSF AD biomarkers are extremely useful for differentiating AD from DLB patients particularly at this stage when the clinical diagnosis is difficult. Thus, these results open up new perspectives on the interpretation of AD biomarkers in DLB.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Enzyme-Linked Immunosorbent Assay; Female; Humans; Lewy Body Disease; Male; Middle Aged; Peptide Fragments; Prodromal Symptoms; Psychiatric Status Rating Scales; Retrospective Studies; Statistics, Nonparametric; tau Proteins

Different Expression Patterns of Amyloid-β Protein Precursor Secretases in Human and Mouse Hippocampal Neurons: A Potential Contribution to Species Differences in Neuronal Susceptibility to Amyloid-β Pathogenesis. - Xu, Zhi-Qiang; Huang, Huang; Chen, Ya-Li; Gao, Yun-Ying; Xu, Jun; Marshall, Charles; Cai, Zhi-You; Xiao, Ming (J Alzheimers Dis, 2016)
Extensive loss of hippocampal neurons serves a pathological basis for irreversible cognitive impairment in patients with Alzheimer's disease (AD). However, this characteristic cannot be replicated by transgenic mouse models, and its underlying mechanisms are unclear. Here, we present evidence that different expression patterns of amyloid-β protein precursor (AβPP) secretases in human and mouse hippocampal neurons are a decisive cause of species difference in the susceptibility to Aβ pathogenesis. Cell bodies of both pyramidal and granular neurons did not appear to undergo Aβ deposits in the 10-month-old transgenic mutant human AβPP/presenilin-1 (PS1) mice. They expressed high levels of non-amyloidogenic α-secretase, and its neuroprotective products soluble AβPPα, but low levels of amyloidogenic β-secretase and γ-secretase, and a neurotoxic product, Aβ42 peptide. Unlike those found in the mouse, human hippocampal neuronal cell bodies expressed β-secretase and γ-secretase, but not α-secretase, which could increase Aβ generation, thus undergoing death in response to various pathological conditions. Increased hippocampal neuronal apoptosis at 48 h following local microinjection of α-secretase antibody ADAM10 into the hippocampus of AβPP/PS1 mice further suggests that high α-secretase expression in mouse neuronal cell bodies is a factor in the paucity of neuronal loss in AD-like pathology. Therefore, selective down-regulation of brain α-secretase in transgenic AD models will better replicate the disease spectrum, including decreased brain soluble AβPPα levels and massive neuronal loss in AD patients, and be beneficial for preclinical therapeutic evaluation of AD.
Keywords: ADAM10 Protein; Amyloid beta-Peptides; Amyloid Precursor Protein Secretases; Animals; Antibodies; Aspartic Acid Endopeptidases; Cell Count; Dose-Response Relationship, Drug; Female; Gene Expression Regulation; Hippocampus; Humans; Low Density Lipoprotein Receptor-Related Protein-1; Male; Mice; Mice, Transgenic; Middle Aged; Mutation; Neurons; Peptide Fragments; Presenilin-1; Species Specificity; Time Factors

Differential Diagnosis of Dementia with High Levels of Cerebrospinal Fluid Tau Protein. - Grangeon, Lou; Paquet, Claire; Bombois, Stephanie; Quillard-Muraine, Muriel; Martinaud, Olivier; Bourre, Bertrand; Lefaucheur, Romain; Nicolas, Gaël; Dumurgier, Julien; Gerardin, Emmanuel; Jan, Mary; Laplanche, Jean-Louis; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Total Tau concentration in cerebrospinal fluid (CSF) is widely used as a biomarker in the diagnosis of neurodegenerative process primarily in Alzheimer's disease (AD). A particularly high Tau level may indicate AD but may also be associated with Creutzfeldt-Jakob disease (CJD). In such situations little is known about the distribution of differential diagnoses. OBJECTIVE: Our study aimed to describe the different diagnoses encountered in clinical practice for patients with dementia and CSF Tau levels over 1000 pg/ml. We studied the p-Tau/Tau ratio to specify its ability to distinguish AD from CJD. METHODS: Patients (n = 202) with CSF Tau levels over 1000 pg/ml were recruited in three memory clinics in France. All diagnoses were made using the same diagnostic procedure and criteria. RESULTS: Patients were diagnosed with AD (n = 148, 73.2%), mixed dementia (n = 38, 18.8%), CJD, vascular dementia (n = 4, 2.0% for each), Lewy body dementia, and frontotemporal dementia (n = 3, 1.5% for each). Dispersion of CSF Tau levels clearly showed an overlap between all diagnoses. Using the p-Tau/Tau ratio suggestive of CJD (<0.075), all CJD patients were correctly categorized and only two AD patients were miscategorized. This ratio was highly associated with CJD compared to AD (p < 0.0001). CONCLUSION: Our study showed that in clinical practice, extremely high CSF Tau levels are mainly related to diagnosis of AD. CJD patients represent a minority. Our results support a sequential interpretation algorithm for CSF biomarkers in dementia. High CSF Tau levels should alert clinicians to check the p-Tau/Tau ratio to consider a probable diagnosis of CJD.
Keywords: Adult; Age of Onset; Aged; Aged, 80 and over; Alzheimer Disease; Biomarkers; Creutzfeldt-Jakob Syndrome; Dementia, Vascular; Diagnosis, Differential; Female; France; Frontotemporal Dementia; Humans; Lewy Body Disease; Male; Mental Status Schedule; Middle Aged; Phosphorylation; Retrospective Studies; Sex Factors; tau Proteins

Differential Mass Spectrometry Profiles of Tau Protein in the Cerebrospinal Fluid of Patients with Alzheimer's Disease, Progressive Supranuclear Palsy, and Dementia with Lewy Bodies. - Barthélemy, Nicolas R; Gabelle, Audrey; Hirtz, Christophe; Fenaille, François; Sergeant, Nicolas; Schraen-Maschke, Susanna; Vialaret, Jérôme; Buée, Luc; Junot, Christophe; Becher, François; Lehmann, Sylvain (J Alzheimers Dis, 2016)
Microtubule-associated Tau proteins are major actors in neurological disorders, the so-called tauopathies. In some of them, and specifically in Alzheimer's disease (AD), hyperphosphorylated forms of Tau aggregate into neurofibrillary tangles. Following and understanding the complexity of Tau's molecular profile with its multiple isoforms and post-translational modifications represent an important issue, and a major analytical challenge. Immunodetection methods are, in fact, limited by the number, specificity, sensitivity, and capturing property of the available antibodies. Mass spectrometry (MS) has recently allowed protein quantification in complex biological fluids using isotope-labeled recombinant standard for absolute quantification (PSAQ). To study Tau proteins, which are found at very low concentrations within the cerebrospinal fluid (CSF), we relied on an innovative two-step pre-fractionation strategy, which was not dependent on immuno-enrichment. We then developed a sensitive multiplex peptide detection capability using targeted high-resolution MS to quantify Tau-specific peptides covering its entire sequence. This approach was used on a clinical cohort of patients with AD, progressive supranuclear palsy (PSP), and dementia with Lewy body (DLB) and with control non-neurodegenerative disorders. We uncovered a common CSF Tau molecular profile characterized by a predominance of central core expression and 1N/3R isoform detection. While PSP and DLB tau profiles showed minimal changes, AD was characterized by a unique pattern with specific modifications of peptide distribution. Taken together these results provide important information on Tau biology for future therapeutic interventions, and improved molecular diagnosis of tauopathies.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Analysis of Variance; Chromatography, Liquid; Enzyme-Linked Immunosorbent Assay; Female; Humans; Lewy Body Disease; Male; Mental Status Schedule; Middle Aged; Neuroimaging; Neuropsychological Tests; Peptide Fragments; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; Statistics as Topic; Supranuclear Palsy, Progressive; tau Proteins

Differential Membrane Toxicity of Amyloid-β Fragments by Pore Forming Mechanisms. - Peters, Christian; Bascuñán, Denisse; Opazo, Carlos; Aguayo, Luis G (J Alzheimers Dis, 2016)
A major characteristic of Alzheimer's disease (AD) is the presence of amyloid-β peptide (Aβ) oligomers and aggregates in the brain. It is known that Aβ oligomers interact with the neuronal membrane and induce perforations that cause an influx of calcium ions and enhance the release of synaptic vesicles leading to a delayed synaptic failure by vesicle depletion. To better understand the mechanism by which Aβ exerts its effect on the plasma membrane, we evaluated three Aβ fragments derived from different regions of Aβ(1-42); Aβ(1-28) from the N-terminal region, Aβ(25-35) from the central region, and Aβ(17-42) from the C-terminal region. The neuronal activities of these fragments were examined with patch clamp, immunofluorescence, transmission electron microscopy, aggregation assays, calcium imaging, and MTT reduction assays. The present results indicate that the fragment Aβ(1-28) contributes to aggregation, an increase in intracellular calcium and synaptotoxicity, but is not involved in membrane perforation; Aβ(25-35) is important for membrane perforation, calcium increase, and synaptotoxicity; and Aβ(17-42) induced mitochondrial toxicity similar to the full length Aβ(1-42), but was unable to induce membrane perforation and calcium increase, supporting the idea that it is less toxic in the non-amyloidogenic pathway.
Keywords: Amyloid beta-Peptides; Animals; Calcium; Cell Membrane; Cells, Cultured; Fluorescent Antibody Technique; HEK293 Cells; Hippocampus; Humans; Microscopy, Electron, Transmission; Neurons; Patch-Clamp Techniques; Peptide Fragments; Porosity; Rats, Sprague-Dawley; Voltage-Sensitive Dye Imaging

Differential Regulation of N-Methyl-D-Aspartate Receptor Subunits is an Early Event in the Actions of Soluble Amyloid-β(1-40) Oligomers on Hippocampal Neurons. - Chang, Lirong; Zhang, Yali; Liu, Jinping; Song, Yizhi; Lv, Angchu; Li, Yan; Zhou, Wei; Yan, Zhen; Almeida, Osborne F X; Wu, Yan (J Alzheimers Dis, 2016)
Synaptic dysfunction during early stages of Alzheimer's disease (AD) is triggered by soluble amyloid-β (Aβ) oligomers that interact with NMDA receptors (NMDARs). We previously showed that Aβ induces synaptic protein loss through NMDARs, albeit through undefined mechanisms. Accordingly, we here examined the contribution of individual NMDAR subunits to synaptotoxicity and demonstrate that Aβ exerts differential effects on the levels and distribution of GluN2A and GluN2B subunits of NMDAR in dendrites. Treatment of cultured hippocampal neurons with Aβ1-40 (10 μM, 1 h) induced a significant increase of dendritic and synaptic GluN2B puncta densities with parallel decreases in the puncta densities of denritic and synaptic pTyr1472-GluN2B. Conversely, Aβ significantly decreased dendritic and synaptic GluN2A and dendritic pTyr1325-GluN2A puncta densities and increased synaptic pTyr1325-GluN2A puncta densities. Unexpectedly, Aβ treatment resulted in a significant reduction of GluN2B and pTyr1472-GluN2B protein levels but did not influence GluN2A and pTyr1325-GluN2A levels. These results show that Aβ exerts complex and distinct regulatory effects on the trafficking and phosphorylation of GluN2A and GluN2B, as well as on their localization within synaptic and non-synaptic sites. Increased understanding of these early events in Aβ-induced synaptic dysfunction is likely to be important for the development of timely preventive and therapeutic interventions.
Keywords: Amyloid beta-Peptides; Animals; Animals, Newborn; Cells, Cultured; Dendrites; Gene Expression Regulation; Hippocampus; Male; Neurons; Peptide Fragments; Phosphorylation; Rats; Rats, Wistar; Receptors, N-Methyl-D-Aspartate

Diminished CRE-Induced Plasticity is Linked to Memory Deficits in Familial Alzheimer's Disease Mice. - Bartolotti, Nancy; Segura, Laura; Lazarov, Orly (J Alzheimers Dis, 2016)
The mechanism underlying impaired learning and memory in Alzheimer's disease is not fully elucidated. The phosphorylation of cyclic-AMP response element binding protein (pCREB) in the hippocampus is thought to be a critical initiating step in the formation of long-term memories. Here, we tested CRE-driven gene expression following learning in mice harboring the familial Alzheimer's disease-linked APPswe/PS1ΔE9 mutations using CRE-β galactosidase reporter. We show that young adult APPswe/PS1ΔE9 mice exhibit impaired recognition memory and reduced levels of pCREB, and its cofactors CREB binding protein (CBP) and p-300 following a learning task, compared to their wild type littermate counterparts. Impairments in learning-induced activation of CREB in these mice are manifested by reduced CRE-driven gene transcription. Importantly, expression of the CRE-driven immediate early gene, Egr-1 (Zif268) is decreased in the CA1 region of the hippocampus. These studies implicate defective CREB-dependent plasticity in the mechanism underlying learning and memory deficits in Alzheimer's disease.
Keywords: Alzheimer Disease; Animals; Cyclic AMP Response Element-Binding Protein; Disease Models, Animal; Hippocampus; Maze Learning; Memory Disorders; Mice; Neuronal Plasticity; Neurons; Phosphorylation

Direct Evidence of Internalization of Tau by Microglia In Vitro and In Vivo. - Bolós, Marta; Llorens-Martín, María; Jurado-Arjona, Jerónimo; Hernández, Félix; Rábano, Alberto; Avila, Jesús (J Alzheimers Dis, 2016)
The microtubule-associated protein (MAP) tau plays a critical role in the pathogenesis of tauopathies. Excess tau can be released into the extracellular medium in a physiological or pathological manner to be internalized by surrounding neurons-a process that contributes to the spread of this protein throughout the brain. Such spreading may correlate with the progression of the abovementioned diseases. In addition to neurons, tau can be internalized into other cells. Here we demonstrate that microglia take up tau in vitro and in vivo. In this regard, microglia from primary cultures internalized soluble (human recombinant tau42) and insoluble (homogenates derived from human AD brain) tau in vitro. Furthermore, using stereotaxic injection of tau in mice in vivo, we show that murine microglia internalize human tau. In addition, we demonstrate, for the first time, that microglia colocalize with various forms of tau in postmortem brain tissue of patients with Alzheimer's disease and non-demented control subjects. Our data reveal a potential role of microglia in the internalization of tau that might be relevant for the design of strategies to enhance the clearance of extracellular tau in neurodegenerative diseases characterized by the accumulation of this protein.
Keywords: Alzheimer Disease; Analysis of Variance; Animals; Animals, Newborn; Calcium-Binding Proteins; Cells, Cultured; Cerebral Cortex; Glial Fibrillary Acidic Protein; Hippocampus; Humans; Mice; Mice, Inbred C57BL; Microfilament Proteins; Microglia; Phosphorylation; Protein Transport; Rats; tau Proteins; Time Factors

The Disconnection Hypothesis in Alzheimer's Disease Studied Through Multimodal Magnetic Resonance Imaging: Structural, Perfusion, and Diffusion Tensor Imaging. - Lacalle-Aurioles, María; Navas-Sánchez, Francisco Javier; Alemán-Gómez, Yasser; Olazarán, Javier; Guzmán-De-Villoria, Juan Adán; Cruz-Orduña, Isabel; Mateos-Pérez, José María; Desco, Manuel (J Alzheimers Dis, 2016)
According to the so-called disconnection hypothesis, the loss of synaptic inputs from the medial temporal lobes (MTL) in Alzheimer's disease (AD) may lead to reduced activity of target neurons in cortical areas and, consequently, to decreased cerebral blood flow (CBF) in those areas. The aim of this study was to assess whether hypoperfusion in parietotemporal and frontal cortices of patients with mild cognitive impairment who converted to AD (MCI-c) and patients with mild AD is associated with atrophy in the MTL and/or microstructural changes in the white matter (WM) tracts connecting these areas. We assessed these relationships by investigating correlations between CBF in hypoperfused areas, mean cortical thickness in atrophied regions of the MTL, and fractional anisotropy (FA) in WM tracts. In the MCI-c group, a strong correlation was observed between CBF of the superior parietal gyri and FA in the parahippocampal tracts (left: r = 0.90, p <  0.0001; right: r = 0.597, p = 0.024), and between FA in the right parahippocampal tract and the right precuneus (r = 0.551, p = 0.041). No significant correlations between CBF in hypoperfused regions and FA in the WM tract were observed in the AD group. These results suggest an association between perfusion deficits and altered WM tracts in prodromal AD, while microvasculature impairments may have a greater influence in more advanced stages. We did not find correlations between cortical thinning in the medial temporal lobes and decreased FA in the WM tracts of the limbic system in either group.
Keywords: Aged; Alzheimer Disease; Brain; Brain Mapping; Cerebral Angiography; Cerebrovascular Circulation; Cognitive Dysfunction; Diffusion Tensor Imaging; Female; Functional Laterality; Humans; Magnetic Resonance Imaging; Male; Mental Status Schedule; Models, Neurological; Multimodal Imaging; Organ Size; Prospective Studies

Discovery and Subsequent Confirmation of Novel Serum Biomarkers Diagnosing Alzheimer's Disease. - Shah, Dipti Jigar; Rohlfing, Frederick; Anand, Swati; Johnson, W Evan; Alvarez, MeiHwa Tanielle Bench; Cobell, Jesse; King, Jackson; Young, Sydney A; Kauwe, John S K; Graves, Steven W (J Alzheimers Dis, 2016)
BACKGROUND: Alzheimer's disease (AD) remains challenging to diagnose, especially early disease. Having serum AD biomarkers would be of significant interest both in the clinical setting and in drug development efforts. OBJECTIVE: We applied a novel serum proteomic approach to interrogate the low-molecular weight proteome for serum AD biomarkers. METHODS: A discovery study used sera from 58 any-stage AD cases and 55 matched controls analyzed by capillary liquid chromatography-electrospray ionization-tandem mass spectrometry. Candidate biomarkers were statistically modeled and promising biomarkers were retested in a second, blinded confirmatory study (AD cases = 68, controls = 57). Biomarkers that replicated in the second study were modeled for the diagnosis of any-stage and very early stage AD. Further, they were chemically identified by tandem MS. RESULTS: The initial discovery study found 59 novel potential AD biomarkers. Thirteen recurred in more than one multi-marker panel. In a second, blinded, confirmatory study, these same biomarkers were retested in separate specimens. In that study, four markers validated comparing controls to patients with any-stage AD and also with very early AD. The four biomarkers with replicable ability to diagnose AD were then chemically identified. CONCLUSION: These results suggest novel serum AD diagnostic biomarkers can be found using this approach.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Biomarkers; Case-Control Studies; Chromatography, Liquid; Female; Humans; Male; Psychiatric Status Rating Scales; Reproducibility of Results; ROC Curve; Tandem Mass Spectrometry

Distinctive Resting State Network Disruptions Among Alzheimer's Disease, Subcortical Vascular Dementia, and Mixed Dementia Patients. - Kim, Hee Jin; Cha, Jungho; Lee, Jong-Min; Shin, Ji Soo; Jung, Na-Yeon; Kim, Yeo Jin; Choe, Yearn Seong; Lee, Kyung Han; Kim, Sung Tae; Kim, Jae Seung; Lee, Jae Hong; Na, Duk L; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Recent advances in resting-state functional MRI have revealed altered functional networks in Alzheimer's disease (AD), especially those of the default mode network (DMN) and central executive network (CEN). However, few studies have evaluated whether small vessel disease (SVD) or combined amyloid and SVD burdens affect the DMN or CEN. OBJECTIVE: The aim of this study was to evaluate whether SVD or combined amyloid and SVD burdens affect the DMN or CEN. METHODS: In this cross-sectional study, we investigated the resting-state functional connectivity within DMN and CEN in 37 Pittsburgh compound-B (PiB)(+) AD, 37 PiB(-) subcortical vascular dementia (SVaD), 13 mixed dementia patients, and 65 normal controls. RESULTS: When the resting-state DMN of PiB(+) AD and PiB(-) SVaD patients were compared, the PiB(+) AD patients displayed lower functional connectivity in the inferior parietal lobule while the PiB(-) SVaD patients displayed lower functional connectivity in the medial frontal and superior frontal gyri. Compared to the PiB(-) SVaD or PiB(+) AD, the mixed dementia patients displayed lower functional connectivity within the DMN in the posterior cingulate gyrus. When the resting-state CEN connectivity of PiB(+) AD and PiB(-) SVaD patients were compared, the PiB(-) SVaD patients displayed lower functional connectivity in the anterior insular region. Compared to the PiB(-) SVaD or PiB(+) AD, the mixed dementia patients displayed lower functional connectivity within the CEN in the inferior frontal gyrus. CONCLUSIONS: Our findings suggest that in PiB(+) AD and PiB(-) SVaD, there is divergent disruptions in resting-state DMN and CEN. Furthermore, patients with combined amyloid and SVD burdens exhibited more disrupted resting-state DMN and CEN than patients with only amyloid or SVD burden.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Aniline Compounds; Cerebral Cortex; Cross-Sectional Studies; Dementia; Dementia, Vascular; Female; Humans; Image Processing, Computer-Assisted; Male; Middle Aged; Models, Neurological; Neural Pathways; Neuropsychological Tests; Oxygen; Psychiatric Status Rating Scales; Radionuclide Imaging; Rest; Thiazoles

Diversity of Cognitive Phenotypes Associated with C9ORF72 Hexanucleotide Expansion. - Gómez-Tortosa, Estrella; Prieto-Jurczynska, Cristina; Serrano, Soledad; Franco-Macías, Emilio; Olivié, Laura; Gallego, Jesús; Guerrero-López, Rosa; Trujillo-Tiebas, María José; Ayuso, Carmen; García Ruiz, Pedro; Pérez-Pérez, Julián; Sainz, María José (J Alzheimers Dis, 2016)
For diagnostic purposes, we screened for the C9ORF72 mutation in a) 162 FTLD cases, and b) 145 cases with other diagnoses but with some frontotemporal features or manifestations previously reported in C9 carriers. Ten cases (onset 50 to 75 years) harbored the expansion: seven had FTLD syndromes (4.3% of total, 11% of familial cases), and three (2%) had a different diagnosis. All positive cases had family history of dementia, psychiatric disease, or ALS, but only 20% of families with mixed FTLD/ALS phenotypes carried the expansion. Language impairment was the most common symptom, followed by behavioral changes, memory deficits, and parkinsonism. C9ORF72 mutation has a low frequency in our dementia series and very diverse clinical manifestations.
Keywords: Adult; Age of Onset; Apolipoprotein E4; Cognition; DNA Repeat Expansion; Family; Female; Follow-Up Studies; Frontotemporal Lobar Degeneration; Genetic Association Studies; Genetic Predisposition to Disease; Genotyping Techniques; Humans; Male; Middle Aged; Prevalence; Proteins; Spain

Does Microglial Activation Influence Hippocampal Volume and Neuronal Function in Alzheimer's Disease and Parkinson's Disease Dementia? - Femminella, Grazia D; Ninan, Siddharth; Atkinson, Rebecca; Fan, Zhen; Brooks, David J; Edison, Paul (J Alzheimers Dis, 2016)
BACKGROUND: The influence of neuroinflammation on neuronal function and hippocampal atrophy in Alzheimer's disease (AD) and Parkinson's disease dementia (PDD) is still unclear. OBJECTIVES: Here we investigated whether microglial activation measured by [11C]PK11195 PET is associated with neuronal function measured by cerebral glucose metabolic rate (rCMRGlc) using FDG-PET and hippocampal volume measurements. METHODS: We enrolled 25 subjects (9 PDD, 8 AD, and 8 controls) who underwent PET scans with [11C](R)PK11195, [18F]FDG, and volumetric MRI scanning. RESULTS: SPM correlation analysis in AD and PDD showed a negative correlation between hippocampal volume and microglial activation within hippocampus or parahippocampus and with cortical and subcortical areas of projections from hippocampus, while there was a positive correlation between rCMRGlc in cortical and subcortical areas of projections from hippocampus and hippocampal volume. Hippocampal volume was significantly reduced in AD compared to controls but not in PDD. CONCLUSIONS: These findings indicate that microglial activation inversely correlated with hippocampal volume and hippocampal rCMRGlc in neurodegenerative diseases with dementia, providing further evidence for the central role of microglial activation in neurodegenerative diseases.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Antineoplastic Agents; Brain Mapping; Cognition; Female; Fluorodeoxyglucose F18; Hippocampus; Humans; Isoquinolines; Magnetic Resonance Imaging; Male; Microglia; Middle Aged; Neurons; Neuropsychological Tests; Parkinson Disease; Positron-Emission Tomography; Psychiatric Status Rating Scales; Supranuclear Palsy, Progressive

Dogs with Cognitive Dysfunction as a Spontaneous Model for Early Alzheimer's Disease: A Translational Study of Neuropathological and Inflammatory Markers. - Schütt, Trine; Helboe, Lone; Pedersen, Lars Østergaard; Waldemar, Gunhild; Berendt, Mette; Pedersen, Jan Torleif (J Alzheimers Dis, 2016)
Aged companion dogs with canine cognitive dysfunction (CCD) spontaneously develop varying degrees of progressive cognitive decline and particular neuropathological features correspondent to the changes associated with Alzheimer's disease (AD) in humans. The aim of the present study was to characterize certain aspects of neuropathology and inflammatory markers related to aging and CCD in dogs in comparison with human AD. Fifteen brains from aged dogs with normal cognitive function, mild cognitive impairment, or CCD were investigated and compared with two control brains from young dogs and brain sections from human AD subjects. The neuropathological investigations included evaluation of amyloid-β (Aβ) plaque deposition (N-terminally truncated and pyroglutamyl-modified Aβ included), tau pathology, and inflammatory markers in prefrontal cortex. Cortical Aβ deposition was found to be only of the diffuse subtype as no dense-core or neuritic plaques were found. The Aβ deposition followed a progressive pattern in four maturation stages. Accumulation of the Aβ peptide was also observed in the vessel walls. Both immunohistochemically and biochemically measured levels of Aβ pathology in prefrontal cortex showed a consistent positive correlation to age but not to cognitive deficit severity. No evidence of neurofibrillary tau pathology was found. The level of pro-inflammatory cytokines was generally low and showed no significant association to cognitive status. The findings of the present study support the senescent dog with spontaneous cognitive dysfunction as a valuable non-transgenic model for further investigations of the molecular events involved in the neurodegenerative processes associated with aging and early stage AD, especially the Aβ-related pathology.
Keywords: Aging; Alzheimer Disease; Animals; Brain; Cognitive Dysfunction; Cytokines; Denmark; Disease Models, Animal; Disease Progression; Dog Diseases; Dogs; Female; Humans; Immunohistochemistry; Longitudinal Studies; Male; Plaque, Amyloid; Severity of Illness Index; Species Specificity; tau Proteins; Translational Medical Research

Dose-Dependent Neuroprotection and Neurotoxicity of Simvastatin through Reduction of Farnesyl Pyrophosphate in Mice Treated with Intracerebroventricular Injection of Aβ 1-42. - Jin, Huafeng; Chen, Tingting; Li, Guoxi; Wang, Conghui; Zhang, Baofeng; Cao, Xinyuan; Sha, Sha; Wan, Qi; Chen, Ling (J Alzheimers Dis, 2016)
BACKGROUND: Simvastatin (SV) has been reported to improve dementia and slow progression of Alzheimer's disease (AD), however there are conflicting reports. OBJECTIVE & METHODS: Intracerebroventricular injection of aggregated Aβ1-42 in mice (Aβ1-42-mice) caused spatial cognitive deficits, long-term potentiation (LTP) impairment, and death of hippocampal pyramidal cells. The present study focused on exploring the dose-dependent effects of SV (10-80 mg/kg) on Aβ1-42-impaired spatial memory and the underlying mechanisms. RESULTS: The treatment of Aβ1-42-mice with SV for continuous 15 days could attenuate the spatial cognitive deficits and recover the LTP induction in a "U" type dose-dependent manner. The death of pyramidal cells in Aβ1-42-mice was significantly reduced by the SV-treatment at 20 mg/kg, but not at a dose of 10 or 40 mg/kg, even was aggravated at a dose of 80 mg/kg. Hippocampal NMDA receptor (NMDAr) NR2B phosphorylation (phospho-NR2B) was elevated in Aβ1-42-mice, which was further dose-dependently increased by SV-treatment. Replenishment of isoprenoid farnesyl pyrophosphate (FPP) by applying farnesol (FOH) could abolish the SV-increased phospho-NR2B in Aβ1-42-mice, but had no effect on the Aβ1-42-enhanced phospho-NR2B. NMDAr antagonist blocked the neurotoxicity of Aβ1-42 and SV (80 mg/kg) in Aβ1-42-mice, whereas FOH only inhibited SV (80 mg/kg)-neurotoxicity. The SV-treatment in Aβ1-42-mice corrected the decrease in hippocampal Akt phosphorylation. The PI3K inhibitor abolished the SV (20 mg/kg)-neuroprotection in Aβ1-42-mice. CONCLUSION: SV-treatment in Aβ1-42-mice exerts dose-dependent neuroprotection and neurotoxicity by reducing FPP to enhance the phosphorylation of NR2B and Akt.
Keywords: Amyloid beta-Peptides; Animals; Dose-Response Relationship, Drug; Hippocampus; Injections, Intraventricular; Male; Maze Learning; Mice; Neuroprotective Agents; Peptide Fragments; Phosphorylation; Polyisoprenyl Phosphates; Receptors, N-Methyl-D-Aspartate; Sesquiterpenes; Simvastatin; Spatial Memory

Drivers: A Biologically Contextualized, Cross-Inferential View of the Epidemiology of Neurodegenerative Disorders. - de Pedro-Cuesta, Jesús; Martínez-Martín, Pablo; Rábano, Alberto; Alcalde-Cabero, Enrique; José García López, Fernando; Almazán-Isla, Javier; Ruiz-Tovar, María; Medrano, Maria-José; Avellanal, Fuencisla; Calero, Olga; Calero, Miguel (J Alzheimers Dis, 2016)
BACKGROUND: Sutherland et al. (2011) suggested that, instead of risk factors for single neurodegenerative disorders (NDDs), there was a need to identify specific "drivers", i.e., risk factors with impact on specific deposits, such as amyloid-β, tau, or α-synuclein, acting across entities. OBJECTIVES AND METHODS: Redefining drivers as "neither protein/gene- nor entity-specific features identifiable in the clinical and general epidemiology of conformational NDDs (CNDDs) as potential footprints of templating/spread/transfer mechanisms", we conducted an analysis of the epidemiology of ten CNDDs, searching for patterns. RESULTS: We identified seven potential drivers, each of which was shared by at least two CNDDs: 1) an age-at-exposure-related susceptibility to Creutzfeldt-Jakob disease (CJD) and several late-life CNDDs; 2) a relationship between age at onset, survival, and incidence; 3) shared genetic risk factors for CJD and late-life CNNDs; 4) partly shared personal (diagnostic, educational, behavioral, and social risk factors) predating clinical onset of late-life CNDDs; 5) two environmental risk factors, namely, surgery for sporadic CJD and amyotrophic lateral sclerosis, and Bordetella pertussis infection for Parkinson's disease; 6) reticulo-endothelial system stressors or general drivers (andropause or premenopausal estrogen deficiency, APOEɛ4, and vascular risk factors) for late-life CNDDs such as dementia/Alzheimer's disease, type-2 diabetes mellitus, and some sporadic cardiac and vascular degenerative diseases; and 7) a high, invariant incidence ratio of sporadic to genetic forms of mid- and late-life CNDDs, and type-2 diabetes mellitus. CONCLUSION: There might be a systematic epidemiologic pattern induced by specific proteins (PrP, TDP-43, SOD1, α-synuclein, amyloid-β, tau, Langerhans islet peptide, and transthyretin) or established combinations of these.
Keywords: Age Factors; Aging; Amyloid Precursor Protein Secretases; Apolipoproteins E; Aspartic Acid Endopeptidases; Creutzfeldt-Jakob Syndrome; Environment; Female; Humans; Incidence; Male; Neurodegenerative Diseases; Personality; Risk Factors; Vascular Diseases

Dysregulation and diagnostic potential of microRNA in Alzheimer's disease. - Pan, Yaoqian; Liu, Ruizhu; Terpstra, Erin; Wang, Yanqing; Qiao, Fangfang; Wang, Jin; Tong, Yigang; Pan, Bo (J Alzheimers Dis, 2016)
Alzheimer's disease (AD) is one of the most common neurodegenerative diseases and is considered to be the main cause of cognitive impairment in elderly people. The major symptom of AD is progressive dementia that eventually results in dysfunction of daily life. Due to the fact that AD has a long period of incubation before clinical symptoms emerge, the available therapeutic treatments can only improve the symptoms but not delay the progression of AD. Therefore, there is an urgent need to explore effective diagnostic approaches to catch and better treat the disease before clinical symptoms appear. Recent research revealed that abnormal expression of certain miRNA could have a crucial role in the pathological process of neurodegenerative disease including AD. Furthermore, given that AD patients show increased level of miRNAs in the blood and cerebrospinal fluid, miRNAs are considered promising non-invasive candidates for AD diagnosis and prognosis. Here, we reviewed the current research related to implications of miRNAs during the development of AD, summarized of actively used approaches to identifying potential miRNA biomarkers in body fluids, and discussed the diagnostic potential of microRNAs as biomarkers for AD.
Keywords: Aged; Alzheimer Disease; Biomarkers; Disease Progression; Humans; MicroRNAs; Prognosis

Early in vivo Effects of the Human Mutant Amyloid-β Protein Precursor (hAβPPSwInd) on the Mouse Olfactory Bulb. - Rusznák, Zoltán; Kim, Woojin Scott; Hsiao, Jen-Hsiang T; Halliday, Glenda M; Paxinos, George; Fu, YuHong (J Alzheimers Dis, 2016)
The amyloid-β protein precursor (AβPP) has long been linked to Alzheimer's disease (AD). Using J20 mice, which express human AβPP with Swedish and Indiana mutations, we studied early pathological changes in the olfactory bulb. The presence of AβPP/amyloid-β (Aβ) was examined in mice aged 3 months (before the onset of hippocampal Aβ deposition) and over 5 months (when hippocampal Aβ deposits are present). The number of neurons, non-neurons, and proliferating cells was assessed using the isotropic fractionator method. Our results demonstrate that although AβPP is overexpressed in some of the mitral cells, widespread Aβ deposition and microglia aggregates are not prevalent in the olfactory bulb. The olfactory bulbs of the younger J20 group harbored significantly fewer neurons than those of the age-matched wild-type mice (5.57±0.13 million versus 6.59±0.36 million neurons; p = 0.011). In contrast, the number of proliferating cells was higher in the young J20 than in the wild-type group (i.e., 6617±425 versus 4455±623 cells; p = 0.011). A significant increase in neurogenic activity was also observed in the younger J20 olfactory bulb. In conclusion, our results indicate that (1) neurons participating in the mouse olfactory function overexpress AβPP; (2) the cellular composition of the young J20 olfactory bulb is different from that of wild-type littermates; (3) these differences may reflect altered neurogenic activity and/or delayed development of the J20 olfactory system; and (4) AβPP/Aβ-associated pathological changes that take place in the J20 hippocampus and olfactory bulb are not identical.
Keywords: Age Factors; Alzheimer Disease; Amyloid beta-Peptides; Amyloid beta-Protein Precursor; Animals; Cell Proliferation; Disease Models, Animal; Gene Expression Regulation; Humans; Ki-67 Antigen; Mice; Mice, Inbred C57BL; Mice, Transgenic; Mutation; Nerve Tissue Proteins; Neurogenesis; Neurons; Olfactory Bulb; Piriform Cortex

Early-Life Exposure to Lead (Pb) Alters the Expression of microRNA that Target Proteins Associated with Alzheimer's Disease. - Masoud, Anwar M; Bihaqi, Syed W; Machan, Jason T; Zawia, Nasser H; Renehan, William E (J Alzheimers Dis, 2016)
There is a growing recognition of the impact of environmental toxins on the epigenetic regulation of gene expression, including the genes that play a critical role in neural development, neural function, and neurodegeneration. We have shown previously that exposure to the heavy metal lead (Pb) in early life results in a latent over-expression of AD-related proteins in rodents and primates. The present study provides evidence that early postnatal exposure to Pb also alters the expression of select miRNA. Mice were exposed to 0.2% Pb acetate from Postnatal Day 1 (PND 1, first 24 h after birth) to PND 20 via their mother's milk. Brain tissue was harvested at PND 20, 180, or 700, and miRNA were isolated and quantified by qPCR. This exposure produced a transient increase (relative to control) in the expression of miR-106b (binds to AβPP mRNA), miR-29b (targets the mRNA for the transcription factor SP1) and two miRNAs (miR-29b and miR-132) that have the ability to inhibit translation of proteins involved in promoter methylation. The expression of miR-106b decreased over time in the Pb-exposed animals and was significantly less than the levels exhibited by the control animals at PND700. The level of miR-124, which binds to SP1 mRNA, was also reduced (relative to controls) at PND700. In summary, we show that exposure to the heavy metal Pb in early life has a significant impact on the short- and long-term expression of miRNA that target epigenetic mediators and neurotoxic proteins.
Keywords: Age Factors; Amyloid beta-Protein Precursor; Animals; Animals, Newborn; Disease Models, Animal; Dose-Response Relationship, Drug; Female; Gene Expression Regulation, Developmental; Lead; Male; Mice; Mice, Inbred C57BL; MicroRNAs; Pregnancy; RNA, Messenger; Sp1 Transcription Factor

Economic Analysis of Formal Care, Informal Care, and Productivity Losses in Primary Care Patients who Screened Positive for Dementia in Germany. - Michalowsky, Bernhard; Thyrian, Jochen René; Eichler, Tilly; Hertel, Johannes; Wucherer, Diana; Flessa, Steffen; Hoffmann, Wolfgang (J Alzheimers Dis, 2016)
BACKGROUND: The majority of people with dementia (PwD) live at home and require professional formal care and informal care that is generally provided by close relatives. OBJECTIVE: To determine the utilization and costs of formal and informal care for PwD, indirect costs because of productivity losses of caregivers, and the associations between cost, socio-demographic and clinical variables. METHODS: The analysis includes the data of 262 community-dwelling PwD and their caregivers. Socio-demographics, clinical variables, and the utilization of formal care were assessed within the baseline assessment. To evaluate informal care costs, the Resource Utilization in Dementia (RUD) questionnaire was used. Costs were calculated from a social perspective. Associations were evaluated using multiple linear and logistic regression models. RESULTS: Formal care services were utilized less (26.3%) than informal care (85.1%), resulting in a cost ratio of one to ten(1,646 €; 16,473 €, respectively). In total, 29% of caregivers were employed, and every seventh (14.3%) experienced productivity losses, which corresponded to 1,258 € annually. Whereas increasing deficits in daily living activities were associated with higher formal and higher informal costs, living alone was significantly associated with higher formal care costs and the employment of a caregiver was associated with lower informal care costs. CONCLUSION: Informal care contributes the most to total care costs. Living alone is a major cost driver for formal costs because of the lower availability of potential informal care. The availability of informal care is limited and productivity losses are increased when a caregiver is employed.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Caregivers; Cost of Illness; Cross-Sectional Studies; Dementia; Female; Germany; Health Care Costs; Home Care Services; Humans; Male; Patient Care; Sensitivity and Specificity; Surveys and Questionnaires

Effect of Continuous Propofol Infusion in Rat on Tau Phosphorylation with or without Temperature Control. - Huang, Chunxia; Ng, Olivia Tsz-Wa; Ho, Yuen-Shan; Irwin, Michael Garnet; Chang, Raymond Chuen-Chung; Wong, Gordon Tin-Chun (J Alzheimers Dis, 2016)
Several studies suggest a relationship between anesthesia-induced tau hyperphosphorylation and the development of postoperative cognitive dysfunction. This study further characterized the effects of continuous propofol infusion on tau protein phosphorylation in rats, with or without temperature control. Propofol was administered intravenously to 8-10-week-old male Sprague-Dawley rats and infused to the loss of the righting reflex for 2 h continuously. Proteins from cortex and hippocampus were examined by western blot and immunohistochemistry. Rectal temperature was significantly decreased during propofol infusion. Propofol with hypothermia significantly increased phosphorylation of tau at AT8, AT180, Thr205, and Ser199 in cortex and hippocampus except Ser396. With temperature maintenance, propofol still induced significant elevation of AT8, Thr205, and Ser199 in cortex and hippocampus; however, increase of AT180 and Ser396 was only found in hippocampus and cortex, respectively. Differential effects of propofol with or without hypothermia on multiple tau related kinases, such as Akt/GSK3β, MAPK pathways, or phosphatase (PP2A), were demonstrated in region-specific manner. These findings indicated that propofol increased tau phosphorylation under both normothermic and hypothermic conditions, and temperature control could partially attenuate the hyperphosphorylation of tau. Further studies are warranted to determine the long-term impact of propofol on the tau pathology and cognitive functions.
Keywords: Amyloid beta-Peptides; Analysis of Variance; Anesthetics, Intravenous; Animals; Body Temperature; Brain; Gene Expression Regulation; Glycogen Synthase Kinase 3 beta; Hypothermia, Induced; Male; Peptide Fragments; Phosphorylation; Propofol; Rats; Rats, Sprague-Dawley; Signal Transduction; tau Proteins

Effect of Early Referral to Specialist in Dementia on Institutionalization and Functional Decline: Findings from a Population-Based Study. - Pimouguet, Clément; Le-Goff, Mélanie; Rizzuto, Debora; Berr, Claudine; Leffondré, Karen; Pérès, Karine; Dartigues, Jean François; Helmer, Catherine (J Alzheimers Dis, 2016)
BACKGROUND: Although early diagnosis has been hypothesized to benefit both patients and caregivers, until now studies evaluating the effect of early dementia diagnosis are lacking. OBJECTIVE: To investigate the influence of early specialist referral for dementia on the risk of institutionalization and functional decline in Activity of Daily Living (ADL). METHODS: Incident dementia cases were screened in a prospective population-based cohort, the Three-City Study, and initial specialist consultation for cognitive complaint was assessed at dementia diagnosis. Proportional hazard regression and illness-death models were used to test the association between specialist referral and, respectively, institutionalization and functional decline. RESULTS: Only one third of the incident individuals with dementia had consulted a specialist for cognitive problems early (36%). After adjustment on potential confounders (including cognitive and functional decline) and competing risk of death, participants who had consulted a specialist early in the disease course presented a higher rate of being institutionalized than those who did not (Hazard Ratio = 2.00, 95% Confidence Interval (CI): 1.09- 3.64). But early specialist referral was not associated with further functional decline (HR = 1.09, 95% CI: 0.71- 1.67). CONCLUSIONS: Early specialist referral in dementia is associated with increased risk of institutionalization but not with functional decline in ADL. These findings suggest that early care referral in dementia may be a marker of concern for patients and/or caregivers; subsequent medical and social care could be suboptimal or inappropriate to allow patients to stay longer at home.
Keywords: Activities of Daily Living; Cognition Disorders; Community Health Planning; Dementia; Disability Evaluation; Female; Finland; Follow-Up Studies; Humans; Institutionalization; Male; Psychiatric Status Rating Scales; Referral and Consultation; Specialization

Effect of Tween-20 on Core Biomarkers Measured in Cerebrospinal Fluid from Patients with Alzheimer's Disease, Mild Cognitive Impairment, or Healthy Control Individuals. - Berge, Guro; Lauridsen, Camilla; Sando, Sigrid Botne; Holder, Daniel Joseph; Møller, Ina; Aasly, Jan Olav; Bråthen, Geir; Savage, Mary Josephine; White, Linda Rosemary (J Alzheimers Dis, 2016)
BACKGROUND: There is substantial variation caused by preanalytical procedures in the measurement of cerebrospinal fluid (CSF) biomarkers for Alzheimer's disease (AD) reported in the literature. OBJECTIVE: Determine whether the detergent Tween-20 improves diagnostic accuracy. METHODS: CSF proteins (Aβ42, Aβ40, total tau, and phosphorylated tau) were measured by standard ELISA, in uncentrifuged CSF with or without 0.05% Tween-20 from patients with AD or amnestic mild cognitive impairment, and healthy elderly controls. In the main study, collection tubes containing Tween-20 (Sarstedt 15 mL) were filled with 5 mL CSF to ensure consistent detergent concentration across subsequent aliquots into Corning 2 mL tubes. These latter were also the primary collection vessel for samples without Tween-20. The effect of centrifugation, and extra tube transfer of samples with Tween-20 were also examined. RESULTS: 0.05% Tween-20 significantly increased mean measured CSF concentration of Aβ42 (30% ), Aβ40 (23% ), and total tau (4% ), but not phosphorylated tau. Generally, these increases were similar in all groups, although for Aβ42, the mean percentage increase with Tween-20 was slightly larger for AD. Areas under receiver-operator characteristic curves were similar whether Tween-20 was present or not. Centrifuged CSF without Tween-20 significantly reduced the measured concentration of Aβ42 versus non-centrifuged samples, a difference not seen when detergent was added. Similar CSF Aβ42 levels were found whether Tween-20 was added at collection in an extra tube or directly to the main collection tube. CONCLUSION: Addition of Tween-20 to CSF did not improve differentiation of patients from controls.
Keywords: Aged; Alzheimer Disease; Amyloid beta-Peptides; Cognitive Dysfunction; Enzyme-Linked Immunosorbent Assay; Female; Humans; Longitudinal Studies; Male; Middle Aged; Peptide Fragments; Phosphorylation; Polysorbates; ROC Curve; Surface-Active Agents; tau Proteins

Effects of Hypertension and Anti-Hypertensive Treatment on Amyloid-β (Aβ) Plaque Load and Aβ-Synthesizing and Aβ-Degrading Enzymes in Frontal Cortex. - Ashby, Emma L; Miners, James S; Kehoe, Patrick G; Love, Seth (J Alzheimers Dis, 2016)
Epidemiological data associate hypertension with a predisposition to Alzheimer's disease (AD), and a number of postmortem and in vivo studies also demonstrate that hypertension increases amyloid-β (Aβ) pathology. In contrast, anti-hypertensive medications reportedly improve cognition and decrease the risk of AD, while certain classes of anti-hypertensive drugs are associated with decreased AD-related pathology. We investigated the effects of hypertension and anti-hypertensive treatment on Aβ plaque load in postmortem frontal cortex in AD. Aβ load was significantly increased in hypertensive (n = 20) relative to normotensive cases (n = 62) and was also significantly higher in treated (n = 9) than untreated hypertensives (n = 11). We then looked into mechanisms by which hypertension and treatment might increase Aβ load, focusing on Aβ-synthesizing enzymes, β- and γ-secretase, and Aβ-degrading enzymes, angiotensin-converting enzyme (ACE), insulin-degrading enzyme (IDE) and neprilysin. ACE and IDE protein levels were significantly lower in hypertensive (n = 21) than normotensive cases (n = 64), perhaps translating to decreased Aβ catabolism in hypertensives. ACE level was significantly higher in treated (n = 9) than untreated hypertensives (n = 12), possibly reflecting feedback upregulation of the renin-angiotensin system. Prospective studies in larger cohorts stratified according to anti-hypertensive drug class are needed to confirm these initial findings and to elucidate the interactions between hypertension, anti-hypertensive treatments, and Aβ metabolism.
Keywords: Aged; Aged, 80 and over; Amyloid Precursor Protein Secretases; Antihypertensive Agents; Female; Frontal Lobe; Humans; Hypertension; Immunohistochemistry; Insulysin; Male; Neprilysin; Peptidyl-Dipeptidase A; Plaque, Amyloid; Retrospective Studies

The Effects of Latrepirdine on Amyloid-β Aggregation and Toxicity. - Porter, Tenielle; Bharadwaj, Prashant; Groth, David; Paxman, Adrian; Laws, Simon M; Martins, Ralph N; Verdile, Giuseppe (J Alzheimers Dis, 2016)
Latrepirdine (Dimebon) has been demonstrated to be a neuroprotective and cognition improving agent in neurodegenerative diseases that feature protein aggregation and deposition, such as Alzheimer's disease (AD). The accumulation of amyloid-β (Aβ) protein aggregates is a key event in the neurodegenerative process in AD. This study explores if latrepirdine modulation of protein aggregation contributes to its neuroprotective mechanism of action. Assessment of neuronal cell death showed that there was a significant reduction in lactate dehydrogenase release at an equimolar ratio of Aβ:latrepirdine and with lower concentrations of latrepirdine. The ability of latrepirdine to alter the formation of Aβ42 aggregates was assessed by thioflavin-T fluorescence, western immunoblotting and atomic force microscopy (AFM). Despite showing a reduction in thioflavin-T fluorescence with latrepirdine treatment, indicating a decrease in aggregation, immunoblotting and AFM showed a modest increase in both the formation and size of Aβ aggregates. The discrepancies between thioflavin-T and the other assays are consistent with previous evidence that cyclic molecules can interfere with thioflavin-T binding of amyloid protein preparations. The ability of latrepirdine to modulate Aβ aggregation appears to be independent of its neuroprotective effects, and is unlikely to be a mechanism by which latrepirdine offers protection. This study investigates the effect of latrepirdine on Aβ aggregation, and presents evidence suggesting that caution should be applied in the use of thioflavin-T fluorescence based assays as a method for screening compounds for protein aggregation altering properties.
Keywords: Amyloid beta-Peptides; Analysis of Variance; Antipsychotic Agents; Cell Line, Tumor; Dose-Response Relationship, Drug; Drug Interactions; Humans; Indoles; L-Lactate Dehydrogenase; Microscopy, Atomic Force; Neuroblastoma; Peptide Fragments; Protein Aggregates

Efficacy and Safety of ABT-126 in Subjects with Mild-to-Moderate Alzheimer's Disease on Stable Doses of Acetylcholinesterase Inhibitors: A Randomized, Double-Blind, Placebo-Controlled Study. - Florian, Hana; Meier, Andreas; Gauthier, Serge; Lipschitz, Stanley; Lin, Yunzhi; Tang, Qi; Othman, Ahmed A; Robieson, Weining Z; Gault, Laura M (J Alzheimers Dis, 2016)
BACKGROUND: ABT-126 is a potent, selective α7 nicotinic acetylcholine receptor agonist with putative procognitive effects as a monotherapy in treating Alzheimer's disease (AD). OBJECTIVE: This randomized, double-blind, placebo-controlled multicenter study (NCT01549834) investigated the efficacy and safety of ABT-126 in subjects with mild-to-moderate AD who were taking stable doses of acetylcholinesterase inhibitors (AChEIs). METHODS: Subjects received 25 mg ABT-126 (n = 143), 75 mg ABT-126 (n = 145), or placebo (n = 146) once daily for 24 weeks. Subjects who completed the 24-week double-blind study were eligible to enroll in a 28-week open-label extension study (NCT01690195) and received 75 mg ABT-126 daily. The primary efficacy endpoint was the change from baseline to week 24 in the 11-item total score of the Alzheimer's Disease Assessment Scale- Cognitive Subscale (ADAS-Cog). RESULTS: Neither dose of ABT-126 demonstrated significant improvement compared with placebo in the primary efficacy endpoint. However, 25 mg ABT-126 demonstrated significant improvement compared with placebo in ADAS-Cog scores at week 4 (least squares mean difference, -1.21; standard error, 0.51; p <  0.010, one-sided); 75 mg ABT-126 did not demonstrate significant improvements in ADAS-Cog scores compared with placebo at any time point. A treatment effect was not observed for any secondary efficacy measures of cognition, function, or global improvement. ABT-126 was generally well tolerated; the most common adverse events were agitation, constipation, diarrhea, fall, and headache. CONCLUSIONS: Overall, the efficacy profile of ABT-126 did not warrant further development as add-on therapy to AChEIs to treat mild-to-moderate AD.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Alzheimer Disease; Cholinesterase Inhibitors; Disease Progression; Dose-Response Relationship, Drug; Double-Blind Method; Female; Humans; Indans; International Cooperation; Male; Medication Adherence; Middle Aged; Piperidines; Psychiatric Status Rating Scales; Treatment Outcome

Efficacy and Safety of Sustained Release Donepezil High Dose versus Immediate Release Donepezil Standard Dose in Japanese Patients with Severe Alzheimer's Disease: A Randomized, Double-Blind Trial. - Homma, Akira; Atarashi, Hirotsugu; Kubota, Naoki; Nakai, Kenya; Takase, Takao (J Alzheimers Dis, 2016)
BACKGROUND: Donepezil is an established treatment for mild, moderate, and severe Alzheimer's disease (AD). An international study demonstrated superior efficacy of sustained release (SR) 23 mg/day donepezil over immediate release (IR) 10 mg/day donepezil for cognitive function, but not global function in moderate-to-severe AD. OBJECTIVE: To demonstrate the superiority of SR 23 mg/day donepezil over IR 10 mg/day donepezil in Japanese patients with severe AD (SAD). METHODS: In this multicenter, randomized, double-blind, parallel-group study, Japanese outpatients with SAD were randomly assigned to continue IR 10 mg/day or switch to SR 23 mg/day for 24 weeks. Endpoints included the Severe Impairment Battery (SIB), Clinician's Interview-Based Impression of Change Plus Caregiver Input (CIBIC-plus), and safety. RESULTS: Overall, 166 and 185 patients were randomized to receive IR 10 mg/day and SR 23 mg/day, respectively. SR 23 mg/day was not statistically superior to IR 10 mg/day by SIB (least squares mean difference [LSMD]: 0.0; 95% confidence interval [CI]: -1.7, 1.8; p = 0.981) or CIBIC-plus (LSMD: 0.2; 95% CI: 0.0, 0.4; p = 0.080). Common adverse events in the SR 23 mg group were decreased appetite, vomiting, diarrhea, and contusion. Safety findings were consistent with known safety profiles of donepezil. CONCLUSION: SR 23 mg/day donepezil was not superior to IR 10 mg/day donepezil regarding the efficacy endpoints for Japanese SAD. Considering that a 10 mg/day dose is approved for SAD in Japan, the present findings suggest that IR 10 mg/day donepezil is the optimal dosage for Japanese patients with SAD.
Keywords: Aged; Alzheimer Disease; Cholinesterase Inhibitors; Delayed-Action Preparations; Double-Blind Method; Female; Humans; Indans; Japan; Male; Mental Status Schedule; Nootropic Agents; Outpatients; Piperidines; Psychiatric Status Rating Scales; Severity of Illness Index; Treatment Outcome

Evaluation of Cerebrospinal Fluid Assay Variability in Alzheimer's Disease. - White, Matthew T; Shaw, Leslie M; Xie, Sharon X (J Alzheimers Dis, 2016)
Studies of cerebrospinal fluid (CSF) biomarkers in Alzheimer's disease (AD) have indicated that much of the variability observed in the biomarkers may be due to measurement error. Biomarkers are often obtained with measurement error, which may make the diagnostic biomarker appear less effective than it truly is. In the Alzheimer's Disease Neuroimaging Initiative (ADNI) database, technical replicates of CSF biomarkers are available; the National Alzheimer's Coordinating Center database contains longitudinal replicates of CSF biomarkers. We focus on the area under the receiver operating characteristic curve (AUC) as the measure of diagnostic effectiveness for differentiating AD from normal cognition using CSF biomarkers and compare AUC estimates obtained by a more standard, naïve method (which uses a single observation per subject and ignores measurement error) to a maximum likelihood (ML) based method (which uses all replicates per subject and adjusts for measurement error). The choice of analysis method depends upon the noise to signal ratio (i.e., the magnitude of the measurement error variability relative to the true biomarker variability); moderate to high ratios may significantly bias the naïve AUC estimate, and the ML-based method would be preferred. The noise to signal ratios were low for the ADNI biomarkers but high for the tTau and pTau biomarkers in NACC. Correspondingly, the naïve and ML-based AUC estimates were nearly identical in the ADNI data but dissimilar for the tTau and pTau biomarkers in the NACC data. Therefore, using the naïve method is adequate for analysis of CSF biomarkers in the ADNI study, but the ML method is recommended for the NACC data.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Area Under Curve; Biomarkers; Databases, Factual; Female; Humans; Likelihood Functions; Male; Peptide Fragments; Phosphorylation; ROC Curve; tau Proteins

Examining the Relationship Between Autobiographical Memory Impairment and Carer Burden in Dementia Syndromes. - Kumfor, Fiona; Teo, Drusilla; Miller, Laurie; Lah, Suncica; Mioshi, Eneida; Hodges, John R; Piguet, Olivier; Irish, Muireann (J Alzheimers Dis, 2016)
BACKGROUND: Autobiographical memory (ABM) refers to the capacity to remember one's own past, and is known to be central for supporting one's identity and sense of self. This capacity is commonly affected in Alzheimer's disease (AD), as well as semantic dementia (SD) and behavioral-variant frontotemporal dementia (bvFTD). Importantly, ABM plays a critical social function, facilitating relationship intimacy and empathy, and thus loss of ABM may also negatively affect families and carers. OBJECTIVE: To explore the relationship between ABM disruption and carer burden in AD, SD, and bvFTD, and establish whether characteristic ABM profiles differentially relate to carer burden across dementia syndromes. METHODS: We recruited 12 AD, 10 SD, and 13 bvFTD patients and their primary carer. All participants completed the Autobiographical Interview to assess memory for recent and remote events. Carers completed: the Zarit Burden Interview; Depression, Anxiety and Stress Scale (DASS-21); and the Intimate Bond Measure (IBM). RESULTS: In AD, loss of recent ABM was associated with worse psychological wellbeing of carers on the DASS-21. In contrast in SD, remote ABM dysfunction was associated with SD patients showing greater controlling behavior within their intimate relationships. In bvFTD, surprisingly, despite pervasive ABM impairment, no relationship between extent of ABM loss and carer burden was observed. CONCLUSION: These preliminary results reveal that ABM impairment impacts on patients' families and carers and suggest that these influences vary according to the pattern of ABM dysfunction. Disease-specific interventions focusing on preserved aspects of ABM may improve quality of life for both patients and carers.
Keywords: Adaptation, Psychological; Aged; Alzheimer Disease; Analysis of Variance; Behavioral Symptoms; Caregivers; Female; Frontotemporal Dementia; Humans; Male; Memory Disorders; Memory, Episodic; Middle Aged; Neuropsychological Tests; Psychiatric Status Rating Scales; Statistics as Topic

Familial Presenilin Mutations and Sporadic Alzheimer's Disease Pathology: Is the Assumption of Biochemical Equivalence Justified? - Roher, Alex E; Maarouf, Chera L; Kokjohn, Tyler A (J Alzheimers Dis, 2016)
Studies of presenilin (PSEN) gene mutations producing early onset Alzheimer's disease (AD) have helped elucidate the pathogenic mechanisms of dementia and guided clinical trials of potential therapeutic interventions. Although familial and sporadic forms of AD share features, it is unclear if the two are precisely equivalent. In addition, PSEN mutations do not all produce a single phenotype, but exhibit substantial variability in clinical manifestations, which are related to the position and chemical nature of their amino acid substitutions as well as ratios of critical molecules such as Aβ40 and Aβ42. These differences complicate the interpretation of critical clinical trial results and their desired extrapolation to sporadic AD treatment. In this perspective, we examine differences between familial AD and sporadic AD as well as attributes shared by these uniquely arising disturbances in brain biochemical homeostasis that culminate in dementia.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Brain; Humans; Mutation; Presenilins

Fibrillar Amyloid-β Accumulation Triggers an Inflammatory Mechanism Leading to Hyperphosphorylation of the Carboxyl-Terminal End of Tau Polypeptide in the Hippocampal Formation of the 3×Tg-AD Transgenic Mouse. - Ontiveros-Torres, Miguel Ángel; Labra-Barrios, María Luisa; Díaz-Cintra, Sofía; Aguilar-Vázquez, Azucena Ruth; Moreno-Campuzano, Samadhi; Flores-Rodríguez, Paola; Luna-Herrera, Claudia; Mena, Raúl; Perry, George; Florán-Garduño, Benjamín; Luna-Muñoz, José; Luna-Arias, Juan Pedro (J Alzheimers Dis, 2016)
Alzheimer's disease (AD) is a degenerative and irreversible disorder whose progressiveness is dependent on age. It is histopathologically characterized by the massive accumulation of insoluble forms of tau and amyloid-β (Aβ) asneurofibrillary tangles and neuritic plaques, respectively. Many studies have documented that these two polypeptides suffer several posttranslational modifications employing postmortem tissue sections from brains of patients with AD. In order to elucidate the molecular mechanisms underlying the posttranslational modifications of key players in this disease, including Aβ and tau, several transgenic mouse models have been developed. One of these models is the 3×Tg-AD transgenic mouse, carrying three transgenes encoding APPSWE, S1M146V, and TauP301L proteins. To further characterize this transgenicmouse, we determined the accumulation of fibrillar Aβ as a function of age in relation to the hyperphosphorylation patterns of TauP301L at both its N- and C-terminus in the hippocampal formation by immunofluorescence and confocal microscopy. Moreover, we searched for the expression of activated protein kinases and mediators of inflammation by western blot of wholeprotein extracts from hippocampal tissue sections since 3 to 28 months as well. Our results indicate that the presence of fibrillar Aβ deposits correlates with a significant activation of astrocytes and microglia in subiculum and CA1 regions of hippocampus. Accordingly, we also observed a significant increase in the expression of TNF-α associated to neuritic plaques and glial cells. Importantly, there is an overexpression of the stress activated protein kinases SAPK/JNK and Cdk-5 in pyramidal neurons, which might phosphorylate several residues at the C-terminus of TauP301L. Therefore, the accumulation of Aβ oligomers results in an inflammatory environment that upregulates kinases involved in hyperphosphorylation of TauP301L polypeptide.
Keywords: Aged; Aged, 80 and over; Aging; Alzheimer Disease; Amyloid beta-Peptides; Animals; Disease Models, Animal; Female; Hippocampus; Humans; Male; Mice, Inbred C57BL; Mice, Transgenic; Neuroglia; Phosphorylation; Plaque, Amyloid; Presenilin-1; Pyramidal Cells; tau Proteins

Fluoxetine Treatment Induces Seizure Behavior and Premature Death in APPswe/PS1dE9 Mice. - Sierksma, Annerieke S R; de Nijs, Laurence; Hoogland, Govert; Vanmierlo, Tim; van Leeuwen, Fred W; Rutten, Bart P F; Steinbusch, Harry W M; Prickaerts, Jos; van den Hove, Daniel L A (J Alzheimers Dis, 2016)
Treatment of Alzheimer's disease (AD) patients with the antidepressant fluoxetine is known to improve memory and cognitive function. However, the mechanisms underlying these effects are largely unknown. To unravel these mechanisms, we aimed to treat APPswe/PS1dE9 mice with fluoxetine. Unexpectedly, with time, an increased number of animals displayed seizure behavior and died. Although spontaneous behavioral seizures have been reported previously in this mouse model, the observation of seizures and death consequential to fluoxetine treatment is new. Our results warrant further research on the underlying mechanisms as this may refine the treatment of AD patients.
Keywords: Alzheimer Disease; Amyloid beta-Protein Precursor; Animals; Anticonvulsants; Body Weight; Disease Models, Animal; Fluoxetine; Humans; Logistic Models; Male; Mice, Inbred C57BL; Mice, Transgenic; Neuroprotective Agents; Presenilin-1; Seizures

Formal Psychiatric Disorders are not Overrepresented in Behavioral Variant Frontotemporal Dementia. - Gossink, Flora T; Dols, Annemieke; Krudop, Welmoed A; Sikkes, Sietske A; Kerssens, Cora J; Prins, Niels D; Scheltens, Philip; Stek, Max L; Pijnenburg, Yolande A L (J Alzheimers Dis, 2016)
While psychiatric misdiagnosis is well-known in behavioral variant frontotemporal dementia (bvFTD), a systematic evaluation of standardized criteria for psychiatric disorders in bvFTD is still missing. Our aim was to define frequency and character of DSM-IV psychiatric disorders among patients with probable and definite bvFTD compared to possible bvFTD, other neurodegenerative diseases, and psychiatric diagnoses, using MINI-International Neuropsychiatric Interview. We additionally compared psychiatric prodromes between these groups. Subjects were participants of the late-onset frontal lobe (LOF) study, a longitudinal multicenter study. In each patient, after baseline diagnostic procedure, a neurologist and geriatric psychiatrist made a joint clinical diagnosis. Independently, a structured diagnostic interview according to DSM-IV and ICD-10 criteria (MINI-Plus) was performed by a trained professional blinded to clinical diagnosis. Out of 91 patients, 23 with probable and definite bvFTD, 3 with possible bvFTD, 25 with a non bvFTD neurodegenerative disease, and 40 with a clinical psychiatric diagnosis were included. Overall frequency of formal current and past psychiatric disorders in probable and definite bvFTD (21.7% current, 8.7% past) did not differ from other neurodegenerative diseases (12.0% current, 16.0% past) or possible bvFTD (66.7% current, 66.7% past), but was less than in patients with a clinical psychiatric diagnosis (57.5% current, 62.5% past; p <  0.01). In probable and definite bvFTD unipolar mood disorders were most common. Formally diagnosed psychiatric disorders are not overrepresented in probable bvFTD, suggesting that psychiatric misdiagnosis in bvFTD can be reduced by strictly applying diagnostic criteria. In suspected bvFTD close collaboration between neurologists and psychiatrists will advance diagnostics and subsequent treatment.
Keywords: Aged; Cohort Studies; Diagnostic and Statistical Manual of Mental Disorders; Female; Frontotemporal Dementia; Humans; Male; Mental Disorders; Middle Aged; Neuropsychological Tests; Psychiatric Status Rating Scales

Future Dementia Severity is Almost Entirely Explained by the Latent Variable δ's Intercept and Slope. - Palmer, Raymond F; Royall, Donald R (J Alzheimers Dis, 2016)
BACKGROUND: Structural equation models (SEM) can explicitly distinguish dementia-relevant variance in cognitive task performance. The resulting latent construct "δ" (for dementia) provides a relatively "error free" continuously varying dementia-specific phenotype. OBJECTIVE: To estimate δ's change over time (Δδ) and determine Δδ's predictive validity using future dementia status as an outcome. METHODS: Data from n = 2,191 participants of the Texas Alzheimer's Research and Care Consortium (TARCC) were used to construct a latent growth curve model of longitudinal change over four years using five cognitive measures and one measure of Instrumental Activities of Daily Living. Four final latent factors, including baseline δ and Δδ, were simultaneously entered as predictors of wave 4 dementia severity, as estimated by the Clinical Dementia Rating Scale "sum of boxes" (CDR). RESULTS: All observed measures exhibited significant change [χ2 = 1,152 (df = 229); CFI = 0.968; RMSEA = 0.043]. The final model demonstrated excellent fit to the data [χ2 = 543 (df = 245); CFI = 0.991; RMSEA = 0.023]. All latent indicator loadings were significant, yielding four distinct factors. After adjustment for demographic covariates and baseline CDR scores, d and Δd were significantly independently associated with CDR4, explaining 25% and 49% of its variance, respectively. The latent variable g' significantly explained 3% of CDR4 variance independently of d and Δd. Δg' was not significantly associated with CDR4. Baseline CDR explained 16% of CDR4 variance. CONCLUSIONS: Future dementia severity is almost entirely explained by the latent construct δ's intercept and slope.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cognition; Cognitive Dysfunction; Factor Analysis, Statistical; Female; Humans; Longitudinal Studies; Male; Neuropsychological Tests; Psychiatric Status Rating Scales

Gene Expression Profiling in the APP/PS1KI Mouse Model of Familial Alzheimer's Disease. - Weissmann, Robert; Hüttenrauch, Melanie; Kacprowski, Tim; Bouter, Yvonne; Pradier, Laurent; Bayer, Thomas A; Kuss, Andreas W; Wirths, Oliver (J Alzheimers Dis, 2016)
Alzheimer's disease (AD) is a devastating neurodegenerative disorder characterized by early intraneuronal amyloid-β (Aβ) accumulation, extracellular deposition of Aβ peptides, and intracellular hyperphosphorylated tau aggregates. These lesions cause dendritic and synaptic alterations and induce an inflammatory response in the diseased brain. Although the neuropathological characteristics of AD have been known for decades, the molecular mechanisms causing the disease are still under investigation. Studying gene expression changes in postmortem AD brain tissue can yield new insights into the molecular disease mechanisms. To that end, one can employ transgenic AD mouse models and the next-generation sequencing technology. In this study, a whole-brain transcriptome analysis was carried out using the well-characterized APP/PS1KI mouse model for AD. These mice display a robust phenotype reflected by working memory deficits at 6 months of age, a significant neuron loss in a variety of brain areas including the CA1 region of the hippocampus and a severe amyloid pathology. Based on deep sequencing, differentially expressed genes (DEGs) between 6-month-old WT or PS1KI and APP/PS1KI were identified and verified by qRT-PCR. Compared to WT mice, 250 DEGs were found in APP/PS1KI mice, while 186 DEGs could be found compared to PS1KI control mice. Most of the DEGs were upregulated in APP/PS1KI mice and belong to either inflammation-associated pathways or lysosomal activation, which is likely due to the robust intraneuronal accumulation of Aβ in this mouse model. Our comprehensive brain transcriptome study further highlights APP/PS1KI mice as a valuable model for AD, covering molecular inflammatory and immune responses.
Keywords: Alzheimer Disease; Amyloid beta-Protein Precursor; Animals; Brain; Disease Models, Animal; Gene Expression Profiling; Male; Mice; Mice, Transgenic; Nerve Degeneration; Presenilin-1; Transcriptome

Genetic Counseling and Testing for Alzheimer's Disease and Frontotemporal Lobar Degeneration: An Italian Consensus Protocol. - Bocchetta, Martina; Mega, Anna; Bernardi, Livia; Di Maria, Emilio; Benussi, Luisa; Binetti, Giuliano; Borroni, Barbara; Colao, Rosanna; Di Fede, Giuseppe; Fostinelli, Silvia; Galimberti, Daniela; Gennarelli, Massimo; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Genetic testing of familial Alzheimer's disease (AD) and frontotemporal lobar degeneration (FTLD) is attracting interest thanks to innovative primary prevention clinical trials and increased request for information by at-risk individuals. However, ethical, social, and psychological implications are paramount and genetic testing must be supported by structured genetic counseling. In Italy, practice parameters and guidelines for genetic counseling in dementia are not available. OBJECTIVE: To develop a nationally harmonized protocol for genetic counseling and testing of familial AD and FTLD. METHODS: Activities were carried out in the context of the Italian Dominantly Inherited Alzheimer's and Frontotemporal Network (IT-DIAfN) project, a national network of centers of excellence with expertise in managing patients with familial AD and FTLD. A survey of the literature on genetic counseling protocols and guidelines was conducted. Local protocols for genetic counseling were surveyed. Differences and commonalities among protocols were identified and discussed among project partners. Consensus was reached following implicit aggregation methods. RESULTS: Consensus was reached on a protocol for patients with clinically diagnosed familial AD or FTLD and a distinct protocol for their at-risk relatives. Genetic counseling should be provided by a multidisciplinary team including a geneticist, a neurologist/geriatrician, and a psychologist/psychiatrist, according to the following schedule: (i) initial consultation with tailored information on the genetics of the dementias; (ii) clinical, psychological, and cognitive assessment; if deemed appropriate (iii) genetic testing following a structured decision tree for gene mutation search; (iv) genetic testing result disclosure; (v) psychological support follow-up. CONCLUSION: This genetic counseling protocol provides Italian centers with a line of shared practice for dealing with the requests for genetic testing for familial AD and FTLD from patients and at-risk relatives, who may also be eligible participants for novel prevention clinical trials.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Consensus; Female; Follow-Up Studies; Frontotemporal Lobar Degeneration; Genetic Counseling; Genetic Testing; Humans; Italy; Male; Peptide Fragments; Psychiatric Status Rating Scales

Genetic Influences on Plasma Homocysteine Levels in African Americans and Yoruba Nigerians. - Kim, Sungeun; Nho, Kwangsik; Ramanan, Vijay K; Lai, Dongbing; Foroud, Tatiana M; Lane, Katie; Murrell, Jill R; Gao, Sujuan; Hall, Kathleen S; Unverzagt, Frederick W; Baiyewu, Olusegun; Ogunniyi, Adesola; et al. (J Alzheimers Dis, 2016)
Plasma homocysteine, a metabolite involved in key cellular methylation processes seems to be implicated in cognitive functions and cardiovascular health with its high levels representing a potential modifiable risk factor for Alzheimer's disease (AD) and other dementias. A better understanding of the genetic factors regulating homocysteine levels, particularly in non-white populations, may help in risk stratification analyses of existing clinical trials and may point to novel targets for homocysteine-lowering therapy. To identify genetic influences on plasma homocysteine levels in individuals with African ancestry, we performed a targeted gene and pathway-based analysis using a priori biological information and then to identify new association performed a genome-wide association study. All analyses used combined data from the African American and Yoruba cohorts from the Indianapolis-Ibadan Dementia Project. Targeted analyses demonstrated significant associations of homocysteine and variants within the CBS (Cystathionine beta-Synthase) gene. We identified a novel genome-wide significant association of the AD risk gene CD2AP (CD2-associated protein) with plasma homocysteine levels in both cohorts. Minor allele (T) carriers of identified CD2AP variant (rs6940729) exhibited decreased homocysteine level. Pathway enrichment analysis identified several interesting pathways including the GABA receptor activation pathway. This is noteworthy given the known antagonistic effect of homocysteine on GABA receptors. These findings identify several new targets warranting further investigation in relation to the role of homocysteine in neurodegeneration.
Keywords: Adaptor Proteins, Signal Transducing; African Americans; African Continental Ancestry Group; Aged; Aged, 80 and over; Cohort Studies; Cystathionine beta-Synthase; Cytoskeletal Proteins; Female; Genetic Variation; Genome-Wide Association Study; Heterozygote; Homocysteine; Humans; Indiana; Longitudinal Studies; Male; Nigeria; Prospective Studies

The Genetic Variability of UCP4 Affects the Individual Susceptibility to Late-Onset Alzheimer's Disease and Modifies the Disease's Risk in APOE-ɛ4 Carriers. - Montesanto, Alberto; Crocco, Paolina; Anfossi, Maria; Smirne, Nicoletta; Puccio, Gianfranco; Colao, Rosanna; Maletta, Raffaele; Passarino, Giuseppe; Bruni, Amalia C; Rose, Giuseppina (J Alzheimers Dis, 2016)
Uncoupling proteins (UCPs) are a group of five mitochondrial inner membrane transporters with a tissue specific expression that uncouple biofuel oxidation from ATP synthesis and function as regulators of energy homeostasis and antioxidants. Previous data suggested that neuronal UCPs (UCP2, UCP4, and UCP5) can directly influence synaptic plasticity, neurotransmission, and neurodegenerative processes, and have a crucial role in the function and protection of the central nervous system. In fact, it has been observed that the expression of neuronal UCPs significantly decreases in Alzheimer's disease (AD) patients. Here we analyzed the variability of UCP2, -3, -4, and 5 genes in sporadic and familial cases (n = 465) of late-onset AD (LOAD) with respect to healthy controls (n = 442). We showed that a genetic variant in the human UCP4, rs9472817, not only significantly affects the individual susceptibility to LOAD, but also modulates the effect of APOE-ɛ4 on AD risk. In fact, rs9472817-C allele was significantly more frequent in both groups of patients with respect to the control group (p = 6.934*10-4 for familial and p = 1.033*10-3 for sporadic cases). In addition, gene-gene interaction analysis revealed that the effect of APOE-ɛ4 allele on LOAD risk was doubled in homozygote CC subjects; conversely, the risk conferred by the APOE-ɛ4 allele was annulled in subjects with two copies of the G allele. Our findings are further evidence that the efficiency in mitochondrial energy metabolism and oxidative stress are important factors in AD pathogenesis.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Apolipoprotein E4; Female; Genetic Association Studies; Genotype; Humans; Male; Mental Status Schedule; Mitochondrial Uncoupling Proteins; Neuroimaging; Polymorphism, Single Nucleotide

Greater specificity for cerebrospinal fluid P-tau231 over P-tau181 in the differentiation of healthy controls from Alzheimer's disease. - Spiegel, Jonathan; Pirraglia, Elizabeth; Osorio, Ricardo S; Glodzik, Lidia; Li, Yi; Tsui, Wai; Saint Louis, Leslie A; Randall, Catherine; Butler, Tracy; Xu, Jinfeng; Zinkowski, Raymond P; Zetterberg, Henrik; et al. (J Alzheimers Dis, 2016)
Cerebrospinal fluid (CSF) measures of phosphorylated-tau (P-tau) 231 and P-tau181 are two biomarkers for the identification of tau pathology as related to Alzheimer's disease (AD). While both are pathologically validated, their relative diagnostic performances are not well known. This cross-sectional diagnostic study of 87 normal (NL) subjects and 28 AD subjects compared CSF P-tau231 with CSF P-tau181. Logistic regression modeling demonstrated that the P-tau231 was superior to the P-tau181 in the diagnostic classifications. At a fixed 85% sensitivity cutoff, the ROC analysis shows that P-tau231 has greater overall specificity than P-tau181. While both P-tau analytes demonstrated equivalent negative predictive accuracies, P-tau231 yielded significantly fewer false positives. Moreover, P-tau231, but not P-tau181, demonstrated sensitivity to the E4 genotype. A postmortem validation with 9 AD subjects confirmed the superiority of the CSF P-tau231 specificity. This study suggests that P-tau231 has the potential to improve the CSF tau biomarker diagnosis of AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Case-Control Studies; Cross-Sectional Studies; Female; Humans; Logistic Models; Male; Middle Aged; Phosphorylation; ROC Curve; Sensitivity and Specificity; tau Proteins

Greater than the Sum of Its Parts: δ can be Constructed from Item Level Data. - Royall, Donald R; Palmer, Raymond F; Matsuoka, Teruyuki; Kato, Yuka; Taniguchi, Shogo; Ogawa, Mayu; Fujimoto, Hiroshi; Okamura, Aiko; Shibata, Keisuke; Nakamura, Kaeko; Nakaaki, Shutaro; Koumi, Hiroyuki; et al. (J Alzheimers Dis, 2016)
"δ", a latent variable constructed from cognitive performance and functional status measures, can accurately diagnose dementia. The minimal assessment needed is unknown. We have constructed a δ homolog, "dTEXAS", from Telephone Executive Assessment Scale (TEXAS) items, and validated it in a convenience sample of Japanese persons (n = 176). dTEXAS scores correlated strongly with both Instrumental Activities of Daily Living (IADL) (r = -0.86, p <  0.001) and Clinical Dementia Rating Scale (CDR) (r = 0.71, p <  0.001). Constructed independently of their diagnoses, dTEXAS scores accurately distinguished dementia versus controls (area under the receiver operating curve [(AUC; ROC) = 0.92], dementia versus mild cognitive impairment (MCI) (AUC = 0.80) and controls versus MCI (AUC = 0.74). These AUCs are higher than those of multiple observed executive measures, as reported recently by Matsuoka et al., 2014. A dTEXAS score of -0.58 best discriminated between dementia versus controls with 90.1% sensitivity and 80.0% specificity.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Alzheimer Disease; Cognitive Dysfunction; Executive Function; Female; Humans; Japan; Male; Neuropsychological Tests; Psychiatric Status Rating Scales; ROC Curve; United States

GSK-3β is Dephosphorylated by PP2A in a Leu309 Methylation-Independent Manner. - Chu, Dandan; Tan, Jianxin; Xie, Shutao; Jin, Nana; Yin, Xiaomin; Gong, Cheng-Xin; Iqbal, Khalid; Liu, Fei (J Alzheimers Dis, 2016)
Hyperphosphorylation of tau is pivotally involved in the pathogenesis of Alzheimer's disease (AD) and related tauopathies. Glycogen synthase kinase-3β (GSK-3β) and protein phosphate 2A (PP2A) are crucial enzymes to regulate tau phosphorylation. GSK-3β activity is regulated by its inhibitory phosphorylation at Ser9. We previously reported the cross-talk between GSK-3β and PP2A signaling and showed that PP2A could dephosphorylate GSK-3β at Ser9. Here, we investigated the dephosphorylation of GSK-3β in brain extracts in the presence of phosphatase inhibitors and found that a PP2A-like phosphatase activity was required for dephosphorylation of GSK-3β at Ser9. PP2A interacted with GSK-3β and suppressed its Ser9 phosphorylation in vitro and in HEK-293FT cells. Activity of PP2A negatively correlated to the level of phosphorylated GSK-3β in kainic acid-induced excitotoxic mouse brain. Alteration of methylation of the catalytic subunit of PP2A (PP2Ac) at Leu309 did not affect GSK-3β phosphorylation. These findings suggest that Leu309 methylation is not required for PP2A to dephosphorylate GSK-3β at Ser9.
Keywords: Animals; Brain; Carboxylic Ester Hydrolases; Cell Line, Transformed; Dose-Response Relationship, Drug; Enzyme Inhibitors; Excitatory Amino Acid Agonists; Glycogen Synthase Kinase 3; Glycogen Synthase Kinase 3 beta; Humans; Kainic Acid; Leucine; Luminescent Proteins; Male; Methylation; Mice; Phosphorylation; Protein O-Methyltransferase; Protein Phosphatase 2; RNA, Small Interfering; Serine; tau Proteins

Gx-50 Inhibits Neuroinflammation via α7 nAChR Activation of the JAK2/STAT3 and PI3K/AKT Pathways. - Shi, Shi; Liang, Dongli; Bao, Min; Xie, Yilin; Xu, Wangjie; Wang, Lianyun; Wang, Zhaoxia; Qiao, Zhongdong (J Alzheimers Dis, 2016)
Recent studies have revealed that the α7 nicotinic acetylcholine receptor (α7 nAChR) is a critical link between inflammation and neurodegeneration, which is closely associated with Alzheimer's disease (AD). The JAK2/STAT3 and PI3K/AKT signaling pathways contribute to the neuroprotective and anti-inflammatory effects of α7nAChR. Our previous studies have shown that treatment with gx-50 improves cognitive function and is neuroprotective. Here, we investigated the effect of gx-50 on α7 nAChR and Aβ-induced inflammation in microglia. First, the binding affinity of gx-50 to α7 nAChR was examined using the fluorescence-based Octet RED system, and the expression of α7 nAChR was detected using real-time PCR and western blotting. We also investigated downstream events of α7 nAChR activity, including the translocation of p-STAT3 and the phosphorylation of JAK2, STAT3, PI3K, and AKT. Finally, the effect of gx-50 on Aβ-induced inflammation via α7 nAChR-mediated signaling pathways was investigated using cytokine assays. The results showed that gx-50 is able to act as a specific ligand to activate α7 nAChR, which then upregulates the JAK2/STAT3 and PI3K/AKT signaling pathways to inhibit the secretions of pro-inflammatory cytokines, such as IL-1β. In conclusion, the results suggest that gx-50 could inhibit the Aβ-induced inflammatory response in microglia via α7 nAChR activity, which might be a successful therapeutic target against AD.
Keywords: Acrylamides; alpha7 Nicotinic Acetylcholine Receptor; Amyloid beta-Peptides; Analysis of Variance; Animals; Anti-Inflammatory Agents; Cell Line, Transformed; Cytokines; Enzyme Inhibitors; Enzyme-Linked Immunosorbent Assay; Gene Expression Regulation; Janus Kinase 2; Mice; Microglia; Phosphatidylinositol 3-Kinases; Protein Binding; RNA, Messenger; Signal Transduction

Health-Related Quality of Life in Patients with Alzheimer's Disease in Different German Health Care Settings. - Heßmann, Philipp; Seeberg, Greta; Reese, Jens Peter; Dams, Judith; Baum, Erika; Müller, Matthias J; Dodel, Richard; Balzer-Geldsetzer, Monika (J Alzheimers Dis, 2016)
The purpose of this study is to evaluate the health-related quality of life (HrQoL) of patients with Alzheimer's disease (AD) in different care settings (institutionalized versus community-dwelling) across all severity stages of dementia. Patients were consecutively recruited with their primary caregivers (123 inpatients and 272 outpatients), and the impact of patient-related parameters such as behavioral and psychological symptoms of dementia (BPSD) (Geriatric Depression Scale [GDS] and Neuropsychiatric Inventory [NPI]) and functional capacity (Alzheimer's Disease Cooperative Study-Activities of Daily Living [ADCS-ADL]) on HrQoL was analyzed. Patients' HrQoL was assessed using self-reported and caregiver-rated generic (EuroQoL Instrument) and dementia-specific (Quality of Life-Alzheimer's Disease [Qol-AD]) scales. Patients reported a considerably higher HrQoL than their caregivers on the QoL-AD, EQ-5D, and EQ VAS (p <  0.001). Different dementia severity groups showed significantly worse results in HrQoL for patients with lower MMSE scores. The mean self-reported QoL-AD decreased from 32.3±5.7 in the group with the highest MMSE scores to 27.1±5.5 in patients with the lowest MMSE scores (p <  0.001). A considerably lower HrQoL was shown for institutionalized patients versus participants in outpatient settings (proxy-rated QoL-AD 19.7±4.6 versus 26.0±7.1, p <  0.001). Depressive symptoms (GDS), BPSD (NPI), and reduced functional capacity (ADCS-ADL) were evaluated for their impact on patients' HrQoL. Multivariate models explained between 22% and 54% of the variance in patients' HrQoL. To analyze the causative direction of the reported associations, further longitudinal studies should be conducted.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Caregivers; Depression; Female; Germany; Humans; Inpatients; Male; Multivariate Analysis; Neuropsychological Tests; Outpatients; Psychiatric Status Rating Scales; Quality of Life; Residential Facilities; Self Report; Severity of Illness Index

Hemisphere Asymmetry of Response to Pharmacologic Treatment in an Alzheimer's Disease Mouse Model. - Manousopoulou, Antigoni; Saito, Satoshi; Yamamoto, Yumi; Al-Daghri, Nasser M; Ihara, Masafumi; Carare, Roxana O; Garbis, Spiros D (J Alzheimers Dis, 2016)
The aim of this study was to examine hemisphere asymmetry of response to pharmacologic treatment in an Alzheimer's disease mouse model using cilostazol as a chemical stimulus. Eight-month-old mice were assigned to vehicle or cilostazol treatment for three months and hemispheres were analyzed using quantitative proteomics. Bioinformatics interpretation showed that following treatment, aggregation of blood platelets significantly decreased in the right hemisphere whereas neurodegeneration significantly decreased and synaptic transmission increased in the left hemisphere only. Our study provides novel evidence on cerebral laterality of pharmacologic activity, with important implications in deciphering regional pharmacodynamic effects of existing drugs thus uncovering novel hemisphere-specific therapeutic targets.
Keywords: Alzheimer Disease; Animals; Brain; Disease Models, Animal; Functional Laterality; Male; Mice, Transgenic; Nootropic Agents; Proteome; Tetrazoles

Heterogeneity of Cognitive Anosognosia and its Variation with the Severity of Dementia in Patients with Alzheimer's Disease. - Avondino, Emilie; Antoine, Pascal (J Alzheimers Dis, 2016)
Currently, the lack of awareness of deficits, i.e., anosognosia, is a major obstacle in the healthcare circuit that delays the diagnosis of Alzheimer's disease (AD). However, a clear framework is lacking in the literature related to this phenomenon in terms of its definition, mechanisms, and objects. The aim of this study is to assess the different levels of cognitive anosognosia using a prediction-performance procedure and to identify the potential correlates of these levels. A sample of patients with probable AD was divided into three groups according to the severity of dementia (mild (MiD), moderate (MoD), and moderately severe (MSD) dementia), ranked according to the results of the Mini-Mental State Examination. We observed the following three scores: the real score, the prediction score, and the anosognosia score. These scores were calculated based on the prediction-performance task MISAwareness from the Dementia Rating Scale for cognitive processes (i.e., Attention, Initiation, Conceptualization, Construction, and Memory). We obtained a strong plateau effect between the MiD and MoD groups for anosognosia scores for actual performance or prediction for both the level of overall functioning and for specific processes. The sole exception was the result for memory processes. Moreover, the profiles of the patients' responses on the Memory subscale were substantially different and, indeed, opposite from those for the other processes. The main results confirm the multidimensionality of anosognosia and its variability with the stage of dementia and specifically implicate memory processes that indicate a cleavage between memory and other cognitive functions.
Keywords: Agnosia; Alzheimer Disease; Attention; Chi-Square Distribution; Cognition Disorders; Dementia; Female; Humans; Male; Memory; Neuropsychological Tests; Predictive Value of Tests; Prospective Studies; Psychiatric Status Rating Scales; Severity of Illness Index

Heterogeneous Language Profiles in Patients with Primary Progressive Aphasia due to Alzheimer's Disease. - Louwersheimer, Eva; Keulen, M Antoinette; Steenwijk, Martijn D; Wattjes, Mike P; Jiskoot, Lize C; Vrenken, Hugo; Teunissen, Charlotte E; van Berckel, Bart N M; van der Flier, Wiesje M; Scheltens, Philip; van Swieten, John C; Pijnenburg, Yolande A L (J Alzheimers Dis, 2016)
BACKGROUND: The logopenic variant of Primary Progressive Aphasia (lvPPA) is associated with underlying Alzheimer's disease (AD) pathology and characterized by impaired single word retrieval and repetition of phrases and sentences. OBJECTIVE: We set out to study whether logopenic aphasia is indeed the prototypic language profile in PPA patients with biomarker evidence of underlying AD pathology and to correlate language profiles with cortical atrophy patterns on MRI. METHODS: Inclusion criteria: (I) clinical diagnosis of PPA; (II) CSF profile and/or PiB-PET scan indicative for amyloid pathology; (III) availability of expert language evaluation. Based on language evaluation, patients were classified as lvPPA (fulfilling lvPPA core criteria), lvPPA extended (fulfilling core criteria plus other language disturbances), or PPA unclassifiable (not fulfilling lvPPA core criteria). Cortical atrophy patterns on MRI were visually rated and quantitative measurements of cortical thickness were performed using FreeSurfer. RESULTS: We included 22 patients (age 67±7 years, 50% female, MMSE 21±6). 41% were classified as lvPPA, 36% as lvPPA extended with additional deficits in language comprehension and/or confrontation naming, and 23% as PPA unclassifiable. By both qualitative and quantitative measurements, patients with lvPPA showed mild global cortical atrophy on MRI, whereas patients with lvPPA extended showed more focal cortical atrophy, predominantly at the left tempo-parietal side. For PPA unclassifiable, qualitative measurements revealed a heterogeneous atrophy pattern. CONCLUSION: Although most patients fulfilled the lvPPA criteria, we found that their language profiles were heterogeneous. The clinical and radiological spectrum of PPA due to underlying AD pathology is broader than pure lvPPA.
Keywords: Aged; Alzheimer Disease; Aphasia, Primary Progressive; Atrophy; Biomarkers; Brain; Female; Humans; Language; Language Tests; Magnetic Resonance Imaging; Male; Mental Status Schedule; Organ Size; Positron-Emission Tomography; Retrospective Studies

Higher Fasting Plasma Glucose Levels, within the Normal Range, are Associated with Decreased Processing Speed in High Functioning Young Elderly. - Raizes, Meytal; Elkana, Odelia; Franko, Motty; Ravona Springer, Ramit; Segev, Shlomo; Beeri, Michal Schnaider (J Alzheimers Dis, 2016)
We explored the association of plasma glucose levels within the normal range with processing speed in high functioning young elderly, free of type 2 diabetes mellitus (T2DM). A sample of 41 participants (mean age = 64.7, SD = 10; glucose 94.5 mg/dL, SD = 9.3), were examined with a computerized cognitive battery. Hierarchical linear regression analysis showed that higher plasma glucose levels, albeit within the normal range (<110 mg/dL), were associated with longer reaction times (p <  0.01). These findings suggest that even in the subclinical range and in the absence of T2DM, monitoring plasma glucose levels may have an impact on cognitive function.
Keywords: Aged; Blood Glucose; Cognition; Diabetes Mellitus, Type 2; Fasting; Female; Humans; Linear Models; Male; Middle Aged; Neuropsychological Tests; Psychomotor Performance; Reaction Time; Reference Values

Hippocampal Lipid Homeostasis in APP/PS1 Mice is Modulated by a Complex Interplay Between Dietary DHA and Estrogens: Relevance for Alzheimer's Disease. - Díaz, Mario; Fabelo, Noemí; Casañas-Sánchez, Verónica; Marin, Raquel; Gómez, Tomás; Quinto-Alemany, David; Pérez, José A (J Alzheimers Dis, 2016)
Current evidence suggests that lipid homeostasis in the hippocampus is affected by different genetic, dietary, and hormonal factors, and that its deregulation may be associated with the onset and progression of Alzheimer's disease (AD). However, the precise levels of influence of each of these factors and their potential interactions remain largely unknown, particularly during neurodegenerative processes. In the present study, we have performed multifactorial analyses of the combined effects of diets containing different doses of docosahexaenoic acid (DHA), estrogen status (ovariectomized animals receiving vehicle or 17β-estradiol), and genotype (wild-type or transgenic APP/PS1 mice) in hippocampal lipid profiles. We have observed that the three factors affect lipid classes and fatty acid composition to different extents, and that strong interactions between these factors exist. The most aberrant lipid profiles were observed in APP/PS1 animals receiving DHA-poor diets and deprived of estrogens. Conversely, wild-type animals under a high-DHA diet and receiving estradiol exhibited a lipid profile that closely resembled that of the hippocampus of control animals. Interestingly, though the lipid signatures of APP/PS1 hippocampi markedly differed from wild-type, administration of a high-DHA diet in the presence of estrogens gave rise to a lipid profile that approached that of control animals. Paralleling changes in lipid composition, patterns of gene expression of enzymes involved in lipid biosynthesis were also altered and affected by combination of experimental factors. Overall, these results indicate that hippocampal lipid homeostasis is strongly affected by hormonal and dietary conditions, and that manipulation of these factors might be incorporated in AD therapeutics.
Keywords: Acyl Coenzyme A; Alzheimer Disease; Amyloid beta-Protein Precursor; Analysis of Variance; Animals; Disease Models, Animal; Docosahexaenoic Acids; Dose-Response Relationship, Drug; Estrogens; Gene Expression Regulation; Hippocampus; Homeostasis; Humans; Lipid Metabolism; Mice; Mice, Transgenic; Mutation; Presenilin-1; RNA, Messenger

Hyperactivity with Agitative-Like Behavior in a Mouse Tauopathy Model. - Jul, Pia; Volbracht, Christiane; de Jong, Inge E M; Helboe, Lone; Elvang, Anders Brandt; Pedersen, Jan Torleif (J Alzheimers Dis, 2016)
Tauopathies, such as Alzheimer's disease (AD) and frontotemporal dementia (FTD), are characterized by formation of neurofibrillary tangles consisting of hyperphosphorylated tau. In addition to memory loss, patients experience behavioral symptoms such as agitation, aggression, depression, and insomnia. We explored the behavioral phenotype of a mouse model (rTg4510) carrying the human tau P301L mutation found in a familial form of FTD. We tested these mice in locomotor activity assays as well as in the Morris water maze to access spatial memory. In addition to cognitive impairments, rTg4510 mice exhibited a hyperactivity phenotype which correlated with progression of tau pathology and was dependent on P301L tau transgene expression. The hyperactive phenotype was characterized by significantly increased locomotor activity in a novel and in a simulated home cage environment together with a disturbed day/night cycle. The P301L-tau-dependent hyperactivity and agitative-like phenotype suggests that these mice may form a correlate to some of the behavioral disturbances observed in advanced AD and FTD.
Keywords: Age Factors; Analysis of Variance; Animals; Brain; Cognition Disorders; Disease Models, Animal; Doxycycline; Exploratory Behavior; Humans; Hyperkinesis; Male; Maze Learning; Mice; Mice, Transgenic; Motor Activity; Mutation; Psychomotor Agitation; tau Proteins; Tauopathies; Time Factors

"I Don't Think Of It As An Illness": Illness Representations in Mild to Moderate Dementia. - Clare, Linda; Quinn, Catherine; Jones, Ian Rees; Woods, Robert T (J Alzheimers Dis, 2016)
The self-regulatory model proposes that illness representations influence adjustment and coping in chronic conditions. Better understanding of the illness representations held by people with dementia could help with targeting information and support so as to optimize adjustment and coping. In this mixed-methods study of illness representations among people with mild to moderate Alzheimer's, vascular, or mixed dementia we aimed to clarify the nature of the representations held, to determine whether specific profiles can be identified based on perceptions of the identity and cause of the condition, and to examine associations between these profiles and other participant characteristics. Data were collected in the second wave of the Memory Impairment and Dementia Awareness Study (MIDAS). Sixty-four people with dementia, who had been told their diagnosis at a memory clinic, completed interviews and responded to questionnaires. In each case a carer was also interviewed. Cluster analysis based on responses about identity and cause identified three profiles. 'Illness' cluster participants saw themselves as living with an illness and used diagnostic labels, 'ageing' cluster participants did not use diagnostic labels and viewed their difficulties as related to ageing, and 'no problem' cluster participants considered that they did not have any difficulties. 'Illness' cluster participants had better cognition and better awareness, but lower mood, and perceived more practical consequences, than 'ageing' cluster participants. Holding an 'illness' model may not be advantageous. Rather than encouraging adoption of such a model, it may be preferable to target information and select interventions in line with the person's representation profile.
Keywords: Adaptation, Psychological; Aged; Aged, 80 and over; Aging; Awareness; Caregivers; Dementia; Female; Follow-Up Studies; Humans; Male; Middle Aged; Psychiatric Status Rating Scales; Residence Characteristics; Self Concept; Statistics, Nonparametric; Surveys and Questionnaires

Impact of Depressive Symptoms on Conversion from Mild Cognitive Impairment Subtypes to Alzheimer's Disease: A Community-Based Longitudinal Study. - Kida, Jiro; Nemoto, Kiyotaka; Ikejima, Chiaki; Bun, Shogyoku; Kakuma, Tatsuyuki; Mizukami, Katsuyoshi; Asada, Takashi (J Alzheimers Dis, 2016)
BACKGROUND: While longitudinal studies have investigated the relationships between mild cognitive impairment (MCI) subtypes and dementia subtypes, the results have been contradictory. In addition, some research shows that depression accompanied by MCI might increase the risk of Alzheimer's disease (AD). OBJECTIVE: The aim of this study is to longitudinally investigate the relationships between MCI subtypes and dementia subtypes, with special attention to the effect of comorbid depressive symptoms in a Japanese rural community. METHODS: Non-demented participants (n = 802) completed a baseline and follow-up study. Outcomes were conversion to dementia especially AD, MCI, or no conversion. A complementary log-log analysis was conducted to investigate the risk of dementia and AD in amnestic MCI (aMCI) compared to nonamnestic MCI (naMCI) groups. The impact of depressive symptoms on the transition from MCI to AD and from cognitively normal to MCI or AD was also analyzed. RESULTS: The risk of developing dementia, in particular AD, for the aMCI group was significantly higher than that for the naMCI group. In the aMCI group, the presence of depressive symptoms increased the risk of developing AD, but depressive symptoms in the naMCI group did not. In the cognitively normal group, the presence of depressive symptoms increased the risk of aMCI but not naMCI or AD. CONCLUSION: MCI subtyping could be useful in finding a prodrome for dementia and in particular for AD. The differing impacts of depressive symptoms on the development of AD suggest that the relationship between depressive symptoms and cognitive impairment could differ in aMCI and naMCI patients.
Keywords: Activities of Daily Living; Aged; Alzheimer Disease; Cognitive Dysfunction; Depression; Disease Progression; Female; Follow-Up Studies; Humans; Longitudinal Studies; Male; Neuropsychological Tests; Prodromal Symptoms; Prognosis; Risk

Impaired Autophagy in APOE4 Astrocytes. - Simonovitch, Shira; Schmukler, Eran; Bespalko, Alina; Iram, Tal; Frenkel, Dan; Holtzman, David M; Masliah, Eliezer; Michaelson, Danny M; Pinkas-Kramarski, Ronit (J Alzheimers Dis, 2016)
Alzheimer's disease (AD) is the most prevalent form of dementia in elderly. Genetic studies revealed allelic segregation of the apolipoprotein E (ApoE) gene in sporadic AD and in families with higher risk of AD. The mechanisms underlying the pathological effects of ApoE4 are not yet entirely clear. Several studies indicate that autophagy, which plays an important role in degradation pathways of proteins, organelles and protein aggregates, may be impaired in AD. In the present study, we investigated the effects of ApoE4 versus the ApoE3 isoform on the process of autophagy in mouse-derived astrocytes. The results obtained reveal that under several autophagy-inducing conditions, astrocytes expressing ApoE4 exhibit lower autophagic flux compared to astrocytes expressing ApoE3. Using an in situ model, we examined the role of autophagy and the effects thereon of ApoE4 in the elimination of Aβ plaques from isolated brain sections of transgenic 5xFAD mice. This revealed that ApoE4 astrocytes eliminate Aβ plaques less effectively than the corresponding ApoE3 astrocytes. Additional experiments showed that the autophagy inducer, rapamycin, enhances Aβ plaque degradation by ApoE4 astrocytes whereas the autophagy inhibitor, chloroquine, blocks Aβ plaque degradation by ApoE3 astrocytes. Taken together, these findings show that ApoE4 impairs autophagy in astrocyte cultures and that this effect is associated with reduced capacity to clear Aβ plaques. This suggests that impaired autophagy may play a role in mediating the pathological effects of ApoE4 in AD.
Keywords: Amyloid beta-Peptides; Animals; Apolipoprotein E3; Apolipoprotein E4; Astrocytes; Autophagy; Brain; Cells, Cultured; Central Nervous System Agents; Chloroquine; Disease Models, Animal; Humans; Mice, Transgenic; Plaque, Amyloid; Sirolimus; Time Factors

Increased Intrinsic Activity of Medial-Temporal Lobe Subregions is Associated with Decreased Cortical Thickness of Medial-Parietal Areas in Patients with Alzheimer's Disease Dementia. - Pasquini, Lorenzo; Scherr, Martin; Tahmasian, Masoud; Myers, Nicholas E; Ortner, Marion; Kurz, Alexander; Förstl, Hans; Zimmer, Claus; Grimmer, Timo; Akhrif, Atae; Wohlschläger, Afra M; Riedl, Valentin; et al. (J Alzheimers Dis, 2016)
In Alzheimer's disease (AD), disrupted connectivity between medial-parietal cortices and medial-temporal lobes (MTL) is linked with increased MTL local functional connectivity, and parietal atrophy is associated with increased MTL memory activation. We hypothesized that intrinsic activity in MTL subregions is increased and associated with medial-parietal degeneration and impaired memory in AD. To test this hypothesis, resting-state-functional and structural-MRI was assessed in 22 healthy controls, 22 mild cognitive impairment patients, and 21 AD-dementia patients. Intrinsic activity was measured by power-spectrum density of blood-oxygenation-level-dependent signal, medial-parietal degeneration by cortical thinning. In AD-dementia patients, intrinsic activity was increased for several right MTL subregions. Raised intrinsic activity in dentate gyrus and cornu ammonis 1 was associated with cortical thinning in posterior cingulate cortices, and at-trend with impaired delayed recall. Critically, increased intrinsic activity in the right entorhinal cortex was associated with ipsilateral posterior cingulate degeneration. Our results provide evidence that in AD, intrinsic activity in MTL subregions is increased and associated with medial-parietal atrophy. Results fit a model in which medial-parietal degeneration contributes to MTL dysconnectivity from medial-parietal cortices, potentially underpinning disinhibition-like changes in MTL activity.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cognitive Dysfunction; Female; Humans; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Male; Memory Disorders; Middle Aged; Nerve Net; Parietal Lobe; Temporal Lobe

Increased Total Homocysteine Levels Predict the Risk of Incident Dementia Independent of Cerebral Small-Vessel Diseases and Vascular Risk Factors. - Miwa, Kaori; Tanaka, Makiko; Okazaki, Shuhei; Yagita, Yoshiki; Sakaguchi, Manabu; Mochizuki, Hideki; Kitagawa, Kazuo (J Alzheimers Dis, 2016)
BACKGROUND: Homocysteine has been identified as a potential risk factor for stroke, cerebral small-vessel diseases (SVD), and dementia. OBJECTIVE: The present study aimed to investigate the predictive value of homocysteine levels on incident dementia while simultaneously controlling for MRI findings and vascular risk factors. METHODS: Within a Japanese cohort of participants with vascular risk factors in an observational study, we evaluated the association between baseline total homocysteine (tHcy) levels (per 1 μmol/L and the tertile of tHcy), the prevalence of MRI-findings at baseline, and incident all-cause dementia. Baseline brain MRI was used to determine SVD (lacunas, white matter hyperintensities, and cerebral microbleeds [CMBs]) and atrophy (medial-temporal lobe atrophy and bicaudate ratio). Logistic regression analyses were used to estimate the cross-sectional association between tHcy and each of MRI findings. Cox proportional hazards analyses were performed to estimate the longitudinal association between tHcy and dementia. RESULTS: In the 643 subjects (age: 67.2 ± 8.4 years, male: 59% ; education: 12.9 ± 2.6 years), multivariable analyses adjusted for several potential confounders, including estimated glomerular filtration rate (eGFR) and intima-media thickness, showed that highest tHcy tertile was associated with lacunas, CMBs, and strictly deep CMBs. During the mean 7.3-year follow-up (range: 2-13), 47 patients were diagnosed with dementia (Alzheimer's disease: 24; vascular dementia: 18; mixed-type: 3; other: 2). After adjusting for age, gender, APOE ɛ4, education, BMI, MMSE, hypertension, cerebrovascular events, eGFR, and MRI-findings, tHcy level (hazard ratios [HR]: 1.08, p = 0.043) and the highest tertile of tHcy (HR: 2.50, p = 0.047) for all-cause dementia remained significant. CONCLUSIONS: Our results provide additional evidence of tHcy that contributes to increased susceptibility to dementia risk.
Keywords: Aged; Carotid Intima-Media Thickness; Cerebral Small Vessel Diseases; Dementia; Female; Homocysteine; Humans; Incidence; Longitudinal Studies; Magnetic Resonance Imaging; Male; Mental Status Schedule; Middle Aged; Neuropsychological Tests; Predictive Value of Tests; Proportional Hazards Models; Risk Factors; Statistics, Nonparametric

Influence of Incipient Dementia on Hospitalization for Primary Care Sensitive Conditions: A Population-Based Cohort Study. - Pimouguet, Clément; Rizzuto, Debora; Fastbom, Johan; Lagergren, Mårten; Fratiglioni, Laura; Xu, Weili (J Alzheimers Dis, 2016)
BACKGROUND: Studies have reported that moderate/severe stages of dementia are linked to increased hospitalization rates, but little is known about the influence of incipient dementia on hospitalizations for primary care sensitive conditions (PCSCs). OBJECTIVE: To examine the associations between incipient dementia and hospitalization outcomes, including all-cause and PCSC hospitalization. METHODS: A total of 2,268 dementia-free participants in the Swedish National study on Aging and Care-Kungsholmen were interviewed and clinically examined at baseline. Participants aged ≥78 years were followed for 3 years, and those aged 60-72 years, for 6 years. Number of hospitalizations was retrieved from the National Patient Register. Dementia was diagnosed in accordance with Diagnostic and Statistical Manual of Mental Disorders-IV criteria. Hospitalization outcomes were compared in participants who did and did not develop dementia. Zero-inflated Poisson regressions and logistic regressions were used in data analysis. RESULTS: During the follow-up, 175 participants developed dementia. The unadjusted PCSC admission rate was 88.2 per 1000 person-years in those who developed dementia and 25.6 per 1000 person-years in those who did not. In the fully adjusted logistic regression model, incipient dementia was associated with an increased risk of hospitalization for PCSCs (OR = 2.3, 95% CI 1.3-3.9) but not with the number of hospitalizations or with all-cause hospitalization. Risks for hospitalization for diabetes, congestive heart failure, and pyelonephritis were higher in those who developed dementia than in those who did not. About 10% participants had a PCSC hospitalization attributable to incipient dementia. CONCLUSION: People with incipient dementia are more prone to hospitalization for PCSCs but not to all-cause hospitalization.
Keywords: Acute Disease; Age Factors; Aged; Aged, 80 and over; Chronic Disease; Dementia; Female; Follow-Up Studies; Hospitalization; Humans; Logistic Models; Longitudinal Studies; Male; Primary Health Care; Registries; Risk; Sensitivity and Specificity; Socioeconomic Factors; Sweden

Inhibition of Cholesterol Biosynthesis Reduces γ-Secretase Activity and Amyloid-β Generation. - Kim, Yoonhee; Kim, Chaeyoung; Jang, Hye Young; Mook-Jung, Inhee (J Alzheimers Dis, 2016)
Amyloid-β (Aβ) is one of major molecules contributing to the pathogenesis of Alzheimer's disease (AD). Aβ is derived from amyloid-β protein precursor (AβPP) through sequential cleavages by β- and γ-secretases. Regulation of these components is thought to be an important factor in Aβ generation during the pathogenesis of AD. AβPP, β-secretase, and γ-secretase reside in lipid rafts, where cholesterol regulates the integrity and flexibility of membrane proteins and Aβ is generated. However, the relationship between cholesterol and Aβ generation is controversial. In this study, we aimed to elucidate the direct effects of cholesterol depletion on AβPP processing using AY9944, which blocks the last step of cholesterol biosynthesis and thus minimizes the unknown side effects of upstream inhibitors, such as HMG-CoA reductase inhibitors. Treatment with AY9944 decreased γ-secretase activity and Aβ generation. These results suggested that changes in membrane composition by lowering cholesterol with AY9944 affected γ-secretase activity and Aβ generation, which is associated with AD pathogenesis.
Keywords: Amyloid beta-Peptides; Amyloid beta-Protein Precursor; Amyloid Precursor Protein Secretases; Analysis of Variance; Animals; Anticholesteremic Agents; Cell Line; Cholesterol; Cricetinae; Down-Regulation; Humans; In Situ Nick-End Labeling; Luminescent Proteins; Membrane Glycoproteins; Membrane Microdomains; Mutation; Presenilin-1; Protein Transport; trans-1,4-Bis(2-chlorobenzaminomethyl)cyclohexane Dihydrochloride; Transfection

Inhibition of Histone Deacetylase 3 Restores Amyloid-β Oligomer-Induced Plasticity Deficit in Hippocampal CA1 Pyramidal Neurons. - Krishna, Kumar; Behnisch, Thomas; Sajikumar, Sreedharan (J Alzheimers Dis, 2016)
Neurodegenerative diseases such as Alzheimer's disease (AD) are associated with alterations in epigenetic factors leading to cognitive decline. Histone deacetylase 3 (HDAC3) is a known critical epigenetic negative regulator of learning and memory. In this study, attenuation of long-term potentiation by amyloid-β oligomer, and its reversal by specific HDAC3 inhibitor RGFP966, was performed in rat CA1 pyramidal neurons using whole cell voltage-clamp and field recording techniques. Our findings provide the first evidence that amyloid-β oligomer-induced synaptic plasticity impairment can be prevented by inhibition of HDAC3 enzyme both at the single neuron as well as in a population of neurons, thus identifying HDAC3 as a potential target for ameliorating AD related plasticity impairments.
Keywords: Acrylamides; Alzheimer Disease; Amyloid beta-Peptides; Animals; Excitatory Postsynaptic Potentials; Hippocampus; Histone Deacetylase Inhibitors; Histone Deacetylases; Long-Term Potentiation; Male; Patch-Clamp Techniques; Peptide Fragments; Phenylenediamines; Pyramidal Cells; Rats, Wistar; Tissue Culture Techniques

Integrating Biomarkers for Underlying Alzheimer's Disease in Mild Cognitive Impairment in Daily Practice: Comparison of a Clinical Decision Support System with Individual Biomarkers. - Rhodius-Meester, Hanneke F M; Koikkalainen, Juha; Mattila, Jussi; Teunissen, Charlotte E; Barkhof, Frederik; Lemstra, Afina W; Scheltens, Philip; Lötjönen, Jyrki; van der Flier, Wiesje M (J Alzheimers Dis, 2016)
BACKGROUND: Recent criteria allow biomarkers to provide evidence of Alzheimer's disease (AD) pathophysiology. How they should be implemented in daily practice remains unclear, especially in mild cognitive impairment (MCI) patients. OBJECTIVE: We evaluated how a clinical decision support system such as the PredictAD tool can aid clinicians to integrate biomarker evidence to support AD diagnosis. METHODS: With available data on demographics, cerebrospinal fluid (CSF), and MRI, we trained the PredictAD tool on a reference population of 246 controls and 491 AD patients. We then applied the identified algorithm to 211 MCI patients. For comparison, we also classified patients based on individual biomarkers (MRI; CSF) and the NIA-AA criteria. Progression to dementia was used as outcome measure. RESULTS: After a median follow up of 3 years, 72 (34%) MCI patients remained stable and 139 (66%) progressed to AD. The PredictAD tool assigned a likelihood of underlying AD to each patient (AUC 0.82). Excluding patients with missing data resulted in an AUC of 0.87. According to the NIA-AA criteria, half of the MCI patients had uninformative biomarkers, precluding an assignment of AD likelihood. A minority (41%) was assigned to high or low AD likelihood with good predictive value. The individual biomarkers showed best value for CSF total tau (AUC 0.86). CONCLUSION: The ability of the PredictAD tool to identify AD pathophysiology was comparable to individual biomarkers. The PredictAD tool has the advantage that it assigns likelihood to all patients, regardless of missing or conflicting data, allowing clinicians to integrate biomarker data in daily practice.
Keywords: Aged; Aged, 80 and over; Algorithms; Alzheimer Disease; Area Under Curve; Biomarkers; Cognitive Dysfunction; Cohort Studies; Decision Support Systems, Clinical; Disease Progression; Female; Humans; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Male; Mental Status Schedule; Middle Aged; Neuropsychological Tests; Outcome Assessment (Health Care); Predictive Value of Tests

Intranasal TAT-haFGF Improves Cognition and Amyloid-β Pathology in an AβPP/PS1 Mouse Model of Alzheimer's Disease. - Lou, Guofeng; Zhang, Qihao; Xiao, Fei; Xiang, Qi; Su, Zhijian; Huang, Yadong (J Alzheimers Dis, 2016)
Neurotoxic amyloid-β (Aβ) peptide causing cognitive function disabilities is one of the most characteristic pathological features in Alzheimer's disease (AD). A novel fusion protein, TAT-haFGF, was administrated to AβPP/PS1 transgenic mice by intravenous (IV) injection and intranasal (IN) delivery, respectively, for 5 weeks to compare the pharmacodynamics between the two routes of administration. Our results showed that IN administration of TAT-haFGF improved cognition and reduced Aβ plaques more significantly in AβPP/PS1 mice, when compared with IV injection. Our new findings suggest that TAT-haFGF might be a promising new therapy to attenuate AD pathological process.
Keywords: Administration, Intranasal; Alzheimer Disease; Amyloid beta-Protein Precursor; Animals; Brain; Cognition Disorders; Disease Models, Animal; Fibroblast Growth Factors; Gene Products, tat; Humans; Injections, Intraventricular; Maze Learning; Mice; Mice, Inbred C57BL; Mice, Transgenic; Movement; Mutation; Peptide Fragments; Plaque, Amyloid; Presenilin-1

Iron Regulates Apolipoprotein E Expression and Secretion in Neurons and Astrocytes. - Xu, He; Perreau, Victoria M; Dent, Krista A; Bush, Ashley I; Finkelstein, David I; Adlard, Paul A (J Alzheimers Dis, 2016)
BACKGROUND: There is strong evidence that iron homeostasis is impaired in the aging and Alzheimer's disease (AD) brain and that this contributes to neurodegeneration. Apolipoprotein E (APOE) has been identified as the strongest genetic risk factor for AD. However, the interaction between the two has yet to be fully explored. OBJECTIVE: This study aimed to investigate the relationship between exogenous iron levels and ApoE in neurons and astrocytes. METHODS: Our study used primary cultured cortical neurons and astrocytes to investigate the changes in ApoE caused by iron. Western blot and RT-PCR were used to measure ApoE. RESULTS: We observed that iron upregulated intracellular ApoE levels in both neurons and astrocytes at the post-transcriptional and transcriptional level, respectively. However, there was less full-length ApoE secreted by neurons and astrocytes after iron treatment. We speculate that this might impair brain lipid metabolism and amyloid-β clearance. In terms of ApoE receptors, we observed that neuronal LRP-1 levels were increased by the addition of exogenous iron, which could contribute to AβPP endocytosis in neurons. However, there were no significant changes in neuronal LDLR, astrocyte LDLR, or astrocyte LRP-1. CONCLUSION: Our study reveals that iron may contribute to the pathogenesis of AD by affecting ApoE and its receptors and supports the notion that iron chelation should be investigated as a therapeutic strategy for AD.
Keywords: Amyloid beta-Peptides; Animals; Apolipoproteins E; Astrocytes; Blotting, Western; Cell Survival; Cells, Cultured; Cerebral Cortex; Copper; Ferritins; Immunohistochemistry; Iron; Mice, Inbred C57BL; Neurons; Polymerase Chain Reaction; Reactive Oxygen Species; Receptors, LDL; RNA, Messenger; Tumor Suppressor Proteins; Zinc

Japanese Care Location and Medical Procedures for People with Dementia in the Last Month of Life. - Nakanishi, Miharu; Nakashima, Taeko; Shindo, Yumi; Niimura, Junko; Nishida, Atsushi (J Alzheimers Dis, 2016)
BACKGROUND: Dementia-related societies worldwide have called for palliative end-of-life care for those suffering dementia; meanwhile, the Japanese dementia plan was revised on January 2015 to introduce into its objectives the support for end-of-life care via increased social and health care collaboration. OBJECTIVE: The study focus was the use of medical procedures in the last month of life among dementia patients in different care locations in Japan. METHODS: This study was conducted using a retrospective study design. Data from the Survey of Institutions and Establishments for Long-Term Care, which is a nationally representative cross-sectional survey of the public long-term care insurance services, were used. The 6,148 patients who received end-of-life care in their own home, nursing homes, or hospitals in September 2007, 2010, and 2013 were included for analysis. The primary disease of each patient was based on the ICD-10 code; a diagnosis of dementia included F00 (Alzheimer's), F01 (vascular), F02 (other), and F03 (unspecified). RESULTS: Of 6,148 patients, 886 (14.4%) had dementia as a primary disease; most received care in the last month of life in nursing homes (48.0%) or hospitals (44.8%) rather than in their own home (7.2%). Patients were less likely to undergo pain management when their primary disease was dementia (adjusted odds ratio, 0.44; 95% confidence interval, 0.21-0.91). CONCLUSION: Education and policy efforts are required to provide palliative end-of-life care to people with dementia at home. The national dementia plan should also explore possible approaches regarding pain management for dying people who have dementia.
Keywords: Aged, 80 and over; Cross-Sectional Studies; Dementia; Female; Hospitals; Housing; Humans; Japan; Male; Nursing Homes; Pain Management; Retrospective Studies; Terminal Care; Time Factors

The Korean Size/Weight Attribute Test: A Semantic Knowledge Test for Korean Older Adults and Brain-Imaging Evidence. - Yoo, Yongjoon; Shin, Seong A; Park, Soowon; Lee, Ji-Hye; Youn, Jung-Hae; Kim, Yu Kyeong; Lee, Jun-Young (J Alzheimers Dis, 2016)
BACKGROUND: A standardized tool for evaluating semantic knowledge of the Korean population is needed. OBJECTIVE: The purpose of this study was to develop a neuropsychological test for the evaluation of semantic knowledge in the Korean elderly population. METHODS: The Korean version of the Size/Weight Attribute Test (SWAT-K) was developed in reference to the original version. The diagnostic validity of SWAT-K was evaluated with 95 elderly outpatients [67 normal controls; 18 with Alzheimer's disease (AD); 10 with semantic-variant progressive aphasia (SV-PPA)]. Voxel-based morphometry (VBM) was employed to examine associations between SWAT-K scores and morphological changes of the brain. RESULTS: SWAT-K could discriminate the three subject groups (normal >AD, p <  0.001; AD >SV-PPA, p = 0.040), whereas Boston Naming Test could not distinguish SV-PPA from AD. ROC curve analysis confirmed high levels of sensitivity (0.90) and specificity (0.93) for SWAT-K. The test's inter-rater reliability (ICC = 0.827) and test-retest reliability (ICC = 0.666) were assessed as well. VBM found a significant positive correlation (uncorrected p <  0.005, k >  100) between SWAT-K scores and gray matter volume in right inferior frontal cortex (T = 4.08, k = 191) and bilateral temporal cortices (left, T = 4.42, k = 135; right, T = 3.55, k = 253), the areas the most affected in SV-PPA. CONCLUSIONS: SWAT-K is a sensitive and reliable test for evaluating semantic knowledge in the Korean elderly population. Strong positive correlations between SWAT-K scores and the brain areas responsible for semantic processing further corroborate the validity of SWAT-K.
Keywords: Aged; Aged, 80 and over; Aging; Alzheimer Disease; Analysis of Variance; Brain; Dementia; Female; Humans; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Male; Neuropsychological Tests; Psychiatric Status Rating Scales; Republic of Korea; ROC Curve; Semantics

The Language Profile of Behavioral Variant Frontotemporal Dementia. - Hardy, Chris J D; Buckley, Aisling H; Downey, Laura E; Lehmann, Manja; Zimmerer, Vitor C; Varley, Rosemary A; Crutch, Sebastian J; Rohrer, Jonathan D; Warrington, Elizabeth K; Warren, Jason D (J Alzheimers Dis, 2016)
BACKGROUND: The language profile of behavioral variant frontotemporal dementia (bvFTD) remains to be fully defined. OBJECTIVE: We aimed to quantify the extent of language deficits in this patient group. METHODS: We assessed a cohort of patients with bvFTD (n = 24) in relation to patients with semantic variant primary progressive aphasia (svPPA; n = 14), nonfluent variant primary progressive aphasia (nfvPPA; n = 18), and healthy age-matched individuals (n = 24) cross-sectionally and longitudinally using a comprehensive battery of language and general neuropsychological tests. Neuroanatomical associations of language performance were assessed using voxel-based morphometry of patients' brain magnetic resonance images. RESULTS: Relative to healthy controls, and after accounting for nonverbal executive performance, patients with bvFTD showed deficits of noun and verb naming and single word comprehension, diminished spontaneous propositional speech, and deterioration in naming performance over time. Within the bvFTD group, patients with MAPT mutations had more severe impairments of noun naming and single word comprehension than patients with C9orf72 mutations. Overall the bvFTD group had less severe language deficits than patients with PPA, but showed a language profile that was qualitatively similar to svPPA. Neuroanatomical correlates of naming and word comprehension performance in bvFTD were identified predominantly in inferior frontal and antero-inferior temporal cortices within the dominant hemispheric language network. CONCLUSIONS: bvFTD is associated with a language profile including verbal semantic impairment that warrants further evaluation as a novel biomarker.
Keywords: Aged; Aphasia, Primary Progressive; Atrophy; Brain; Cognition; Comprehension; Female; Frontotemporal Dementia; Humans; Language; Magnetic Resonance Imaging; Male; Middle Aged; Neuroimaging; Neuropsychological Tests; Primary Progressive Nonfluent Aphasia

The Latent Dementia Phenotype δ is Associated with Cerebrospinal Fluid Biomarkers of Alzheimer's Disease and Predicts Conversion to Dementia in Subjects with Mild Cognitive Impairment. - Koppara, Alexander; Wolfsgruber, Steffen; Kleineidam, Luca; Schmidtke, Klaus; Frölich, Lutz; Kurz, Alexander; Schulz, Stefanie; Hampel, Harald; Heuser, Isabella; Peters, Oliver; Reischies, Friedel M; Jahn, Holger; et al. (J Alzheimers Dis, 2016)
BACKGROUND: The recently proposed latent variable δ is a new tool for dementia case finding. It is built in a structural equation modeling framework of cognitive and functional data and constitutes a novel endophenotype for Alzheimer's disease (AD) research and clinical trials. OBJECTIVE: To investigate the association of δ with AD biomarkers and to compare the prediction of δ with established scales for conversion to dementia in patients with mild cognitive impairment (MCI). METHODS: Using data from a multicenter memory clinic study, we examined the external associations of the latent variable δ and compared δ with well-established cognitive and functional scales and cognitive-functional composite scores. For that purpose, logistic regressions with cerebrospinal fluid (CSF) biomarkers and conversion to dementia as dependent variables were performed with the investigated scores. The models were tested for significant differences. RESULTS: In patients with MCI, δ based on a broad range of cognitive scales (including the ADAS-cog, the MMSE, and the CERAD neuropsychological battery) predicted an abnormal CSF Aβ42/tau ratio indicative of AD (n = 340, AUC = 0.78, p <  0.001), and predicted incident dementia within 1-3 years of follow-up (n = 525, AUC = 0.84, p <  0.001). These associations were generally stronger than for any other scale or cognitive-functional composite examined. Homologs of δ based on reduced test batteries yielded somewhat lower effects. CONCLUSION: These findings support the interpretation of δ as a construct capturing the disease-related "essence" of cognitive and functional impairments in patients with MCI and dementia, and suggest that δ might become an analytical tool for dementia research.
Keywords: Activities of Daily Living; Aged; Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Cognitive Dysfunction; Dementia; Disease Progression; Female; Humans; Logistic Models; Longitudinal Studies; Male; Mental Status Schedule; Middle Aged; Neuropsychological Tests; Peptide Fragments; Phenotype; Predictive Value of Tests; Retrospective Studies; tau Proteins

Lewy Bodies, Vascular Risk Factors, and Subcortical Arteriosclerotic Leukoencephalopathy, but not Alzheimer Pathology, are Associated with Development of Psychosis in Alzheimer's Disease. - Fischer, Corinne E; Qian, Winnie; Schweizer, Tom A; Millikin, Colleen P; Ismail, Zahinoor; Smith, Eric E; Lix, Lisa M; Shelton, Paul; Munoz, David G (J Alzheimers Dis, 2016)
BACKGROUND: The neuropathological correlates of psychosis in Alzheimer's disease (AD) is unclear, with some studies reporting a correlation between psychosis and increased AD pathology while others have found no association. OBJECTIVE: To determine the demographic, clinical, and neuropathological features associated with psychotic symptoms in clinically attributed and neuropathologically proven AD. METHOD: We separately reviewed two overlapping groups of clinically diagnosed (cAD) AD patients with neuropathology data and neuropathologically definite (npAD) cases (regardless of clinical diagnosis) from the NACC database, and explored the relationships between psychosis and clinical variables, neuropathologic correlates, and vascular risk factors. Delusions and hallucinations, defined according to the NPI-Q, were analyzed separately. RESULTS: 1,073 subjects in the database fulfilled our criteria (890 cAD and 728 npAD patients). 34% of cAD and 37% of npAD had psychotic symptoms during their illness. Hallucinations were associated with greater cognitive and functional impairments on the MMSE and CDR, while delusional patients showed less impairment on CDR, consistent across cAD and npAD groups. Burden of AD pathology appears to relate to presence of psychotic symptoms in the clinical AD group, but this result is not confirmed in the neuropathologically confirmed group suggesting the findings in the clinical group were due to misdiagnosis of AD. Lewy body pathology, subcortical arteriosclerotic leukoencephalopathy, and vascular risk factors, including a history of hypertension and diabetes, were associated with the development of psychosis. METHOD: Vascular and Lewy body pathologies and vascular risk factors are important modifiers of the risk of psychosis in AD.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Alzheimer Disease; Cognition Disorders; Databases, Factual; Dementia, Vascular; Female; Hemorrhage; Humans; Lewy Bodies; Male; Middle Aged; Psychiatric Status Rating Scales; Psychotic Disorders; Retrospective Studies; Risk Factors; Severity of Illness Index; Surveys and Questionnaires

Lifelong Reading Disorder and Mild Cognitive Impairment: Implications for Diagnosis. - Lebowitz, Brian K; Weinstein, Cheryl; Beiser, Alexa; Seshadri, Sudha; Wolf, Philip A; Auerbach, Sandford; Au, Rhoda (J Alzheimers Dis, 2016)
Although neuropsychological tests are commonly used in the evaluation of possible mild cognitive impairment (MCI), poor test scores may be indicative of factors other than neurological compromise. The current study assessed the role of lifelong reading disorder on MCI classification. Community dwelling older adults with a suspected developmental reading disorder were identified by inference based on reading test performance. Individuals with a suspected reading disorder were significantly more likely to perform at a level consistent with MCI on several commonly used neuropsychological tests. The findings suggest a relationship between a history of reading disorder and MCI classification.
Keywords: Aged; Aged, 80 and over; Cognitive Dysfunction; Dyslexia; Female; Humans; Independent Living; Longitudinal Studies; Male; Neuropsychological Tests; Psychometrics; Retrospective Studies

Limiting Factors of Brain Donation in Neurodegenerative Diseases: The Example of French Memory Clinics. - Le Bouc, Raphael; Marelli, Cecilia; Beaufils, Emilie; Berr, Claudine; Hommet, Caroline; Touchon, Jacques; Pasquier, Florence; Deramecourt, Vincent (J Alzheimers Dis, 2016)
Postmortem neuropathological examination of the brain is essential in neurodegenerative diseases, to ensure accurate diagnosis, to obtain an a posteriori critical assessment of the adequacy of clinical care, and to validate new biomarkers, but is only rarely performed. The purpose of this study was to assess factors limiting brain donation, such as reluctance of physicians to seek donation consent, opposition from patients and families, and organizational constraints. We conducted a survey across French memory clinics and major neuropathological centers. Few postmortem examinations were performed annually, as less than one third of the centers had performed at least five autopsies, and 41% had performed none. The main limiting factor was the lack of donation requests made by physicians, as half of them never approach patients for brain donation. Reasons for not seeking donation consent often include discomfort broaching the subject and lack of awareness of the medical and scientific benefit of postmortems (77%), organizational constraints (61%), and overestimation of families' negative reaction (51%). Family refusals represented a second major obstacle, and were often caused by misconceptions. Identifying and addressing these biases early could help improve physicians' rate of making requests and the public's awareness about the importance of brain donation.
Keywords: Autopsy; Brain; France; Health Knowledge, Attitudes, Practice; Humans; Neurodegenerative Diseases; Physicians; Retrospective Studies

Linguistic Features Identify Alzheimer's Disease in Narrative Speech. - Fraser, Kathleen C; Meltzer, Jed A; Rudzicz, Frank (J Alzheimers Dis, 2016)
BACKGROUND: Although memory impairment is the main symptom of Alzheimer's disease (AD), language impairment can be an important marker. Relatively few studies of language in AD quantify the impairments in connected speech using computational techniques. OBJECTIVE: We aim to demonstrate state-of-the-art accuracy in automatically identifying Alzheimer's disease from short narrative samples elicited with a picture description task, and to uncover the salient linguistic factors with a statistical factor analysis. METHODS: Data are derived from the DementiaBank corpus, from which 167 patients diagnosed with "possible" or "probable" AD provide 240 narrative samples, and 97 controls provide an additional 233. We compute a number of linguistic variables from the transcripts, and acoustic variables from the associated audio files, and use these variables to train a machine learning classifier to distinguish between participants with AD and healthy controls. To examine the degree of heterogeneity of linguistic impairments in AD, we follow an exploratory factor analysis on these measures of speech and language with an oblique promax rotation, and provide interpretation for the resulting factors. RESULTS: We obtain state-of-the-art classification accuracies of over 81% in distinguishing individuals with AD from those without based on short samples of their language on a picture description task. Four clear factors emerge: semantic impairment, acoustic abnormality, syntactic impairment, and information impairment. CONCLUSION: Modern machine learning and linguistic analysis will be increasingly useful in assessment and clustering of suspected AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Diagnosis, Computer-Assisted; Factor Analysis, Statistical; Female; Humans; Language Disorders; Linguistics; Logistic Models; Machine Learning; Male; Mental Status Schedule; Middle Aged; Narration; Photic Stimulation; Speech; Verbal Behavior

Longitudinal Changes in Functional Brain Connectivity Predicts Conversion to Alzheimer's Disease. - Serra, Laura; Cercignani, Mara; Mastropasqua, Chiara; Torso, Mario; Spanò, Barbara; Makovac, Elena; Viola, Vanda; Giulietti, Giovanni; Marra, Camillo; Caltagirone, Carlo; Bozzali, Marco (J Alzheimers Dis, 2016)
This longitudinal study investigates the modifications in structure and function occurring to typical Alzheimer's disease (AD) brains over a 2-year follow-up, from pre-dementia stages of disease, with the aim of identifying biomarkers of prognostic value. Thirty-one patients with amnestic mild cognitive impairment were recruited and followed-up with clinical, neuropsychological, and MRI assessments. Patients were retrospectively classified as AD Converters or Non-Converters, and the data compared between groups. Cross-sectional MRI data at baseline, assessing volume and functional connectivity abnormalities, confirmed previous findings, showing a more severe pattern of regional grey matter atrophy and default-mode network disconnection in Converters than in Non-Converters. Longitudinally, Converters showed more grey matter atrophy in the frontotemporal areas, accompanied by increased connectivity in the precuneus. Discriminant analysis revealed that functional connectivity of the precuneus within the default mode network at baseline is the parameter able to correctly classify patients in Converters and Non-Converters with high sensitivity, specificity, and accuracy.
Keywords: Aged; Alzheimer Disease; Atrophy; Brain; Brain Mapping; Cognitive Dysfunction; Cross-Sectional Studies; Discriminant Analysis; Disease Progression; Female; Follow-Up Studies; Gray Matter; Humans; Image Processing, Computer-Assisted; Longitudinal Studies; Magnetic Resonance Imaging; Male; Neural Pathways; Neuropsychological Tests; Prognosis; Rest

Longitudinal Memory Profiles in Behavioral-Variant Frontotemporal Dementia and Alzheimer's Disease. - Schubert, Samantha; Leyton, Cristian E; Hodges, John R; Piguet, Olivier (J Alzheimers Dis, 2016)
BACKGROUND: Alzheimer's disease (AD) and behavioral-variant of frontotemporal dementia (bvFTD) can present with an overlapping neuropsychological profile, which often hinders their clinical differentiation. OBJECTIVE: To compare changes over time in memory, general cognition tasks, and functional scales between bvFTD and AD. METHODS: Consecutive cases diagnosed with probable bvFTD (n = 22) and typical AD (n = 31) with at least two clinical visits were selected. Of these, 13 (9 AD, 4 bvFTD) underwent Pittsburgh compound B PET scan, which supported the clinical diagnosis in all cases. Mixed-model regressions were used to estimate the differential rate of decline on selected tasks between cohorts. RESULTS: Analyses demonstrated that, despite equivalent baseline performance, bvFTD patients experienced a more rapid functional deterioration and a steeper decline in global cognition than AD patients. At baseline, both groups were impaired on executive function and memory tasks compared to controls, but these deficits were more marked in the bvFTD group. In addition, performance on these domains continued to decline more rapidly in this group. CONCLUSIONS: Neither the initial neuropsychological assessment nor projected performances can reliably distinguish the totality of bvFTD and AD individuals. Nevertheless, annual rates of progression on cognitive tasks provide valuable information and will potentially help establish the impact of future therapeutic treatments in these dementia syndromes.
Keywords: Alzheimer Disease; Aniline Compounds; Brain; Diagnosis, Differential; Disease Progression; Executive Function; Female; Follow-Up Studies; Frontotemporal Dementia; Humans; Longitudinal Studies; Male; Memory; Middle Aged; Neuropsychological Tests; Positron-Emission Tomography; Radiopharmaceuticals; Thiazoles

Looking for Neuroimaging Markers in Frontotemporal Lobar Degeneration Clinical Trials: A Multi-Voxel Pattern Analysis Study in Granulin Disease. - Premi, Enrico; Cauda, Franco; Costa, Tommaso; Diano, Matteo; Gazzina, Stefano; Gualeni, Vera; Alberici, Antonella; Archetti, Silvana; Magoni, Mauro; Gasparotti, Roberto; Padovani, Alessandro; Borroni, Barbara (J Alzheimers Dis, 2016)
In light of future pharmacological interventions, neuroimaging markers able to assess the response to treatment would be crucial. In Granulin (GRN) disease, preclinical data will prompt pharmacological trials in the future. Two main points need to be assessed: (1) to identify target regions in different disease stages and (2) to determine the most accurate functional and structural neuroimaging index to be used. To this aim, we have taken advantage of the multivariate approach of multi-voxel pattern analysis (MVPA) to explore the information of brain activity patterns in a cohort of GRN Thr272fs carriers at different disease stages (14 frontotemporal dementia (FTD) patients and 17 asymptomatic carriers) and a group of 33 healthy controls. We studied structural changes by voxel-based morphometry (VBM), functional connectivity by assessing salience, default mode, fronto-parietal, dorsal attentional, executive networks, and local connectivity by regional homogeneity, amplitude of low frequency fluctuations (ALFF), fractional ALFF (fALFF), degree centrality, and voxel-mirrored homotopic connectivity. In FTD patients with GRN mutation, the most predictive measure was VBM structural analysis, while in asymptomatic carriers the best predictor marker was the local connectivity measure (fALFF). Altogether, all indexes demonstrated fronto-temporo-parietal damage in GRN pathology, with widespread structural damage of fronto-parietal and temporal regions when disease is overt. MVPA could be of aid in identifying the most accurate neuroimaging marker for clinical trials. This approach was able to identify both the target region and the best neuroimaging approach, which would be specific in the different disease stages. Further studies are needed to simultaneously integrate multimodal indexes in a classifier able to trace the disease progression moving from preclinical to clinical stage of the disease.
Keywords: Adult; Aged; Brain; Brain Mapping; Cohort Studies; Female; Frontotemporal Lobar Degeneration; Humans; Image Processing, Computer-Assisted; Intercellular Signaling Peptides and Proteins; Magnetic Resonance Imaging; Male; Middle Aged; Mutation; Neural Pathways; Oxygen; Phenylalanine; Threonine

Low Prevalence of Mixed Dementia in a Cohort of 2,000 Elderly Patients in a Memory Clinic Setting. - Claus, Jules J; Staekenborg, Salka S; Roorda, Jelmen J; Stevens, Martijn; Herderschee, Dirk; van Maarschalkerweerd, Willy; Schuurmans, Lilly; Tielkes, Caroline E M; Koster, Pieter; Bavinck, Chris; Scheltens, Philip (J Alzheimers Dis, 2016)
BACKGROUND: It is generally assumed that with increasing age, pathology in clinically diagnosed Alzheimer's disease (AD) becomes more mixed, i.e., co-existence of amyloid plaques and cerebrovascular pathology. OBJECTIVE: To test the hypothesis of increasing prevalence of mixed dementia in late-onset clinically diagnosed Alzheimer's disease (AD) in a single-center memory clinic population. METHODS: Patients included had diagnoses of AD (n = 832), subjective cognitive impairment (SCI, n = 333), mild cognitive impairment (MCI, n = 492), vascular dementia (VaD, n = 57), other dementia (n = 53), or other diagnosis (n = 233). Prevalence of severe white matter lesions (WML) was defined as a score of 2 or higher on the Fazekas-scale on brain computed tomography to classify AD patients as having mixed dementia. We examined the effect of age on WML using multiple linear regression analysis, and AD patients were compared to SCI to determine the effect of disease on WML. RESULTS: Prevalence of severe WML was 33.6% in AD patients (mixed dementia), 11.4% in SCI, 22.7% in MCI, 75.4% in VaD, 3.8% in other dementia, and 15.5% in other diagnosis. With increasing age there was a significant and similar increase of WML scores in SCI, MCI, AD, other dementia, and other diagnosis, indicating no effect modification by AD. The difference between AD patients and SCI averaged 0.16 on the WML score and difference in percentage severe WML between AD and SCI patients was 15% across all ages. CONCLUSION: We found a low prevalence of mixed dementia. Furthermore, severe WML in AD was largely explained by age rather than effect of disease.
Keywords: Age Factors; Aged; Aged, 80 and over; Analysis of Variance; Cognitive Dysfunction; Cohort Studies; Dementia; Female; Humans; Male; Middle Aged; Neuropsychological Tests; Prevalence; Regression Analysis; Risk Factors; Tomography Scanners, X-Ray Computed

Lower Prevalence of Alzheimer's Disease among Tibetans: Association with Religious and Genetic Factors. - Huang, Fukai; Shang, Ying; Luo, Yuandai; Wu, Peng; Huang, Xue; Tan, Xiaohui; Lu, Xingyi; Zhen, Lifang; Hu, Xianda (J Alzheimers Dis, 2016)
BACKGROUND: The prevalence of dementia differs among racial groups, the highest prevalence being in Latin America (8.5%) compared to sub-Saharan African regions (2-4%). The most common type of dementia is Alzheimer's disease (AD). OBJECTIVE: To estimate the prevalence of AD in the Qinghai-Tibet plateau and to investigate the related factors. METHODS: This was a cross-sectional, multistage cluster sampling design survey. Data was collected from May 2014 to September 2014 from 4,060 Tibetan aged >60 years. Participants underwent clinical examinations and neuropsychological evaluations. MALDI-TOF was used to test the genotypes of CLU, TFAM, TP53INP1, IGHV1-67, CR1, ApoE, and BIN1. Logistic regression models were used to ascertain the associations with AD. RESULTS: The prevalence of AD among Tibetan individuals aged >60 years was 1.33% (95% CI: 0.98-1.69). The CLU haplotypes AA+GA (odds ratio (OR) = 4.483; 95% CI: 1.069-18.792) of rs2279590 was correlated with AD. The CLU haplotypes GG+GC (OR = 0.184; 95% CI: 0.038-0.888) of rs9331888 and kowtow (OR = 0.203; 95% CI 0.046-0.896) were negatively correlated with AD. CONCLUSION: A low prevalence of AD was found in Tibetans from the Qinghai-Tibet plateau. Multivariate analysis might suggest that regular "mind-body" religious meditative activities may be negatively associated with AD in this population, as well as the CLU genotype at rs9331888.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Clusterin; Cognition Disorders; Cross-Sectional Studies; Female; Genetic Association Studies; Genetic Predisposition to Disease; Humans; Logistic Models; Male; Middle Aged; Neuropsychological Tests; Polymorphism, Single Nucleotide; Psychiatric Status Rating Scales; Religion; Risk Factors; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; Tibet

LRP/LR Antibody Mediated Rescuing of Amyloid-β-Induced Cytotoxicity is Dependent on PrPc in Alzheimer's Disease. - Pinnock, Emma C; Jovanovic, Katarina; Pinto, Maxine G; Ferreira, Eloise; Dias, Bianca Da Costa; Penny, Clement; Knackmuss, Stefan; Reusch, Uwe; Little, Melvyn; Schatzl, Hermann M; Weiss, Stefan F T (J Alzheimers Dis, 2016)
The neuronal perturbations in Alzheimer's disease are attributed to the formation of extracellular amyloid-β (Aβ) neuritic plaques, composed predominantly of the neurotoxic Aβ42 isoform. Although the plaques have demonstrated a role in synaptic dysfunction, neuronal cytotoxicity has been attributed to soluble Aβ42 oligomers. The 37kDa/67kDa laminin receptor has been implicated in Aβ42 shedding and Aβ42-induced neuronal cytotoxicity, as well as internalization of this neurotoxic peptide. As the cellular prion protein binds to both LRP/LR and Aβ42, the mechanism underlying this cytotoxicity may be indirectly due to the PrPc-Aβ42 interaction with LRP/LR. The effects of this interaction were investigated by 3-[4,5-dimethylthiazol-2-yl]-2,5 diphenyl tetrazolium bromide assays. PrPc overexpression significantly enhanced Aβ42 cytotoxicity in vitro, while PrP-/-  cells were more resistant to the cytotoxic effects of Aβ42 and exhibited significantly less cell death than PrPc expressing N2a cells. Although anti-LRP/LR specific antibody IgG1-iS18 significantly enhanced cell viability in both pSFV1-huPrP1-253 transfected and non-transfected cells treated with exogenous Aβ42, it failed to have any cell rescuing effect in PrP-/-  HpL3-4 cells. These results suggest that LRP/LR plays a significant role in Aβ42-PrPc mediated cytotoxicity and that anti-LRP/LR specific antibodies may serve as potential therapeutic tools for Alzheimer's disease.
Keywords: Amyloid beta-Peptides; Animals; Antibodies; Cell Line, Transformed; Cell Survival; Flow Cytometry; Gene Expression Regulation; Humans; Mice; Peptide Fragments; Prions; Receptors, Laminin; Transfection

Maintenance of Cognitive Performance and Mood for Individuals with Alzheimer's Disease Following Consumption of a Nutraceutical Formulation: A One-Year, Open-Label Study. - Remington, Ruth; Bechtel, Cynthia; Larsen, David; Samar, Annemarie; Page, Robert; Morrell, Christopher; Shea, Thomas B (J Alzheimers Dis, 2016)
Nutritional interventions have shown varied efficacy on cognitive performance during Alzheimer's disease (AD). Twenty-four individuals diagnosed with AD received a nutraceutical formulation (NF: folate, alpha-tocopherol, B12, S-adenosyl methioinine, N-acetyl cysteine, acetyl-L-carnitine) under open-label conditions (ClinicalTrials.gov NCT01320527). Primary outcome was cognitive performance. Secondary outcomes were behavioral and psychological symptoms of dementia (BPSD) and activities of daily living. Participants maintained their baseline cognitive performance and BPSD over 12 months. These findings are consistent with improvement in cognitive performance and BPSD in prior placebo-controlled studies with NF, and contrast with the routine decline for participants receiving placebo.
Keywords: Aged; Aged, 80 and over; alpha-Tocopherol; Alzheimer Disease; Cognition Disorders; Dietary Supplements; Disease Progression; Female; Folic Acid; Follow-Up Studies; Humans; Male; Mood Disorders; Neuropsychological Tests; Psychiatric Status Rating Scales; Time Factors; Vitamin B 12

MAPT H1 Haplotype is Associated with Late-Onset Alzheimer's Disease Risk in APOEɛ4 Noncarriers: Results from the Dementia Genetics Spanish Consortium. - Pastor, Pau; Moreno, Fermín; Clarimón, Jordi; Ruiz, Agustin; Combarros, Onofre; Calero, Miguel; López de Munain, Adolfo; Bullido, Maria J; de Pancorbo, Marian M; Carro, Eva; Antonell, Anna; Coto, Eliecer; et al. (J Alzheimers Dis, 2016)
The MAPT H1 haplotype has been linked to several disorders, but its relationship with Alzheimer's disease (AD) remains controversial. A rare variant in MAPT (p.A152T) has been linked with frontotemporal dementia (FTD) and AD. We genotyped H1/H2 and p.A152T MAPT in 11,572 subjects from Spain (4,327 AD, 563 FTD, 648 Parkinson's disease (PD), 84 progressive supranuclear palsy (PSP), and 5,950 healthy controls). Additionally, we included 101 individuals from 21 families with genetic FTD. MAPT p.A152T was borderline significantly associated with FTD [odds ratio (OR) = 2.03; p = 0.063], but not with AD. MAPT H1 haplotype was associated with AD risk (OR = 1.12; p = 0.0005). Stratification analysis showed that this association was mainly driven by APOE ɛ4 noncarriers (OR = 1.14; p = 0.0025). MAPT H1 was also associated with risk for PD (OR = 1.30; p = 0.0003) and PSP (OR = 3.18; p = 8.59 × 10-8) but not FTD. Our results suggest that the MAPT H1 haplotype increases the risk of PD, PSP, and non-APOE ɛ4 AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Apolipoprotein E4; Female; Frontotemporal Dementia; Genetic Predisposition to Disease; Haplotypes; Humans; Logistic Models; Male; Middle Aged; Polymorphism, Single Nucleotide; Spain; tau Proteins

Measuring Information Processing Speed in Mild Cognitive Impairment: Clinical Versus Research Dichotomy. - Haworth, Judy; Phillips, Michelle; Newson, Margaret; Rogers, Peter J; Torrens-Burton, Anna; Tales, Andrea (J Alzheimers Dis, 2016)
A substantial body of research evidence is indicative of disproportionately slowed information processing speed in a wide range of multi-trial, computer-based, neuroimaging- and electroencephalography-based reaction time (RT) tests in Alzheimer's disease and mild cognitive impairment (MCI). However, in what is arguably a dichotomy between research evidence and clinical practice, RT associated with different brain functions is rarely assessed as part of their diagnosis. Indeed, often only the time taken to perform a single, specific task, commonly the Trail making test (TMT), is measured. In clinical practice therefore, there can be a failure to assess adequately the integrity of the rapid, serial information processing and response, necessary for efficient, appropriate, and safe interaction with the environment. We examined whether a typical research-based RT task could at least match the TMT in differentiating amnestic MCI (aMCI) from cognitively healthy aging at group level. As aMCI is a heterogeneous group, typically containing only a proportion of individuals for whom aMCI represents the early stages of dementia, we examined the ability of each test to provide intra-group performance variation. The results indicate that as well as significant slowing in performance of the operations involved in TMT part B (but not part A), individuals with aMCI also experience significant slowing in RT compared to controls. The results also suggest that research-typical RT tests may be superior to the TMT in differentiating between cognitively healthy aging and aMCI at group level and in revealing the performance variability one would expect from an etiologically heterogeneous disorder such as aMCI.
Keywords: Aged; Aged, 80 and over; Attention; Cognitive Dysfunction; Electroencephalography; Female; Humans; Male; Mental Processes; Mental Status Schedule; Middle Aged; Neuroimaging; Neuropsychological Tests; Photic Stimulation; Reaction Time; Residence Characteristics

Memory for Public Events in Mild Cognitive Impairment and Alzheimer's Disease: The Importance of Rehearsal. - Langlois, Roxane; Joubert, Sven; Benoit, Sophie; Dostie, Valérie; Rouleau, Isabelle (J Alzheimers Dis, 2016)
Ribot's law refers to the better preservation of remote memories compared with recent ones that presumably characterizes retrograde amnesia. Even if Ribot-type temporal gradient has been extensively studied in retrograde amnesia, particularly in Alzheimer's disease (AD), this pattern has not been consistently found. One explanation for these results may be that rehearsal frequency rather than remoteness accounts for the better preservation of these memories. Thus, the aim of present study was to address this question by studying retrograde semantic memory in subjects with amnestic mild cognitive impairment (aMCI) (n = 20), mild AD (n = 20) and in healthy older controls (HC; n = 19). In order to evaluate the impact of repetition as well as the impact of remoteness, we used a test assessing memory for enduring and transient public events that occurred in the recent and remote past. Results show no clear temporal gradient across time periods (1960-1975; 1976-1990; 1991-2005; 2006-2011), but a better performance was observed in all three groups for enduring compared with transient events. Moreover, although deficits were globally found in both patients groups compared with HC, more specific analyses revealed that aMCI patients were only impaired on transient events while AD patients were impaired on both transient and enduring events. Exploratory analyses also revealed a tendency suggesting preservation of remote transient events in aMCI. These findings are discussed with regards to memory consolidation models.
Keywords: Aged; Alzheimer Disease; Cognitive Dysfunction; Female; Humans; Learning; Male; Memory; Psychological Tests; Semantics

A Meta-Analysis of Alzheimer's Disease Incidence and Prevalence Comparing African-Americans and Caucasians. - Steenland, Kyle; Goldstein, Felicia C; Levey, Allan; Wharton, Whitney (J Alzheimers Dis, 2016)
BACKGROUND: Several studies have shown higher Alzheimer's disease (AD) incidence rates are in African-Americans (AAs) than Caucasians (CCs). If this finding is consistent across studies, it raises important etiologic questions regarding factors responsible for this discrepancy. It also affects the likely public health burden of AD in the US in the future, as the non-Caucasian population becomes the majority. OBJECTIVE: Estimate the AA/CC rate ratio for AD incidence across all available studies. METHODS: We conducted a meta-analysis of population-based studies for the rate ratio (RR) of AD incidence for AAs versus CCs, after identifying six relevant studies from the literature. We calculated an AA/CC rate ratio across all studies using inverse-variance weighting, and assessed inter-study heterogeneity. Using these incidence data, as well as data on survival after diagnosis, and on all-cause mortality, we also estimated the US prevalence of AD among AAs and CCs. RESULTS: There were six population-based studies with data comparing AD incidence between AAs and CCs, with an estimated 370 AA and 640 CC incident cases. The meta-analysis RR showed that the AD rate for AAs was 64% higher than for CCs (RR = 1.64 (95% CI 1.35-2.00)) 1.35-2.00)), with no evidence of heterogeneity. We estimated the current US AD prevalence for ages 65-90 to be 5.5% for CCs, and 8.6% for AAs (prevalence ratio 1.56). CONCLUSION: AAs have an increased risk of incident and prevalent AD compared to CCs for reasons which are unknown, but are hypothesized to reflect biological, psychological, and socioeconomic factors.
Keywords: African Americans; Alzheimer Disease; Community Health Planning; European Continental Ancestry Group; Female; Follow-Up Studies; Humans; Incidence; Male; Prevalence

Metallothioneins in Prion- and Amyloid-Related Diseases. - Adam, Pavlína; Křížková, Soňa; Heger, Zbyněk; Babula, Petr; Pekařík, Vladimír; Vaculovičoá, Markéta; Gomes, Cláudio M; Kizek, René; Adam, Vojtěch (J Alzheimers Dis, 2016)
Prion and other amyloid-forming diseases represent a group of neurodegenerative disorders that affect both animals and humans. The role of metal ions, especially copper and zinc is studied intensively in connection with these diseases. Their involvement in protein misfolding and aggregation and their role in creation of reactive oxygen species have been shown. Recent data also show that metal ions not only bind the proteins with high affinity, but also modify their biochemical properties, making them important players in prion-related diseases. In particular, the level of zinc ions is tightly regulated by several mechanisms, including transporter proteins and the low molecular mass thiol-rich metallothioneins. From four metallothionein isoforms, metallothionein-3, a unique brain-specific metalloprotein, plays a crucial role only in this regulation. This review critically evaluates the involvement of metallothioneins in prion- and amyloid-related diseases in connection with the relationship between metallothionein isoforms and metal ion regulation of their homeostasis.
Keywords: Amyloidosis; Animals; Brain Diseases; Humans; Metallothionein; Prion Diseases

Metformin in Amnestic Mild Cognitive Impairment: Results of a Pilot Randomized Placebo Controlled Clinical Trial. - Luchsinger, Jose A; Perez, Thania; Chang, Helena; Mehta, Pankaj; Steffener, Jason; Pradabhan, Gnanavalli; Ichise, Masanori; Manly, Jennifer; Devanand, Davangere P; Bagiella, Emilia (J Alzheimers Dis, 2016)
Diabetes and hyperinsulinemia may be risk factors for Alzheimer's disease (AD). We conducted a pilot study of metformin, a medication efficacious in treating and preventing diabetes while reducing hyperinsulinemia, among persons with amnestic mild cognitive impairment (aMCI) with the goal of collecting preliminary data on feasibility, safety, and efficacy. Participants were 80 men and women aged 55 to 90 years with aMCI, overweight or obese, without treated diabetes. We randomized participants to metformin 1000 mg twice a day or matching placebo for 12 months. The co-primary clinical outcomes were changes from baseline to 12 months in total recall of the Selective Reminding Test (SRT) and the score of the Alzheimer's Disease Assessment Scale-cognitive subscale (ADAS-cog). The secondary outcome was change in relative glucose uptake in the posterior cingulate-precuneus in brain fluorodeoxyglucose positron emission tomography. Change in plasma Aβ42 was an exploratory outcome. The mean age of participants was 65 years. Fifty percent of participants were women. The only baseline variable that was different between the arms was the ADAS-Cog. Metformin could not be tolerated by 7.5% of participants; 15% tolerated 500 mg/day, 35% tolerated 1000 mg/day, 32.5% tolerated 1500 mg/day, and only 10% tolerated the maximum dose. There were no serious adverse events related to metformin. The 7.5% of persons who did not tolerate metformin reported gastrointestinal symptoms. After adjusting for baseline ADAS-cog, changes in total recall of the SRT favored the metformin group (9.7±8.5 versus 5.3±8.5; p = 0.02). Differences for other outcomes were not significant. A larger trial seems warranted to evaluate the efficacy and cognitive safety of metformin in prodromal AD.
Keywords: Aged; Aged, 80 and over; Amyloid beta-Peptides; Brain; Cognitive Dysfunction; Double-Blind Method; Female; Follow-Up Studies; Glucose; Humans; Male; Metformin; Middle Aged; Nootropic Agents; Overweight; Peptide Fragments; Pilot Projects; Positron-Emission Tomography; Psychological Tests; Severity of Illness Index; Treatment Outcome

Mild Cognitive Impairment and Susceptibility to Scams in Old Age. - Han, S Duke; Boyle, Patricia A; James, Bryan D; Yu, Lei; Bennett, David A (J Alzheimers Dis, 2016)
BACKGROUND: Falling victim to financial scams can have a significant impact upon social and financial wellbeing and independence. A large proportion of scam victims are older adults, but whether older victims with mild cognitive impairment (MCI) are at higher risk remains unknown. OBJECTIVE: We tested the hypothesis that older persons with MCI exhibit greater susceptibility to scams compared to those without cognitive impairment. METHODS: Seven hundred and thirty older adults without dementia were recruited from the Rush Memory and Aging Project, a community-based epidemiologic study of aging. Participants completed a five-item self-report measure of susceptibility to scams, a battery of cognitive measures, and clinical diagnostic evaluations. RESULTS: In models adjusted for age, education, and gender, the presence of MCI was associated with greater susceptibility to scams (B = 0.125, SE = 0.063, p-value = 0.047). Further, in analyses of the role of specific cognitive systems in susceptibility to scams among persons with MCI (n = 144), the level of performance in two systems, episodic memory and perceptual speed abilities, were associated with susceptibility. CONCLUSIONS: Adults with MCI may be more susceptible to scams in old age than older persons with normal cognition. Lower abilities in specific cognitive systems, particularly perceptual speed and episodic memory, may contribute to greater susceptibility to scams in those with MCI.
Keywords: Aged; Aged, 80 and over; Aging; Cognitive Dysfunction; Crime Victims; Disease Susceptibility; Female; Humans; Male; Memory, Episodic; Middle Aged; Neuropsychological Tests; Psychiatric Status Rating Scales; Residence Characteristics; Self Report

miR-302 Attenuates Amyloid-β-Induced Neurotoxicity through Activation of Akt Signaling. - Li, Hsin-Hua; Lin, Shi-Lung; Huang, Chien-Ning; Lu, Fung-Jou; Chiu, Pai-Yi; Huang, Wen-Nung; Lai, Te-Jen; Lin, Chih-Li (J Alzheimers Dis, 2016)
Deficiency of insulin signaling has been linked to diabetes and ageing-related neurodegenerative diseases such as Alzheimer's disease (AD). In this regard, brains exhibit defective insulin receptor substrate-1 (IRS-1) and hence result in alteration of insulin signaling in progression of AD, the most common cause of dementia. Consequently, dysregulation of insulin signaling plays an important role in amyloid-β (Aβ)-induced neurotoxicity. As the derivation of induced pluripotent stem cells (iPSC) involves cell reprogramming, it may provide a means for regaining the control of ageing-associated dysfunction and neurodegeneration via affecting insulin-related signaling. To this, we found that an embryonic stem cell (ESC)-specific microRNA, miR-302, silences phosphatase and tensin homolog (PTEN) to activate Akt signaling, which subsequently stimulates nuclear factor erythroid 2-related factor 2 (Nrf2)/heme oxygenase-1 (HO-1) elevation and hence inhibits Aβ-induced neurotoxicity. miR-302 is predominantly expressed in iPSCs and is known to regulate several important biological processes of anti-oxidative stress, anti-apoptosis, and anti-aging through activating Akt signaling. In addition, we also found that miR-302-mediated Akt signaling further stimulates Nanog expression to suppress Aβ-induced p-Ser307 IRS-1 expression and thus enhances tyrosine phosphorylation and p-Ser 473-Akt/p-Ser 9-GSK3β formation. Furthermore, our in vivo studies revealed that the mRNA expression levels of both Nanog and miR-302-encoding LARP7 genes were significantly reduced in AD patients' blood cells, providing a novel diagnosis marker for AD. Taken together, our findings demonstrated that miR-302 is able to inhibit Aβ-induced cytotoxicity via activating Akt signaling to upregulate Nrf2 and Nanog expressions, leading to a marked restoration of insulin signaling in AD neurons.
Keywords: Aged; Aged, 80 and over; Amyloid beta-Peptides; Cell Line, Tumor; Cell Survival; Female; Glycogen Synthase Kinase 3 beta; Heme Oxygenase-1; Humans; Insulin; Male; Membrane Potential, Mitochondrial; MicroRNAs; Neurons; NF-E2-Related Factor 2; Oxidative Stress; Proto-Oncogene Proteins c-akt; PTEN Phosphohydrolase; Reactive Oxygen Species; Ribonucleoproteins

A Mitochondrial Role of SV2a Protein in Aging and Alzheimer's Disease: Studies with Levetiracetam. - Stockburger, Carola; Miano, Davide; Baeumlisberger, Marion; Pallas, Thea; Arrey, Tabiwang N; Karas, Michael; Friedland, Kristina; Müller, Walter E (J Alzheimers Dis, 2016)
Aberrant neuronal network activity associated with neuronal hyperexcitability seems to be an important cause of cognitive decline in aging and Alzheimer's disease (AD). Out of many antiepileptics, only levetiracetam improved cognitive dysfunction in AD patients and AD animal models by reducing hyperexcitability. As impaired inhibitory interneuronal function, rather than overactive neurons, seems to be the underlying cause, improving impaired neuronal function rather than quieting overactive neurons might be relevant in explaining the lack of activity of the other antiepileptics. Interestingly, improvement of cognitive deficits by levetiracetam caused by small levels of soluble Aβ was accompanied by improvement of synaptic function and plasticity. As the negative effects of Aβ on synaptic plasticity strongly correlate with mitochondrial dysfunction, wehypothesized that the effect of levetiracetam on synaptic activity might be raised by an improved mitochondrial function. Accordingly, we investigated possible effects of levetiracetam on neuronal deficits associated with mitochondrial dysfunction linked to aging and AD. Levetiracetam improved several aspects of mitochondrial dysfunction including alterations of fission and fusion balance in a cell model for aging and early late-onset AD. We demonstrate for the first time, using immunohistochemistry and proteomics, that the synaptic vesicle protein 2A (SV2a), the molecular target of levetiracetam, is expressed in mitochondria. In addition, levetiracetam shows significant effect on the opening of the mitochondrial permeability transition pore. Importantly, the effects of levetiracetam were significantly abolished when SV2a was knockdown using siRNA. In conclusion, interfering with the SV2a protein at the mitochondrial level and thereby improving mitochondrial function might represent an additional therapeutic effect of levetiracetam to improve symptoms of late-onset AD.
Keywords: Adenosine Triphosphate; Aging; Alzheimer Disease; Animals; Brain; Cell Line; Cognition Disorders; Female; GAP-43 Protein; Gene Expression Regulation; Humans; Male; Membrane Glycoproteins; Mitochondria; Mitochondrial Membrane Transport Proteins; Nerve Tissue Proteins; Nitroprusside; Nootropic Agents; Piracetam; Proteomics; Rats; RNA, Small Interfering

Modulation of miR-19 in Aluminum-Induced Neural Cell Apoptosis. - Zhu, Mingming; Huang, Cong; Ma, Xiao; Wu, Rui; Zhu, Weiwei; Li, Xiaoting; Liang, Zhaofeng; Deng, Feifei; Zhu, Jianyun; Xie, Wei; Yang, Xue; Jiang, Ye; et al. (J Alzheimers Dis, 2016)
Neuronal cell death is an important feature of neurodegeneration. Aluminum is associated with neurodegenerative disorders, particularly Alzheimer's disease. However, the underlying mechanisms by which aluminum induces neuronal apoptosis remain to be elucidated. miR-19 is a key miRNA implicated in regulating cell survival process, while the role of miR-19 in Alzheimer's disease has not been investigated. In the present study, we showed that Aluminum maltolate (Al-malt), a lipophilic Al complex which is a common component of human diet with the ability to facilitate the entry of Al into the brain, induced apoptosis in human neuroblastoma SH-SY5Y cells, along with downregulation of miR-19a/miR-19b, upregulation of miR-19-targeted PTEN, and alterations of its downstream apoptosis related proteins including AKT, p53, Bax, and Bcl-2. miR-19 overexpression attenuated Al-malt-induced apoptosis as well as changes in the expression of apoptosis related proteins in SH-SY5Y cells. We further revealed that exposure of rats to Al-malt for 12 weeks at doses relevant to human exposure significantly elevated Al concentrations in serum and brain tissues. Al-malt dose-dependently induced apoptosis in rat brain, as evidenced by increased caspase activation and increased TUNEL staining. Consistent with in vitro results, Al-malt reduced miR-19 expression and altered the expression of apoptotic related proteins in rat brain. Taken together, our data suggest for the first time that miR-19 modulation is critically involved in Al-induced neural cell apoptosis. Findings from this study could provide new insight into the molecular mechanisms of Al-associated neurodegenerative pathogenesis.
Keywords: Aluminum; Animals; Apoptosis; Brain; Cell Line, Tumor; Dose-Response Relationship, Drug; Humans; Male; MicroRNAs; Neurons; Proto-Oncogene Proteins c-akt; PTEN Phosphohydrolase; Rats, Sprague-Dawley; Tumor Suppressor Protein p53

Molecular markers of amnestic mild cognitive impairment among Mexican Americans. - Edwards, Melissa; Hall, James; Williams, Benjamin; Johnson, Leigh; O'Bryant, Sid (J Alzheimers Dis, 2016)
BACKGROUND: Mexican Americans face a significant health disparity when it comes to Alzheimer's disease (AD) as they present with higher rates of the disease and develop AD at an earlier age compared to other ethnic groups. Recent work identified a proteomic profile of AD among this population; however, no work to date has sought to examine the biological profile of pre-AD among Mexican Americans. OBJECTIVE: This study aims to identify an amnestic mild cognitive impairment (aMCI) proteomic profile among Mexican Americans. METHODS: Data were analyzed from 284 Mexican American participants (aMCI, n = 73; normal controls, n = 211) from the Health & Aging Brain among Latino Elders study. Fasting serum samples were analyzed using a multi-plex biomarker assay platform. A biomarker profile was generated using random forest analyses. RESULTS: Among aMCI cases, the biomarker profile was found to be largely inflammatory with the top three markers shown to include TNFα, IL10, and TARC. The overall diagnostic accuracy of the biomarkers in detecting aMCI was 96% (sensitivity = 0.82; specificity = 0.97). Inclusion of clinical variables with the selected biomarkers did not impact the overall detection accuracy (area under the curve = 0.96) but led to a slight improvement in specificity (specificity = 0.99) and decrease in sensitivity (sensitivity = 0.74). CONCLUSION: The biomarker profile of aMCI was shown to be different from our previously generated AD profile among Mexican Americans, which was largely metabolic in nature. The findings implicate a possible interplay between inflammatory and metabolic processes and additional work is needed to further examine this.
Keywords: Aged; Alzheimer Disease; Area Under Curve; Biomarkers; Cognitive Dysfunction; Female; Humans; Male; Mexican Americans; Middle Aged; Neuropsychological Tests; Proteome; Sensitivity and Specificity; United States

Morroniside-Induced PP2A Activation Antagonizes Tau Hyperphosphorylation in a Cellular Model of Neurodegeneration. - Yang, Cui-cui; Kuai, Xue-xian; Gao, Wen-bin; Yu, Jian-chun; Wang, Qi; Li, Lin; Zhang, Lan (J Alzheimers Dis, 2016)
BACKGROUND: An accumulation of hyperphosphorylated tau in the brain is a hallmark of Alzheimer's disease (AD). Deficits in protein phosphatase 2A (PP2A) are associated with tau hyperphosphorylation in AD. OBJECTIVE: To investigate the effects of morroniside (MOR), isolated from Cornus officinalis, on tau hyperphosphorylation and its underlying mechanisms related to PP2A. METHODS: SK-N-SH cells were pretreated with 50-200 μM MOR for 24 h followed by 20 nM okadaic acid (OA) for 6 h. PP2Ac siRNA was transfected into HEK293 cells to determine the direct interaction of MOR with PP2A. Western blotting was used to measure the expression of proteins and enzymes. PP2A activity was measured by molybdenum blue spectrophotometry. RESULTS: Pretreatment with MOR improved the cellular morphological damage and inhibited tau hyperphosphorylation in SK-N-SH cells induced by OA, a PP2A inhibitor. Moreover, MOR increased PP2A activity, concurrent with a decrease in the expression of demethylated PP2A at Leu309 and phosphorylated PP2A at Tyr307. MOR decreased protein phosphatase methylesterase 1 (PME-1) expression and the ratio of PME-1/leucine carboxyl methyltransferase 1 (LCMT-1). Furthermore, MOR treatment decreased the phosphorylation of Src at Tyr416, which regulates the phosphorylation of PP2A. MOR had no effect on PP2Ac expression and tau hyperphosphorylation in PP2Ac siRNA-transfected cells. CONCLUSION: MOR attenuated OA-induced tau hyperphosphorylation via PP2A activation, and its mechanism might be related to the regulation of PP2Ac post-translational modification and upstream enzymes such as Src and PME-1.
Keywords: Analysis of Variance; Cell Line; Enzyme Inhibitors; Gene Expression Regulation; Glycogen Synthase Kinase 3 beta; Glycosides; HEK293 Cells; Humans; Neuroblastoma; Okadaic Acid; Phosphorylation; Protein Phosphatase 2; RNA, Small Interfering; tau Proteins; Transfection; Tyrosine

Multifunctional Effect of Human Serum Albumin Reduces Alzheimer's Disease Related Pathologies in the 3xTg Mouse Model. - Ezra, Assaf; Rabinovich-Nikitin, Inna; Rabinovich-Toidman, Polina; Solomon, Beka (J Alzheimers Dis, 2016)
Alzheimer's disease (AD), the prevalent dementia in the elderly, involves many related and interdependent pathologies that manifests simultaneously, eventually leading to cognitive impairment and death. No treatment is currently available; however, an agent addressing several key pathologies simultaneously has a better therapeutic potential. Human serum albumin (HSA) is a highly versatile protein, harboring multifunctional properties that are relevant to key pathologies underlying AD. This study provides insight into the mechanism for HSA's therapeutic effect. In vivo, a myriad of beneficial effects were observed by pumps infusing HSA intracerebroventricularly, for the first time in an AD 3xTg mice model. A significant effect on amyloid-β (Aβ) pathology was observed. Aβ1-42, soluble oligomers, and total plaque area were reduced. Neuroblastoma SHSY5Y cell line confirmed that the reduction in Aβ1-42 toxicity was due to direct binding rather than other properties of HSA. Total and hyperphosphorylated tau were reduced along with an increase in tubulin, suggesting increased microtubule stability. HSA treatment also reduced brain inflammation, affecting both astrocytes and microglia markers. Finally, evidence for blood-brain barrier and myelin integrity repair was observed. These multidimensional beneficial effects of intracranial administrated HSA, together or individually, contributed to an improvement in cognitive tests, suggesting a non-immune or Aβ efflux dependent means for treating AD.
Keywords: Albumins; Alzheimer Disease; Amyloid beta-Peptides; Amyloid beta-Protein Precursor; Animals; Blood-Brain Barrier; Brain; Calcium; Cell Line, Tumor; Cognition Disorders; Disease Models, Animal; Drug Delivery Systems; Encephalitis; Humans; Male; Mice; Mice, Inbred C57BL; Mice, Transgenic; Mutation; Neuroblastoma; Neuropsychological Tests; Peptide Fragments; Presenilin-1; tau Proteins

Multimodal Magnetic Resonance Imaging in Alzheimer's Disease Patients at Prodromal Stage. - Eustache, Pierre; Nemmi, Federico; Saint-Aubert, Laure; Pariente, Jérémie; Péran, Patrice (J Alzheimers Dis, 2016)
One objective of modern neuroimaging is to identify markers that can aid in diagnosis, monitor disease progression, and impact long-term drug analysis. In this study, physiopathological modifications in seven subcortical structures of patients with mild cognitive impairment (MCI) due to Alzheimer's disease (AD) were characterized by simultaneously measuring quantitative magnetic resonance parameters that are sensitive to complementary tissue characteristics (e.g., volume atrophy, shape changes, microstructural damage, and iron deposition). Fourteen MCI patients and fourteen matched, healthy subjects underwent 3T-magnetic resonance imaging with whole-brain, T1-weighted, T2*-weighted, and diffusion-tensor imaging scans. Volume, shape, mean R2*, mean diffusivity (MD), and mean fractional anisotropy (FA) in the thalamus, hippocampus, putamen, amygdala, caudate nucleus, pallidum, and accumbens were compared between MCI patients and healthy subjects. Comparisons were then performed using voxel-based analyses of R2*, MD, FA maps, and voxel-based morphometry to determine which subregions showed the greatest difference for each parameter. With respect to the micro- and macro-structural patterns of damage, our results suggest that different and distinct physiopathological processes are present in the prodromal phase of AD. MCI patients had significant atrophy and microstructural changes within their hippocampi and amygdalae, which are known to be affected in the prodromal stage of AD. This suggests that the amygdala is affected in the same, direct physiopathological process as the hippocampus. Conversely, atrophy alone was observed within the thalamus and putamen, which are not directly involved in AD pathogenesis. This latter result may reflect another mechanism, whereby atrophy is linked to indirect physiopathological processes.
Keywords: Aged; Alzheimer Disease; Biomarkers; Brain; Cognitive Dysfunction; Diffusion Tensor Imaging; Female; Fluorodeoxyglucose F18; Humans; Magnetic Resonance Imaging; Male; Mental Status Schedule; Multimodal Imaging; Neuropsychological Tests; Organ Size; Positron-Emission Tomography; Prodromal Symptoms; Radiopharmaceuticals

Naphthoquinone-Tryptophan Hybrid Inhibits Aggregation of the Tau-Derived Peptide PHF6 and Reduces Neurotoxicity. - Frenkel-Pinter, Moran; Tal, Sharon; Scherzer-Attali, Roni; Abu-Hussien, Malak; Alyagor, Idan; Eisenbaum, Tal; Gazit, Ehud; Segal, Daniel (J Alzheimers Dis, 2016)
Tauopathies, such as Alzheimer's disease (AD), are a group of disorders characterized neuropathologically by intracellular toxic accumulations of abnormal protein aggregates formed by misfolding of the microtubule-associated protein tau. Since protein self-assembly appears to be an initial key step in the pathology of this group of diseases, intervening in this process can be both a prophylactic measure and a means for modifying the course of the disease for therapeutic purposes. We and others have shown that aromatic small molecules can be effective inhibitors of aggregation of various protein assemblies, by binding to the aromatic core in aggregation-prone motifs and preventing their self-assembly. Specifically, we have designed a series of small aromatic naphthoquinone-tryptophan hybrid molecules as candidate aggregation inhibitors of β -sheet based assembly and demonstrated their efficacy toward inhibiting aggregation of the amyloid-β peptide, another culprit of AD, as well as of various other aggregative proteins involved in other protein misfolding diseases. Here we tested whether a leading naphthoquinone-tryptophan hybrid molecule, namely NQTrp, can be repurposed as an inhibitor of the aggregation of the tau protein in vitro and in vivo. We show that the molecule inhibits the in vitro assembly of PHF6, the aggregation-prone fragment of tau protein, reduces hyperphosphorylated tau deposits and ameliorates tauopathy-related behavioral defect in an established transgenic Drosophila model expressing human tau. We suggest that NQTrp, or optimized versions of it, could act as novel disease modifying drugs for AD and other tauopathies.
Keywords: Animals; Carrier Proteins; Disease Models, Animal; Drosophila; Drosophila Proteins; Eye; Female; Humans; Immunoprecipitation; In Vitro Techniques; Larva; Locomotion; Mice, Transgenic; Microscopy, Electron, Scanning; Naphthoquinones; Neurotoxicity Syndromes; Protein Aggregates; Retinal Pigments; tau Proteins; Tryptophan

Neuronal activity and amyloid plaque pathology: an update. - Ovsepian, Saak V; O'Leary, Valerie B (J Alzheimers Dis, 2016)
A breakthrough in Alzheimer's disease (AD) research came with the discovery of the link between activity-dependent release of amyloid-β (Aβ) from neurons and formation of amyloid plaques. Along with elucidating the cellular basis of behavioral-dependent fluctuations in Aβ levels in the brain, insights have been gained toward understanding the mechanisms that warrant selective vulnerability of various forebrain circuits to amyloid pathology. The notion of elevated activity as a source of excessive Aβ production and plaque formation is, however, in conflict with ample electrophysiological data, which demonstrate exceedingly intense activity (both intrinsic and synaptic) of neurons in several brain regions that are spared or marginally affected by amyloid plaques of AD. Thus, the link between the functional load of brain circuits and their vulnerability to amyloidosis, while evident, is also complex and remains poorly understood. Here, we discuss emerging data suggestive of a major role for super-intense synchronous activity of cortical and limbic networks in excessive Aβ production and plaque formation. It is proposed that dense recurrent wiring of associative areas prone to epileptic seizures might be of critical relevance to their higher susceptibility to plaque pathology and related functional impairments.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Amyloid Precursor Protein Secretases; Amyloidosis; Animals; Disease Models, Animal; Humans; Mice; Mice, Transgenic; Neurons; Plaque, Amyloid; Prosencephalon; Seizures

Non-Verbal Episodic Memory Deficits in Primary Progressive Aphasias are Highly Predictive of Underlying Amyloid Pathology. - Ramanan, Siddharth; Flanagan, Emma; Leyton, Cristian E; Villemagne, Victor L; Rowe, Christopher C; Hodges, John R; Hornberger, Michael (J Alzheimers Dis, 2016)
Diagnostic distinction of primary progressive aphasias (PPA) remains challenging, in particular for the logopenic (lvPPA) and nonfluent/agrammatic (naPPA) variants. Recent findings highlight that episodic memory deficits appear to discriminate these PPA variants from each other, as only lvPPA perform poorly on these tasks while having underlying amyloid pathology similar to that seen in amnestic dementias like Alzheimer's disease (AD). Most memory tests are, however, language based and thus potentially confounded by the prevalent language deficits in PPA. The current study investigated this issue across PPA variants by contrasting verbal and non-verbal episodic memory measures while controlling for their performance on a language subtest of a general cognitive screen. A total of 203 participants were included (25 lvPPA; 29 naPPA; 59 AD; 90 controls) and underwent extensive verbal and non-verbal episodic memory testing, with a subset of patients (n = 45) with confirmed amyloid profiles as assessed by Pittsburgh Compound B and PET. The most powerful discriminator between naPPA and lvPPA patients was a non-verbal recall measure (Rey Complex Figure delayed recall), with 81% of PPA patients classified correctly at presentation. Importantly, AD and lvPPA patients performed comparably on this measure, further highlighting the importance of underlying amyloid pathology in episodic memory profiles. The findings demonstrate that non-verbal recall emerges as the best discriminator of lvPPA and naPPA when controlling for language deficits in high load amyloid PPA cases.
Keywords: Aged; Alzheimer Disease; Amyloid; Aniline Compounds; Aphasia, Primary Progressive; Brain; Diagnosis, Differential; Female; Humans; Logistic Models; Male; Memory, Episodic; Neuropsychological Tests; Positron-Emission Tomography; Radiopharmaceuticals; Speech Perception; Thiazoles

Normal Amplitude of Electroretinography and Visual Evoked Potential Responses in AβPP/PS1 Mice. - Leinonen, Henri; Lipponen, Arto; Gurevicius, Kestutis; Tanila, Heikki (J Alzheimers Dis, 2016)
Alzheimer's disease has been shown to affect vision in human patients and animal models. This may pose the risk of bias in behavior studies and therefore requires comprehensive investigation. We recorded electroretinography (ERG) under isoflurane anesthesia and visual evoked potentials (VEP) in awake amyloid expressing AβPPswe/PS1dE9 (AβPP/PS1) and wild-type littermate mice at a symptomatic age. The VEPs in response to patterned stimuli were normal in AβPP/PS1 mice. They also showed normal ERG amplitude but slightly shortened ERG latency in dark-adapted conditions. Our results indicate subtle changes in visual processing in aged male AβPP/PS1 mice specifically at a retinal level.
Keywords: Alzheimer Disease; Amyloid beta-Protein Precursor; Animals; Contrast Sensitivity; Disease Models, Animal; Electroencephalography; Electroretinography; Evoked Potentials, Visual; Humans; Male; Mice; Mice, Inbred C57BL; Mice, Transgenic; Mutation; Photic Stimulation; Presenilin-1; Reaction Time

Novel Selective Calpain 1 Inhibitors as Potential Therapeutics in Alzheimer's Disease. - Fà, Mauro; Zhang, Hong; Staniszewski, Agnieszka; Saeed, Faisal; Shen, Li W; Schiefer, Isaac T; Siklos, Marton I; Tapadar, Subhasish; Litosh, Vladislav A; Libien, Jenny; Petukhov, Pavel A; Teich, Andrew F; et al. (J Alzheimers Dis, 2016)
Alzheimer's disease, one of the most important brain pathologies associated with neurodegenerative processes, is related to overactivation of calpain-mediated proteolysis. Previous data showed a compelling efficacy of calpain inhibition against abnormal synaptic plasticity and memory produced by the excess of amyloid-β, a distinctive marker of the disease. Moreover, a beneficial effect of calpain inhibitors in Alzheimer's disease is predictable by the occurrence of calpain hyperactivation leading to impairment of memory-related pathways following abnormal calcium influxes that might ensue independently of amyloid-β elevation. However, molecules currently available as effective calpain inhibitors lack adequate selectivity. This work is aimed at characterizing the efficacy of a novel class of epoxide-based inhibitors, synthesized to display improved selectivity and potency towards calpain 1 compared to the prototype epoxide-based generic calpain inhibitor E64. Both functional and preliminary toxicological investigations proved the efficacy, potency, and safety of the novel and selective calpain inhibitors NYC438 and NYC488 as possible therapeutics against the disease.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Amyloid beta-Protein Precursor; Animals; Cysteine Proteinase Inhibitors; Disease Models, Animal; Dose-Response Relationship, Drug; Fear; Glycoproteins; Hippocampus; Humans; In Vitro Techniques; Long-Term Potentiation; Maze Learning; Memory; Mice; Mice, Inbred ICR; Mice, Transgenic; Mutation; Patch-Clamp Techniques; Peptide Fragments; Presenilin-1; Spectrin

N-truncated Aβ2-X starting with position two in sporadic Alzheimer's disease cases and two Alzheimer mouse models. - Savastano, Adriana; Klafki, Hans; Haußmann, Ute; Oberstein, Timo Jan; Muller, Petr; Wirths, Oliver; Wiltfang, Jens; Bayer, Thomas A (J Alzheimers Dis, 2016)
According to the modified amyloid hypothesis, the key event in the pathogenesis of Alzheimer's disease (AD) is the deposition of neurotoxic amyloid β-peptides (Aβs) in plaques and cerebral blood vessels. Additionally to full-length peptides, a great diversity of N-truncated Aβ variants is derived from the larger amyloid-β protein precursor (AβPP). Vast evidence suggests that Aβx-42 isoforms play an important role in triggering neurodegeneration due to their high abundance, amyloidogenic propensity and toxicity. Although N-truncated Aβ peptides and Aβx-42 species appear to be the crucial players in AD etiology, the Aβ2-X isoforms did not receive much attention yet. The present study is the first to show immunohistochemical evidence of Aβ2-X in cases of AD and its distribution in AβPP/PS1KI and 5XFAD transgenic mouse models using a novel antibody pAB77 that has been developed using Aβ2-14 as antigen. Positive plaques and congophilic amyloid angiopathy (CAA) were observed in AD cases and in both mouse models. While in AD cases, abundant CAA and less pronounced plaque pathology was evident, the two mouse models showed predominantly extracellular Aβ deposits and minor CAA staining. Western blotting and a capillary isoelectric focusing immunoassay demonstrated the high specificity of the antibody pAb77 against Aβ-variants starting with the N-terminal Alanine-2.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Animals; Blotting, Western; Brain; Cerebral Amyloid Angiopathy; Disease Models, Animal; Female; Humans; Male; Mice; Mice, Transgenic; Plaque, Amyloid

Older Adults Taking AT1-Receptor Blockers Exhibit Reduced Cerebral Amyloid Retention. - Nation, Daniel A; Ho, Jean; Yew, Belinda (J Alzheimers Dis, 2016)
BACKGROUND: Evidence suggests that angiotensin II AT1-receptor blockers (ARBs) may be protective against dementia, and studies in transgenic animals indicate that this may be due to improved amyloid-β (Aβ) clearance. OBJECTIVE: We investigated whether taking ARBs was associated with an attenuation of age-related increases in cerebral Aβ retention, and reduced progression to dementia. METHODS: Eight hundred seventy-one stroke-free and dementia-free older adults from the Alzheimer's Disease Neuroimaging Initiative (ADNI) study underwent baseline lumbar puncture, and a subgroup (n = 124) underwent 12 and 24 month follow-up lumbar puncture. Participants were followed at variable intervals for clinical progression to dementia. Linear mixed models and ANCOVA compared ARBs users with those taking other antihypertensives (O-antiHTN) or no antihypertensives (No-antiHTN) on cerebrospinal fluid (CSF) Aβ and phosphorylated tau (P-tau) levels. Cox regression and chi-square analyses compared groups on progression to dementia. RESULTS: ARBs users exhibited greater vascular risk and lower educational attainment than the No-antiHTN group. Longitudinal analyses indicated higher CSF Aβ and lower P-tau in ARBs users versus other groups. Cross-sectional analyses revealed age-related decreases in CSF Aβ in other groups but not ARBs users. ARBs users were less likely to progress to dementia and showed reduced rate of progression relative to the No-antiHTN group. DISCUSSION: Patients taking ARBs showed an attenuation of age-related decreases in CSF Aβ, a finding that is consistent with studies done in transgenic animals. These findings may partly explain why ARBs users show reduced progression to dementia despite their lower educational attainment and greater vascular risk burden.
Keywords: Aged; Aged, 80 and over; Aging; Amyloid beta-Peptides; Angiotensin Receptor Antagonists; Antihypertensive Agents; Chi-Square Distribution; Cross-Sectional Studies; Dementia; Female; Humans; Longitudinal Studies; Male; Middle Aged; Peptide Fragments; Psychiatric Status Rating Scales; Regression Analysis; tau Proteins; Time Factors

Optimization of Statistical Single Subject Analysis of Brain FDG PET for the Prognosis of Mild Cognitive Impairment-to-Alzheimer's Disease Conversion. - Lange, Catharina; Suppa, Per; Frings, Lars; Brenner, Winfried; Spies, Lothar; Buchert, Ralph (J Alzheimers Dis, 2016)
BACKGROUND: Positron emission tomography (PET) with the glucose analog F-18-fluorodeoxyglucose (FDG) is widely used in the diagnosis of neurodegenerative diseases. Guidelines recommend voxel-based statistical testing to support visual evaluation of the PET images. However, the performance of voxel-based testing strongly depends on each single preprocessing step involved. OBJECTIVE: To optimize the processing pipeline of voxel-based testing for the prognosis of dementia in subjects with amnestic mild cognitive impairment (MCI). METHODS: The study included 108 ADNI MCI subjects grouped as 'stable MCI' (n = 77) or 'MCI-to-AD converter' according to their diagnostic trajectory over 3 years. Thirty-two ADNI normals served as controls. Voxel-based testing was performed with the statistical parametric mapping software (SPM8) starting with default settings. The following modifications were added step-by-step: (i) motion correction, (ii) custom-made FDG template, (iii) different reference regions for intensity scaling, and (iv) smoothing was varied between 8 and 18 mm. The t-sum score for hypometabolism within a predefined AD mask was compared between the different settings using receiver operating characteristic (ROC) analysis with respect to differentiation between 'stable MCI' and 'MCI-to-AD converter'. The area (AUC) under the ROC curve was used as performance measure. RESULTS: The default setting provided an AUC of 0.728. The modifications of the processing pipeline improved the AUC up to 0.832 (p = 0.046). Improvement of the AUC was confirmed in an independent validation sample of 241 ADNI MCI subjects (p = 0.048). CONCLUSION: The prognostic value of voxel-based single subject analysis of brain FDG PET in MCI subjects can be improved considerably by optimizing the processing pipeline.
Keywords: Aged; Alzheimer Disease; Area Under Curve; Brain; Cognitive Dysfunction; Disease Progression; Female; Fluorodeoxyglucose F18; Follow-Up Studies; Glucose; Humans; Image Interpretation, Computer-Assisted; Male; Positron-Emission Tomography; Prognosis; Radiopharmaceuticals; ROC Curve

An Optimized Combination of Ginger and Peony Root Effectively Inhibits Amyloid-β Accumulation and Amyloid-β-Mediated Pathology in AβPP/PS1 Double-Transgenic Mice. - Lim, Soonmin; Choi, Jin Gyu; Moon, Minho; Kim, Hyo Geun; Lee, Wonil; Bak, Hyoung-Rok; Sung, Hachang; Park, Chi Hye; Kim, Sun Yeou; Oh, Myung Sook (J Alzheimers Dis, 2016)
The progressive aggregation of amyloid-β protein (Aβ) into senile plaques is a major pathological factor of Alzheimer's disease (AD) and is believed to result in memory impairment. We aimed to investigate the effect of an optimized combination of ginger and peony root (OCGP), a standardized herbal mixture of ginger and peony root, on Aβ accumulation and memory impairment in amyloid-β protein precursor (AβPP)/presenilin 1 (PS1) double-transgenic mice. In an in vitro thioflavin T fluorescence assay, 100 μg/ml OCGP inhibited Aβ accumulation to the same extent as did 10 μM curcumin. Furthermore, AβPP/PS1 double-transgenic mice treated with OCGP (50 or 100 mg/kg/day given orally for 14 weeks) exhibited reduced Aβ plaque accumulation in the hippocampus and lower levels of glial fibrillary acid protein and cyclooxygease-2 expression compared with vehicle-treated controls. These results suggest that OCGP may prevent memory impairment in AD by inhibiting Aβ accumulation and inflammation in the brain.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Amyloid beta-Protein Precursor; Analysis of Variance; Animals; Cyclooxygenase 2; Disease Models, Animal; Dose-Response Relationship, Drug; Ginger; Glial Fibrillary Acidic Protein; Humans; Male; Mice; Mice, Transgenic; Mutation; Paeonia; Phytotherapy; Plant Preparations; Plaque, Amyloid; Presenilin-1

The Oral Iron Chelator, Deferasirox, Reverses the Age-Dependent Alterations in Iron and Amyloid-β Homeostasis in Rat Brain: Implications in the Therapy of Alzheimer's Disease. - Banerjee, Priyanjalee; Sahoo, Arghyadip; Anand, Shruti; Bir, Aritri; Chakrabarti, Sasanka (J Alzheimers Dis, 2016)
The altered metabolism of iron impacts the brain function in multiple deleterious ways during normal aging as well as in Alzheimer's disease. We have shown in this study that chelatable iron accumulates in the aged rat brain along with overexpression of transferrin receptor 1 (TfR1) and ferritin, accompanied by significant alterations in amyloid-β (Aβ) peptide homeostasis in the aging brain, such as an increased production of the amyloid-β protein precursor, a decreased level of neprilysin, and increased accumulation of Aβ42. When aged rats are given daily the iron chelator, deferasirox, over a period of more than 4 months starting from the 18th month, the age-related accumulation of iron and overexpression of TfR1 and ferritin in the brain are significantly prevented. More interestingly, the chelator treatment also considerably reverses the altered Aβ peptide metabolism in the aging brain implying a significant role of iron in the latter phenomenon. Further, other results indicate that iron accumulation results in oxidative stress and the activation of NF-κB in the aged rat brain, which are also reversed by the deferasirox treatment. The analysis of the results together suggests that iron accumulation and oxidative stress interact at multiple levels that include transcriptional and post-transcriptional mechanisms to bring about changes in the expression levels of TfR1 and ferritin and also alterations in Aβ peptide metabolism in the aging rat brain. The efficacy of deferasirox in preventing age-related changes in iron and Aβ peptide metabolism in the aging brain, as shown here, has obvious therapeutic implications for Alzheimer's disease.
Keywords: Administration, Oral; Aging; Amyloid beta-Peptides; Amyloid beta-Protein Precursor; Amyloid Precursor Protein Secretases; Animals; Benzoates; Brain; Ferritins; Gene Expression Regulation; Iron; Iron Chelating Agents; Neprilysin; NF-kappa B; Oxidative Stress; Peptide Fragments; Protein Carbonylation; Rats; Rats, Wistar; Receptors, Transferrin; Spectrophotometry; Triazoles

Overexpression of Metallothionein-1 Modulates the Phenotype of the Tg2576 Mouse Model of Alzheimer's Disease. - Manso, Yasmina; Comes, Gemma; López-Ramos, Juan C; Belfiore, Mónica; Molinero, Amalia; Giralt, Mercedes; Carrasco, Javier; Adlard, Paul A; Bush, Ashley I; Delgado-García, José María; Hidalgo, Juan (J Alzheimers Dis, 2016)
Alzheimer's disease (AD) is the most commonly diagnosed dementia, where signs of neuroinflammation and oxidative stress are prominent. In this study we intend to further characterize the roles of the antioxidant, anti-inflammatory, and heavy metal binding protein, metallothionein-1 (MT-1), by crossing Mt1 overexpressing mice with a well-known mouse model of AD, Tg2576 mice, which express the human amyloid-β protein precursor (hAβPP) with the Swedish K670N/M671L mutations. Mt1 overexpression increased overall perinatal survival, but did not affect significantly hAβPP-induced mortality and weight loss in adult mice. Amyloid plaque burden in ∼14-month-old mice was increased by Mt1 overexpression in the hippocampus but not the cortex. Despite full length hAβPP levels and amyloid plaques being increased by Mt1 overexpression in the hippocampus of both sexes, oligomeric and monomeric forms of Aβ, which may contribute more to toxicity, were decreased in the hippocampus of females and increased in males. Several behavioral traits such as exploration, anxiety, and learning were altered in Tg2576 mice to various degrees depending on the age and the sex. Mt1 overexpression ameliorated the effects of hAβPP on exploration in young females, and potentiated those on anxiety in old males, and seemed to improve the rate of spatial learning (Morris water maze) and the learning elicited by a classical conditioning procedure (eye-blink test). These results clearly suggest that MT-1 may be involved in AD pathogenesis.
Keywords: Age Factors; Alzheimer Disease; Amyloid beta-Protein Precursor; Animals; Anxiety; Disease Models, Animal; Exploratory Behavior; Female; Gene Expression Regulation; Humans; Male; Matrix Metalloproteinase 16; Maze Learning; Metallothionein; Mice; Mice, Inbred C57BL; Mice, Transgenic; Motor Activity; Mutation; Phenotype; Psychomotor Disorders

Pain Assessment in Elderly with Behavioral and Psychological Symptoms of Dementia. - Malara, Alba; De Biase, Giuseppe Andrea; Bettarini, Francesco; Ceravolo, Francesco; Di Cello, Serena; Garo, Michele; Praino, Francesco; Settembrini, Vincenzo; Sgrò, Giovanni; Spadea, Fausto; Rispoli, Vincenzo (J Alzheimers Dis, 2016)
BACKGROUND: Pain is under-detected and undertreated in people with dementia. The present study investigates the prevalence of pain in people with dementia hospitalized in nursing homes that are members of National Association of Third Age Residences (ANASTE) Calabria, and evaluates the association among pain, mood, and behavioral and psychological symptoms of dementia (BPSD). OBJECTIVE: The aim of this study is to define the prevalence of pain in people with dementia in long term care facilities using scales of self-reporting and observational tools and, particularly, to study the relationship between pain and BPSD. METHODS: A prospective observational study was carried out on 233 patients. Pain assessment was performed using self-reporting tools such as the Numeric Rating Scale (NRS) for patients with slight cognitive impairment or no cognitive impairment and observational tools such as Pain Assessment In Advanced Dementia Scale (PAINAD) for patients with moderate or severe cognitive impairment. Mood was evaluated through the Cornell Scale for Depression in Dementia (CSDD) while behavioral problems were assessed through the Cohen-Mansfield Agitation Inventory (CMAI) and Neuropsychiatric Inventory (NPI). RESULTS: Only 42.5% of patients evaluated by NRS provided a reliable answer; of these, 20.4% reported no pain. The percentage of pain evaluated by PAINAD was 51.8% . Analysis of data showed a statistically significant correlation between diagnosis of pain and depressive symptoms, assessed with CSDD (p = 0.0113), as well as by single items of NPI, such as anxiety (p = 0.0362) and irritability (p = 0.0034), and F1 profile (Aggression) of CMAI (p = 0.01). CONCLUSION: This study confirms that self-report alone is not sufficient to assess pain in elderly people with dementia; the observational tool is a necessary and suitable way of assessing pain in patients with cognitive impairment. If not adequately treated, chronic pain can cause depression, agitation, and aggression in patients with dementia.
Keywords: Affect; Aged, 80 and over; Analgesics; Anxiety; Dementia; Depression; Female; Humans; Italy; Logistic Models; Long-Term Care; Male; Multivariate Analysis; Nursing Homes; Pain; Pain Measurement; Prevalence; Prospective Studies; Psychiatric Status Rating Scales; Self Report; Severity of Illness Index

Patients that have Undergone Hemodialysis Exhibit Lower Amyloid Deposition in the Brain: Evidence Supporting a Therapeutic Strategy for Alzheimer's Disease by Removal of Blood Amyloid. - Sakai, Kazuyoshi; Senda, Takao; Hata, Ryuji; Kuroda, Makoto; Hasegawa, Midori; Kato, Masao; Abe, Masato; Kawaguchi, Kazunori; Nakai, Shigeru; Hiki, Yoshiyuki; Yuzawa, Yukio; Kitaguchi, Nobuya (J Alzheimers Dis, 2016)
As a proof of concept that removal of blood amyloid-β (Aβ) can reduce Aβ deposition in the brains of patients with Alzheimer's disease, cortices of patients who had undergone hemodialysis (HD), which removes Aβ from the blood, were histochemically analyzed; postmortem brain sections were stained with anti-Aβ antibodies. Brains from patients who had undergone HD had significantly fewer senile plaques than those of patient who had not undergone HD. This significant difference was also confirmed by silver staining. Our findings suggest that removal of blood Aβ by hemodialysis results in lower accumulation of Aβ in the brain.
Keywords: Aged; Aged, 80 and over; Amyloid beta-Peptides; Autopsy; Brain; Case-Control Studies; Humans; Kidney Diseases; Plaque, Amyloid; Renal Dialysis; Silver Staining; Statistics, Nonparametric

Patients with Mild Alzheimer's Disease Fail When Using Their Working Memory: Evidence from the Eye Tracking Technique. - Fernández, Gerardo; Manes, Facundo; Politi, Luis E; Orozco, David; Schumacher, Marcela; Castro, Liliana; Agamennoni, Osvaldo; Rotstein, Nora P (J Alzheimers Dis, 2016)
Patients with Alzheimer's disease (AD) develop progressive language, visuoperceptual, attentional, and oculomotor changes that can have an impact on their reading comprehension. However, few studies have examined reading behavior in AD, and none have examined the contribution of predictive cueing in reading performance. For this purpose we analyzed the eye movement behavior of 35 healthy readers (Controls) and 35 patients with probable AD during reading of regular and high-predictable sentences. The cloze predictability of words N - 1, and N + 1 exerted an influence on the reader's gaze duration. The predictabilities of preceding words in high-predictable sentences served as task-appropriate cues that were used by Control readers. In contrast, these effects were not present in AD patients. In Controls, changes in predictability significantly affected fixation duration along the sentence; noteworthy, these changes did not affect fixation durations in AD patients. Hence, only in healthy readers did predictability of upcoming words influence fixation durations via memory retrieval. Our results suggest that Controls used stored information of familiar texts for enhancing their reading performance and imply that contextual-word predictability, whose processing is proposed to require memory retrieval, only affected reading behavior in healthy subjects. In AD patients, this loss reveals impairments in brain areas such as those corresponding to working memory and memory retrieval. These findings might be relevant for expanding the options for the early detection and monitoring in the early stages of AD. Furthermore, evaluation of eye movements during reading could provide a new tool for measuring drug impact on patients' behavior.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Eye Movements; Female; Humans; Linear Models; Magnetic Resonance Imaging; Male; Memory Disorders; Memory, Short-Term; Mental Recall; Mental Status Schedule; Predictive Value of Tests; Semantics; Verbal Learning

Pauses During Autobiographical Discourse Reflect Episodic Memory Processes in Early Alzheimer's Disease. - Pistono, Aurélie; Jucla, Mélanie; Barbeau, Emmanuel J; Saint-Aubert, Laure; Lemesle, Béatrice; Calvet, Benjamin; Köpke, Barbara; Puel, Michèle; Pariente, Jérémie (J Alzheimers Dis, 2016)
There is a large body of research on discourse production in Alzheimer's disease (AD). Some studies have focused on pause production, revealing that patients make extensive use of pauses during speech. This has been attributed to lexical retrieval difficulties, but pausing may also reflect other forms of cognitive impairment as it increases with cognitive load. The aim of the present study was to analyze autobiographical discourse impairment in AD from a broad perspective, looking at pausing behavior (frequency, duration, and location). Our first objective was to characterize discourse changes in mild cognitive impairment (MCI) due to AD. Our second objective was to determine the cognitive and neuroanatomical correlates of these changes. Fifteen patients with MCI due to AD and 15 matched cognitively normal controls underwent an ecological episodic memory task, a full neuropsychological assessment, and a 3D T1-weighted MRI scans. Autobiographical discourse collected from the ecological episodic memory task was recorded, transcribed, and analyzed, focusing on pausing. Intergroup comparisons showed that although patients did not produce more pauses than controls overall, they did make more between-utterance pauses. The number of these specific pauses was positively correlated with patients' episodic memory performance. Furthermore, neuroimaging analysis showed that, in the patient group, their use was negatively correlated with frontopolar area (BA 10) grey matter density. This region may therefore play an important role in the planning of autobiographical discourse production. These findings demonstrate that pauses in early AD may reflect a compensatory mechanism for improving mental time travel and memory retrieval.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid; Brain; Female; Humans; Male; Memory Disorders; Memory, Episodic; Mental Status Schedule; Neuropsychological Tests; Positron-Emission Tomography; Statistics as Topic

PDE5 Exists in Human Neurons and is a Viable Therapeutic Target for Neurologic Disease. - Teich, Andrew F; Sakurai, Mikako; Patel, Mitesh; Holman, Cameron; Saeed, Faisal; Fiorito, Jole; Arancio, Ottavio (J Alzheimers Dis, 2016)
Phosphodiesterase 5 (PDE5) is a critical component of the cGMP-PKG axis of cellular signaling in neurons, and inhibition of PDE5 has been shown to be therapeutic in a wide range of neurologic conditions in animal models. However, enthusiasm for PDE5 inhibitors in humans is limited by data suggesting that PDE5 may not exist in human neurons. Here, we first show that past attempts to quantify PDE5 mRNA were flawed due to the use of incorrect primers, and that when correct primers are used, PDE5 mRNA is detectable in human brain tissue. We then show that PDE5 protein exists in human brain by western blot and ELISA. Most importantly, we performed immunohistochemistry and demonstrate that PDE5 is present in human neurons. We hope that this work will trigger a renewed interest in the development of PDE5 inhibitors for neurologic disease.
Keywords: Blotting, Western; Brain; Cyclic Nucleotide Phosphodiesterases, Type 5; DNA Primers; Enzyme-Linked Immunosorbent Assay; Humans; Immunohistochemistry; Nervous System Diseases; Neurons; Phosphodiesterase 5 Inhibitors; Polymerase Chain Reaction; RNA, Messenger

Performance of Hippocampus Volumetry with FSL-FIRST for Prediction of Alzheimer's Disease Dementia in at Risk Subjects with Amnestic Mild Cognitive Impairment. - Suppa, Per; Hampel, Harald; Kepp, Timo; Lange, Catharina; Spies, Lothar; Fiebach, Jochen B; Dubois, Bruno; Buchert, Ralph (J Alzheimers Dis, 2016)
MRI-based hippocampus volume, a core feasible biomarker of Alzheimer's disease (AD), is not yet widely used in clinical patient care, partly due to lack of validation of software tools for hippocampal volumetry that are compatible with routine workflow. Here, we evaluate fully-automated and computationally efficient hippocampal volumetry with FSL-FIRST for prediction of AD dementia (ADD) in subjects with amnestic mild cognitive impairment (aMCI) from phase 1 of the Alzheimer's Disease Neuroimaging Initiative. Receiver operating characteristic analysis of FSL-FIRST hippocampal volume (corrected for head size and age) revealed an area under the curve of 0.79, 0.70, and 0.70 for prediction of aMCI-to-ADD conversion within 12, 24, or 36 months, respectively. Thus, FSL-FIRST provides about the same power for prediction of progression to ADD in aMCI as other volumetry methods.
Keywords: Aged; Aging; Alzheimer Disease; Area Under Curve; Cognitive Dysfunction; Databases, Factual; Disease Progression; Hippocampus; Humans; Image Interpretation, Computer-Assisted; Magnetic Resonance Imaging; Neuropsychological Tests; Organ Size; Pattern Recognition, Automated; Prognosis; Reproducibility of Results; Risk; ROC Curve; Sensitivity and Specificity; Time Factors

Performance on Specific Cognitive Domains and Cause of Death: A Prospective Population-Based Study in Non-Demented Older Adults (NEDICES). - Benito-León, Julián; Contador, Israel; Mitchell, Alex J; Domingo-Santos, Ángela; Bermejo-Pareja, Félix (J Alzheimers Dis, 2016)
Evidence regarding the relationship between performance on specific cognitive domains and cause of death is scarce. We assessed whether specific cognitive domains predicted mortality and the presence of any association with specific causes of death in a population-dwelling sample of non-demented older adults. In this population-based, prospective study (NEDICES), 2,390 non-demented subjects ≥65 years completed a brief neuropsychological battery. Cox's proportional hazards models, adjusted by sociodemographic and comorbidity factors, global cognitive performance, educational level, and premorbid intelligence were used to assess the risk of death. Participants were followed for a median of 9.2 years (range 0.01-10.7), after which the death certificates of those who died were examined. 880 (36.8%) of 2,390 participants died over a median follow-up of 5.5 years (range 0.01-10.5). Using adjusted Cox regression models, we found that hazard ratios for mortality in participants within the lowest tertiles (worse performance) were 1.31 (speed of cognitive processing, p = 0.03); 1.22 (semantic fluency, p = 0.04), 1.32 (delayed free recall, p = 0.003), and 1.23 (delayed logical memory, p = 0.03). Poor performance on delayed recall and speed of cognitive processing tests were associated with dementia and cerebrovascular disease mortality, respectively. Further, poor performance on semantic fluency was associated with decreased cancer mortality. In this study of community dwelling non-demented older adults, worse neuropsychological performance was associated with increased risk of mortality. Performance on specific cognitive domains were related to different causes of death. Of particular note there appears to be an inverse association between poor semantic fluency and cancer mortality.
Keywords: Aged; Cause of Death; Cerebrovascular Disorders; Cognitive Aging; Dementia; Educational Status; Female; Follow-Up Studies; Humans; Intelligence; Longitudinal Studies; Male; Neuropsychological Tests; Prospective Studies; Risk; Spain

Plasma Phospholipid and Sphingolipid Alterations in Presenilin1 Mutation Carriers: A Pilot Study. - Chatterjee, Pratishtha; Lim, Wei L F; Shui, Guanghou; Gupta, Veer B; James, Ian; Fagan, Anne M; Xiong, Chengjie; Sohrabi, Hamid R; Taddei, Kevin; Brown, Belinda M; Benzinger, Tammie; Masters, Colin; et al. (J Alzheimers Dis, 2016)
BACKGROUND AND OBJECTIVE: Aberrant lipid metabolism has been implicated in sporadic Alzheimer's disease (AD). The current study investigated plasma phospholipid and sphingolipid profiles in individuals carrying PSEN1 mutations responsible for autosomal dominant AD (ADAD). METHODS: Study participants evaluated were from the Perth and Melbourne sites of the Dominantly Inherited Alzheimer Network (DIAN) study. Plasma phospholipid and sphingolipid profiles were measured using liquid chromatography coupled with mass spectrometry in 20 PSEN1 mutation carriers (MC; eight of whom were symptomatic and twelve asymptomatic, based on Clinical Dementia Rating scores) and compared with six non carriers (NC) using linear mixed models. Further, AD gold standard biomarker data obtained from the DIAN database were correlated with lipid species significantly altered between MC and NC, using Spearman's correlation coefficient. RESULTS: One-hundred and thirty-nine plasma phospholipid and sphingolipid species were measured. Significantly altered species in MC compared to NC primarily belonged to choline and ethanolamine containing phospholipid classes and ceramides. Further phosphatidylcholine species (34:6, 36:5, 40:6) correlated with cerebrospinal fluid tau (p <  0.05), and plasmalogen ethanolamine species (34:2, 36:,4) correlated with both cerebrospinal fluid tau and brain amyloid load within the MC group (p <  0.05). CONCLUSION: These findings indicate altered phospholipid and sphingolipid metabolism in ADAD and provide insight into the pathomolecular changes occurring with ADAD pathogenesis. Further, findings reported in this study allow comparison of lipid alterations in ADAD with those reported previously in sporadic AD. The findings observed in the current pilot study warrant validation in the larger DIAN cohort.
Keywords: Adult; Alzheimer Disease; Apolipoproteins E; Female; Humans; Linear Models; Male; Middle Aged; Mutation; Phospholipids; Pilot Projects; Presenilin-1; Sphingolipids

Posterior Accumulation of Tau and Concordant Hypometabolism in an Early-Onset Alzheimer's Disease Patient with Presenilin-1 Mutation. - Smith, Ruben; Wibom, Moa; Olsson, Tomas; Hägerström, Douglas; Jögi, Jonas; Rabinovici, Gil D; Hansson, Oskar (J Alzheimers Dis, 2016)
It is unclear whether the distribution of tau pathology differs between cases with early-onset familial Alzheimer's disease (AD) and sporadic AD. We present positron emission tomography (PET) data from a young patient with a presenilin-1 mutation (Thr116Asn). 18F-flutemetamol PET showed a distribution of amyloid-β fibrils similar to sporadic AD. However, the pattern of tau pathology, revealed using 18F-AV1451 PET, showed higher uptake in posterior cingulate, precuneus, parietal and occipital cortices compared to late-onset sporadic AD. Further, the tau pathology, but not amyloid pathology, exhibited a very clear inverse relationship with 18F-fluorodeoxyglucose-metabolism, indicating neuronal hypometabolism in regions affected by tau aggregates.
Keywords: Adult; Age of Onset; Alzheimer Disease; Amyloid beta-Peptides; Aniline Compounds; Benzothiazoles; Brain; Brain Mapping; Fluorodeoxyglucose F18; Humans; Magnetic Resonance Imaging; Male; Positron-Emission Tomography; Presenilin-1; Radiopharmaceuticals; tau Proteins

Prediction of Progressive Mild Cognitive Impairment by Multi-Modal Neuroimaging Biomarkers. - Xu, Lele; Wu, Xia; Li, Rui; Chen, Kewei; Long, Zhiying; Zhang, Jiacai; Guo, Xiaojuan; Yao, Li (J Alzheimers Dis, 2016)
For patients with mild cognitive impairment (MCI), the likelihood of progression to probable Alzheimer's disease (AD) is important not only for individual patient care, but also for the identification of participants in clinical trial, so as to provide early interventions. Biomarkers based on various neuroimaging modalities could offer complementary information regarding different aspects of disease progression. The current study adopted a weighted multi-modality sparse representation-based classification method to combine data from the Alzheimer's Disease Neuroimaging Initiative (ADNI) database, from three imaging modalities: Volumetric magnetic resonance imaging (MRI), fluorodeoxyglucose (FDG) positron emission tomography (PET), and florbetapir PET. We included 117 normal controls (NC) and 110 MCI patients, 27 of whom progressed to AD within 36 months (pMCI), while the remaining 83 remained stable (sMCI) over the same time period. Modality-specific biomarkers were identified to distinguish MCI from NC and to predict pMCI among MCI. These included the hippocampus, amygdala, middle temporal and inferior temporal regions for MRI, the posterior cingulum, precentral, and postcentral regions for FDG-PET, and the hippocampus, amygdala, and putamen for florbetapir PET. Results indicated that FDG-PET may be a more effective modality in discriminating MCI from NC and in predicting pMCI than florbetapir PET and MRI. Combining modality-specific sensitive biomarkers from the three modalities boosted the discrimination accuracy of MCI from NC (76.7%) and the prediction accuracy of pMCI (82.5%) when compared with the best single-modality results (73.6% for MCI and 75.6% for pMCI with FDG-PET).
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Aniline Compounds; Biomarkers; Brain; Cognitive Dysfunction; Disease Progression; Ethylene Glycols; Female; Fluorodeoxyglucose F18; Humans; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Male; Positron-Emission Tomography; Predictive Value of Tests; Psychiatric Status Rating Scales; Sensitivity and Specificity

Predictive Value of Cerebrospinal Fluid Visinin-Like Protein-1 Levels for Alzheimer's Disease Early Detection and Differential Diagnosis in Patients with Mild Cognitive Impairment. - Babić Leko, Mirjana; Borovečki, Fran; Dejanović, Nenad; Hof, Patrick R; Šimić, Goran (J Alzheimers Dis, 2016)
Visinin-like protein 1 (VILIP-1) recently emerged as a potential biomarker of Alzheimer's disease (AD). This neuronal calcium sensor protein previously used as a marker of acute ischemic stroke is elevated in the cerebrospinal fluid (CSF) of AD patients. The goal of this study was to assess CSF VILIP-1 potential in early AD diagnosis and in differentiating mild cognitive impairment (MCI) patients with and without risk of AD. Additionally, we tested VILIP-1 ability to differentiate AD from other primary causes of dementia, and predict the progression of AD-related cognitive decline. VILIP-1 levels were compared with five CSF AD biomarkers (t-tau, Aβ1-42, p-tau181, p-tau199, and p-tau231). VILIP-1 successfully differentiated two MCI patient groups characterized by absence or presence of pathological levels of these CSF biomarkers, except for t-tau. VILIP-1/Aβ(1-42) and VILIP-1/p-tau181 ratios also differentiated MCI patients with pathological CSF biomarker levels. However, there was no difference in VILIP-1 levels between AD and MCI patients. VILIP-1/Aβ(1-42) and VILIP-1/p-tau231 ratios reached high sensitivities (above 70%) and very high specificities (above 85%) in differentiating AD patients from HC. Additionally, VILIP-1 differentiated AD from patients with Lewy body disease with 77.1% sensitivity and 100% specificity. VILIP-1 potential as a prognostic biomarker of cognitive decline in AD was also proved since VILIP-1/t-tau, VILIP-1/p-tau181, and VILIP-1/p-tau231 ratios correlated with MMSE scores. These data indicate that VILIP-1 alone or in combination with other AD CSF biomarkers represent a valuable marker for the early diagnosis of AD, recognition of MCI patients at higher risk to develop dementia, and in differentiating AD from LBD.
Keywords: Adult; Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Cognitive Dysfunction; Diagnosis, Differential; Disease Progression; Female; Humans; Male; Mental Status Schedule; Middle Aged; Neurocalcin; Peptide Fragments; Predictive Value of Tests; ROC Curve; Statistics as Topic; tau Proteins

Predictors of Response to Cholinesterase Inhibitors Treatment of Alzheimer's Disease: Date Mining from the TREDEM Registry. - Gallucci, Maurizio; Spagnolo, Pierpaolo; Aricò, Maria; Grossi, Enzo (J Alzheimers Dis, 2016)
BACKGROUND: The pharmacological treatment of Alzheimer's disease (AD) is based largely on cholinesterase inhibitors (ChEI). OBJECTIVE: To investigate whether or not some non-pharmacological and contextual factors measured prior to starting treatment such as past occupation, lifestyles, marital status, degree of autonomy and cognitive impairment, living alone or with others, and the degree of brain atrophy are associated with a better response to ChEI treatment. METHODS: Eighty-four AD and six AD with cerebrovascular disease (AD + CVD) outpatients of Treviso Dementia (TREDEM) Registry, with an average cholinesterase inhibitors treatment length of four years, were considered. The outpatients had undergone a complete evaluation and some non-pharmacological and contextual factors were collected. We defined responder a patient with a delta score T0 - T1 equal or inferior to 2.0 points per year of MMSE and a non-responder a patient with a delta score T0 - T1 superior to 2.0 points per year. In order to identify hidden relationships between variables related to response and non-response, we use a special kind of artificial neural network called Auto-CM, able to create a semantic connectivity map of the variables considered in the study. RESULTS: A higher cognitive profile, a previous intellectual occupation, healthier lifestyles, being married and not living alone, a higher degree of autonomy, and lower degree of brain atrophy at baseline resulted in affecting the response to long-term ChEI therapy. CONCLUSION: Non-pharmacological and contextual factors appear to influence the effectiveness of treatment with ChEI in the long term.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cerebrovascular Disorders; Cholinesterase Inhibitors; Female; Humans; Life Style; Male; Marital Status; Mental Status Schedule; Neural Networks (Computer); Neuropsychological Tests; Occupations; Outpatients; Prognosis; Registries; Treatment Outcome

Preliminary Study of Plasma Exosomal Tau as a Potential Biomarker for Chronic Traumatic Encephalopathy. - Stern, Robert A; Tripodis, Yorghos; Baugh, Christine M; Fritts, Nathan G; Martin, Brett M; Chaisson, Christine; Cantu, Robert C; Joyce, James A; Shah, Sahil; Ikezu, Tsuneya; Zhang, Jing; Gercel-Taylor, Cicek; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Chronic traumatic encephalopathy (CTE) is a tauopathy associated with prior exposure to repetitive head impacts, such as those incurred through American football and other collision sports. Diagnosis is made through neuropathological examination. Many of the clinical features of CTE are common in the general population, with and without a history of head impact exposure, making clinical diagnosis difficult. As is now common in the diagnosis of other neurodegenerative disorders, such as Alzheimer's disease, there is a need for methods to diagnose CTE during life through objective biomarkers. OBJECTIVE: The aim of this study was to examine tau-positive exosomes in plasma as a potential CTE biomarker. METHODS: Subjects were 78 former National Football League (NFL) players and 16 controls. Extracellular vesicles were isolated from plasma. Fluorescent nanoparticle tracking analysis was used to determine the number of vesicles staining positive for tau. RESULTS: The NFL group had higher exosomal tau than the control group (p <  0.0001). Exosomal tau discriminated between the groups, with 82% sensitivity, 100% specificity, 100% positive predictive value, and 53% negative predictive value. Within the NFL group, higher exosomal tau was associated with worse performance on tests of memory (p = 0.0126) and psychomotor speed (p = 0.0093). CONCLUSION: These preliminary findings suggest that exosomal tau in plasma may be an accurate, noninvasive CTE biomarker.
Keywords: Adult; Aged; Analysis of Variance; Case-Control Studies; Chronic Traumatic Encephalopathy; Extracellular Vesicles; Humans; Male; Middle Aged; Plasma; tau Proteins

The Presence of Select Tau Species in Human Peripheral Tissues and Their Relation to Alzheimer's Disease. - Dugger, Brittany N; Whiteside, Charisse M; Maarouf, Chera L; Walker, Douglas G; Beach, Thomas G; Sue, Lucia I; Garcia, Angelica; Dunckley, Travis; Meechoovet, Bessie; Reiman, Eric M; Roher, Alex E (J Alzheimers Dis, 2016)
Tau becomes excessively phosphorylated in Alzheimer's disease (AD) and is widely studied within the brain. Further examination of the extent and types of tau present in peripheral tissues and their relation to AD is warranted given recent publications on pathologic spreading. Cases were selected based on the presence of pathological tau spinal cord deposits (n = 18). Tissue samples from sigmoid colon, scalp, abdominal skin, liver, and submandibular gland were analyzed by western blot and enzyme-linked immunosorbent assays (ELISAs) for certain tau species; frontal cortex gray matter was used for comparison. ELISAs revealed brain to have the highest total tau levels, followed by submandibular gland, sigmoid colon, liver, scalp, and abdominal skin. Western blots with antibodies recognizing tau phosphorylated at threonine 231(pT231), serine 396 and 404 (PHF-1), and an unmodified total human tau between residues 159 and 163 (HT7) revealed multiple banding patterns, some of which predominated in peripheral tissues. As submandibular gland had the highest levels of peripheral tau, a second set of submandibular gland samples were analyzed (n = 36; 19 AD, 17 non-demented controls). ELISAs revealed significantly lower levels of pS396 (p = 0.009) and pT231 (p = 0.005) in AD cases but not total tau (p = 0.18). Furthermore, pT231 levels in submandibular gland inversely correlated with Braak neurofibrillary tangle stage (p = 0.04), after adjusting for age at death, gender, and postmortem interval. These results provide evidence that certain tau species are present in peripheral tissues. Of potential importance, submandibular gland pT231 is progressively less abundant with increasing Braak neurofibrillary tangle stage.
Keywords: Aged; Aged, 80 and over; Aging; Alzheimer Disease; Blotting, Western; Colon; Enzyme-Linked Immunosorbent Assay; Female; Frontal Lobe; Gray Matter; Humans; Immunohistochemistry; Liver; Male; Neurofibrillary Tangles; Phosphorylation; Severity of Illness Index; Sex Characteristics; Skin; Submandibular Gland; tau Proteins

Prevalence and Risk Factor of Cognitive Impairment were Different between Urban and Rural Population: A Community-Based Study. - Tang, Hui-Dong; Zhou, Yi; Gao, Xiang; Liang, Liang; Hou, Miao-Miao; Qiao, Yuan; Ma, Jian-Fang; Chen, Sheng-Di (J Alzheimers Dis, 2016)
BACKGROUND: China is facing a continuously rising numbers of people with cognitive impairment (CI). OBJECTIVES: To investigate the prevalence and risk factors of CI among elderly people living in rural and urban communities. METHODS: We conducted a face-to-face survey of CI on 7,900 individuals aged 50 years or older meeting inclusion criteria in the Malu (rural community, n = 4,429) and Wuliqiao (urban community, n = 3,471) communities of Shanghai. The Mini-Mental State Examination (MMSE) was used to evaluate the cognitive function. Information on demographic features and potential risk factors for CI was collected during the interview. Multivariate logistic regression was performed to identify risk factors associated with CI. RESULTS: Based on the education modified MMSE score, we identified 329 CI cases in rural community and 227 in urban community. The prevalence of CI was 7.43% in rural population and 6.54% in urban population (p = 0.13). In the urban population, risk of having CI was associated with age (OR = 1.04; 95% CI: 1.01-1.08), lack of physical activities (OR = 2.25; 95% CI: 1.11-4.57), presence of diabetes mellitus (OR = 1.79; 95% CI: 1.04-3.07), and having three or more children (OR = 2.39; 95% CI: 1.27-4.50). In contrast, factors associated with rural populations included female gender (OR = 2.03; 95% CI: 1.08-3.82), age (OR = 1.06; 95% CI: 1.03-1.08), exposure to pesticides (OR = 4.68; 95% CI: 1.27-17.21), history of encephalitis or meningitis (OR = 6.02; 95% CI: 1.92-18.85) and head trauma (OR = 1.89; 95% CI: 1.10-3.24). CONCLUSIONS: Urban rural and populations showed different risk factors for CI, suggesting that different preventive strategies in these areas should be performed.
Keywords: Aged; Aged, 80 and over; China; Cognition Disorders; Female; Humans; Logistic Models; Male; Mental Status Schedule; Middle Aged; Multivariate Analysis; Prevalence; Risk Factors; Rural Population; Urban Population

Prion Protein-Hemin Interaction Upregulates Hemoglobin Synthesis: Implications for Cerebral Hemorrhage and Sporadic Creutzfeldt-Jakob Disease. - Tripathi, Ajai K; Singh, Neena (J Alzheimers Dis, 2016)
Hemin is known to induce endocytosis of prion-protein (PrP(C)) from the neuronal plasma membrane, potentially limiting propagation of the disease causing PrP-scrapie (PrP(Sc)) isoform. Hemin is therefore an attractive disease-modifying option for sporadic Creutzfeldt-Jakob disease (sCJD), a human prion disorder with no effective treatment. The hemin-PrP(C) interaction is also of interest in cerebral-hemorrhage (CH), a condition where potentially toxic hemin molecules come in contact with neuronal PrP(C). Interestingly, PrP(C) is upregulated in penumbric neurons surrounding CH and is known to confer neuroprotection in a dose-dependent manner. The underlying mechanism, however, is not clear. Here, we report that hemin binds PrP(C) on diverse cell lines, resulting in its aggregation or degradation in a cell-type specific manner. Surprisingly, the hemin-PrP(C) interaction upregulates Hb synthesis in hematopoietic cells, a response reversed by deleting the hemin-binding octa-peptide repeat region of PrP(C). A similar response is noted in brain organotypic cultures where exposure to hemin induces significantly more α-globin in wild-type (PrP(+/+)) relative to PrP-knock-out (PrP(-/-)) samples. Furthermore, red blood cells and brain tissue from PrP(-/-) mice show significantly less α-globin relative to PrP(+/+) controls, indicating a positive effect of PrP(C) on Hb synthesis under physiological conditions as well. Surprisingly, levels of α-globin are significantly higher in sCJD brain tissue relative to controls, suggesting compensatory upregulation of Hb synthesis by surviving neurons or misregulation in diseased brains. These observations reveal a unique function of PrP(C) that is likely to impact the therapeutic management of CH and sCJD.
Keywords: Animals; Brain; Cell Line, Tumor; Creutzfeldt-Jakob Syndrome; Endocytosis; Ferritins; Green Fluorescent Proteins; Hemin; Hemoglobins; Humans; In Vitro Techniques; Leukemia, Erythroblastic, Acute; Mice; Mice, Transgenic; Neuroblastoma; Neuroglia; Neurons; Organ Culture Techniques; Prion Proteins; Transfection; Up-Regulation

PRNP P39L Variant is a Rare Cause of Frontotemporal Dementia in Italian Population. - Oldoni, Emanuela; Fumagalli, Giorgio G; Serpente, Maria; Fenoglio, Chiara; Scarioni, Marta; Arighi, Andrea; Bruno, Giuseppe; Talarico, Giuseppina; Confaloni, Annamaria; Piscopo, Paola; Nacmias, Benedetta; Sorbi, Sandro; et al. (J Alzheimers Dis, 2016)
The missense P39L variant in the prion protein gene (PRNP) has recently been associated with frontotemporal dementia (FTD). Here, we analyzed the presence of the P39L variant in 761 patients with FTD and 719 controls and found a single carrier among patients. The patient was a 67-year-old male, with a positive family history for dementia, who developed apathy, short term memory deficit, and postural instability at 66. Clinical and instrumental workup excluded prion disease. At MRI, bilateral frontal lobe atrophy was present. A diagnosis of FTD was made, with a mainly apathetic phenotype. The PRNP P39L mutation may be an extremely rare cause of FTD (0.13%).
Keywords: Aged; Atrophy; Frontal Lobe; Frontotemporal Dementia; Genetic Predisposition to Disease; Humans; Italy; Language; Magnetic Resonance Imaging; Male; Memory Disorders; Memory, Short-Term; Neuropsychological Tests; Prion Proteins; Prions; Temporal Lobe

Prognostic Significance of Mild Cognitive Impairment Subtypes for Dementia and Mortality: Data from the NEDICES Cohort. - Bermejo-Pareja, Félix; Contador, Israel; Trincado, Rocío; Lora, David; Sánchez-Ferro, Álvaro; Mitchell, Alex J; Boycheva, Elina; Herrero, Alejandro; Hernández-Gallego, Jesús; Llamas, Sara; Villarejo Galende, Alberto; Benito-León, Julián (J Alzheimers Dis, 2016)
BACKGROUND: The predictive value of diverse subtypes of mild cognitive impairment (MCI) for dementia and death is highly variable. OBJECTIVE: To compare the predictive value of several MCI subtypes in progression to dementia and/or mortality in the NEDICES (Neurological Disorders in Central Spain) elderly cohort. METHODS: Retrospect algorithmic MCI subgroups were established in a non-dementia baseline NEDICES cohort using Spanish adaptations of the original Mini-Mental State Examination (MMSE-37) and Pfeffer's Functional Activities Questionnaire (Pfeffer-11). The presence of MCI was defined according two cognitive criteria: using two cut-offs points on the total MMSE-37 score. Five cognitive domains were used to establish the MCI subtypes. Functional capacity (Pfeffer-11) was preserved or minimally impaired in all MCI participants. The incident dementia diagnoses were established by specialists and the mortality data obtained from Spanish official registries. RESULTS: 3,411 participants without dementia were assessed in 1994-5. The baseline prevalence of MCI varied according to the MCI definition (4.3%-31.8%). The follow-up was a mean of 3.2 years (1997-8). The dementia incidence varied between 14.9 and 71.8 per 1,000/person-years. The dementia conversion rate was increased in almost all MCI subgroups (p >  0.01), and mortality rate was raised only in four MCI subtypes. The amnestic-multi-domain MCI (aMd-MCI) had the best dementia predictive accuracy (highest positive likelihood ratio and highest clinical utility when negative). CONCLUSIONS: Those with aMd-MCI were at greatest risk of progression to dementia, as in other surveys and might be explored with increased attention in MCI research and in dementia preventive trials.
Keywords: Aged; Aged, 80 and over; Algorithms; Cognitive Dysfunction; Cohort Studies; Dementia; Female; Humans; Male; Mental Status Schedule; Neuropsychological Tests; Predictive Value of Tests; Prognosis; Proportional Hazards Models; Spain

Progranulin Protein Levels in Cerebrospinal Fluid in Primary Neurodegenerative Dementias. - Morenas-Rodriguez, Estrella; Cervera-Carles, Laura; Vilaplana, Eduard; Alcolea, Daniel; Carmona-Iragui, María; Dols-Icardo, Oriol; Ribosa-Nogué, Roser; Muñoz-Llahuna, Laia; Sala, Isabel; Belén Sánchez-Saudinós, M; Blesa, Rafael; Clarimón, Jordi; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Progranulin is implicated in frontotemporal dementia (FTD), but its role in other neurodegenerative disorders is unknown. OBJECTIVE: To investigate the levels of progranulin (PGRN) in cerebrospinal fluid (CSF) in different neurodegenerative dementias and their correlation with levels in plasma in cognitively normal subjects. METHODS: We measured PGRN in CSF in 229 patients with amnestic mild cognitive impairment, Alzheimer's disease dementia, sporadic FTD, dementia with Lewy bodies, corticobasal syndrome, or progressive supranuclear palsy. We also measured PGRN in CSF and plasma in 74 cognitively normal individuals. We examined the correlation between PGRN levels in CSF and diagnosis, cortical thickness, genetic factors and other CSF biomarkers. We also investigated the correlation between plasma and CSF levels of PGRN in cognitively normal individuals. RESULTS: CSF levels did not differ across diagnoses or correlate with cortical thickness. Polymorphism rs5848 in GRN influenced CSF PGRN levels, but APOEɛ4 allele did not. Amyloid-β42, t-tau, p-tau, and YKL-40 levels correlated weakly with PGRN in CSF. We found a weak correlation (r = 0.362) between plasma and CSF PGRN levels in cognitively normal individuals. CONCLUSIONS: Our findings do not support a diagnostic value of CSF PGRN in neurodegenerative diseases. Our data confirm that levels of PGRN in plasma do not reflect accurately levels in CSF in cognitively normal controls. These data should be considered in clinical trials aiming to increase PGRN.
Keywords: Aged; Aged, 80 and over; Amyloid beta-Peptides; Biomarkers; Dementia; Female; Humans; Intercellular Signaling Peptides and Proteins; Male; Middle Aged; Neurodegenerative Diseases; Polymorphism, Single Nucleotide; tau Proteins

Protective Effect of Amyloid-β Peptides Against Herpes Simplex Virus-1 Infection in a Neuronal Cell Culture Model. - Bourgade, Karine; Le Page, Aurélie; Bocti, Christian; Witkowski, Jacek M; Dupuis, Gilles; Frost, Eric H; Fülöp, Tamás (J Alzheimers Dis, 2016)
Senile amyloid plaques are one of the main hallmarks of Alzheimer's disease (AD). They correspond to insoluble deposits of amyloid-β peptides (Aβ) and are responsible for the inflammatory response and neurodegeneration that lead to loss of memory. Recent data suggest that Aβ possess antimicrobial and anti-viral activity in vitro. Here, we have used cocultures of neuroglioma (H4) and glioblastoma (U118-MG) cells as a minimal in vitro model to investigate whether Aβ is produced by neuroglioma cells and whether this could result in protective anti-viral activity against HSV-1 infection. Results showed that H4 cells secreted Aβ42 in response to HSV-1 challenge and that U118-MG cells could rapidly internalize Aβ42. Production of pro-inflammatory cytokines TNFα and IL-1β by H4 and U118-MG cells occurred under basal conditions but infection of the cells with HSV-1 did not significantly upregulate production. Both cell lines produced low levels of IFNα. However, extraneous Aβ42 induced strong production of these cytokines. A combination of Aβ42 and HSV-1 induced production of pro-inflammatory cytokines TNFα and IL-1β, and IFNα in the cell lines. The reported anti-viral protection of Aβ42 was revealed in transfer experiments involving conditioned medium (CM) of HSV-1-infected H4 cells. CM conferred Aβ-dependent protection against HSV-1 replication in de novo cultures of H4 cells challenged with HSV-1. Type 1 interferons did not play a role in these assays. Our data established that H4 neuroglioma cells produced Aβ42 in response to HSV-1 infection thus inhibiting secondary replication. This mechanism may play a role in the etiology of AD.
Keywords: Amyloid beta-Peptides; Amyloid Precursor Protein Secretases; Cell Line, Tumor; Coculture Techniques; Culture Media, Conditioned; Herpes Simplex; Herpesvirus 1, Human; Humans; Interferon-alpha; Interleukin-1beta; Neuroglia; Neurons; Peptide Fragments; Tumor Necrosis Factor-alpha; Virus Replication

Protein Kinase Activity Decreases with Higher Braak Stages of Alzheimer's Disease Pathology. - Rosenberger, Andrea F N; Hilhorst, Riet; Coart, Elisabeth; García Barrado, Leandro; Naji, Faris; Rozemuller, Annemieke J M; van der Flier, Wiesje M; Scheltens, Philip; Hoozemans, Jeroen J M; van der Vies, Saskia M (J Alzheimers Dis, 2016)
Alzheimer's disease (AD) is characterized by a long pre-clinical phase (20-30 years), during which significant brain pathology manifests itself. Disease mechanisms associated with pathological hallmarks remain elusive. Most processes associated with AD pathogenesis, such as inflammation, synaptic dysfunction, and hyper-phosphorylation of tau are dependent on protein kinase activity. The objective of this study was to determine the involvement of protein kinases in AD pathogenesis. Protein kinase activity was determined in postmortem hippocampal brain tissue of 60 patients at various stages of AD and 40 non-demented controls (Braak stages 0-VI) using a peptide-based microarray platform. We observed an overall decrease of protein kinase activity that correlated with disease progression. The phosphorylation of 96.7% of the serine/threonine peptides and 37.5% of the tyrosine peptides on the microarray decreased significantly with increased Braak stage (p-value <0.01). Decreased activity was evident at pre-clinical stages of AD pathology (Braak I-II). Increased phosphorylation was not observed for any peptide. STRING analysis in combination with pathway analysis and identification of kinases responsible for peptide phosphorylation showed the interactions between well-known proteins in AD pathology, including the Ephrin-receptor A1 (EphA1), a risk gene for AD, and sarcoma tyrosine kinase (Src), which is involved in memory formation. Additionally, kinases that have not previously been associated with AD were identified, e.g., protein tyrosine kinase 6 (PTK6/BRK), feline sarcoma oncogene kinase (FES), and fyn-associated tyrosine kinase (FRK). The identified protein kinases are new biomarkers and potential drug targets for early (pre-clinical) intervention.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Cohort Studies; Female; Hippocampus; Humans; Male; Middle Aged; Phosphorylation; Protein Kinases; Protein-Serine-Threonine Kinases; Severity of Illness Index

Psychometric Properties of the Memory Binding Test: Test-Retest Reliability and Convergent Validity. - Gramunt, Nina; Sánchez-Benavides, Gonzalo; Buschke, Herman; Lipton, Richard B; Masramon, Xavier; Gispert, Juan D; Peña-Casanova, Jordi; Fauria, Karine; Molinuevo, José L (J Alzheimers Dis, 2016)
BACKGROUND: Episodic memory testing is fundamental for the diagnosis of Alzheimer's disease (AD). Although the Free and Cued Selective Reminding Test (FCSRT) is widely used for this purpose, it may not be sensitive enough for early detection of subtle decline in preclinical AD. The Memory Binding Test (MBT) intends to overcome this limitation. OBJECTIVES: To analyze the test-retest reliability of the MBT and its convergent validity with the FCRST. METHODS: 36 cognitively healthy participants of the ALFA Study, aged 45 to 65, were included for the test-retest study and 69 for the convergent analysis. They were visited twice in a period of 6 ± 2 weeks. Test-retest reliability was determined by the calculation of the intra-class correlation coefficient (ICC). Score differences were studied by computing the mean percentage of score variation between visits and visualized by Bland-Altman plots. Convergent validity was determined by Pearson's correlations. RESULTS: ICC values in the test-retest reliability analysis of the MBT direct scores ranged from 0.64 to 0.76. Subjects showed consistent practice effects, with mean amounts of score increasing between 10% and 26%. Pearson correlation between MBT and FCSRT direct scores showed r values between 0.40 and 0.53. The FCSRT displayed ceiling effects not observed in the MBT. CONCLUSIONS: The MBT shows adequate test-retest reliability and overall moderate convergent validity with the FCSRT. Unlike the FCSRT, the MBT does not have ceiling effects and it may therefore be especially useful in longitudinal studies, facilitating the measurement of subtle memory performance decline and the detection of very early AD.
Keywords: Aged; Alzheimer Disease; Female; Humans; Male; Memory; Middle Aged; Psychological Tests; Psychometrics; Reproducibility of Results

Psychotropic Drug Prescription in Patients with Dementia: Nursing Home Residents Versus Patients Living at Home. - Jacquin-Piques, Agnès; Sacco, Guillaume; Tavassoli, Neda; Rouaud, Olivier; Bejot, Yannick; Giroud, Maurice; Robert, Philippe; Vellas, Bruno; Bonin-Guillaume, Sylvie (J Alzheimers Dis, 2016)
BACKGROUND: Psychotropic drugs are frequently prescribed in nursing homes (NH). Nonetheless, we hoped that institutionalization decreases the number of psychotropic drug classes prescribed, because NH residents may have more psychosocial interventions than patients living at home. OBJECTIVE: The aim was to compare the type and number of psychotropic drugs prescribed in elderly NH residents with dementia with those in community-living patients. METHODS: This cross-sectional study included elderly patients (at least 75 years old) with dementia recorded in the National Alzheimer's data Bank ("Banque Nationale Alzheimer") during the year 2012 and who were taking at least one psychotropic drug. Psychotropic drugs were classified as follows: antidepressant, anxiolytic, hypnotic, and antipsychotic drugs. Patients were classified into three categories of dementia severity according to the MMSE score. RESULTS: Among the 50,932 patients with dementia recorded in the BNA, 40.1% had at least one psychotropic drug prescribed. Most of the patients who were treated by at least one psychotropic drug class had antidepressant therapy (69.0%), whatever their residence type, and 16.1% were treated with antipsychotics. Among the study population, 51.9% of the NH residents and 67.4% of the patients living at home had only one psychotropic drug class prescribed. Living in a NH was significantly associated with the more frequent prescription of anxiolytic, hypnotic, and antipsychotic drugs, and with a greater number of psychotropic drug classes prescribed, whatever the severity of the dementia. CONCLUSION: We underlined the more frequent prescription of psychotropic drugs in NH residents regardless of MMSE scores.
Keywords: Aged; Aged, 80 and over; Chi-Square Distribution; Cross-Sectional Studies; Databases, Factual; Dementia; Drug Prescriptions; Female; Humans; Male; Nursing Homes; Psychotropic Drugs; Residence Characteristics

Puerarin Ameliorates D-Galactose Induced Enhanced Hippocampal Neurogenesis and Tau Hyperphosphorylation in Rat Brain. - Hong, Xiao-Ping; Chen, Tao; Yin, Ni-Na; Han, Yong-Ming; Yuan, Fang; Duan, Yan-Jun; Shen, Feng; Zhang, Yan-Hong; Chen, Ze-Bin (J Alzheimers Dis, 2016)
Enhanced neurogenesis has been reported in the hippocampus of patients with Alzheimer's disease (AD), the most common neurodegenerative disorder characterized with amyloid-β (Aβ) aggregation, tau hyperphosphorylation, and progressive neuronal loss. Previously we reported that tau phosphorylation played an essential role in adult hippocampal neurogenesis, and activation of glycogen synthase kinase (GSK-3), a crucial tau kinase, could induce increased hippocampal neurogenesis. In the present study, we found that treatment of D-galactose rats with Puerarin could significantly improve behavioral performance and ameliorate the enhanced neurogenesis and microtubule-associated protein tau hyperphosphorylation in the hippocampus of D-galactose rat brains. FGF-2/GSK-3 signaling pathway might be involved in the effects of Puerarin on hippocampal neurogenesis and tau hyperphosphorylation. Our finding provides primary in vivo evidence that Puerarin can attenuate AD-like enhanced hippocampal neurogenesis and tau hyperphosphorylation. Our finding also suggests Puerarin can be served as a treatment for age-related neurodegenerative disorders, such as AD.
Keywords: Animals; Cognition Disorders; Disease Models, Animal; Fibroblast Growth Factor 2; Galactose; Glycogen Synthase Kinase 3; Hippocampus; Isoflavones; Male; Maze Learning; Neurogenesis; Neurons; Neuroprotective Agents; Phosphorylation; Random Allocation; Rats, Sprague-Dawley; Signal Transduction; Spatial Memory; tau Proteins

A Qualitative Impairment in Face Perception in Alzheimer's Disease: Evidence from a Reduced Face Inversion Effect. - Lavallée, Marie Maxime; Gandini, Delphine; Rouleau, Isabelle; Vallet, Guillaume T; Joannette, Maude; Kergoat, Marie-Jeanne; Busigny, Thomas; Rossion, Bruno; Joubert, Sven (J Alzheimers Dis, 2016)
Prevalent face recognition difficulties in Alzheimer's disease (AD) have typically been attributed to the underlying episodic and semantic memory impairment. The aim of the current study was to determine if AD patients are also impaired at the perceptual level for faces, more specifically at extracting a visual representation of an individual face. To address this question, we investigated the matching of simultaneously presented individual faces and of other nonface familiar shapes (cars), at both upright and inverted orientation, in a group of mild AD patients and in a group of healthy older controls matched for age and education. AD patients showed a reduced inversion effect (i.e., larger performance for upright than inverted stimuli) for faces, but not for cars, both in terms of error rates and response times. While healthy participants showed a much larger decrease in performance for faces than for cars with inversion, the inversion effect did not differ significantly for faces and cars in AD. This abnormal inversion effect for faces was observed in a large subset of individual patients with AD. These results suggest that AD patients have deficits in higher-level visual processes, more specifically at perceiving individual faces, a function that relies on holistic representations specific to upright face stimuli. These deficits, combined with their memory impairment, may contribute to the difficulties in recognizing familiar people that are often reported in patients suffering from the disease and by their caregivers.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Analysis of Variance; Face; Facial Recognition; Female; Humans; Male; Middle Aged; Neuropsychological Tests; Orientation; Pattern Recognition, Visual; Perceptual Disorders; Photic Stimulation; Psychiatric Status Rating Scales; Reaction Time; Statistics as Topic

Quantitative phosphoproteomic analyses of the inferior parietal lobule from three different pathological stages of Alzheimer's disease. - Triplett, Judy C; Swomley, Aaron M; Cai, Jian; Klein, Jon B; Butterfield, D Allan (J Alzheimers Dis, 2016)
Alzheimer's disease (AD), the most common age-related neurodegenerative disorder, is clinically characterized by progressive neuronal loss resulting in loss of memory and dementia. AD is histopathologically characterized by the extensive distribution of senile plaques and neurofibrillary tangles, and synapse loss. Amnestic mild cognitive impairment (MCI) is generally accepted to be an early stage of AD. MCI subjects have pathology and symptoms that fall on the scale intermediately between 'normal' cognition with little or no pathology and AD. A rare number of individuals, who exhibit normal cognition on psychometric tests but whose brains show widespread postmortem AD pathology, are classified as 'asymptomatic' or 'preclinical' AD (PCAD). In this study, we evaluated changes in protein phosphorylation states in the inferior parietal lobule of subjects with AD, MCI, PCAD, and control brain using a 2-D PAGE proteomics approach in conjunction with Pro-Q Diamond phosphoprotein staining. Statistically significant changes in phosphorylation levels were found in 19 proteins involved in energy metabolism, neuronal plasticity, signal transduction, and oxidative stress response. Changes in the disease state phosphoproteome may provide insights into underlying mechanisms for the preservation of memory with expansive AD pathology in PCAD and the progressive memory loss in amnestic MCI that escalates to the dementia and the characteristic pathology of AD brain.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Cognitive Dysfunction; Disease Progression; Female; Humans; Male; Memory; Neurofibrillary Tangles; Oxidative Stress; Parietal Lobe; Phosphorylation; Plaque, Amyloid; Proteome

Reduction of Amyloid-β Plasma Levels by Hemodialysis: An Anti-Amyloid Treatment Strategy? - Tholen, Susanne; Schmaderer, Christoph; Chmielewski, Stefan; Förstl, Hans; Heemann, Uwe; Baumann, Marcus; Steubl, Dominik; Grimmer, Timo (J Alzheimers Dis, 2016)
BACKGROUND: Cognitive impairment in hemodialysis patients is common, but the underlying pathogenesis remains unclear. Alzheimer's disease is the most common cause of dementia in the general elderly population. Histopathological hallmarks are, among others, senile plaques, which consist of amyloid-β (Aβ). OBJECTIVE: To measure plasma levels of Aβ42 and Aβ40 during hemodialysis and to examine potential associations with cognitive performance in cognitively impaired hemodialysis patients. METHODS: Plasma samples of 26 hemodialysis patients were collected shortly before, after 50% of dialysis time, and at the end of a dialysis session. Aβ42 and Aβ40 levels were measured by a high-sensitivity ELISA for human amyloid-β. Cognition was tested under standardized conditions using the Montreal Cognitive Assessment (MoCA) as proposed previously. RESULTS: Clearance rates of both peptides during one dialysis session were 22% and 35% for Aβ42 and Aβ40, respectively. Aβ42 but not Aβ40 baseline levels were significantly associated with MoCA test results (r = 0.654, p = 0.001). CONCLUSION: In cognitively impaired hemodialysis patients plasma Aβ42 levels were associated with cognitive performance and both Aβ42 and Aβ40 plasma levels could be effectively reduced by dialysis. By inducing peripheral Aβ sink, hemodialysis may be considered as an anti-amyloid treatment strategy.
Keywords: Adult; Aged; Aged, 80 and over; Amyloid beta-Peptides; Cognition Disorders; Enzyme-Linked Immunosorbent Assay; Female; Humans; Male; Mental Status Schedule; Middle Aged; Neuropsychological Tests; Peptide Fragments; Renal Dialysis

Reproductive history and risk of cognitive impairment in elderly women: a cross-sectional study in eastern China. - Li, Fu-Dong; He, Fan; Chen, Ting-Rui; Xiao, Yuan-Yuan; Lin, Shang-Tong; Shen, Wei; Wang, Xin-Yi; Zhai, Yu-Jia; Shang, Xiao-Peng; Lin, Jun-Fen (J Alzheimers Dis, 2016)
BACKGROUND: Epidemiological studies suggest that proxies of higher lifetime estrogen exposure are associated with better cognitive function in postmenopausal women, but this has not been found consistently. OBJECTIVE: To determine whether reproductive history, an important modifier of estrogen exposure across the lifetime, is associated with risk of cognitive impairment in postmenopausal women. METHODS: We analyzed the baseline data from Zhejiang Major Public Health Surveillance Program (ZPHS) including 4,796 postmenopausal women. Cognitive impairment was assessed through the application of Mini-Mental State Examination questionnaire. Logistic regression models, controlled for an extensive range of potential confounders, were generated to examine the associations between women's reproductive history and risk of cognitive impairment in their later life. RESULTS: The length of reproductive period was inversely associated with risk of cognitive impairment (p = 0.001). Odds ratio (OR) of cognitive impairment were 1.316 (95% CI 1.095∼1.582) for women with 5 or more times of full-term pregnancies, compared with those with 1∼4 times of full-term pregnancies. Women without incomplete pregnancy had a significant higher risk of cognitive impairment (OR = 1.194, 95% CI 1.000∼1.429), compared with the reference (1∼2 times of incomplete pregnancies). Oral contraceptive use (OR = 0.489, 95% CI 0.263∼0.910) and intrauterine device (IUD) use (OR = 0.684, 95% CI 0.575∼0.815) were associated with significantly reduced risk of cognitive impairment. CONCLUSION: Our results indicated that shorter reproductive period, higher number of full-term pregnancies and no incomplete pregnancy history were associated with an increased risk of cognitive impairment. In contrast, oral contraceptive and IUD use corresponded to reduced risk of cognitive impairment.
Keywords: Aged; Aged, 80 and over; China; Cognition; Cognition Disorders; Contraceptives, Oral; Cross-Sectional Studies; Estrogens; Female; Humans; Intrauterine Devices; Logistic Models; Middle Aged; Neuropsychological Tests; Odds Ratio; Postmenopause; Psychiatric Status Rating Scales; Reproductive History

Resting-State Cardiac Workload is Related to Both Increased Neocortical Aggregation of Amyloid-β and Relative Impairments in Spatial Working Memory in Pre-Clinical Alzheimer's Disease. - Santos, Cláudia Yang; Lim, Yen Ying; Wu, Wen-Chih; Machan, Jason Timothy; Polynice, Shahena; Schindler, Rachel; Maruff, Paul; Snyder, Peter Jeffrey (J Alzheimers Dis, 2016)
We sought to determine whether there is any association between a cardiac workload marker, rate pressure product (RPP), working memory, and cortical amyloid-β (Aβ) burden in 63 cognitively normal midlife adults (Mage = 62.8 years; range = 55 to 75 years) at risk for Alzheimer's disease (AD). The results show a small-to-moderate relationship between increasing cardiac workload (at rest) and neocortical amyloidosis in individuals at the preclinical stage of AD. Moreover, increasing RPP was linearly related to increasing relative impairments on a spatial working memory task (R2 = 0.30), but only for those individuals with neuroimaging evidence suggestive of preclinical AD. These results support a relationship between the aggregation of Aβ protein plaques in the neocortex, increased cognitive impairment, and more inefficient myocardial oxygen use in the absence of significant metabolic demands.
Keywords: Aged; Alzheimer Disease; Amyloid beta-Peptides; Blood Pressure; Disease Progression; Female; Heart Rate; Humans; Male; Maze Learning; Memory Disorders; Middle Aged; Neocortex; Neuropsychological Tests; Positron-Emission Tomography; Protein Aggregation, Pathological; Workload

Reversal of LTP-Like Cortical Plasticity in Alzheimer's Disease Patients with Tau-Related Faster Clinical Progression. - Koch, Giacomo; Di Lorenzo, Francesco; Del Olmo, Miguel Fernandez; Bonní, Sonia; Ponzo, Viviana; Caltagirone, Carlo; Bozzali, Marco; Martorana, Alessandro (J Alzheimers Dis, 2016)
Cerebrospinal fluid (CSF) concentrations of amyloid-β (Aβ), total tau (t-tau), and phosphorylated tau proteins are associated with different clinical progression in Alzheimer's disease (AD). We enrolled forty newly diagnosed AD patients, who underwent lumbar puncture, and carried out a K-means cluster analysis based on CSF biomarkers levels, resulting in two AD patient groups: Cluster 1 showed relatively high levels of Aβ and low levels of tau; Cluster 2 showed relatively low levels of Aβ and high levels of tau. Cortical plasticity was tested using the intermittent and continuous theta burst stimulation (iTBS and cTBS) protocols evoking respectively long-term potentiation (LTP) and depression (LTD). Cholinergic transmission was tested by the short-latency afferent inhibition protocol. Neurophysiological evaluation showed that the two AD groups differed in terms of cortical plasticity: after iTBS, Cluster 2 patients showed a remarkable reversal of LTP toward LTD that was not observed in Cluster 1. LTD and central cholinergic transmission did not differ between groups. Patients were assessed longitudinally with Mini-Mental State Examination at 6, 12, and 18 month follow-ups. Cluster 2 AD had a faster cognitive decline already evident at the 12 month follow-up. High tau CSF levels were associated with LTD-like cortical plasticity and faster clinical progression. These results suggest that more aggressive tau pathology is associated with prominent LTD-like mechanisms of cortical plasticity and faster cognitive decline.
Keywords: Aged; Alzheimer Disease; Amyloid beta-Peptides; Cognition; Disease Progression; Evoked Potentials, Motor; Female; Humans; Male; Motor Cortex; Neuronal Plasticity; Neuropsychological Tests; Phosphorylation; tau Proteins; Transcranial Magnetic Stimulation

Revisiting the Heidenhain Variant of Creutzfeldt-Jakob Disease: Evidence for Prion Type Variability Influencing Clinical Course and Laboratory Findings. - Baiardi, Simone; Capellari, Sabina; Ladogana, Anna; Strumia, Silvia; Santangelo, Mario; Pocchiari, Maurizio; Parchi, Piero (J Alzheimers Dis, 2016)
The Heidenhain variant defines a peculiar clinical presentation of sporadic Creutzfeldt-Jakob disease (sCJD) characterized by isolated visual disturbances at disease onset and reflecting the early targeting of prions to the occipital cortex. Molecular and histopathological typing, thus far performed in 23 cases, has linked the Heidenhain variant to the MM1 sCJD type. To contribute a comprehensive characterization of cases with the Heidenhain variant, we reviewed a series of 370 definite sCJD cases. Eighteen patients (4.9%) fulfilled the selection criteria. Fourteen of them belonging to sCJD types MM1 or MM1+2C had a short duration of isolated visual symptoms and overall clinical disease, a high prevalence of periodic sharp-wave complexes in EEG, and a marked increase of cerebrospinal fluid proteins t-tau and 14-3-3 levels. In contrast, three cases of the MM 2C or MM 2+1C types showed a longer duration of isolated visual symptoms and overall clinical disease, non-specific EEG findings, and cerebrospinal fluid concentration below threshold for the diagnosis of "probable" CJD of both 14-3-3 and t-tau. However, a brain DWI-MRI disclosed an occipital cortical hyperintensity in the majority of examined cases of both groups. While confirming the strong linkage with the methionine genotype at the polymorphic codon 129 of the prion protein gene, our results definitely establish that the Heidenhain variant can also be associated with the MM 2C sCJD type in addition to the more common MM1 type. Likewise, our results highlight the significant differences in clinical evolution and laboratory findings between cases according to the dominant PrPSc type (type 1 versus type 2).
Keywords: Aged; Aged, 80 and over; Brain; Creutzfeldt-Jakob Syndrome; Female; Genotype; Humans; Magnetic Resonance Imaging; Male; Middle Aged; Phenotype; Prions

Risk of dementia in patients with celiac disease: a population-based cohort study. - Lebwohl, Benjamin; Luchsinger, Jose A; Freedberg, Daniel E; Green, Peter H R; Ludvigsson, Jonas F (J Alzheimers Dis, 2016)
BACKGROUND: Patients with celiac disease (CD) frequently report cognitive symptoms when they are exposed to gluten, and cognitive deficits have been quantified in patients with newly diagnosed CD. OBJECTIVE: To determine whether patients with CD have an increased risk of dementia. METHODS: Using a population-based database of older adults (age ≥50 years) with histologically proven CD (duodenal/jejunal villous atrophy) from all 28 pathology departments in Sweden, we compared the incidence of a subsequent dementia diagnosis to those of age- and gender-matched controls. RESULTS: Among patients with CD (n = 8,846) and controls (n = 43,474), the median age was 63 years and 56% were female. During a median follow-up time of 8.4 years, dementia was diagnosed in 4.3% of CD patients and 4.4% of controls (HR 1.07; 95% CI 0.95-1.20). Although there was an increased risk of dementia in the first year following a diagnosis of CD (HR 1.73; 95% CI 1.15-2.61), this risk was not present in the whole observation period. Among those subjects with a dementia subtype specified, the increased risk was restricted to vascular dementia (HR 1.28; 95% CI 1.00-1.64) and was not present for Alzheimer's dementia (HR 1.12; 95% CI 0.91-1.37). CONCLUSIONS: Patients with CD are not at increased risk for dementia overall, though subgroup analysis suggests that they may be at increased risk for vascular dementia.
Keywords: Aged; Celiac Disease; Cohort Studies; Databases, Factual; Dementia; Female; Humans; Incidence; Logistic Models; Male; Middle Aged; Proportional Hazards Models; Risk Factors; Sweden

Safety and Efficacy of Medical Cannabis Oil for Behavioral and Psychological Symptoms of Dementia: An-Open Label, Add-On, Pilot Study. - Shelef, Assaf; Barak, Yoram; Berger, Uri; Paleacu, Diana; Tadger, Shelly; Plopsky, Igor; Baruch, Yehuda (J Alzheimers Dis, 2016)
BACKGROUND: Tetrahydrocannabinol (THC) is a potential treatment for Alzheimer's disease (AD). OBJECTIVE: To measure efficacy and safety of medical cannabis oil (MCO) containing THC as an add-on to pharmacotherapy, in relieving behavioral and psychological symptoms of dementia (BPSD). METHODS: Eleven AD patients were recruited to an open label, 4 weeks, prospective trial. RESULTS: Ten patients completed the trial. Significant reduction in CGI severity score (6.5 to 5.7; p <  0.01) and NPI score were recorded (44.4 to 12.8; p <  0.01). NPI domains of significant decrease were: Delusions, agitation/aggression, irritability, apathy, sleep and caregiver distress. CONCLUSION: Adding MCO to AD patients' pharmacotherapy is safe and a promising treatment option.
Keywords: Aged; Aged, 80 and over; Antipsychotic Agents; Behavioral Symptoms; Cognition Disorders; Dementia; Female; Humans; Male; Medical Marijuana; Neuropsychological Tests; Outcome Assessment (Health Care); Physical Examination; Pilot Projects; Prospective Studies; Psychiatric Status Rating Scales

Safety and Tolerability of R(+) Pramipexole in Mild-to-Moderate Alzheimer's Disease. - Bennett, James; Burns, Jeffrey; Welch, Paul; Bothwell, Rebecca (J Alzheimers Dis, 2016)
Alzheimer's disease (AD) is an aging-related, degenerative brain disease of adults. Most (∼95%) of AD occurs sporadically and is associated with early-appearing deficits in brain regional glucose uptake, changes in cerebrospinal fluid (CSF) AD-related proteins, regional brain atrophy, and oxidative stress damage. We treated mild-moderate AD individuals with R(+)-pramipexole-dihydrochloride (R(+)PPX), a neuroprotective, lipophilic-cation, free-radical scavenger that accumulates into brain and mitochondria. 19 subjects took R(+)PPX twice a day in increasing daily doses up to 300 mg/day under a physician-sponsor IND (60,948, JPB), IRB-approved protocol and quarterly external safety committee monitoring. 15 persons finished and contributed baseline and post-treatment serum, lumbar spinal fluid, brain 18F-2DG PET scans, and ADAS-Cog scores. ADAS-Cog scores did not change (n = 1), improved (n = 2), declined 1-3 points (n = 5), or declined 4-13 points (n = 8) over 6 months of R(+)PPX treatment. Serum PPX levels were not related to changes in ADAS-Cog scores. Fasting AM serum PPX levels at 6 months varied considerably across subjects and correlated strongly with CSF [PPX] (r = 0.97, p <  0.0001). CSF [PPX] was not related to CSF [Aβ(42)], [Tau], or [P-Tau]. Regional 18F-2DG measures of brain glucose uptake demonstrated a 3-6% decline during R(+)PPX treatment. 56 mild-moderate adverse events occurred, 26 probably/definitely related to R(+)PPX use, with 4 withdrawals. R(+)PPX was generally well-tolerated and entered brain extracellular space linearly. Further studies of R(+)PPX in AD should include a detailed pharmacokinetic study of peak and trough serum [PPX] variations among subjects prior to planning any larger studies that would be needed to determine efficacy in altering disease progression.
Keywords: Aged; Alzheimer Disease; Amyloid beta-Peptides; Benzothiazoles; Biomarkers; Brain; Female; Glucose; Humans; Male; Neuropsychological Tests; Nootropic Agents; Peptide Fragments; Positron-Emission Tomography; Severity of Illness Index; tau Proteins; Treatment Outcome

Salidroside, a Bioactive Compound of Rhodiola Rosea, Ameliorates Memory and Emotional Behavior in Adult Mice. - Palmeri, Agostino; Mammana, Leonardo; Tropea, Maria Rosaria; Gulisano, Walter; Puzzo, Daniela (J Alzheimers Dis, 2016)
Rhodiola Rosea (R. Rosea) is a plant used in traditional popular medicine to enhance cognition and physical performance. R. Rosea medicinal properties have been related to its capability to act as an adaptogen, i.e., a substance able to increase the organism's resistance to a variety of chemical, biological, and physical stressors in a non-specific way. These adaptogen properties have been mainly attributed to the glycoside salidroside, one of the bioactive compounds present in the standardized extracts of R. Rosea. Here, we aimed to investigate whether a single dose of salidroside is able to affect memory and emotional behavior in wild type adult mice. We performed fear conditioning to assess cued and contextual memory, elevated plus maze and open field to evaluate anxiety, and tail suspension test to evaluate depression. Our results showed that a single i.p. administration of salidroside was able to enhance fear memory and exerted an anxiolytic and antidepressant effect. These data confirmed the adaptogenic effect of R. Rosea bioactive compounds in animal models and suggest that salidroside might represent an interesting pharmacological tool to ameliorate cognition and counteract mood disorders.
Keywords: Animals; Anti-Anxiety Agents; Antidepressive Agents; Anxiety Disorders; Conditioning (Psychology); Depressive Disorder; Disease Models, Animal; Drug Evaluation, Preclinical; Exploratory Behavior; Fear; Female; Freezing Reaction, Cataleptic; Glucosides; Male; Maze Learning; Memory; Mice, Inbred C57BL; Motor Activity; Nootropic Agents; Phenols; Phytotherapy; Plant Extracts; Rhodiola

Screening for Mild Cognitive Impairment: Comparison of "MCI Specific" Screening Instruments. - O'Caoimh, Rónán; Timmons, Suzanne; Molloy, D William (J Alzheimers Dis, 2016)
BACKGROUND: Sensitive and specific instruments are required to screen for cognitive impairment (CI) in busy clinical practice. The Montreal Cognitive Assessment (MoCA) is widely validated but few studies compare it to tests designed specifically to detect mild cognitive impairment (MCI). OBJECTIVE: Comparison of two "MCI specific" screens: the Quick Mild Cognitive Impairment screen (Qmci) and MoCA. METHODS: Patients with subjective memory complaints (SMC; n = 73), MCI (n = 103), or dementia (n = 274), were referred to a university hospital memory clinic and underwent comprehensive assessment. Caregivers, without cognitive symptoms, were recruited as normal controls (n = 101). RESULTS: The Qmci was more accurate than the MoCA in differentiating MCI from controls, area under the curve (AUC) of 0.90 versus 0.80, p = 0.009. The Qmci had greater (AUC 0.81), albeit non-significant, accuracy than the MoCA (AUC 0.73) in separating MCI from SMC, p = 0.09. At its recommended cut-off (<62/100), the Qmci had a sensitivity of 90% and specificity of 87% for CI (MCI/dementia). Raising the cut-off to <65 optimized sensitivity (94%), reducing specificity (80%). At <26/30 the MoCA had better sensitivity (96%) but poor specificity (58%). A MoCA cut-off of <24 provided the optimal balance. Median Qmci administration time was 4.5 (±1.3) minutes compared with 9.5 (±2.8) for the MoCA. CONCLUSIONS: Although both tests distinguish MCI from dementia, the Qmci is particularly accurate in separating MCI from normal cognition and has shorter administration times, suggesting it is more useful in busy hospital clinics. This study reaffirms the high sensitivity of the MoCA but suggests a lower cut-off (<24) in this setting.
Keywords: Aged; Aged, 80 and over; Area Under Curve; Cognitive Dysfunction; Dementia; Diagnosis, Differential; Female; Humans; Male; Neuropsychological Tests; Perception; ROC Curve; Sensitivity and Specificity; Time Factors

Self-Consciousness in Patients with Behavioral Variant Frontotemporal Dementia. - Arroyo-Anlló, Eva M; Bouston, Adèle Turpin; Fargeau, Marie-Noëlle; Orgaz Baz, Begõna; Gil, Roger (J Alzheimers Dis, 2016)
Self-consciousness (SC) is multifaceted and considered to be the consciousness of one's own mental states. The medial prefrontal cortex may play a critical role in SC. The main aim of this paper was to examine SC in patients with behavioral variant frontotemporal dementia, who are characterized more by changes in personal, social, and emotional conduct and loss of insight than by cognitive disturbances. Control and patient groups of 21 subjects each, matched by age, educational level, gender, and nationality were assessed using a SC questionnaire. It measures several aspects: Personal identity, Anosognosia, Affective state, Body representation, Prospective memory, Introspection, and Moral judgments. The most disturbed ones in patients were Anosognosia, Affective state, and Moral judgments, and the least disturbed aspects were awareness of identity and of body representation. No significant correlations were found between the SC score and any clinical or demographical characteristics. The core deficiency of SC in patients was related to behavioral SC aspects, which are more dependent on orbito-frontal functioning.
Keywords: Aged; Brain; Educational Status; Female; Frontotemporal Dementia; Humans; Magnetic Resonance Imaging; Male; Mental Status Schedule; Middle Aged; Positron-Emission Tomography; Psychological Tests; Self Concept

Serotonin 2A Receptor Inverse Agonist as a Treatment for Parkinson's Disease Psychosis: A Systematic Review and Meta-analysis of Serotonin 2A Receptor Negative Modulators. - Yasue, Ichiro; Matsunaga, Shinji; Kishi, Taro; Fujita, Kiyoshi; Iwata, Nakao (J Alzheimers Dis, 2016)
BACKGROUND: There is uncertainty about the efficacy and tolerability of serotonin 2A (5-HT2A) receptor negative modulators for Parkinson's disease psychosis (PDP). OBJECTIVE: This is the first meta-analysis of randomized placebo-controlled trials (RCTs) testing negative modulators of the 5-HT2A receptor as a treatment for PDP. METHODS: The primary outcome was the Scale for Assessment of Positive Symptoms (SAPS)-hallucinations (H) and -delusions (D) scores (SAPS-H+D). Other outcome measures were SAPS-H, SAPS-D, the Unified Parkinson's Disease Rating Scale Part II and III (UPDRS-II+III), discontinuation rates, and individual adverse events. RESULTS: Four RCTs were identified that met inclusion criteria, all assessing the 5-HT2A inverse agonist pimavanserin (including 417 drug-treated and 263 placebo-treated PDP patients). Pimavanserin significantly decreased SAPS-H+D scores compared to placebo [weighted mean differences (WMD) = -2.26, 95% confidence interval (95% CI) = -3.86 to -0.67, p = 0.005, I2 = 30% , N = 4 studies, n = 502 patients]. Moreover, pimavanserin was superior to placebo for reducing SAPS-H (WMD = -2.15, 95% CI = -3.45 to -0.86, p = 0.001, I2 = 0% , N = 2, n = 237) and SAPS-D scores (WMD = -1.32, 95% CI = -2.32 to -0.32, p = 0.010, I2 = 0% , N = 2, n = 237). Pimavanserin was associated with less orthostatic hypotension than placebo (risk ratio = 0.33, 95% CI = 0.15-0.75, p = 0.008, I2 = 0% , number needed to harm = 17, p = 0.01, N = 3, n = 476). There were no significant differences in rates of all-cause discontinuation, adverse events, and death, UPDRS-II+III scores, and incidences of individual adverse events (other than orthostatic hypotension) between pimavanserin and placebo groups. CONCLUSIONS: Pooled RCT results suggest that pimavanserin is beneficial for the treatment of PDP and is well tolerated. We did not identify other negative modulators of the 5-HT2A receptor for the treatment of PDP.
Keywords: Antiparkinson Agents; Humans; Parkinson Disease; Randomized Controlled Trials as Topic; Receptor, Serotonin, 5-HT2A; Serotonin 5-HT2 Receptor Agonists

Shared Genetic Etiology between Type 2 Diabetes and Alzheimer's Disease Identified by Bioinformatics Analysis. - Gao, Lei; Cui, Zhen; Shen, Liang; Ji, Hong-Fang (J Alzheimers Dis, 2016)
Type 2 diabetes (T2D) and Alzheimer's disease (AD) are two major health issues, and increasing evidence in recent years supports the close connection between these two diseases. The present study aimed to explore the shared genetic etiology underlying T2D and AD based on the available genome wide association studies (GWAS) data collected through August 2014. We performed bioinformatics analyses based on GWAS data of T2D and AD on single nucleotide polymorphisms (SNPs), gene, and pathway levels, respectively. Six SNPs (rs111789331, rs12721046, rs12721051, rs4420638, rs56131196, and rs66626994) were identified for the first time to be shared genetic factors between T2D and AD. Further functional enrichment analysis found lipid metabolism related pathways to be common between these two disorders. The findings may have important implications for future mechanistic and interventional studies for T2D and AD.
Keywords: Alzheimer Disease; Apolipoprotein C-I; Computational Biology; Databases, Factual; Diabetes Mellitus, Type 2; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Lipid Metabolism; Male; Polymorphism, Single Nucleotide

Shared Genetic Risk Factors for Late-Life Depression and Alzheimer's Disease. - Ye, Qing; Bai, Feng; Zhang, Zhijun (J Alzheimers Dis, 2016)
BACKGROUND: Considerable evidence has been reported for the comorbidity between late-life depression (LLD) and Alzheimer's disease (AD), both of which are very common in the general elderly population and represent a large burden on the health of the elderly. The pathophysiological mechanisms underlying the link between LLD and AD are poorly understood. Because both LLD and AD can be heritable and are influenced by multiple risk genes, shared genetic risk factors between LLD and AD may exist. OBJECTIVE: The objective is to review the existing evidence for genetic risk factors that are common to LLD and AD and to outline the biological substrates proposed to mediate this association. METHODS: A literature review was performed. RESULTS: Genetic polymorphisms of brain-derived neurotrophic factor, apolipoprotein E, interleukin 1-beta, and methylenetetrahydrofolate reductase have been demonstrated to confer increased risk to both LLD and AD by studies examining either LLD or AD patients. These results contribute to the understanding of pathophysiological mechanisms that are common to both of these disorders, including deficits in nerve growth factors, inflammatory changes, and dysregulation mechanisms involving lipoprotein and folate. Other conflicting results have also been reviewed, and few studies have investigated the effects of the described polymorphisms on both LLD and AD. CONCLUSION: The findings suggest that common genetic pathways may underlie LLD and AD comorbidity. Studies to evaluate the genetic relationship between LLD and AD may provide insights into the molecular mechanisms that trigger disease progression as the population ages.
Keywords: Age of Onset; Alzheimer Disease; Animals; Depressive Disorder; Genetic Predisposition to Disease; Humans; Polymorphism, Single Nucleotide; Risk Factors

Spatial Memory Impairment is Associated with Intraneural Amyloid-β Immunoreactivity and Dysfunctional Arc Expression in the Hippocampal-CA3 Region of a Transgenic Mouse Model of Alzheimer's Disease. - Morin, Jean-Pascal; Cerón-Solano, Giovanni; Velázquez-Campos, Giovanna; Pacheco-López, Gustavo; Bermúdez-Rattoni, Federico; Díaz-Cintra, Sofía (J Alzheimers Dis, 2016)
Dysfunction of synaptic communication in cortical and hippocampal networks has been suggested as one of the neuropathological hallmarks of the early stages of Alzheimer's disease (AD). Also, several lines of evidence have linked disrupted levels of activity-regulated cytoskeletal associated protein (Arc), an immediate early gene product that plays a central role in synaptic plasticity, with AD "synaptopathy". The mapping of Arc expression patterns in brain networks has been extensively used as a marker of memory-relevant neuronal activity history. Here we evaluated basal and behavior-induced Arc expression in hippocampal networks of the 3xTg-AD mouse model of AD. The basal percentage of Arc-expressing cells in 10-month-old 3xTg-AD mice was higher than wild type in CA3 (4.88% versus 1.77% , respectively) but similar in CA1 (1.75% versus 2.75% ). Noteworthy, this difference was not observed at 3 months of age. Furthermore, although a Morris water maze test probe induced a steep (∼4-fold) increment in the percentage of Arc+ cells in the CA3 region of the 10-month-old wild-type group, no such increment was observed in age-matched 3xTg-AD, whereas the amount of Arc+ cells in CA1 increased in both groups. Further, we detected that CA3 neurons with amyloid-β were much more likely to express Arc protein under basal conditions. We propose that in 3xTg-AD mice, intraneuronal amyloid-β expression in CA3 could increase unspecific neuronal activation and subsequent Arc protein expression, which might impair further memory-stabilizing processes.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Amyloid beta-Protein Precursor; Animals; Benzeneacetamides; CA3 Region, Hippocampal; Cytoskeletal Proteins; Disease Models, Animal; Gene Expression Regulation; Humans; Maze Learning; Memory Disorders; Mice; Mice, Transgenic; Mutation; Nerve Tissue Proteins; Neurons; Presenilin-1; Pyridines; tau Proteins

Spatial Navigation in Preclinical Alzheimer's Disease. - Allison, Samantha L; Fagan, Anne M; Morris, John C; Head, Denise (J Alzheimers Dis, 2016)
Although several previous studies have demonstrated navigational deficits in early-stage symptomatic Alzheimer's disease (AD), navigational abilities in preclinical AD have not been examined. The present investigation examined the effects of preclinical AD and early-stage symptomatic AD on spatial navigation performance. Performance on tasks of wayfinding and route learning in a virtual reality environment were examined. Comparisons were made across the following three groups: Clinically normal without preclinical AD (n = 42), clinically normal with preclinical AD (n = 13), and early-stage symptomatic AD (n = 16) groups. Preclinical AD was defined based on cerebrospinal fluid Aβ42 levels below 500 pg/ml. Preclinical AD was associated with deficits in the use of a wayfinding strategy, but not a route learning strategy. Moreover, post-hoc analyses indicated that wayfinding performance had moderate sensitivity and specificity. Results also confirmed early-stage symptomatic AD-related deficits in the use of both wayfinding and route learning strategies. The results of this study suggest that aspects of spatial navigation may be particularly sensitive at detecting the earliest cognitive deficits of AD.
Keywords: Aged; Alzheimer Disease; Biomarkers; Educational Status; Female; Humans; Learning; Male; Neuropsychological Tests; Prodromal Symptoms; Psychomotor Performance; ROC Curve; Spatial Navigation; tau Proteins; User-Computer Interface

Specific Features of Subjective Cognitive Decline Predict Faster Conversion to Mild Cognitive Impairment. - Fernández-Blázquez, Miguel A; Ávila-Villanueva, Marina; Maestú, Fernando; Medina, Miguel (J Alzheimers Dis, 2016)
BACKGROUND: Alzheimer's disease (AD) is a silent disorder that needs the earliest possible intervention in order to reduce its high economic and social impact. It has been recently suggested that subjective cognitive decline (SCD) appears at preclinical stages many years before the onset of AD. Therefore, SCD could become an ideal target for early therapeutic intervention. OBJECTIVE: The goal of this study was to evaluate the clinical significance of SCD on the conversion from a cognitively healthy stage to a mild cognitive impairment (MCI) in one-year follow-up. METHODS: A total of 608 cognitively intact individuals from the Vallecas Project's cohort, a community-based prospective study to identify early markers of AD, were enrolled in this study. Participants were classified in three groups: i) No Complaints (NCg), ii) Subjects with complaints in one or more cognitive domains (SCDg), and iii) Subjects who, besides complaints, fulfilled the features of SCD Plus proposed by the International Working Group of SCD (SCD-Pg). RESULTS: Individuals were followed up for a mean of 13.1 months (range 10.7-22.4). During this time, 41 volunteers developed MCI (6.7% of total sample). The conversion rate for SCD-Pg (18.9%) was significantly higher than SCDg (5.6%) and NCg (4.9%). CONCLUSION: Specific features associated with SCD may help to identify individuals at high risk of fast conversion to MCI. These results highlight the importance of a close follow-up of subjects with SCD-P and include them in early intervention programs because of their increased risk for the development of MCI.
Keywords: Aged; Alzheimer Disease; Apolipoprotein E4; Cognitive Dysfunction; Disease Progression; Female; Follow-Up Studies; Genotyping Techniques; Humans; Kaplan-Meier Estimate; Male; Neuropsychological Tests; Perception; Prodromal Symptoms; Prognosis; Prospective Studies; Time Factors

Subjective Memory Complaints in APOEɛ4 Carriers are Associated with High Amyloid-β Burden. - Zwan, Marissa D; Villemagne, Victor L; Doré, Vincent; Buckley, Rachel; Bourgeat, Pierrick; Veljanoski, Robyn; Salvado, Olivier; Williams, Rob; Margison, Laura; Rembach, Alan; Macaulay, S Lance; Martins, Ralph; et al. (J Alzheimers Dis, 2016)
BACKGROUND: APOEɛ4 genotype and aging have been identified as risk factors for Alzheimer's disease (AD). In addition, subjective memory complaints (SMC) might be a first clinical expression of the effect of AD pathology on cognitive functioning. OBJECTIVE: To assess whether APOEɛ4 genotype, age, SMC, and episodic memory are risk factors for high amyloid-β (Aβ) burden in cognitively normal elderly. METHODS: 307 cognitively normal participants (72.7 ± 6.8 years, 53% female, 55% SMC) from the Australian Imaging, Biomarkers and Lifestyle (AIBL) study underwent amyloid PET and APOE genotyping. Logistic regression analyses were performed to determine the association of APOEɛ4 genotype, age, SMC, and episodic memory with Aβ pathology. RESULTS: Odds of high Aβ burden were greater at an older age (OR = 3.21; 95% CI = 1.68-6.14), when SMC were present (OR = 1.90; 95% CI = 1.03-3.48), and for APOEɛ4 carriers (OR = 7.49; 95% CI = 3.96-14.15), while episodic memory was not associated with odds of high Aβ burden. Stratified analyses showed that odds of SMC for high Aβ burden were increased in specifically APOEɛ4 carriers (OR = 4.58, 95% CI = 1.83-11.49) and younger participants (OR = 3.73, 95% CI = 1.39-10.01). CONCLUSION: Aging, APOEɛ4 genotype, and SMC were associated with high Aβ burden. SMC were especially indicative of high Aβ burden in younger participants and in APOEɛ4 carriers. These findings suggest that selection based on the presence of SMC, APOEɛ4 genotype and age may help identify healthy elderly participants with high Aβ burden eligible for secondary prevention trials.
Keywords: Aged; Aging; Amyloid beta-Peptides; Aniline Compounds; Apolipoprotein E4; Benzothiazoles; Brain; Cognition Disorders; Female; Genotyping Techniques; Heterozygote; Humans; Logistic Models; Male; Neuropsychological Tests; Positron-Emission Tomography; Radiopharmaceuticals; Thiazoles

T3D-959: A Multi-Faceted Disease Remedial Drug Candidate for the Treatment of Alzheimer's Disease. - Tong, Ming; Deochand, Chetram; Didsbury, John; de la Monte, Suzanne M (J Alzheimers Dis, 2016)
BACKGROUND: T3D-959, a dual PPAR-δ/PPAR γ nuclear receptor agonist and former diabetes drug candidate, has been repositioned as an Alzheimer's disease (AD)-modifying therapy. OBJECTIVE: This study examines the effectiveness and mechanisms of T3D-959's therapeutic effects using in vivo and ex vivo rat models of sporadic AD. METHODS: A sporadic AD model was generated by intracerebral (i.c.) administration of streptozotocin (STZ). Control and i.c. STZ treated rats were gavaged with saline or T3D-959 (0.3 to 3.0 mg/kg/day) for 28 days. Spatial learning and memory were evaluated using the Morris water maze test. Frontal lobe slice cultures generated 24 hours after i.c. STZ or vehicle were used to study early effects of T3D-959 (0.5-1.0 μM) on viability and molecular markers of AD. RESULTS: T3D-959 significantly improved spatial learning and memory in i.c STZ-treated rats. Mechanistically, T3D-959 significantly improved culture viability and brain morphology, reduced levels of oxidative stress and Aβ, and normalized expression of phospho-tau, choline acetyltransferase, and myelin-associated glycoprotein. Protective effects occurred even at the lowest tested dose of T3D-959. CONCLUSIONS: Pre-clinical proof of concept has been demonstrated that T3D-959 can improve multiple pathologies of AD resulting in significant improvements in cognitive function and molecular and biochemical indices of neurodegeneration. These results support the theses that (1) effective disease modification in AD can be achieved by targeting relevant nuclear receptors, and (2) treating AD as a metabolic disease has the potential to be disease remedial. A Phase 2a trial of T3D-959 in mild-to-moderate AD patients has been initiated (ClinicalTrials.gov identifier NCT02560753).
Keywords: Alzheimer Disease; Analysis of Variance; Animals; Animals, Newborn; Antibiotics, Antineoplastic; Antipsychotic Agents; Blood Glucose; Body Weight; Brain; Choline O-Acetyltransferase; Disease Models, Animal; Dose-Response Relationship, Drug; Glial Fibrillary Acidic Protein; Glucosephosphate Dehydrogenase; In Vitro Techniques; Maze Learning; Myelin Basic Protein; Neurotoxicity Syndromes; Organ Culture Techniques; PPAR delta; PPAR gamma; Rats; Rats, Long-Evans; Spatial Learning; Streptozocin

Tau Accumulation in Primary Motor Cortex of Variant Alzheimer's Disease with Spastic Paraparesis. - Lyoo, Chul Hyoung; Cho, Hanna; Choi, Jae Yong; Hwang, Mi Song; Hong, Sang Kyoon; Kim, Yun Joong; Ryu, Young Hoon; Lee, Myung Sik (J Alzheimers Dis, 2016)
We studied topographic distribution of tau and amyloid-β in a patient with variant Alzheimer's disease with spastic paraparesis (VarAD) by comparing AD patients. The proband developed progressive memory impairment, dysarthria, and spastic paraparesis at age 23. Heterozygous missense mutation (L166P) was found in exon 6 of presenilin-1 gene. The proband showed prominently increased amyloid binding in striatum and cerebellum and asymmetrical tau binding in the primary sensorimotor cortex contralateral to the side more affected by spasticity. We suspect that upper motor neuron dysfunctions may be attributed to excessive abnormal tau accumulation rather than amyloid-β in the primary motor cortex.
Keywords: Adult; Aged; Alzheimer Disease; Aniline Compounds; Brain Mapping; Carbolines; Female; Humans; Male; Motor Cortex; Mutation, Missense; Paraparesis, Spastic; Positron-Emission Tomography; Presenilin-1; Radiopharmaceuticals; Stilbenes; tau Proteins

A TgCRND8 Mouse Model of Alzheimer's Disease Exhibits Sexual Dimorphisms in Behavioral Indices of Cognitive Reserve. - Granger, Matthew W; Franko, Bettina; Taylor, Matthew W; Messier, Claude; George-Hyslop, Peter St; Bennett, Steffany A L (J Alzheimers Dis, 2016)
Cognitive decline is sexually dimorphic in Alzheimer's disease (AD). Men show higher incidences of amnestic mild cognitive impairment yet women disproportionally phenoconvert to AD. It is hypothesized that men maintain greater cognitive reserve than women under comparable amyloid-β (Aβ) challenge. One behavioral aspect of cognitive reserve in mice is the capacity to cope with Aβ-associated stereotypies by switching to increasingly effective navigational search strategies in the Morris water maze. To explore inherent sex differences in this paradigm, however, we require an AβPP mouse model wherein behavioral flexibility is impaired earlier in females than males despite equivalent Aβ load. Here, we show that when F1 C57Bl/6×C3H/HeJ TgCRND8 mice are placed on C57Bl/6 background, N5 Tg males and females exhibit equivalent Aβ pathologies at 2, 4, 6, and 8 months of age yet females display learning and memory deficits earlier than males. We further show that this N5 line does not carry the autosomal recessive pde6brd1 mutation that impairs visual acuity and that the estrous cycle is not disrupted on this genetic background. At 5.5 months of age, Tg males, but not females, compensate for Aβ-associated stereotypic behaviors (i.e., hyperactive tight circling) by alternating navigational search strategies and adopting increasingly productive spatial search strategies. Females fail to overcome Aβ-associated stereotypies and do not efficiently switch from systematic to spatial learning strategies. Together, these data identify a novel AβPP mouse model that can be used for preclinical testing of interventions targeting sexual dimorphisms in behavioral indices of cognitive reserve.
Keywords: Alzheimer Disease; Amyloid beta-Protein Precursor; Animals; Brain; Cognitive Reserve; Cyclic Nucleotide Phosphodiesterases, Type 6; Disease Models, Animal; Female; Humans; Male; Maze Learning; Mice, Inbred C3H; Mice, Inbred C57BL; Mice, Transgenic; Plaque, Amyloid; Psychomotor Performance; Sex Characteristics; Spatial Memory; Spatial Navigation; Survival Analysis

Tobacco Smoke Exposure Impairs Brain Insulin/IGF Signaling: Potential Co-Factor Role in Neurodegeneration. - Deochand, Chetram; Tong, Ming; Agarwal, Amit R; Cadenas, Enrique; de la Monte, Suzanne M (J Alzheimers Dis, 2016)
BACKGROUND: Human studies suggest tobacco smoking is a risk factor for cognitive impairment and neurodegeneration, including Alzheimer's disease (AD). However, experimental data linking tobacco smoke exposures to underlying mediators of neurodegeneration, including impairments in brain insulin and insulin-like growth factor (IGF) signaling in AD are lacking. OBJECTIVE: This study tests the hypothesis that cigarette smoke (CS) exposures can impair brain insulin/IGF signaling and alter expression of AD-associated proteins. METHODS: Adult male A/J mice were exposed to air for 8 weeks (A8), CS for 4 or 8 weeks (CS4, CS8), or CS8 followed by 2 weeks recovery (CS8+R). Gene expression was measured by qRT-PCR analysis and proteins were measured by multiplex bead-based or direct binding duplex ELISAs. RESULTS: CS exposure effects on insulin/IGF and insulin receptor substrate (IRS) proteins and phosphorylated proteins were striking compared with the mRNA. The main consequences of CS4 or CS8 exposures were to significantly reduce insulin R, IGF-1R, IRS-1, and tyrosine phosphorylated insulin R and IGF-1R proteins. Paradoxically, these effects were even greater in the CS8+R group. In addition, relative levels of S312-IRS-1, which inhibits downstream signaling, were increased in the CS4, CS8, and CS8+R groups. Correspondingly, CS and CS8+R exposures inhibited expression of proteins and phosphoproteins required for signaling through Akt, PRAS40, and/or p70S6K, increased AβPP-Aβ, and reduced ASPH protein, which is a target of insulin/IGF-1 signaling. CONCLUSION: Secondhand CS exposures caused molecular and biochemical abnormalities in brain that overlap with the findings in AD, and many of these effects were sustained or worsened despite short-term CS withdrawal.
Keywords: Animals; Brain; Insulin; Male; Mice; Nerve Degeneration; Neurons; Phosphorylation; Receptor, IGF Type 1; Signal Transduction; Somatomedins; Tobacco Smoke Pollution

Tobacco Smoke-Induced Brain White Matter Myelin Dysfunction: Potential Co-Factor Role of Smoking in Neurodegeneration. - Yu, Rosa; Deochand, Chetram; Krotow, Alexander; Leão, Raiane; Tong, Ming; Agarwal, Amit R; Cadenas, Enrique; de la Monte, Suzanne M (J Alzheimers Dis, 2016)
BACKGROUND: Meta-analysis studies showed that smokers have increased risk for developing Alzheimer's disease (AD) compared with non-smokers, and neuroimaging studies revealed that smoking damages white matter structural integrity. OBJECTIVE: The present study characterizes the effects of side-stream (second hand) cigarette smoke (CS) exposures on the expression of genes that regulate oligodendrocyte myelin-synthesis, maturation, and maintenance and neuroglial functions. METHODS: Adult male A/J mice were exposed to air (8 weeks; A8), CS (4 or 8 weeks; CS4, CS8), or CS8 followed by 2 weeks recovery (CS8 + R). The frontal lobes were used for histology and qRT-PCR analysis. RESULTS: Luxol fast blue, Hematoxylin and Eosin stained histological sections revealed CS-associated reductions in myelin staining intensity and narrowing of the corpus callosum. CS exposures broadly decreased mRNA levels of immature and mature oligodendrocyte myelin-associated, neuroglial, and oligodendrocyte-related transcription factors. These effects were more prominent in the CS8 compared with CS4 group, suggesting that molecular abnormalities linked to white matter atrophy and myelin loss worsen with duration of CS exposure. Recovery normalized or upregulated less than 25% of the suppressed genes; in most cases, inhibition of gene expression was either sustained or exacerbated. CONCLUSION: CS exposures broadly inhibit expression of genes needed for myelin synthesis and maintenance. These adverse effects often were not reversed by short-term CS withdrawal. The results support the hypothesis that smoking contributes to white matter degeneration, and therefore could be a key risk factor for a number of neurodegenerative diseases, including AD.
Keywords: 2',3'-Cyclic-Nucleotide Phosphodiesterases; AC133 Antigen; Animals; Antigens, CD; Brain; Disease Models, Animal; Galactosylceramides; Gene Expression Regulation; Glycoproteins; Leukoencephalopathies; Male; Mice; Nerve Degeneration; Nerve Tissue Proteins; Neuroglia; Neurons; Oligodendroglia; Papain; Peptides; Smoking; Tobacco; Transcription Factors

Transferring cut-off values between assays for cerebrospinal fluid Alzheimer's disease biomarkers. - García Barrado, Leandro; Coart, Els; Vanderstichele, Hugo M J; Burzykowski, Tomasz (J Alzheimers Dis, 2016)
Current technologies quantifying cerebrospinal fluid biomarkers to identify subjects with Alzheimer's disease pathology report different concentrations in function of technology and suffer from between-laboratory variability. Hence, lab- and technology-specific cut-off values are required. It is common practice to establish cut-off values on small datasets and, in the absence of well-characterized samples, to transfer the cut-offs to another assay format using 'side-by-side' testing of samples with both assays. We evaluated the uncertainty in cut-off estimation and the performance of two methods of cut-off transfer by using two clinical datasets and simulated data. The cut-off for the new assay was transferred by applying the commonly-used linear regression approach and a new Bayesian method, which consists of using prior information about the current assay for estimation of the biomarker's distributions for the new assay. Simulations show that cut-offs established with current sample sizes are insufficiently precise and also show the effect of increasing sample sizes on the cut-offs' precision. The Bayesian method results in unbiased and less variable cut-offs with substantially narrower 95% confidence intervals compared to the linear-regression transfer. For the BIODEM datasets, the transferred cut-offs for INNO-BIA Aβ1-42 are 167.5 pg/mL (95% credible interval [156.1, 178.0] and 172.8 pg/mL (95% CI [147.6, 179.6]) with Bayesian and linear regression methods, respectively. For the EUROIMMUN assay, the estimated cut-offs are 402.8 pg/mL (95% credible interval [348.0, 473.9]) and 364.4 pg/mL (95% CI [269.7, 426.8]). Sample sizes and statistical methods used to establish and transfer cut-off values have to be carefully considered to guarantee optimal diagnostic performance of biomarkers.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Bayes Theorem; Biomarkers; Cognitive Dysfunction; Datasets as Topic; Humans; Linear Models; Multivariate Analysis; Peptide Fragments; tau Proteins

Two Phase 2 Multiple Ascending-Dose Studies of Vanutide Cridificar (ACC-001) and QS-21 Adjuvant in Mild-to-Moderate Alzheimer's Disease. - Pasquier, Florence; Sadowsky, Carl; Holstein, Ann; Leterme, Ghislaine Le Prince; Peng, Yahong; Jackson, Nicholas; Fox, Nick C; Ketter, Nzeera; Liu, Enchi; Ryan, J Michael (J Alzheimers Dis, 2016)
Vanutide cridificar (ACC-001), an immunotherapeutic vaccine, is a potentially disease-modifying therapy that aims to reduce brain amyloid-β (Aβ) plaques in patients with Alzheimer's disease (AD). ACC-001 was evaluated in two phase 2a, multicenter, randomized, third party-unblinded, placebo-controlled, multiple ascending-dose studies of ACC-001 (3μg, 10μg, 30μg) with and without QS-21 adjuvant that enrolled patients with mild-to-moderate AD (n = 245). Patients were treated with up to five doses of study vaccine or placebo and followed for safety and tolerability (primary objective) and anti-Aβ IgG immunogenicity (secondary objective) up to 12 months after the last vaccination. Exploratory assessments included cognitive/functional measures, brain magnetic resonance imaging (MRI) volumetry, and pharmacodynamic markers in plasma and cerebrospinal fluid (CSF). The most frequent treatment-emergent adverse events (≥10%) were local injection reactions and headache. Amyloid-related imaging abnormalities with vasogenic edema occurred in two (0.8%) patients (ACC-001 30μg + QS-21; ACC-001 10μg). ACC-001 + QS-21 elicited consistently higher peak and sustained anti-Aβ IgG titers compared with ACC-001 alone. Plasma Aβx-40 was significantly higher in all ACC-001 + QS-21 groups versus placebo (weeks 16-56), with no evidence of dose response. Exploratory cognitive evaluations, volumetric brain MRI, and CSF biomarkers did not show differences or trends between treatment groups and placebo. ACC-001 with or without QS-21 adjuvant has an acceptable safety profile in patients with mild-to-moderate AD.
Keywords: Adjuvants, Immunologic; Aged; Alzheimer Disease; Amyloid beta-Peptides; Antipsychotic Agents; Dose-Response Relationship, Drug; Female; Follow-Up Studies; Humans; Interferon-gamma; Magnetic Resonance Imaging; Male; Middle Aged; Neuropsychological Tests; Peptide Fragments; Recombinant Fusion Proteins; Saponins; Single-Blind Method; Treatment Outcome

UCH-L1 Inhibition Decreases the Microtubule-Binding Function of Tau Protein. - Xie, Min; Han, Yun; Yu, Quntao; Wang, Xia; Wang, Shaohui; Liao, Xiaomei (J Alzheimers Dis, 2016)
Ubiquitin C-terminal hydrolase L1 (UCH-L1) is critical for protein degradation and free ubiquitin recycling. In Alzheimer's disease brains, UCH-L1 is negatively related to neurofibrillary tangles whose major component is hyperphosphorylated tau protein, but the direct action of UCH-L1 on tau has not been reported. In the current study, mouse neuroblastoma Neuro2a (N2a) cells were treated by the different concentrations of UCH-L1 inhibitor LDN (2.5, 5 and 10 μM) to inhibit the hydrolase activity of UCH-L1. In addition, we also used UCH-L1 siRNA to treat the HEK293/tau441 cells to decrease the expression of UCH-L1. After LDN and UCH-L1 siRNA treatment, we used immunofluorescence, immunoprecipitation, and tau-microtubule binding assay to measure the microtubule-binding ability and post-translational modifications of tau protein. All the results presented that both inhibition of the activity and expression of UCH-L1 induced the decreased microtubule-binding ability and increased phosphorylation of tau protein. Abnormal aggregation and ubiquitination of tau protein was also observed after UCH-L1 inhibition. The above results suggested that aggregation of tau protein might be devoted to the abnormal post-translational modifications of tau protein. Our study first indicates that dysfunction of UCH-L1 most likely affected normal biological function of tau protein through decreasing degradation of ubiquitinated and hyperphosphorylated tau.
Keywords: Animals; Cell Line, Tumor; Dose-Response Relationship, Drug; HEK293 Cells; Humans; Immunoprecipitation; Indoles; Mice; Microtubules; Neuroblastoma; Oximes; Protein Binding; Proteolysis; RNA, Small Interfering; tau Proteins; Ubiquitin Thiolesterase; Ubiquitination

Unmet Needs of Community-Dwelling Primary Care Patients with Dementia in Germany: Prevalence and Correlates. - Eichler, Tilly; Thyrian, Jochen René; Hertel, Johannes; Richter, Steffen; Wucherer, Diana; Michalowsky, Bernhard; Teipel, Stefan; Kilimann, Ingo; Dreier, Adina; Hoffmann, Wolfgang (J Alzheimers Dis, 2016)
BACKGROUND: To provide an optimal care for persons with dementia (PWD), their individual unmet needs have to be identified and comprehensively addressed. OBJECTIVES: Present analyses aim to describe the number and types of unmet needs of German primary care patients screened positive for dementia and factors associated with the number of unmet needs. METHODS: DelpHi-MV (Dementia: life- and person-centered help in Mecklenburg-Western Pomerania) is a general practitioner-based, cluster-randomized controlled intervention trial. Analyses are based on the baseline data of 227 PWD (≥70 years, living at home) of the intervention group who had screened positive for dementia (DemTect<9) and received a standardized computer-assisted needs assessment. RESULTS: PWD had on average 8.77±5.04 unmet needs (Range = 0-31). More than 90% of the PWD had three or more unmet needs. Unmet needs were identified across all predefined 26 subcategories. The majority of unmet needs occurred in the domains "nursing treatment and care" (38%), "social counseling and legal support" (20%), and "pharmacological treatment and care" (15%). More impairment in the activities of daily living was the only factor that was significantly associated with a higher number of unmet needs, independent of age, gender, living situation, presence of an informal caregiver, cognitive impairment, and depression. CONCLUSIONS: Present results demonstrate that community-dwelling PWD had a broad range of varying unmet needs. These findings emphasize the importance of a comprehensive needs assessment that allows the identification of individual needs as the basis for a tailored intervention- such as Dementia Care Management- that can address these needs.
Keywords: Aged, 80 and over; Caregivers; Cross-Sectional Studies; Dementia; Depression; Female; Germany; Health Services Needs and Demand; Humans; Male; Needs Assessment; Prevalence

Upregulation of Connexin 43 Expression Via C-Jun N-Terminal Kinase Signaling in Prion Disease. - Lee, Geon-Hwi; Jang, Byungki; Choi, Hong-Seok; Kim, Hee-Jun; Park, Jeong-Ho; Jeon, Yong-Chul; Carp, Richard I; Kim, Yong-Sun; Choi, Eun-Kyoung (J Alzheimers Dis, 2016)
Prion infection leads to neuronal cell death, glial cell activation, and the accumulation of misfolded prion proteins. However, the altered cellular environments in animals with prion diseases are poorly understood. In the central nervous system, cells connect the cytoplasm of adjacent cells via connexin (Cx)-assembled gap junction channels to allow the direct exchange of small molecules, including ions, neurotransmitters, and signaling molecules, which regulate the activities of the connected cells. Here, we investigate the role of Cx43 in the pathogenesis of prion diseases. Upregulated Cx43 expression, which was dependent on c-Jun N-Terminal Kinase (JNK)/c-Jun signaling cascades, was found in prion-affected brain tissues and hippocampal neuronal cells. Scrapie infection-induced Cx43 formed aggregated plaques within the cytoplasmic compartments at the cell-cell interfaces. The ethidium bromide (EtBr) uptake assay and scrape-loading dye transfer assay demonstrated that increased Cx43 has functional consequences for the activity of Cx43 hemichannels. Interestingly, blockade of PrPSc accumulation reduced Cx43 expression through the inhibition of JNK signaling, indicating that PrPSc accumulation may be directly involved in JNK activation-mediated Cx43 upregulation. Overall, our findings describe a scrapie infection-mediated novel regulatory signaling pathway of Cx43 expression and may suggest a role for Cx43 in the pathogenesis of prion diseases.
Keywords: Animals; Brain; Cell Membrane; Cells, Cultured; Connexin 43; Disease Models, Animal; JNK Mitogen-Activated Protein Kinases; MAP Kinase Signaling System; Mesocricetus; Mice, Inbred C57BL; Mice, Knockout; PrPSc Proteins; RNA, Messenger; Scrapie; Up-Regulation

The Utilization of Retinal Nerve Fiber Layer Thickness to Predict Cognitive Deterioration. - Shi, Zhongyong; Zhu, Yingbo; Wang, Meijuan; Wu, Yujie; Cao, Jing; Li, Chunbo; Xie, Zhongcong; Shen, Yuan (J Alzheimers Dis, 2016)
Our previous studies have shown that longitudinal reduction in retinal nerve fiber layer (RNFL) thickness is associated with cognitive deterioration. However, whether the combination of longitudinal reduction in RNFL thickness with baseline episodic memory performance can better predict cognitive deterioration remains unknown. Therefore, we set out to re-analyze the data obtained from our previous studies with 78 elderly adults (mean age 74.4 ± 3.83 years, 48.7% male) in the community over a 25-month period. The participants were categorized as either stable participants whose cognitive status did not change (n = 60) or converted participants whose cognitive status deteriorated (n = 18). A logistic regression analysis was applied to determine a conversion score for predicting the cognitive deterioration in the participants. We found that the area under the receiver operating characteristic curve (AUC) for the multivariable model was 0.854 (95% CI 0.762-0.947) using baseline story recall as a predictor, but the AUC increased to 0.915 (95% CI 0.849-0.981) with the addition of the longitudinal reduction of RNFL thickness in the inferior quadrant. The conversion score was significantly higher for the converted participants than the stable participants (0.59 ± 0.30 versus 0.12 ± 0.19, p <  0.001). Finally, the optimal cutoff value of the conversion score (0.134) was determined by the analysis of receiver operating characteristic curve, and this conversion score generated a sensitivity of 0.944 and a specificity of 0.767 in predicting the cognitive deterioration. These findings have established a system to perform a larger scale study to further test whether the longitudinal reduction in RNFL thickness could serve as a biomarker of Alzheimer's disease.
Keywords: Aged; Cognition Disorders; Female; Humans; Logistic Models; Longitudinal Studies; Male; Nerve Fibers; Neuropsychological Tests; Predictive Value of Tests; Retina; ROC Curve; Statistics, Nonparametric; Tomography, Optical Coherence

Vascular Risk Factors and Cognition in Parkinson's Disease. - Pilotto, Andrea; Turrone, Rosanna; Liepelt-Scarfone, Inga; Bianchi, Marta; Poli, Loris; Borroni, Barbara; Alberici, Antonella; Premi, Enrico; Formenti, Anna; Bigni, Barbara; Cosseddu, Maura; Cottini, Elisabetta; et al. (J Alzheimers Dis, 2016)
Vascular risk factors have been associated with cognitive deficits and incident dementia in the general population, but their role on cognitive dysfunction in Parkinson's disease (PD) is still unclear. The present study addresses the single and cumulative effect of vascular risk factors on cognition in PD patients, taking clinical confounders into account. Standardized neuropsychological assessment was performed in 238 consecutive PD patients. We evaluated the association of single and cumulative vascular risk factors (smoking, diabetes, hypercholesterolemia, hypertension, and heart disease), with the diagnosis of PD normal cognition (PDNC, n = 94), mild cognitive impairment (PD-MCI, n = 111), and dementia (PDD, n = 33). The association between single neuropsychological tests and vascular risk factors was evaluated with covariance analyses adjusted for age at onset, educational levels, gender, disease duration, and motor performance. Age, educational levels, disease duration, and motor function were significantly different between PDNC, PD-MCI, and PDD. Heart disease was the only vascular factor significantly more prevalent in PDD compared with PDNC in adjusted analyses. Performance of tests assessing executive and attention functions were significantly worse in patients with hypertension, heart disease, and/or diabetes (p <  0.05). Heart disease is associated with dementia in PD, suggesting a potential window of intervention. Vascular risk factors act especially on attention and executive functions in PD. Vascular risk stratification may be useful in order to identify PD patients with a greater risk of developing dementia. These findings need to be verified in longitudinal studies.
Keywords: Age of Onset; Aged; Attention; Disability Evaluation; Educational Status; Executive Function; Female; Humans; Male; Motor Activity; Neuropsychological Tests; Parkinson Disease; Prevalence; Risk Factors; Sex Factors; Time Factors; Vascular Diseases

Ventilatory Response to Hypercapnia Predicts Dementia with Lewy Bodies in Late-Onset Major Depressive Disorder. - Takahashi, Sho; Mizukami, Katsuyoshi; Arai, Tetsuaki; Ogawa, Ryoko; Kikuchi, Norihiro; Hattori, Satoshi; Darby, David; Asada, Takashi (J Alzheimers Dis, 2016)
BACKGROUND: Studies have shown that developing major depressive disorder (MDD) at 50 years of age or older can predict dementia. Depression is particularly common in dementia with Lewy bodies (DLB), and occasionally occurs before the onset of extrapyramidal symptoms. Moreover, systemic autonomic dysfunction, including an abnormal ventilatory response to hypercapnia (VRH), is common in patients with DLB. OBJECTIVE: Here, we aimed to determine whether the VRH is useful for distinguishing depression that is predictive of DLB from other types of MDD. METHODS: Participants were 35 consecutive patients with first onset MDD at 50 years or older with bradykinesia. After diagnosing the clinical subtype of MDD according to DSM-IV criteria, each subject underwent a battery of psychological tests, autonomic examinations including VRH, brain magnetic resonance imaging, and 123I-meta-iodobenzylguanidine scintigraphy. RESULTS: Longitudinal follow-up showed that all 18 patients with abnormal VRH results developed DLB, whereas none of the 17 patients with normal VRH results converted to DLB within the study period (sensitivity: 100% , specificity: 100%). Additionally, over half of the DLB converters showed abnormalities on other autonomic examinations. For converters, the most common MDD subtype had psychotic and melancholic features simultaneously. The frequency of hypersensitivity to psychotropics was higher in converters than it was in non-converters. CONCLUSION: In the present study, patients with abnormal VRH results were very likely to develop DLB. Thus, for patients with late-onset MDD accompanied by bradykinesia, the VRH in combination with the clinical subtype of MDD or hypersensitivity to psychotropics may be useful for diagnosing prodromal DLB.
Keywords: 3-Iodobenzylguanidine; Aged; Aged, 80 and over; Depressive Disorder, Major; Follow-Up Studies; Heart Rate; Humans; Hypercapnia; Hypotension, Orthostatic; Kaplan-Meier Estimate; Lewy Body Disease; Middle Aged; Partial Pressure; Psychiatric Status Rating Scales; Retrospective Studies; Ventilators, Mechanical

Vitamin D and Memory Decline: Two Population-Based Prospective Studies. - Kuźma, Elżbieta; Soni, Maya; Littlejohns, Thomas J; Ranson, Janice M; van Schoor, Natasja M; Deeg, Dorly J H; Comijs, Hannie; Chaves, Paulo H M; Kestenbaum, Bryan R; Kuller, Lewis H; Lopez, Oscar L; Becker, James T; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Vitamin D deficiency has been linked with dementia risk, cognitive decline, and executive dysfunction. However, the association with memory remains largely unknown. OBJECTIVE: To investigate whether low serum 25-hydroxyvitamin D (25(OH)D) concentrations are associated with memory decline. METHODS: We used data on 1,291 participants from the US Cardiovascular Health Study (CHS) and 915 participants from the Dutch Longitudinal Aging Study Amsterdam (LASA) who were dementia-free at baseline, had valid vitamin D measurements, and follow-up memory assessments. The Benton Visual Retention Test (in the CHS) and Rey's Auditory Verbal Learning Test (in the LASA) were used to assess visual and verbal memory, respectively. RESULTS: In the CHS, those moderately and severely deficient in serum 25(OH)D changed -0.03 SD (95% CI: -0.06 to 0.01) and -0.10 SD (95% CI: -0.19 to -0.02) per year respectively in visual memory compared to those sufficient (p = 0.02). In the LASA, moderate and severe deficiency in serum 25(OH)D was associated with a mean change of 0.01 SD (95% CI: -0.01 to 0.02) and -0.01 SD (95% CI: -0.04 to 0.02) per year respectively in verbal memory compared to sufficiency (p = 0.34). CONCLUSIONS: Our findings suggest an association between severe vitamin D deficiency and visual memory decline but no association with verbal memory decline. They warrant further investigation in prospective studies assessing different memory subtypes.
Keywords: Humans; Memory Disorders; Netherlands; Prospective Studies; United States; Vitamin D; Vitamin D Deficiency

Volumetric and shape analysis of the thalamus and striatum in amnestic mild cognitive impairment. - Leh, Sandra E; Kälin, Andrea M; Schroeder, Clemens; Park, Min Tae M; Chakravarty, M Mallar; Freund, Patrick; Gietl, Anton F; Riese, Florian; Kollias, Spyros; Hock, Christoph; Michels, Lars (J Alzheimers Dis, 2016)
Alterations in brain structures, including progressive neurodegeneration, are a hallmark in patients with Alzheimer's disease (AD). However, pathological mechanisms, such as the accumulation of amyloid and the proliferation of tau, are thought to begin years, even decades, before the initial clinical manifestations of AD. In this study, we compare the brain anatomy of amnestic mild cognitive impairment patients (aMCI, n = 16) to healthy subjects (CS, n = 22) using cortical thickness, subcortical volume, and shape analysis, which we believe to be complimentary to volumetric measures. We were able to replicate "classical" cortical thickness alterations in aMCI in the hippocampus, amygdala, putamen, insula, and inferior temporal regions. Additionally, aMCI showed significant thalamic and striatal shape differences. We observed higher global amyloid deposition in aMCI, a significant correlation between striatal displacement and global amyloid, and an inverse correlation between executive function and right-hemispheric thalamic displacement. In contrast, no volumetric differences were detected in thalamic, striatal, and hippocampal regions. Our results provide new evidence for early subcortical neuroanatomical changes in patients with aMCI, which are linked to cognitive abilities and amyloid deposition. Hence, shape analysis may aid in the identification of structural biomarkers for identifying individuals at highest risk of conversion to AD.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid; Biomarkers; Case-Control Studies; Cognitive Dysfunction; Corpus Striatum; Female; Hippocampus; Humans; Magnetic Resonance Imaging; Male; Middle Aged; Neuropsychological Tests; Positron-Emission Tomography; Thalamus

What are the Most Frequently Impaired Markers of Neurodegeneration in ADNI Subjects? - Andriuta, Daniela; Moullart, Véronique; Schraen, Susanna; Devendeville, Agnes; Meyer, Marc-Etienne; Godefroy, Olivier (J Alzheimers Dis, 2016)
The aim of this study was to examine the relationship between cerebrospinal fluid (CSF) levels of biomarkers for Alzheimer's disease (AD) (Aβ1-42, t-tau, and p-tau) and 18Fluorodeoxyglucose positron emission tomography (FDG-PET) hypometabolism in subjects from the Alzheimer's Disease Neuroimaging Initiative, and specifically to determine which index of neurodegeneration was most frequently affected. The secondary objective was to determine the most frequently hypometabolic region in patients with a CSF AD signature (abnormal Aβ1-42 and abnormal p-tau). We included the 372 subjects (85 normal subjects, 212 patients with mild cognitive impairment, and 75 patients with AD) with a CSF biomarker dosage (Aβ1-42, t-tau, and p-tau) and brain FDG-PET. The relationship between FDG-PET metabolism (in five regions of interest (ROI) known to be damaged in AD) and CSF t-tau and p-tau levels was studied as a function of CSF Aβ1-42 status. FDG-PET hypometabolism and CSF t-tau and p-tau levels were correlated only in patients with an abnormal CSF Aβ1-42 level (t-tau: R2 = 0.044, p = 0.001; p-tau: R2 = 0.02, p = 0.03). In the latter patients, CSF p-tau was the most frequently (p = 0.0001) abnormal neurodegeneration marker (p-tau: 92.8%; FDG-PET: 56.5%; CSF t-tau: 59.1%). Within the five ROI of FDG PET, the angular gyrus metabolism (R2 = 0.149; p = 0.0001) was selected as the most tightly associated with CSF AD signature. The relation between CSF markers of neurodegeneration (p-tau and t-tau) and brain hypometabolism (in FDG-PET) is conditioned by presence of amyloid abnormality. This finding supports the current physiopathological model of AD. P-tau is the most frequently impaired biomarker. Using FDG PET angular gyrus hypometabolism is the most sensitive to CSF-biomarker-defined AD.
Keywords: Aged; Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Brain; Cognitive Dysfunction; Databases, Factual; Female; Fluorodeoxyglucose F18; Humans; Male; Peptide Fragments; Phosphorylation; Positron-Emission Tomography; Radiopharmaceuticals; tau Proteins

White Matter Abnormalities Track Disease Progression in PSEN1 Autosomal Dominant Alzheimer's Disease. - Sánchez-Valle, Raquel; Monté, Gemma C; Sala-Llonch, Roser; Bosch, Beatriz; Fortea, Juan; Lladó, Albert; Antonell, Anna; Balasa, Mircea; Bargalló, Nuria; Molinuevo, José Luis (J Alzheimers Dis, 2016)
PSEN1 mutations are the most frequent cause of autosomal dominant Alzheimer's disease (ADAD), and show nearly full penetrance. There is presently increasing interest in the study of biomarkers that track disease progression in order to test therapeutic interventions in ADAD. We used white mater (WM) volumetric characteristics and diffusion tensor imaging (DTI) metrics to investigate correlations with the normalized time to expected symptoms onset (relative age ratio) and group differences in a cohort of 36 subjects from PSEN1 ADAD families: 22 mutation carriers, 10 symptomatic (SMC) and 12 asymptomatic (AMC), and 14 non-carriers (NC). Subjects underwent a 3T MRI. WM morphometric data and DTI metrics were analyzed. We found that PSEN1 MC showed significant negative correlation between fractional anisotropy (FA) and the relative age ratio in the genus and body of corpus callosum and corona radiate (p <  0.05 Family-wise error correction (FWE) at cluster level) and positive correlation with mean diffusivity (MD), axial diffusivity (AxD), and radial diffusivity (RD) in the splenium of corpus callosum. SMC presented WM volume loss, reduced FA and increased MD, AxD, and RD in the anterior and posterior corona radiate, corpus callosum (p <  0.05 FWE) compared with NC. No significant differences were observed between AMC and NC in WM volume or DTI measures. These findings suggest that the integrity of the WM deteriorates linearly in PSEN1 ADAD from the early phases of the disease; thus DTI metrics might be useful to monitor the disease progression. However, the lack of significant alterations at the preclinical stages suggests that these indexes might not be good candidates for early markers of the disease.
Keywords: Adult; Aging; Alzheimer Disease; Brain; Cohort Studies; Diffusion Tensor Imaging; Disease Progression; Family; Female; Heterozygote; Humans; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Male; Mental Status Schedule; Middle Aged; Mutation; Neuropsychological Tests; Organ Size; Presenilin-1; White Matter

δ Scores are Exportable Across Cultural and Linguistic Boundaries. - Royall, Donald R; Palmer, Raymond F; Matsuoka, Teruyuki; Kato, Yuka; Taniguchi, Shogo; Ogawa, Mayu; Fujimoto, Hiroshi; Okamura, Aiko; Shibata, Keisuke; Nakamura, Kaeko; Nakaaki, Shutaro; Koumi, Hiroyuki; et al. (J Alzheimers Dis, 2016)
The latent variable "δ", can accurately diagnose dementia. Its generalizability across populations is unknown. We constructed a δ homolog ("dT2J") in data collected by the Texas Alzheimer's Research and Care Consortium (TARCC). From this, we calculated a composite d-score "d". We then tested d's generalizability across random subsets of TARCC participants and to a convenience sample of elderly Japanese persons with normal cognition (NC), mild cognitive impairment (MCI), and dementia (AD) (n = 176). dT2J was indicated by Instrumental Activities of Daily Living and psychometric measures. Embedded in this battery were the Mini-Mental Status Examination (MMSE) and an executive clock-drawing task (CLOX). Only MMSE and CLOX were available in both TARCC and the Japanese cohort. Therefore, a second composite variable, "T2J", was constructed solely from the factor loadings of CLOX and MMSE on d. The diagnostic accuracy of T2J was estimated in the validation sample, the remainder of the TARCC cohort, and in the Japanese sample. The areas under the receiver operating curve (AUC; ROC) for T2J were compared in each sample, and against d in TARCC. The AUCs for T2J were statistically indiscriminable within TARCC, and in Japanese persons. In Japanese persons, AUCs for T2J were 0.97 for the discrimination between AD versus NC, 0.86 for AD versus MCI, and 0.79 for NC versus MCI. The AUCs for T2J in Japanese persons were higher than any individual psychometric measure in that sample. Valid d-score composites can be abstracted from a subset of δ's indicators. Moreover, those composites are exportable across cultural and linguistic boundaries.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Asian Continental Ancestry Group; Cognitive Dysfunction; Cohort Studies; Culture; Executive Function; Female; Humans; Linguistics; Male; Mental Status Schedule; Middle Aged; Neuropsychological Tests; Psychometrics; Reproducibility of Results; ROC Curve; Texas

Advancing research diagnostic criteria for Alzheimer's disease: the IWG-2 criteria. - Dubois, Bruno; Feldman, Howard H; Jacova, Claudia; Hampel, Harald; Molinuevo, José Luis; Blennow, Kaj; DeKosky, Steven T; Gauthier, Serge; Selkoe, Dennis; Bateman, Randall; Cappa, Stefano; Crutch, Sebastian; et al. (Lancet Neurol, 2014)
In the past 8 years, both the International Working Group (IWG) and the US National Institute on Aging-Alzheimer's Association have contributed criteria for the diagnosis of Alzheimer's disease (AD) that better define clinical phenotypes and integrate biomarkers into the diagnostic process, covering the full staging of the disease. This Position Paper considers the strengths and limitations of the IWG research diagnostic criteria and proposes advances to improve the diagnostic framework. On the basis of these refinements, the diagnosis of AD can be simplified, requiring the presence of an appropriate clinical AD phenotype (typical or atypical) and a pathophysiological biomarker consistent with the presence of Alzheimer's pathology. We propose that downstream topographical biomarkers of the disease, such as volumetric MRI and fluorodeoxyglucose PET, might better serve in the measurement and monitoring of the course of disease. This paper also elaborates on the specific diagnostic criteria for atypical forms of AD, for mixed AD, and for the preclinical states of AD.
Keywords: Alzheimer Disease; Biomarkers; Humans; International Cooperation; Phenotype; Practice Guidelines as Topic; Societies, Medical

C9orf72 nucleotide repeat structures initiate molecular cascades of disease. - Haeusler, Aaron R; Donnelly, Christopher J; Periz, Goran; Simko, Eric A J; Shaw, Patrick G; Kim, Min-Sik; Maragakis, Nicholas J; Troncoso, Juan C; Pandey, Akhilesh; Sattler, Rita; Rothstein, Jeffrey D; Wang, Jiou (Nature, 2014)
A hexanucleotide repeat expansion (HRE), (GGGGCC)n, in C9orf72 is the most common genetic cause of the neurodegenerative diseases amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD). Here we identify a molecular mechanism by which structural polymorphism of the HRE leads to ALS/FTD pathology and defects. The HRE forms DNA and RNA G-quadruplexes with distinct structures and promotes RNA•DNA hybrids (R-loops). The structural polymorphism causes a repeat-length-dependent accumulation of transcripts aborted in the HRE region. These transcribed repeats bind to ribonucleoproteins in a conformation-dependent manner. Specifically, nucleolin, an essential nucleolar protein, preferentially binds the HRE G-quadruplex, and patient cells show evidence of nucleolar stress. Our results demonstrate that distinct C9orf72 HRE structural polymorphism at both DNA and RNA levels initiates molecular cascades leading to ALS/FTD pathologies, and provide the basis for a mechanistic model for repeat-associated neurodegenerative diseases.
Keywords: Amyotrophic Lateral Sclerosis; B-Lymphocytes; Base Sequence; Cell Nucleolus; DNA; DNA Repeat Expansion; Frontotemporal Dementia; G-Quadruplexes; HEK293 Cells; Humans; Models, Molecular; Neurons; Open Reading Frames; Phosphoproteins; Ribonucleoproteins; RNA; RNA-Binding Proteins; Stress, Physiological; Transcription, Genetic

Plasma phospholipids identify antecedent memory impairment in older adults. - Mapstone, Mark; Cheema, Amrita K; Fiandaca, Massimo S; Zhong, Xiaogang; Mhyre, Timothy R; MacArthur, Linda H; Hall, William J; Fisher, Susan G; Peterson, Derick R; Haley, James M; Nazar, Michael D; Rich, Steven A; et al. (Nat Med, 2014)
Alzheimer's disease causes a progressive dementia that currently affects over 35 million individuals worldwide and is expected to affect 115 million by 2050 (ref. 1). There are no cures or disease-modifying therapies, and this may be due to our inability to detect the disease before it has progressed to produce evident memory loss and functional decline. Biomarkers of preclinical disease will be critical to the development of disease-modifying or even preventative therapies. Unfortunately, current biomarkers for early disease, including cerebrospinal fluid tau and amyloid-β levels, structural and functional magnetic resonance imaging and the recent use of brain amyloid imaging or inflammaging, are limited because they are either invasive, time-consuming or expensive. Blood-based biomarkers may be a more attractive option, but none can currently detect preclinical Alzheimer's disease with the required sensitivity and specificity. Herein, we describe our lipidomic approach to detecting preclinical Alzheimer's disease in a group of cognitively normal older adults. We discovered and validated a set of ten lipids from peripheral blood that predicted phenoconversion to either amnestic mild cognitive impairment or Alzheimer's disease within a 2-3 year timeframe with over 90% accuracy. This biomarker panel, reflecting cell membrane integrity, may be sensitive to early neurodegeneration of preclinical Alzheimer's disease.
Keywords: Aged; Alzheimer Disease; Asparagine; Biomarkers; Carnitine; Cohort Studies; Dipeptides; Female; Humans; Longitudinal Studies; Lysophosphatidylcholines; Malates; Male; Memory Disorders; Metabolome; Mild Cognitive Impairment; Neuropsychological Tests; Phosphatidylcholines; Phosphatidylinositols; Phospholipids; Proline; Prospective Studies; Sensitivity and Specificity; Sphingomyelins; Ursodeoxycholic Acid

REST and stress resistance in ageing and Alzheimer's disease. - Lu, Tao; Aron, Liviu; Zullo, Joseph; Pan, Ying; Kim, Haeyoung; Chen, Yiwen; Yang, Tun-Hsiang; Kim, Hyun-Min; Drake, Derek; Liu, X Shirley; Bennett, David A; Colaiácovo, Monica P; et al. (Nature, 2014)
Human neurons are functional over an entire lifetime, yet the mechanisms that preserve function and protect against neurodegeneration during ageing are unknown. Here we show that induction of the repressor element 1-silencing transcription factor (REST; also known as neuron-restrictive silencer factor, NRSF) is a universal feature of normal ageing in human cortical and hippocampal neurons. REST is lost, however, in mild cognitive impairment and Alzheimer's disease. Chromatin immunoprecipitation with deep sequencing and expression analysis show that REST represses genes that promote cell death and Alzheimer's disease pathology, and induces the expression of stress response genes. Moreover, REST potently protects neurons from oxidative stress and amyloid β-protein toxicity, and conditional deletion of REST in the mouse brain leads to age-related neurodegeneration. A functional orthologue of REST, Caenorhabditis elegans SPR-4, also protects against oxidative stress and amyloid β-protein toxicity. During normal ageing, REST is induced in part by cell non-autonomous Wnt signalling. However, in Alzheimer's disease, frontotemporal dementia and dementia with Lewy bodies, REST is lost from the nucleus and appears in autophagosomes together with pathological misfolded proteins. Finally, REST levels during ageing are closely correlated with cognitive preservation and longevity. Thus, the activation state of REST may distinguish neuroprotection from neurodegeneration in the ageing brain.
Keywords: Aged; Aged, 80 and over; Aging; Alzheimer Disease; Amyloid beta-Peptides; Animals; Autophagy; Brain; Caenorhabditis elegans Proteins; Cell Death; Cell Nucleus; Chromatin Immunoprecipitation; Cognition; DNA-Binding Proteins; Down-Regulation; Frontotemporal Dementia; Gene Expression Regulation; Humans; Lewy Body Disease; Longevity; Mice; Mild Cognitive Impairment; Neurons; Neuroprotective Agents; Oxidative Stress; Phagosomes; Repressor Proteins; Transcription Factors; Up-Regulation; Wnt Signaling Pathway; Young Adult

A three-dimensional human neural cell culture model of Alzheimer's disease. - Choi, Se Hoon; Kim, Young Hye; Hebisch, Matthias; Sliwinski, Christopher; Lee, Seungkyu; D'Avanzo, Carla; Chen, Hechao; Hooli, Basavaraj; Asselin, Caroline; Muffat, Julien; Klee, Justin B; Zhang, Can; et al. (Nature, 2014)
Alzheimer's disease is the most common form of dementia, characterized by two pathological hallmarks: amyloid-β plaques and neurofibrillary tangles. The amyloid hypothesis of Alzheimer's disease posits that the excessive accumulation of amyloid-β peptide leads to neurofibrillary tangles composed of aggregated hyperphosphorylated tau. However, to date, no single disease model has serially linked these two pathological events using human neuronal cells. Mouse models with familial Alzheimer's disease (FAD) mutations exhibit amyloid-β-induced synaptic and memory deficits but they do not fully recapitulate other key pathological events of Alzheimer's disease, including distinct neurofibrillary tangle pathology. Human neurons derived from Alzheimer's disease patients have shown elevated levels of toxic amyloid-β species and phosphorylated tau but did not demonstrate amyloid-β plaques or neurofibrillary tangles. Here we report that FAD mutations in β-amyloid precursor protein and presenilin 1 are able to induce robust extracellular deposition of amyloid-β, including amyloid-β plaques, in a human neural stem-cell-derived three-dimensional (3D) culture system. More importantly, the 3D-differentiated neuronal cells expressing FAD mutations exhibited high levels of detergent-resistant, silver-positive aggregates of phosphorylated tau in the soma and neurites, as well as filamentous tau, as detected by immunoelectron microscopy. Inhibition of amyloid-β generation with β- or γ-secretase inhibitors not only decreased amyloid-β pathology, but also attenuated tauopathy. We also found that glycogen synthase kinase 3 (GSK3) regulated amyloid-β-mediated tau phosphorylation. We have successfully recapitulated amyloid-β and tau pathology in a single 3D human neural cell culture system. Our unique strategy for recapitulating Alzheimer's disease pathology in a 3D neural cell culture model should also serve to facilitate the development of more precise human neural cell models of other neurodegenerative disorders.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Cell Culture Techniques; Cell Differentiation; Drug Evaluation, Preclinical; Extracellular Space; Glycogen Synthase Kinase 3; Humans; Microtubule-Associated Proteins; Models, Biological; Neural Stem Cells; Neurites; Phosphorylation; Presenilin-1; Protein Aggregation, Pathological; Reproducibility of Results; tau Proteins

Two phase 3 trials of bapineuzumab in mild-to-moderate Alzheimer's disease. - Salloway, Stephen; Sperling, Reisa; Fox, Nick C; Blennow, Kaj; Klunk, William; Raskind, Murray; Sabbagh, Marwan; Honig, Lawrence S; Porsteinsson, Anton P; Ferris, Steven; Reichert, Marcel; Ketter, Nzeera; et al. (N Engl J Med, 2014)
BACKGROUND: Bapineuzumab, a humanized anti-amyloid-beta monoclonal antibody, is in clinical development for the treatment of Alzheimer's disease. METHODS: We conducted two double-blind, randomized, placebo-controlled, phase 3 trials involving patients with mild-to-moderate Alzheimer's disease--one involving 1121 carriers of the apolipoprotein E (APOE) ε4 allele and the other involving 1331 noncarriers. Bapineuzumab or placebo, with doses varying by study, was administered by intravenous infusion every 13 weeks for 78 weeks. The primary outcome measures were scores on the 11-item cognitive subscale of the Alzheimer's Disease Assessment Scale (ADAS-cog11, with scores ranging from 0 to 70 and higher scores indicating greater impairment) and the Disability Assessment for Dementia (DAD, with scores ranging from 0 to 100 and higher scores indicating less impairment). A total of 1090 carriers and 1114 noncarriers were included in the efficacy analysis. Secondary outcome measures included findings on positron-emission tomographic amyloid imaging with the use of Pittsburgh compound B (PIB-PET) and cerebrospinal fluid phosphorylated tau (phospho-tau) concentrations. RESULTS: There were no significant between-group differences in the primary outcomes. At week 78, the between-group differences in the change from baseline in the ADAS-cog11 and DAD scores (bapineuzumab group minus placebo group) were -0.2 (P=0.80) and -1.2 (P=0.34), respectively, in the carrier study; the corresponding differences in the noncarrier study were -0.3 (P=0.64) and 2.8 (P=0.07) with the 0.5-mg-per-kilogram dose of bapineuzumab and 0.4 (P=0.62) and 0.9 (P=0.55) with the 1.0-mg-per-kilogram dose. The major safety finding was amyloid-related imaging abnormalities with edema among patients receiving bapineuzumab, which increased with bapineuzumab dose and APOE ε4 allele number and which led to discontinuation of the 2.0-mg-per-kilogram dose. Between-group differences were observed with respect to PIB-PET and cerebrospinal fluid phospho-tau concentrations in APOE ε4 allele carriers but not in noncarriers. CONCLUSIONS: Bapineuzumab did not improve clinical outcomes in patients with Alzheimer's disease, despite treatment differences in biomarkers observed in APOE ε4 carriers. (Funded by Janssen Alzheimer Immunotherapy and Pfizer; Bapineuzumab 301 and 302 ClinicalTrials.gov numbers, NCT00575055 and NCT00574132, and EudraCT number, 2009-012748-17.).
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Antibodies, Monoclonal, Humanized; Apolipoproteins E; Biomarkers; Brain; Cognition; Double-Blind Method; Edema; Female; Humans; Intention to Treat Analysis; Male; Middle Aged; Neuropsychological Tests; Phosphorylation; Positron-Emission Tomography; Severity of Illness Index; tau Proteins; Treatment Failure

Young blood reverses age-related impairments in cognitive function and synaptic plasticity in mice. - Villeda, Saul A; Plambeck, Kristopher E; Middeldorp, Jinte; Castellano, Joseph M; Mosher, Kira I; Luo, Jian; Smith, Lucas K; Bieri, Gregor; Lin, Karin; Berdnik, Daniela; Wabl, Rafael; Udeochu, Joe; et al. (Nat Med, 2014)
As human lifespan increases, a greater fraction of the population is suffering from age-related cognitive impairments, making it important to elucidate a means to combat the effects of aging. Here we report that exposure of an aged animal to young blood can counteract and reverse pre-existing effects of brain aging at the molecular, structural, functional and cognitive level. Genome-wide microarray analysis of heterochronic parabionts--in which circulatory systems of young and aged animals are connected--identified synaptic plasticity-related transcriptional changes in the hippocampus of aged mice. Dendritic spine density of mature neurons increased and synaptic plasticity improved in the hippocampus of aged heterochronic parabionts. At the cognitive level, systemic administration of young blood plasma into aged mice improved age-related cognitive impairments in both contextual fear conditioning and spatial learning and memory. Structural and cognitive enhancements elicited by exposure to young blood are mediated, in part, by activation of the cyclic AMP response element binding protein (Creb) in the aged hippocampus. Our data indicate that exposure of aged mice to young blood late in life is capable of rejuvenating synaptic plasticity and improving cognitive function.
Keywords: Age Factors; Aging; Animals; Blood Transfusion; Blotting, Western; Cell Line; Cognition Disorders; Cyclic AMP Response Element-Binding Protein; DNA Primers; Hippocampus; Immunohistochemistry; Mice; Mice, Inbred C57BL; Microarray Analysis; Neuronal Plasticity; Parabiosis; Polymerase Chain Reaction

Alzheimer's disease risk gene CD33 inhibits microglial uptake of amyloid beta. - Griciuc, Ana; Serrano-Pozo, Alberto; Parrado, Antonio R; Lesinski, Andrea N; Asselin, Caroline N; Mullin, Kristina; Hooli, Basavaraj; Choi, Se Hoon; Hyman, Bradley T; Tanzi, Rudolph E (Neuron, 2013)
The transmembrane protein CD33 is a sialic acid-binding immunoglobulin-like lectin that regulates innate immunity but has no known functions in the brain. We have previously shown that the CD33 gene is a risk factor for Alzheimer's disease (AD). Here, we observed increased expression of CD33 in microglial cells in AD brain. The minor allele of the CD33 SNP rs3865444, which confers protection against AD, was associated with reductions in both CD33 expression and insoluble amyloid beta 42 (Aβ42) levels in AD brain. Furthermore, the numbers of CD33-immunoreactive microglia were positively correlated with insoluble Aβ42 levels and plaque burden in AD brain. CD33 inhibited uptake and clearance of Aβ42 in microglial cell cultures. Finally, brain levels of insoluble Aβ42 as well as amyloid plaque burden were markedly reduced in APP(Swe)/PS1(ΔE9)/CD33(-/-) mice. Therefore, CD33 inactivation mitigates Aβ pathology and CD33 inhibition could represent a novel therapy for AD.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; Case-Control Studies; Disease Models, Animal; Genetic Predisposition to Disease; Humans; Matched-Pair Analysis; Mice; Mice, Inbred C57BL; Mice, Knockout; Mice, Transgenic; Microglia; Polymorphism, Single Nucleotide; Reference Values; RNA, Messenger; Sialic Acid Binding Ig-like Lectin 3

Anti-amyloid β autoantibodies in cerebral amyloid angiopathy-related inflammation: implications for amyloid-modifying therapies. - Piazza, Fabrizio; Greenberg, Steven M; Savoiardo, Mario; Gardinetti, Margherita; Chiapparini, Luisa; Raicher, Irina; Nitrini, Ricardo; Sakaguchi, Hideya; Brioschi, Monica; Billo, Giuseppe; Colombo, Antonio; Lanzani, Francesca; et al. (Ann Neurol, 2013)
OBJECTIVE: Cerebral amyloid angiopathy-related inflammation (CAA-ri) is characterized by vasogenic edema and multiple cortical/subcortical microbleeds, sharing several aspects with the recently defined amyloid-related imaging abnormalities (ARIA) reported in Alzheimer's disease (AD) passive immunization therapies. Herein, we investigated the role of anti-amyloid β (Aβ) autoantibodies in the acute and remission phases of CAA-ri. METHODS: We used a novel ultrasensitive technique on patients from a retrospective multicenter case-control study, and evaluated the anti-Aβ autoantibody concentration in the cerebrospinal fluid (CSF) of 10 CAA-ri, 8 CAA, 14 multiple sclerosis, and 25 control subjects. Levels of soluble Aβ40, Aβ42, tau, P-181 tau, and APOE genotype were also investigated. RESULTS: During the acute phase of CAA-ri, anti-Aβ autoantibodies were specifically increased and directly correlated with Aβ mobilization, together with augmented tau and P-181 tau. Following clinical and radiological remission, autoantibodies progressively returned to control levels, and both soluble Aβ and axonal degeneration markers decreased in parallel. INTERPRETATION: Our data support the hypothesis that the pathogenesis of CAA-ri may be mediated by a selective autoimmune reaction against cerebrovascular Aβ, directly related to autoantibody concentration and soluble Aβ. The CSF dosage of anti-Aβ autoantibodies with the technique here described can thus be proposed as a valid alternative tool for the diagnosis of CAA-ri. Moreover, given the similarities between ARIA developing spontaneously and those observed during immunization trials, anti-Aβ autoantibodies can be considered as novel potential biomarkers in future amyloid-modifying therapies for the treatment of AD and CAA.
Keywords: Adult; Aged; Amyloid beta-Peptides; Apolipoproteins E; Autoantibodies; Brain; Case-Control Studies; Cerebral Amyloid Angiopathy; Female; Humans; Inflammation; Male; Middle Aged; Peptide Fragments; Phosphorylation; Retrospective Studies; Steroids; tau Proteins

Meta-analysis of 74,046 individuals identifies 11 new susceptibility loci for Alzheimer's disease. - Lambert, J C; Ibrahim-Verbaas, C A; Harold, D; Naj, A C; Sims, R; Bellenguez, C; DeStafano, A L; Bis, J C; Beecham, G W; Grenier-Boley, B; Russo, G; Thorton-Wells, T A; et al. (Nat Genet, 2013)
Eleven susceptibility loci for late-onset Alzheimer's disease (LOAD) were identified by previous studies; however, a large portion of the genetic risk for this disease remains unexplained. We conducted a large, two-stage meta-analysis of genome-wide association studies (GWAS) in individuals of European ancestry. In stage 1, we used genotyped and imputed data (7,055,881 SNPs) to perform meta-analysis on 4 previously published GWAS data sets consisting of 17,008 Alzheimer's disease cases and 37,154 controls. In stage 2, 11,632 SNPs were genotyped and tested for association in an independent set of 8,572 Alzheimer's disease cases and 11,312 controls. In addition to the APOE locus (encoding apolipoprotein E), 19 loci reached genome-wide significance (P < 5 × 10(-8)) in the combined stage 1 and stage 2 analysis, of which 11 are newly associated with Alzheimer's disease.
Keywords: Age of Onset; Aged; Aged, 80 and over; Alzheimer Disease; Case-Control Studies; Cohort Studies; Female; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide

Modeling Alzheimer's disease with iPSCs reveals stress phenotypes associated with intracellular Aβ and differential drug responsiveness. - Kondo, Takayuki; Asai, Masashi; Tsukita, Kayoko; Kutoku, Yumiko; Ohsawa, Yutaka; Sunada, Yoshihide; Imamura, Keiko; Egawa, Naohiro; Yahata, Naoki; Okita, Keisuke; Takahashi, Kazutoshi; Asaka, Isao; et al. (Cell Stem Cell, 2013)
Oligomeric forms of amyloid-β peptide (Aβ) are thought to play a pivotal role in the pathogenesis of Alzheimer's disease (AD), but the mechanism involved is still unclear. Here, we generated induced pluripotent stem cells (iPSCs) from familial and sporadic AD patients and differentiated them into neural cells. Aβ oligomers accumulated in iPSC-derived neurons and astrocytes in cells from patients with a familial amyloid precursor protein (APP)-E693Δ mutation and sporadic AD, leading to endoplasmic reticulum (ER) and oxidative stress. The accumulated Aβ oligomers were not proteolytically resistant, and docosahexaenoic acid (DHA) treatment alleviated the stress responses in the AD neural cells. Differential manifestation of ER stress and DHA responsiveness may help explain variable clinical results obtained with the use of DHA treatment and suggests that DHA may in fact be effective for a subset of patients. It also illustrates how patient-specific iPSCs can be useful for analyzing AD pathogenesis and evaluating drugs.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Cell Differentiation; Cerebral Cortex; Docosahexaenoic Acids; Humans; Induced Pluripotent Stem Cells; Intracellular Space; Models, Biological; Mutant Proteins; Neurons; Oxidative Stress; Phenotype; Protein Structure, Quaternary

Cerebrospinal fluid levels of β-amyloid 1-42, but not of tau, are fully changed already 5 to 10 years before the onset of Alzheimer dementia. - Buchhave, Peder; Minthon, Lennart; Zetterberg, Henrik; Wallin, Asa K; Blennow, Kaj; Hansson, Oskar (Arch Gen Psychiatry, 2012)
CONTEXT: Early detection of prodromal Alzheimer disease (AD) is important because new disease-modifying therapies are most likely to be effective when initiated during the early stages of disease. OBJECTIVES: To assess the ability of the cerebrospinal fluid (CSF) biomarkers total tau (T-tau), phosphorylated tau (P-tau), and β-amyloid 1-42 (Aβ42) to predict future development of AD dementia within 9.2 years in patients with mild cognitive impairment (MCI) and to compare CSF biomarkers between early and late converters to AD. DESIGN: A clinical study with a median follow-up of 9.2 years (range, 4.1-11.8 years). SETTING: Memory disorder clinic. Patients A total of 137 patients with MCI who underwent lumbar puncture at baseline. MAIN OUTCOME MEASURE Conversion to AD dementia. RESULTS: During follow-up, 72 patients (53.7%) developed AD and 21 (15.7%) progressed to other forms of dementia. At baseline, CSF Aβ42 levels were reduced and T-tau and P-tau levels were elevated in patients who converted to AD during follow-up compared with nonconverters (P < .001). Baseline CSF Aβ42 levels were equally reduced in patients with MCI who converted to AD within 0 to 5 years (early converters) compared with those who converted between 5 and 10 years (late converters). However, CSF T-tau and P-tau levels were significantly higher in early converters vs late converters. A baseline Aβ42:P-tau ratio predicted the development of AD within 9.2 years with a sensitivity of 88%, specificity of 90%, positive predictive value of 91%, and negative predictive value of 86%. CONCLUSIONS: Approximately 90% of patients with MCI and pathologic CSF biomarker levels at baseline develop AD within 9 to 10 years. Levels of Aβ42 are already fully decreased at least 5 to 10 years before conversion to AD dementia, whereas T-tau and P-tau seem to be later markers. These results provide direct support in humans for the hypothesis that altered Aβ metabolism precedes tau-related pathology and neuronal degeneration.
Keywords: Aged; Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Female; Follow-Up Studies; Humans; Male; Mild Cognitive Impairment; Peptide Fragments; Predictive Value of Tests; tau Proteins; Time Factors

Demonstrated brain insulin resistance in Alzheimer's disease patients is associated with IGF-1 resistance, IRS-1 dysregulation, and cognitive decline. - Talbot, Konrad; Wang, Hoau-Yan; Kazi, Hala; Han, Li-Ying; Bakshi, Kalindi P; Stucky, Andres; Fuino, Robert L; Kawaguchi, Krista R; Samoyedny, Andrew J; Wilson, Robert S; Arvanitakis, Zoe; Schneider, Julie A; et al. (J Clin Invest, 2012)
While a potential causal factor in Alzheimer's disease (AD), brain insulin resistance has not been demonstrated directly in that disorder. We provide such a demonstration here by showing that the hippocampal formation (HF) and, to a lesser degree, the cerebellar cortex in AD cases without diabetes exhibit markedly reduced responses to insulin signaling in the IR→IRS-1→PI3K signaling pathway with greatly reduced responses to IGF-1 in the IGF-1R→IRS-2→PI3K signaling pathway. Reduced insulin responses were maximal at the level of IRS-1 and were consistently associated with basal elevations in IRS-1 phosphorylated at serine 616 (IRS-1 pS⁶¹⁶) and IRS-1 pS⁶³⁶/⁶³⁹. In the HF, these candidate biomarkers of brain insulin resistance increased commonly and progressively from normal cases to mild cognitively impaired cases to AD cases regardless of diabetes or APOE ε4 status. Levels of IRS-1 pS⁶¹⁶ and IRS-1 pS⁶³⁶/⁶³⁹ and their activated kinases correlated positively with those of oligomeric Aβ plaques and were negatively associated with episodic and working memory, even after adjusting for Aβ plaques, neurofibrillary tangles, and APOE ε4. Brain insulin resistance thus appears to be an early and common feature of AD, a phenomenon accompanied by IGF-1 resistance and closely associated with IRS-1 dysfunction potentially triggered by Aβ oligomers and yet promoting cognitive decline independent of classic AD pathology.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Apolipoprotein E4; Brain; Cerebellar Cortex; Cognition Disorders; Diabetes Complications; Drug Resistance; Female; Glucose; Hippocampus; Humans; Insulin; Insulin Receptor Substrate Proteins; Insulin Resistance; Insulin-Like Growth Factor I; Male; Middle Aged; Phosphorylation; Phosphoserine; Protein Processing, Post-Translational; Recombinant Proteins; Signal Transduction

An epigenetic blockade of cognitive functions in the neurodegenerating brain. - Gräff, Johannes; Rei, Damien; Guan, Ji-Song; Wang, Wen-Yuan; Seo, Jinsoo; Hennig, Krista M; Nieland, Thomas J F; Fass, Daniel M; Kao, Patricia F; Kahn, Martin; Su, Susan C; Samiei, Alireza; et al. (Nature, 2012)
Cognitive decline is a debilitating feature of most neurodegenerative diseases of the central nervous system, including Alzheimer's disease. The causes leading to such impairment are only poorly understood and effective treatments are slow to emerge. Here we show that cognitive capacities in the neurodegenerating brain are constrained by an epigenetic blockade of gene transcription that is potentially reversible. This blockade is mediated by histone deacetylase 2, which is increased by Alzheimer's-disease-related neurotoxic insults in vitro, in two mouse models of neurodegeneration and in patients with Alzheimer's disease. Histone deacetylase 2 associates with and reduces the histone acetylation of genes important for learning and memory, which show a concomitant decrease in expression. Importantly, reversing the build-up of histone deacetylase 2 by short-hairpin-RNA-mediated knockdown unlocks the repression of these genes, reinstates structural and synaptic plasticity, and abolishes neurodegeneration-associated memory impairments. These findings advocate for the development of selective inhibitors of histone deacetylase 2 and suggest that cognitive capacities following neurodegeneration are not entirely lost, but merely impaired by this epigenetic blockade.
Keywords: Acetylation; Alzheimer Disease; Amyloid beta-Peptides; Animals; Brain; Disease Models, Animal; Epigenesis, Genetic; Gene Expression Regulation; Gene Knockdown Techniques; Hippocampus; Histone Deacetylase 2; Histones; Humans; Hydrogen Peroxide; Memory Disorders; Mice; Neurodegenerative Diseases; Neuronal Plasticity; Peptide Fragments; Phosphorylation; Promoter Regions, Genetic; Receptors, Glucocorticoid; RNA Polymerase II

Exercise Engagement as a Moderator of the Effects of APOE Genotype on Amyloid Deposition. - Head, Denise; Bugg, Julie M; Goate, Alison M; Fagan, Anne M; Mintun, Mark A; Benzinger, Tammie; Holtzman, David M; Morris, John C (Arch Neurol, 2012)
OBJECTIVE: APOE ε4 status has been associated with greater cortical amyloid deposition, whereas exercise has been associated with less in cognitively normal adults. The primary objective here was to examine whether physical exercise moderates the association between APOE genotype and amyloid deposition in cognitively normal adults. DESIGN: APOE genotyping data and answers to a questionnaire on physical exercise engagement over the last decade were obtained in conjunction with cerebrospinal fluid (CSF) samples and amyloid imaging with carbon 11-labeled Pittsburgh Compound B ([(11)C]PiB) positron emission tomography. Participants were classified as either low or high exercisers based on exercise guidelines of the American Heart Association. SETTING: Knight Alzheimer's Disease Research Center at Washington University, St Louis, Missouri. PARTICIPANTS: A total of 201 cognitively normal adults (135 of whom were women) aged 45 to 88 years were recruited from the Knight Alzheimer's Disease Research Center. Samples of CSF were collected from 165 participants. Amyloid imaging was performed for 163 participants. RESULTS: APOE ε4 carriers evidenced higher [(11)C]PiB binding (P<.001) and lower CSF Aβ42 levels (P<.001) than did noncarriers. Our previous findings of higher [(11)C]PiB binding (P=.005) and lower CSF Aβ42 levels (P=.009) in more sedentary individuals were replicated. Most importantly, we observed a novel interaction between APOE status and exercise engagement for [(11)C]PiB binding (P=.008) such that a more sedentary lifestyle was significantly associated with higher [(11)C]PiB binding for ε4 carriers (P=.013) but not for noncarriers (P=.20). All findings remained significant after controlling for age; sex; educational level; body mass index; the presence or history of hypertension, diabetes mellitus, heart problems, or depression; and the interval between assessments. CONCLUSION: Collectively, these results suggest that cognitively normal sedentary APOE ε4-positive individuals may be at augmented risk for cerebral amyloid deposition.
Keywords: Aged; Aged, 80 and over; Amyloid beta-Peptides; Aniline Compounds; Apolipoprotein E4; Brain; Cognition; Cohort Studies; Exercise; Female; Genetic Association Studies; Genotype; Humans; Male; Middle Aged; Neuropsychological Tests; Peptide Fragments; Positron-Emission Tomography; Regression Analysis; Surveys and Questionnaires; Thiazoles

A mutation in APP protects against Alzheimer's disease and age-related cognitive decline. - Jonsson, Thorlakur; Atwal, Jasvinder K; Steinberg, Stacy; Snaedal, Jon; Jonsson, Palmi V; Bjornsson, Sigurbjorn; Stefansson, Hreinn; Sulem, Patrick; Gudbjartsson, Daniel; Maloney, Janice; Hoyte, Kwame; Gustafson, Amy; et al. (Nature, 2012)
The prevalence of dementia in the Western world in people over the age of 60 has been estimated to be greater than 5%, about two-thirds of which are due to Alzheimer's disease. The age-specific prevalence of Alzheimer's disease nearly doubles every 5 years after age 65, leading to a prevalence of greater than 25% in those over the age of 90 (ref. 3). Here, to search for low-frequency variants in the amyloid-β precursor protein (APP) gene with a significant effect on the risk of Alzheimer's disease, we studied coding variants in APP in a set of whole-genome sequence data from 1,795 Icelanders. We found a coding mutation (A673T) in the APP gene that protects against Alzheimer's disease and cognitive decline in the elderly without Alzheimer's disease. This substitution is adjacent to the aspartyl protease β-site in APP, and results in an approximately 40% reduction in the formation of amyloidogenic peptides in vitro. The strong protective effect of the A673T substitution against Alzheimer's disease provides proof of principle for the hypothesis that reducing the β-cleavage of APP may protect against the disease. Furthermore, as the A673T allele also protects against cognitive decline in the elderly without Alzheimer's disease, the two may be mediated through the same or similar mechanisms.
Keywords: Aging; Alleles; Alzheimer Disease; Amyloid beta-Protein Precursor; Amyloid Precursor Protein Secretases; Aspartic Acid Endopeptidases; Cognition; Cognition Disorders; Genetic Predisposition to Disease; HEK293 Cells; Humans; Mutation; Plaque, Amyloid

National Institute on Aging-Alzheimer's Association guidelines for the neuropathologic assessment of Alzheimer's disease. - Hyman, Bradley T; Phelps, Creighton H; Beach, Thomas G; Bigio, Eileen H; Cairns, Nigel J; Carrillo, Maria C; Dickson, Dennis W; Duyckaerts, Charles; Frosch, Matthew P; Masliah, Eliezer; Mirra, Suzanne S; Nelson, Peter T; et al. (Alzheimers Dement, 2012)
A consensus panel from the United States and Europe was convened recently to update and revise the 1997 consensus guidelines for the neuropathologic evaluation of Alzheimer's disease (AD) and other diseases of brain that are common in the elderly. The new guidelines recognize the pre-clinical stage of AD, enhance the assessment of AD to include amyloid accumulation as well as neurofibrillary change and neuritic plaques, establish protocols for the neuropathologic assessment of Lewy body disease, vascular brain injury, hippocampal sclerosis, and TDP-43 inclusions, and recommend standard approaches for the workup of cases and their clinico-pathologic correlation.
Keywords: Alzheimer Disease; Brain; Consensus Development Conferences, NIH as Topic; Humans; National Institute on Aging (U.S.); Practice Guidelines as Topic; Societies, Medical; United States

Neuroinflammation, hyperphosphorylated tau, diffuse amyloid plaques, and down-regulation of the cellular prion protein in air pollution exposed children and young adults. - Calderón-Garcidueñas, Lilian; Kavanaugh, Michael; Block, Michelle; D'Angiulli, Amedeo; Delgado-Chávez, Ricardo; Torres-Jardón, Ricardo; González-Maciel, Angelica; Reynoso-Robles, Rafael; Osnaya, Norma; Villarreal-Calderon, Rodolfo; Guo, Ruixin; Hua, Zhaowei; et al. (J Alzheimers Dis, 2012)
Air pollution exposures have been linked to neuroinflammation and neuropathology. Autopsy samples of the frontal cortex from control (n = 8) and pollution-exposed (n = 35) children and young adults were analyzed by RT-PCR (n = 43) and microarray analysis (n = 12) for gene expression changes in oxidative stress, DNA damage signaling, NFκB signaling, inflammation, and neurodegeneration pathways. The effect of apolipoprotein E (APOE) genotype on the presence of protein aggregates associated with Alzheimer's disease (AD) pathology was also explored. Exposed urbanites displayed differential (>2-fold) regulation of 134 genes. Forty percent exhibited tau hyperphosphorylation with pre-tangle material and 51% had amyloid-β (Aβ) diffuse plaques compared with 0% in controls. APOE4 carriers had greater hyperphosphorylated tau and diffuse Aβ plaques versus E3 carriers (Q = 7.82, p = 0.005). Upregulated gene network clusters included IL1, NFκB, TNF, IFN, and TLRs. A 15-fold frontal down-regulation of the prion-related protein (PrP(C)) was seen in highly exposed subjects. The down-regulation of the PrP(C) is critical given its important roles for neuroprotection, neurodegeneration, and mood disorder states. Elevation of indices of neuroinflammation and oxidative stress, down-regulation of the PrP(C) and AD-associated pathology are present in young megacity residents. The inducible regulation of gene expression suggests they are evolving different mechanisms in an attempt to cope with the constant state of inflammation and oxidative stress related to their environmental exposures. Together, these data support a role for air pollution in CNS damage and its impact upon the developing brain and the potential etiology of AD and mood disorders.
Keywords: Adolescent; Adult; Age Factors; Air Pollution; Child; Child, Preschool; Cohort Studies; Down-Regulation; Encephalitis; Female; Frontal Lobe; Gene Regulatory Networks; Humans; Infant; Male; Mexico; Phosphorylation; Plaque, Amyloid; Prions; tau Proteins; Young Adult

An operational approach to National Institute on Aging-Alzheimer's Association criteria for preclinical Alzheimer disease. - Jack, Clifford R; Knopman, David S; Weigand, Stephen D; Wiste, Heather J; Vemuri, Prashanthi; Lowe, Val; Kantarci, Kejal; Gunter, Jeffrey L; Senjem, Matthew L; Ivnik, Robert J; Roberts, Rosebud O; Rocca, Walter A; et al. (Ann Neurol, 2012)
OBJECTIVE: A workgroup commissioned by the Alzheimer's Association (AA) and the National Institute on Aging (NIA) recently published research criteria for preclinical Alzheimer disease (AD). We performed a preliminary assessment of these guidelines. METHODS: We employed Pittsburgh compound B positron emission tomography (PET) imaging as our biomarker of cerebral amyloidosis, and (18) fluorodeoxyglucose PET imaging and hippocampal volume as biomarkers of neurodegeneration. A group of 42 clinically diagnosed AD subjects was used to create imaging biomarker cutpoints. A group of 450 cognitively normal (CN) subjects from a population-based sample was used to develop cognitive cutpoints and to assess population frequencies of the different preclinical AD stages using different cutpoint criteria. RESULTS: The new criteria subdivide the preclinical phase of AD into stages 1 to 3. To classify our CN subjects, 2 additional categories were needed. Stage 0 denotes subjects with normal AD biomarkers and no evidence of subtle cognitive impairment. Suspected non-AD pathophysiology (SNAP) denotes subjects with normal amyloid PET imaging, but abnormal neurodegeneration biomarker studies. At fixed cutpoints corresponding to 90% sensitivity for diagnosing AD and the 10th percentile of CN cognitive scores, 43% of our sample was classified as stage 0, 16% stage 1, 12 % stage 2, 3% stage 3, and 23% SNAP. INTERPRETATION: This cross-sectional evaluation of the NIA-AA criteria for preclinical AD indicates that the 1-3 staging criteria coupled with stage 0 and SNAP categories classify 97% of CN subjects from a population-based sample, leaving only 3% unclassified. Future longitudinal validation of the criteria will be important.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Aniline Compounds; Biomarkers; Brain; Cognition Disorders; Disease Progression; Female; Fluorodeoxyglucose F18; Humans; Longitudinal Studies; Male; Mental Status Schedule; National Institute on Aging (U.S.); Neuropsychological Tests; Positron-Emission Tomography; Thiazoles; United States

Reduction of hippocampal hyperactivity improves cognition in amnestic mild cognitive impairment. - Bakker, Arnold; Krauss, Gregory L; Albert, Marilyn S; Speck, Caroline L; Jones, Lauren R; Stark, Craig E; Yassa, Michael A; Bassett, Susan S; Shelton, Amy L; Gallagher, Michela (Neuron, 2012)
Elevated hippocampal activation is observed in conditions that confer risk for Alzheimer's disease, including amnestic mild cognitive impairment (aMCI). Studies in relevant animal models have indicated that overactivity in selective hippocampal circuits contributes to cognitive impairment. Here, we tested the effect of reducing hippocampal activation in aMCI. Under placebo treatment, hippocampal activation in the dentate gyrus/CA3 was elevated in aMCI patients compared to a healthy control group. By using a low dose of the antiepileptic levetiracetam hippocampal activation in aMCI was reduced to a level that did not differ from the control group. Compared to aMCI memory performance under placebo, performance in the scanning task was significantly improved under drug treatment. Contrary to the view that greater hippocampal activation might serve a beneficial function, these results support the view that increased hippocampal activation in aMCI is a dysfunctional condition and that targeting excess hippocampal activity has therapeutic potential.
Keywords: Aged; Aged, 80 and over; Amnesia; Brain Mapping; Case-Control Studies; Choice Behavior; Double-Blind Method; Female; Hippocampus; Humans; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Male; Middle Aged; Mild Cognitive Impairment; Neuropsychological Tests; Nootropic Agents; Oxygen; Photic Stimulation; Piracetam; Statistics as Topic

Caspase signalling controls microglia activation and neurotoxicity. - Burguillos, Miguel A; Deierborg, Tomas; Kavanagh, Edel; Persson, Annette; Hajji, Nabil; Garcia-Quintanilla, Albert; Cano, Josefina; Brundin, Patrik; Englund, Elisabet; Venero, Jose L; Joseph, Bertrand (Nature, 2011)
Activation of microglia and inflammation-mediated neurotoxicity are suggested to play a decisive role in the pathogenesis of several neurodegenerative disorders. Activated microglia release pro-inflammatory factors that may be neurotoxic. Here we show that the orderly activation of caspase-8 and caspase-3/7, known executioners of apoptotic cell death, regulate microglia activation through a protein kinase C (PKC)-δ-dependent pathway. We find that stimulation of microglia with various inflammogens activates caspase-8 and caspase-3/7 in microglia without triggering cell death in vitro and in vivo. Knockdown or chemical inhibition of each of these caspases hindered microglia activation and consequently reduced neurotoxicity. We observe that these caspases are activated in microglia in the ventral mesencephalon of Parkinson's disease (PD) and the frontal cortex of individuals with Alzheimer's disease (AD). Taken together, we show that caspase-8 and caspase-3/7 are involved in regulating microglia activation. We conclude that inhibition of these caspases could be neuroprotective by targeting the microglia rather than the neurons themselves.
Keywords: Alzheimer Disease; Animals; Caspase 3; Caspase 7; Caspase 8; Caspase Inhibitors; Caspases; Cell Death; Cells, Cultured; Dopamine; Enzyme Activation; Frontal Lobe; Gene Knockdown Techniques; Humans; Lipopolysaccharides; Mice; Microglia; Neostriatum; Neurotoxicity Syndromes; Parkinson Disease; Protein Kinase C-delta; Rats; Signal Transduction; Substantia Nigra; Toll-Like Receptor 4

The diagnosis of dementia due to Alzheimer's disease: recommendations from the National Institute on Aging-Alzheimer's Association workgroups on diagnostic guidelines for Alzheimer's disease. - McKhann, Guy M; Knopman, David S; Chertkow, Howard; Hyman, Bradley T; Jack, Clifford R; Kawas, Claudia H; Klunk, William E; Koroshetz, Walter J; Manly, Jennifer J; Mayeux, Richard; Mohs, Richard C; Morris, John C; et al. (Alzheimers Dement, 2011)
The National Institute on Aging and the Alzheimer's Association charged a workgroup with the task of revising the 1984 criteria for Alzheimer's disease (AD) dementia. The workgroup sought to ensure that the revised criteria would be flexible enough to be used by both general healthcare providers without access to neuropsychological testing, advanced imaging, and cerebrospinal fluid measures, and specialized investigators involved in research or in clinical trial studies who would have these tools available. We present criteria for all-cause dementia and for AD dementia. We retained the general framework of probable AD dementia from the 1984 criteria. On the basis of the past 27 years of experience, we made several changes in the clinical criteria for the diagnosis. We also retained the term possible AD dementia, but redefined it in a manner more focused than before. Biomarker evidence was also integrated into the diagnostic formulations for probable and possible AD dementia for use in research settings. The core clinical criteria for AD dementia will continue to be the cornerstone of the diagnosis in clinical practice, but biomarker evidence is expected to enhance the pathophysiological specificity of the diagnosis of AD dementia. Much work lies ahead for validating the biomarker diagnosis of AD dementia.
Keywords: Alzheimer Disease; Biomarkers; Diagnosis, Differential; Diagnostic Imaging; Disease Progression; Humans; National Institute on Aging (U.S.); Practice Guidelines as Topic; Societies, Medical; United States

The diagnosis of mild cognitive impairment due to Alzheimer's disease: recommendations from the National Institute on Aging-Alzheimer's Association workgroups on diagnostic guidelines for Alzheimer's disease. - Albert, Marilyn S; DeKosky, Steven T; Dickson, Dennis; Dubois, Bruno; Feldman, Howard H; Fox, Nick C; Gamst, Anthony; Holtzman, David M; Jagust, William J; Petersen, Ronald C; Snyder, Peter J; Carrillo, Maria C; et al. (Alzheimers Dement, 2011)
The National Institute on Aging and the Alzheimer's Association charged a workgroup with the task of developing criteria for the symptomatic predementia phase of Alzheimer's disease (AD), referred to in this article as mild cognitive impairment due to AD. The workgroup developed the following two sets of criteria: (1) core clinical criteria that could be used by healthcare providers without access to advanced imaging techniques or cerebrospinal fluid analysis, and (2) research criteria that could be used in clinical research settings, including clinical trials. The second set of criteria incorporate the use of biomarkers based on imaging and cerebrospinal fluid measures. The final set of criteria for mild cognitive impairment due to AD has four levels of certainty, depending on the presence and nature of the biomarker findings. Considerable work is needed to validate the criteria that use biomarkers and to standardize biomarker analysis for use in community settings.
Keywords: Alzheimer Disease; Biomarkers; Cognition Disorders; Diagnosis, Differential; Diagnostic Imaging; Humans; National Institute on Aging (U.S.); Practice Guidelines as Topic; Societies, Medical; United States

Directed conversion of Alzheimer's disease patient skin fibroblasts into functional neurons. - Qiang, Liang; Fujita, Ryousuke; Yamashita, Toru; Angulo, Sergio; Rhinn, Herve; Rhee, David; Doege, Claudia; Chau, Lily; Aubry, Laetitia; Vanti, William B; Moreno, Herman; Abeliovich, Asa (Cell, 2011)
Directed conversion of mature human cells, as from fibroblasts to neurons, is of potential clinical utility for neurological disease modeling as well as cell therapeutics. Here, we describe the efficient generation of human-induced neuronal (hiN) cells from adult skin fibroblasts of unaffected individuals and Alzheimer's patients, using virally transduced transcription regulators and extrinsic support factors. hiN cells from unaffected individuals display morphological, electrophysiological, and gene expression profiles that typify glutamatergic forebrain neurons and are competent to integrate functionally into the rodent CNS. hiN cells from familial Alzheimer disease (FAD) patients with presenilin-1 or -2 mutations exhibit altered processing and localization of amyloid precursor protein (APP) and increased production of Aβ, relative to the source patient fibroblasts or hiN cells from unaffected individuals. Together, our findings demonstrate directed conversion of human fibroblasts to a neuronal phenotype and reveal cell type-selective pathology in hiN cells derived from FAD patients.
Keywords: Alzheimer Disease; Amyloid beta-Protein Precursor; Cell Transdifferentiation; Cells, Cultured; Fibroblasts; Humans; Neurons; Presenilin-1; Presenilin-2; Regenerative Medicine; Skin

Human apoE isoforms differentially regulate brain amyloid-β peptide clearance. - Castellano, Joseph M; Kim, Jungsu; Stewart, Floy R; Jiang, Hong; DeMattos, Ronald B; Patterson, Bruce W; Fagan, Anne M; Morris, John C; Mawuenyega, Kwasi G; Cruchaga, Carlos; Goate, Alison M; Bales, Kelly R; et al. (Sci Transl Med, 2011)
The apolipoprotein E (APOE) ε4 allele is the strongest genetic risk factor for late-onset, sporadic Alzheimer's disease (AD). The APOE ε4 allele markedly increases AD risk and decreases age of onset, likely through its strong effect on the accumulation of amyloid-β (Aβ) peptide. In contrast, the APOE ε2 allele appears to decrease AD risk. Most rare, early-onset forms of familial AD are caused by autosomal dominant mutations that often lead to overproduction of Aβ(42) peptide. However, the mechanism by which APOE alleles differentially modulate Aβ accumulation in sporadic, late-onset AD is less clear. In a cohort of cognitively normal individuals, we report that reliable molecular and neuroimaging biomarkers of cerebral Aβ deposition vary in an apoE isoform-dependent manner. We hypothesized that human apoE isoforms differentially affect Aβ clearance or synthesis in vivo, resulting in an apoE isoform-dependent pattern of Aβ accumulation later in life. Performing in vivo microdialysis in a mouse model of Aβ-amyloidosis expressing human apoE isoforms (PDAPP/TRE), we find that the concentration and clearance of soluble Aβ in the brain interstitial fluid depends on the isoform of apoE expressed. This pattern parallels the extent of Aβ deposition observed in aged PDAPP/TRE mice. ApoE isoform-dependent differences in soluble Aβ metabolism are observed not only in aged but also in young PDAPP/TRE mice well before the onset of Aβ deposition in amyloid plaques in the brain. Additionally, amyloidogenic processing of amyloid precursor protein and Aβ synthesis, as assessed by in vivo stable isotopic labeling kinetics, do not vary according to apoE isoform in young PDAPP/TRE mice. Our results suggest that APOE alleles contribute to AD risk by differentially regulating clearance of Aβ from the brain, suggesting that Aβ clearance pathways may be useful therapeutic targets for AD prevention.
Keywords: Adult; Aged; Alleles; Alzheimer Disease; Amyloid beta-Peptides; Animals; Apolipoprotein E4; Biomarkers; Brain; Female; Genotype; Humans; Male; Mice; Mice, Inbred C57BL; Mice, Transgenic; Microdialysis; Middle Aged; Protein Isoforms

Neuronal activity regulates the regional vulnerability to amyloid-β deposition. - Bero, Adam W; Yan, Ping; Roh, Jee Hoon; Cirrito, John R; Stewart, Floy R; Raichle, Marcus E; Lee, Jin-Moo; Holtzman, David M (Nat Neurosci, 2011)
Amyloid-β (Aβ) plaque deposition in specific brain regions is a pathological hallmark of Alzheimer's disease. However, the mechanism underlying the regional vulnerability to Aβ deposition in Alzheimer's disease is unknown. Herein, we provide evidence that endogenous neuronal activity regulates the regional concentration of interstitial fluid (ISF) Aβ, which drives local Aβ aggregation. Using in vivo microdialysis, we show that ISF Aβ concentrations in several brain regions of APP transgenic mice before plaque deposition were commensurate with the degree of subsequent plaque deposition and with the concentration of lactate, a marker of neuronal activity. Furthermore, unilateral vibrissal stimulation increased ISF Aβ, and unilateral vibrissal deprivation decreased ISF Aβ and lactate, in contralateral barrel cortex. Long-term unilateral vibrissal deprivation decreased amyloid plaque formation and growth. Our results suggest a mechanism to account for the vulnerability of specific brain regions to Aβ deposition in Alzheimer's disease.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Amyloid beta-Protein Precursor; Animals; Cerebral Cortex; Disease Models, Animal; Extracellular Fluid; Female; Lactic Acid; Male; Mice; Mice, Inbred C57BL; Mice, Transgenic; Microdialysis; Neurons; Plaque, Amyloid; Sensory Deprivation; Somatosensory Cortex

Neuronal basis of age-related working memory decline. - Wang, Min; Gamo, Nao J; Yang, Yang; Jin, Lu E; Wang, Xiao-Jing; Laubach, Mark; Mazer, James A; Lee, Daeyeol; Arnsten, Amy F T (Nature, 2011)
Many of the cognitive deficits of normal ageing (forgetfulness, distractibility, inflexibility and impaired executive functions) involve prefrontal cortex (PFC) dysfunction. The PFC guides behaviour and thought using working memory, which are essential functions in the information age. Many PFC neurons hold information in working memory through excitatory networks that can maintain persistent neuronal firing in the absence of external stimulation. This fragile process is highly dependent on the neurochemical environment. For example, elevated cyclic-AMP signalling reduces persistent firing by opening HCN and KCNQ potassium channels. It is not known if molecular changes associated with normal ageing alter the physiological properties of PFC neurons during working memory, as there have been no in vivo recordings, to our knowledge, from PFC neurons of aged monkeys. Here we characterize the first recordings of this kind, revealing a marked loss of PFC persistent firing with advancing age that can be rescued by restoring an optimal neurochemical environment. Recordings showed an age-related decline in the firing rate of DELAY neurons, whereas the firing of CUE neurons remained unchanged with age. The memory-related firing of aged DELAY neurons was partially restored to more youthful levels by inhibiting cAMP signalling, or by blocking HCN or KCNQ channels. These findings reveal the cellular basis of age-related cognitive decline in dorsolateral PFC, and demonstrate that physiological integrity can be rescued by addressing the molecular needs of PFC circuits.
Keywords: Action Potentials; Adrenergic alpha-2 Receptor Agonists; Aging; Animals; Biomedical Enhancement; Cues; Cyclic AMP; Cyclic Nucleotide-Gated Cation Channels; Guanfacine; Humans; Hyperpolarization-Activated Cyclic Nucleotide-Gated Channels; KCNQ Potassium Channels; Macaca mulatta; Male; Memory, Short-Term; Models, Neurological; Neural Pathways; Potassium Channel Blockers; Potassium Channels; Prefrontal Cortex; Receptors, Adrenergic, alpha-2; Signal Transduction; Time Factors

Pathogenic protein seeding in Alzheimer disease and other neurodegenerative disorders. - Jucker, Mathias; Walker, Lary C (Ann Neurol, 2011)
The misfolding and aggregation of specific proteins is a seminal occurrence in a remarkable variety of neurodegenerative disorders. In Alzheimer disease (the most prevalent cerebral proteopathy), the two principal aggregating proteins are β-amyloid (Aβ) and tau. The abnormal assemblies formed by conformational variants of these proteins range in size from small oligomers to the characteristic lesions that are visible by optical microscopy, such as senile plaques and neurofibrillary tangles. Pathologic similarities with prion disease suggest that the formation and spread of these proteinaceous lesions might involve a common molecular mechanism-corruptive protein templating. Experimentally, cerebral β-amyloidosis can be exogenously induced by exposure to dilute brain extracts containing aggregated Aβ seeds. The amyloid-inducing agent probably is Aβ itself, in a conformation generated most effectively in the living brain. Once initiated, Aβ lesions proliferate within and among brain regions. The induction process is governed by the structural and biochemical nature of the Aβ seed, as well as the attributes of the host, reminiscent of pathogenically variant prion strains. The concept of prionlike induction and spreading of pathogenic proteins recently has been expanded to include aggregates of tau, α-synuclein, huntingtin, superoxide dismutase-1, and TDP-43, which characterize such human neurodegenerative disorders as frontotemporal lobar degeneration, Parkinson/Lewy body disease, Huntington disease, and amyotrophic lateral sclerosis. Our recent finding that the most effective Aβ seeds are small and soluble intensifies the search in bodily fluids for misfolded protein seeds that are upstream in the proteopathic cascade, and thus could serve as predictive diagnostics and the targets of early, mechanism-based interventions. Establishing the clinical implications of corruptive protein templating will require further mechanistic and epidemiologic investigations. However, the theory that many chronic neurodegenerative diseases can originate and progress via the seeded corruption of misfolded proteins has the potential to unify experimental and translational approaches to these increasingly prevalent disorders.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; DNA-Binding Proteins; Humans; Neurodegenerative Diseases; Prions; Proteins; tau Proteins

Report of the task force on designing clinical trials in early (predementia) AD. - Aisen, P S; Andrieu, S; Sampaio, C; Carrillo, M; Khachaturian, Z S; Dubois, B; Feldman, H H; Petersen, R C; Siemers, E; Doody, R S; Hendrix, S B; Grundman, M; et al. (Neurology, 2011)
BACKGROUND: A large number of promising candidate disease-modifying treatments for Alzheimer disease (AD) continue to advance into phase II and phase III testing. However, most completed trials have failed to demonstrate efficacy, and there is growing concern that methodologic difficulties may contribute to these clinical trial failures. The optimal time to intervene with such treatments is probably in the years prior to the onset of dementia, before the neuropathology has progressed to the advanced stage corresponding to clinical dementia. METHOD: An international task force of individuals from academia, industry, nonprofit foundations, and regulatory agencies was convened to discuss optimal trial design in early (predementia) AD. RESULTS: General consensus was reached on key principles involving the scope of the AD diagnosis, the selection of subjects for trials, outcome measures, and analytical methods. CONCLUSION: A consensus has been achieved in support of the testing of candidate treatments in the early (predementia) AD population.
Keywords: Advisory Committees; Alzheimer Disease; Amyloidogenic Proteins; Biomarkers; Clinical Trials as Topic; Cognition; Consensus; Disease Progression; Drug Industry; Early Diagnosis; Europe; Humans; Indans; International Cooperation; Nootropic Agents; Outcome Assessment (Health Care); Patient Selection; Piperidines; Positron-Emission Tomography; Research Design; Treatment Outcome; United States; United States Food and Drug Administration; Vitamin E

Soluble amyloid beta-protein dimers isolated from Alzheimer cortex directly induce Tau hyperphosphorylation and neuritic degeneration. - Jin, Ming; Shepardson, Nina; Yang, Ting; Chen, Gang; Walsh, Dominic; Selkoe, Dennis J (Proc Natl Acad Sci U S A, 2011)
Alzheimer disease is a major cause of cognitive failure, and a pathogenically related but more subtle process accounts for many cases of mild memory symptoms in older humans. Insoluble fibrillar plaques of amyloid β-proteins (Aβ) and neurofibrillary deposits of hyperphosphorylated tau proteins are the diagnostic lesions of AD, but their temporal mechanistic relationship has long been debated. The recent recognition that small, diffusible oligomers may be the principal bioactive form of Aβ raises the key question of whether these are sufficient to initiate cytoskeletal change and neurite degeneration. A few studies have examined the effects of oligomers of synthetic Aβ peptides of one defined length at supraphysiological concentrations, but the existence of such assemblies in the AD brain is not established. Here, we isolated Aβ dimers, the most abundant form of soluble oligomer detectable in the human brain, from the cortices of typical AD subjects and found that at subnanomolar concentrations, they first induced hyperphosphorylation of tau at AD-relevant epitopes in hippocampal neurons and then disrupted the microtubule cytoskeleton and caused neuritic degeneration, all in the absence of amyloid fibrils. Application of pure, synthetic dimers confirmed the effects of the natural AD dimers, although the former were far less potent. Knocking down endogenous tau fully prevented the neuritic changes, whereas overexpressing human tau accelerated them. Coadministering Aβ N-terminal antibodies neutralized the cytoskeletal disruption. We conclude that natural dimers isolated from the AD brain are sufficient to potently induce AD-type tau phosphorylation and then neuritic dystrophy, but passive immunotherapy mitigates this.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Animals; Blotting, Western; Chromatography, Gel; Dimerization; Genetic Vectors; Hippocampus; Humans; Immunohistochemistry; Immunoprecipitation; In Situ Nick-End Labeling; Lentivirus; Microscopy, Confocal; Microtubules; Neurites; Phosphorylation; Rats; Rats, Sprague-Dawley; tau Proteins

Toward defining the preclinical stages of Alzheimer's disease: recommendations from the National Institute on Aging-Alzheimer's Association workgroups on diagnostic guidelines for Alzheimer's disease. - Sperling, Reisa A; Aisen, Paul S; Beckett, Laurel A; Bennett, David A; Craft, Suzanne; Fagan, Anne M; Iwatsubo, Takeshi; Jack, Clifford R; Kaye, Jeffrey; Montine, Thomas J; Park, Denise C; Reiman, Eric M; et al. (Alzheimers Dement, 2011)
The pathophysiological process of Alzheimer's disease (AD) is thought to begin many years before the diagnosis of AD dementia. This long "preclinical" phase of AD would provide a critical opportunity for therapeutic intervention; however, we need to further elucidate the link between the pathological cascade of AD and the emergence of clinical symptoms. The National Institute on Aging and the Alzheimer's Association convened an international workgroup to review the biomarker, epidemiological, and neuropsychological evidence, and to develop recommendations to determine the factors which best predict the risk of progression from "normal" cognition to mild cognitive impairment and AD dementia. We propose a conceptual framework and operational research criteria, based on the prevailing scientific evidence to date, to test and refine these models with longitudinal clinical research studies. These recommendations are solely intended for research purposes and do not have any clinical implications at this time. It is hoped that these recommendations will provide a common rubric to advance the study of preclinical AD, and ultimately, aid the field in moving toward earlier intervention at a stage of AD when some disease-modifying therapies may be most efficacious.
Keywords: Alzheimer Disease; Biomarkers; Cognition Disorders; Humans; National Institute on Aging (U.S.); Practice Guidelines as Topic; United States

Vascular risk factors promote conversion from mild cognitive impairment to Alzheimer disease. - Li, J; Wang, Y J; Zhang, M; Xu, Z Q; Gao, C Y; Fang, C Q; Yan, J C; Zhou, H D (Neurology, 2011)
OBJECTIVE: Growing evidence suggests that vascular risk factors (VRF) contribute to cognitive decline. The aim of this study was to investigate the impact of VRF on the conversion from mild cognitive impairment (MCI) to Alzheimer disease (AD) dementia. METHODS: A total of 837 subjects with MCI were enrolled at baseline and followed up annually for 5 years. The incidence of AD dementia was investigated. A mixed random effects regression model was used to analyze the association between VRF and the progression of MCI assessed with Mini-Mental State Examination and instrumental Activities of Daily Living. Cox proportional hazard models were used to identify the association between VRF and dementia conversion, and to examine whether treatment of VRF can prevent dementia conversion. RESULTS: At the end of the follow-up, 298 subjects converted to AD dementia, while 352 remained MCI. Subjects with VRF had a faster progression in cognition and function relative to subjects without. VRF including hypertension, diabetes, cerebrovascular diseases, and hypercholesterolemia increased the risk of dementia conversion. Those subjects with MCI in whom all VRF were treated had a lower risk of dementia than those who had some VRF treated. Treatment of individual VRF including hypertension, diabetes, and hypercholesterolemia was associated with the reduced risk of AD conversion. CONCLUSION: VRF increased the risk of incident AD dementia. Treatment of VRF was associated with a reduced risk of incident AD dementia. Although our findings are observational, they suggest active intervention for VRF might reduce progression in MCI to AD dementia.
Keywords: Aged; Alzheimer Disease; Cerebrovascular Disorders; Cognition Disorders; Disease Progression; Female; Humans; Incidence; Longitudinal Studies; Male; Mental Status Schedule; Middle Aged; Neuropsychological Tests; Peptides; Regression Analysis; Residence Characteristics; Retrospective Studies; Risk Factors; Statistics, Nonparametric

APOE predicts amyloid-beta but not tau Alzheimer pathology in cognitively normal aging. - Morris, John C; Roe, Catherine M; Xiong, Chengjie; Fagan, Anne M; Goate, Alison M; Holtzman, David M; Mintun, Mark A (Ann Neurol, 2010)
OBJECTIVE: To examine interactions of apolipoprotein E (APOE) genotype with age and with in vivo measures of preclinical Alzheimer disease (AD) in cognitively normal aging. METHODS: Two hundred forty-one cognitively normal individuals, aged 45-88 years, had cerebral amyloid imaging studies with Pittsburgh Compound-B (PIB). Of the 241 individuals, 168 (70%) also had cerebrospinal fluid (CSF) assays of amyloid-beta(42) (Abeta(42)), tau, and phosphorylated tau (ptau(181)). All individuals were genotyped for APOE. RESULTS: The frequency of individuals with elevated mean cortical binding potential (MCBP) for PIB rose in an age-dependent manner from 0% at ages 45-49 years to 30.3% at 80-88 years. Reduced levels of CSF Abeta(42) appeared to begin earlier (18.2% of those aged 45-49 years) and increase with age in higher frequencies (50% at age 80-88 years) than elevations of MCBP. There was a gene dose effect for the APOE4 genotype, with greater MCBP increases and greater reductions in CSF Abeta(42) with increased numbers of APOE4 alleles. Individuals with an APOE2 allele had no increase in MCBP with age and had higher CSF Abeta(42) levels than individuals without an APOE2 allele. There was no APOE4 or APOE2 effect on CSF tau or ptau(181). INTERPRETATION: Increasing cerebral Abeta deposition with age is the pathobiological phenotype of APOE4. The biomarker sequence that detects Abeta deposition may first be lowered CSF Abeta(42), followed by elevated MCBP for PIB. A substantial proportion of cognitively normal individuals have presumptive preclinical AD.
Keywords: Aged; Aged, 80 and over; Aging; Alzheimer Disease; Amyloid beta-Peptides; Aniline Compounds; Apolipoprotein E2; Apolipoprotein E4; Apolipoproteins E; Brain; Female; Follow-Up Studies; Genotype; Humans; Longitudinal Studies; Male; Middle Aged; Peptide Fragments; Phosphorylation; Plaque, Amyloid; tau Proteins; Thiazoles

Divergence of human and mouse brain transcriptome highlights Alzheimer disease pathways. - Miller, Jeremy A; Horvath, Steve; Geschwind, Daniel H (Proc Natl Acad Sci U S A, 2010)
Because mouse models play a crucial role in biomedical research related to the human nervous system, understanding the similarities and differences between mouse and human brain is of fundamental importance. Studies comparing transcription in human and mouse have come to varied conclusions, in part because of their relatively small sample sizes or underpowered methodologies. To better characterize gene expression differences between mouse and human, we took a systems-biology approach by using weighted gene coexpression network analysis on more than 1,000 microarrays from brain. We find that global network properties of the brain transcriptome are highly preserved between species. Furthermore, all modules of highly coexpressed genes identified in mouse were identified in human, with those related to conserved cellular functions showing the strongest between-species preservation. Modules corresponding to glial and neuronal cells were sufficiently preserved between mouse and human to permit identification of cross species cell-class marker genes. We also identify several robust human-specific modules, including one strongly correlated with measures of Alzheimer disease progression across multiple data sets, whose hubs are poorly-characterized genes likely involved in Alzheimer disease. We present multiple lines of evidence suggesting links between neurodegenerative disease and glial cell types in human, including human-specific correlation of presenilin-1 with oligodendrocyte markers, and significant enrichment for known neurodegenerative disease genes in microglial modules. Together, this work identifies convergent and divergent pathways in mouse and human, and provides a systematic framework that will be useful for understanding the applicability of mouse models for human brain disorders.
Keywords: Alzheimer Disease; Animals; Brain; Gene Expression Profiling; Gene Regulatory Networks; Humans; Male; Mice; Presenilin-1; Systems Biology

Gamma-secretase activating protein is a therapeutic target for Alzheimer's disease. - He, Gen; Luo, Wenjie; Li, Peng; Remmers, Christine; Netzer, William J; Hendrick, Joseph; Bettayeb, Karima; Flajolet, Marc; Gorelick, Fred; Wennogle, Lawrence P; Greengard, Paul (Nature, 2010)
Accumulation of neurotoxic amyloid-beta is a major hallmark of Alzheimer's disease. Formation of amyloid-beta is catalysed by gamma-secretase, a protease with numerous substrates. Little is known about the molecular mechanisms that confer substrate specificity on this potentially promiscuous enzyme. Knowledge of the mechanisms underlying its selectivity is critical for the development of clinically effective gamma-secretase inhibitors that can reduce amyloid-beta formation without impairing cleavage of other gamma-secretase substrates, especially Notch, which is essential for normal biological functions. Here we report the discovery of a novel gamma-secretase activating protein (GSAP) that drastically and selectively increases amyloid-beta production through a mechanism involving its interactions with both gamma-secretase and its substrate, the amyloid precursor protein carboxy-terminal fragment (APP-CTF). GSAP does not interact with Notch, nor does it affect its cleavage. Recombinant GSAP stimulates amyloid-beta production in vitro. Reducing GSAP concentrations in cell lines decreases amyloid-beta concentrations. Knockdown of GSAP in a mouse model of Alzheimer's disease reduces levels of amyloid-beta and plaque development. GSAP represents a type of gamma-secretase regulator that directs enzyme specificity by interacting with a specific substrate. We demonstrate that imatinib, an anticancer drug previously found to inhibit amyloid-beta formation without affecting Notch cleavage, achieves its amyloid-beta-lowering effect by preventing GSAP interaction with the gamma-secretase substrate, APP-CTF. Thus, GSAP can serve as an amyloid-beta-lowering therapeutic target without affecting other key functions of gamma-secretase.
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Amyloid beta-Protein Precursor; Amyloid Precursor Protein Secretases; Animals; Benzamides; Cell Line; Disease Models, Animal; Gene Knockdown Techniques; Humans; Imatinib Mesylate; Mice; Peptide Fragments; Piperazines; Proteins; Pyrimidines; Receptor, Notch1; RNA Interference

Genetic evidence implicates the immune system and cholesterol metabolism in the aetiology of Alzheimer's disease. - Jones, Lesley; Holmans, Peter A; Hamshere, Marian L; Harold, Denise; Moskvina, Valentina; Ivanov, Dobril; Pocklington, Andrew; Abraham, Richard; Hollingworth, Paul; Sims, Rebecca; Gerrish, Amy; Pahwa, Jaspreet Singh; et al. (PLoS One, 2010)
BACKGROUND: Late Onset Alzheimer's disease (LOAD) is the leading cause of dementia. Recent large genome-wide association studies (GWAS) identified the first strongly supported LOAD susceptibility genes since the discovery of the involvement of APOE in the early 1990s. We have now exploited these GWAS datasets to uncover key LOAD pathophysiological processes. METHODOLOGY: We applied a recently developed tool for mining GWAS data for biologically meaningful information to a LOAD GWAS dataset. The principal findings were then tested in an independent GWAS dataset. PRINCIPAL FINDINGS: We found a significant overrepresentation of association signals in pathways related to cholesterol metabolism and the immune response in both of the two largest genome-wide association studies for LOAD. SIGNIFICANCE: Processes related to cholesterol metabolism and the innate immune response have previously been implicated by pathological and epidemiological studies of Alzheimer's disease, but it has been unclear whether those findings reflected primary aetiological events or consequences of the disease process. Our independent evidence from two large studies now demonstrates that these processes are aetiologically relevant, and suggests that they may be suitable targets for novel and existing therapeutic approaches.
Keywords: Alzheimer Disease; Apolipoproteins E; Cholesterol; Chromosome Mapping; Genetic Predisposition to Disease; Genome, Human; Genome-Wide Association Study; Humans; Immune System; Polymorphism, Single Nucleotide

Memory impairment in transgenic Alzheimer mice requires cellular prion protein. - Gimbel, David A; Nygaard, Haakon B; Coffey, Erin E; Gunther, Erik C; Laurén, Juha; Gimbel, Zachary A; Strittmatter, Stephen M (J Neurosci, 2010)
Soluble oligomers of the amyloid-beta (Abeta) peptide are thought to play a key role in the pathophysiology of Alzheimer's disease (AD). Recently, we reported that synthetic Abeta oligomers bind to cellular prion protein (PrP(C)) and that this interaction is required for suppression of synaptic plasticity in hippocampal slices by oligomeric Abeta peptide. We hypothesized that PrP(C) is essential for the ability of brain-derived Abeta to suppress cognitive function. Here, we crossed familial AD transgenes encoding APPswe and PSen1DeltaE9 into Prnp-/- mice to examine the necessity of PrP(C) for AD-related phenotypes. Neither APP expression nor Abeta level is altered by PrP(C) absence in this transgenic AD model, and astrogliosis is unchanged. However, deletion of PrP(C) expression rescues 5-HT axonal degeneration, loss of synaptic markers, and early death in APPswe/PSen1DeltaE9 transgenic mice. The AD transgenic mice with intact PrP(C) expression exhibit deficits in spatial learning and memory. Mice lacking PrP(C), but containing Abeta plaque derived from APPswe/PSen1DeltaE9 transgenes, show no detectable impairment of spatial learning and memory. Thus, deletion of PrP(C) expression dissociates Abeta accumulation from behavioral impairment in these AD mice, with the cognitive deficits selectively requiring PrP(C).
Keywords: Alzheimer Disease; Amyloid beta-Peptides; Amyloid beta-Protein Precursor; Animals; Avoidance Learning; Brain; Disease Models, Animal; Maze Learning; Memory; Mice; Mice, Inbred C57BL; Mice, Transgenic; Nerve Degeneration; Presenilin-1; PrPC Proteins; Random Allocation; Serotonin; Survival Analysis

Tau in Alzheimer disease and related tauopathies. - Iqbal, K; Liu, F; Gong, C-X; Grundke-Iqbal, I (Curr Alzheimer Res, 2010)
Tau is the major microtubule associated protein (MAP) of a mature neuron. The other two neuronal MAPs are MAP1 and MAP2. An established function of MAPs is their interaction with tubulin and promotion of its assembly into microtubules and stabilization of the microtubule network. The microtubule assembly promoting activity of tau, a phosphoprotein, is regulated by its degree of phosphorylation. Normal adult human brain tau contains 2-3 moles phosphate/mole of tau protein. Hyperphosphorylation of tau depresses this biological activity of tau. In Alzheimer disease (AD) brain tau is ~three to four-fold more hyperphosphorylated than the normal adult brain tau and in this hyperphosphorylated state it is polymerized into paired helical filaments ([PHF) admixed with straight filaments (SF) forming neurofibrillary tangles. Tau is transiently hyperphosphorylated during development and during anesthesia and hypothermia but not to the same state as in AD brain. The abnormally hyperphosphorylated tau in AD brain is distinguished from transiently hyperphosphorylated tau by its ability (1) to sequester normal tau, MAP1 and MAP2 and disrupt microtubules, and (2) to self-assemble into PHF/SF. The cytosolic abnormally hyperphosphorylated tau, because of oligomerization, unlike normal tau, is sedimentable and on self-assembly into PHF/SF, loses its ability to sequester normal MAPs. Some of the tau in AD brain is truncated which also promotes its self-assembly. Tau mutations found in frontotemporal dementia apparently promote its abnormal hyperphosphorylation. Thus, the AD abnormally hyperphosphorylated tau (1) is distinguishable from both normal and transiently hyperphosphorylated taus, and (2) is inhibitory when in a cytosolic/oligomeric state but not when it is self-assembled into PHF/SF. Inhibition of abnormal hyperphosphorylation of tau offers a promising therapeutic target for AD and related tauopathies.
Keywords: Alzheimer Disease; Animals; Humans; Phosphorylation; tau Proteins; Tauopathies